1,10]Phenanthroline based cyanine dyes as fluorescent probes for ribonucleic acids in live cells - Kovalska, Vladyslava B.; Kuperman, Marina; Varzatskii, Oleg; Kryvorotenko, Dmytro; Kinski, Elisa; Schikora, Margot; Janko, Christina; Alexiou, Christoph; Yarmoluk, Sergiy; Mokhir, Andriy (Methods and Applications in Fluorescence, 2017)
A series of monomethine, trimethine- and styrylcyanine dyes based on a [1,10]phenanthroline moiety was synthesized, characterized and investigated as potential fluorescent probes for nucleic acids in cell free settings and in cells. The dyes were found to be weakly fluorescent in the unbound state, whereas upon the binding to dsDNA or RNA their emission intensity raised up to 50 times (for monomethine benzothiazole derivative FT1 complexed with RNA). The strongest fluorescence intensity in assemblies with dsDNA and RNA was observed for the trimethine benzothiazole derivative FT4. The quantum yield of FT4 fluorescence in its complex with dsDNA was found to be 1.5% and the binding constant (K b) was estimated to be 7.9 × 104 M-1 that is a typical value for intercalating molecules. The FT4 dye was found to be cell membrane permeable. It stains RNA rich components-the nucleoli and most probably the cytoplasmic RNA. FT4 bound to RNAs delivers a very strong fluorescence signal, which makes this easily accessible dye a potentially useful alternative to known RNA stains, e.g. expensive SYTO® 83. The advantage of FT4 is its easy synthetic access including no chromatographic purification steps, which will be reflected in its substantially lower price.
EVALuna2:35777

3D-FV-FE Aeroacoustic Larynx Model for Investigation of Functional Based Voice Disorders - Falk, Sebastian; Kniesburges, Stefan; Schoder, Stefan; Jakubaß, Bernhard; Maurerlehner, Paul; Echternach, Matthias; Kaltenbacher, Manfred; Döllinger, Michael (Frontiers in Physiology, 2021)
For the clinical analysis of underlying mechanisms of voice disorders, we developed a numerical aeroacoustic larynx model, called simVoice, that mimics commonly observed functional laryngeal disorders as glottal insufficiency and vibrational left-right asymmetries. The model is a combination of the Finite Volume (FV) CFD solver Star-CCM+ and the Finite Element (FE) aeroacoustic solver CFS++. simVoice models turbulence using Large Eddy Simulations (LES) and the acoustic wave propagation with the perturbed convective wave equation (PCWE). Its geometry corresponds to a simplified larynx and a vocal tract model representing the vowel /a/. The oscillations of the vocal folds are externally driven. In total, 10 configurations with different degrees of functional-based disorders were simulated and analyzed. The energy transfer between the glottal airflow and the vocal folds decreases with an increasing glottal insufficiency and potentially reflects the higher effort during speech for patients being concerned. This loss of energy transfer may also have an essential influence on the quality of the sound signal as expressed by decreasing sound pressure level (SPL), Cepstral Peak Prominence (CPP), and Vocal Efficiency (VE). Asymmetry in the vocal fold oscillations also reduces the quality of the sound signal. However, simVoice confirmed previous clinical and experimental observations that a high level of glottal insufficiency worsens the acoustic signal quality more than oscillatory left-right asymmetry. Both symptoms in combination will further reduce the quality of the sound signal. In summary, simVoice allows for detailed analysis of the origins of disordered voice production and hence fosters the further understanding of laryngeal physiology, including occurring dependencies. A current walltime of 10 h/cycle is, with a prospective increase in computing power, auspicious for a future clinical use of simVoice.
CRIS-Team Scopus Importer:2021-04-02
Keywords: computational aero acoustics; computational fluid dynamics; glottal insufficiency; left-right asymmetry; posterior gap; simVoice (numerical larynx model)

3D Reconstruction of Human Laryngeal Dynamics Based on Endoscopic High-Speed Recordings - Semmler, Marion; Kniesburges, Stefan; Birk, Veronika; Ziethe, Anke; Patel, Rita; Döllinger, Michael (IEEE Transactions on Medical Imaging, 2016)
Standard laryngoscopic imaging techniques provide only limited two-dimensional insights into the vocal fold vibrations not taking the vertical component into account. However, previous experiments have shown a significant vertical component in the vibration of the vocal folds. We present a 3D reconstruction of the entire superior vocal fold surface from 2D high-speed videoendoscopy via stereo triangulation. In a typical camera-laser set-up the structured laser light pattern is projected on the vocal folds and captured at 4000 fps. The measuring device is suitable for in vivo application since the external dimensions of the miniaturized set-up barely exceed the size of a standard rigid laryngoscope. We provide a conservative estimate on the resulting resolution based on the hardware components and point out the possibilities and limitations of the miniaturized camera-laser set-up. In addition to the 3D vocal fold surface, we extended previous approaches with a G2-continuous model of the vocal fold edge. The clinical applicability was successfully established by the reconstruction of visual data acquired from 2D in vivo high-speed recordings of a female and a male subject. We present extracted dynamic parameters like maximum amplitude and velocity in the vertical direction. The additional vertical component reveals deeper insights into the vibratory dynamics of the vocal folds by means of a non-invasive method. The successful miniaturization allows for in vivo application giving access to the most realistic model available and hence enables a comprehensive understanding of the human phonation process.
EVALuna2:33214

3D semi-quantification of nanoparticle content in tissue on experimental and commercial µCT-scanner - Rahn, Helene; Bayer, Katharina; Odenbach, Stefan; Lyer, Stefan; Alexiou, Christoph; Wiekhorst, Frank; Trahms, Lutz; Baumann, Michael; Buckwar, Julia; Krause, Mechthild (Springer Proceedings in Physics, 2012)
X-ray computed tomography is a widely used imaging technique nowadays. Especially in medicine it takes an important role for visualization and diagnostics. Micro-computed tomography (µCT) follows the same principle as conventional medical CT-Scanner. But the objects analyzed are smaller, thus an improvement in spatial resolution down to few micrometers is possible. In the work field of biomedical application of magnetic nanoparticles µCT has been used for the visualization of the nanoparticle accumulations within tumoral regions after magnetic drug targeting. Further on, a calibration procedure has been developed and applied with a µCT-apparatus. The calibration procedure enables a semi-quantification of the nanoparticle content within the tissue samples. The next step stone in visualization process is the observation of the nanoparticle accumulation during the application of magnetic drug targeting in an animal. Thus, we have tested the calibration procedure on a commercial animal scanner. In this paper we compare the semi-quantitative results figured out in two different µCT-equipments.
CRIS-Team Scopus Importer:2022-06-27

3D-Shaped Binders of Unfolded Proteins Inducing Cancer Cell-Specific Endoplasmic Reticulum Stress In Vitro and In Vivo - Klemt, Insa; Varzatskii, Oleg; Selin, Roman; Vakarov, Serhii; Kovalska, Vladyslava B.; Bila, Galyna; Bilyy, Rostyslav; Voloshin, Yan; Cossío Cuartero, Itziar; Hidalgo, Andrés; Frey, Benjamin; Becker, Ina; et al. (Journal of the American Chemical Society, 2023)
The amount of unfolded proteins is increased in cancer cells, leading to endoplasmic reticulum (ER) stress. Therefore, cancer cells are sensitive to drugs capable of further enhancing ER stress. Examples of such drugs include the clinically approved proteosome inhibitors bortezomib and carfilzomib. Unfortunately, the known ER stress inducers exhibit dose-limiting side effects that justify the search for better, more cancer-specific drugs of this type. Herein, we report on FeC 2, which binds to unfolded proteins prevents their further processing, thereby leading to ER stress and ROS increase in cancer cells, but not in normal cells. FeC 2 exhibits low micromolar toxicity toward human acute promyelocytic leukemia HL-60, Burkitt’s lymphoma BL-2, T-cell leukemia Jurkat, ovarian carcinoma A2780, lung cancer SK-MES-1, and murine lung cancer LLC1 cells. Due to the cancer-specific mode of action, 2 is not toxic in vivo up to the dose of 147 mg/kg, does not affect normal blood and bone marrow cells at the therapeutically active dose, but strongly suppresses both primary tumor growth (confirmed in Nemeth-Kellner lymphoma and LLC1 lung cancer models of murine tumor) and spreading of metastases (LLC1).

3D visualization and analysis of vocal fold dynamics - Bohr, Christopher; Döllinger, Michael; Kniesburges, Stefan; Traxdorf, Maximilian (HNO, 2016)
BACKGROUND: Visual investigation methods of the larynx mainly allow for the two-dimensional presentation of the three-dimensional structures of the vocal fold dynamics. The vertical component of the vocal fold dynamics is often neglected, yielding a loss of information. The latest studies show that the vertical dynamic components are in the range of the medio-lateral dynamics and play a significant role within the phonation process. OBJECTIVES: This work presents a method for future 3D reconstruction and visualization of endoscopically recorded vocal fold dynamics. MATERIALS AND METHODS: The setup contains a high-speed camera (HSC) and a laser projection system (LPS). The LPS projects a regular grid on the vocal fold surfaces and in combination with the HSC allows a three-dimensional reconstruction of the vocal fold surface. Hence, quantitative information on displacements and velocities can be provided. The applicability of the method is presented for one ex-vivo human larynx, one ex-vivo porcine larynx and one synthetic silicone larynx. RESULTS: The setup introduced allows the reconstruction of the entire visible vocal fold surfaces for each oscillation status. This enables a detailed analysis of the three dimensional dynamics (i. e. displacements, velocities, accelerations) of the vocal folds. CONCLUSIONS: The next goal is the miniaturization of the LPS to allow clinical in-vivo analysis in humans. We anticipate new insight on dependencies between 3D dynamic behavior and the quality of the acoustic outcome for healthy and disordered phonation.
EVALuna2:33161

7q31.2q31.31 deletion downstream of FOXP2 segregating in a family with speech and language disorder - Rieger, Melissa; Krumbiegel, Mandy; Reuter, Miriam; Schützenberger, Anne; Reis, André; Zweier, Christiane (American Journal of Medical Genetics Part A, 2020)
Chromosomal 7q31 deletions have been described in individuals with variable neurodevelopmental phenotypes including speech and language impairment. These copy number variants usually encompass FOXP2, haploinsufficiency of which represents a widely acknowledged cause for specific speech and language disorders. By chromosomal microarray analysis we identified a 4.7 Mb microdeletion at 7q31.2q31.31 downstream of FOXP2 in three family members presenting with variable speech, language and neurodevelopmental phenotypes. The index individual showed delayed speech development with impaired speech production, reduced language comprehension, and additionally learning difficulties, microcephaly, and attention deficit. His younger sister had delayed speech development with impaired speech production and partially reduced language comprehension. Their mother had attended a school for children with speech and language deficiencies and presented with impaired articulation. The deletion had occurred de novo in the mother, includes 15 protein-coding genes and is located in close proximity to the 3′ end of FOXP2. Though a novel locus at 7q31.2q31.31 associated with mild neurodevelopmental and more prominent speech and language impairment is possible, the close phenotypic overlap with FOXP2-associated speech and language disorder rather suggests a positional effect on FOXP2 expression and function.
CRIS-Team Scopus Importer:2020-09-11
Keywords: 7q; deletion; FOXP2; language; speech

A 9-year analysis of transoral laser microsurgery (TLM) of head and neck cancer on their potential suitability for transoral robotic surgery (TORS) for estimation of future TORS-specific caseload - Von Scotti, F.; Kapsreiter, M.; Scherl, C.; Iro, Heinrich; Bohr, Christopher (European Review for Medical and Pharmacological Sciences, 2018)
OBJECTIVE: After that the establishment of transoral robotic surgery (TORS) for head and neck cancer has been adopted in North America, it has also recently been adopted in Europe. In these parts, transoral laser microsurgery (TLM) is widely applied. The aim of the study was to identify the absolute number of operations amenable to TORS at a TORS initiating institution on the basis of all former TLM cases. PATIENTS AND METHODS: All laser surgery procedures from May 2004 to April 2013 (108 months) were initially retrospectively registered; after that, all stage pT1 and pT2 squamous cell carcinomas of the oropharynx, hypopharynx, and larynx were selected. RESULTS: Over a period of nine years out of all TLM cases, there were 45 cases of pT1 and pT2 orohypopharyngeal and supraglottic squamous cell carcinomas, which could have been considered for TORS surgery. With the inclusion of a nowadays-typical TORS indication such as tonsil cancer, 142 cases would have been amendable to TORS. CONCLUSIONS: The indication for TORS would have been made in five of the TLM cases per year. Institutions initiating TORS, which own an intensive TLM experience, are encouraged to TORS indications in more than solely typical TLM indications. By indicating TORS instead of handheld surgery, a higher caseload of more than 15 cases per year can be achieved for TORS indications.
EVALuna2:35389

A blast without power - cell death induced by the tuberculosis-necrotizing toxin fails to elicit adequate immune responses - Maueroeder, C.; Chaurio, R. A.; Dumych, T.; Podolska, M.; Lootsik, M. D.; Culemann, S.; Friedrich, Ralf P.; Bilyy, R.; Alexiou, Christoph; Schett, Georg; Berens, C.; Herrmann, Martin; et al. (Cell Death and Differentiation, 2016)
In this study, we deploy a doxycycline-dependent suicide switch integrated in a tumor challenge model. With this experimental setup, we characterized the immunological consequences of cells dying by four distinct cell death stimuli in vivo. We observed that apoptotic cell death induced by expression of the truncated form of BH3 interacting-domain death agonist (tBid) and a constitutively active form of caspase 3 (revC3), respectively, showed higher immunogenicity than cell death induced by expression of the tuberculosis-necrotizing toxin (TNT). Our data indicate that the early release of ATP induces the silent clearance of dying cells, whereas the simultaneous presence of 'find me' signals and danger-associated molecular patterns (DAMPs) promotes inflammatory reactions and increased immunogenicity. This proposed model is supported by findings showing that the production and release of high concentrations of IL-27 by bone-marrow-derived macrophages (BMDM) is limited to BMDM exposed to those forms of death that simultaneously released ATP and the DAMPs heat-shock protein 90 (HSP90) and high-mobility group box-1 protein (HMGB1). These results demonstrate that the tissue microenvironment generated by dying cells may determine the subsequent immune response.
EVALuna2:13264

Abscesstonsillectomy: Uni- or bilateral? - Fauck, Vanessa; Schinz, Katharina; Alexiou, Christoph; Mantsopoulos, Konstantinos; Iro, Heinrich; Mueller, Sarina K. (Laryngo-Rhino-Otologie, 2022)
Objective In addition to an empirical use of antibiotics for treatment of a peritonsillar abscess (PTA) there is a drainage of pus or the abscess tonsillectomy. Postoperative bleeding after abscesstonsillectomy (ABTE) is this surgery's most feared complication which can rarely lead to patients' deaths. The objective of this study was to compare bleeding complications of ABTE with and without contralateral tonsillectomy (TE) and to analyze the occurrence of a metachronous PTA at the contralateral side. Methods Retrospective study of n= 655 patients undergoing ABTE with and without TE of the contralateral side from January 2004 to February 2019. Bleeding complications needing surgical hemostasis were analyzed regarding demographic and surgical parameters. In addition, occurrence of PTA and need for ABTE of the contralateral side after unilateral ABTE were evaluated. Results Overall, 10/655 (1.5 %) patients presented with postoperative bleeding after ABTE. In 404/655 an ABTE with contralateral TE was performed. Here, 8/404 (1.98 %) patients showed contra- or bilateral bleeding. Only in 2/251 (0.7 %) patients occurred a bleeding complication after unilateral ABTE. Therefore, bleeding after unilateral ABTE was significantly lower than ABTE with contralateral TE (1.98 % vs. 0.7 %, p= 0.001). In 0.8 % of the patients a contralateral ABTE was necessary due to a metachronous PTA. Conclusion Overall, the rate of postoperative bleeding after ABTE (1.5 %) was low. Unilateral ABTE showed significantly lower postoperative bleeding rates compared to ABTE with contralateral TE. Consequently, the indication of a contralateral TE must be very strict.
CRIS-Team WoS Importer:2022-06-03

A Chemical Reaction Network to Generate Random, Power-Law-Distributed Time Intervals - Krauß, Patrick; Schulze, Holger; Metzner, Claus (Artificial Life, 2017)
In Lévy walks (LWs), particles move with a fixed speed along straight line segments and turn in new directions after random time intervals that are distributed according to a power law. Such LWs are thought to be an advantageous foraging and search strategy for organisms. While complex nervous systems are certainly capable of producing such behavior, it is not clear at present how single-cell organisms can generate the long-term correlated control signals required for a LW. Here, we construct a biochemical reaction system that generates long-time correlated concentration fluctuations of a signaling substance, with a tunable fractional exponent of the autocorrelation function. The network is based on well-known modules, and its basic function is highly robust with respect to the parameter settings.
EVALuna2:33191

A comparison between p16-positive head and neck cancer of unknown primary (HPV-HNCUP) and oropharyngeal squamous cell carcinoma (HPV-OPSCC): are they the same disease? - Balk, Matthias; Rupp, Robin; Sievert, Matti; Mantsopoulos, Konstantinos; Allner, Moritz; Grundtner, Philipp; Müller-Hübner, Sarina; Eckstein, Markus; Iro, Heinrich; Hecht, Markus; Gostian, Antoniu-Oreste (European Archives of Oto-Rhino-Laryngology, 2023)
Introduction: The following study aimed to answer the question if HPV-HNCUP and HPV-OPSCC are the same disease. Propensity score matching (PSM) was used to compare the oncological outcomes of both groups, in particular the 5-year overall survival rate (OS), the 5-year disease specific survival rate (DSS) and the 5-year progression free survival rate (PFS). Materials and methods: Firstly, between January 1st, 2007, and March 31st, 2020 a total of 131 patients were treated with HNCUP at our Department. Out of these, 21 patients with a confirmed positive p16 status were referred to surgery followed by adjuvant therapy. Secondly, between January 1st, 2000, and January 31st, 2017, a total of 1596 patients were treated with an OPSSC at our Department. Out of these, 126 patients with a confirmed positive p16 status were referred to surgery followed by adjuvant therapy. After PSM, 84 patients with HPV-OPSCC and 21 HPV-HNCUP remained in the study for further comparison. Results: The OS was 63.5% (95% CI 39.4–87.6) for HPV-HNCUP and 88.9% (95% CI 90.4–100.0) for HPV-OPSCC patients and therefore, significantly lower for the first mentioned (p = 0.013). The DSS was also significantly impaired for HPV-HNCUP (71.0%, 95% CI 46.3–95.7), in comparison with HPV-OPSCC patients (95.5%, 95% CI 90.4–100.0; p = 0.002). The PFS for HPV-HNCUP patients was lower (75.6%, 95% CI 54.0–97.2) yet not significantly different to HPV-OPSCC (90.4%, 95% CI 83.5–97.3; p = 0.067). Conclusions: The results presented demonstrate a significant reduced OS and DSS for HPV-HNCUP patients. Accordingly, in our study HPV-HNCUP and HPV-OPSCC are two different entities with a different oncological outcome.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Cancer of unknown primary; Head and neck cancer; HPV-HNCUP; HPV-OPSCC; Neck dissection; Oropharyngeal cancer

A complex fracture of the hyoid bone and the larynx after a bicycle accident – Case report and review of literature - Sievert, Matti; Eisenhut, Felix; Iro, Heinrich; Traxdorf, Maximilian; Müller, Susanna; Taha, Lava (International Journal of Surgery Case Reports, 2021)
Introduction and importance: Reports about laryngeal trauma and fractures of the hyoid bone are rare in the literature. Most cases are forensic cases and the results of postmortem analysis. Traumatic larynx and hyoid bone fractures represent a rare but important differential diagnosis of the common symptom hoarseness. Case presentation: A 60-year-old female patient presented with unclear dysphonia and globus sensation following intubation for a surgical treatment for a lower leg fracture after a bicycle accident two months ago. Endoscopy and the computed tomography (CT) of the neck revealed a fixed and immobile fractured piece of the larynx, a hyoid bone fracture and a pseudarthrosis between the greater horn of the hyoid bone and the upper edge of the thyroid cartilage. The hyoid bone fracture led to a distortion of the supraglottis. After surgical removal of the fractured part of the hyoid bone and the pseudarthrosis separation, the supraglottis appeared symmetrical again. Four weeks after surgery the patient was symptom-free. Clinical discussion: Though combined hyoid bone and larynx fractures after traumatic injuries are rare, they represent an important differential diagnosis in trauma patients with dysphagia or dysphonia. The clinical symptoms can vary and occur immediately or within a latent period taking weeks or months until the proper diagnosis. Depending on the symptoms, surgical management can be effective. Conclusion: An isolated partial resection of the hyoid bone with separation of the pseudarthrosis is a reasonable therapeutic option and can lead to completely resolving symptom. Preoperatively, a CT provides further valuable information.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Case report; Computed tomography; Dysphagia; Dysphonia; Hyoid bone fracture; Laryngeal trauma

Acoustic analysis of professional singing masks - Tur, Bogac; Echternach, Matthias; Turowski, Stefan; Müller, Meinard; Koeberlein, Marie; Döllinger, Michael; Kniesburges, Stefan (Acta Acustica, 2022)
Wearing face coverings became one essential tool in order to prohibit virus transmission during the COVID-19 pandemic. In comparison to speaking and breathing, singing emits a much higher amount of aerosol particles. Therefore, there are situations in which singers can perform or rehearse only if they are using protective masks. However, such masks have a more or less adverse effect not only on the singer's comfort and tightness of the mask but also on the radiated sound. For this reason, the spectral filtering and directivity of masks designed specifically for professional singing was measured. The tests were performed with a head phantom. Over most of the spectrum, attenuation is observed, although amplification happens at some low frequency bands for different mask types and directions. Especially singing masks with a plastic face shield showed partial amplification of up to +10 dB below a frequency of 2 kHz, while only slight significant attenuation and no amplification (minimal acoustic loss) were seen for woven fabric masks. Above 2.5 kHz, the transparent masks showed the greatest sound attenuation up to -30 dB, while woven fabric masks produced an overall lower sound attenuation of up to -5 dB. In addition at low frequencies, the sound was amplified or attenuated equally in all directions for masks with a stiff plastic face shield. At higher frequencies, the attenuation is higher to the frontal than to the backward direction.
CRIS-Team WoS Importer:2022-11-04

Acoustic and Aerodynamic Coupling during Phonation in MRI-Based Vocal Tract Replicas - Probst, Judith; Lodermeyer, Alexander; Fattoum, Sahar; Becker, Stefan; Echternach, Matthias; Richter, Bernhard; Döllinger, Michael; Kniesburges, Stefan (Applied Sciences, 2019)

Acoustic Impact of Ventricular Folds on Phonation Studied in Ex Vivo Human Larynx Models - Birk, Veronika; Sutor, Alexander; Döllinger, Michael; Bohr, Christopher; Kniesburges, Stefan (Acta Acustica United With Acustica, 2016)
A reliable and objective evaluation of voice quality is of essential importance in the therapy of pathological voices. The cepstral peak prominence (CPP) is calculated in the cepstral domain and is insensitive to variations of the fundamental frequency or pitch-tracking errors. Owing to the inconsistent information about its calculation procedure in the literature, the quantitative comparison of CPP values is difficult. This study provides insight into different definitions for the cepstrum calculation and also parameter variations. Their influence on the resulting CPP is presented on the basis of an acoustic dataset of sustained phonation obtained from an ex vivo human larynx model. Applying the different definitions for cepstrum calculation, the absolute CPP values varied within six orders of magnitude. Variation of the window length for partitioning the acoustic time signal and use of the averaging method over the windows yielded both quantitative and qualitative deviations of the CPP distribution. The results showed that it is essential to provide detailed information about the CPP calculation procedure to permit quantitative comparisons with the literature. After its evaluation, the CPP was used to investigate the acoustic influence of the ventricular folds as a function of the sub-glottal pressure (P-sub). In the present study, the CPP definition of Hillenbrand et al. [1], which has become established in voice research, was applied. In vitro experiments with two excised human larynx models, each in the configuration with and without ventricular folds, were executed. The results were compared with those of available studies with canine larynges. The analysis turns out that the ventricular folds stabilise and enhance the acoustic output at low P-sub ranges at which the ventricular folds do not oscillate. After oscillation onset of the vocal folds, the CPP increases for increasing Psub and reaches its maximum at relatively low Path values. By further increasing Psub the CPP decreases much faster for the configuration with ventricular folds than without. This could be attributed to the movement of the ventricular folds. We suggest that the ventricular folds support and stabilise the vocal fold phonation process as far as they act as stationary boundary conditions. As soon as the glottal flow excites the ventricular folds to move periodically, the process is destabilised resulting in a decrease of voice quality, represented by lower CPP values.

Acoustic source term interpolation in a hybrid aeroacoustic simulation of the human phonation - Weitz, Michael; Schoder, Stefan; Maurerlehner, Paul; Falk, Sebastian; Döllinger, Michael; Kaltenbacher, Manfred (Proceedings of the International Congress on Acoustics, 2019)
Voice research is carried out experimentally by applying physical replicas and numerical models. Experimental investigations involve high personnel, material and thus financial costs. Furthermore, the scientific outcome is limited to the few parameters that are measured at specific positions in the larynx replica. In contrast to that, numerical models provide a much higher amount of results since parameters from all possible locations in the model can be obtained and analyzed. We follow a hybrid aeroacoustic approach, which performs in a first step an incompressible flow simulation on a computational grid which is capable of resolving all relevant turbulent scales. In a second step, we compute the acoustic source terms on the flow grid and perform a conservative interpolation to the acoustic grid on which we solve the perturbed convective wave equation to obtain the acoustic field. Finally, we validate the simulation results with results obtained from measurements.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Computational aeroacoustics; Finite element method; Human phonation

Acute and Long-Term Circuit-Level Effects in the Auditory Cortex After Sound Trauma - Jeschke, Marcus; Happel, Max F.K.; Tziridis, Konstantin; Krauß, Patrick; Schilling, Achim; Schulze, Holger; Ohl, Frank W. (Frontiers in Neuroscience, 2021)
Harmful environmental sounds are a prevailing source of chronic hearing impairments, including noise induced hearing loss, hyperacusis, or tinnitus. How these symptoms are related to pathophysiological damage to the sensory receptor epithelia and its effects along the auditory pathway, have been documented in numerous studies. An open question concerns the temporal evolution of maladaptive changes after damage and their manifestation in the balance of thalamocortical and corticocortical input to the auditory cortex (ACx). To address these issues, we investigated the loci of plastic reorganizations across the tonotopic axis of the auditory cortex of male Mongolian gerbils (Meriones unguiculatus) acutely after a sound trauma and after several weeks. We used a residual current-source density analysis to dissociate adaptations of intracolumnar input and horizontally relayed corticocortical input to synaptic populations across cortical layers in ACx. A pure tone-based sound trauma caused acute changes of subcortical inputs and corticocortical inputs at all tonotopic regions, particularly showing a broad reduction of tone-evoked inputs at tonotopic regions around the trauma frequency. At other cortical sites, the overall columnar activity acutely decreased, while relative contributions of lateral corticocortical inputs increased. After 4–6 weeks, cortical activity in response to the altered sensory inputs showed a general increase of local thalamocortical input reaching levels higher than before the trauma. Hence, our results suggest a detailed mechanism for overcompensation of altered frequency input in the auditory cortex that relies on a changing balance of thalamocortical and intracortical input and along the frequency gradient of the cortical tonotopic map.
CRIS-Team Scopus Importer:2021-01-29
Keywords: auditory cortex; circuit level analysis; corticocortical; noise-induced hearing loss; thalamocortical

Adaptive stochastic resonance for unknown and variable input signals - Krauß, Patrick; Metzner, Claus; Schilling, Achim; Schütz, Christian; Tziridis, Konstantin; Fabry, Ben; Schulze, Holger (Scientific Reports, 2017)

Additional Diffusion-Weighted Imaging with Background Body Signal Suppression (DWIBS) Improves Pre-Therapeutical Detection of Early-Stage (pT1a) Glottic Cancer: A Feasibility and Interobserver Reliability Study - Schleder, Stephan; May, Matthias; Habicher, Werner; Dinkel, Johannes; Schreyer, Andreas G.; Gostian, Antoniu-Oreste; Schicho, Andreas (Diagnostics, 2022)
(1) Background: Early-stage glottic cancer is easily missed on magnetic resonance imaging (MRI). Diffusion-weighted imaging (DWI) may improve diagnostic accuracy. Therefore, our aim was to assess the value of adding diffusion-weighted imaging with background body signal suppression (DWIBS) to pre-therapeutic MRI staging. (2) Methods: Two radiologists with 8 and 13 years of experience, blinded to each other's findings, initially interpreted only standard MRI, later DWIBS alone, and afterward, standard MRI + DWIBS in 41 patients with histopathologically proven pT1a laryngeal cancer of the glottis. (3) Results: Detectability rates with standard MRI, DWIBS only, and standard MRI + DWIBS were 68-71%, 63-66%, and 73-76%, respectively. Moreover, interobserver reliability was calculated as good (kappa = 0.712), very good (kappa = 0.84), and good (kappa = 0.69) for standard MRI, DWIBS only, and standard MRI + DWIBS, respectively. (4) Conclusions: Standard MRI, DWIBS alone, and standard MRI + DWIBS showed an encouraging detection rate, as well as distinct interobserver reliability in the diagnosis of early-stage laryngeal cancer when compared to the definitive histopathologic report.
CRIS-Team WoS Importer:2023-01-06

A deep learning enhanced novel software tool for laryngeal dynamics analysis - Kist, Andreas; Gómez, Pablo; Dubrovskiy, Denis; Schlegel, Patrick; Kunduk, Melda; Echternach, Matthias; Patel, Rita; Semmler, Marion; Bohr, Christopher; Durr, Stephan; Schützenberger, Anne; Döllinger, Michael (Journal of Speech Language and Hearing Research, 2021)
Purpose: High-speed videoendoscopy (HSV) is an emerging, but barely used, endoscopy technique in the clinic to assess and diagnose voice disorders because of the lack of dedicated software to analyze the data. HSV allows to quantify the vocal fold oscillations by segmenting the glottal area. This challenging task has been tackled by various studies; however, the proposed approaches are mostly limited and not suitable for daily clinical routine. Method: We developed a user-friendly software in C# that allows the editing, motion correction, segmentation, and quantitative analysis of HSV data. We further provide pretrained deep neural networks for fully automatic glottis segmentation. Results: We freely provide our software Glottis Analysis Tools (GAT). Using GAT, we provide a general threshold-based region growing platform that enables the user to analyze data from various sources, such as in vivo recordings, ex vivo recordings, and high-speed footage of artificial vocalfolds. Additionally, especially for in vivo recordings, we provide three robust neural networks at various speed and quality settings to allow a fully automatic glottis segmentation needed for application by untrained personnel. GAT further evaluates video and audio data in parallel and is able to extract various features from the video data, among others the glottal area waveform, that is, the changing glottal area over time. In total, GAT provides 79 unique quantitative analysis parameters for video-and audio-based signals. Many of these parameters have already been shown to reflect voice disorders, highlighting the clinical importance and usefulness of the GAT software. Conclusion: GAT is a unique tool to process HSV and audio data to determine quantitative, clinically relevant parameters for research, diagnosis, and treatment of laryngeal disorders.
CRIS-Team Scopus Importer:2021-07-02

Adhesion/growth-regulatory galectins in the human eye: localization profiles and tissue reactivities as a standard to detect disease-associated alterations - Schlötzer-Schrehardt, Ursula; Andre, Sabine; Janko, Christina; Kaltner, Herbert; Kopitz, Juergen; Gabius, Hans-Joachim; Herrmann, Martin (Graefes Archive For Clinical and Experimental Ophthalmology, 2012)
To characterize the localization profiles of seven adhesion/growth-regulatory galectins in the normal human eye using immunodetection of endogenous galectins and binding of labeled galectins to sections, useful as a basis to detect disease-associated alterations.Non-cross-reactive anti-galectin antibodies and biotinylated galectins were tested on acetone-fixed cryosections of normal human donor eyes. Controls included omission of first-step reagent, testing of an antibody against a galectin specific for rat (galectin-5), and blocking of galectin binding with lactose.Galectin presence was not restricted to one or few members of this family. Signal occurrence can even include all tested or most proteins (conjunctival or corneal epithelium), whereas choroid positivity is fully accounted for by galectin-9. Regional specificity and characteristic profiles for each protein, immuno- and galectin histochemically, were determined. Differences in tissue reactivity among the galectins were detected.That the galectins have characteristic localization/reactivity profiles supports the concept of a network with potential for non-overlapping functions. The reported data thus prompt to proceed to the respective analysis of specimens from ocular diseases.
EVALuna2:12715

Adjusting Degree of Modification and Composition of gelAGE-Based Hydrogels Improves Long-Term Survival and Function of Primary Human Fibroblasts and Endothelial Cells in 3D Cultures - Genc, Hatice; Cianciosi, Alessandro; Lohse, Raphael; Stahlhut, Philipp; Groll, Jurgen; Alexiou, Christoph; Cicha, Iwona; Juengst, Tomasz (Biomacromolecules, 2023)
This study aimed to develop a suitable hydrogel-based 3D platform to support long-term culture of primary endothelial cells (ECs) and fibroblasts. Two hydrogel systems based on allyl-modified gelatin (gelAGE), G1MM and G2LH, were cross-linked via thiol-ene click reaction with a four-arm thiolated polyethylene glycol (PEG-4-SH). Compared to G1MM, the G2LH hydrogel was characterized by the lower polymer content and cross -linking density with a softer matrix and homogeneous and open porosity. Cell viability in both hydrogels was comparable, although the G2LH-based platform supported better F-actin organization, cell- cell interactions, and collagen and fibronectin production. In co -cultures, early morphogenesis leading to tubular-like structures was observed within 2 weeks. Migration of fibroblasts out of spheroids embedded in the G2LH hydrogels started after 5 days of incubation. Taken together, the results demonstrated that the G2LH hydrogel fulfilled the demands of both ECs and fibroblasts to enable long-term culture and matrix remodeling.
CRIS-Team WoS Importer:2023-03-17

Advance directives in patients with head and neck cancer - status quo and factors influencing their creation - Allner, Moritz; Gostian, Magdalena; Rupp, Robin; Allner, Clarissa; Mantsopoulos, Konstantinos; Ostgathe, Christoph; Iro, Heinrich; Hecht, Markus; Gostian, Antoniu-Oreste; Balk, Matthias (BMC Palliative Care, 2022)
Background: Advance Care Planning including living wills and durable powers of attorney for healthcare is a highly relevant topic aiming to increase patient autonomy and reduce medical overtreatment. Data from patients with head and neck cancer (HNC) are not currently available. The main objective of this study was to survey the frequency of advance directives (AD) in patients with head and neck cancer. Methods: In this single center cross-sectional study, we evaluated patients during their regular follow-up consultations at Germany’s largest tertiary referral center for head and neck cancer, regarding the frequency, characteristics, and influencing factors for the creation of advance directives using a questionnaire tailored to our cohort. The advance directives included living wills, durable powers of attorney for healthcare, and combined directives. Results: Four hundred and forty-six patients were surveyed from 07/01/2019 to 12/31/2019 (response rate = 68.9%). The mean age was 62.4 years (SD 11.9), 26.9% were women (n = 120). 46.4% of patients (n = 207) reported having authored at least one advance directive. These documents included 16 durable powers of attorney for healthcare (3.6%), 75 living wills (16.8%), and 116 combined directives (26.0%). In multivariate regression analysis, older age (OR ≤ 0.396, 95% CI 0.181–0.868; p = 0.021), regular medication (OR = 1.896, 95% CI 1.029–3.494; p = 0.040), and the marital status (“married”: OR = 2.574, 95% CI 1.142–5.802; p = 0.023; and “permanent partnership”: OR = 6.900, 95% CI 1.312–36.295; p = 0.023) emerged as significant factors increasing the likelihood of having an advance directive. In contrast, the stage of disease, the therapeutic regimen, the ECOG status, and the time from initial diagnosis did not correlate with the presence of any type of advance directive. Ninety-one patients (44%) with advance directives created their documents before the initial diagnoses of head and neck cancer. Most patients who decide to draw up an advance directive make the decision themselves or are motivated to do so by their immediate environment. Only 7% of patients (n = 16) actively made a conscious decision not create an advance directive. Conclusion: Less than half of head and neck cancer patients had created an advance directive, and very few patients have made a conscious decision not to do so. Older and comorbid patients who were married or in a permanent partnership had a higher likelihood of having an appropriate document. Advance directives are an essential component in enhancing patient autonomy and allow patients to be treated according to their wishes even when they are unable to consent. Therefore, maximum efforts are advocated to increase the prevalence of advance directives, especially in head and neck cancer patients, whose disease often takes a crisis-like course.
CRIS-Team Scopus Importer:2022-04-22
Keywords: Advance care planning; Advance directive; Head and neck Cancer; Living will; Patient autonomy; Power of attorney for healthcare

Aeroacoustic analysis of the human phonation process based on a hybrid acoustic PIV approach - Lodermeyer, Alexander; Tautz, Matthias; Becker, Stefan; Döllinger, Michael; Birk, Veronika; Kniesburges, Stefan (Experiments in Fluids, 2018)
The detailed analysis of sound generation in human phonation is severely limited as the accessibility to the laryngeal flow region is highly restricted. Consequently, the physical basis of the underlying fluid–structure–acoustic interaction that describes the primary mechanism of sound production is not yet fully understood. Therefore, we propose the implementation of a hybrid acoustic PIV procedure to evaluate aeroacoustic sound generation during voice production within a synthetic larynx model. Focusing on the flow field downstream of synthetic, aerodynamically driven vocal folds, we calculated acoustic source terms based on the velocity fields obtained by time-resolved high-speed PIV applied to the mid-coronal plane. The radiation of these sources into the acoustic far field was numerically simulated and the resulting acoustic pressure was finally compared with experimental microphone measurements. We identified the tonal sound to be generated downstream in a small region close to the vocal folds. The simulation of the sound propagation underestimated the tonal components, whereas the broadband sound was well reproduced. Our results demonstrate the feasibility to locate aeroacoustic sound sources inside a synthetic larynx using a hybrid acoustic PIV approach. Although the technique employs a 2D-limited flow field, it accurately reproduces the basic characteristics of the aeroacoustic field in our larynx model. In future studies, not only the aeroacoustic mechanisms of normal phonation will be assessable, but also the sound generation of voice disorders can be investigated more profoundly.

Aeroacoustic and vibroacoustic mechanisms during phonation - Lodermeyer, Alexander; Mohamadi Bagheri, Eman; Näger, Christoph; Nusser, Katrin; Becker, Stefan; Döllinger, Michael; Kniesburges, Stefan (13th International Conference on Advances in Quantitative Laryngology, Voice and Speech Research, 2019)

Aeroacoustic sound generation during phonation - analysis of acoustic analogies for a hybrid acoustic PIV approach - Lodermeyer, Alexander; Tautz, Matthias; Mohamadi Bagheri, Eman; Becker, Stefan; Döllinger, Michael; Kniesburges, Stefan (11th International Conference on Voice Physiology and Biomechanics, 2018)

Aeroacoustic sound generation during phonation - analysis of acoustic analogies for a Hybrid Acoustic PIV approach - Lodermeyer, Alexander; Tautz, Matthias; Mohamadi Bagheri, Eman; Becker, Stefan; Döllinger, Michael; Kniesburges, Stefan (11th Internation conference on voice physiology and biomechanics, 2018)

Aeroacoustic sound generation during phonation in a synthetic larynx model - Kniesburges, Stefan; Lodermeyer, Alexander; Tautz, Matthias; Becker, Stefan; Döllinger, Michael (Journal of the Acoustical Society of America, 2016)

Aeroacoustic sound generation during phonation in a synthetic larynx model - Kniesburges, Stefan; Lodermeyer, Alexander; Tautz, Matthias; Döllinger, Michael; Becker, Stefan (Fortschritte der Akustik – DAGA 2017, 2017)

Aeroacoustic sound source characterization of the human voice production-perturbed convective wave equation - Schoder, Stefan; Maurerlehner, Paul; Wurzinger, Andreas; Hauser, Alexander; Falk, Sebastian; Kniesburges, Stefan; Döllinger, Michael; Kaltenbacher, Manfred (Applied Sciences, 2021)
The flow-induced sound sources of human voice production are investigated based on a validated voice model. This analysis is performed using a hybrid aeroacoustic workflow based on the perturbed convective wave equation. In the first step, the validated 3D incompressible turbulent flow simulation is computed by the finite volume method using STARCCM+. In a second step, the aeroacoustic sources are evaluated and studied in detail. The formulation of the sound sources is compared to the simplification (neglecting the convective sources) systematically using time-domain and Fourier-space analysis. Additionally, the wave equation is solved with the finite element solver openCFS to obtain the 3D sound field in the acoustic far-field. During the detailed effect analysis, the far-field sound spectra are compared quantitatively, and the flow-induced sound sources are visualized within the larynx. In this contribution, it is shown that the convective part of the sources dominates locally near the vocal folds (VFs) while the local time derivative of the incompressible pressure is distributed in the whole supra-glottal area. Although the maximum amplitude of the time derivative is lower, the integral contribution dominates the sound spectrum. As a by-product of the detailed perturbed convective wave equation source study, we show that the convective source term can be neglected since it only reduces the validation error by 0.6%. Neglecting the convective part reduces the algorithmic complexity of the aeroacoustic source computation of the perturbed convective wave equation and the stored flow data. From the source visualization, we learned how the VF motion transforms into specific characteristics of the aeroacoustic sources. We found that if the VFs are fully closing, the aeroacoustic source terms yield the highest dynamical range. If the VFs are not fully closing, VFs motion does not provide as much source energy to the flow-induced sound sources as in the case of a healthy voice. As a consequence of not fully closing VFs, the cyclic pulsating velocity jet is not cut off entirely and therefore turbulent structures are permanently present inside the supraglottal region. These turbulent structures increase the broadband component of the voice signal, which supports research results of previous studies regarding glottis closure and insufficient voice production.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Computational aeroacoustics; Convective wave equation; Human voice; Phonation; Source term analysis; Vocal folds; Voice production

Aerodynamic impact of the ventricular folds in computational larynx models - Sadeghi, Hossein; Döllinger, Michael; Kaltenbacher, Manfred; Kniesburges, Stefan (Journal of the Acoustical Society of America, 2019)
Ventricular folds (VeFs) act as passive, non-moving structures during normal phonation. According to the literature, VeFs potentially aid the flow-driven oscillations of the vocal folds (VFs) that produce the primary sound of human phonation. In this study, large eddy simulations were performed to analyze this influence in a numerical model with imposed VF motion as measured experimentally from a synthetic silicone vocal fold model. Model configurations with and without VeFs were considered. Furthermore, configurations with rectangular and elliptical glottis shapes were simulated to investigate the effects of three-dimensional glottal jet evolutions. Results showed that VeFs increased flow rate and transglottal pressure difference by a decrease in the pressure level in the ventricles immediately downstream of the VFs. This led to an increase in the glottal flow resistance, increased energy transfer rate between the flow and VFs, and a simultaneous decrease in the laryngeal flow resistance, which shows a higher amount of kinetic energy in the glottal flow. This enhancement was more pronounced in the rectangular glottis and varied with the subglottal pressure and VeF gap size.
CRIS-Team Scopus Importer:2019-05-14

Aerosol Transmission of SARS-CoV-2: Inhalation as well as Exhalation Matters for COVID-19 Reply - Echternach, Matthias; Westphalen, Caroline; Koeberlein, Marie Christine; Gantner, Sophia; Peters, Gregor; Benthaus, Tobias; Jakubaß, Bernhard; Kuranova, Liudmila; Döllinger, Michael; Kniesburges, Stefan (American Journal of Respiratory and Critical Care Medicine, 2021)
CRIS-Team WoS Importer:2021-05-21

A Founder Mutation in EHD1 Presents with Tubular Proteinuria and Deafness - Issler, Naomi; Afonso, Sara; Weissman, Irith; Jordan, Katrin; Cebrian-Serrano, Alberto; Meindl, Katrin; Dahlke, Eileen; Tziridis, Konstantin; Yan, Guanhua; Robles-López, José M.; Tabernero, Lydia; Patel, Vaksha; et al. (Journal of the American Society of Nephrology, 2022)
BACKGROUND: The endocytic reabsorption of proteins in the proximal tubule requires a complex machinery and defects can lead to tubular proteinuria. The precise mechanisms of endocytosis and processing of receptors and cargo are incompletely understood. EHD1 belongs to a family of proteins presumably involved in the scission of intracellular vesicles and in ciliogenesis. However, the relevance of EHD1 in human tissues, in particular in the kidney, was unknown. METHODS: Genetic techniques were used in patients with tubular proteinuria and deafness to identify the disease-causing gene. Diagnostic and functional studies were performed in patients and disease models to investigate the pathophysiology. RESULTS: We identified six individuals (5-33 years) with proteinuria and a high-frequency hearing deficit associated with the homozygous missense variant c.1192C>T (p.R398W) in EHD1. Proteinuria (0.7-2.1 g/d) consisted predominantly of low molecular weight proteins, reflecting impaired renal proximal tubular endocytosis of filtered proteins. Ehd1 knockout and Ehd1R398W/R398W knockin mice also showed a high-frequency hearing deficit and impaired receptor-mediated endocytosis in proximal tubules, and a zebrafish model showed impaired ability to reabsorb low molecular weight dextran. Interestingly, ciliogenesis appeared unaffected in patients and mouse models. In silico structural analysis predicted a destabilizing effect of the R398W variant and possible inference with nucleotide binding leading to impaired EHD1 oligomerization and membrane remodeling ability. CONCLUSIONS: A homozygous missense variant of EHD1 causes a previously unrecognized autosomal recessive disorder characterized by sensorineural deafness and tubular proteinuria. Recessive EHD1 variants should be considered in individuals with hearing impairment, especially if tubular proteinuria is noted.
CRIS-Team Scopus Importer:2022-04-22
Keywords: epithelial transport physiology; Eps15 homology domain; genetic renal disease; infertility; megalin; mutation; proximal tubule

Age-Related Decline of Speech Perception - Hoppe, Ulrich; Hocke, Thomas; Iro, Heinrich (Frontiers in Aging Neuroscience, 2022)
Hearing loss is one of the most common disorders worldwide. It affects communicative abilities in all age groups. However, it is well known that elderly people suffer more frequently from hearing loss. Two different model approaches were employed: A generalised linear model and a random forest regression model were used to quantify the relationship between pure-tone hearing loss, age, and speech perception. Both models were applied to a large clinical data set of 19,801 ears, covering all degrees of hearing loss. They allow the estimation of age-related decline in speech recognition for different types of audiograms. Our results show that speech scores depend on the specific type of hearing loss and life decade. We found age effects for all degrees of hearing loss. A deterioration in speech recognition of up to 25 percentage points across the whole life span was observed for constant pure-tone thresholds. The largest decrease was 10 percentage points per life decade. This age-related decline in speech recognition cannot be explained by elevated hearing thresholds as measured by pure-tone audiometry.
CRIS-Team Scopus Importer:2022-07-22
Keywords: age-related hearing loss (ARHL); hearing loss; machine learning; maximum word recognition; random forest regression; speech audiometry; speech perception

Age-related language performance and device use in children with very early bilateral cochlear implantation - Glaubitz, Cynthia; Liebscher, Tim; Hoppe, Ulrich (International Journal of Pediatric Otorhinolaryngology, 2021)
Objectives: Paediatric cochlear implantation within the first year of life results in better outcome in auditory and language skills. Beside individual, audiological and social factors, quantity and quality of daily cochlear implant (CI) use also seem to be an influencing factor. The purpose of this study was to evaluate children's early receptive and expressive language performance considering bilingual language development as well as quantity and quality of daily CI use and intraoperative objective measurements. Methods: The retrospective analysis included data from 35 very early bilaterally cochlear-implanted children (age at CI M = 8.4 +/- 1.5 months). Language performance was assessed by the German standardised test SETK-2 (age at testing M = 29.4 +/- 4.0 months). The CI system-integrated data-logging was analysed with regard to daily CoilOn-time, CoilOff and exposure to classified listening scenes. Intraoperatively measured thresholds of evoked compound action potentials (T-ECAPs) were analysed to ensure CI functionality. Results: The cohort showed language performance within the normal range for word comprehension, sentence comprehension and word production, level of sentence production was reduced. Overall, bilingual children performed less well than monolingual children. Intraoperative T-ECAPs were recorded for the total cohort and no anomalies were detected. Children used their CI for about 8.7 +/- 1.4 h per day, most of this time spent in a quiet environment (38%). Word production was significantly correlated with the daily duration of CI use (CoilOn-time) and with exposure to the listening environment Speech. No correlation was found between number of daily coil disconnections (CoilOff) and language performance. Conclusion: Very early bilateral cochlear implantation may result in age-appropriate language skills already at the age of 2 years. Monolingualism seems to a better condition for early language development with CI than bilingualism. Especially for word production, the daily duration of CI use and exposure time in a speechcharacterised environment seem to be additional positive factors. Monitoring the data-logs should be one important focus of professionals during the postoperative rehabilitation process to detect potential benefits and risks. These findings should be integrated into rehabilitative therapy and parent counselling.
CRIS-Team WoS Importer:2021-07-30

Agranulozytose nach Metamizol-Einnahme – ein unterschätztes Risiko? - Schinz, Katharina; Wüst, Wolfgang; Iro, Heinrich; Waldfahrer, Frank (Laryngo-Rhino-Otologie, 2020)
OBJECTIVE: Metamizole was the second most common drug prescribed in Germany in 2018 despite the known risk of agranulocytosis and the strict indication. According to Stammschulte et al. up to 25 % of all prescriptions are off-label use. Although mandatory according to the prescribing information of metamizole, regular blood cell counts are not performed in up to 50 % of the patients with long-term use of this drug. MATERIAL AND METHODS: Retrospective analysis of eight cases metamizole-induced agranulocytosis over a period of five years (2016-2020) in the university ENT department in Erlangen. Five patients were men and three women. Mean age of diagnosis was 52,4 years (± 25,6). RESULTS: Agranulocytosis after use of metamizole is a serious adverse drug reaction that may affect patients of all ages. Frequently, only distinct clinical symptoms such as temperature of unknown origin, dysphagia and tonsillitis in combination with abscesses in the head and neck area result in the detection of a metamizole-induced agranulocytosis. An agranulocytosis provokes partially radical surgery and/ or intensive-care measures and could lead to sepsis with organ failure or even to death. CONCLUSIONS: These patient cases show that agranulocytosis is a dangerous or even deadly adverse drug reaction after use of metamizole. Although the risk of agranulocytosis appears to increase with duration of use, we would recommend patient education as well as documentation of even a single administration of metamizole. This may facilitate early diagnosis of metamizole-induced agranulocytosis and thus prevent the onset of severe complications with possible lethal outcome.
CRIS-Team Scopus Importer:2020-07-10

A hybrid acoustic PIV approach to characterize sound generation in a human larynx model - Lodermeyer, Alexander; Becker, Stefan; Mohamadi Bagheri, Eman; Tautz, Matthias; Döllinger, Michael; Kniesburges, Stefan (19th International Symposium on the Application of Laser and Imaging Techniques to Fluid Mechanics, 2018)

ALK Rearrangements Characterize 2 Distinct Types of Salivary Gland Carcinomas Clinicopathologic and Molecular Analysis of 4 Cases and Literature Review - Agaimy, Abbas; Baneckova, Martina; Ihrler, Stephan; Mueller, Sarina K.; Franchi, Alessandro; Hartmann, Arndt; Stöhr, Robert; Skalova, Alena (American Journal of Surgical Pathology, 2021)
The majority of salivary gland carcinomas are characterized by recurrent gene fusions that proved highly valuable diagnostically, but only rarely of therapeutic impact. Most of these fusion-positive carcinomas belong to the low-grade or intermediategrade biological category. To date, only 5 cases of salivary gland carcinomas carrying an oncogenic ALK fusion have been reported in 4 recent studies, but their phenotypic spectrum and their nosological classification remain uncharacterized. We herein describe in detail the clinicopathologic and molecular features of 4 ALK-fusion-positive salivary carcinomas and review previously reported cases to assess if they could be classified into a defined World Health Organization (WHO) category. Patients were 3 men and 1 woman aged from 67 to 79 years (median: 70 y). All tumors originated in the parotid gland. Their size ranged from 1.1 to 3 cm (mean, 2 cm). Three tumors were de novo high-grade salivary duct carcinomas (SDCs) and 1 was a low-grade intercalated-type intraductal carcinoma. Histologically, high-grade tumors were predominantly solid, composed of intimately admixed basal (CK5+, androgen-) and luminal (CK5-, androgen+) components. The remarkable basal component showed squamoid basophilic pattern imparting an adenosquamous-like appearance in all cases. Conventional apocrine intraductal high-grade carcinoma was noted in 1 case. Prominent intraductal growth of the solid basal component (highlighted by p63 staining) was seen in all cases. The tumor cells expressed CK7 (3/3), mammaglobin (3/3, 1 focal), GATA3 (3/3, 1 focal), variably CK5 (3/3), and focally the androgen receptor (1/3), but lacked expression of HER2/neu, SOX10, MUC4, TTF1, FS100, and Napsin A. The low-grade tumor showed classic histologic and immunophenotypic features of intercalated-type non-invasive intraductal carcinoma. Molecular profiling showed rearrangements involving exon 20 of ALK in all cases, confirmed by ALK immunohistochemistry (IHC and FISH). The fusion partner was EML4 (n= 2) and STRN (n= 1) in high-grade tumors and EML4 in the intraductal carcinoma. Two patients with high-grade tumors developed progressive disease (1 died at 9 mo; 1 alive under palliative therapy at 5 mo). This series and a review of 5 published cases indicate that ALK rearrangements characterize 2 distinct subsets of salivary gland carcinomas in the spectrum of high-grade androgen-poor, basal-like SDC (total reported: 5 cases) and low-grade intercalated-type intraductal carcinomas (4 cases). Given the therapeutic relevance of ALK fusions, inclusion of ALK IHC in any atypical-looking or androgen-poor SDC and in high-grade adenocarcinoma-not otherwise specified is recommended. Absence of aberrant ALK expression in genetically characterized secretory (n= 15) and intraductal (n= 9) carcinomas lacking ALK fusions underlines the value of ALK IHC as a diagnostic screening method for identifying potential cases.
CRIS-Team WoS Importer:2021-08-27

Altered glycosylation of complexed native IgG molecules is associated with disease activity of systemic lupus erythematosus - Sjowall, Christopher; Zapf, J.; Von Loehneysen, S.; Magorivska, I.; Biermann, M.; Janko, Christina; Winkler, Sophie; Bilyy, R.; Schett, Georg; Herrmann, Martin; Munoz Becerra, Luis (Lupus, 2015)
In addition to the redundancy of the receptors for the Fc portion of immunoglobulins, glycans result in potential ligands for a plethora of lectin receptors found in immune effector cells. Here we analysed the exposure of glycans containing fucosyl residues and the fucosylated tri-mannose N-type core by complexed native IgG in longitudinal serum samples of well-characterized patients with systemic lupus erythematosus. Consecutive serum samples of a cohort of 15 patients with systemic lupus erythematosus during periods of increased disease activity and remission were analysed. All patients fulfilled the 1982 American College of Rheumatology classification criteria. Sera of 15 sex- and age-matched normal healthy blood donors served as controls. The levels and type of glycosylation of complexed random IgG was measured with lectin enzyme-immunosorbent assays. After specifically gathering IgG complexes from sera, biotinylated lectins Aleuria aurantia lectin and Lens culinaris agglutinin were employed to detect IgG-associated fucosyl residues and the fucosylated tri-mannose N-glycan core, respectively. In sandwich-ELISAs, IgG-associated IgM, IgA, C1q, C3c and C-reactive protein (CRP) were detected as candidates for IgG immune complex constituents. We studied associations of the glycan of complexed IgG and disease activity according to the physician's global assessment of disease activity and the systemic lupus erythematosus disease activity index 2000 documented at the moment of blood taking. Our results showed significantly higher levels of Aleuria aurantia lectin and Lens culinaris agglutinin binding sites exposed on IgG complexes of patients with systemic lupus erythematosus than on those of normal healthy blood donors. Disease activity in systemic lupus erythematosus correlated with higher exposure of Aleuria aurantia lectin-reactive fucosyl residues by immobilized IgG complexes. Top levels of Aleuria aurantia lectin-reactivity were found in samples taken during the highest activity of systemic lupus erythematosus. Our results show that native circulating IgG complexes from active systemic lupus erythematosus patients expose fucosyl residues and their glycan core is accessible to soluble lectins. Two putative mechanisms may contribute to the increased exposure of these glycans: (1) the canonical N-glycosylation site of the IgG-CH2 domain; (2) an IgG binding non-IgG molecule, like complement or C-reactive protein. In both cases the complexed IgG may be alternatively targeted to lectin receptors of effector cells, e.g. dendritic cells.
EVALuna2:13017

A method for characterizing stapes prostheses by their mechanical transfer function - Sutor, Alexander; Hornung, Joachim; Goßler, Julian; Döllinger, Michael; Lerch, Reinhard (Medical Engineering & Physics, 2012)
In this contribution, we present and evaluate a method for characterizing stapes prostheses by their mechanical transfer function. The measurements were carried out after a stapedotomy surgery was performed in three human temporal bones conserved in 4% formaldehyde. The inner ear was drained of fluid. Successively, one of three different stapes prostheses was inserted. After such preparation, the prosthesis piston movement compared to the incus movement is measured with laser vibrometry. The magnitude transfer function considered is defined as the amplitude of the prosthesis piston movement compared to the amplitude of the incus movement. Measurements were made in a frequency range from 500 Hz to 4 kHz. The measured amplitudes roughly ranged between 10 nm and 100 nm. A great advantage of the presented method is the fact that only a small portion of the ossicular chain influences the measurement, mainly the joint between the prosthesis and the incus. Furthermore, the usage of cadaver temporal bones allows for an automated measurement setup, long term experiments and the access of measurement positions inapproachable during in vivo measurements. With this method, the different kinds of prostheses could be evaluated on incuses of different diameters. (C) 2012 IPEM. Published by Elsevier Ltd. All rights reserved.
Keywords: Otosclerosis; Stapes prosthesis; Crimping; Mechanical transfer function; Laser vibrometer

An acoustic pressure pipette aspiration method for isotropic materials - Maghzinajafabadi, M.; Lamprecht, R.; Döllinger, Michael; Semmler, Marion; Sutor, Sutor (Journal of Physics: Conference Series, 2019)
A measurement setup is presented as a method to determine the elasticity modulus of both artificial and real tissue as a function of frequency. The future goal at the end is to develop and validate the method to measure the elasticity modulus of ex vivo cadaver animal vocal folds over the human phonation frequency range. In the present study, we investigate an innovative acoustic pressure pipette aspiration technique to measure the material characteristic of an isotropic silicone specimen with similar characteristics as human vocal folds. With the aim of ensuring reliable results, we test our method on different mixtures of silicone rubber. Four silicone samples with different consistencies were tested over a frequency range of 50 -500Hz. Influence of vibrometer laser spot location in an enclosed area on the sample surface was investigated by repeating the measurements ten times. The results show only small standard deviations demonstrating the potential of the acoustic pressure pipette aspiration technique for material characterization.
CRIS-Team Scopus Importer:2020-02-21

Analysis and visualization of sleep stages based on deep neural networks - Krauß, Patrick; Metzner, Claus; Joshi, Nidhi; Schulze, Holger; Traxdorf, Maximilian; Maier, Andreas; Schilling, Achim (Neurobiology of Sleep and Circadian Rhythms, 2021)
Automatic sleep stage scoring based on deep neural networks has come into focus of sleep researchers and physicians, as a reliable method able to objectively classify sleep stages would save human resources and simplify clinical routines. Due to novel open-source software libraries for machine learning, in combination with enormous recent progress in hardware development, a paradigm shift in the field of sleep research towards automatic diagnostics might be imminent. We argue that modern machine learning techniques are not just a tool to perform automatic sleep stage classification, but are also a creative approach to find hidden properties of sleep physiology. We have already developed and established algorithms to visualize and cluster EEG data, facilitating first assessments on sleep health in terms of sleep-apnea and consequently reduced daytime vigilance. In the following study, we further analyze cortical activity during sleep by determining the probabilities of momentary sleep stages, represented as hypnodensity graphs and then computing vectorial cross-correlations of different EEG channels. We can show that this measure serves to estimate the period length of sleep cycles and thus can help to find disturbances due to pathological conditions.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Artificial neural networks; Deep learning; Electroencephalography (EEG); Hypnodensity graphs; Multidimensional scaling (MDS); Polysomnography (PSG); Sleep cycle analysis; Sleep stage scoring

Analysis Method for the Neurological and Physiological Processes Underlying the Pitch-Shift Reflex - Petermann, Simon; Döllinger, Michael; Kniesburges, Stefan; Ziethe, Anke (Acta Acustica United With Acustica, 2016)
The Pitch-shift reflex (PSR) is the adjustment of the voice pitch during phonation or speech in response to a spontaneous perturbation (pitch-shift) of the perceived auditory feedback. The PSR is the result of the interaction of neurological and physiological processes underlying mechanisms for the pitch control during voice production. We present an experimental set-up for a comprehensive analysis of the PSR. Therefore, EEG, EGG, the voice signal and vocal fold dynamics are synchronously recorded and analysed for two paradigms, i.e. phonation (vowel /a/) and speech (['mama]). To visualise vocal fold dynamics, transnasal high-speed endoscopy (HSE) imaging was conducted. The PSR was elicited by a synthetic increase of the fundamental frequency of the auditory feedback. The occurrence of the PSR was verified by detecting the N100 and the Mismatch Negativity (MMN) in the EEG. For voice and EGG, statistical tests were applied to detect significant variations of the fundamental frequency due to the PSR. Additionally, the HSE footage was evaluated to judge for the applicability of PSR detection in comparison to the common voice and EGG signal. A preliminary study with five subjects was conducted. PSR was found in physiological latency ranges for EEG, EGG, and voice signals. Furthermore, the PSR was also successfully verified in the HSE data which showed similar sensitivity for PSR detection as EGG and voice signals. Hence, we suggest HSE as promising additional tool to gain further information on PSR processes due to the possibility of directly observing the vocal fold dynamics in detail.
EVALuna2:33201

Analysis of Audiometric Differences of Patients with and without Tinnitus in a Large Clinical Database - Gollnast, Dominik; Tziridis, Konstantin; Krauß, Patrick; Schilling, Achim; Hoppe, Ulrich; Schulze, Holger (Frontiers in Neurology, 2017)
Human hearing loss (HL) and comorbidities like tinnitus pose serious problems for people's daily life, which in most severe cases may lead to social isolation, depression, and suicide. Here, we investigate the relationship between hearing deficits and tinnitus. To this end, we conducted a retrospective study on anonymized pure tone and speech audiometric data from patients of the ENT hospital Erlangen in which we compare audiometric data between patients with and without tinnitus. Overall data from 37,661 patients with sensorineural (SHL) or conductive HL (CHL) with (T, 9.5%) or without (NT, 90.5%) a tinnitus percept in different age groups and with different tinnitus pitches were included in this study. The results of the pure tone audiometry comparisons showed significant differences in T patients compared to NT patients. In young patients, we generally found lower hearing thresholds in T compared to NT patients. In adult patients, differences were more heterogeneous: hearing thresholds in T patients were lower in low frequency ranges, while they were higher at high frequencies. Furthermore, lower thresholds were more often found in CHL patients and could rarely be detected in SHL patients. In speech audiometry, only CHL patients with high-pitched tinnitus showed lower thresholds compared to NT patients' thresholds. The results of this study may point to a biologically plausible functional benefit on hearing thresholds in HL tinnitus patients. We hypothesize that the physiological mechanism of stochastic resonance counteracts HL by adding neuronal noise to the system. This neuronal noise may induce changes in the auditory pathway and finally-as a side effect of threshold improvement-lead to the development of a tinnitus percept. We propose a general model of changed hearing thresholds in T patients, being either decreased or increased compared to NT patients.
EVALuna2:33169

Analysis of CRSsNP Proteome Using a Highly Multiplexed Approach in Nasal Mucus - Pesold, Vanessa; Wendler, Olaf; Morgenthaler, Lisa; Gröhn, Franziska; Mueller, Sarina K. (American Journal of Rhinology & Allergy, 2022)
Background: Chronic rhinosinusitis without nasal polyps (CRSsNP) represents a phenotype of CRS, whose immunological mechanisms are still unclear. So far there are neither suitable biomarkers to determine the course of the disease nor an individual therapy. Objective: The purpose of this study was to characterize the CRSsNP endotype by identifying and validating non-invasive proteomic biomarkers. Methods: A highly-multiplexed proteomic array consisting of antibodies against 2000 proteins was used to identify proteins that are differentially expressed in the nasal mucus of the CRSsNP and control groups (n = 7 per group). The proteins identified to be most differentially expressed were validated in matched nasal mucus samples using western blots and enzyme-linked immunosorbent assay (ELISA). Validation was also done in a second cohort using western blots (CRSsNP n = 25, control n = 23) and ELISA (n = 30 per group). Additionally, immunohistochemistry in CRSsNP and control tissue samples was performed to characterize the selected proteins further. Results: Out of the 2000 proteins examined, 7 from the most differentially expressed proteins were chosen to be validated. The validation results showed that 4 proteins were significantly upregulated in CRSsNP mucus, including macrophage inflammatory protein-1beta (MIP-1β), resistin, high mobility group box 1 (HMGB1), and forkhead box protein 3 (FOXP3). Cartilage acidic protein 1 (CRTAC1) was not significantly upregulated. Two proteins were significantly downregulated including scavenger receptor class F member 2 (SCARF2) and P-selectin. All proteins selected are mainly associated with inflammation, cell proliferation/differentiation, apoptosis and cell–cell or cell–matrix interaction. Conclusion: Proteomic analysis of CRSsNP and control mucus has confirmed known and revealed novel disease-associated proteins that could potentially serve as a new biosignature for CRSsNP. Analysis of the associated pathways will specify endotypes of CRSsNP and will lead to an improved understanding of the pathophysiology of CRSsNP. Furthermore, our data contribute to the development of a reproducible, non-invasive, and quantitative “liquid biopsy” for rhinosinusitis.
CRIS-Team Scopus Importer:2022-11-25
Keywords: biomarker; biosignature; chronic rhinosinusitis; chronic rhinosinusitis with nasal polyps; inflammation; microarray; mucus; noninvasive; proteomics; sinusitis

Analysis of Hypericin-Mediated Effects and Implications for Targeted Photodynamic Therapy - Mühleisen, Laura; Alev, Magdalena; Unterweger, Harald; Subatzus, Daniel; Poettler, Marina; Friedrich, Ralf P.; Alexiou, Christoph; Janko, Christina (International Journal of Molecular Sciences, 2017)
The phototoxic effect of hypericin can be utilized for Photodynamic Therapy (PDT) of cancer. After intravenous application and systemic distribution of the drug in the patient's body, the tumor site is exposed to light. Subsequently, toxic reactive oxygen species (ROS) are generated, inducing tumor cell death. To prevent unwanted activation of the drug in other regions of the body, patients have to avoid light during and after the treatment cycles, consequently impairing quality of life. Here, we characterize toxicity and hypericin-mediated effects on cancer cells in vitro and confirm that its effect clearly depends on concentration and illumination time. To reduce side effects and to increase therapy success, selective accumulation of hypericin in the tumor region is a promising solution. Loading hypericin on superparamagnetic iron oxide nanoparticles (SPIONs) and guiding them to the desired place using an external magnetic field might accomplish this task (referred to as Magnetic Drug Targeting (MDT)). Thus, using a double targeting strategy, namely magnetic accumulation and laser induced photoactivation, might improve treatment effectivity as well as specificity and reduce toxic side effects in future clinical applications.
EVALuna2:33199

Analysis of Multichannel EEG Patterns During Human Sleep: A Novel Approach - Krauß, Patrick; Schilling, Achim; Bauer, Judith; Tziridis, Konstantin; Metzner, Claus; Schulze, Holger; Traxdorf, Maximilian (Frontiers in Human Neuroscience, 2018)
Classic visual sleep stage scoring is based on electroencephalogram (EEG) frequency band analysis of 30 s epochs and is commonly performed by highly trained medical sleep specialists using additional information from submental EMG and eye movements electrooculogram (EOG). In this study, we provide the proof-of-principle in 40 subjects that sleep stages can be consistently differentiated solely on the basis of spatial 3-channel EEG patterns based on root-mean-square (RMS) amplitudes. The polysomnographic 3-channel EEG data are pre-processed by RMS averaging over intervals of 30 s leading to spatial cortical activity patterns represented by 3-dimensional vectors. These patterns are visualized using multidimensional scaling (MDS), allowing a comparison of the spatial cortical activity patterns with the conventional visual sleep scoring system according to the American Academy of Sleep Medicine (AASM). Spatial cortical activity patterns based on RMS amplitudes naturally divide into different clusters that correspond to visually scored sleep stages. Furthermore, these clusters are reproducible between different subjects. Especially the cluster associated with the REM sleep stage seems to be very different from the one associated with the wake state. This study provides a proof-of-principle that it is possible to separate sleep stages solely by analyzing spatially distributed EEG RMS amplitudes reflecting cortical activity and without classical EEG feature extractions like power spectrum analysis.
EVALuna2:35750

Analysis of Process Costing for the Use of Navigation Systems in Functional Endoscopic Sinus Surgery - Schwan, Franziska Eva; Traxdorf, Maximilian; Seebauer, Caroline Theresa; Sekita, Alexander; Habekost, Cornelia; Iro, Heinrich; Bohr, Christopher (Applied Sciences, 2021)
Featured Application This paper and its findings are important for any clinic that is thinking about setting up a navigation system for its ENT department, concerning the costs, efficiency in the operating room, and applicability for training purposes. (1) Background: The use of navigation systems is rarely necessary for routine sinus surgery. They may prove to be advantageous for difficult operations, for example, in finding structures that are difficult to reach, in the treatment of cancers, or in revisional surgery. Navigation systems are also said to have positive effects on the self-confidence of surgeons in stressful situations and in the training of doctors. (2) Methods: This retrospective study included patients who underwent surgical treatment for chronic sinusitis from 2012 to 2016 at the ENT clinic of the University Hospital, Erlangen. Two groups were formed; one includes patients without navigated sinus surgery, the other includes those with navigation. The incision-suture times of both groups and cost analysis are compared. An appropriate cost estimate for sinus surgery is determined. (3) Results: From the available results, no economically efficient navigation systems in sinus surgery at the ENT clinic can be shown. The main reason is that lengthening the operating time leads to higher costs. (4) Conclusions: Although the use of a navigation system for endonasal sinus surgery cannot be economically justified, it is an important tool, especially in cases with complex anatomical conditions, and the system is essential for training purposes.
CRIS-Team WoS Importer:2021-10-08

Analysis of Structure and Dynamics in Three-Neuron Motifs - Krauß, Patrick; Zankl, Alexandra; Schilling, Achim; Schulze, Holger; Metzner, Claus (Frontiers in Computational Neuroscience, 2019)
Recurrent neural networks can produce ongoing state-to-state transitions without any driving inputs, and the dynamical properties of these transitions are determined by the neuronal connection strengths. Due to non-linearity, it is not clear how strongly the system dynamics is affected by discrete local changes in the connection structure, such as the removal, addition, or sign-switching of individual connections. Moreover, there are no suitable metrics to quantify structural and dynamical differences between two given networks with arbitrarily indexed neurons. In this work, we present such permutation-invariant metrics and apply them to motifs of three binary neurons with discrete ternary connection strengths, an important class of building blocks in biological networks. Using multidimensional scaling, we then study the similarity relations between all 3,411 topologically distinct motifs with regard to structure and dynamics, revealing a strong clustering and various symmetries. As expected, the structural and dynamical distance between pairs of motifs show a significant positive correlation. Strikingly, however, the key parameter controlling motif dynamics turns out to be the ratio of excitatory to inhibitory connections.
CRIS-Team WoS Importer:2019-02-27

Analysis of surgical treatment strategy and outcome factors in persistent tracheoesophageal fistula: a critical analysis of own cases and review of the literature - Koch, Matthias; de Vasconcelos Craveiro, Antonio; Mantsopoulos, Konstantinos; Sievert, Matti; Iro, Heinrich; Gostian, Antoniu-Oreste (European Review for Medical and Pharmacological Sciences, 2022)
OBJECTIVE: Surgical closure of persistent tracheoesophageal fistulas (TEFs) is complex. Most patients present with multiple risk factors, which may negatively impact the outcome and influence the treatment strategies. PATIENTS AND METHODS: This retrospective study included 22 patients presenting with persistent TEFs. Preoperative RT, comorbidities, tissue conditions of the TEFs and neck skin, and surgical techniques were evaluated regarding a possible impact on success rates and outcome. RESULTS: 21 patients were operated, 95.45% with final success. However, in 52.39% repeated surgery was needed. Final closure of TEFs was achieved in 91.47% only after more invasive surgery was performed. The surgical technique applied had the most significant impact on success rates and outcome compared to all other risk factors analyzed. Our own data and that of the literature point out that the surgical strategy should be adapted to the patients' individual risk factors. CONCLUSIONS: According to the literature, surgical closure of persistent TEFss is demanding. Our data suggest that, considering that the majority of patients with persistent TEFs exhibit multiple risk factors, early performance of more invasive surgery seems associated with a better outcome.
CRIS-Team WoS Importer:2022-02-04

Analysis of the Auditory Feedback and Phonation in Normal Voices - Arbeiter, Mareike; Petermann, Simon; Hoppe, Ulrich; Bohr, Christopher; Döllinger, Michael; Ziethe, Anke (Annals of Otology Rhinology and Laryngology, 2018)
PURPOSE: The aim of this study was to investigate the auditory feedback mechanisms and voice quality during phonation in response to a spontaneous pitch change in the auditory feedback. Does the pitch shift reflex (PSR) change voice pitch and voice quality? Quantitative and qualitative voice characteristics were analyzed during the PSR. METHOD: Twenty-eight healthy subjects underwent transnasal high-speed video endoscopy (HSV) at 8000 fps during sustained phonation [a]. While phonating, the subjects heard their sound pitched up for 700 cents (interval of a fifth), lasting 300 milliseconds in their auditory feedback. The electroencephalography (EEG), acoustic voice signal, electroglottography (EGG), and high-speed-videoendoscopy (HSV) were analyzed to compare feedback mechanisms for the pitched and unpitched condition of the phonation paradigm statistically. Furthermore, quantitative and qualitative voice characteristics were analyzed. RESULTS: The PSR was successfully detected within all signals of the experimental tools (EEG, EGG, acoustic voice signal, HSV). A significant increase of the perturbation measures and an increase of the values of the acoustic parameters during the PSR were observed, especially for the audio signal. CONCLUSIONS: The auditory feedback mechanism seems not only to control for voice pitch but also for voice quality aspects.
EVALuna2:33156

Analysis of the tonal sound generation during phonation with and without glottis closure - Kniesburges, Stefan; Lodermeyer, Alexander; Semmler, Marion; Schulz, Yvonne; Schützenberger, Anne; Becker, Stefan (Journal of the Acoustical Society of America, 2020)

Analyzing iron oxide nanoparticles for drug delivery - innovative investigation tools for nanotoxicology - Janko, Christina; Poettler, M.; Friedrich, Ralf P.; Zaloga, Jan; Unterweger, Harald; Dürr, Stephan; Tietze, Rainer; Cicha, Iwona; Lyer, Stefan; Alexiou, Christoph (2016)
EVALuna2:33178

An Application of Concentration Shift Keying in a Molecular Communication Testbed - Bartunik, Max; Unterweger, Harald; Kirchner, Jens (Conference on Networked Systems 2021, 2021)

Anatomical study of all carpal and adjoining bones of the wrist using 3D CT reconstruction –Finding the ultimate biomechanical theory - Gill, Dominik; Lyer, Stefan; Alexiou, Christoph; Fried, Frederik; Buder, Thomas; Neuhuber, Winfried; Jacxsens, Matthijs; Horch, Raymund E.; Arkudas, Andreas (Annals of Anatomy-Anatomischer Anzeiger, 2022)
Background: The complex interplay of single wrist bones acting in combination with their ligamentous connections is still not fully understood. In this regard various theories exist, divisible in columnar and ring/row theories. The object of this study was to examine the mobility of the individual carpal bones as well as the ulna and metacarpals relative to each other in wrists of cadaveric hands using CT scans. Methods: The regular wrist mobility of a total of 21 cadaveric hands was examined by CT imaging in neutral position, radial/ulnar abduction as well as wrist flexion and extension. The data were evaluated as 3D models by using a standardized global coordinate system and object coordinate systems. Rotation and translation of each carpal bone as well as radius/ulna and all metacarpal bones were evaluated. Results: The principal motion took place in the carpus between the radius and the proximal carpal row followed by the midcarpal joint and the carpometacarpal joints and not mainly between the individual bones of a row. The scaphoid moves out of its row aggregate mainly during flexion and adapts to the motion of the distal carpal row. The trapezium and first metacarpal bones play a specific role detached from the remaining bones. Conclusions: With this study, a better understanding of the motion of the individual bones of the carpus, the metacarpals and the radius/ulna is shown. The study supports the row theory, where most motion takes place between the individual rows and not between the carpal bones, leaving the scaphoid and the first ray in a special role between the rows.
CRIS-Team Scopus Importer:2022-03-18
Keywords: 3-dimensional Computed Tomography; Biomechanical Theory; Wrist

Anatomy and blood supply of the sternum - Neuhuber, Winfried; Lyer, Stefan; Alexiou, Christoph; Buder, Thomas (Deep Sternal Wound Infections, 2017)
The sternum is a sword-shaped flat bone about 15-17 cm long in the adult (? Fig. 2.1) (Putz and Müller-Gerbi Benninghoff 2003; Williams and Warwick 1980). Its cranial part, the manubrium, connects to the corpus by a synchondrosis in 90% of adults; in the remaining 10% there is a bony fusion (synostosis).
CRIS-Team Scopus Importer:2022-06-27
Keywords: Alba; Corti; Iodine; Ster; Synostosis

An Endoplasmic Reticulum Specific Pro-amplifier of Reactive Oxygen Species in Cancer Cells - Xu, Honggui; Schikora, Margot; Sisa, Miroslav; Daum, Steffen; Klemt, Insa; Janko, Christina; Alexiou, Christoph; Bila, Galyna; Bilyy, Rostyslav; Gong, Wenjie; Schmitt, Michael; Sellner, Leopold; et al. (Angewandte Chemie International Edition, 2021)
The folding and export of proteins and hydrolysis of unfolded proteins are disbalanced in the endoplasmic reticulum (ER) of cancer cells, leading to so-called ER stress. Agents further augmenting this effect are used as anticancer drugs including clinically approved proteasome inhibitors bortezomib and carfilzomib. However, these drugs can affect normal cells, which also rely strongly on ER functions, leading, for example, to accumulation of reactive oxygen species (ROS). To address this problem, we have developed ER-targeted prodrugs activated only in cancer cells in the presence of elevated ROS amounts. These compounds are conjugates of cholic acid with N-alkylaminoferrocene-based prodrugs. We confirmed their accumulation in the ER of cancer cells, their anticancer efficacy, and cancer cell specificity. These prodrugs induce ER stress, attenuate mitochondrial membrane potential, and generate mitochondrial ROS leading to cell death via necrosis. We also demonstrated that the new prodrugs are activated in vivo in Nemeth-Kellner lymphoma (NK/Ly) murine model.
CRIS-Team WoS Importer:2021-04-16

An Enhanced Magnetomotive Ultrasound Algorithm to Quantitatively Estimate the Concentration of Iron-Oxide Nanoparticles in Perfused Tissue for Magnetic Drug Targeting - Fink, Michael; Rupitsch, Stefan; Lyer, Stefan; Alexiou, Christoph; Ermert, Helmut (Proceedings IEEE IUS 2019, 2019)

A New Immortalized Human Lacrimal Gland Cell Line - Gleixner, Sophie; Zahn, Ingrid; Dietrich, Jana; Singh, Swati; Drobny, Alice; Schneider, Yanni; Schwendner, Raphael; Socher, Eileen; Blavet, Nicolas; Bräuer, Lars; Gostian, Antoniu-Oreste; Balk, Matthias; et al. (Cells, 2024)
The lacrimal gland is crucial for maintaining ocular health by producing the aqueous component of the tear film, which hydrates and nourishes the ocular surface. Decreased production of this component results in dry eye disease, a condition affecting over 250 million people worldwide. However, the scarcity of primary human material for studying its underlying mechanisms and the absence of a cell model for human lacrimal gland epithelial cells present significant challenges. Here, we describe the generation of immortalized human lacrimal gland cell lines through the introduction of an SV40 antigen. We successfully isolated and characterized three cell clones from a female lacrimal gland donor, confirming their epithelial identity through genomic and protein analyses, including PCR, RNAseq, immunofluorescence and cultivation in a 3D spheroid model. Our findings represent a significant advancement, providing improved accessibility to investigate the molecular pathogenesis mechanisms of dry eye disease and potential therapeutic interventions. We identified the expression of typical epithelial cell marker genes and demonstrated the cells’ capability to form 2D cell sheets and 3D spheroids. This establishment of immortalized human lacrimal gland cells with epithelial characteristics holds promise for future comprehensive studies, contributing to a deeper understanding of dry eye disease and its cellular mechanisms.<br
Keywords: lacrimal gland; epithelial cells; immortalized; cell line; dry eye; tears; tear secretion

A New Statistical Approach for the Evaluation of Gap-prepulse Inhibition of the Acoustic Startle Reflex (GPIAS) for Tinnitus Assessment - Schilling, Achim; Krauß, Patrick; Gerum, Richard; Metzner, Claus; Tziridis, Konstantin; Schulze, Holger (Frontiers in Behavioral Neuroscience, 2017)
Background: An increasingly used behavioral paradigm for the objective assessment of a possible tinnitus percept in animal models has been proposed by Turner and coworkers in 2006. It is based on gap-prepulse inhibition (PPI) of the acoustic startle reflex (ASR) and usually referred to as GPIAS. As it does not require conditioning it became the method of choice to study neuroplastic phenomena associated with the development of tinnitus.Objective:It is still controversial if GPIAS is really appropriate for tinnitus screening, as the hypothesis that a tinnitus percept impairs the gap detection ability ("filling-in interpretation" is still questioned. Furthermore, a wide range of criteria for positive tinnitus detection in GPIAS have been used across different laboratories and there still is no consensus on a best practice for statistical evaluation of GPIAS results. Current approaches are often based on simple averaging of measured PPI values and comparisons on a population level without the possibility to perform valid statistics on the level of the single animal.Methods:A total number of 32 animals were measured using the standard GPIAS paradigm with varying number of measurement repetitions. Based on this data further statistical considerations were performed.Results:We here present a new statistical approach to overcome the methodological limitations of GPIAS. In a first step we show that ASR amplitudes are not normally distributed. Next we estimate the distribution of the measured PPI values by exploiting the full combinatorial power of all measured ASR amplitudes. We demonstrate that the amplitude ratios (1-PPI) are approximately lognormally distributed, allowing for parametrical testing of the logarithmized values and present a new statistical approach allowing for a valid and reliable statistical assessment of PPI changes in GPIAS.Conclusion:Based on our statistical approach we recommend using a constant criterion, which does not systematically depend on the number of measurement repetitions, in order to divide animals into a tinnitus and a non-tinnitus group. In particular, we recommend using a constant threshold based on the effect size as criterion, as the effect size, in contrast to thep-value, does not systematically depend on the number of measurement repetitions.
EVALuna2:33208

An in silico model of the capturing of magnetic nanoparticles in tumour spheroids in the presence of flow - Wirthl, Barbara; Janko, Christina; Lyer, Stefan; Schrefler, Bernhard A.; Alexiou, Christoph; Wall, Wolfgang A. (Biomedical Microdevices, 2023)
One of the main challenges in improving the efficacy of conventional chemotherapeutic drugs is that they do not reach the cancer cells at sufficiently high doses while at the same time affecting healthy tissue and causing significant side effects and suffering in cancer patients. To overcome this deficiency, magnetic nanoparticles as transporter systems have emerged as a promising approach to achieve more specific tumour targeting. Drug-loaded magnetic nanoparticles can be directed to the target tissue by applying an external magnetic field. However, the magnetic forces exerted on the nanoparticles fall off rapidly with distance, making the tumour targeting challenging, even more so in the presence of flowing blood or interstitial fluid. We therefore present a computational model of the capturing of magnetic nanoparticles in a test setup: our model includes the flow around the tumour, the magnetic forces that guide the nanoparticles, and the transport within the tumour. We show how a model for the transport of magnetic nanoparticles in an external magnetic field can be integrated with a multiphase tumour model based on the theory of porous media. Our approach based on the underlying physical mechanisms can provide crucial insights into mechanisms that cannot be studied conclusively in experimental research alone. Such a computational model enables an efficient and systematic exploration of the nanoparticle design space, first in a controlled test setup and then in more complex in vivo scenarios. As an effective tool for minimising costly trial-and-error design methods, it expedites translation into clinical practice to improve therapeutic outcomes and limit adverse effects for cancer patients.
CRIS-Team Scopus Importer:2023-12-08
Keywords: Cylindrical permanent magnet; Magnetic drug targeting; Magnetic nanoparticles; Multiphase porous media; Tumour-growth model

An Investigation of Acoustic Back-Coupling in Human Phonation on a Synthetic Larynx Model - Näger, Christoph; Kniesburges, Stefan; Tur, Bogac; Schoder, Stefan; Becker, Stefan (Bioengineering, 2023)
In the human phonation process, acoustic standing waves in the vocal tract can influence the fluid flow through the glottis as well as vocal fold oscillation. To investigate the amount of acoustic back-coupling, the supraglottal flow field has been recorded via high-speed particle image velocimetry (PIV) in a synthetic larynx model for several configurations with different vocal tract lengths. Based on the obtained velocity fields, acoustic source terms were computed. Additionally, the sound radiation into the far field was recorded via microphone measurements and the vocal fold oscillation via high-speed camera recordings. The PIV measurements revealed that near a vocal tract resonance frequency fR, the vocal fold oscillation frequency fo (and therefore also the flow field’s fundamental frequency) jumps onto fR. This is accompanied by a substantial relative increase in aeroacoustic sound generation efficiency. Furthermore, the measurements show that fo-fR-coupling increases vocal efficiency, signal-to-noise ratio, harmonics-to-noise ratio and cepstral peak prominence. At the same time, the glottal volume flow needed for stable vocal fold oscillation decreases strongly. All of this results in an improved voice quality and phonation efficiency so that a person phonating with fo-fR-coupling can phonate longer and with better voice quality.<br
Keywords: human phonation; source–filter interaction; particle image velocimetry; synthetic larynx model; transmission line model; aeroacoustic source computation

An LMMSE-based Estimation of Temporal Response Function in Auditory Attention Decoding - Kuruvila, Ivine; Fischer, Eghart; Hoppe, Ulrich (Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBS, 2020)
One of the remarkable abilities of humans is to focus the attention on a certain speaker in a multi-speaker environment that is known as the cocktail party effect. How the human brain solves this non-trivial task is a challenge that the scientific community has not yet found answers to. In recent years, progress has been made thanks to the development of system identification method based on least-squares (LS) that maps the variations between the cortical signals of a listener and the speech signals present in an auditory scene. Results from numerous two-speaker experiments simulating the cocktail party effect have shown that the auditory attention could be inferred from electroencephalography (EEG) using the LS method. It has been suggested that these methods have the potential to be integrated into hearing aids for algorithmic control. However, a major challenge remains using LS methods such that a large number of scalp EEG electrodes are required in order to get a reliable estimate of the attention. Here we present a new system identification method based on linear minimum mean squared error (LMMSE) that could estimate the attention with the help of two electrodes: one for the true signal estimation and other for the noise estimation. The algorithm is tested using EEG signals collected from ten subjects and its performance is compared against the state-of-the-art LS algorithm.
CRIS-Team Scopus Importer:2020-09-25

A Novel and Simple Technique to Reduce the Rate of Pharyngocutaneous Fistula Formation Following a Total Laryngectomy - our Initial Results - Poutoglidis, Alexandros; Forozidou, Evropi; Fyrmpas, Georgios; Mantsopoulos, Konstantinos; Paraskevas, George K.; Lazaridis, Nikolaos; Savvakis, Stavros; Karamitsou, Paraskevi (Indian Journal of Otolaryngology and Head and Neck Surgery, 2023)
Objective: Pharyngocutaneous fistula (PCF) is a common and often devastating complication of total laryngectomy. Patients undergoing a total laryngectomy need enhancement of the neopharynx to reduce the risk of PCF formation. Our study aimed to evaluate the formation of a PCF following a total laryngectomy in patients that underwent a modified closure technique of their neopharynx. This technique included the recruitment of a flap of the muscular division of the pretracheal fascia that invests the strap muscles as a protective blanket. We called this surgical technique the ‘curtain call’. Methods: We conducted a retrospective study for patients who underwent a total laryngectomy in our department between May 2022 and May 2023. Results: Twelve patients were identified. Our results demonstrated that the recruitment of this modified closure technique to cover the neopharynx resulted in a very low rate of postoperative PCF formation (8.3%). Conclusion: The ‘curtain call’ technique is an excellent method to support the neopharynx with extremely low rates of postoperative chronic dysphagia and with no evidence of impairing the development of esophageal speech. It could sometimes substitute much more time-consuming techniques like major pectoralis flap and supraclavicular flap.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Laryngeal cancer; Pharyngocutaneous Fistula; Salvage Laryngectomy; Surgical Technique; Total Laryngectomy

A novel human artery model to assess the magnetic accumulation of SPIONs under flow conditions - Janikowska, Agata; Matuszak, Jasmin; Lyer, Stefan; Schreiber, Eveline; Unterweger, Harald; Zaloga, Jan; Groll, Juergen; Alexiou, Christoph; Cicha, Iwona (Scientific Reports, 2017)
Magnetic targeting utilises the properties of superparamagnetic iron oxide nanoparticles (SPIONs) to accumulate particles in specified vasculature regions under an external magnetic field. As the behaviour of circulating particles varies depending on nanoparticle characteristics, magnetic field strength and flow dynamics, we established an improved ex vivo model in order to estimate the magnetic capture of SPIONs in physiological-like settings. We describe here a new, easy to handle ex vivo model of human umbilical artery. Using this model, the magnetic targeting of different types of SPIONs under various external magnetic field gradients and flow conditions was investigated by atomic emission spectroscopy and histology. Among tested particles, SPION-1 with lauric acid shell had the largest capacity to accumulate at the specific artery segment. SPION-2 (lauric acid/albumin-coated) were also successfully targeted, although the observed peak in the iron content under the tip of the magnet was smaller than for SPION-1. In contrast, we did not achieve magnetic accumulation of dextran-coated SPION-3. Taken together, the umbilical artery model constitutes a time- and cost-efficient, 3R-compliant tool to assess magnetic targeting of SPIONs under flow. Our results further imply the possibility of an efficient in vivo targeting of certain types of SPIONs to superficial arteries.
EVALuna2:33177

A Novel Magnetic Field Device for Inducing Hyperthermia Using Magnetic Nanoparticles - Dürr, Stephan; Schmidt, Oliver; Janko, Christina; Kraemer, H P; Tripal, Philipp; Eiermann, F; Tietze, R; Lyer, Stefan; Alexiou, Christoph (Biomedizinische Technik, 2013)
A new alternating current (AC) magnetic field applicator was designed to induce hyperthermia in an animal tumour model using superparamagnetic iron oxidenanoparticles (SPION). First experiments on phantoms including different concentrations of SPION were conducted.The results confirmed that the new AC magnetic field applicator could heat-p SPION. This proofs the capability to induce hyperthermia by SPION, dependent on the concentration
EVALuna2:19922
Keywords: Magnetic drug targeting; nanoparticles; alternating current magnetic field; hyperthermia

A novel nasopharyngeal stent for the treatment of obstructive sleep apnea: a case series of nasopharyngeal stenting versus continuous positive airway pressure - Traxdorf, Maximilian; Hartl, Michael; Angerer, Florian; Bohr, Christopher; Grundtner, Philipp; Iro, Heinrich (European Archives of Oto-Rhino-Laryngology, 2016)
The objective of the study was to investigate the first-night treatment success of a nasopharyngeal stent compared to standard nCPAP-titration. This is a case series and a single-center study. Eight participants (n = 8) were selected with untreated obstructive sleep apnea with a prestudy AHI >=10. A newly developed nasopharyngeal stent was tested individually versus standard nCPAP-titration. Cardiorespiratory polysomnography was performed on two consecutive nights (random order: stent, nCPAP). The AHI, the number of obstructive apneas and hypopneas, the mean oxygen saturation, and the minimum oxygen saturation were compared before and after using the nasopharyngeal stent or standard nCPAP. The AHI value before treatment (AHIpre) was 31.1 ± 12.0 (mean ± standard deviation). After inserting the AlaxoStent, the mean AHIstent was 19 ± 12.0 compared to mean AHInCPAP 8.2 ± 11.9 with standard nCPAP-titration. Both nasopharyngeal stenting and nCPAP-titration could reduce the mean number of obstructive apneas by >94 %. Compared to responder rates of classic surgical interventions like uvulopalatopharyngoplasty or multi-level surgery, the nasopharyngeal stent seems to give a comparable responder rate of 50 %. There were no complications associated with the use of the stent and it was well tolerated by all subjects. Nasopharyngeal stenting widens the range of non-invasive mechanical treatment and seems to be an effective mechanical therapeutic alternative to surgery in nCPAP non-compliant patients with OSA. Careful selection of the patient population is a prerequisite of treatment and therefore it should be reserved for individual cases only.
EVALuna2:20017

A Novel Setup for the Controlled Adduction of Vocal Folds - Gedeon, Dominik; Rupitsch, Stefan; Lerch, Reinhard; Luegmair, Georg; Döllinger, Michael (Mechatronics 2012 - The 13th Mechatronics Forum International Conference, 2012)

Anticancer Aminoferrocene Derivatives Inducing Production of Mitochondrial Reactive Oxygen Species - Özkan, Hülya Gizem; Thakor, Vanrajsinh; Xu, Honggui; Bila, Galyna; Bilyy, Rostyslav; Bida, Daria; Boettcher, Martin; Mougiakakos, Dimitrios; Tietze, Rainer; Mokhir, Andriy (Chemistry - A European Journal, 2022)
Elevated levels of reactive oxygen species (ROS) and deficient mitochondria are two weak points of cancer cells. Their simultaneous targeting is a valid therapeutic strategy to design highly potent anticancer drugs. The remaining challenge is to limit the drug effects to cancer cells without affecting normal ones. We have previously developed three aminoferrocene (AF)-based derivatives, which are activated in the presence of elevated levels of ROS present in cancer cells with formation of electron-rich compounds able to generate ROS and reduce mitochondrial membrane potential (MMP). All of them exhibit important drawbacks including either low efficacy or high unspecific toxicity that prevents their application in vivo up to date. Herein we describe unusual AF-derivatives lacking these drawbacks. These compounds act via an alternative mechanism: they are chemically stable in the presence of ROS, generate mitochondrial ROS in cancer cells, but not normal cells and exhibit anticancer effect in vivo.
CRIS-Team WoS Importer:2022-04-29

Anticancer Effect of an Electronically Coupled Oligoferrocene - Zeh, Gina; Haines, Philipp; Miehlich, Matthias; Kienz, Torben; Neidlinger, Andreas; Friedrich, Ralf P.; Alexiou, Christoph; Hampel, Frank; Guldi, Dirk Michael; Meyer, Karsten; Schatz, Jürgen; Heinze, Katja; et al. (Organometallics, 2020)
The mode of anticancer activity of simple ferrocenes often relies on their intracellular oxidation with the formation of cytotoxic ferrocenium species. The former compounds should be considered as prodrugs and derived from them ferroceniums as drugs. The drugs are 17e- organometallic species. Therefore, they are chemically unstable and decompose with formation of free cyclopentadienyl ligands (which are further transformed to more stable species) and iron ions. The short lifetime of ferrocenium drugs limits the anticancer effect of ferrocene prodrugs. In this paper we prepared a series of acylated aminoferrocene monomers, dimers, and higher oligonuclear complexes FcN (where N = 1-4). Drugs [FcN]+ derived from FcN (N > 1) are more stable than monomeric [Fc]+, provided that the ferrocene units are electronically coupled. Correspondingly, we expected that FcN species will be more potent anticancer agents in comparison to the related monomers. These assumptions were confirmed for dimer 10. We observed that this prodrug has sufficient solubility in aqueous solution (100 μM) and favorable lipophilicity (log P = 2.2 ± 0.2). Ferrocene units in 10 are efficiently electronically coupled via a -C(═O)NH- linker according to cyclic voltammetry, differential pulse voltammetry, and spectroelectrochemistry. We observed that 10 is the most efficient catalyst of the production of reactive oxygen species (ROS) and the most active anticancer agent in comparison to control monomers and their mixtures.
CRIS-Team Scopus Importer:2020-09-14

Applicability of shear wave elastography of the major salivary glands: values in healthy patients and effects of gender, smoking and pre-compression - Mantsopoulos, Konstantinos; Klintworth, Nils; Iro, Heinrich; Bozzatoy, Alessandro (Ultrasound in Medicine and Biology, 2015)
Our aim in this study was to determine normal shear wave elastography (SWE) values for the parenchyma of the major salivary glands and to evaluate the influences of gender, smoking, side and type of gland and varying amounts of ultrasound probe pressure on SWE values. Twenty-five consecutive healthy patients were examined with ultrasound. SWE velocities were measured with acoustic radiation force imaging in the hilum and central region of both glands with "normal" and very low pressure. Mean SWE velocities were 1.854 m/s for the parotid gland and 1.932 m/s for the submandibular gland. No statistically significant differences were detected between males and females, smokers and non-smokers, parotid and submandibular gland and left and right sides. Greater pre-compression with the ultrasound probe resulted in a statistically significant increase in the SWE values of both salivary glands (p < 0.000). The degree of pre-compression by the ultrasound transducer should be standardized, so that the reliability and reproducibility of this innovative method can be improved.
EVALuna2:19987

A Print-and-Fuse Strategy for Sacrificial Filaments Enables Biomimetically Structured Perfusable Microvascular Networks with Functional Endothelium Inside 3D Hydrogels - Ryma, Matthias; Genc, Hatice; Nadernezhad, Ali; Paulus, Ilona; Schneidereit, Dominik; Friedrich, Oliver; Andelovic, Kristina; Lyer, Stefan; Alexiou, Christoph; Cicha, Iwona; Groll, Juergen (Advanced Materials, 2022)
A facile and flexible approach for the integration of biomimetically branched microvasculature within bulk hydrogels is presented. For this, sacrificial scaffolds of thermoresponsive poly(2-cyclopropyl-2-oxazoline) (PcycloPrOx) are created using melt electrowriting (MEW) in an optimized and predictable way and subsequently placed into a customized bioreactor system, which is then filled with a hydrogel precursor solution. The aqueous environment above the lower critical solution temperature (LCST) of PcycloPrOx at 25 degrees C swells the polymer without dissolving it, resulting in fusion of filaments that are deposited onto each other (print-and-fuse approach). Accordingly, an adequate printing pathway design results in generating physiological-like branchings and channel volumes that approximate Murray's law in the geometrical ratio between parent and daughter vessels. After gel formation, a temperature decrease below the LCST produces interconnected microchannels with distinct inlet and outlet regions. Initial placement of the sacrificial scaffolds in the bioreactors in a pre-defined manner directly yields perfusable structures via leakage-free fluid connections in a reproducible one-step procedure. Using this approach, rapid formation of a tight and biologically functional endothelial layer, as assessed not only through fluorescent dye diffusion, but also by tumor necrosis factor alpha (TNF-alpha) stimulation, is obtained within three days.
CRIS-Team WoS Importer:2022-06-17

A quasi-static quantitative ultrasound elastography algorithm using optical flow - Lamprecht, Raphael; Scheible, Florian; Semmler, Marion; Sutor, Alexander (Sensors, 2021)
Ultrasound elastography is a constantly developing imaging technique which is capable of displaying the elastic properties of tissue. The measured characteristics could help to refine physiological tissue models, but also indicate pathological changes. Therefore, elastography data give valuable insights into tissue properties. This paper presents an algorithm that measures the spatially resolved Young’s modulus of inhomogeneous gelatin phantoms using a CINE sequence of a quasi-static compression and a load cell measuring the compressing force. An optical flow algorithm evaluates the resulting images, the stresses and strains are computed, and, conclusively, the Young’s modulus and the Poisson’s ratio are calculated. The whole algorithm and its results are evaluated by a performance descriptor, which determines the subsequent calculation and gives the user a trustability index of the modulus estimation. The algorithm shows a good match between the mechanically measured modulus and the elastography result—more precisely, the relative error of the Young’s modulus estimation with a maximum error 35%. Therefore, this study presents a new algorithm that is capable of measuring the elastic properties of gelatin specimens in a quantitative way using only the image data. Further, the computation is monitored and evaluated by a performance descriptor, which measures the trustability of the results.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Elastography; Phantom study; Quantitative; Quasi-static; Ultrasound

A rare diagnosis of unilateral neck pain Eine seltene Diagnose beim einseitigen Halsschmerz - Shabli, Sami; Stuermer, Sophie; Klussmann, Jens Peter; Gostian, Antoniu-Oreste; Grosheva, Maria (Laryngo-Rhino-Otologie, 2020)
CRIS-Team Scopus Importer:2020-07-10

Are source-filter interactions detectable in classical singing during vowel glides? - Echternach, Matthias; Herbst, Christian T.; Köberlein, Marie; Story, Brad; Döllinger, Michael; Gellrich, Donata (Journal of the Acoustical Society of America, 2021)
In recent studies, it has been assumed that vocal tract formants (Fn) and the voice source could interact. However, there are only few studies analyzing this assumption in vivo. Here, the vowel transition /i/-/a/-/u/-/i/ of 12 professional classical singers (6 females, 6 males) when phonating on the pitch D4 [fundamental frequency (ƒo) ca. 294 Hz] were analyzed using transnasal high speed videoendoscopy (20.000 fps), electroglottography (EGG), and audio recordings. Fn data were calculated using a cepstral method. Source-filter interaction candidates (SFICs) were determined by (a) algorithmic detection of major intersections of Fn/nƒo and (b) perceptual assessment of the EGG signal. Although the open quotient showed some increase for the /i-a/ and /u-i/ transitions, there were no clear effects at the expected Fn/nƒo intersections. In contrast, ƒo adjustments and changes in the phonovibrogram occurred at perceptually derived SFICs, suggesting level-two interactions. In some cases, these were constituted by intersections between higher nƒo and Fn. The presented data partially corroborates that vowel transitions may result in level-two interactions also in professional singers. However, the lack of systematically detectable effects suggests either the absence of a strong interaction or existence of confounding factors, which may potentially counterbalance the level-two-interactions.
CRIS-Team Scopus Importer:2021-07-09

A Simple and Low-Cost Technique to Measure the Magnetic Susceptibility of Ferrofluids - Thalmayer, Angelika; Xiao, Keyu; Lübke, Maximilian; Borin, Dmitry; Odenbach, Stefan; Unterweger, Harald; Helmreich, Klaus; Fischer, Georg (IEEE Sensors, 2023)

A single latent channel is sufficient for biomedical glottis segmentation - Kist, Andreas; Breininger, Katharina; Dörrich, Marion; Dürr, Stephan; Schützenberger, Anne; Semmler, Marion (Scientific Reports, 2022)
Glottis segmentation is a crucial step to quantify endoscopic footage in laryngeal high-speed videoendoscopy. Recent advances in deep neural networks for glottis segmentation allow for a fully automatic workflow. However, exact knowledge of integral parts of these deep segmentation networks remains unknown, and understanding the inner workings is crucial for acceptance in clinical practice. Here, we show that a single latent channel as a bottleneck layer is sufficient for glottal area segmentation using systematic ablations. We further demonstrate that the latent space is an abstraction of the glottal area segmentation relying on three spatially defined pixel subtypes allowing for a transparent interpretation. We further provide evidence that the latent space is highly correlated with the glottal area waveform, can be encoded with four bits, and decoded using lean decoders while maintaining a high reconstruction accuracy. Our findings suggest that glottis segmentation is a task that can be highly optimized to gain very efficient and explainable deep neural networks, important for application in the clinic. In the future, we believe that online deep learning-assisted monitoring is a game-changer in laryngeal examinations.
CRIS-Team Scopus Importer:2022-09-02

Assessing Cytotoxicity, Endotoxicity, and Blood Compatibility of Nanoscale Iron Oxide Magnetosomes for Biomedical Applications - Mickoleit, Frank; Pfister, Felix; Friedrich, Bernhard; Markert, Simon; Kerpes, Andrea; Janko, Christina; Lyer, Stefan; Alexiou, Christoph; Schüler, Dirk; Tietze, Rainer (ACS Applied Nano Materials, 2024)
Magnetosomes are biogenic magnetic nanoparticles with unique material properties, such as high crystallinity and strong magnetization as well as uniform and tunable shapes and sizes. In particular, the ability to genetically modify their enveloping membrane could render isolated magnetosomes as versatile tools for a variety of potential applications in the biomedical field. However, the biocompatibility of the bacterially produced particles has so far not been fully been assessed. In this study, different biocompatibility and toxicity factors of magnetosomes isolated from the model organism Magnetospirillum gryphiswaldense were investigated and tested with THP-1, Jurkat cells, and primary human-derived material such as peripheral blood mononuclear cells (PBMCs). The obtained data demonstrate generally good biocompatibility for all tested magnetosome concentrations as well as high blood compatibility. Only slight but not significant complement activation was observed, with no indications for plasma coagulation or hemolysis. However, the presence of lipopolysaccharides originating from the Gram-negative cell wall of M. gryphiswaldense caused activation of PBMCs expressed as significant cytokine release. Thus, this endotoxicity represents an issue for possible in vivo applications, which needs to be addressed in future studies. Nevertheless, the results show that, overall, magnetosomes have high potential for different (bio)medical applications and are already well-suited for the fields of in vitro diagnostics.
CRIS-Team Scopus Importer:2024-01-26
Keywords: biocompatibility; biogenic magnetic nanoparticles; blood compatibility; endotoxicity; magnetosomes

Assessing quality of life in patients after partial laryngectomy - Hebel, Florian; Mantsopoulos, K.; Bohr, Christopher (Hippokratia, 2014)
In the present prospective cross-sectional clinical study, correlations between global quality of life (QoL) and coping strategies were examined in patients who had undergone partial laryngeal resection for T1-T2 laryngeal cancer. Correlations between point scores in the "Trier Illness Coping Scales" and SF-36 were analysed in 71 patients (65 males, 6 females, mean age 62 years) at routine follow-up visits by means of linear regression and Pearson's R.The most important coping strategy was "threat control", followed by "search for social integration". Greater expression of "rumination" was statistically correlated with poorer quality of life, and patients with more advanced disease were more inclined to seek social integration.Coping strategies exert substantial influence on the quality of life of cancer survivors. Disease- or treatment-related day-to-day problems and anxieties about the oncological outcome have a greater influence on the quality of life of laryngeal cancer survivors than do voice changes. This finding should be taken into account in survivorship care planning.
EVALuna2:19997

Association between lateral wall electrode array insertion parameters and audiological outcomes in bilateral cochlear implantation - Thimsen, Vivian; Mantsopoulos, Konstantinos; Liebscher, Tim; Taha, Lava; Eisenhut, Felix; Iro, Heinrich; Hoppe, Ulrich; Hornung, Joachim (European Archives of Oto-Rhino-Laryngology, 2022)
Purpose The aims of this study were to compare speech recognition at different postoperative times for both ears in bilaterally implanted patients and to assess the influence of the time of deafness, frequency-to-place mismatch, angular insertion depth (AID) and angular separation between neighbouring electrode contacts on audiometric outcomes. Methods This study was performed at an academic tertiary referral centre. A total of 19 adult patients (6 men, 13 women), who received sequential bilateral implantation with lateral wall electrode arrays, were analysed in retrospective. Statistical analysis was performed using two-sided t test, Wilcoxon test, median test, and Spearman's correlation. Results Postlingually deafened patients (deafness after the age of 10) had a significantly better speech perception (WRS65[CI]) than the perilingually deafened subjects (deafness at the age of 1-10 years) (p < 0.001). Comparison of cochlear duct length between peri- and postlingually deafened subjects showed a slightly significantly smaller cochleae in perilingual patients (p = 0.045). No association between frequency-to-place mismatch as well as angular separation and speech perception could be detected. There was even no significant difference between the both ears in the intraindividual comparison, even if insertion parameters differed. Conclusion The exact electrode position seems to have less influence on the speech comprehension of CI patients than already established parameters as preoperative speech recognition or duration of deafness.
CRIS-Team WoS Importer:2022-12-16

A statistical method for analyzing and comparing spatiotemporal cortical activation patterns - Krauß, Patrick; Metzner, Claus; Schilling, Achim; Tziridis, Konstantin; Traxdorf, Maximilian; Wollbrink, Andreas; Rampp, Stefan; Pantev, Christo; Schulze, Holger (Scientific Reports, 2018)
Information in the cortex is encoded in spatiotemporal patterns of neuronal activity, but the exact nature of that code still remains elusive. While onset responses to simple stimuli are associated with specific loci in cortical sensory maps, it is completely unclear how the information about a sustained stimulus is encoded that is perceived for minutes or even longer, when discharge rates have decayed back to spontaneous levels. Using a newly developed statistical approach (multidimensional cluster statistics (MCS)) that allows for a comparison of clusters of data points in n-dimensional space, we here demonstrate that the information about long-lasting stimuli is encoded in the ongoing spatiotemporal activity patterns in sensory cortex. We successfully apply MCS to multichannel local field potential recordings in different rodent models and sensory modalities, as well as to human MEG and EEG data, demonstrating its universal applicability. MCS thus indicates novel ways for the development of powerful read-out algorithms of spatiotemporal brain activity that may be implemented in innovative brain-computer interfaces (BCI).
EVALuna2:35749

A time-resolved PIV-based methodology to analyse the acoustics of human phonation - Lodermeyer, Alexander; Mohamadi Bagheri, Eman; Näger, Christoph; Nusser, Katrin; Becker, Stefan; Döllinger, Michael; Kniesburges, Stefan (13th International Symposium on Particle Image Velocimetry – ISPIV 2019, 2019)

Attentional modulation of the cortical contribution to the frequency-following response evoked by continuous speech - Schüller, Alina; Schilling, Achim; Krauß, Patrick; Rampp, Stefan; Reichenbach, Tobias (The Journal of Neuroscience, 2023)
Selective attention to one of several competing speakers is required for comprehending a target speaker amongst other voices and for successful communication with them. It moreover has been found to involve the neural tracking of low-frequency speech rhythms in the auditory cortex. Effects of selective attention have also been found in subcortical neural activities, in particular regarding the high-frequency neural response at the fundamental frequency of speech, the speech-FFR. Recent investigations have, however, shown that the speech-FFR contains cortical contributions as well. It remains unclear whether these are also modulated by selective attention. Here we employed magnetoencephalography (MEG) to assess the attentional modulation of the cortical contributions to the speech-FFR. We presented both male and female participants with two competing speech signals and analyzed the cortical responses during attentional switching between the two speakers. Our findings revealed robust attentional modulation of the cortical contribution to the speech-FFR: the neural responses were higher when the speaker was attended than when they were ignored. We also found that, regardless of attention, a voice with a lower fundamental frequency elicited a larger cortical contribution to the speech-FFR than a voice with a higher fundamental frequency. Our results show that the attentional modulation of the speech-FFR does not only occur subcortically but extends to the auditory cortex as well.
CRIS-Team Scopus Importer:2023-11-17

Atypical Fibroxanthoma - Histological Diagnosis, Immunohistochemical Markers and Concepts of Therapy - Koch, Michael; Freundl, Anne J.; Agaimy, Abbas; Kiesewetter, Franklin; Kuenzel, Julian; Cicha, Iwona; Alexiou, Christoph (Anticancer Research, 2015)
Atypical fibroxanthoma (AFX) is an uncommon, rapidly growing cutaneous neoplasm of uncertain histogenesis. Thus far, there are no guidelines for diagnosis and therapy of this tumor.We included 18 patients with 21 AFX, and 2,912 patients with a total of 2,939 AFX cited in the literature between 1962 and 2014.In our cohort, excision with safety margin was performed in 100% of primary tumors. Local recurrences were observed in 25% of primary tumors and parotid metastases in 5%. Ten-year disease-specific survival was 100%. The literature research yielded 280 relevant publications. Over 90% of the reported cases were negative for cytokeratins, S100, desmin and human melanoma black 45 (HMB-45). Recurrent AFX was reported in 7.6% and metastasizing AFX in 2.75% cases. No significant differences in the recurrence and survival rates following wide local excision versus Mohs microsurgery were observed. Twenty-year disease-specific survival rate was 97.8%.A well-selected panel of immunohistochemical markers is necessary to establish AFX diagnosis with sufficient certainty. Adequately treated, AFX has an excellent prognosis, but long-term follow-up is recommended due to the potential for aggressive behavior.
EVALuna2:6738

Audiometry-Based Screening Procedure for Cochlear Implant Candidacy - Hoppe, Ulrich; Hast, Anne; Hocke, Thomas (Otology & Neurotology, 2015)
This study defines a screening procedure for cochlear implant (CI) candidacy in hearing aid users by using simple audiometric measures.Within this retrospective study, hearing aid performance and audiometric measures in 185 subjects (318 ears) were analyzed. By means of a linear Naive Bayes classifier, the pure-tone average and the maximum monosyllabic score (PB(max)) were used to predict the aided monosyllabic word score and CI candidacy.The two parameters PB(max) and four-frequency hearing threshold average can be used to predict speech perception with hearing aids with reasonable accuracy for screening purposes. The classification has a sensitivity of 87% and a specificity of 91%. The classification can be represented by a simple linear formula.CI candidacy can be predicted based on commonly used audiometric measures.Cochlear implant candidacy may be considered if the difference between the average pure-tone threshold (in decibels) and PBmax (in percent) exceeds 8.
EVALuna2:19998

Auditory group therapy in adult cochlear implant rehabilitation - Glaubitz, Cynthia; Lehmann, E. K.; Weber, L.; Kulke, A. -M.; Hoppe, Ulrich (HNO, 2019)
BACKGROUND: Auditory training is an established intervention in adult cochlear implant (CI) aural rehabilitation. In most cases, training is implemented in an individual therapy setting. Increasing patient numbers and the associated time-economic and cost-related demands as well as psychosocial and communicative aspects support the use of aural group interventions. OBJECTIVES: This study aimed 1) to describe concepts and contents of group interventions for adult CI users and 2) to present results of a questionnaire-based evaluation. METHODS: Group interventions have been offered at the CI Centre Erlangen CICERO for several years. In Auditory Training Groups, exercises have priority, while Thematic Group Workshops focus on psychosocial aspects and provide information for the participants. The Auditory Training Groups were evaluated based on a patient questionnaire. Additionally, the reliability of the questionnaire was analyzed. RESULTS: The median overall satisfaction of CI users participating in Auditory Training Groups was rated as good. Training of speech perception in noise as well as communicative exchange are of great importance for CI users. They rated the therapeutic design as very good to good. Reliability analysis showed significant positive intercorrelations of the questionnaire items. CONCLUSION: Group interventions are well accepted by CI users and represent a useful complement to individual therapy during the rehabilitation process. As group interventions place special demands on patients and therapists, structured and well-proven concepts should be used in practice.
EVALuna2:209999

Auswirkungen der SARS-CoV‑2-Pandemie auf die universitäre Hals-Nasen-Ohren-Heilkunde im Bereich der Forschung, Lehre und Weiterbildung - Stöver, T.; Dazert, S.; Plontke, S. K.; Kramer, S.; Ambrosch, P.; Arens, C.; Betz, C.; Beutner, D.; Bohr, C.; Bruchhage, K. L.; Canis, M.; Dietz, A.; et al. (HNO, 2021)
Background: From spring 2020, SARS-CoV‑2 began to spread worldwide, with what is now known as the first wave of the pandemic, starting in March 2020. This resulted in restructuring and shift of resources at many hospitals. The aim of our work was to detect the effects of the pandemic on the german Oto-Rhino-Laryngology (ORL) university hospitals in terms of research, student teaching and further specialist training. Material and methods: The chairmen of the 39 ORL university hospitals in Germany were asked about the effects of the pandemic on research, student teaching and ORL specialist training (residency) in the period from March to April 2020 using a structured online survey. Results: All 39 chairmen took part in the survey. Of these, 74.4% (29/39) stated that their research activities had deteriorated as a result of the pandemic. In 61.5% (24/39) pandemic-related research issues were addressed. All hospitals reported a restriction for in-house teaching and 97.5% (38/39) introduced new digital teaching methods. During the observation period, 74.4% of the chairmen did not see ORL specialist training (residency)at risk. Conclusion: Our results provide an insight into the heterogeneous effects of the pandemic. The fast processing of pandemic-related research topics and the introduction of innovative digital concepts for student teaching impressively demonstrates the great innovative potential and the ability of the ORL university hospitals to react quickly in order to maintain their tasks in research, student teaching and ORL specialist training in the best possible way even during the pandemic.
CRIS-Team Scopus Importer:2021-02-05
Keywords: COVID-19; ORL; Otorhinolaryngology; Research; Residency; SARS-CoV‑2 pandemic; Specialist training; Teaching; University hospitals

Auswirkungen der SARS-CoV-2-Pandemie auf die universitäre Hals-Nasen-Ohrenheilkunde im Bereich der Krankenversorgung - Stöver, T.; Dazert, S.; Hoffmann, T. K.; Plontke, S. K.; Ambrosch, P.; Arens, C.; Betz, C.; Beutner, D.; Bohr, C.; Bruchhage, K. L.; Canis, M.; Dietz, A.; et al. (Laryngo-Rhino-Otologie, 2020)
Introduction Since December 2019, the SARS-CoV-2 virus has been rapidly spreading worldwide. In Germany, an exponential increase in the number of infections was registered at the beginning of March 2020 and led to a call of the Ministry of Health to create more capacity for intensive medical treatment in hospitals. The aim of the present study was to determine the effects of the SARS-CoV-2 pandemic on Oto-Rhino-Laryngology (ORL) university hospitals regarding patient care. Materials and methods An online survey was sent out to all chairmen of the 39 ORL university hospitals in Germany. The answers to the questions referred to the defined period from March 15 thto April 15 th2020 and were carried out using the online survey tool SurveyMonkey. 87 questions focused on general information, health care, and structural effects in the respective institution. Results All chairmen of the 39 university hospitals in Germany participated in the survey. The collected data prove the considerable impact on organizational, structural and medical aspects of patient care. For example, the surveyed clinics reported a decrease in outpatient cases by 73.8% to 26.2±14.2% and in surgical treatments by 65.9% to 34.1±13.9%. In contrast, emergency treatment remained unchanged or even increased in 80% of the facilities and surgical treatment of emergency patients remained unchanged or even increased in more than 90%. Emergency outpatient and surgical treatment of patients was provided throughout the pandemic in all facilities. In total, about 35000 outpatients and about 12000 surgical cases were postponed. As a result of the acute structural changes, the potential danger of falling below current treatment standards was seen in individual areas of patient care. Discussion The assessment of the impact of the SARS-CoV-2 pandemic is heterogeneous. The majority of the chairmen are critically aware of the risk of falling below current medical treatment standards or guidelines. In the phase of an exponential increase in the number of infections, significant changes in treatment processes had to be accepted for understandable reasons. However, with the currently significantly reduced number of infections, falling below treatment standards and guidelines should not be allowed to remain constant and tolerated. Summary This study shows a differentiated picture with regard to the effects of the SARS-CoV-2 pandemic on outpatient, inpatient and operative patient care at the ORL university hospitals in Germany and illustrates the importance of these institutions for ensuring patient care during this critical phase.
CRIS-Team Scopus Importer:2020-09-04
Keywords: Covid-19; Oto-Rhino-Laryngology (ORL); patient care; restructuring; SARS-CoV-2 pandemic; university hospitals

Automated setup for ex vivo larynx experiments - Birk, Veronika; Döllinger, Michael; Sutor, Alexander; Berry, David A.; Gedeon, Dominik; Traxdorf, Maximilian; Wendler, Olaf; Bohr, Christopher; Kniesburges, Stefan (Journal of the Acoustical Society of America, 2017)
Ex vivo larynx experiments are limited in time due to degeneration of the laryngeal tissues. In order to acquire a significant and comparable amount of data, automatization of current manual experimental procedures is desirable. A computer controlled, electro-mechanical setup was developed for time-dependent variation of specific physiological parameters, including adduction and elongation level of the vocal folds and glottal flow. The setup offers a standardized method to induce defined forces on the laryngeal cartilages. Furthermore, phonation onset is detected automatically and the subsequent measurement procedure is automated and standardized to improve the efficiency of the experimental process. The setup was validated using four ex vivo porcine larynges, whereas each validation measurement series was executed with one separate larynx. Altogether 31 single measurements were undertaken, which can be summed up to a total experimental time of about 4 min. Vocal fold elongation and adduction lead both to an increase in fundamental frequency and subglottal pressure. Measurement procedures like applying defined subglottal pressure steps and onset-offset detection were reliably executed. The setup allows for a computer-based parameter control, which enables fast experimental execution over a wide range of laryngeal configurations. This maximizes the number of measurements and reduces personal effort compared with manual procedures.
EVALuna2:33159

Automatic Classification and Pathological Staging of Confocal Laser Endomicroscopic Images of the Vocal Cords - Vo, Kim; Jaremenko, Christian; Bohr, Christopher; Neumann, Helmut; Maier, Andreas (Bildverarbeitung für die Medizin 2017 Algorithmen Systeme Anwendungen, 2017)
Confocal laser endomicroscopy is a novel imaging technique which provides real-time in vivo examination and histological analysis of tissue during an ongoing endoscopy. We present an automatic classification system that is able to differentiate between healthy and cancerous tissue of the vocal cords. Textural as well as CNN features are encoded using Fisher vectors and vector of locally aggregated descriptors while the classification is performed using random forests and support vector machines. Two experiments are investigated following a leave-one-sequence-out cross-validation and a fixed training and test set approach. Classification rates reach up to 87.6 % and 81.5 %, respectively.
UnivIS-Import:2017-12-18:Pub.2017.tech.IMMD.IMMD5.automa_7

Automatic detection of anatomical landmarks on the knee joint using MRI data - Xue, Ning; Döllinger, Michael; Ho, Charles P.; Surowiec, Rachel K.; Schwarz, Raphael (Journal of Magnetic Resonance Imaging, 2015)
To propose a new automated learning-based scheme for locating anatomical landmarks on the knee joint using three-dimensional (3D) MR image data.This method makes use of interest points as candidates for landmarks. All candidates are evaluated by a "coarse to fine" 3D feature descriptor computed from manually placed landmarks in training datasets. The results are refined using a multi-classifier boosting system. We demonstrate our method by the detection of 24 landmarks on the knee joint of 35 subjects. To verify the robustness, the test datasets differ in contrast, resolution, patient positioning, and health condition of the knee joint. The proposed method is evaluated by measuring the distance between manually placed landmarks and automatically detected landmarks and the computational cost for detecting one landmark in a 3D dataset.The results reveal that the method is capable of localizing landmarks with a reasonable accuracy (1.64 ± 1.03 mm [mean ± standard deviation]), sensitivity (97%) and run time efficiency (4.82 s).This study suggests that the proposed method is an accurate and robust approach for the automated landmark detection in various MR datasets. The proposed method can be used as the initialization or constraint in higher level medical image processing workflows such as in kinematic description, segmentation and registration.
EVALuna2:19995

Automatic Evaluation of Voice Quality Using Text-Based Laryngograph Measurements and Prosodic Analysis - Haderlein, Tino; Schwemmle, Cornelia; Döllinger, Michael; Matoušek, Václav; Ptok, Martin; Nöth, Elmar (Computational and Mathematical Methods in Medicine, 2015)
UnivIS-Import:2015-07-08:Pub.2015.tech.IMMD.IMMD5.automa

Automatic model-based semantic registration of multimodal MRI knee data - Xue, Ning; Döllinger, Michael; Fripp, Jurgen; Ho, Charles P.; Surowiec, Rachel K.; Schwarz, Raphael (Journal of Magnetic Resonance Imaging, 2015)
To propose a robust and automated model-based semantic registration for the multimodal alignment of the knee bone and cartilage from three-dimensional (3D) MR image data.The movement of the knee joint can be semantically interpreted as a combination of movements of each bone. A semantic registration of the knee joint was implemented by separately reconstructing the rigid movements of the three bones. The proposed method was validated by registering 3D morphological MR datasets of 25 subjects into the corresponding T2 map datasets, and was compared with rigid and elastic methods using two criteria: the spatial overlap of the manually segmented cartilage and the distance between the same landmarks in the reference and target datasets.The mean Dice Similarity Coefficient (DSC) of the overlapped cartilage segmentation was increased to 0.68 ± 0.1 (mean ± SD) and the landmark distance was reduced to 1.3 ± 0.3 mm after the proposed registration method. Both metrics were statistically superior to using rigid (DSC: 0.59 ± 0.12; landmark distance: 2.1 ± 0.4 mm) and elastic (DSC: 0.64 ± 0.11; landmark distance: 1.5 ± 0.5 mm) registrations.The proposed method is an efficient and robust approach for the automated registration between morphological knee datasets and T2 MRI relaxation maps.
EVALuna2:20006

Automatic Speech Recognition Systems for the Evaluation of Voice and Speech Disorders in Head and Neck Cancer - Maier, Andreas; Haderlein, Tino; Stelzle, Florian; Nöth, Elmar; Nkenke, Emeka; Rosanowski, Frank; Schützenberger, Anne; Schuster, Maria (EURASIP Journal on Audio, Speech, and Music Processing, 2010)

Automatische Bestimmung der Verständlichkeit expressiver Sprache - Haderlein, Tino; Nöth, Elmar; Döllinger, Michael (43. Jahrestagung der Deutschen Gesellschaft für Medizinische Physik, 2012)

Automatische prosodische Stimmqualitätsbewertung aus Textaufnahmen bei großem Mikrofonabstand - Haderlein, Tino; Schützenberger, Anne; Döllinger, Michael; Nöth, Elmar (Aktuelle phoniatrisch-pädaudiologische Aspekte 2016, 2016)
UnivIS-Import:2017-12-18:Pub.2016.tech.IMMD.IMMD5.automa_4
Keywords: Sprache

BAGLS, a multihospital Benchmark for Automatic Glottis Segmentation - Gómez, Pablo; Kist, Andreas; Schlegel, Patrick; Berry, David A.; Chhetri, Dinesh K.; Dürr, Stephan; Echternach, Matthias; Johnson, Aaron M.; Kniesburges, Stefan; Kunduk, Melda; Maryn, Youri; Schützenberger, Anne; et al. (Scientific Data, 2020)
Laryngeal videoendoscopy is one of the main tools in clinical examinations for voice disorders and voice research. Using high-speed videoendoscopy, it is possible to fully capture the vocal fold oscillations, however, processing the recordings typically involves a time-consuming segmentation of the glottal area by trained experts. Even though automatic methods have been proposed and the task is particularly suited for deep learning methods, there are no public datasets and benchmarks available to compare methods and to allow training of generalizing deep learning models. In an international collaboration of researchers from seven institutions from the EU and USA, we have created BAGLS, a large, multihospital dataset of 59,250 high-speed videoendoscopy frames with individually annotated segmentation masks. The frames are based on 640 recordings of healthy and disordered subjects that were recorded with varying technical equipment by numerous clinicians. The BAGLS dataset will allow an objective comparison of glottis segmentation methods and will enable interested researchers to train their own models and compare their methods.
CRIS-Team Scopus Importer:2020-06-26

Band-Pass Filter Design by Segmentation in Frequency Domain for Detection of Epithelial Cells in Endomicroscope Images - Bier, Bastian; Mualla, Firas; Steidl, Stefan; Bohr, Christopher; Neumann, Helmut; Maier, Andreas; Hornegger, Joachim (Bildverarbeitung für die Medizin 2015 - Algorithmen, Systeme, Anwendungen, 2015)
Voice hoarseness can have various reasons, one of them is a change of the vocal fold mucus. This change can be examined with micro endoscopes. Cell detection in these images is a difficult task, due to bad image quality, caused by noise and illumination variations. In previous works, it was observed that the repetitive pattern of the cell walls cause an elliptical shape in the Fourier domain [1, 2]. A manual segmentation and back transformation of this shape results in filtered images, where the cell detection is much easier [3]. The goal of this work is to automatically segment the elliptical shape in Fourier domain. Two different approaches are developed to get a suitable band-pass filter: a thresholding and an active contour method. After the band-pass filter is applied, the achieved results are superior to the manual segmentation case.
UnivIS-Import:2018-09-11:Pub.2015.tech.IMMD.IMMD5.bandpa_5
Keywords: medizinische Bildverarbeitung; Zelldetektion

Behavioral Assessment of Zwicker Tone Percepts in Gerbils - Schilling, Achim; Tziridis, Konstantin; Schulze, Holger; Krauß, Patrick (Neuroscience, 2023)
The Zwicker tone illusion – an auditory phantom percept after hearing a notched noise stimulus – can serve as an interesting model for acute tinnitus. Recent mechanistic models suggest that the underlying neural mechanisms of both percepts are similar. To date it is not clear if animals do perceive the Zwicker tone, as up to now no behavioral paradigms are available to objectively assess the presence of this phantom percept. Here we introduce, for the first time, a modified version of the gap pre-pulse inhibition of the acoustic startle reflex (GPIAS) paradigm to test if it is possible to induce a Zwicker tone percept in our rodent model, the Mongolian gerbil. Furthermore, we developed a new aversive conditioning learning paradigm and compare the two approaches. We found a significant increase in the GPIAS effect when presenting a notched noise compared to white noise gap pre-pulse inhibition, which is consistent with the interpretation of a Zwicker tone percept in these animals. In the aversive conditioning learning paradigm, no clear effect could be observed in the discrimination performance of the tested animals. When investigating the first 33% of the correct conditioned responses, an effect of a possible Zwicker tone percept can be seen, i.e. animals show identical behavior as if a pure tone was presented, but the paradigm needs to be further improved. Nevertheless, the results indicate that Mongolian gerbils are able to perceive a Zwicker tone and can serve as a neurophysiological model for human tinnitus generation.
CRIS-Team Scopus Importer:2023-05-05
Keywords: acoustic startle reflex; auditory phantom perception; aversive conditioning; shuttle box; tinnitus; Zwicker tone

Bilateral Functional Electrical Stimulation for the Treatment of Presbyphonia in a Sheep Model - Kirsch, Andrijana; Gerstenberger, Claus; Jakubaß, Bernhard; Tschernitz, Magdalena; Perkins, Justin D.; Groselj-Strele, Andrea; Lanmüller, Hermann; Jarvis, Jonathan C.; Kniesburges, Stefan; Döllinger, Michael; Gugatschka, Markus (Laryngoscope, 2023)
Objectives: The aim of the study was to increase muscle volume and improve phonation characteristics of the aged ovine larynx by functional electrical stimulation (FES) using a minimally invasive surgical procedure. Methods: Stimulation electrodes were placed bilaterally near the terminal adduction branch of the recurrent laryngeal nerves (RLN). The electrodes were connected to battery powered pulse generators implanted subcutaneously at the neck region. Training patterns were programmed by an external programmer using a bidirectional radio frequency link. Training sessions were repeated automatically by the implant every other day for 1 week followed by every day for 8 weeks in the awake animal. Another group of animals were used as sham, with electrodes positioned but not connected to an implant. Outcome parameters included gene expression analysis, histological assessment of muscle fiber size, functional analysis, and volumetric measurements based on three-dimensional reconstructions of the entire thyroarytenoid muscle (TAM). Results: Increase in minimal muscle fiber diameter and an improvement in vocal efficiency were observed following FES, compared with sham animals. Conclusion: This is the first study to demonstrate beneficial effects in the TAM of FES at molecular, histological, and functional levels. FES of the terminal branches of the RLN reversed the effects of age-related changes and improved vocal efficiency. Level of Evidence: NA Laryngoscope, 2023.
CRIS-Team Scopus Importer:2023-09-01
Keywords: aged larynx; functional electrical stimulation; vocal fold atrophy

Bildverarbeitung für die Medizin 2003 - Wittenberg, Thomas; Hastreiter, Peter; Hoppe, Ulrich; Handels, Heinz; Horsch, Alexander; Meinzer, Hans-Peter (Springer, 2003)
UnivIS-Import:2017-03-24:Pub.2003.tech.IMMD.IMMD9.bildve_1

Bimodal benefit for cochlear implant listeners with different grades of hearing loss in the opposite ear - Hoppe, Ulrich; Hocke, Thomas; Digeser, Frank (Acta Oto-Laryngologica, 2018)
OBJECTIVE: To determine speech perception in quiet and noise of adult cochlear implant listeners retaining a hearing aid contralaterally. Second, to investigate the influence of contralateral hearing thresholds and speech perception on bimodal hearing. PATIENTS AND METHODS: Sentence recognition with hearing aid alone, cochlear implant alone and bimodally at 6 months after cochlear implantation were assessed in 148 postlingually deafened adults. Data were analyzed for bimodal summation using measures of speech perception in quiet and in noise. RESULTS: Most of the subjects showed improved sentence recognition in quiet and in noise in the bimodal condition compared to the hearing aid-only or cochlear implant-only mode. The large variability of bimodal benefit in quiet can be partially explained by the degree of pure tone loss. Also, subjects with better hearing on the acoustic side experience significant benefit from the additional electrical input. CONCLUSIONS: Bimodal summation shows different characteristics in quiet and noise. Bimodal benefit in quiet depends on hearing thresholds at higher frequencies as well as in the lower- and middle-frequency ranges. For the bimodal benefit in noise, no correlation with hearing threshold in any frequency range was found.
EVALuna2:35458

Biocompatibility of Dextran-Coated 30 nm and 80 nm Sized SPIONs towards Monocytes, Dendritic Cells and Lymphocytes - Zschiesche, Lisa; Janko, Christina; Friedrich, Bernhard; Frey, Benjamin; Band, Julia; Lyer, Stefan; Alexiou, Christoph; Unterweger, Harald (Nanomaterials, 2023)
Dextran-coated superparamagnetic iron oxide nanoparticles (SPIONDex) of various sizes can be used as contrast agents in magnetic resonance imaging (MRI) of different tissues, e.g., liver or atherosclerotic plaques, after intravenous injection. In previous studies, the blood compatibility and the absence of immunogenicity of SPIONDex was demonstrated. The investigation of the interference of SPIONDex with stimulated immune cell activation is the aim of this study. For this purpose, sterile and endotoxin-free SPIONDex with different hydrodynamic sizes (30 and 80 nm) were investigated for their effect on monocytes, dendritic cells (DC) and lymphocytes in concentrations up to 200 µg/mL, which would be administered for use as an imaging agent. The cells were analyzed using flow cytometry and brightfield microscopy. We found that SPIONDex were hardly taken up by THP-1 monocytes and did not reduce cell viability. In the presence of SPIONDex, the phagocytosis of zymosan and E. coli by THP-1 was dose-dependently reduced. SPIONDex neither induced the maturation of DCs nor interfered with their stimulated maturation. The particles did not induce lymphocyte proliferation or interfere with lymphocyte proliferation after stimulation. Since SPIONDex rapidly distribute via the blood circulation in vivo, high concentrations were only reached locally at the injection site immediately after application and only for a very limited time. Thus, SPIONDex can be considered immune compatible in doses required for use as an MRI contrast agent.
CRIS-Team Scopus Importer:2023-01-20
Keywords: biocompatibility; immune response; magnetic resonance imaging (MRI); nanomedicine; superparamagnetic iron oxide nanoparticles (SPION)

Bioelectric impedance phase angle is associated with hospital mortality of geriatric patients - Wirth, Rainer; Volkert, Dorothee; Roesler, A.; Sieber, Cornel; Bauer, Judith (Archives of gerontology and geriatrics, 2010)
Malnutrition is regularly associated with weight loss and changes in body composition, which lead to an increase in disability, complications and mortality. Bioelectric impedance analysis (BIA) is a simple and non-invasive bedside body composition analysis technique. In particular, bioelectric impedance phase angle (PA) has been shown to predict prognosis and mortality in several clinical conditions. The purpose of this study was to determine the relationship of BIA measurements and hospital mortality in multimorbid geriatric patients. The data obtained from the routine clinical admissions of 1071 consecutive patients (783 women and 288 men, age 81.4 +/- 8.5 years) to a geriatric hospital unit was analyzed retrospectively. A significant difference of PA (50 kHz) between survivors (4.2 +/- 1.1 degrees) and non-survivors (3.6 +/- 1.2 degrees; p < 0.001) of the hospital stay could be detected. Subjects with a PA below 3.5 degrees showed a significant fourfold increased hospital mortality of 20% (95% CI = 15-24%) compared to all other subjects (5%; 95% CI = 4-7%). No calculated parameters of BIA reflecting body composition were associated with hospital mortality. Although the extent to which the PA may be regarded as a marker of nutritional state is still controversial, it was associated with hospital mortality in geriatric patients. (C) 2009 Elsevier Ireland Ltd. All rights reserved.
Keywords: Bioelectric impedance; Hospital mortality; Malnutrition of elderly; Phase angle; Geriatric patients

Biofabrication of vessel grafts based on natural hydrogels - Cicha, Iwona; Detsch, Rainer; Singh, Raminder; Reakasame, Supachai; Alexiou, Christoph; Boccaccini, Aldo R. (Current Opinion in Biomedical Engineering, 2017)

Biomechanical modeling of laryngeal dynamics - Döllinger, Michael; Yang, Anxiong; Stingl, Michael; Eysholdt, Ulrich; Lohscheller, Jörg (2008 First International Symposium on Applied Sciences on Biomedical and Communication Technologies, 2008)
Interferences in the laryngeal area based on anatomical alterations or disturbances being only visible during vocal fold oscillations yield hoarseness. Most often, asymmetries caused by the vibrating vocal folds are the origin for this hoarseness. This work presents an enhancement of biomechanical models to simulate three dimensional vocal fold vibrations. The model consists of coupled mass-spring elements similar to Ishizaka and Flanagan (1972). The new model simulates the vibrations at 25 different positions for each vocal fold. The masses are arranged at 5 positions in longitudinal direction by 5 positions in vertical direction. The masses are capable to move in all three physical directions to better simulate human laryngeal vocal fold vibrations. The physical parameters applied in the model were chosen to visually fit real three-dimensional excised human vocal fold dynamics. Exemplarily, a symmetric dynamics simulation will be given.

Biomechanical simulation of vocal fold dynamics in adults based on laryngeal high-speed videoendoscopy - Döllinger, Michael; Gómez, Pablo; Patel, Rita R.; Alexiou, Christoph; Bohr, Christopher; Schützenberger, Anne (PLoS ONE, 2017)
MOTIVATION: Human voice is generated in the larynx by the two oscillating vocal folds. Owing to the limited space and accessibility of the larynx, endoscopic investigation of the actual phonatory process in detail is challenging. Hence the biomechanics of the human phonatory process are still not yet fully understood. Therefore, we adapt a mathematical model of the vocal folds towards vocal fold oscillations to quantify gender and age related differences expressed by computed biomechanical model parameters. METHODS: The vocal fold dynamics are visualized by laryngeal high-speed videoendoscopy (4000 fps). A total of 33 healthy young subjects (16 females, 17 males) and 11 elderly subjects (5 females, 6 males) were recorded. A numerical two-mass model is adapted to the recorded vocal fold oscillations by varying model masses, stiffness and subglottal pressure. For adapting the model towards the recorded vocal fold dynamics, three different optimization algorithms (Nelder-Mead, Particle Swarm Optimization and Simulated Bee Colony) in combination with three cost functions were considered for applicability. Gender differences and age-related kinematic differences reflected by the model parameters were analyzed. RESULTS AND CONCLUSION: The biomechanical model in combination with numerical optimization techniques allowed phonatory behavior to be simulated and laryngeal parameters involved to be quantified. All three optimization algorithms showed promising results. However, only one cost function seems to be suitable for this optimization task. The gained model parameters reflect the phonatory biomechanics for men and women well and show quantitative age- and gender-specific differences. The model parameters for younger females and males showed lower subglottal pressures, lower stiffness and higher masses than the corresponding elderly groups. Females exhibited higher subglottal pressures, smaller oscillation masses and larger stiffness than the corresponding similar aged male groups. Optimizing numerical models towards vocal fold oscillations is useful to identify underlying laryngeal components controlling the phonatory process.
EVALuna2:33166

Biomimetic Magnetic Particles for the Removal of Gram-Positive Bacteria and Lipoteichoic Acid. - Friedrich, Bernhard; Eichermüller, Julia; Bogdan, Christian; Cunningham, Sarah; Hackstein, Holger; Strauss, Richard; Alexiou, Christoph; Lyer, Stefan; Tietze, Rainer (Pharmaceutics, 2022)
Gram+ bacteria are very common in clinical medicine and responsible for a large number of infectious diseases. For example, Gram+ bacteria play a major role in causing bloodstream infections and sepsis. Therefore, the detection of Gram+ bacteria is of great importance for the diagnosis and treatment of infectious diseases. Furthermore, these bacteria are often present in biofilms that cover implants. Recent research work has mainly focused on the biologic activity and removal of Gram-negative bacteria or bacterial components such as lipopolysaccharides (LPS). In contrast, the effects of lipoteichoic acid (LTA) have been less well studied so the relevance of their removal from body fluids is possibly underestimated. To address this topic, we evaluated superparamagnetic iron oxide particles (SPION) carrying different peptides derived from the innate immune receptor (GP-340) for their ability to bind and remove Gram+ bacteria and LTA from different media. Our results show that, beyond S. aureus, effective agglutinating and removing of S. pneumoniae was possible. Furthermore, we were able to show for the first time that this was possible with LTA alone and that the magnetic removal of bacteria was also efficient under flow conditions. We also found that this method was able to capture Stapyhylococcus aureus from platelet concentrates, which can help to enhance the sensitivity of microbiological diagnostics, quality control measures, and blood product safety.
EVALuna2:508460

Biophysical Characterization of (Silica-coated) Cobalt Ferrite Nanoparticles for Hyperthermia Treatment - Lucht, Niklas; Friedrich, Ralf P.; Draack, Sebastian; Alexiou, Christoph; Viereck, Thilo; Ludwig, Frank; Hankiewicz, Birgit (Nanomaterials, 2019)
Magnetic hyperthermia is a technique that describes the heating of material through an external magnetic field. Classic hyperthermia is a medical condition where the human body overheats, being usually triggered by a heat stroke, which can lead to severe damage to organs and tissue due to the denaturation of cells. In modern medicine, hyperthermia can be deliberately induced to specified parts of the body to destroy malignant cells. Magnetic hyperthermia describes the way that this overheating is induced and it has the inherent advantage of being a minimal invasive method when compared to traditional surgery methods. This work presents a particle system that offers huge potential for hyperthermia treatments, given its good loss value, i.e., the particles dissipate a lot of heat to their surroundings when treated with an ac magnetic field. The measurements were performed in a low-cost custom hyperthermia setup. Additional toxicity assessments on Jurkat cells show a very low short-term toxicity on the particles and a moderate low toxicity after two days due to the prevalent health concerns towards nanoparticles in organisms.
CRIS-Team WoS Importer:2020-01-28

BKPYV-SPECIFIC T CELLS REDUCE VIRAL LOAD IN A PRIMARY TUBULAR CELL MODEL - Wasielewski, E.; Lippler, Susanne; Knaup, Karl; Gary, Regina; Aigner, Michael; Kremer, Anna-Lena; Pfister, Felix; Amann, Kerstin Ute; Schiffer, Mario; Mackensen, Andreas; Wiesener, Michael (TRANSPLANT INTERNATIONAL, 2021)
CRIS-Team WoS Importer:2021-10-15

Boron containing magnetic nanoparticles for neutron capture therapy - an innovative approach for specifically targeting tumors - Tietze, Rainer; Unterweger, Harald; Dürr, Stephan; Lyer, Stefan; Canella, Lea; Kudejova, Petra; Wagner, Franz M.; Petry, Winfried; Taccardi, Nicola; Alexiou, Christoph (Applied Radiation and Isotopes, 2015)
The selective delivery of (10)B into the tumor tissue remains to be further improved for successful and reliable Boron Neutron Capture Therapy applications. Magnetic Drug Targeting using intraarterially administered superparamagnetic nanoparticles and external magnetic fields already exhibited convincing results in terms of highly efficient and selective drug deposition. Using the same technique for the targeted (10)B delivery is a promising new approach. Here, systematic irradiation experiments of phantom cubes containing different concentrations of boron and nanoparticles as well as varying three-dimensional arrangements have been performed.
EVALuna2:19923

Boys Choirs in the Pandemic: Effects of Distance and Other Factors on Spectral and Temporal Accuracy - Kirsch, Jonas; Köberlein, Marie; Tur, Bogac; Hermann, Laila Ava; Kniesburges, Stefan; Echternach, Matthias (Journal of Voice, 2023)
During the Covid-19 pandemic, choral singing has been either completely prohibited or regulated with safety measures due to increased transmission risks. However, the impact of larger inter-singer spacings on the performance and educational process in boys’ choirs is unclear. This study analyzed recordings of six groups of five singers each from two boys’ choirs aged 7–16 who sang Beethoven's Ode to Joy while standing on an arc with a 4 m radius and an inter-subject spacing of 0.5–3 m. The effects of singers’ masks, distance, group age, and relative position on the timing of articulation and fundamental frequency were investigated, along with the amount, rate, and sign of pitch drift and loudness. The ANOCOVA results showed that onsets were robust to the tested factors, while errors in fundamental frequency tended to decrease with increasing age/experience. Loudness was affected by distance, mask, and relative position, with increasing loudness as spacing decreased. Understanding influencing factors can inform recommendations for choral singing and education.
CRIS-Team Scopus Importer:2023-11-10
Keywords: Boys choir; Covid-19; Distance; Singing mask

Boys Choirs in the Pandemic: Exploring Qualitative Aspects of Safety Measures - Köberlein, Marie; Kirsch, Jonas; Tur, Bogac; Hermann, Laila Ava; Kniesburges, Stefan; Echternach, Matthias (Journal of Voice, 2023)
Introduction: During the Covid-19 pandemic, choirs had to apply safety measures such as distances and wearing masks. For children's choirs, there is no knowledge of their reaction to these measures, regarding their age and experience. This study aimed to investigate boys choir singers’ perceptions of the measures, regarding wellbeing and feasibility, as well as the quality of the performance outcomes. Methods: Six groups were put together, assembling five singers of the same age (7–16 years, before voice change) and experience level. The boys sang one verse of the same song at inter-subject distances of 3, 1.5, 0.5, 0.5 m plus wearing a mask and again 3 m. Afterward they filled out questionnaires concerning difficulty, irritation, hearing themselves and their neighbors, and if they could imagine singing regularly in the respective setting. Fifteen parents were asked to fill out questionnaires about their opinions about choir safety measures during the pandemic. Six anonymous boys choir experts rated the randomized recordings of all tasks regarding homogenous sound quality, rhythmical precision, and uniform intonation. Results: Even though most of the children preferred smaller distances, they were open to all kinds of settings. The answers given were very specific to the individuals. Masks were voted out by a majority of the subjects. Parents found choir singing very important for their children and did in majority neither fear infection of their children, nor mind precautions. The experts rated the performance outcomes of the largest distance (3 m) as best in most of the cases. Conclusion: Different interspatial settings do not harm the children and adolescents and could be introduced as a beneficial approach to give them a broader listening experience and to make them flexible, alert, adaptable, and resilient singers. Singers’ masks are only recommended for compelling circumstances.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Boys choir; Inter-singer distance; Singers’ mask

Brave new world revisited: Focus on nanomedicine - Fadeel, Bengt; Alexiou, Christoph (Biochemical and Biophysical Research Communications, 2020)
Nanomedicine is at a crossroads: with relatively few success stories in terms of clinical translation despite more and more research on increasingly sophisticated nanomaterials, it is important to consider whether we are on the right track. Indeed, it is crucial that we address the fact that while considerable efforts are being made to overcome barriers to translation from the bench to the clinic, scientists are still struggling to decipher fundamental aspects of nanomaterial interactions with biological systems. We believe that a key to the successful adoption of nanomedicines in oncology and beyond lies in a deeper understanding of underlying biological processes and in decoding interactions between engineered nanomaterials and biological systems. Here we provide an overview of progress in nanomedicine during the past 5 years.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Cardiovascular disease; Nanomedicine; Nanosafety; Oncology; Theranostics

Calcification in Salivary Gland Cancer Mimicking Sialolithiasis-A Diagnostic Pitfall on Imaging: Report of Two Cases and Brief Review of the Literature - Thimsen, Vivian; Fauck, Vanessa; Wiesmüller, Marco; Agaimy, Abbas; Schapher, Mirco; Iro, Heinrich; Koch, Michael; Mantsopoulos, Konstantinos (Journal of Clinical Medicine, 2022)
Objectives: Sialolithiasis is the most common cause of calcifications detected with ultrasound in patients with chronic inflammatory symptoms and swellings of the salivary glands. Other differential diagnoses of calcifications are extremely rare and mostly benign. Methods: Case report and literature review. Results: Two rare cases of malignant parotid gland tumors with calcifications in a localization typical for sialolithiasis, which were mistaken for salivary calculi based on image findings, are presented. Conclusions: This report intends to highlight the pitfalls in the imaging of parotid gland diseases. Even if malignant tumors of the parotid gland with calcifications are extremely rare, in ambiguous cases, differential diagnoses should be considered carefully. A high suspicion index of the need for further diagnostics in cases with calcifications is practical and could include missing periprandial symptoms, no obstruction signs in the proximal duct, and missing evidence of sialolithiasis in sialendoscopy.
CRIS-Team WoS Importer:2022-07-08

Cancer research by means of tissue engineering - is there a rationale? - Horch, Raymund E.; Boos, Anja; Yuan, Quan; Bleiziffer, Oliver; Detsch, Rainer; Boccaccini, Aldo R.; Alexiou, Christoph; Sun, Jiaming; Beier, Justus; Arkudas, Andreas (Journal of Cellular and Molecular Medicine, 2013)
Tissue engineering (TE) has evoked new hopes for the cure of organ failure and tissue loss by creating functional substitutes in the laboratory. Besides various innovations in the context of Regenerative Medicine (RM), TE also provided new technology platforms to study mechanisms of angiogenesis and tumour cell growth as well as potentially tumour cell spreading in cancer research. Recent advances in stem cell technology - including embryonic and adult stem cells and induced pluripotent stem cells - clearly show the need to better understand all relevant mechanisms to control cell growth when such techniques will be administered to patients. Such TE-Cancer research models allow us to investigate the interactions that occur when replicating physiological and pathological conditions during the initial phases of replication, morphogenesis, differentiation and growth under variable given conditions. Tissue microenvironment has been extensively studied in many areas of TE and it plays a crucial role in cell signalling and regulation of normal and malignant cell functions. This article is intended to give an overview on some of the most recent developments and possible applications of TE and RM methods with regard to the improvement of cancer research with TE platforms. The synthesis of TE with innovative methods of molecular biology and stem-cell technology may help investigate and potentially modulate principal phenomena of tumour growth and spreading, as well as tumour-related angiogenesis. In the future, these models have the potential to investigate the optimal materials, culture conditions and material structure to propagate tumour growth. © 2013 The Authors.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.cancer
Keywords: Angiogenesis; AV loop; Cancer research; Cell transplantation; in vitro tumour models; Metastasis; Telocytes; Tissue engineering; Tumour cells; Tumour growth; Tumourgenesis

Can stapedius reflex testing objectively measure muscle function in Pompe patients? - Hilz, Max-Josef; Hoppe, Ulrich; Möller, Sebastian; Wang, Ruihao; Koehn, Julia (Clinical Case Reports, 2015)
We assessed the value of stapedius reflex testing as an objective measurement of striated muscle function in four patients with Pompe disease. Common tests of disease severity and efficacy of enzyme replacement therapy (ERT) yield highly variable results that depend on patient cooperation and day-to-day performance, whereas stapedius reflex thresholds improved in seven of eight ears after 2 years of ERT.
EVALuna2:19973

Cardiovascular applications of magnetic particles - Cicha, Iwona; Alexiou, Christoph (Journal of Magnetism and Magnetic Materials, 2021)
The global burden of atherothrombotic diseases continues to grow. Worldwide, 17.9 million deaths per year are caused by cardiovascular diseases (CVD). According to WHO estimates, this number is expected to grow to more than 23.6 million by 2030. To achieve a more effective primary prevention of cardiovascular morbidity and mortality, the development of new diagnostic and therapeutic strategies is required. Nanomedicine offers a unique platform for novel approaches to the diagnosis and therapy of CVD. In particular iron oxide-based magnetic nanoparticles, a class of nanosized agents with superparamagnetic properties, are considered a promising tool in management of cardiovascular patients. Their possible applications range from plaque imaging and thrombus detection to the targeted drug-delivery, stent endothelialisation and blood vessel regeneration. This paper summarizes recent advances in the implementation of magnetic nanoparticles to diagnosis and treatment of cardiovascular disorders.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Atherosclerosis; Magnetic drug targeting; Magnetic resonance imaging; Stent endothelialization; Superparamagnetic iron oxide nanoparticles; Thrombolysis

Cartilaginous bending spring for preventing tympanic membrane graft medialisation in anterior or subtotal tympanic membrane perforations—how I do it - Mantsopoulos, Konstantinos; Iro, Heinrich; Hornung, Joachim (European Archives of Oto-Rhino-Laryngology, 2021)
Background: The reconstruction of anterior or subtotal tympanic membrane perforations is critical due to the risk of anterior graft medialisation and retraction or recurrent perforation. Method: After reconstruction of the tympanic membrane by means of grafting, a rectangular cartilage strut (length 6 mm, breadth 2 mm, thickness 0.1 mm) is prepared using a cartilage knife and scalpel. This strut graft is placed between the cartilage graft and the promontory in the anterior inferior part of the middle ear cavity. Conclusion: Our experience shows that using a U-shaped cartilage strut to sustain the tympanic reconstruction effectively prevents the medialisation of the graft and recurrent perforations.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Cartilage; Graft medialisation; Tympanic membrane; Tympanic perforation

Cartilaginous bending spring tympanoplasty: a temporal bone study and first clinical results - Rupp, Robin; Schelhorn, Tony; Kniesburges, Stefan; Allner, Moritz; Mantsopoulos, Konstantinos; Iro, Heinrich; Hornung, Joachim; Gostian, Antoniu-Oreste; Balk, Matthias (European Archives of Oto-Rhino-Laryngology, 2022)
Objective: Anchoring grafts for tympanic membrane (TM) reconstruction in anterior and subtotal TM defects is essential to prevent medialisation and can be facilitated by cartilaginous bending spring tympanoplasty (CBST). The purpose of this study was to analyse the impact of spring cartilages on middle ear transfer functions and patient hearing levels. Methods: In six fresh-frozen human temporal bones a cartilage graft (measuring 6 × 2 mm with a thickness of 0.1–0.2 mm) was formed into a ‘U’-shaped bending spring, to be placed between the medial tympanic wall and the tympanic underlay grafts. The stapes velocity for excitation by exponential sweeps from 400 to 10,000 Hz was measured with a laser Doppler vibrometer. The resulting middle ear transfer functions were compared with the reconstructed middle ear. For clinical evaluation, 23 ears in 21 patients with chronic otitis media and an intact ossicular chain were operated using CBST. At each follow-up visit, the patients underwent pure-tone audiometry and the Freiburg monosyllabic speech test at a presentation level of 65 dB SPL for the word recognition score (WRS). Results: The measured stapes velocities at one-third octave midband frequencies averaged 3.56 × 10–2 ± 9.46 × 10–3 (mm/s/Pa) compared to 3.06 × 10–2 ± 6.86 × 10–3 (mm/s/Pa) with the bending and underlay cartilage in place (p = 0.319; r = 0.32). The bending spring tympanoplasty reduced the transfer function by 1.41 ± 0.98 dB on average. In the clinical part of the study, the graft success rate was 96% (22 out of 23 patients) after a mean follow-up of 5.8 ± 2.4 months (min. 3.5 months, max. 12.0 months). The air–bone gap improved significantly by 6.2 dB (± 6.6 dB; p < 0.001; r = 0.69), as well as the WRS from 61.8 ± 33.3% preoperatively to 80.0 ± 20.9% postoperatively (p = 0.031; r = 0.35). Conclusion: Experimental data as well as initial clinical results suggest that CBST is an effective method for reconstructing anterior or subtotal defects of the tympanic membrane with satisfactory audiologic results and graft success rates comparable to previously described methods. It can, therefore, be added to the arsenal of tympanoplasty techniques for anterior and subtotal TM perforations.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Anterior tympanic membrane defect; Chronic otitis media; Laser Doppler vibrometry; Middle ear transfer function; Tympanoplasty

Case report: Patient specific combination of surgery and immunotherapy in advanced squamous cell carcinoma of the head and neck – a case series and review of literature - Olmos, Manuel; Lutz, Rainer; Büntemeyer, Tjark-Ole; Glajzer, Jacek; Nobis, Christopher-Philipp; Ries, Jutta; Möst, Tobias; Eckstein, Markus; Hecht, Markus; Gostian, Antoniu-Oreste; Erdmann, Michael; Foerster, Yannick; et al. (Frontiers in Immunology, 2022)
Background: Prognosis of patients with recurrent or metastatic head and neck cancer is generally poor. Adjuvant immunotherapy (IT) featuring immune checkpoint inhibition (ICI) is standard of care in advanced stage head and neck squamous cell carcinoma (HNSCC) and cutaneous squamous cell carcinoma (CSCC). ICI response rates in CSCC are described as higher than in HNSCC. IT is constantly shifting into earlier disease stages which confronts the surgeon with immunotherapeutically pre-treated patients. It is therefore becoming increasingly difficult to assess which patients with symptomatic tumor disease and a lack of curative surgical option might benefit from salvage surgery. Case presentations: The following 6 cases describe therapeutic decision-making regarding ICI and (salvage) surgery in patients with advanced stage HNSCC or CSCC. Cases A and B focus on neoadjuvant ICI followed by salvage surgery. In Cases C and D salvage surgery was performed after short-term stabilization with partial response to ICI. The last two cases (Cases E and F) address the surgical approach after failure of ICI. All cases are discussed in the context of the current study landscape and with focus on individual decision-making. For better understanding, a timetable of the clinical course is given for each case. Conclusions: ICI is rapidly expanding its frontiers into the neoadjuvant setting, frequently confronting the surgeon with heavily pretreated patients. Salvage surgery is a viable therapeutic concept despite the rise of systemic treatment options. Decision-making on surgical intervention in case of a salvage surgery remains an individual choice. For neoadjuvant ICI monitoring regarding pathological tumor response or tumor necrosis rate, we suggest correlation between the initial biopsy and the definite tumor resectate in order to increase its significance as a surrogate marker. Scheduling of neoadjuvant ICI should be further investigated, as recent studies indicate better outcomes with shorter time frames.
CRIS-Team Scopus Importer:2022-11-25
Keywords: anti-PD 1; checkpoint inhibition; CSCC; HNSCC; immunotherapy; neoadjuvant; OSCC; salvage surgery

Cell specificity of magnetic cell seeding approach to hydrogel colonization - Singh, Raminder; Wieser, Anna; Reakasame, Supachai; Detsch, Rainer; Dietel, Barbara; Alexiou, Christoph; Boccaccini, Aldo R.; Cicha, Iwona (Journal of Biomedical Materials Research Part A, 2017)
Keywords: alginate-based hydrogels; endothelial cells; fibroblasts; magnetic cell seeding; superparamagnetic iron oxide nanoparticles

Cellular density and variability in laryngeal and pharyngeal squamous cell carcinoma using confocal laser endomicroscopy - Sievert, Matti; Aubreville, M.; Eckstein, Markus; Mantsopoulos, Konstantinos; Koch, Matthias; Gostian, Antoniu-Oreste; Mueller, Sarina K.; Iro, Heinrich; Goncalves, M. (European Review for Medical and Pharmacological Sciences, 2023)
OBJECTIVE: Confocal laser endomicroscopy (CLE) allows the visualization of epithelium in a thousand-fold magnification. This study analyzes the architectural differences at the cellular level of the mucosa and squamous cell carcinoma (SCC). PATIENTS AND METHODS: A total of 60 CLE sequences recorded in 5 patients with SCC undergoing laryngectomy between October 2020 and February 2021 were analyzed. The corresponding histologic sample derived from H&E staining was assigned to each sequence, capturing CLE images of the tumor and healthy mucosa. In addition, the cellular structure analysis was performed to diagnose SCC by measuring the total number of cells and cell size in 60 sequences in a fixed field of view (FOV) with 240 μm in diameter (45,239 μm2). RESULTS: Out of 3,600 images, 1,620 (45%) showed benign mucosa and 1,980 (55%) SCC. The automated analysis yielded a difference in cell size, with healthy epithelial cells being 171.9±82.0 μm2 smaller than SCC cells, which were 246.3±171.9 μm2 and showed greater variability in size (p=0.037). In addition, due to the probe’s fixed FOV, there was a difference in cell count with a total of 188.7±38.3 and 124.8±38.6 cells in images of normal epithelium and SCC (p<0.001), respectively. Regarding cell density as a criterion for the differentiation of benign/malign, using a cut-off value of 145.5 cells/FOV, we obtained sensitivity and specificity of 88.0% and 71.9%, respectively. CONCLUSIONS: SCC reveals marked differences at a cellular level compared to the healthy epithelium. Our results further support the importance of this feature for identifying SCC during CLE imaging.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Classification; Confocal laser endomicroscopy; Head and neck squamous cell carcinoma; Larynx; Optical biopsy; Pharynx

Cellular effects of paclitaxel-loaded iron oxide nanoparticles on breast cancer using different 2D and 3D cell culture models - Lugert, Stephan; Unterweger, Harald; Mühlberger, Marina; Janko, Christina; Janko, Christina; Draack, Sebastian; Ludwig, Frank; Eberbeck, Dietmar; Alexiou, Christoph; Friedrich, Ralf P. (International Journal of Nanomedicine, 2019)
Background: Magnetic drug targeting (MDT) is an effective alternative for common drug applications, which reduces the systemic drug load and maximizes the effect of, eg, chemotherapeutics at the site of interest. After the conjugation of a magnetic carrier to a chemotherapeutic agent, the intra-arterial injection into a tumor-afferent artery in the presence of an external magnetic field ensures the accumulation of the drug within the tumor tissue. Materials and methods: In this study, we used superparamagnetic iron oxide nanoparticles (SPIONs) coated with lauric acid and human serum albumin as carriers for paclitaxel (SPIONLA-HSA-Ptx). To investigate whether this particle system is suitable for a potential treatment of cancer, we investigated its physicochemical properties by dynamic light scattering, ζ potential measurements, isoelectric point titration, infrared spectroscopy, drug release quantification, and magnetic susceptibility measurements. The cytotoxic effects were evaluated using extensive toxicological methods using flow cytometry, IncuCyte® live-cell imaging, and growth experiments on different human breast cancer cell lines in two- and three-dimensional cell cultures. Conclusion: The data showed that next to their high magnetization capability, SPIONLA-HSA-Ptx have similar cytostatic effects on human breast cancer cells as pure paclitaxel, suggesting their usage for future MDT-based cancer therapy.
EVALuna2:35447

Cellular Response to Reagent-Free Electron-Irradiated Gelatin Hydrogels - Wisotzki, Emilia I.; Friedrich, Ralf P.; Weidt, Astrid; Alexiou, Christoph; Mayr, Stefan G.; Zink, Mareike (Macromolecular Bioscience, 2016)
As a biomaterial, it is well established that gelatin exhibits low cytotoxicity and can promote cellular growth. However, to circumvent the potential toxicity of chemical crosslinkers, reagent-free crosslinking methods such as electron irradiation are highly desirable. While high energy irradiation has been shown to exhibit precise control over the degree of crosslinking, these hydrogels have not been thoroughly investigated for biocompatibility and degradability. Here, NIH 3T3 murine fibroblasts are seeded onto irradiated gelatin hydrogels to examine the hydrogel's influence on cellular viability and morphology. The average projected area of cells seeded onto the hydrogels increases with irradiation dose, which correlates with an increase in the hydrogel's shear modulus up to 10 kPa. Cells on these hydrogels are highly viable and exhibits normal cell cycles, particularly when compared to those grown on glutaraldehyde crosslinked gelatin hydrogels. However, proliferation is reduced on both types of crosslinked samples. To mimic the response of the hydrogels in physiological conditions, degradability is monitored in simulated body fluid to reveal strongly dose-dependent degradation times. Overall, given the low cytotoxicity, influence on cellular morphology and variability in degradation times of the electron irradiated gelatin hydrogels, there is significant potential for application in areas ranging from regenerative medicine to mechanobiology.
EVALuna2:33220

Cellular spion uptake and toxicity in various head and neck cancer cell lines - Balk, Matthias; Haus, Theresa; Band, Julia; Unterweger, Harald; Schreiber, Eveline; Friedrich, Ralf P.; Alexiou, Christoph; Gostian, Antoniu Oreste (Nanomaterials, 2021)
Superparamagnetic iron oxide nanoparticles (SPIONs) feature distinct magnetic properties that make them useful and effective tools for various diagnostic, therapeutic and theranostic applica-tions. In particular, their use in magnetic drug targeting (MDT) promises to be an effective approach for the treatment of various diseases such as cancer. At the cellular level, SPION uptake, along with SPION-mediated toxicity, represents the most important prerequisite for successful application. Thus, the present study determines SPION uptake, toxicity and biocompatibility in human head and neck tumor cell lines of the tongue, pharynx and salivary gland. Using magnetic susceptibility measurements, microscopy, atomic emission spectroscopy, flow cytometry, and plasma coagulation, we analyzed the magnetic properties, cellular uptake and biocompatibility of two different SPION types in the presence and absence of external magnetic fields. Incubation of cells with lauric acid and human serum albumin-coated nanoparticles (SPIONLA-HSA) resulted in substantial particle uptake with low cytotoxicity. In contrast, uptake of lauric acid-coated nanoparticles (SPIONLA) was sub-stantially increased but accompanied by higher toxicity. The presence of an external magnetic field significantly increased cellular uptake of both particles, although cytotoxicity was not significantly increased in any of the cell lines. SPIONs coated with lauric acid and/or human serum albumin show different patterns of uptake and toxicity in response to an external magnetic field. Consequently, the results indicate the potential use of SPIONs as vehicles for MDT in head and neck cancer.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Atomic emission spectroscopy; Cytotoxicity; Flow cytometry; Holotomographic microscopy; Superparamagnetic iron oxide nanoparticles

Cell Viability and Immunogenic Function of T Cells Loaded with Nanoparticles for Spatial Guidance in Magnetic Fields - Pfister, Felix; Alexiou, Christoph; Janko, Christina (Humana Press Inc., 2023)
Immune cell therapies, such as adoptive T cell therapies, are an innovative and powerful treatment option for previously non-treatable diseases. Although immune cell therapies are thought to be very specific, there is still the danger of developing severe to life-threatening side effects due to the unspecific distribution of the cells throughout the body (on-target/off-tumor effects). A possible solution for the reduction of these side effects and the improvement of tumor infiltration is the specific targeting of the effector cells (e.g., T cells) to the desired destination (e.g., tumor region). This can be achieved by the magnetization of cells with superparamagnetic iron oxide nanoparticles (SPIONs) for spatial guidance via external magnetic fields. A prerequisite for the use of SPION-loaded T cells in adoptive T cell therapies is that cell viability and functionality after nanoparticle loading are preserved. Here, we demonstrate a protocol to analyze cell viability and functionality such as activation, proliferation, cytokine release, and differentiation at a single cell level using flow cytometry.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Cell viability; Flow cytometry; Intracellular cytokine staining; T cells; T cell activation; T cell proliferation

Characterization of an Inductance-based Detector in Molecular Communication Testbed Based on Superparamagnetic Iron Oxide Nanoparticles - Ahmed, Doaa; Unterweger, Harald; Fischer, Georg; Schober, Robert; Kirchner, Jens (IEEE SENSORS 2019, 2019)
Molecular communication (MC), using chemicals or particles, is a promising approach to bridge the gaps of conventional communication systems, e.g. in nano-scale or in pipelines. Our testbed depends on superparamagnetic iron oxide nanoparticles (SPIONs) as information carriers, which are detected using a susceptometer. In this paper, we study how the position and distribution of particles near the susceptometer, i.e., coil, affect its detected signal. When the particles move axially through the coil, an increment in the signal is detected. In addition, we observed a nonlinear additive behaviour of inductance in the same axial direction, i.e., changes in inductance due to partial volumes are not additive. An exponentially-like signal is detected when the particles move radially through the coil. Moreover, a linear additive behaviour of inductance is observed in this direction. Increasing the magnetic susceptibility has a significant effect on the detected signal. However, the susceptibility of SPIONs is relatively small in order to keep superparamagnetic properties. The coil inductance depends not only on the volume, or permeability of magnetic particles in its core, but also on how they are distributed inside. <br
Keywords: molecular communication; superparamagnetic nanoparticles; simulation; MC testbed; coils; magnetic fields

Characterizations of drug carrying magnetic nanoparticles for tumor therapy: Biological outcome and first immunological aspects - Dürr, Stephan; Tietze, Rainer; Lyer, Stefan; Janko, Christina; Schreiber, Eveline; Mann, Johannes; Turcu, R.; Gitter, K.; Odenbach, S.; Vasylyev, Serhiy; Herrmann, Martin; Peukert, Wolfgang; et al. (Magnetohydrodynamics, 2013)
Nanosized magnetic drug carriers offer a splendid prospect for directed drug application. The increased drug concentration in cancer tissue reached for this kind of application enables therapeutic effects on tumors that cannot be achieved using conventional chemotherapeutic treatment. Characterizing the drug targeting system and its behavior in vitro is necessary for understanding the biological outcome. In our studies, IRspectroscopy shows covalent binding of the biocompatible fatty acid layer. Although binding of mitoxantrone (MTO) to particles is hardly defined, considerable amounts of drug can be carried by nanoparticles. Furthermore, the nanosized drug carrier complex has to be investigated due to its biological outcome. Real-time cell analysis is useful to observe the therapeutic particles concerning their outcome in cell culture time-resolved up to several days. First experiments in concordance to a conventional assay show that the effectivity of nanoparticle bound MTO in cell culture is higher than treatment with pure MTO. A preliminary study demonstrates that the burden of the immune system is reduced by Magnetic Drug Targeting (MDT) vs. conventional chemotherapy. For a better understanding of MDT for cancer treatment, further studies have to be done to explain especially the binding behavior of superparamagnetic iron oxide nanoparticles to the respective chemotherapeutic agent.
Keywords: nano; magnetic; characterization; particle; agent

Characterizing vibratory kinematics in children and adults with high-speed digital imaging - Patel, Rita; Dubrovskiy, Denis; Döllinger, Michael (Journal of Speech Language and Hearing Research, 2014)
PURPOSE The aim of this study is to quantify and identify characteristic vibratory motion in typically developing prepubertal children and young adults using high-speed digital imaging. METHOD The vibrations of the vocal folds were recorded from 27 children (ages 5-9 years) and 35 adults (ages 21-45 years), with high speed at 4,000 frames per second for sustained phonation. Kinematic features of amplitude periodicity, time periodicity, phase asymmetry, spatial symmetry, and glottal gap index were analyzed from the glottal area waveform across mean and standard deviation (i.e., intercycle variability) for each measure. RESULTS Children exhibited lower mean amplitude periodicity compared to men and women and lower time periodicity compared to men. Children and women exhibited greater variability in amplitude periodicity, time periodicity, phase asymmetry, and glottal gap index compared to men. Women had lower mean values of amplitude periodicity and time periodicity compared to men. CONCLUSION Children differed both spatially but more temporally in vocal fold motion, suggesting the need for the development of children-specific kinematic norms. Results suggest more uncontrolled vibratory motion in children, reflecting changes in the vocal fold layered structure and aero-acoustic source mechanisms.
EVALuna2:20185

Chemoresistance in Pancreatic Cancer - Zeng, Siyuan; Pöttler, Marina; Lan, Bin; Grützmann, Robert; Pilarsky, Christian; Yang, Hai (International Journal of Molecular Sciences, 2019)
Pancreatic ductal adenocarcinoma (PDAC), generally known as pancreatic cancer (PC), ranks the fourth leading cause of cancer-related deaths in the western world. While the incidence of pancreatic cancer is displaying a rising tendency every year, the mortality rate has not decreased significantly because of late diagnosis, early metastasis, and limited reaction to chemotherapy or radiotherapy. Adjuvant chemotherapy after surgical resection is typically the preferred option to treat early pancreatic cancer. Although 5-fluorouracil/leucovorin with irinotecan and oxaliplatin (FOLFIRINOX) and gemcitabine/nab-paclitaxel can profoundly improve the prognosis of advanced pancreatic cancer, the development of chemoresistance still leads to poor clinical outcomes. Chemoresistance is multifactorial as a result of the interaction among pancreatic cancer cells, cancer stem cells, and the tumor microenvironment. Nevertheless, more pancreatic cancer patients will benefit from precision treatment and targeted drugs. Therefore, we outline new perspectives for enhancing the efficacy of gemcitabine after reviewing the related factors of gemcitabine metabolism, mechanism of action, and chemoresistance.
CRIS-Team Scopus Importer:2019-09-20
Keywords: chemoresistance; FOLFIRINOX; gemcitabine; pancreatic cancer; PDAC

Children with cochlear implant and additional disabilities benefit from consistent device use - Glaubitz, Cynthia; Liebscher, Tim; Hoppe, Ulrich (International Journal of Pediatric Otorhinolaryngology, 2022)
Objectives: Although the prevalence of additional disabilities (AD) in children with a cochlear implant (CI) is high, children with such disabilities are often excluded from clinical studies, or their specific characteristics are only partially included. The literature shows that several factors need to be considered in evaluating auditory and language development in CI children with AD, including demographic variables as well as the severity and type of disability. Current findings on device use in children show correlations with auditory and language outcome, but little is known about device use specifically in children with AD. The purpose of this study was to determine the auditory and language outcome of CI children with AD and to analyse their datalogging-based daily device use, both 1 year and 2 years after implantation. In addition, any potential correlations between outcome and device use were to be identified.Methods: A cohort of 32 CI children with 5 different types of AD were included in this retrospective analysis. The children's auditory and language outcome was assessed by the parental questionnaires LittlEARS and ELFRA and by the professional observation tool CAP (Categories of Auditory Performance) 1 and 2 years after implantation. Longitudinal device use was analysed by using the CI system-integrated data-logging; daily duration of CI use, number of coil disconnections and exposure to different listening scenes were recorded.Results: Overall, the cohort's auditory and language performance showed significant progress over time, while reduced abilities became more obvious after 2 years of CI experience. The mean daily duration of CI use increased significantly from 7.8 +/- 2.8 to 8.2 +/- 2.7 h after 2 years. High numbers of daily coil disconnections were detected, with a significant mean decrease from 83.4 +/- 73.1 to 66.3 +/- 54.6 whereas the percentage exposure to different listening environments was widely stable over time. Significant rank correlations were identified between outcomes measured by ELFRA and CAP with daily duration of CI use, numbers of coil disconnections and percentage of exposure to speech-characterised listening scenes.Conclusion: The auditory and language outcome in CI children with AD is variable, but it progresses over time. Children benefit from a consistent daily device use as well as from a high exposure to speech-characterised environments. Device use should be monitored constantly, with particular focus on daily duration of CI use and, in particular, on the number of coil disconnections if children have a severe motor impairment. Objective data-logging is an important addition to outcome assessment by testing, observations and parental questionnaires. Although assessment in children with AD is a major challenge for professionals, comprehensive assessment is needed to improve cochlear implant services with special adaption to children with AD, and this should include audiological, development-related and psychosocial information. A unified system to classify types of disabilities could help to improve procedures for analysing different outcomes.
CRIS-Team WoS Importer:2022-10-07

Circadian Sensitivity of Noise Trauma-Induced Hearing Loss and Tinnitus in Mongolian Gerbils - Grimm, Jannik; Schulze, Holger; Tziridis, Konstantin (Frontiers in Neuroscience, 2022)
Noise-induced hearing loss (HL) has a circadian component: In nocturnal mice, hearing thresholds (HT) have a significantly stronger effect to acoustic trauma when induced during the night compared to rather mild effects on hearing when induced during daytime. Here, we investigate whether such effects are also present in diurnal Mongolian gerbils and determined whether trauma-induced HL correlated with the development of a tinnitus percept in these animals. In particular, we investigated the effects of acoustic trauma (2 kHz, 115 dB SPL, 75 min) on HT and tinnitus development in 34 male gerbils exposed either at 9 AM, 1 PM, 5 PM, or 12 PM. HT was measured by acoustic brainstem response audiometry at defined times 1 day before and 1 week after the trauma. Possible tinnitus percepts were assessed behaviorally by the gap prepulse inhibition of the acoustic startle response at defined times 1 day before and 1 week after the trauma. We found daytime-dependent changes due to trauma in mean HT in a frequency-dependent manner comparable to the results in mice, but the results temporally shifted according to respective activity profiles. Additionally, we found linear correlations of these threshold changes with the strength of the tinnitus percept, with the most prominent correlations in the 5 PM trauma group. Taken together, circadian sensitivity of the HT to noise trauma can also be found in gerbils, and tinnitus strength correlates most strongly with HL only when the trauma is applied at the most sensitive times, which seem to be the evening.
CRIS-Team WoS Importer:2022-07-01

Citrate-coated superparamagnetic iron oxide nanoparticles enable a stable non-spilling loading of t cells and their magnetic accumulation - Boosz, Philipp; Pfister, Felix; Stein, René; Friedrich, Bernhard; Fester, Lars; Band, Julia; Mühlberger, Marina; Schreiber, Eveline; Lyer, Stefan; Dudziak, Diana; Alexiou, Christoph; Janko, Christina (Cancers, 2021)
T cell infiltration into a tumor is associated with a good clinical prognosis of the patient and adoptive T cell therapy can increase anti-tumor immune responses. However, immune cells are often excluded from tumor infiltration and can lack activation due to the immune-suppressive tumor microenvironment. To make T cells controllable by external forces, we loaded primary human CD3+ T cells with citrate-coated superparamagnetic iron oxide nanoparticles (SPIONs). Since the efficacy of magnetic targeting depends on the amount of SPION loading, we investigated how experimental conditions influence nanoparticle uptake and viability of cells. We found that loading in the presence of serum improved both the colloidal stability of SPIONs and viability of T cells, whereas stimulation with CD3/CD28/CD2 and IL-2 did not influence nanoparticle uptake. Further-more, SPION loading did not impair cytokine secretion after polyclonal stimulation. We finally achieved 1.4 pg iron loading per cell, which was both located intracellularly in vesicles and bound to the plasma membrane. Importantly, nanoparticles did not spill over to non-loaded cells. Since SPION-loading enabled efficient magnetic accumulation of T cells in vitro under dynamic condi-tions, we conclude that this might be a good starting point for the investigation of in vivo delivery of immune cells.
CRIS-Team Scopus Importer:2021-09-03
Keywords: Adoptive T cell transfer; Immune therapy; Magnetic targeting; Nanomedicine; Solid tumor; Superparamagnetic iron oxide nanoparticles (SPIONs); Targeted transport

Classification at the accuracy limit: facing the problem of data ambiguity - Metzner, Claus; Schilling, Achim; Traxdorf, Maximilian; Tziridis, Konstantin; Maier, Andreas; Schulze, Holger; Krauß, Patrick (Scientific Reports, 2022)
Data classification, the process of analyzing data and organizing it into categories or clusters, is a fundamental computing task of natural and artificial information processing systems. Both supervised classification and unsupervised clustering work best when the input vectors are distributed over the data space in a highly non-uniform way. These tasks become however challenging in weakly structured data sets, where a significant fraction of data points is located in between the regions of high point density. We derive the theoretical limit for classification accuracy that arises from this overlap of data categories. By using a surrogate data generation model with adjustable statistical properties, we show that sufficiently powerful classifiers based on completely different principles, such as perceptrons and Bayesian models, all perform at this universal accuracy limit under ideal training conditions. Remarkably, the accuracy limit is not affected by certain non-linear transformations of the data, even if these transformations are non-reversible and drastically reduce the information content of the input data. We further compare the data embeddings that emerge by supervised and unsupervised training, using the MNIST data set and human EEG recordings during sleep. We find for MNIST that categories are significantly separated not only after supervised training with back-propagation, but also after unsupervised dimensionality reduction. A qualitatively similar cluster enhancement by unsupervised compression is observed for the EEG sleep data, but with a very small overall degree of cluster separation. We conclude that the handwritten letters in MNIST can be considered as ’natural kinds’, whereas EEG sleep recordings are a relatively weakly structured data set, so that unsupervised clustering will not necessarily re-cover the human-defined sleep stages.
CRIS-Team Scopus Importer:2023-03-07

Classification of three prognostically different groups of head and neck cancer patients based on their metabolic response to induction chemotherapy (IC-1) - Semrau, Sabine; Schmidt, Daniela; Hecht, Markus; Haderlein, Marlen; Kitzsteiner, Christian; Müller, Susanna; Traxdorf, Maximilian; Agaimy, Abbas; Iro, Heinrich; Kuwert, Torsten; Fietkau, Rainer (Oral Oncology, 2020)
Objectives: There exist no uniform decision criteria for conservative organ preservation treatments in head and neck cancer patients. Even with 18F-FDG-PET/CT after induction chemotherapy patient selection is challenging. This study correlated metabolic tumor response with treatment types and recurrence patterns. Materials and methods: Decrease in SUVmax in 18F-FDG-PET/CT was measured 21–28 days after IC-1 in 102 patients and correlated to cancer-specific endpoints. Results: Residual SUVmax (resSUVmax) values were uniformly distributed across five cut-off levels (0–0.2 vs. >0.2–0.4 vs. >0.4–0.6 vs. >0.6–0.8 vs. >0.8) containing 20%, 25% 25%, 15% and 15% of patients. Patients were stratified into three response categories according to residual SUVmax (Group A: 0–0.4 = high response Group B: >0.4–0.8 = moderate response, Group C > 0.8 = non-response), 5-year local control rates were 90.5% (Group A) vs. 78.9% (Group B; univariate p = 0.07, multivariate: HR: 3.6, p = 0.03) vs. 49.4% (Group C vs. B; univariate p = 0.04, multivariate: HR 5.5, p < 0.01). After IC-1, Group A received chemoradiotherapy (CRT) only. Group B received surgery plus either (chemo)radiotherapy (B_S + RT/CRT) or chemoradiotherapy (B_CRT), yielding local control rates of 100% and 74.2% (p = 0.11). Group C received surgery plus CRT or CRT alone; both achieved equally poor local control (p = 0.71). Group C had significantly worse distant metastasis-free survival and overall survival than Groups A and B (p < 0.05). Conclusion: Metabolic response after IC-1 differentiates HNC patients into three subgroups predicting local tumor control. Non-response was associated with a poor outcome.
CRIS-Team Scopus Importer:2019-12-03
Keywords: 18F-FDG PET/CT; Chemoradiation; Chemoselection; Head and neck cancer; Hypopharynx; Induction chemotherapy; Larynx; Metabolic response; Resection

Clinical Behavior of the Mucoepidermoid Carcinoma of the Larynx—A Scoping Review - Poutoglidis, Alexandros; Forozidou, Evropi; Fyrmpas, Georgios; Mantsopoulos, Konstantinos; Chrysanthou, Chrysanthos; Galanis, Nektarios; Paraskevas, George; Savvakis, Stavros; Karamitsou, Paraskevi (Laryngoscope, 2023)
Objective: Mucoepidermoid carcinomas (MEC) of the larynx account for less than 1% of all laryngeal tumors. The unique features and clinical behavior of these rare entities remain unknown. To fill this knowledge gap, we performed a scoping review of every reported case of laryngeal MEC to study the clinical behavior and the treatment modalities in this rare entity. Review Methods: We followed the guidelines outlined in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews (PRISMA-ScR) statement. Data Sources: MedLine, Google Scholar, and Science Direct databases were searched to identify eligible studies. Results: We concluded with 25 studies and overall 66 cases. Our study revealed that the average age of cases was 55.7 years, and the range was from 12 to 81 years, with younger onset in females. Supraglottic (60%) is the most common subsite of laryngeal MEC s followed by glottis (27.3%). Supraglottic carcinomas frequently present with metastatic neck disease at the time of the initial diagnosis and require more extensive surgical approaches. Surgery with negative surgical margins seems to be the cornerstone in the treatment of MEC. Radiation therapy has not been tested widely as monotherapy but is considered a useful adjuvant modality. Conclusion: This study suggests that negative surgical margins seem to be associated to higher disease control rate and that high-grade supraglottic cases likely benefit from addressing neck disease simultaneously. Level of Evidence: NA Laryngoscope, 2023.
CRIS-Team Scopus Importer:2023-12-01
Keywords: head and neck; laryngeal cancer; mucoepidermoid carcinoma; Oncology; scoping review

Clinical characterization of respiratory large droplet production during common airway procedures using high-speed imaging - Mueller, Sarina K.; Veltrup, Reinhard; Jakubaß, Bernhard; Kniesburges, Stefan; Hübner, Matthias; Kempfle, J. S.; Dittrich, Sven; Iro, Heinrich; Döllinger, Michael (Scientific Reports, 2021)
During the COVID-19 pandemic, a significant number of healthcare workers have been infected with SARS-CoV-2. However, there remains little knowledge regarding large droplet dissemination during airway management procedures in real life settings. 12 different airway management procedures were investigated during routine clinical care. A high-speed video camera (1000 frames/second) was for imaging. Quantitative droplet characteristics as size, distance traveled, and velocity were computed. Droplets were detected in 8/12 procedures. The droplet trajectories could be divided into two distinctive patterns (type 1/2). Type 1 represented a ballistic trajectory with higher speed large droplets whereas type 2 represented a random trajectory of slower particles that persisted longer in air. The use of tracheal cannula filters reduced the amount of droplets. Respiratory droplet patterns generated during airway management procedures follow two distinctive trajectories based on the influence of aerodynamic forces. Speaking and coughing produce more droplets than non-invasive ventilation therapy confirming these behaviors as exposure risks. Even large droplets may exhibit patterns resembling the fluid dynamics smaller airborne aerosols that follow the airflow convectively and may place the healthcare provider at risk.
CRIS-Team Scopus Importer:2021-06-04

Clinical Picture of IgG4-Rhinosinusitis - Waldfahrer, Frank (HNO, 2018)
EVALuna2:210078

Clinical practice guideline: tonsillitis I. Diagnostics and nonsurgical management - Windfuhr, Jochen P.; Toepfner, Nicole; Steffen, Gregor; Waldfahrer, Frank; Berner, Reinhard (European Archives of Oto-Rhino-Laryngology, 2016)
More than 120,000 patients are treated annually in Germany to resolve repeated episodes of acute tonsillitis. Therapy is aiming at symptom regression, avoidance of complications, reduction in the number of disease-related absences in school or at work, increased cost-effectiveness and improved quality of life. The purpose of this part of the guideline is to provide clinicians in any setting with a clinically focused multi-disciplinary guidance through different conservative treatment options in order to reduce inappropriate variation in clinical care, improve clinical outcome and reduce harm. Surgical management in terms of intracapsular as well as extracapsular tonsillectomy (i.e. tonsillotomy) is the subject of part II of this guideline. To estimate the probability of tonsillitis caused by ?-hemolytic streptococci, a diagnostic scoring system according to Centor or McIsaac is suggested. If therapy is considered, a positive score of >=3 should lead to pharyngeal swab or rapid test or culture in order to identify ?-hemolytic streptococci. Routinely performed blood tests for acute tonsillitis are not indicated. After acute streptococcal tonsillitis, there is no need to repeat a pharyngeal swab or any other routine blood tests, urine examinations or cardiological diagnostics such as ECG. The determination of the antistreptolysin O-titer (ASLO titer) and other antistreptococcal antibody titers do not have any value in relation to acute tonsillitis with or without pharyngitis and should not be performed. First-line therapy of ?-hemolytic streptococci consists of oral penicillin. Instead of phenoxymethylpenicillin-potassium (penicillin V potassium), also phenoxymethlpenicillin-benzathine with a clearly longer half-life can be used. Oral intake for 7 days of one of both the drugs is recommended. Alternative treatment with oral cephalosporins (e.g. cefadroxil, cefalexin) is indicated only in cases of penicillin failure, frequent recurrences, and whenever a more reliable eradication of ?-hemolytic streptococci is desirable. In cases of allergy or incompatibility of penicillin, cephalosporins or macrolides (e.g. Erythromycin-estolate) are valuable alternatives.
EVALuna2:20015

Clinical practice guideline: tonsillitis II. Surgical management - Windfuhr, Jochen P.; Toepfner, Nicole; Steffen, Gregor; Waldfahrer, Frank; Berner, Reinhard (European Archives of Oto-Rhino-Laryngology, 2016)
In 2013, a total of 84,332 patients had undergone extracapsular tonsillectomies (TE) and 11,493 a tonsillotomy (TT) procedure in Germany. While the latter is increasingly performed, the number of the former is continually decreasing. However, a constant number of approximately 12,000 surgical procedures in terms of abscess-tonsillectomies or incision and drainage are annually performed in Germany to treat patients with a peritonsillar abscess. The purpose of this part of the clinical guideline is to provide clinicians in any setting with a clinically focused multi-disciplinary guidance through the surgical treatment options to reduce inappropriate variation in clinical care, improve clinical outcome and reduce harm. Surgical treatment options encompass intracapsular as well as extracapsular tonsil surgery and are related to three distinct entities: recurrent episodes of (1) acute tonsillitis, (2) peritonsillar abscess and (3) infectious mononucleosis. Conservative management of these entities is subject of part I of this guideline. (1) The quality of evidence for TE to resolve recurrent episodes of tonsillitis is moderate for children and low for adults. Conclusions concerning the efficacy of TE on the number of sore throat episodes per year are limited to 12 postoperative months in children and 5-6 months in adults. The impact of TE on the number of sore throat episodes per year in children is modest. Due to the heterogeneity of data, no firm conclusions on the effectiveness of TE in adults can be drawn. There is still an urgent need for further research to reliably estimate the value of TE compared to non-surgical therapy of tonsillitis/tonsillo-pharyngitis. The impact of TE on quality of life is considered as being positive, but further research is mandatory to establish appropriate inventories and standardized evaluation procedures, especially in children. In contrast to TE, TT or comparable procedures are characterized by a substantially lower postoperative morbidity in terms of pain and bleeding. Although tonsillar tissue remains along the capsule, the outcome appears not to differ from TE, at least in the pediatric population and young adults. Age and a history of tonsillitis are not a contraindication, abscess formation in the tonsillar remnants is an extremely rare finding. The volume of the tonsils should be graded according to Brodsky and a grade >1 is considered to be eligible for TT. The number of episodes during 12 months prior to presentation is crucial to indicate either TE or TT. While surgery is not indicated in patients with less than three episodes, a wait-and-see policy for 6 months is justified to include the potential of a spontaneous healing before surgery is considered. Six or more episodes appear to justify tonsil surgery. (2) Needle aspiration, incision and drainage, and abscess tonsillectomy are effective methods to treat patients with peritonsillar abscess. Compliance and ability of the patient to cooperate must be taken into account when choosing the surgical method. Simultaneous antibiotic therapy is recommended but still subject of scientific research. Abscess tonsillectomy should be preferred, if complications have occurred or if alternative therapeutic procedures had failed. Simultaneous TE of the contralateral side should only be performed when criteria for elective TE are matched or in cases of bilateral peritonsillar abscess. Needle aspiration or incision and drainage should be preferred if co-morbidities exist or an increased surgical risk or coagulation disorders are present. Recurrences of peritonsillar abscesses after needle aspiration or incision and drainage are rare. Interval TE should not be performed, the approach is not supported by contemporary clinical studies. (3) In patients with infectious mononucleosis TE should not be performed as a routine procedure for symptom control. TE is indicated in cases with clinically significant upper airway obstruction resulting from inflammatory tonsillar hyperplasia. If signs of a concomitant bacterial infection are not present, antibiotics should not be applied. Steroids may be administered for symptom relief.
EVALuna2:20016

Clinical relevance and prognostic value of radiographic findings in Zenker's diverticulum - Mantsopoulos, Konstantinos; Psychogios, Georgios; Karatzanis, Alexander; Kuenzel, Julian; Lell, Michael; Zenk, Johannes; Koch, Michael (European Archives of Oto-Rhino-Laryngology, 2014)
The aim of this study was to evaluate the clinical relevance and prognostic value of preoperative and postoperative oesophagography in patients with Zenker's diverticulum. The medical records of 155 patients who underwent surgical treatment (with an endoscopic or transcervical approach) for Zenker's diverticulum between 1992 and 2010 in a tertiary referral centre were retrospectively evaluated. The size of the diverticula on oesophagography, recognizable muscular septum, and protection of the diverticulum were assessed relative to the surgical procedures performed. The incidence of diverticular remnants on postoperative oesophagography was also assessed relative to the surgical procedure. It was investigated whether the detection of a residual pharyngeal pouch and filling of it with contrast medium were related to the patients' immediate postoperative symptoms and the development of symptomatic recurrence. Larger diverticula (Brombart III-IV) were manageable significantly more often with endoscopic procedures (P = 0.007). Residual diverticulum and filling with contrast medium were strongly associated with prolonged dysphagia immediately postoperatively (P = 0.005 and P = 0.009, respectively). However, these parameters failed to correlate significantly with a symptomatic recurrence. Preoperative oesophagography proved to be extremely important for surgical planning, with the surgeon's personal preference seeming to be the driving indicator in many cases. Postoperative oesophagography is only useful for excluding postoperative complications in the immediate postoperative phase and did not have a prognostic value as to a recurrence of the disease.
EVALuna2:14353

Clinical relevance of endoscopic three-dimensional imaging for quantitative assessment of phonation - Semmler, Marion; Döllinger, Michael; Patel, Rita R.; Ziethe, Anke; Schützenberger, Anne (Laryngoscope, 2018)
OBJECTIVE/HYPOTHESIS: Laser-based three-dimensional (3D) imaging allows realistic visualization and absolute measurement of the vocal folds for comprehensive characterization of the oscillation pattern. STUDY DESIGN: Exploratory study with descriptive data analysis in healthy cohort. METHODS: The custom-developed miniaturized measuring device is an endoscopic camera-laser setup for stereo triangulation and suitable for in vivo application. The laser projection unit generates a regular laser grid that is projected on the vocal folds and recorded at 4000 fps using a high-speed camera. Recordings are performed during sustained phonation on 10 healthy subjects. RESULTS: We present absolute values for the lateral and vertical displacement amplitudes and maximum velocities during opening and closing phase. On average over all study participants, the vertical parameters are at least 50% higher than their lateral counterparts. The mean male/female amplitudes are 0.93 mm/0.80 mm in the lateral and 1.28 mm/1.45 mm in the vertical direction. Only 20% of the healthy subjects displayed slight asymmetries in the lateral direction, but 70% showed significant asymmetries in the vertical component. In only 30% of all subjects, the asymmetry trends matched in the lateral and vertical direction. CONCLUSIONS: The study illustrates the additional benefit of 3D imaging: consideration of the vertical component and computation of metric units. New, relevant, and even unexpected information was obtained by the incorporation of the additional vertical dimension. Metric units allow for an absolute evaluation of anatomy and dynamics and therefore enables cross-study comparability. The noninvasive acquisition of quantitative measures for evidence-based medicine has the potential to enhance diagnostic and therapeutic procedures as well as basic medical research. LEVEL OF EVIDENCE: 4. Laryngoscope, 128:2367-2374, 2018.
EVALuna2:209972

Cochleaimplantate für die bimodale Versorgung bei asymmetrischem Hörverlust - Hoppe, Ulrich; Wesarg, Thomas (HNO, 2023)
CRIS-Team Scopus Importer:2023-08-11

Cochlear implantation after canal wall down mastoidectomy — Outcomes after partial mastoid obliteration - Balk, Matthias; Schwarz, David; Wolber, Philipp; Anagiotos, Andreas; Gostian, Antoniu Oreste (Auris Nasus Larynx, 2019)
Objective: To describe and evaluate the partial mastoid obliteration of the so-called radical mastoid cavity after canal-wall down mastoidectomy (CWD) for cochlear implantation (CI) compared to overclosure of the external ear canal as two stage procedures. Methods: Out of 1020 patients undergoing cochlear implantation between January 1st, 2003 and June 15th, 2016 at the Department of Otolaryngology, Head & Neck Surgery, University Hospital Cologne, eight patients underwent obliteration of the radical cavity prior to cochlear implantation. In four additional patients, the external ear canal was overclosed prior to cochlear implantation. Results: Patients undergoing partial mastoid obliteration (five ♀, 4 left ears) and overclosure of the external ear canal (one ♀, 3 left ears) averaged 56 years and 61 years, respectively. The radical cavities had been present for 21.8 years on average before partial obliteration and for 19.5 years before overclosure. Cochlear implantation following mastoid obliteration was performed after a mean period of 5.1 months and 3.8 months after overclosure. After partial mastoid obliteration, complete insertion of all electrodes was achieved and the clinical courses were uneventful for all patients. Likewise, no patient revealed any complications after overclosure of the external ear canal. Conclusion: Partial mastoid obliteration with bone paté and cartilage after canal wall down mastoidectomy can be advocated as a feasible alternative technique that allows for a safe subsequent cochlear implantation.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Canal wall down mastoidectomy; Cochlear implantation; Overclosure of the external ear canal; Partial mastoid obliteration

Cochlear Implantation Following Explorative Tympanotomy in Patients With Sudden Sensorineural Hearing Loss: Surgical Features and Audiological Outcomes - Rupp, Robin; Hornung, Joachim; Balk, Matthias; Sievert, Matti; Müller, Susanna; Hoppe, Ulrich; Iro, Heinrich; Gostian, Antoniu Oreste (Ent-Ear Nose & Throat Journal, 2021)
Objective: To investigate the anatomical status of the round window niche and hearing outcome of cochlear implantation (CI) after explorative tympanotomy (ExT) with sealing of the round window membrane in patients with sudden sensorineural hearing loss at a tertiary referral medical center. Methods: Between January 1, 2007, and July 30, 2020, 1602 patients underwent CI at our department. Out of these, all patients previously treated by ExT with sealing of the round window membrane because of unilateral sudden hearing loss were included in the study. A retrospective chart review was conducted concerning method of round window membrane sealing, intraoperative findings during CI, postoperative imaging, and hearing results. Results: Twenty one patients (9 females; 8 right ears; 54.3 years [± 12.9 years]) underwent ExT with sealing of the round window membrane with subsequent CI after 26.6 months (± 32.9 mo) on average. During CI, in 76% of cases (n = 16), the round window niche was blocked by connective tissue due to the previous intervention but could be removed completely in all cases. The connective tissue itself and its removal had no detrimental effects on the round window membrane. Postoperative computed tomography scan showed no electrode dislocation. Mean postoperative word recognition score after 3 months was 57.4% (± 17.2%) and improved significantly to 73.1% (± 16.4%, P =.005) after 2 years. Conclusion: Performing CI after preceding ExT, connective tissue has to be expected blocking the round window niche. Remaining tissue can be removed safely and does not alter the round window membrane allowing for a proper electrode insertion. Short- and long-term hearing results are satisfactory. Consequently, ExT with sealing of the round window membrane in patients with sudden sensorineural hearing loss does not impede subsequent CI that can still be performed safely.
CRIS-Team Scopus Importer:2021-05-21
Keywords: cochlear implant; explorative tympanotomy; round window membrane sealing; sudden sensorineural hearing loss

Cochlear Implantation in Candidates With Moderate-to-Severe Hearing Loss and Poor Speech Perception - Hoppe, Ulrich; Hocke, Thomas; Hast, Anne; Iro, Heinrich (Laryngoscope, 2020)
Objectives/Hypothesis: To determine the improvement in word recognition score (WRS65) after cochlear implant (CI) surgery in hearing aid (HA) users with preoperative hearing threshold ≤80 dB HL and inadequate speech recognition scores with HA. Secondarily, to identify predictive factors for WRS65 with a CI (WRS65[CI]) 6 months after surgery, derived from the standard German CI preoperative assessment. Study Design: Retrospective chart review. Methods: Retrospective review of all adult patients who received a Nucleus cochlear implant in the ear, nose, and throat department of the University Hospital of Erlangen between January 2010 and April 2019. The inclusion criteria were a preoperative hearing threshold ≤80 dB HL in the ear to receive the implantation, German as the native language, and at least 6 months postimplantation care at our center. Results: The inclusion criteria were met by 128 patients. All but two patients (98.4%) showed a significant improvement, WRS65(CI) versus WRS65 with an (HA) (WRS65[HA]), of at least 15 percentage points (pp). The median improvement was 55 pp with a median WRS65(CI) of 70%. Three preoperative audiometric measures, the maximum word recognition score, age at implantation, and WRS65(HA) were identified as predictive factors for WRS65(CI). For three-quarters of the CI recipients, the score was not poorer than 12 pp below the predicted WRS65(CI). Conclusions: For patients with a hearing loss ≤80 dB HL, cochlear implantation should be considered when speech perception with an HA is insufficient. The prediction model can support counseling in this patient group. Level of Evidence: 4 Laryngoscope, 2020.
CRIS-Team Scopus Importer:2020-06-09
Keywords: adult; Cochlear implant; hearing aid; hearing threshold; speech audiometry

Cochlear implant fitting strategies - Hoppe, Ulrich; Liebscher, Tim; Hornung, Joachim (HNO, 2017)
Cochlear implant (CI) fitting is the technical adjustment of a CI processor to the individual needs of a subject. Fitting comprises the choice of stimulation strategy and determination of the lower and upper stimulation levels for the individual. This electrical dynamic range defines the stimulation range for the real-time functioning of the CI system. All of the CI manufacturers provide a large set of parameters which have to be optimized for proper hearing and speech comprehension. As a consequence of the widening of indication criteria for CIs and lowering the age of implantation for children, the fitting process has changed dramatically over the years. This includes replacement of behavioral responses by other data from objective electrophysiologic measures and from expert knowledge. Recent developments aim to structure and automatize the CI fitting process. This reduces the time requirement for CI fitting and leads to fast settings which can be tested in the real-time situation. This review provides an overview of state-of-the-art fitting procedures and recent developments for fitting strategies. These will be discussed with respect to practicability and quality assurance.
EVALuna2:33172

Cochlear implants in the social courts - Lottner, Anna; Iro, Heinrich; Schützenberger, Anne; Hoppe, Ulrich (HNO, 2018)
BACKGROUND: Since the indication for receiving a cochlear implant (CI) has widened (single-sided deafness [SSD], electric acoustic stimulation [EAS], bilateral CI, CI for long-term deafness), more and more patients come into consideration for such a treatment. Hence, disputes increasingly arise between patients and their insurance companies concerning the question of whether surgery and follow-up treatment have to be paid for by statutory health insurance. OBJECTIVE: This work provides an overview of judgments rendered by the German social courts. We investigated whether and in which cases it is advisable for a patient to go to court, and how long the proceedings may take. MATERIALS AND METHODS: We looked for judgments in the two biggest commercial legal databases and in the database of the German social courts, using combinations of the search parameters "Cochlear," "Cochlea," "Implant," and "Implantat." Three verdicts were attained by directly contacting the court; another one was mentioned in an article. The reviewed judgements were issued between 2003 and 2017. RESULTS: A total of 12 judgments were found. The patients won in all but one of the main proceedings. The case that was lost concerned exceptional circumstances. One patient didn't get the desired interim measure, but won in the main proceedings. The proceedings took between 1 year and 8 months, and 9 years and 5 months. CONCLUSION: Despite the amount of time the patient has to invest, taking legal action is worthwhile. The proceedings at the social courts are generally exempt from charges. In most cases, the statutory health insurance is ordered to pay for a CI.
EVALuna2:33194

Cochrane Review: Tympanic Tubes for Patients with acute Otitis Media - Waldfahrer, Frank (HNO, 2019)
CRIS-Team WoS Importer:2019-09-20

Coincidence detection and integration behavior in spiking neural networks - Stoll, Andreas; Maier, Andreas; Krauß, Patrick; Gerum, Richard; Schilling, Achim (Cognitive Neurodynamics, 2023)
Recently, the interest in spiking neural networks (SNNs) remarkably increased, as up to now some key advances of biological neural networks are still out of reach. Thus, the energy efficiency and the ability to dynamically react and adapt to input stimuli as observed in biological neurons is still difficult to achieve. One neuron model commonly used in SNNs is the leaky-integrate-and-fire (LIF) neuron. LIF neurons already show interesting dynamics and can be run in two operation modes: coincidence detectors for low and integrators for high membrane decay times, respectively. However, the emergence of these modes in SNNs and the consequence on network performance and information processing ability is still elusive. In this study, we examine the effect of different decay times in SNNs trained with a surrogate-gradient-based approach. We propose two measures that allow to determine the operation mode of LIF neurons: the number of contributing input spikes and the effective integration interval. We show that coincidence detection is characterized by a low number of input spikes as well as short integration intervals, whereas integration behavior is related to many input spikes over long integration intervals. We find the two measures to linearly correlate via a correlation factor that depends on the decay time. Thus, the correlation factor as function of the decay time shows a powerlaw behavior, which could be an intrinsic property of LIF networks. We argue that our work could be a starting point to further explore the operation modes in SNNs to boost efficiency and biological plausibility.
CRIS-Team Scopus Importer:2023-12-22
Keywords: Artificial intelligence; Coincidence detection; Computational modeling; Leaky-integrate-and-fire neuron; Neural networks

Collagen/silica nanocomposites and hybrids for bone tissue engineering - Sarker, Bapi; Lyer, Stefan; Arkudas, Andreas; Boccaccini, Aldo R. (Nanotechnology Reviews, 2013)
UnivIS-Import:2015-04-14:Pub.2013.tech.IW.LM.collag

Comparative analysis of human dendritic cell subpopulations in steady state and inflammation - Heger, Lukas; Heidkamp, Gordon Frederik; Lehmann, Christian; Eissing, N.; Söder, Stephan; Hartmann, Arndt; Zenk, J.; Alexiou, Christoph; Schuler, Gerold; Purbojo, Ariawan; Cesnjevar, Robert; Nimmerjahn, Falk; et al. (2017)
EVALuna2:33136

Comparative analysis of human dendritic cell subpopulations in steady state and inflammation - Heger, Lukas; Heidkamp, Gordon Frederik; Lehmann, Christian; Söder, Stephan; Hartmann, Arndt; Alexiou, Christoph; Schuler, Gerold; Purbojo, Ariawan; Cesnjevar, Robert; Nimmerjahn, Falk; Dudziak, Diana (2018)
EVALuna2:34382

Comparative analysis of nanosystems' effects on human endothelial and monocytic cell functions - Matuszak, Jasmin; Doerfler, Philipp; Lyer, Stefan; Unterweger, Harald; Juenet, Maya; Chauvierre, Cedric; Alaarg, Amr; Franke, Danielle; Almer, Gunter; Texier, Isabelle; Metselaar, Josbert M.; Prassl, Ruth; et al. (Nanotoxicology, 2018)
The objective of our work was to investigate the effects of different types of nanoparticles on endothelial (HUVEC) and monocytic cell functions. We prepared and tested 14 different nanosystems comprising liposomes, lipid nanoparticles, polymer, and iron oxide nanoparticles. Some of the tested nanosystems contained targeting, therapeutic, or contrast agent(s). The effect of particles (0-400 mu g/mL) on endothelial-monocytic cell interactions in response to TNF-alpha was investigated using an arterial bifurcation model and dynamic monocyte adhesion assay. Spontaneous HUVEC migration (0-100 mu g/mL nanoparticles) and chemotaxis of monocytic cells towards MCP-1 in presence of particles (0-400 mu g/mL) were determined using a barrier assay and a modified Boyden chamber assay, respectively. Lipid nanoparticles dose-dependently reduced monocytic cell chemotaxis and adhesion to activated HUVECs. Liposomal nanoparticles had little effect on cell migration, but one formulation induced monocytic cell recruitment by HUVECs under non-uniform shear stress by about 50%. Fucoidan-coated polymer nanoparticles (25-50 mu g/mL) inhibited HUVEC migration and monocytic cell chemotaxis, and had a suppressive effect on monocytic cell recruitment under non-uniform shear stress. No significant effects of iron oxide nanoparticles on monocytic cell recruitment were observed except lauric acid and human albumin-coated particles which increased endothelial-monocytic interactions by 60-70%. Some of the iron oxide nanoparticles inhibited HUVEC migration and monocytic cell chemotaxis. These nanoparticle-induced effects are of importance for vascular cell biology and function and must be considered before the potential clinical use of some of the analyzed nanosystems in cardiovascular applications.
CRIS-Team WoS Importer:2019-03-06

Comparative analysis of titanium clip prostheses for partial ossiculoplasty - Mantsopoulos, Konstantinos; Thimsen, Vivian; Taha, Lava; Eisenhut, Felix; Müller-Hübner, Sarina; Sievert, Matti; Iro, Heinrich; Hornung, Joachim (American Journal of Otolaryngology, 2021)
Objectives: The aim of our study was to perform a comparative analysis in our cases with titanium partial clip ossiculoplasty in terms of audiometric outcome and extrusion rates as well as to review the literature for relevant information on this surgical issue. Materials and methods: The records of all patients who had undergone primary partial ossiculoplasty with the implantation of a CliP® Partial Prosthesis Dresden Type (CPPDT, group A) or a CliP Partial FlexiBAL® (CPF, Group B, both Heinz Kurz GmbH, Dusslingen, Germany) between 2012 and 2020 were studied retrospectively. Results: 274 patients made up our study sample (148 men, 126 women, male to female ratio: 1.17). Their mean age at the time of first surgery was 39.6 years (range: 4–79 years). The mean preoperative air-bone gap (ABG) was 22.7dΒ ± 10.5 dB. Mean follow-up was approximately 4 months (1–12 months). The mean postoperative ABG was 15.7 ± 8.1 dB. In total, the postoperative ABG was significantly improved compared to preoperative values (P < 0.001). Surgical success, defined as an ABG ≤ 20 dB, was achieved in the majority of our study patients (210/274, 76.6%). Extrusion of the prosthesis was detected in 3/216 CPF and 5/58 CPPDT cases (p = 0.012). Comparison of both prosthesis groups revealed a significantly better audiological outcome for the patients with ossicular reconstruction using CPF. A significantly better audiological outcome was detected in the cases with a normal aeration of the middle ear. Discussion: Titanium clip partial ossiculoplasty is a reliable component of modern tympanoplasty, allowing a satisfying audiologic outcome. The higher adaptability of the CPF to the changing postoperative circumstances and the frequently defective aeration of the middle ear is reflected in the better audiologic outcome for this prosthesis.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Air-bone gap; Middle ear; Ossiculoplasty; Outcome; Partial prosthesis; PORP

Comparative Evaluation of a New Sensor for Superparamagnetic Iron Oxide Nanoparticles in a Molecular Communication Setting - Bartunik, Max; Unterweger, Harald; Alexiou, Christoph; Schober, Robert; Lübke, Maximilian; Fischer, Georg; Kirchner, Jens (EAI BICT 2020 - 12th EAI International Conference on Bio-inspired Information and Communications Technologies, 2020)
Testbeds are required to assess concepts and devices in the context of molecular communication. These allow the observation of real-life phenomena in a controlled environment and therefore present the basis of future work. A testbed using superparamagnetic iron oxide nanoparticles (SPIONs) as information carriers was constructed with regard to this context and requires a sensitive receiver for the detection of SPIONs. This paper focusses on the comparison between a newly presented device (inductance sensor), a previously constructed SPION sensor (resonance bridge), and a commercial susceptometer as reference. The new inductance sensor is intended to improve on a low sensitivity achieved with the previous device and restrictions with respect to sample rate and measurement aperture encountered with the susceptometer. The signal-to-noise ratio (SNR) for each device is assessed at a variety of SPION concentrations. Furthermore, the sensors bit error rates (BER) for a random bit sequence are determined. The results show the device based on an inductance sensor to be the most promising for further investigation as values both for BER and SNR exceed those of the resonance bridge while providing a suciently high sample rate. On average the SNR of the new device is 13 dB higher while the BER for the worst transmission scenario is 9% lower. The commercial susceptometer, although returning the highest SNR, lacks adaptability for the given use case.<br
Keywords: Molecular Communication; Superparamagnetic Iron Oxide; Nanoparticles; SPION; Testbed; Susceptometer; Resonance Bridge; Inductance Sensor; SNR; BER

Comparative in vitro and in vivo Evaluation of Different Iron Oxide-Based Contrast Agents to Promote Clinical Translation in Compliance with Patient Safety - Unterweger, Harald; Janko, Christina; Folk, Tamara; Cicha, Iwona; Kovacs, Noemi; Gyebnar, Gyula; Horvath, Ildiko; Mathe, Domokos; Zheng, Kang H.; Coolen, Bram F.; Stroes, Erik; Szebeni, Janos; et al. (International Journal of Nanomedicine, 2023)
Introduction: One of the major challenges in the clinical translation of nanoparticles is the development of formulations combining favorable efficacy and optimal safety. In the past, iron oxide nanoparticles have been introduced as an alternative for gadolinium-containing contrast agents; however, candidates available at the time were not free from adverse effects. Methods: Following the development of a potent iron oxide-based contrast agent SPIONDex, we now performed a systematic comparison of this formulation with the conventional contrast agent ferucarbotran and with ferumoxytol, taking into consideration their physicochemical characteristics, bio-and hemocompatibility in vitro and in vivo, as well as their liver imaging properties in rats. Results: The results demonstrated superior in vitro cyto-, hemo-and immunocompatibility of SPIONDex in comparison to the other two formulations. Intravenous administration of ferucarbotran or ferumoxytol induced strong complement activation-related pseu-doallergy in pigs. In contrast, SPIONDex did not elicit any hypersensitivity reactions in the experimental animals. In a rat model, comparable liver imaging properties, but a faster clearance was demonstrated for SPIONDex. Conclusion: The results indicate that SPIONDex possess an exceptional safety compared to the other two formulations, making them a promising candidate for further clinical translation.
CRIS-Team Scopus Importer:2023-05-26
Keywords: CARPA; complement activation; magnetic resonance imaging; MRI; nanomedicine; nanoparticles

Comparison of acoustic and laryngeal parameters between healthy and disordered subjects - Schlegel, Patrick; Kniesburges, Stefan; Dürr, Stephan; Döllinger, Michael; Schützenberger, Anne (Proceedings of the International Congress on Acoustics, 2019)
In voice research and clinics, various mathematical parameters are in use to describe different features of the recorded data. However, little is known about norm values of parameters and how they are affected by different pathologies such as functional dysphonia.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Functional dysphonia; High-speed video endoscopy; Parameters; Phonation

Comparison of bimodal benefit for the use of DSL v5.0 and NAL-NL2 in cochlear implant listeners - Digeser, Frank; Engler, Max; Hoppe, Ulrich (International Journal of Audiology, 2019)
Objective: For a group of bimodal subjects with moderate to severe hearing loss contralateral to the cochlear implant (CI), the bimodal benefit of the hearing aid (HA) gain prescriptions DSL v5.0, NAL-NL2 and the recipients' own gain setting were assessed. Design: Speech perception in quiet and in noise as well as self-reported ratings of benefit were determined for all three gain-settings. Speech tests were performed in the bimodal, the HA alone and the CI alone condition. The bimodal benefit was assessed for each prescription as the difference score of the bimodal condition and the better ear. Study Sample: Twenty adults with post-lingual hearing loss. Results: Speech perception with DSL v5.0 was significantly higher compared to NAL-NL2 and the own prescription in both quiet and noise. The median bimodal benefit was highest for DSL v5.0 with an average of 15 percentage points for both words in quiet and sentences in noise. Conclusions: DSL v5.0 and NAL-NL2 are both suitable for HA fitting in bimodal users. For subjects with moderate to severe hearing loss and HA experience contralateral to the implanted side, DSL v5.0 may provide better speech perception and bimodal benefit.
CRIS-Team WoS Importer:2019-12-17

Comparison of mucus and serum biomarker sampling in chronic rhinosinusitis with nasal polyps - Müller-Hübner, Sarina; Wendler, Olaf; Mayr, Susanne; Traxdorf, Maximilian; Koch, Michael; Mantsopoulos, Konstantinos; Sievert, Matti; Grundtner, Philipp; Iro, Heinrich; Bleier, Benjamin S. (International Forum of Allergy and Rhinology, 2023)
Objective: The objective of this study was to analyze advantages and disadvantages of mucus and serum for biomarker analysis. Methods: This study includes prospective study of 61 CRS with nasal polyps patients who were followed over 24 months and over nine time points after functional endoscopic sinus surgery. At each time points, the nasal polyp score (NPS) was assessed and mucus as well as serum was collected. Selected were measured in mucus and serum. Mean, standard deviation and variance, undetectable values, and the correlation of the biomarkers to the NPS over time and to early recurrences were calculated, and the effect of surgery on the biomarkers was assessed. Additionally, the diurnal rhythm of all biomarkers was measures in order to assure stable biomarker values during sampling times. Results: All biomarkers showed stable values during sampling times. Serum biomarker levels displayed higher percentages of undetectable values compared to mucus biomarkers. Mucus periostin (p < 0.001, r = 0.89), mucus IgE (p < 0.001, r = 0.51), serum periostin (p < 0.001, r = 0.53), mucus CST1 (p < 0.001, r = 0.27), and serum IgE (p < 0.01, r = −0.18) were the best marker and medium combinations to track the NPS over time and to predict recurrences. Mucus serpinF2 was negatively correlated and predicted early recurrences (p = 0.026, R2 = 0.015). Conclusions: Serum and mucus both represent viable mediums for “liquid biopsies.” The most promising biomarker/medium combinations over time to track disease severity were mucus periostin, mucus IgE, serum periostin, mucus CST1, and serum IgE. Mucus serpinF2 was the best biomarker to predict early recurrences.
CRIS-Team Scopus Importer:2023-12-01
Keywords: biomarker; chronic rhinosinusitis; eosinophilic rhinitis; nasal polyposis

Comparison of vestibular schwannoma visualization between 0.55 T and 1.5 T MRI - Wiesmüller, Marco; Kopp, Markus; Sievert, Matti; May, Matthias; Nagel, Armin Michael; Iro, Heinrich; Uder, Michael; Heiß, Rafael (European Journal of Radiology, 2023)
Objectives: Vestibular schwannoma (VS) is the most common mass of the internal auditory canal (IAC) and is responsible for unilateral sensorineural hearing loss. Magnetic resonance imaging (MRI) at 1.5 T and 3 T is the standard of care for the evaluation of VS, and the feasibility of using modern low-field MRI for imaging of the IAC has not yet been elucidated. Hence, the purpose of this prospective study was to assess image quality and diagnostic performance of a modern 0.55 T MRI. Materials and Methods: Fifty-six patients with known unilateral VS underwent routine MRI of the IAC at 1.5 T, followed immediately by 0.55 T MRI. Two radiologists independently evaluated the image quality, conspicuity of VS, diagnostic confidence, and image artifacts separately for isotropic T2-weighted SPACE images and for transversal and coronal T1-weighted fat-saturated contrast-enhanced images at 1.5 T and 0.55 T using 5-point Likert scales. In a second independent reading, both readers assessed lesion conspicuity and subjective diagnostic confidence in a direct comparison of 1.5 T and 0.55 T images. Results: Image quality of transversal T1-weighted images (p = 0.13 and p = 0.16 for Reader 1 and Reader 2, respectively) and T2-weighted SPACE images (p = 0.39 and p = 0.58) were rated equally at 1.5 T and 0.55 T by both readers, whereas image quality of coronal T1-weighted images was superior at 1.5 T (p = 0.009 and p = 0.001). Analysis of the conspicuity of VS, diagnostic confidence, and image artifacts of all sequences revealed no significant differences between 1.5 T and 0.55 T. In the direct comparison of 1.5 T with 0.55 T images, there were no significant differences in lesion conspicuity or diagnostic confidence for any sequence (p = 0.60–0.73). Conclusions: Modern low-field MRI at 0.55 T provided a sufficient diagnostic image quality and seems feasible for the evaluation of VS of the IAC.
CRIS-Team Scopus Importer:2023-07-28
Keywords: 0.55T MRI; Acoustic neuroma; Image quality; Inner auditory canal; low-field MRI; Vestibular schwannoma

Completion surgery after extracapsular dissection of low-grade parotid gland malignant tumors - Mantsopoulos, Konstantinos; Mueller, Sarina K.; Goncalves, Miguel; Koch, Michael; Iro, Heinrich (Head and Neck-Journal For the Sciences and Specialties of the Head and Neck, 2019)
Background: The aim of the study was to compare the oncological and functional outcome between extracapsular dissection and completion surgery on the one hand and sole extracapsular dissection on the other hand in small low-grade malignant parotid tumors. Methods: The records of all patients treated for T1-T2 low-grade malignant tumors of the parotid gland primarily by means of extracapsular dissection between 2006 and 2015 were studied retrospectively. Results: Forty patients with T1-T2 low-grade parotid malignancies were detected. Our study showed outstanding oncological outcomes in both patient groups, the facial nerve function being significantly better after sole extracapsular dissection in the direct postoperative phase, with no differences between the groups in the long term. Conclusions: Our study showed very encouraging preliminary results following primary extracapsular dissection as the sole surgical therapy for carefully selected low-stage, low-grade, inferiorly located lesions in patients with high compliance.
CRIS-Team Scopus Importer:2019-07-16
Keywords: extracapsular dissection; facial nerve; low-grade; malignant tumor; parotid gland

Complex midfacial defects: Is the extended Abbé flap the ideal solution to a tough problem? - Mantsopoulos, Konstantinos; Iro, Heinrich; Constantinidis, Jannis (Oral Oncology, 2020)
Objectives: The aim of this study was to investigate the role of the extended Abbé flap in the reconstruction of complex midfacial defects (upper lip, nasal base and medial cheek). We describe our personal experience with this method and present some interesting aspects from the relevant literature. Materials and methods: Between 2003 and 2017 we retrospectively evaluated the records of all patients with defects of the upper lip and nasal base after the resection of malignant tumors or traumata and reconstruction by means of the extended Abbé flap. We looked for information on the origin of the defect, the functional result, the aesthetic outcome and postoperative complications. The functional result of the reconstruction of the oral commissure was assessed with regard to postoperative subjective speech integrity, preservation of competence of the oral sphincter and lip sensation. The aesthetic outcome was evaluated with regard to limitations in facial expression and scar formation. Results: The study included 8 patients. Follow–up in the oncological cases was 85 months (range: 20–150 months). No tumor recurrences were detected. All patients achieved normal oral competence and mouth opening. No cases of blunting or microstomia were detected. Conclusion: Reconstruction of the upper lip and nasal base with the extended Abbé flap is associated with an outstanding functional outcome that is cosmetically very acceptable.
CRIS-Team Scopus Importer:2020-01-21
Keywords: Extended Abbé flap; Microstomia; Nasal base; Perioral defect; Upper lip

Complications of tracheoesophageal shunts after laryngectomy - Scherl, C.; Kauffels, J.; Schützenberger, Anne; Döllinger, Michael; Bohr, Christopher; Koch, Matthias; Traxdorf, Maximilian; Iro, Heinrich (2018)
EVALuna2:35392

Computational fluid dynamics of upper airway aerodynamics for exercise-induced laryngeal obstruction: A feasibility study - Döllinger, Michael; Jakubaß, Bernhard; Cheng, Hu; Carter, Stephen J.; Kniesburges, Stefan; Aidoo, Bea; Lee, Chi Hwan; Milstein, Claudio; Patel, Rita R. (Laryngoscope Investigative Otolaryngology, 2023)
Objective: Use of computational fluid dynamic (CFD) simulations to measure the changes in upper airway geometry and aerodynamics during (a) an episode of Exercise-Induced Laryngeal Obstruction (EILO) and (b) speech therapy exercises commonly employed for patients with EILO. Methods: Magnetic resonance imaging stills of the upper airway including the nasal and oral cavities from an adult female were used to re-construct three-dimensional geometries of the upper airway. The CFD simulations were used to compute the maximum volume flow rate (l/s), pressure (Pa), airflow velocity (m/s) and area of cross-section opening in eight planes along the vocal tract, separately for inhalation and exhalation. Results: Numerical predictions from three-dimensional geometrical modeling of the upper airway suggest that the technique of nose breathing for inhalation and pursed lip breathing for exhalation show most promising pressure conditions and cross-sectional diameters for rescue breathing exercises. Also, if EILO is due to the constriction at the vocal fold level, then a quick sniff may also be a proper rescue inhalation exercise. EILO affects both the inspiratory and the expiratory phases of breathing. Conclusions: A prior knowledge of the supraglottal aerodynamics and the corresponding upper airway geometry from CFD analysis has the potential to assist the clinician in choosing the most effective rescue breathing technique for optimal functional outcome of speech therapy intervention in patients with EILO and in understanding the pathophysiology of EILO on a case-by-case basis with future studies. Level of Evidence: 4.
CRIS-Team Scopus Importer:2023-09-01
Keywords: computational fluid dynamics (CFD); exercise-induced laryngeal obstruction (EILO); paradoxical vocal fold motion; speech therapy; voice therapy

Computational hydrodynamics of a typical 3-fin surfboard setup - Falk, Sebastian; Kniesburges, Stefan; Janka, Rolf Matthias; Grosso, Roberto; Becker, Stefan; Semmler, Marion; Döllinger, Michael (Journal of Fluids and Structures, 2019)
Surfing is becoming increasingly popular, and the economic market for surfing products is growing. The performance of the surfboards and the fins has evolved continuously through the experience and innovative spirit of surfers and shapers. However, provided performance characteristics are only subjective and of descriptive nature. Therefore, we apply and analyze objective performance indicators as (1) lift and drag coefficient for each fin and the entire configuration and (2) lift-to-drag ratio for the entire fin configuration. This numerical study investigated a commercial 3-fin configuration, mounted into a rectangular simulation region, considering the flow at several different angles of attack between 0°and 45°. RANS and URANS simulations were performed with the SST k−ω turbulence model at an inflow velocity of 5 m/s. Simulation results showed that the fins have an optimal range of attack angles where they produce the most lift. The lift forces generate a turning moment which forces the board to be turned in direction to the shore favoring the controllability and stability of the surfboard. The higher the angle of attack, the higher is the drag coefficient. Lift-to-drag ratio values showed that for speeding up small attack angles with low drag forces are preferable. Furthermore, unsteady effects as flow separation combined with vortex shedding occur at high angles of attack above 20°which can only be resolved by URANS simulations. These unsteady effects have high negative influences on stability due to high fluctuation amplitudes for lift and drag forces. In summary, this study presents, to the best of the authors’ knowledge, for the first time, steady and unsteady forces on surfboard fins and discusses their potential influences on the surfer's controllability and stability of the surfboard during typical surfing maneuvers.
CRIS-Team Scopus Importer:2019-08-02
Keywords: Computational fluid dynamics (CFD); Fins; Hydrodynamics; STAR-CCM+; Surfboard; Surfing

Computational Models of Laryngeal Aerodynamics: Potentials and Numerical Costs - Sadeghi, Hossein; Kniesburges, Stefan; Kaltenbacher, Manfred; Schützenberger, Anne; Döllinger, Michael (Journal of Voice, 2019)
Human phonation is based on the interaction between tracheal airflow and laryngeal dynamics. This fluid-structure interaction is based on the energy exchange between airflow and vocal folds. Major challenges in analyzing the phonatory process in-vivo are the small dimensions and the poor accessibility of the region of interest. For improved analysis of the phonatory process, numerical simulations of the airflow and the vocal fold dynamics have been suggested. Even though most of the models reproduced the phonatory process fairly well, development of comprehensive larynx models is still a subject of research. In the context of clinical application, physiological accuracy and computational model efficiency are of great interest. In this study, a simple numerical larynx model is introduced that incorporates the laryngeal fluid flow. It is based on a synthetic experimental model with silicone vocal folds. The degree of realism was successively increased in separate computational models and each model was simulated for 10 oscillation cycles. Results show that relevant features of the laryngeal flow field, such as glottal jet deflection, develop even when applying rather simple static models with oscillating flow rates. Including further phonatory components such as vocal fold motion, mucosal wave propagation, and ventricular folds, the simulations show phonatory key features like intraglottal flow separation and increased flow rate in presence of ventricular folds. The simulation time on 100 CPU cores ranged between 25 and 290 hours, currently restricting clinical application of these models. Nevertheless, results show high potential of numerical simulations for better understanding of phonatory process.
CRIS-Team Scopus Importer:2019-07-30
Keywords: Computational cost; Glottal aerodynamics; Human phonation; Large eddy simulation; Numerical larynx model

Computation of physiological human vocal fold parameters by mathematical optimization of a biomechanical model. - Yang, Anxiong; Stingl, Michael; Berry, David A.; Lohscheller, Jörg; Voigt, Daniel; Eysholdt, Ulrich; Döllinger, Michael (Journal of the Acoustical Society of America, 2011)
With the use of an endoscopic, high-speed camera, vocal fold dynamics may be observed clinically during phonation. However, observation and subjective judgment alone may be insufficient for clinical diagnosis and documentation of improved vocal function, especially when the laryngeal disease lacks any clear morphological presentation. In this study, biomechanical parameters of the vocal folds are computed by adjusting the corresponding parameters of a three-dimensional model until the dynamics of both systems are similar. First, a mathematical optimization method is presented. Next, model parameters (such as pressure, tension and masses) are adjusted to reproduce vocal fold dynamics, and the deduced parameters are physiologically interpreted. Various combinations of global and local optimization techniques are attempted. Evaluation of the optimization procedure is performed using 50 synthetically generated data sets. The results show sufficient reliability, including 0.07 normalized error, 96% correlation, and 91% accuracy. The technique is also demonstrated on data from human hemilarynx experiments, in which a low normalized error (0.16) and high correlation (84%) values were achieved. In the future, this technique may be applied to clinical high-speed images, yielding objective measures with which to document improved vocal function of patients with voice disorders.

Computer-based auditory phoneme discrimination training improves speech recognition in noise in experienced adult cochlear implant listeners - Schumann, Annette; Serman, Maja; Gefeller, Olaf; Hoppe, Ulrich (International Journal of Audiology, 2015)
Abstract Objective: Specific computer-based auditory training may be a useful completion in the rehabilitation process for cochlear implant (CI) listeners to achieve sufficient speech intelligibility. This study evaluated the effectiveness of a computerized, phoneme-discrimination training programme.The study employed a pretest-post-test design; participants were randomly assigned to the training or control group. Over a period of three weeks, the training group was instructed to train in phoneme discrimination via computer, twice a week. Sentence recognition in different noise conditions (moderate to difficult) was tested pre- and post-training, and six months after the training was completed. The control group was tested and retested within one month.Twenty-seven adult CI listeners who had been using cochlear implants for more than two years participated in the programme; 15 adults in the training group, 12 adults in the control group.Besides significant improvements for the trained phoneme-identification task, a generalized training effect was noted via significantly improved sentence recognition in moderate noise. No significant changes were noted in the difficult noise conditions. Improved performance was maintained over an extended period.Phoneme-discrimination training improves experienced CI listeners' speech perception in noise. Additional research is needed to optimize auditory training for individual benefit.
EVALuna2:5466

Conceptual Cognitive Maps Formation with Neural Successor Networks and Word Embeddings - Stöwer, Paul; Schilling, Achim; Maier, Andreas; Krauß, Patrick (IEEE International Conference on Development and Learning 2023 (ICDL), 2023)

Confocal laser endomicroscopy of head and neck squamous cell carcinoma: a systematic review Konfokale Laser-Endomikroskopie des Kopf-Hals-Plattenepithelkarzinoms: eine systematische Übersicht - Sievert, Matti; Auberville, Marc; Oetter, Nicolai; Stelzle, Florian; Maier, Andreas; Mantsopoulos, Konstantinos; Iro, Heinrich; Goncalves, Miguel (Laryngo-Rhino-Otologie, 2021)
Objective: Confocal laser endomicroscopy (CLE), with a magnification of up to 1000 ×, offers the possibility to visualize intercellular spaces in vivo. CLE has already established itself in different disciplines. This article gives an overview of the current research on CLE in the diagnosis of the head and neck squamous cell carcinoma. Material and methods: Material and methods: Systematic bibliographic research in the following online databases: PubMed, MEDLINE, Thompson Reuters Web of Science, SPIE using the following keywords: confocal laser endomicroscopy, CLE, endomicroscopy, head and neck, larynx. Evaluation of the scientific relevance according to defined criteria. Results: All studies were analyzed concerning the clinical application, clinical findings, and computer-aided data processing. Conclusions: The recently published data suggest that CLE has a high potential to improve the diagnosis of malignant mucosal lesions in the upper aerodigestive tract.
CRIS-Team Scopus Importer:2021-01-22
Keywords: CLE; confocal laser endomicroscopy; head and neck malignancy; image analysis; laryngeal carcinoma

Consensus definition of sarcopenia, cachexia and pre-cachexia: Joint document elaborated by Special Interest Groups (SIG) "cachexia-anorexia in chronic wasting diseases" and "nutrition in geriatrics" - Muscaritoli, M.; Anker, S. D.; Argiles, J.; Aversa, Z.; Bauer, Judith; Biolo, Gianni; Boirie, Y.; Bosaeus, I.; Cederholm, T.; Costelli, P.; Fearon, K. C.; Laviano, A.; et al. (Clinical Nutrition, 2010)
Chronic diseases as well as aging are frequently associated with deterioration of nutritional status, loss muscle mass and function (i.e. sarcopenia), impaired quality of life and increased risk for morbidity and mortality. Although simple and effective tools for the accurate screening, diagnosis and treatment of malnutrition have been developed during the recent years, its prevalence still remains disappointingly high and its impact on morbidity, mortality and quality of life clinically significant. Based on these premises, the Special Interest Group (SIG) on cachexia-anorexia in chronic wasting diseases was created within ESPEN with the aim of developing and spreading the knowledge on the basic and clinical aspects of cachexia and anorexia as well as of increasing the awareness of cachexia among health professionals and care givers. The definition, the assessment and the staging of cachexia, were identified as a priority by the SIG. This consensus paper reports the definition of cachexia, pre-cachexia and sarcopenia as well as the criteria for the differentiation between cachexia and other conditions associated with sarcopenia, which have been developed in cooperation with the ESPEN SIG on nutrition in geriatrics. (C) 2009 Elsevier Ltd and European Society for Clinical Nutrition and Metabolism. All rights reserved.
Keywords: Chronic diseases; Aging; Pre-cachexia; Cachexia; Anorexia; Sarcopenia

Considerations for Continuing Semielective and Emergency Otolaryngological Procedures During the COVID-19 Pandemic - Mueller, Sarina K.; Traxdorf, Maximilian; Mantsopoulos, Konstantinos; Gostian, Antoniu Oreste; Sievert, Matti; Koch, Michael; Hübner, Matthias; Iro, Heinrich (Ent-Ear Nose & Throat Journal, 2020)
Introduction: During the COVID-19 pandemic, worldwide over 600,000 human beings died due to the cause of the disease. In order to deescalate the transmission rate and to avoid crush loading the countries medical health systems social distancing, face masks, and lockdowns have been considered essential by the majority of governments. Whereas some countries have highly reduced or completely stopped otorhinolaryngological procedures, other countries have continued selected surgeries. The objective of this study was to analyze procedures and outcomes of continuing semielective and emergency surgeries during the COVID-19 pandemic. Methods: Retrospective analysis of n = 750 patients who received semi-elective or emergency surgery between March 26 and June 16, 2020, in the Otolaryngology Department of the Friedrich-Alexander-University of Erlangen-Nürnberg. All patients were screened for COVID symptoms and swabbed for SARS-CoV-2 prior to surgery. Results: Of the n = 750 patients, n = 699 patients received semielective surgery and n = 51 emergency surgery. For 27 patients, the swab result could not be awaited due to a life-threatening condition. In these cases, surgery was performed in full protective equipment. No patient was tested positive during or after the surgery (follow-up 45 to 127 days). No member of the medical personnel showed symptoms or was tested positive after contact with patients. Due to the continuation of surgeries, patients’ lives were saved and improvement of long-term quality-of-life and outcomes is anticipated. Conclusions: Continuing selected otorhinolaryngological surgeries is crucial for patients’ health, survival, and long-time quality of life, yet, the protection of the medical personnel has to be granted.
CRIS-Team Scopus Importer:2020-09-18
Keywords: COVID-19; false-negative; otorhinolaryngological procedures; patient’s health; SARS-CoV-2 test

Contact Guidance by Microstructured Gelatin Hydrogels for Prospective Tissue Engineering Applications - Tadsen, Meike; Friedrich, Ralf P.; Riedel, Stefanie; Alexiou, Christoph; Mayr, Stefan G. (ACS Applied Materials and Interfaces, 2019)
Design of functionalized biomimetic scaffolds is one of the key approaches for regenerative medicine and other biomedical applications. Development of engineered tissue should optimize organization and function of cells and tissue in vitro as well as in vivo. Surface topography is one factor controlling cellular behavior and tissue development. By topographical patterning of biocompatible materials, highly functionalized scaffolds can be developed. Gelatin is hereby a promising candidate due to its biocompatibility and biodegradability. It is low in cost and easy to handle, enabling a variety of applications in science and medicine. However, for biomedical applications at physiological conditions, gelatin has to be additionally stabilized since its gel-sol-transition temperature lies beneath the human body temperature. This is realized by a reagent-free cross-linking technique utilizing electron beam treatment. By topographical patterning, gelatin can be functionalized toward scaffolds for cell cultivation and tissue development. Thereby, customized patterns are transferred onto gelatin hydrogels via molds. Thermal stabilization of gelatin is then achieved by electron-induced cross-linking. In this study, we investigate the influence of gelatin concentration and irradiation dose on pattern transfer, long-term stability of topographically patterned gelatin hydrogels, and their impact on the cellular behavior of human umbilical vein endothelial cells as well as normal human dermal fibroblasts. We will show that contact guidance occurs for both cell types due to a concrete stripe pattern. In addition, the presented studies show a high degree of cytocompatibility, indicating a high potential of topographically patterned gelatin hydrogels as tissue development scaffold for prospective biomedical applications.
CRIS-Team WoS Importer:2019-03-12

Contactless Nanoparticle-Based Guiding of Cells by Controllable Magnetic Fields. - Blumler, Peter; Friedrich, Ralf P.; Pereira, Jorge; Baun, Olga; Alexiou, Christoph; Mailander, Volker (Nanotechnology, Science and Applications, 2021)
Controlled and contactless movements of magnetic nanoparticles are crucial for fundamental biotechnological and clinical research (eg, cell manipulation and sorting, hyperthermia, and magnetic drug targeting). However, the key technological question, how to generate suitable magnetic fields on various length scales (µm-m), is still unsolved. Here, we present a system of permanent magnets which allows for steering of iron oxide nanoparticles (SPIONs) on arbitrary trajectories observable by microscopy. The movement of the particles is simply controlled by an almost force-free rotation of cylindrical arrangements of permanent magnets. The same instrument can be used to move suspended cells loaded with SPIONs along with predetermined directions. Surprisingly, it also allows for controlled movements of intracellular compartments inside of individual cells. The exclusive use of permanent magnets simplifies scaled up versions for animals or even humans, which would open the door for remotely controlled in vivo guidance of nanoparticles or micro-robots.
EVALuna2:472947

Control of Fundamental Frequency in Dysphonic Patients During Phonation and Speech - Ziethe, A.; Petermann, Simon; Hoppe, Ulrich; Greiner, Nicole; Brüning, Marina; Bohr, Christopher; Döllinger, Michael (Journal of Voice, 2019)
Purpose: The pitch-shift reflex (PSR) is the adaptation of the fundamental frequency during phonation and speech and describes the auditory feedback control. Speakers without voice and speech disorders mostly show a compensation of the pitch change in the auditory feedback and adapt their fundamental frequency to the opposite direction. Dysphonic patients often display problems with the auditory perception and control of their voice during therapy. Our study focuses on the auditory and kinesthetic control mechanisms of patients with muscle tension dysphonia (MTD) and speakers without voice and speech problems. Main purpose of the study is the analysis of the functionality of the control mechanisms within phonation and speech between patients with MTD and normal speakers. Method: Sixty-one healthy subjects (17 male, 44 female) and 22 patients with MTD (7 male, 15 female) participated following two paradigms including a sustained phonation (vowel /a/) and speech ([‘mama]). Within both paradigms the fundamental frequency of the auditory feedback was increased synthetically. For the analysis of the PSR the electroencephalogram, electroglottography, the voice signal, and the high-speed endoscopy data were recorded simultaneously. The PSR in the electroencephalogram was detected via the N100 and the mismatch negativity. Statistical tests were applied for the detection of the PSR in the physiological response within the electroglottography, voice, and high-speed endoscopy signals. The results were compared between both groups. Results: No differences were found between the controls and patients with MTD regarding latency and magnitude of the perception of the pitch shift in both paradigms, but for the magnitude of the behavioral response. Differences also could be found for both groups between the “no pitch” and “pitch” condition of the two paradigms regarding vocal fold dynamics and voice quality. Patients with MTD showed more vibrational irregularities during the PSR than the controls, especially regarding the symmetry of vocal fold dynamics. Conclusion: Patients with MTD seem to have a disturbed interaction between the auditory and kinesthetic feedback inducing the execution of an overriding behavioral response.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Auditory feedback; Kinesthetic feedback; Muscle tension dysphonia; Pitch-shift reflex; voice quality

Control of noise-induced coherent oscillations in three-neuron motifs - Boensel, Florian; Krauß, Patrick; Metzner, Claus; Yamakou, Marius (Cognitive Neurodynamics, 2021)
The phenomenon of self-induced stochastic resonance (SISR) requires a nontrivial scaling limit between the deterministic and the stochastic timescales of an excitable system, leading to the emergence of coherent oscillations which are absent without noise. In this paper, we numerically investigate SISR and its control in single neurons and three-neuron motifs made up of the Morris-Lecar model. In single neurons, we compare the effects of electrical and chemical autapses on the degree of coherence of the oscillations due to SISR. In the motifs, we compare the effects of altering the synaptic time-delayed couplings and the topologies on the degree of SISR. Finally, we provide two enhancement strategies for a particularly poor degree of SISR in motifs with chemical synapses: (1) we show that a poor SISR can be significantly enhanced by attaching an electrical or an excitatory chemical autapse on one of the neurons, and (2) we show that by multiplexing the motif with a poor SISR to another motif (with a high SISR in isolation), the degree of SISR in the former motif can be significantly enhanced. We show that the efficiency of these enhancement strategies depends on the topology of the motifs and the nature of synaptic time-delayed couplings mediating the multiplexing connections.
CRIS-Team WoS Importer:2021-12-31

Correction to: Evaluation After Cochlear Implant Surgery: Correlation of Clinical Outcome and Imaging Findings using Flat-detector CT (Clinical Neuroradiology, (2021), 31, 2, (367-372), 10.1007/s00062-020-00922-1) - Stock, Annika; Bozzato, Victoria; Kloska, Stephan; Bozzato, Alessandro; Hoppe, Ulrich; Hornung, Joachim; Dörfler, Arnd; Struffert, Tobias (Clinical Neuroradiology, 2021)
The article “Evaluation After Cochlear Implant Surgery” written by Annika Stock, Victoria Bozzato, Stephan P. Kloska, Alessandro Bozzato, Ulrich Hoppe, Joachim Hornung, Arnd Dörfler and Tobias Struffert was originally published Online First without Open Access. After publication in volume 31, issue 2, page 367–372 the authors decided to opt for Open Choice and to make the article an Open Access publication. Therefore, the copyright of the article has been changed to © The Author(s) 2020 and the article is forthwith distributed under the terms of the Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made.
CRIS-Team Scopus Importer:2021-09-10

Cortical auditory evoked potentials in cochlear implant listeners via single electrode stimulation in relation to speech perception - Liebscher, Tim; Alberter, Katrin; Hoppe, Ulrich (International Journal of Audiology, 2018)
The objectives of this study were to investigate the effects of place of stimulation on cortical auditory evoked potentials in relation to speech performance in cochlear implant listeners. It was designed that cortical responses were recorded for single-electrode bursts at apical, medial and basal portions of the electrode array with varying inter-stimulus intervals ranging from 300 ms to 5 s. Latency and amplitude of N1 and P2 peaks were analysed in relation to monosyllabic word scores. The study sample was 44 adult cochlear implant users ranging in age from 28 to 86 years. N1, P2 and N1-P2 amplitudes declined significantly from apical to basal electrodes. The most robust and pronounced responses were recorded for slower stimulation rates (5 s). Speech recognition correlated positively with N1 and N1-P2 amplitudes at the medial electrode. P2 latency showed a significant negative correlation with speech performance at the apical electrode. At last, cortical responses varied significantly depending on the stimulation site and rate. We can objectively quantify speech performance with the N1, N1-P2 amplitude and P2 latency in cochlear implant users. Deafness-related neural degeneration persists even after the cochlear implantation and is more distinct at the base than the apex of the cochlea.
EVALuna2:35448

Critical Offset Magnetic PArticle SpectroScopy for rapid and highly sensitive medical point-of-care diagnostics - Vogel, Patrick; Rückert, Martin Andreas; Friedrich, Bernhard; Tietze, Rainer; Lyer, Stefan; Kampf, Thomas; Hennig, Thomas; Dölken, Lars; Alexiou, Christoph; Behr, Volker Christian (Nature Communications, 2022)
Magnetic nanoparticles (MNPs) have been adapted for many applications, e.g., bioassays for the detection of biomarkers such as antibodies, by controlled engineering of specific surface properties. Specific measurement of such binding states is of high interest but currently limited to highly sensitive techniques such as ELISA or flow cytometry, which are relatively inflexible, difficult to handle, expensive and time-consuming. Here we report a method named COMPASS (Critical-Offset-Magnetic-Particle-SpectroScopy), which is based on a critical offset magnetic field, enabling sensitive detection to minimal changes in mobility of MNP ensembles, e.g., resulting from SARS-CoV-2 antibodies binding to the S antigen on the surface of functionalized MNPs. With a sensitivity of 0.33 fmole/50 µl (≙7 pM) for SARS-CoV-2-S1 antibodies, measured with a low-cost portable COMPASS device, the proposed technique is competitive with respect to sensitivity while providing flexibility, robustness, and a measurement time of seconds per sample. In addition, initial results with blood serum demonstrate high specificity.
CRIS-Team Scopus Importer:2022-12-02

Cross-modal stochastic resonance as a universal principle to enhance sensory processing. - Krauß, Patrick; Tziridis, Konstantin; Schilling, Achim; Schulze, Holger (Frontiers in Neuroscience, 2018)

Cross-Modal Stochastic Resonance as a Universal Principle to Enhance Sensory Processing. - Krauß, Patrick; Tziridis, Konstantin; Schilling, Achim; Schulze, Holger (Frontiers in Neuroscience, 2018)
EVALuna2:210449

CSF1R-Mediated Myeloid Cell Depletion Prolongs Lifespan But Aggravates Distinct Motor Symptoms in a Model of Multiple System Atrophy - Battis, Kristina; Florio, Jazmin B.; Mante, Michael; Lana, Addison; Naumann, Isabel; Gauer, Carina; Lambrecht, Vera; Mueller, Sarina K.; Cobo, Isidoro; Fixsen, Bethany; Kim, Ha Yeon; Masliah, Eliezer; et al. (Journal of Neuroscience, 2022)
As the CNS-resident macrophages and member of the myeloid lineage, microglia fulfill manifold functions important for brain development and homeostasis. In the context of neurodegenerative diseases, they have been implicated in degenerative and regenerative processes. The discovery of distinct activation patterns, including increased phagocytosis, indicated a damaging role of myeloid cells in multiple system atrophy (MSA), a devastating, rapidly progressing atypical parkinsonian disorder. Here, we analyzed the gene expression profile of microglia in a mouse model of MSA (MBP29-ha-syn) and identified a disease-associated expression profile and upregulation of the colony-stimulating factor 1 (Csf1). Thus, we hypothesized that CSF1 receptor-mediated depletion of myeloid cells using PLX5622 modifies the disease progression and neuropathological phenotype in this mouse model. Intriguingly, sex-balanced analysis of myeloid cell depletion in MBP29-ha-syn mice revealed a two-faced outcome comprising an improved survival rate accompanied by a delayed onset of neurological symptoms in contrast to severely impaired motor functions. Furthermore, PLX5622 reversed gene expression profiles related to myeloid cell activation but reduced gene expression associated with transsynaptic signaling and signal release. While transcriptional changes were accompanied by a reduction of dopaminergic neurons in the SNpc, striatal neuritic density was increased upon myeloid cell depletion in MBP29-ha-syn mice. Together, our findings provide insight into the complex, two-faced role of myeloid cells in the context of MSA emphasizing the importance to carefully balance the beneficial and adverse effects of CSF1R inhibition in different models of neurodegenerative disorders before its clinical translation.
CRIS-Team Scopus Importer:2022-11-04
Keywords: colony-stimulating factor 1 receptor; motor function; multiple system atrophy; myeloid cells; neuron-micro-glia interaction; PLX5622

C-terminal Agrin Fragment as a potential marker for sarcopenia caused by degeneration of the neuromuscular junction - Drey, Michael; Sieber, Cornel; Bauer, Judith; Uter, Wolfgang; Dahinden, P.; Fariello, R. G.; Vrijbloed, J. W. (Experimental Gerontology, 2013)
Introduction: Sarcopenia is considered to be an enormous burden for both the individuals affected and for society at large. A multifactorial aetiology of this geriatric syndrome has been discussed. Amongst other pathomechanisms, the degeneration of the neuromuscular junction (NMJ) may be of major relevance. The intact balance between the pro-synaptic agent agrin and the anti-synaptic agent neurotrypsin ensures a structurally and functionally intact NMJ. Excessive cleavage of the native motoneuron-derived agrin by neurotrypsin into a C-terminal Agrin Fragment (CAF) leads to functional disintegration at the NMJ and may consecutively cause sarcopenia. The present study evaluates the hypothesis that CAF serum concentration is a potential marker for the loss of appendicular lean mass in older adults. It also explores how CAF concentration is influenced by vitamin D supplementation and physical exercise.Method: Serum was taken from 69 (47 female) prefrail community-dwelling older adults participating in a training intervention study to measure the CAF concentration using the Western blot technique. All participants were supplemented orally with vitamin D3 before the training intervention period commenced. Appendicular lean mass (aLM) was evaluated by dual energy X-ray absorptiometry. Multiple linear regression models were used to identify factors significantly associated with CAF concentration.Results: Appendicular lean mass, age and sex were identified as significant explanatory factors for CAF concentration. Gait speed and hand grip strength were not associated with CAF concentration. Male participants showed a strong correlation (r=-0.524) between CAF serum concentration and aLM, whereas this was not the case (r=-0.219) in females. Vitamin D supplementation and physical exercise were significantly associated with a reduction in CAF concentration, especially in participants with initially high CAF concentrations.Conclusions: C-terminal Agrin Fragment could be a potential marker for identifying sarcopenia in a subgroup of affected individuals in the future. The decline of muscle mass seems to be a CAF-associated process in males, whereas the situation in females may be more complex and multifactorial. CAF concentration is reduced by vitamin D supplementation and physical exercise and therefore suggests a potentially positive effect on NMJs. Further prospective studies of sarcopenic patients in addition to muscle biopsy and electromyographical investigations are planned to verify the external validity of the CAF concept. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Sarcopenia; Neuromuscular junction; Agrin; Neurotrypsin; Exercise; Vitamin D

CT support of cardiac structural interventions - Hell, Michaela M.; Achenbach, Stephan (British Journal of Radiology, 2019)
Due to its high temporal and isotropic spatial resolution, CT has become firmly established for pre-procedural imaging in the context of structural heart disease interventions. CT allows to very exactly measure dimensions of the target structure, CT can provide information regarding the access route and, as a very valuable addition, volumetric CT data sets can be used to identify fluoroscopic projection angulations to optimally visualize the target structure and place devices. This review provides an overview of current methods and applications of pre-interventional CT to support adult cardiac interventions including transcatheter aortic valve implantation, percutaneous mitral valve intervention, left atrial appendage occlusion and paravalvular leak closure.
CRIS-Team WoS Importer:2019-06-07

Current methods for modelling voice production - Döllinger, Michael; Kniesburges, Stefan; Kaltenbacher, M.; Echternach, M. (HNO, 2016)
BACKGROUND: Many details of the phonatory process are not yet fully understood. Besides observational research, scientists have long since been trying to explain the physical fundamentals of voicing using simulations. This approach is commonly called modeling. However, the knowledge gained often failed to find its way to professionals working with the voice, such as singing teachers, voice therapists, and voice coaches, and sometimes also to otorhinolaryngologists and phoniatricians. The reason for this is that scientific publications on this topic mostly contain very detailed mathematical and physical descriptions, which are often hard to understand. OBJECTIVE: A simplified presentation and explanation of current methods for modeling the phonatory process, which have contributed greatly to uncovering and understanding the relationships involved in voicing during recent years. METHODS: The presented methods cover a wide spectrum, ranging from numerically rather simple to mathematically highly complex models. Experimental models are based on self-oscillating silicon or static vocal folds. Cadaver models have the advantage of being representative of the natural phonation process. RESULTS: An overview of different kinds of models is given to show the diversity of modeling approaches without going into mathematical or physical details. CONCLUSION: Numerical and experimental models for simulating the phonatory process enable causalities and correlations to be uncovered, which can be used in the future to adapt conservative and surgical voice therapies, or even to suggest entire new treatment strategies.
EVALuna2:33165

Cystatin SN is a potent upstream initiator of epithelial-derived type 2 inflammation in chronic rhinosinusitis - Nocera, Angela L.; Mueller, Sarina K.; Workman, Alan D.; Wu, Dawei; McDonnell, Kristen; Sadow, Peter M.; Amiji, Mansoor M.; Bleier, Benjamin S. (Journal of Allergy and Clinical Immunology, 2022)
Background: Cystatin SN (CST1) and cystatin SA (CST2) are cysteine protease inhibitors that protect against allergen, viral, and bacterial proteases. Cystatins are overexpressed in the setting of allergic rhinitis and chronic rhinosinusitis with nasal polyps (CRSwNP); however, their role in promoting type 2 inflammation remains poorly characterized. Objective: The purpose of this study was to use integrated poly-omics and a murine exposure model to explore the link between cystatin overexpression in CRSwNP and type 2 inflammation. Methods: In this institutional review board– and institutional animal care and use committee–approved study, we compared tissue, exosome, and mucus CST1 and CST2 between CRSwNP and controls (n = 10 per group) by using matched whole exome sequencing, transcriptomic, proteomic, posttranslational modification, histologic, functional, and bioinformatic analyses. C57/BL6 mice were dosed with 3.9 μg/mL of CST1 or PBS intranasally for 5 to 18 days in the presence or absence of epithelial ABCB1a knockdown. Inflammatory cytokines were quantified by using Quansys multiplex assays or ELISAs. Results: Of the 1305 proteins quantified, CST1 and CST2 were among the most overexpressed protease inhibitors in tissue, exosome, and mucus samples; they were localized to the epithelial layer. Multiple posttranslational modifications were identified in the polyp tissue. Exosomal CST1 and CST2 were strongly and significantly correlated with eosinophils and Lund-Mackay scores. Murine type 2 cytokine secretion and TH2 cell infiltration increased in a time-dependent manner following CST1 exposure and was abrogated by epithelial knockdown of ABCB1a, a regulator of epithelial cytokine secretion. Conclusion: CST1 is a potent upstream initiator of epithelial-derived type 2 inflammation in CRSwNP. Therapeutic strategies targeting CST activity and its associated posttranslational modifications deserve further interrogation.
CRIS-Team Scopus Importer:2022-07-15
Keywords: cystatin SA; cystatin SN; Epithelium; exome; P-glycoprotein; posttranslational modification; proteomics; sinonasal mucus; transcriptome

Das weltweite Medizinernetzwerk Aufklärung gegen Tabak – Ehrenamtliche Prävention made in Germany - Brinker, Titus Josef; Buslaff, Fabian; Haney, Caelan; Gaim, Benedikt; Haney, Ailis Ceara; Schmidt, Selina Marisa; Silchmueller, Marc Phillipp; Taha, Lava; Jakob, Lena; Baumert, Hannah Maria; Hallmann, Marvin; Heckl, Marlene; et al. (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2018)
Smoking is the leading preventable cause of premature death in Germany. The network "Education Against Tobacco" (EAT) is an initiative that was founded in Germany in 2012, in which more than 3500 medical students and physicians engage in volunteer work in about 80 medical faculties in 14 countries. In this article, the concept, activities, objectives and associated research studies oft he EAT initiative are introduced.On the school level, the initiative addresses 10- to 15-year-old secondary school students. In addition to a multimodal approach, school visits use modern media such as facemorphing apps, which are not only used by students (45,000 per year in 14 countries), but by a total of over 500,000 other people as well. The effectiveness of the school-based intervention is currently being investigated in randomised long-term studies with 20,000 adolescents in Germany. A first long-term study demonstrated evidence of a protective effect regarding the onset of smoking, especially among female students, students having a low level of education and students with a migratory background.The programme educates several hundred prospective physicians at 13 (of 28 participating) German medical faculties each year in science-based elective courses for the well-established smoking cessation counselling of patients and sensitises them to the tobacco epidemic. The approved members engage in dialogue with local members of the German house of representatives as "Ärzteverband Tabakprävention".EAT motivates the prospective generation of physicians, initially through prevention in school settings, to face the challenge of national tobacco control at the university and federal level.
EVALuna2:277840

Deep brain stimulation in tinnitus: current and future perspectives - Smit, J. V.; Janssen, M. L. F.; Schulze, Holger; Jahanshahi, A.; Van Ouerbeeke, J. J.; Temel, Y.; Stokroos, R. J. (Brain Research, 2015)
Chronic tinnitus, also known as ringing in the ears, affects up to 15% of the adults and causes a serious socio-economic burden. At present, there is no treatment available which substantially reduces the perception of this phantom sound. In the past few years, preclinical and clinical studies have unraveled central mechanisms involved in the pathophysiology of tinnitus, replacing the classical periphery-based hypothesis. In subcortical auditory and non-auditory regions, increased spontaneous activity, neuronal bursting and synchrony were found. When reaching the auditory cortex, these neuronal alterations become perceptually relevant and consequently are perceived as phantom sound. A therapy with a potential to counteract deeply located pathological activity is deep brain stimulation, which has already been demonstrated to be effective in neurological diseases such as Parkinson's disease. In this review, several brain targets are discussed as possible targets for deep brain stimulation in tinnitus. The potential applicability of this treatment in tinnitus is discussed with examples from the preclinical field and clinical case studies.
EVALuna2:19976

Deep Learning and Registration-Based Mapping for Analyzing the Distribution of Nodal Metastases in Head and Neck Cancer Cohorts: Informing Optimal Radiotherapy Target Volume Design - Weissmann, Thomas; Mansoorian, Sina; May, Matthias; Lettmaier, Sebastian; Höfler, Daniel; Deloch, Lisa; Speer, Stefan; Balk, Matthias; Frey, Benjamin; Gaipl, Udo; Bert, Christoph; Distel, Luitpold; et al. (Cancers, 2023)
We introduce a deep-learning- and a registration-based method for automatically analyzing the spatial distribution of nodal metastases (LNs) in head and neck (H/N) cancer cohorts to inform radiotherapy (RT) target volume design. The two methods are evaluated in a cohort of 193 H/N patients/planning CTs with a total of 449 LNs. In the deep learning method, a previously developed nnU-Net 3D/2D ensemble model is used to autosegment 20 H/N levels, with each LN subsequently being algorithmically assigned to the closest-level autosegmentation. In the nonrigid-registration-based mapping method, LNs are mapped into a calculated template CT representing the cohort-average patient anatomy, and kernel density estimation is employed to estimate the underlying average 3D-LN probability distribution allowing for analysis and visualization without prespecified level definitions. Multireader assessment by three radio-oncologists with majority voting was used to evaluate the deep learning method and obtain the ground-truth distribution. For the mapping technique, the proportion of LNs predicted by the 3D probability distribution for each level was calculated and compared to the deep learning and ground-truth distributions. As determined by a multireader review with majority voting, the deep learning method correctly categorized all 449 LNs to their respective levels. Level 2 showed the highest LN involvement (59.0%). The level involvement predicted by the mapping technique was consistent with the ground-truth distribution (p for difference 0.915). Application of the proposed methods to multicenter cohorts with selected H/N tumor subtypes for informing optimal RT target volume design is promising.<br
Keywords: deep learning; artificial intelligence; nodal metastasis; head and neck cancer; radiotherapy; target volume design; atlas; mapping; autosegmentation; lymph node level classification

Deep learning-based detection of motion artifacts in probe-based confocal laser endomicroscopy images. - Aubreville, Marc; Stöve, Maike; Oetter, Nicolai; Goncalves, Miguel; Knipfer, Christian; Neumann, Helmut; Bohr, Christopher; Stelzle, Florian; Maier, Andreas (International Journal of Computer Assisted Radiology and Surgery, 2019)
Probe-based confocal laser endomicroscopy (pCLE) is a subcellular in vivo imaging technique capable of producing images that enable diagnosis of malign structural modifications in epithelial tissue. Images acquired with pCLE are, however, often tainted by significant artifacts that impair diagnosis. This is especially detrimental for automated image analysis, which is why said images are often excluded from recognition pipelines. We present an approach for the automatic detection of motion artifacts in pCLE images and apply this methodology to a data set of 15 thousand images of epithelial tissue acquired in the oral cavity and the vocal folds. The approach is based on transfer learning from intermediate endpoints within a pre-trained Inception v3 network with tailored preprocessing. For detection within the non-rectangular pCLE images, we perform pooling within the activation maps of the network and evaluate this at different network depths. We achieved area under the ROC curve values of 0.92 with the proposed method, compared to 0.80 for the best feature-based machine learning approach. Our overall accuracy with the presented approach is 94.8%. Over traditional machine learning approaches with state-of-the-art features, we achieved significantly improved overall performance. PURPOSE METHODS RESULTS CONCLUSION

Deep learning for automatic head and neck lymph node level delineation provides expert-level accuracy - Weissmann, Thomas; Huang, Yixing; Fischer, Stefan; Roesch, Johannes; Mansoorian, Sina; Gaona, Horacio Ayala; Gostian, Antoniu-Oreste; Hecht, Markus; Lettmaier, Sebastian; Deloch, Lisa; Frey, Benjamin; Gaipl, Udo; et al. (Frontiers in Oncology, 2023)
Background: Deep learning-based head and neck lymph node level (HN_LNL) autodelineation is of high relevance to radiotherapy research and clinical treatment planning but still underinvestigated in academic literature. In particular, there is no publicly available open-source solution for large-scale autosegmentation of HN_LNL in the research setting. Methods: An expert-delineated cohort of 35 planning CTs was used for training of an nnU-net 3D-fullres/2D-ensemble model for autosegmentation of 20 different HN_LNL. A second cohort acquired at the same institution later in time served as the test set (n = 20). In a completely blinded evaluation, 3 clinical experts rated the quality of deep learning autosegmentations in a head-to-head comparison with expert-created contours. For a subgroup of 10 cases, intraobserver variability was compared to the average deep learning autosegmentation accuracy on the original and recontoured set of expert segmentations. A postprocessing step to adjust craniocaudal boundaries of level autosegmentations to the CT slice plane was introduced and the effect of autocontour consistency with CT slice plane orientation on geometric accuracy and expert rating was investigated. Results: Blinded expert ratings for deep learning segmentations and expert-created contours were not significantly different. Deep learning segmentations with slice plane adjustment were rated numerically higher (mean, 81.0 vs. 79.6, p = 0.185) and deep learning segmentations without slice plane adjustment were rated numerically lower (77.2 vs. 79.6, p = 0.167) than manually drawn contours. In a head-to-head comparison, deep learning segmentations with CT slice plane adjustment were rated significantly better than deep learning contours without slice plane adjustment (81.0 vs. 77.2, p = 0.004). Geometric accuracy of deep learning segmentations was not different from intraobserver variability (mean Dice per level, 0.76 vs. 0.77, p = 0.307). Clinical significance of contour consistency with CT slice plane orientation was not represented by geometric accuracy metrics (volumetric Dice, 0.78 vs. 0.78, p = 0.703). Conclusions: We show that a nnU-net 3D-fullres/2D-ensemble model can be used for highly accurate autodelineation of HN_LNL using only a limited training dataset that is ideally suited for large-scale standardized autodelineation of HN_LNL in the research setting. Geometric accuracy metrics are only an imperfect surrogate for blinded expert rating. <
Keywords: Deep learning; lymph node level; segmentation

Deficit in acoustic signal-in-noise detection in glycine receptor ?3 subunit knockout mice - Tziridis, Konstantin; Buerbank, Stefanie; Eulenburg, Volker; Dlugaiczyk, Julia; Schulze, Holger (European Journal of Neuroscience, 2017)
Hearing is an essential sense for communication in animals and humans. Normal function of the cochlea of higher vertebrates relies on a fine-tuned interplay of afferent and efferent innervation of both inner and outer hair cells. Efferent inhibition is controlled via olivocochlear feedback loops, mediated mainly by acetylcholine, ?-aminobutyric acid (GABA) and glycine, and is one of the first sites affected by synapto- and neuropathy in the development of hearing loss. While the functions of acetylcholine, GABA and other inhibitory transmitters within these feedback loops are at least partially understood, especially the function of glycine still remains elusive. To address this question, we investigated hearing in glycine receptor (GlyR) ?3 knockout (KO) and wildtype (WT) mice. We found no differences in pure tone hearing thresholds at 11.3 and 16 kHz between the two groups as assessed by auditory brainstem response (ABR) measurements. Detailed analysis of the ABR waves at 11.3 kHz, however, revealed a latency decrease of wave III and an amplitude increase of wave IV in KO compared to WT animals. GlyR?3 KO animals showed significantly impaired prepulse inhibition of the auditory startle response in a noisy environment, indicating that GlyR?3-mediated glycinergic inhibition is important for signal-in-noise detection.
EVALuna2:4772

Defining a baseline identification of artifacts in confocal laser endomicroscopy in head and neck cancer imaging - Pan, Zhaoya; Breininger, Katharina; Aubreville, Marc; Stelzle, Florian; Maier, Andreas; Oetter, Nicolai; Mantsopoulos, Konstantinos; Iro, Heinrich; Goncalves, Miguel; Sievert, Matti (American Journal of Otolaryngology, 2023)
Purpose: Probe-based confocal laser endomicroscopy (pCLE) allows imaging of the laryngeal mucosa in a thousand-fold magnification. However, the existence of multiple nondiagnostic frames might hinder the performance of automated systems, especially in post-processing and analysis algorithms. This study aims to investigate the feasibility of building a baseline for the identification of diagnostic frames and to evaluate the influence of sequence information in this task. Materials and methods: We included eight patients with squamous cell carcinoma (SCC) and planned total laryngectomy between October 2020 and February 2021. One hundred frames were randomly selected out of 21,272 pCLE frames of the tumor and healthy mucosa during surgery. Three experts were asked to classify these frames into diagnostic and nondiagnostic ones with different subtypes under two settings, i.e., isolated frames or short video sequences. Inter-rater and intra-rater consistency were analyzed with Cohen's kappa coefficients. Results: Among all raters, regarding the classification of diagnostic frames, an average agreement of κ = 0.79 has been achieved. The overall consistency for the subtypes of nondiagnostic frames is κ = 0.75 and κ = 0.57, respectively. Conclusions: The high level of consistency regarding the identification of diagnostic frames shows the reliability of the classification results and builds the foundation for future automatic algorithms.
CRIS-Team Scopus Importer:2023-01-06
Keywords: Classification system; Confocal laser endomicroscopy; Head and neck cancer; Larynx; Non-invasive histological imaging; Pharynx

Degrees of freedom in a vocal fold inverse problem - Gómez, Pablo; Kniesburges, Stefan; Schützenberger, Anne; Bohr, Christopher; Döllinger, Michael (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2017)
Experimental research on human phonation is negatively affected by the complexity of the process and the limiting anatomy of the larynx. Numerical simulation of the vocal folds and the formulation of an inverse problem is one way to remedy this. Several studies have explored this choosing different degrees of freedom (DOFs) in a biomechanical Two-Mass-Model (2MM). The selection of the DOFs in an inverse problem has a critical impact on the quality of possible solutions, but also affects the complexity of the problem and convergence speed in solving it. This work compares previous DOF configurations with several new extended configurations in solving the inverse problem for vocal fold recordings of 20 healthy female subjects. Results indicate that, for the 2MM, uncoupled mass and stiffness, and variable collision strength and damping coefficients improve the matching capabilities. They match physiology and lead to up to 50% smaller errors even for a low number of model evaluations.
CRIS-Team Scopus Importer:2022-09-20
Keywords: High-speed videoendoscopy; Inverse problem; Two-mass-model; Vocal fold oscillation

Deletion 7q31.2q31.31 segregating in a family with speech and language deficiencies - Rieger, Melissa; Krumbiegel, Mandy; Reuter, Miriam; Schützenberger, Anne; Reis, André; Zweier, Christiane (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Dependencies and Ill-designed Parameters Within High-speed Videoendoscopy and Acoustic Signal Analysis - Schlegel, Patrick; Stingl, Michael; Kunduk, Melda; Kniesburges, Stefan; Bohr, Christopher; Döllinger, Michael (Journal of Voice, 2018)
Keywords: Glottal area waveform; High speed video endoscopy; Parameters; Ill design; Mathematical dependencies

Depression and female gender associated with higher postoperative pain scores after sinonasal surgery - Schinz, Katharina; Steigerwald, Lukas; Mantsopoulos, Konstantinos; Gostian, Antoniu-Oreste; Traxdorf, Maximilian; Sievert, Matti; Rupp, Robin; Iro, Heinrich; Müller-Hübner, Sarina (Acta Oto-Laryngologica, 2021)
Background Although it is extremely necessary to reduce the number of opioids taken postoperatively after sinonasal surgery, this is the subject of controversial discussion. Objectives The objective of this study was to identify factors that predict higher postoperative pain scores (PPS) and the need for opioid analgesics after sinonasal surgery. Material and methods This was a retrospective study of n = 492 patients who underwent functional endoscopic sinus surgery (FESS), septoplasty or a combination of both in the Otolaryngology Department in Erlangen between January and December 2018. Postoperative pain using the numeric rating scale and the postoperative need for non-opioid and opioid analgesics in relation to demographic and surgical parameters were evaluated. Results Significant predictors for a higher pain score were depression (p = .009) and female gender (p < .001). A significant predictor of the need for postoperative opioids was the female gender (p < .001), whereas FESS alone showed a significantly lower need for opioids (p = .035) and a significantly lower PPS compared to septoplasty (p < .001). Conclusions and significance The study identified risk factors for a higher PPS and the need for opioids. The results indicated that reducing postoperative opioids might be possible in patients without these risk factors and might help guide individualized postoperative therapy.
CRIS-Team WoS Importer:2022-01-07

Depressive symptoms affect short- and long-term speech recognition outcome in cochlear implant users - Heinze-Köhler, Katharina; Lehmann, Effi Katharina; Hoppe, Ulrich (European Archives of Oto-Rhino-Laryngology, 2020)
Purpose: To investigate the impact of the amount of depressive symptoms in cochlear implant (CI) recipients on the development of speech recognition after CI-activation up to 2 years. Design: Retrospective data analysis of a German short form of the Beck Depression Inventory given at initial activation of the implant in relation to monosyllabic word recognition score at conversational level at initial activation and at 3 months, 1 and 2-year follow-up measurements. Study sample: Thirty-one CI-patients (11 female, 20 male) aged between 41 and 83 (M = 64.77, SD = 10.43) who were German native speakers, postlingually deafened, with severe hearing loss in both sides but unilaterally implanted (19 right-sided, 12 left-sided). Results: The amount of depressive symptoms at initial activation was negatively correlated with the monosyllabic recognition score after 3 months and after 1 year of implant use. Conclusion: The psychological status in terms of depressive symptoms is an important parameter regarding the rehabilitative outcome of CI-patients. Care staff and CI-users should be sensitized to the link between depressive symptoms and the development of speech recognition with CI.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Cochlear implant; Depression; Outcome; Speech recognition

Der Einfluss des Kapseldefektes als Risikofaktor für die Rezidivbildung beim pleomorphen Adenom der Glandula parotidea - Buchta, Peter; Thimsen, Vivian; Iro, Ann-Kristin; Agaimy, Abbas; Iro, Heinrich; Mantsopoulos, Konstantinos (Laryngo-Rhino-Otologie, 2021)
Objective Aim of this study was to enlighten various aspects of the capsular defect of a pleomorphic adenoma and to analyze its influence on recurrence rate with the help of our data and the relevant literature. Material and Methods The clinical records and histopathological findings of all patients who underwent parotidectomy for pleomorphic adenoma between 2006 and 2020 were evaluated retrospectively. The histological slides of all tumours were critically re-evaluated for this study by an experienced head and neck pathologist. The records of the cases with a capsular defect were examined for information on age, gender, type of surgery and surgical outcome. Results A total of 845 patients were included in the primary group.7 (0.8%) recurrences were detected, all of these were resected without a capsular rupture. Positive margins were found in 37 cases (4.4%). In 13/37 cases the capsular defect was detected intraoperatively, whereas the defect was only identified histopathologically in 24 of the 37 cases. In the group of the intraoperative capsular opening, with a median follow-up of 62 months, the sonographic examination suspected a unilocular recurrence of the pleomorphic adenoma in two cases. Conclusion The intraoperative capsule opening does not inevitably seem to lead to a pre-programmed recurrence.
CRIS-Team Scopus Importer:2021-07-09
Keywords: capsule; capsule opening; parotid gland; pleomorphic adenoma; recurrence; recurrence rate

Der histopathologische „Abdruck“ des Paradigmenwechsels in der Behandlung des parotidealen pleomorphen Adenoms - Mant﻿so﻿pou﻿los, Kons﻿tan﻿ti﻿nos; Iro, Ann Kristin; Agaimy, Abbas; Iro, Heinrich (HNO, 2021)
CRIS-Team Scopus Importer:2021-07-02

Detection of iron oxide nanoparticles for local chemotherapeutic treatment employing coded Magnetomotive Ultrasound - Fink, Michael; Ermert, Helmut; Lyer, Stefan; Alexiou, Christoph (Proceedings SENSOR 2017, 2017)

Detection of viral antibodies in camel sera using magnetic particle spectroscopy - Friedrich, Bernhard; Vogel, Patrick; Rückert, Martin A.; Lyer, Stefan; Günther, Johanna; Wernery, Ulrich; Joseph, Sunitha; Müller, Judith; Behr, Volker C.; Alexiou, Christoph; Tietze, Rainer (Applied Microbiology and Biotechnology, 2023)
Abstract: Pandemics like SARS-Cov-2 very frequently have their origin in different animals and in particular herds of camels could be a source of zoonotic diseases. This study took advantage on a highly sensitive and adaptable method for the fast and reliable detection of viral antibodies in camels using low-cost equipment. Magnetic nanoparticles (MNP) have high variability in their functionalization with different peptides and proteins. We confirm that 3-aminopropyl triethoxysilane (APTES)-coated MNP could be functionalized with viral proteins. The protein loading could be confirmed by simple loading controls using FACS-analysis (p < 0.05). Complementary combination of antigen and antibody yields in a significant signal increase could be proven by both FACS and COMPASS. However, COMPASS needs only a few seconds for the measurement. In COMPASS, the phase φn on selected critical point of the fifth higher harmonic (n = 5th). Here, positive sera display highly significant signal increase over the control or negative sera. Furthermore, a clear distinction could be made in antibody detection as an immune response to closely related viruses (SARS-CoV2 and MERS). Using modified MNPs along with COMPASS offers a fast and reliable method that is less cost intensive than current technologies and offers the possibility to be quickly adapted in case of new occurring viral infections. Key points: • COMPASS (critical offset magnetic particle spectroscopy) allows the fast detection of antibodies. • Magnetic nanoparticles can be adapted by exchange of the linked bait molecule. • Antibodies could be detected in camel sera without washing steps within seconds.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Antibody detection; Camels; COMPASS; MNPs; MPS; Rapid bioassay; SARS-Cov-2

Detektion einer in der Standard-Mehrzeilen-CT nicht abgrenzbaren Felsenbeinquerfraktur mittels Flachdetektor-CT: ein Fallbericht - Eisenhut, Felix; Wiesmüller, Marco; Lang, Stefan; Taha, Lava (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2022)
CRIS-Team Scopus Importer:2022-08-05

Determination of clinical parameters sensitive to functional voice disorders applying boosted decision stumps - Schlegel, Patrick; Kist, Andreas; Semmler, Marion; Döllinger, Michael; Kunduk, Melda; Dürr, Stephan; Schützenberger, Anne (IEEE Journal of Translational Engineering in Health and Medicine, 2020)
Background: Various voice assessment tools, such as questionnaires and aerodynamic voice characteristics, can be used to assess vocal function of individuals. However, not much is known about the best combinations of these parameters in identification of functional dysphonia in clinical settings. Methods: This study investigated six scores from clinically commonly used questionnaires and seven acoustic parameters. 514 females and 277 males were analyzed. The subjects were divided into three groups: one healthy group (N01) (49 females, 50 males) and two disordered groups with perceptually hoarse (FD23) (220 females, 96 males) and perceptually not hoarse (FD01) (245 females, 131 males) sounding voices. A tree stumps Adaboost approach was applied to find the subset of parameters that best separates the groups. Subsequently, it was determined if this parameter subset reflects treatment outcome for 120 female and 51 male patients by pairwise pre- and post-treatment comparisons of parameters. Results: The questionnaire "Voice-related-quality-of-Life" and three objective parameters ("maximum fundamental frequency", "maximum Intensity" and "Jitter Percent") were sufficient to separate the groups (accuracy ranging from 0.690 (FD01 vs. FD23, females) to 0.961 (N01 vs. FD23, females)). Our study suggests that a reduced parameter subset (4 out of 13) is sufficient to separate these three groups. All parameters reflected treatment outcome for patients with hoarse voices, Voice-related-quality-of-Life showed improvement for the not hoarse group (FD01). Conclusion: Results show that single parameters are insufficient to separate voice disorders but a set of several well-chosen parameters is. These findings will help to optimize and reduce clinical assessment time.
CRIS-Team Scopus Importer:2020-06-09
Keywords: Acoustic measurements; Acoustics; boosted decision Stumps; classification; Frequency measurement; functional dysphonia; Hospitals; Licenses; Oscillators; Parameters; Tools

Determining the resolution of a tracer for magnetic particle imaging by means of magnetic particle spectroscopy - Remmo, Amani; Wiekhorst, Frank; Kosch, Olaf; Lyer, Stefan; Unterweger, Harald; Kratz, Harald; Löwa, Norbert (RSC Advances, 2023)
Magnetic particle imaging (MPI) is an imaging modality to quantitatively determine the three-dimensional distribution of magnetic nanoparticles (MNPs) administered as a tracer into a biological system. Magnetic particle spectroscopy (MPS) is the zero-dimensional MPI counterpart without spatial coding but with much higher sensitivity. Generally, MPS is employed to qualitatively evaluate the MPI capability of tracer systems from the measured specific harmonic spectra. Here, we investigated the correlation of three characteristic MPS parameters with the achievable MPI resolution from a recently introduced procedure based on a two-voxel-analysis of data taken from the system function acquisition that is mandatory in Lissajous scanning MPI. We evaluated nine different tracer systems and determined their MPI capability and resolution from MPS measurements and compared the results with MPI phantom measurements.
CRIS-Team Scopus Importer:2023-07-07

Developmental regulation of glycine receptors at efferent synapses of the murine cochlea - Buerbank, Stefanie; Becker, Kristina; Becker, Cord-Michael; Brandt, Niels; Engel, Jutta; Knipper, Marlies; Schick, Bernhard; Dlugaiczyk, Julia (Histochemistry and Cell Biology, 2011)
Efferent olivocochlear feedback innervation modulates the stream of auditory information from cochlea to brainstem by regulating auditory nerve activity and controlling the contribution of cochlear outer hair cells to basilar membrane motion. In our previous work, we gave a first description of glycine receptors (GlyRs) in the rat cochlea indicating a possible localization at efferent cochlear synapses. Here, we analyze the developmental regulation of GlyR transcripts and protein within the developing murine organ of Corti (postnatal days P0-P21). Using quantitative RT-PCR, GlyR?1 and ?2 were identified as the predominant GlyR? subunit transcripts before the onset of hearing (
EVALuna2:4668

Development and characterization of magnetic iron oxide nanoparticles with a cisplatin-bearing polymer coating for targeted drug delivery - Unterweger, Harald; Tietze, Rainer; Janko, Christina; Zaloga, Jan; Lyer, Stefan; Dürr, Stephan; Taccardi, Nicola; Goudouri, Ourania Menti; Hoppe, Alexander; Eberbeck, Dietmar; Schubert, Dirk W.; Boccaccini, Aldo R.; et al. (International Journal of Nanomedicine, 2014)
A highly selective and efficient cancer therapy can be achieved using magnetically directed superparamagnetic iron oxide nanoparticles (SPIONs) bearing a sufficient amount of the therapeutic agent. In this project, SPIONs with a dextran and cisplatin-bearing hyaluronic acid coating were successfully synthesized as a novel cisplatin drug delivery system. Transmission electron microscopy images as well as X-ray diffraction analysis showed that the individual magnetite particles were around 4.5 nm in size and monocrystalline. The small crystallite sizes led to the superparamagnetic behavior of the particles, which was exemplified in their magnetization curves, acquired using superconducting quantum interference device measurements. Hyaluronic acid was bound to the initially dextran-coated SPIONs by esterification. The resulting amide bond linkage was verified using Fourier transform infrared spectroscopy. The additional polymer layer increased the vehicle size from 22 nm to 56 nm, with a hyaluronic acid to dextran to magnetite weight ratio of 51:29:20. A maximum payload of 330 μg cisplatin/mL nanoparticle suspension was achieved, thus the particle size was further increased to around 77 nm with a zeta potential of -45 mV. No signs of particle precipitation were observed over a period of at least 8 weeks. Analysis of drug-release kinetics using the dialysis tube method revealed that these were driven by inverse ligand substitution and diffusion through the polymer shell as well as enzymatic degradation of hyaluronic acid. The biological activity of the particles was investigated in a nonadherent Jurkat cell line using flow cytometry. Further, cell viability and proliferation was examined in an adherent PC-3 cell line using xCELLigence analysis. Both tests demonstrated that particles without cisplatin were biocompatible with these cells, whereas particles with the drug induced apoptosis in a dose-dependent manner, with secondary necrosis after prolonged incubation. In conclusion, combination of dextran-coated SPIONs with hyaluronic acid and cisplatin represents a promising approach for magnetic drug targeting in the treatment of cancer.

Development of a time-dependent numerical model for the assessment of non-stationary pharyngoesophageal tissue vibrations after total laryngectomy - Hüttner, Björn; Luegmair, Georg; Patel, Rita R.; Ziethe, Anke; Eysholdt, Ulrich; Bohr, Christopher; Sebova, Irina; Semmler, Marion; Döllinger, Michael (Biomechanics and Modeling in Mechanobiology, 2015)
Laryngeal cancer due to, e.g., extensive smoking and/or alcohol consumption can necessitate the excision of the entire larynx. After such a total laryngectomy, the voice generating structures are lost and with that the quality of life of the concerning patients is drastically reduced. However, the vibrations of the remaining tissue in the so called pharyngoesophageal (PE) segment can be applied as alternative sound generator. Tissue, scar, and geometric aspects of the PE-segment determine the postoperative substitute voice characteristic, being highly important for the future live of the patient. So far, PE-dynamics are simulated by a biomechanical model which is restricted to stationary vibrations, i.e., variations in pitch and amplitude cannot be handled. In order to investigate the dynamical range of PE-vibrations, knowledge about the temporal processes during substitute voice production is of crucial interest. Thus, time-dependent model parameters are suggested in order to quantify non-stationary PE-vibrations and drawing conclusions on the temporal characteristics of tissue stiffness, oscillating mass, pressure, and geometric distributions within the PE-segment. To adapt the numerical model to the PE-vibrations, an automatic, block-based optimization procedure is applied, comprising a combined global and local optimization approach. The suggested optimization procedure is validated with 75 synthetic data sets, simulating non-stationary oscillations of differently shaped PE-segments. The application to four high-speed recordings is shown and discussed. The correlation between model and PE-dynamics is [Formula: see text] 97 %.
EVALuna2:19926

Dextran-coated superparamagnetic iron oxide nanoparticles for magnetic resonance imaging: Evaluation of size-dependent imaging properties, storage stability and safety - Unterweger, Harald; Dezsi, Laszlo; Matuszak, Jasmin; Janko, Christina; Poettler, Marina; Jordan, Jutta; Bäuerle, Tobias; Szebeni, Janos; Fey, Tobias; Boccaccini, Aldo R.; Alexiou, Christoph; Cicha, Iwona (International Journal of Nanomedicine, 2018)
Keywords: Irritation potential; Cross-linking; CARPA; Storage stability; SPION; MRI

Diagnosing complications following cochlear implantation using transcutaneous ultrasound - Rupp, Robin; Thimsen, Vivian; Balk, Matthias; Müller-Hübner, Sarina; Sievert, Matti; Mantsopoulos, Konstantinos; Hoppe, Ulrich; Hornung, Joachim; Iro, Heinrich; Gostian, Antoniu-Oreste (European Archives of Oto-Rhino-Laryngology, 2021)
Purpose: The aim of this study was to investigate the feasibility and reliability of transcutaneous ultrasound for the detection of complications after cochlear implantation. Methods: In a single center retrospective cohort study, 115 consecutive cases of suspected complications after cochlear implantation (intervention group) were examined. The rate of pathologic ultrasound findings for specific leading symptoms and diagnoses was compared to a control group comprising twenty consecutive cochlear implants in symptom-free patients. Results: Diagnostic ultrasound showed distinctly more pathologic findings in the intervention group (n = 67; 58.3%; p < 0.001) compared to the control group (n = 1; 5%). Ultrasound revealed significantly more pathologic findings in haematoma or seroma around the implant (n = 17; 100%; p < 0.001; ϕ = 0.94) and magnet dislocation (n = 44; 97.7%; p < 0.001; ϕ = 0.92) confirmed by a strong effect. Ultrasound examination showed a medium to high effect size in patients presenting with local infections (n = 3; 21.4%; p = 0.283; ϕ = 0.25) and skin flap oedema (n = 2; 50%; p = 0.061; ϕ = 0.51). In contrast, ultrasound examinations displayed a low effect size in undefined cephalgia (0%; p = 0.444; ϕ = 0.17) and device malfunction or failure (0%; p > 0.999; ϕ = 0.13). Conclusion: Transcutaneous ultrasound can be advocated as a feasible and effective method in the diagnostic work-up of magnet dislocation and haematoma or seroma around the implant following cochlear implantation. Contrary, ultrasound findings can be expected to be inconspicuous in patients presenting with undefined cephalgia and device malfunction or failure.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Cochlear implant; Diagnostic sonography; Haematoma; Magnet dislocation; Seroma; Transcutaneous ultrasound

Diagnosis of malignancy in oropharyngeal confocal laser endomicroscopy using GPT 4.0 with vision - Sievert, Matti; Aubreville, Marc; Mueller, Sarina K.; Eckstein, Markus; Breininger, Katharina; Iro, Heinrich; Goncalves, Miguel (European Archives of Oto-Rhino-Laryngology, 2024)
Purpose: Confocal Laser Endomicroscopy (CLE) is an imaging tool, that has demonstrated potential for intraoperative, real-time, non-invasive, microscopical assessment of surgical margins of oropharyngeal squamous cell carcinoma (OPSCC). However, interpreting CLE images remains challenging. This study investigates the application of OpenAI’s Generative Pretrained Transformer (GPT) 4.0 with Vision capabilities for automated classification of CLE images in OPSCC. Methods: CLE Images of histological confirmed SCC or healthy mucosa from a database of 12 809 CLE images from 5 patients with OPSCC were retrieved and anonymized. Using a training data set of 16 images, a validation set of 139 images, comprising SCC (83 images, 59.7%) and healthy normal mucosa (56 images, 40.3%) was classified using the application programming interface (API) of GPT4.0. The same set of images was also classified by CLE experts (two surgeons and one pathologist), who were blinded to the histology. Diagnostic metrics, the reliability of GPT and inter-rater reliability were assessed. Results: Overall accuracy of the GPT model was 71.2%, the intra-rater agreement was κ = 0.837, indicating an almost perfect agreement across the three runs of GPT-generated results. Human experts achieved an accuracy of 88.5% with a substantial level of agreement (κ = 0.773). Conclusions: Though limited to a specific clinical framework, patient and image set, this study sheds light on some previously unexplored diagnostic capabilities of large language models using few-shot prompting. It suggests the model`s ability to extrapolate information and classify CLE images with minimal example data. Whether future versions of the model can achieve clinically relevant diagnostic accuracy, especially in uncurated data sets, remains to be investigated.
CRIS-Team Scopus Importer:2024-02-23
Keywords: Confocal laser endomicroscopy; GPT; Head and neck malignancies; Oropharyngeal squamous cell carcinoma

Diagnostic imaging in cancer therapy with magnetic nanoparticles - Lyer, Stefan; Tietze, Rainer; Dürr, Stephan; Struffert, Tobias; Engelhorn, Tobias Martin; Schwarz, Marc; Dörfler, Arnd; Budinsky, Lubos; Heß, Andreas; Schmidt, Wolfgang; Jurgons, Roland; Alexiou, Christoph (Springer Proceedings in Physics, 2012)
The unfavorable application-to-tumor-dose-ratio is a drawback of conventional systemic chemotherapy, implying an often insufficient drug dose in the tumor being associated with severe side effects for the patient. The use of chemotherapeutics bound to magnetic nanoparticles offers several advantages. On the one hand it is possible to concentrate the chemotherapeutics in the tumor region by the use of magnetic fields, like it is done in Magnetic Drug Targeting (MDT). On the other hand magnetic particles can serve as contrast agent for magnetic resonance imaging (MRI) that is bound to the therapeutics. Hence, the particles possibly are opening an insight into drug distribution in the tumor region directly after administration. Another important factor for a successful MDT-application is detailed knowledge about tumor vascularization. In this pilot study we investigated vascularization and size of an tumor in an experimental in vivo tumor model via flat-panel angiography and DYNA-CT before MDT and the particle distribution with MRI after MDT. We could show that the tumor could be displayed by MRI and DYNA-CT before and after MDT. Flat panel angiography revealed clearly the pathological tumor vascularization before MDT, while MRI imaging afterwards displayed the tumor as well as the particle distribution in the tumor.
CRIS-Team Scopus Importer:2022-06-27
Keywords: Magnetic Nanoparticles; Tumor Region; Magnetic Resonance Imaging Imaging; Signal Extinction; Left Hind Limb

Diagnostic value of 3D dynamic contrast-enhanced magnetic resonance imaging in lymph node metastases of head and neck tumors: a correlation study with histology - Treutlein, Christoph; Stollberg, Adrian; Scherl, Claudia; Agaimy, Abbas; Ellmann, Stephan; Iro, Heinrich; Lell, Michael; Uder, Michael; Bäuerle, Tobias (Acta Radiologica Open, 2020)
Background: Accurate staging of cervical lymph nodes (LN) is pivotal for further clinical management of patients with head and neck cancer. Functional magnetic resonance imaging (MRI) such as three-dimensional (3D) dynamic contrast-enhanced (DCE) acquisition might improve the diagnosis of cervical LN metastases.
CRIS-Team WoS Importer:2020-09-25

Die tracheoösophageale Ersatzstimme: Evaluation durch Experten, naive Hörer und automatische Spracherkennung - Bellanova, Martina; Schuster, Maria; Haderlein, Tino; Nöth, Elmar; Eysholdt, Ulrich; Rosanowski, Frank (Aktuelle phoniatrisch-pädaudiologische Aspekte 2006, 2006)

Differences and Similarities in the Pattern of Early Metabolic and Morphologic Response after Induction Chemo-Immunotherapy versus Induction Chemotherapy Alone in Locally Advanced Squamous Cell Head and Neck Cancer - Beck, Michael; Semrau, Sabine; Haderlein, Marlen; Gostian, Antoniu-Oreste; Hartwich, Julius; Mueller, Sarina K.; Kallies, Annett; Geppert, Carol-Immanuel; Schonath, Miriam; Putz, Florian; Gaipl, Udo; Frey, Benjamin; et al. (Cancers, 2022)
Simple Summary There are differences and similarities when assessing the short-term therapeutic response of chemotherapy and chemotherapy plus immunotherapy using imaging techniques, which may be necessary to make treatment decisions in malignant head and neck tumors. After both chemo- and immunochemotherapy, remission becomes measurable in cross-sectional and metabolic diagnostics after only one cycle of therapy, with (18)FDG-PET/CT predicting complete remission of tumor cells in a representative biopsy better than MRI/CT examination in both therapeutic modalities. While complete tumor remission is highly likely (88%) after immunochemotherapy in tumors with low residual activity (<= 40% of initial SUV), this is less common after chemotherapy alone (65%). In metabolic nonresponse with more than 80% residual activity, the probability of complete remission nevertheless is low after chemotherapy alone (6%). After immunochemotherapy, these false nonresponders are common (35%), requiring additional diagnostics by deep biopsy. Cases of pseudoprogression with an increase of SUVmax of more than 125% of the baseline were not observed. Background: In head and neck cancer patients, parameters of metabolic and morphologic response of the tumor to single-cycle induction chemotherapy (IC) with docetaxel, cis- or carboplatin are used to decide the further course of treatment. This study investigated the effect of adding a double immune checkpoint blockade (DICB) of tremelimumab and durvalumab to IC on imaging parameters and their significance with regard to tumor cell remission. Methods: Response variables of 53 patients treated with IC+DICB (ICIT) were compared with those of 104 who received IC alone. Three weeks after one cycle, pathologic and, in some cases, clinical and endoscopic primary tumor responses were evaluated and correlated with a change in 18F-FDG PET and CT/MRI-based maximum-standardized uptake values (SUVmax) before (SUV(max)pre), after treatment (SUV(max)post) and residually (resSUV(max) in % of SUV(max)pre), and in maximum tumor diameter (D-max) before (D(max)pre) and after treatment (D(max)post) and residually (resD). Results: Reduction of SUVmax and D-max occurred in both groups; values were SUV(max)pre: 14.4, SUV(max)post: 6.6, D(max)pre: 30 mm and D(max)post: 23 mm for ICIT versus SUV(max)pre: 16.5, SUV(max)post: 6.4, D(max)pre: 21 mm, and D(max)post: 16 mm for IC alone (all p < 0.05). ResSUV(max) was the best predictor of complete response (IC: AUC: 0.77; ICIT: AUC: 0.76). Metabolic responders with resSUV(max) <= 40% tended to have a higher rate of CR to ICIT (88%; n = 15/17) than to IC (65%; n = 30/46; p = 0.11). Of the metabolic nonresponders (resSUV(max) > 80%), 33% (n = 5/15) achieved a clinical CR to ICIT versus 6% (n = 1/15) to IC (p = 0.01). Conclusions: ICIT and IC quickly induce a response and 18F-FDG PET is the more accurate modality for identifying complete remission. The rate of discrepant response, i.e., pCR with metabolic nonresponse after ICIT was >30%.
CRIS-Team WoS Importer:2022-10-21

Differences in Need for Opioids After Sinonasal Surgery at Day of Surgery and in the Postoperative Period - Steigerwald, Lukas; Schinz, Katharina; Sievert, Matti; Mantsopoulos, Konstantinos; Gostian, Antoniu Oreste; Iro, Heinrich; Mueller, Sarina K. (Ent-Ear Nose & Throat Journal, 2021)
Introduction: In the last years, the use of opioid analgesics has increased, as well as their morbidity and mortality, especially in the United States. Most patients after sinonasal surgery receive opioid analgesics, although up to 90% have leftover opioid pills. Around 70% of these patients keep the opioid analgesics, which could possibly lead to improper use. The objective of the following study was the investigation of the need for, use of, timing and side effects of opioid and non-opioid analgesics after sinonasal surgery. Methods: This was a retrospective study of (n = 280) patients who underwent sinonasal surgery in the Otolaryngology Department of the University Erlangen-Nürnberg between January and December 2018. The postoperative pain (3-5 days after surgery) using the numeric rating scale and the postoperative need for on-demand opioids and non-opioid analgesics in relation to demographic and surgical parameters were evaluated. Results: Of total, 59.64% of all patients received opioid analgesics postoperatively on the day of surgery. On the first postoperative day (POD1), the mean pain score yielded the highest values; however, only 0.71% of the patients needed opioid analgesics, and pain was sufficiently controlled with non-opioids or no pain medication at all. There was a significant reduction of the pain score from POD2 to 5 (P =.01; P <.01, respectively). Only 1.8% of the patients needed an opioid analgesic from POD1-5. Of total, 2.1% of the patients presented with a postoperative bleeding complication, and only 1 (0.4%) patient needed endoscopic coagulation. Conclusion: Our results indicate that the majority of patients need opioid analgesics almost exclusively on the day of surgery. There were no major complications in patients taking either opioid or non-opioids. Our results indicate that the postoperative pain regimen from POD1 should initially be started using non-opioid analgesics and be further escalated to opioid analgesics in individual cases.
CRIS-Team Scopus Importer:2021-01-22

Differential responses to bioink‐induced oxidative stress in endothelial cells and fibroblasts - Genc, Hatice; Hazur, Jonas; Karakaya, Emine; Dietel, Barbara; Bider, Faina; Groll, Jürgen; Alexiou, Christoph; Boccaccini, Aldo R.; Detsch, Rainer; Cicha, Iwona (International Journal of Molecular Sciences, 2021)
A hydrogel system based on oxidized alginate covalently crosslinked with gelatin (ADA‐ GEL) has been utilized for different biofabrication approaches to design constructs, in which cell growth, proliferation and migration have been observed. However, cell–bioink interactions are not completely understood and the potential effects of free aldehyde groups on the living cells have not been investigated. In this study, alginate, ADA and ADA‐GEL were characterized via FTIR and NMR, and their effect on cell viability was investigated. In the tested cell lines, there was a concen-tration‐dependent effect of oxidation degree on cell viability, with the strongest cytotoxicity observed after 72 h of culture. Subsequently, primary human cells, namely fibroblasts and endothelial cells (ECs) were grown in ADA and ADA‐GEL hydrogels to investigate the molecular effects of oxidized material. In ADA, an extremely strong ROS generation resulting in a rapid depletion of cellular thiols was observed in ECs, leading to rapid necrotic cell death. In contrast, less pronounced cytotoxic effects of ADA were noted on human fibroblasts. Human fibroblasts had higher cellular thiol content than primary ECs and entered apoptosis under strong oxidative stress. The presence of gelatin in the hydrogel improved the primary cell survival, likely by reducing the oxidative stress via binding to the CHO groups. Consequently, ADA‐GEL was better tolerated than ADA alone. Fibroblasts were able to survive the oxidative stress in ADA‐GEL and re‐entered the proliferative phase. To the best of our knowledge, this is the first report that shows in detail the relationship between oxidative stress‐induced intracellular processes and alginate di‐aldehyde‐based bioinks.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Alginate di‐aldehyde; Cell death; Cell viability; Gelatin; Glutathione; Oxidative stress

Different storage conditions influence biocompatibility and physicochemical properties of iron oxide nanoparticles - Zaloga, Jan; Janko, Christina; Agarwal, Rohit; Nowak, Johannes; Müller, Robert; Boccaccini, Aldo R.; Lee, Geoffrey; Odenbach, Stefan; Lyer, Stefan; Alexiou, Christoph (International Journal of Molecular Sciences, 2015)
Superparamagnetic iron oxide nanoparticles (SPIONs) have attracted increasing attention in many biomedical fields. In magnetic drug targeting SPIONs are injected into a tumour supplying artery and accumulated inside the tumour with a magnet. The effectiveness of this therapy is thus dependent on magnetic properties, stability and biocompatibility of the particles. A good knowledge of the effect of storage conditions on those parameters is of utmost importance for the translation of the therapy concept into the clinic and for reproducibility in preclinical studies. Here, core shell SPIONs with a hybrid coating consisting of lauric acid and albumin were stored at different temperatures from 4 to 45 °C over twelve weeks and periodically tested for their physicochemical properties over time. Surprisingly, even at the highest storage temperature we did not observe denaturation of the protein or colloidal instability. However, the saturation magnetisation decreased by maximally 28.8% with clear correlation to time and storage temperature. Furthermore, the biocompatibility was clearly affected, as cellular uptake of the SPIONs into human T-lymphoma cells was crucially dependent on the storage conditions. Taken together, the results show that the particle properties undergo significant changes over time depending on the way they are stored.
Keywords: Colloidal stability; Iron oxide biocompatibility; Iron oxide nanoparticles; Magnetic drug targeting; Magnetite maghemite biocompatibility; Nanomedicine; Nanoparticle stability

Digitalization and (Nano)robotics in nanomedicine - Lyer, Stefan; Blersch, Pascal-Raphael; Huber, Christian; Tietze, Rainer; Alexiou, Christoph (Digital Medicine: Bringing Digital Solutions to Medical Practice, 2023)
CRIS-Team Scopus Importer:2023-07-07

Discriminant analysis followed by unsupervised cluster analysis including exosomal cystatins predict presence of chronic rhinosinusitis, phenotype, and disease severity - Miyake, Michelle M.; Workman, Alan D.; Nocera, Angela L.; Wu, Dawei; Mueller, Sarina K.; Finn, Kristen; Amiji, Mansoor M.; Bleier, Benjamin S. (International Forum of Allergy and Rhinology, 2019)
Background: Cystatins are epithelial protease inhibitors that participate in sinonasal immunity and inflammation. Nasal mucus–derived exosomes (NMDEs) are small vesicles secreted by epithelial cells that carry protein cargo reflective of their host cell. NMDEs have been used as a noninvasive biomarker source to study chronic rhinosinusitis with nasal polyps (CRSwNP) proteomics with superior sensitivity to whole mucus. The purpose of this study was to noninvasively quantify exosomal cystatins in a heterogenous population to determine their utility in predicting phenotype and disease severity. Methods: This was an Institutional Review Board–approved study in which NMDEs were purified from 105 patients undergoing sinonasal surgery by ultracentrifugation. Demographic and clinical variables were collected and phenotypes were assigned a priori. Linear discriminant analysis was executed based on normalized Cystatin values as phenotype predictor variables. Unsupervised cluster analysis was performed using Ward's linkage followed by Duda/Hart Je(2)/Je(1) index cluster stopping rules. Analysis of variance (ANOVA), Welch's test, and Fisher's exact tests were used for continuous and categorical variables. Results: NMDE Cystatin-2 expression segregated by phenotype (mean ± standard error [SEM]): control (23.4 ± 4.2 pg/µg, n = 32); CRS without NP (CRSsNP) (56.6 ± 8.3 pg/µg, n = 33); and CRSwNP (130.5 ± 16.7 pg/µg, n = 40) (p < 0.0001). Seven clusters were identified among patients where the highest NMDE Cystatin-2 levels clustered with asthma, tissue eosinophilia, and aspirin-exacerbated respiratory disease (AERD). Conclusion: Cystatin levels in NMDEs predict CRS phenotype and disease severity. As a “liquid biopsy,” noninvasive NMDE collection offers a promising opportunity to study disease pathophysiology, discriminate disease states, and potentially reveal novel therapeutic targets.
CRIS-Team Scopus Importer:2019-08-02
Keywords: chronic rhinosinusitis; cluster analysis; exosome; nasal polyps; sinonasal mucus

Distribution of magnetic nanoparticles after magnetic drug targeting in an ex vivo bovine artery model - Lyer, Stefan; Tietze, Rainer; Jurgons, R.; Richter, H.; Wiekhorst, F.; Schwarz, K.; Trahms, L.; Alexiou, Christoph (IFMBE Proceedings, 2009)
The aim of Magnetic Drug Targeting (MDT) in cancer therapy is to concentrate chemotherapeutics to a tumor region while simultaneously the over all dose is reduced. This can be achieved by coated superparamagnetic nanoparticles bound to a chemotherapeutic agent. These particles are applied intraarterially close to the tumor region and focused to the tumor by a strong external magnetic field. The interaction of the particles with the field should make them accumulate in the region of the steepest field gradient. Here, we suggest an artery model by which the magnetic targeting mechanism can be studied in detail. In particular, we focus on the quantification of the accumulation profile along the artery by SQUID-based magnetorelaxometry. © 2009 Springer-Verlag.
CRIS-Team Scopus Importer:2022-06-27
Keywords: Chemotherapy; Magnetic drug targeting; Magnetorelaxometry; Nanomedicine; Nanotechnology

Diverse Applications of Nanomedicine - Pelaz, Beatriz; Alexiou, Christoph; Alvarez -Puebla, Ramon A.; Alves, Frauke; Andrews, Anne M.; Ashraf, Sumaira; Balogh, Lajos P.; Ballerini, Laura; Bestetti, Alessandra; Brendel, Cornelia; Bosi, Susanna; Carril, Monica; et al. (Acs Nano, 2017)
The design and use of materials in the nanoscale size range for addressing medical and health-related issues continues to receive increasing interest. Research in nanomedicine spans a multitude of areas, including drug delivery, vaccine development, antibacterial, diagnosis and imaging tools, wearable devices, implants, high-throughput screening platforms, etc. using biological, nonbiological, biomimetic, or hybrid materials. Many of these developments are starting to be translated into viable clinical products. Here, we provide an overview of recent developments in nanomedicine and highlight the current challenges and upcoming opportunities for the field and translation to the clinic.
EVALuna2:33200

Does increasing the incidence of extracapsular dissection for benign tumors of the parotid correlate with an increased need for revision surgery? - Mantsopoulos, Konstantinos; Mueller, Sarina K.; Goncalves, Miguel; Schapher, Mirco; Koch, Michael; Iro, Heinrich (Oral Oncology, 2019)
Objectives: The aim of this study was to investigate the hypothesis of whether extracapsular dissection (ED) of the parotid gland increases the need for revision surgery for benign tumours in comparison to traditional surgical modalities. A further aim of this study was to evaluate and compare the functional outcome of revision procedures after primary ED with other modalities involving the parotid gland in our department.
CRIS-Team WoS Importer:2019-06-21

Dose-dependent deterioration of swallowing function after induction chemotherapy and definitive chemoradiotherapy for laryngopharyngeal cancer - Haderlein, Marlen; Semrau, S.; Ott, O.; Speer, S.; Bohr, Christopher; Fietkau, Rainer (Strahlentherapie und Onkologie, 2014)
To evaluate the influence of clinical, treatment- and dose-dependent factors on posttreatment swallowing function after induction chemotherapy and definitive chemoradiotherapy in a group of homogeneously treated laryngopharyngeal cancer patients.From 28 May 2008 to 15 February 2013, 45 patients with borderline inoperable laryngopharyngeal cancer that had responded well to induction chemotherapy were treated with definitive chemoradiotherapy. Median follow-up was 22 months. Swallowing function and clinical data were prospectively analyzed using the EORTC QLQ-C30 questionnaire. Swallowing structures were retrospectively delineated on the original treatment planning CT. Dose-volume histograms were calculated for swallowing structures and Dmean, Dmax and V50-V64 values (in 2 Gy increments) were determined for each patient. Tumor volume and infiltration of the swallowing apparatus was defined by CT before induction chemotherapy.Of the 45 patients, 26 (57.8 %) fully regained swallowing function after chemoradiotherapy. A further 12 patients (26.7 %) were able to manage soft, pureed and/or liquid foods; the remaining 7 (15.6 %) were completely dependent on percutaneous endoscopic gastrostomy (PEG). Posttreatment swallowing function was significantly influenced by Dmean to the superior pharyngeal constrictor muscle (PCM, p = 0.041). Correlations between late dysphagia and dose-volume relationships in the superior PCM and soft palate were also observed, which were significant from V60 (p = 0.043) and V58 for the soft palate and superior PCM, respectively. Of the evaluated clinical and tumor-related factors, only alcohol abuse (p = 0.024) had an influence on posttreatment swallowing function.Almost 50 % of patients had deterioration of swallowing function after definitive chemoradiotherapy for laryngopharyngeal cancer. The dose to anatomical structures responsible for swallowing function appears to play a role. Therefore, in selected patients, target volume delineation for radiotherapy of laryngopharyngeal cancer should be optimized on an individual basis to spare the swallowing apparatus.
EVALuna2:18123

Dose Reduction in the Swallowing Area by De-intensification of Radiotherapy in Patients with Head and Neck Cancer in the postoperative Situation - first Plan Analyzes of the DIREKHT Study - Haderlein, Marlen; Speer, Stefan; Hecht, Markus; Merten, Ricarda; Scherl, C.; Semrau, S.; Ott, O.; Fietkau, Rainer (2018)
EVALuna2:36499

Dose reduction to the swallowing apparatus and the salivary glands by de-intensification of postoperative radiotherapy in patients with head and neck cancer: First (treatment planning) results of the prospective multicenter DIREKHT trial - Haderlein, Marlen; Speer, Stefan; Ott, Oliver; Lettmaier, Sebastian; Hecht, Markus; Semrau, Sabine; Frey, Benjamin; Scherl, Claudia; Iro, Heinrich; Kesting, Marco Rainer; Fietkau, Rainer (Cancers, 2020)
Aim: Evaluating radiotherapy treatment plans of the prospective DIREKHT trial (ClinicalTrials.gov, NCT02528955) investigating de-intensification of radiotherapy in patients with head and neck cancer. Patients and Methods: The first 30 patients from the DIREKHT trial of the leading study centre were included in this analysis. Standard treatment plans and study treatment plans derived from the protocol were calculated for each patient. Sizes of planning target volumes (PTVs) and mean doses to organs at risk were compared using the Student’s t-test with paired samples. Results: Mean PTV3 including primary tumor region and ipsilateral elective neck up to a dose of 50 Gy in the study treatment plans was 662 mL (+/− 165 mL standard deviation (SD)) and therefore significantly smaller than those of the standard treatment plans (1166 mL (+/− 266 mL SD). In the medial and inferior constrictor muscles, cricopharyngeal muscle, glottic and supraglottic laryngeal areas, arytenoid cartilages, contralateral major salivary glands highly significant dose reductions (p < 0.0001) of more than 10 Gy were achieved in study treatment plan compared to standard treatment plan. Conclusion: De-intensification of radiotherapy led to smaller planning target volumes and clinical relevant dose reductions in the swallowing apparatus and in the contralateral salivary glands.
CRIS-Team Scopus Importer:2020-03-06
Keywords: De-intensification; Head neck cancer; Ipsilateral elective neck irradiation only; Postoperative; Radiotherapy; Salivary glands; Swallowing apparatus

Drug delivery to atherosclerotic plaques using superparamagnetic iron oxide nanoparticles - Matuszak, Jasmin; Lutz, Barbara; Sekita, Aleksander; Zaloga, Jan; Alexiou, Christoph; Lyer, Stefan; Cicha, Iwona (International Journal of Nanomedicine, 2018)
Introduction: Magnetic drug targeting utilizes superparamagnetic iron oxide nanoparticles (SPIONs) to accumulate drugs in specified vasculature regions. Methods: We produced SPIONs conjugated with dexamethasone phosphate (SPION-DEXA). The efficacy of magnetic drug targeting was investigated in a rabbit model of atherosclerosis induced by balloon injury and high cholesterol diet. Results: In vitro, SPION-DEXA were well-tolerated by endothelial cells. SPION-DEXA were internalized by human peripheral blood mononuclear cells and induced CD163 expression comparable with the free drug. In vivo, magnetic targeting of SPIONs to abdominal aorta was confirmed by histology. Upon vascular injury followed by high-cholesterol diet, early administration of SPION-DEXA enhanced the inflammatory burden in the plaques. Increased macrophage content and larger intima- media thickness were observed in animals treated with SPION-DEXA compared with controls. In advanced atherosclerosis, no beneficial effect of local glucocorticoid therapy was detectable. Conclusion: Magnetic drug targeting represents an efficient platform to deliver drugs to diseased arteries in vivo. However, targeting of vascular injury in the lipid-rich environment using dexamethasone-conjugated SPIONs may cause accelerated inflammatory response.
EVALuna2:35457

Drug-Induced Sleep Endoscopy (DISE) with Target Controlled Infusion (TCI) and Bispectral Analysis in Obstructive Sleep Apnea - Traxdorf, Maximilian; Tschaikowsky, Klaus; Scherl, Claudia; Bauer, Judith; Iro, Heinrich; Angerer, Florian (Journal of Visualized Experiments, 2016)
The aim of this study was to establish a standardized protocol for drug-induced sleep endoscopy (DISE) to differentiate obstruction patterns in obstructive sleep apnea (OSA). Target-controlled infusion (TCI) of the sedative propofol was combined with real-time monitoring of the depth of sedation using bispectral analysis. In an observational study 57 patients (mean age 44.8 years, ± SD 10.5; mean apnea hypopnea Index (AHI) 30.8/hr, ± SD 21.6, mean BMI 28.2 kg/m(2), ± SD 5.3) underwent cardiorespiratory polysomnography followed by DISE with TCI and bispectral analysis. Sleep was induced solely by the intravenous infusion of propofol with a TCI-pump, with an initial target plasma level of 2.0 µg/ml. Under continuous monitoring of the patient's respiration, state of consciousness and value of the bispectral analysis, the target plasma propofol level was raised in steps of 0.2 µg/ml/2 min until the desired depth of sedation was reached. The mean value of the bispectral analysis at the target depth of sedation was determined and the obstruction patterns during DISE-TCI-bispectral analysis then classified according to the VOTE-system. Subsequently the results were analyzed according to polysomnographic and anthropometric data. The occurrence of multilevel obstruction sites across all degrees of severity of OSA clarifies the need for sleep endoscopy prior to upper airway surgery. The advantage of this technique is the reproducibility of the protocol even for heterogeneous groups of patients. In addition, the gradual controlled and standardized increase of the plasma level of propofol with real-time control of the bispectral index leads to a precisely controllable depth of sedation. The DISE-TCI-bispectral analysis procedure is a step towards a required reproducible protocol of sleep endoscopy - capable of standardization. However it is not yet known whether these observed obstruction patterns also correspond to findings in natural sleep.
EVALuna2:16743

Duration of biodynamic changes associated with water resistance therapy - Echternach, Matthias; Koeberlein, Marie; Gellrich, Donata; Guzman, Marco; Laukkanen, Anne Maria; Burk, Fabian; Döllinger, Michael; Richter, Bernhard; Kainz, Marie-Anne (Logopedics Phoniatrics Vocology, 2020)
Introduction:In current voice research, there is a growing interest in semi-occluded vocal tract exercises and their contribution to an increased vocal efficiency. However, there are only few studies on the lasting effects. Material and methods:Eight vocally healthy subjects were asked to sustain a phonation at a comfortable loudness on the vowel /i/, with a Fundamental Frequency of 250 Hz (females) or 125 Hz (males). During phonation the subjects were simultaneously recorded with transnasal High Speed Videoendoscopy (HSV, 20,000fps), electroglottography, and audio signals. The subjects then performed a water resistance therapy (WRT) for 10 min (tube: 30 cm length, 5 cm below water surface, diameter 9 mm). Repeated measurements of sustained phonation were performed 0, 5, 10, 20, and 30 min after exercising. From the HSV material the Glottal Area Waveform (GAW) was segmented and GAW parameters were computed. Results:There were strong inter-individual differences concerning the changes of different measures over time after WRT. In general, directly after WRT there was a lowering of the GAW derived Period Perturbation Quotient, a lowering of the Closing Quotient and an increase of the Sound Pressure Level (SPL) in comparison to the pre-intervention measurement. However, only 5 min post WRT there was no longer a clear difference compared to baseline results before WRT. Other values such as Open Quotients exhibited no evident changes by WRT at any timepoint. Conclusions:WRT showed strong inter-individual effects concerning the changes in the evaluated measures post-intervention. General tendencies of some measures directly after the intervention showed a brief effect of only a few minutes.
CRIS-Team WoS Importer:2020-07-31

Dynamics and Information Import in Recurrent Neural Networks - Metzner, Claus; Krauß, Patrick (Frontiers in Computational Neuroscience, 2022)
Recurrent neural networks (RNNs) are complex dynamical systems, capable of ongoing activity without any driving input. The long-term behavior of free-running RNNs, described by periodic, chaotic and fixed point attractors, is controlled by the statistics of the neural connection weights, such as the density d of non-zero connections, or the balance b between excitatory and inhibitory connections. However, for information processing purposes, RNNs need to receive external input signals, and it is not clear which of the dynamical regimes is optimal for this information import. We use both the average correlations C and the mutual information I between the momentary input vector and the next system state vector as quantitative measures of information import and analyze their dependence on the balance and density of the network. Remarkably, both resulting phase diagrams C(b, d) and I(b, d) are highly consistent, pointing to a link between the dynamical systems and the information-processing approach to complex systems. Information import is maximal not at the “edge of chaos,” which is optimally suited for computation, but surprisingly in the low-density chaotic regime and at the border between the chaotic and fixed point regime. Moreover, we find a completely new type of resonance phenomenon, which we call “Import Resonance” (IR), where the information import shows a maximum, i.e., a peak-like dependence on the coupling strength between the RNN and its external input. IR complements previously found Recurrence Resonance (RR), where correlation and mutual information of successive system states peak for a certain amplitude of noise added to the system. Both IR and RR can be exploited to optimize information processing in artificial neural networks and might also play a crucial role in biological neural systems.
CRIS-Team Scopus Importer:2022-09-16
Keywords: dynamical system; edge of chaos; information processing; recurrent neural networks (RNNs); resonance phenomena

Dynamic vocal fold parameters with changing adduction in ex-vivo hemilarynx experiments - Döllinger, Michael; Berry, David A.; Kniesburges, Stefan (Journal of the Acoustical Society of America, 2016)
Ex-vivo hemilarynx experiments allow the visualization and quantification of three-dimensional dynamics of the medial vocal fold surface. For three excised human male larynges, the vibrational output, the glottal flow resistance, and the sound pressure during sustained phonation were analyzed as a function of vocal fold adduction for varying subglottal pressure. Empirical eigenfunctions, displacements, and velocities were investigated along the vocal fold surface. For two larynges, an increase of adduction level resulted in an increase of the glottal flow resistance at equal subglottal pressures. This caused an increase of lateral and vertical oscillation amplitudes and velocity indicating an improved energy transfer from the airflow to the vocal folds. In contrast, the third larynx exhibited an amplitude decrease for rising adduction accompanying reduction of the flow resistance. By evaluating the empirical eigenfunctions, this reduced flow resistance was assigned to an unbalanced oscillation pattern with predominantly lateral amplitudes. The results suggest that adduction facilitates the phonatory process by increasing the glottal flow resistance and enhancing the vibrational amplitudes. However, this interrelation only holds for a maintained balanced ratio between vertical and lateral displacements. Indeed, a balanced vertical-lateral oscillation pattern may be more beneficial to phonation than strong periodicity with predominantly lateral vibrations.
EVALuna2:33167

EAONO/JOS classification for acquired cholesteatoma: evaluating the impact of the number of affected sites on treatment and outcomes - Renner, Beatrix; de Vasconcelos Craveiro, Antonio; Balk, Matthias; Allner, Moritz; Sievert, Matti; Mueller, Sarina K.; Mantsopoulos, Konstantinos; Iro, Heinrich; Rupp, Robin; Hornung, Joachim; Gostian, Antoniu-Oreste (European Archives of Oto-Rhino-Laryngology, 2023)
Purpose: The European and Japanese system for cholesteatoma classification proposed an anatomical differentiation in five sites. In stage I disease, one site would be affected and in stage II, two to five. We tested the significance of this differentiation by analyzing the influence of the number of affected sites on residual disease, hearing ability and surgical complexity. Methods: Cases of acquired cholesteatoma treated at a single tertiary referral center between 2010-01-01 and 2019-07-31 were retrospectively analyzed. Residual disease was determined according to the system. The air–bone gap mean of 0.5, 1, 2, 3 kHz (ABG) and its change with surgery served as hearing outcome. The surgical complexity was estimated regarding the Wullstein’s tympanoplasty classification and the procedure approach (transcanal, canal up/down). Results: 513 ears (431 patients) were followed-up during 21.6 ± 21.5 months. 107 (20.9%) ears had one site affected, 130 (25.3%) two, 157 (30.6%) three, 72 (14.0%) four and 47 (9.2%) five. An increasing number of affected sites resulted in higher residual rates (9.4–21.3%, p = 0.008) and surgical complexity, as well poorer ABG (preoperative 14.1 to 25.3 dB, postoperative 11.3–16.8 dB, p < 0.001). These differences existed between the means of cases of stage I and II, but also when only considering ears with stage II classification. Conclusion: The data showed statistically significant differences when comparing the averages of ears with two to five affected sites, questioning the pertinence of the differentiation between stages I and II.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Cholesteatoma; EAONO/JOS classification; Tympanoplasty

Early stage oropharyngeal carcinomas: comparing quality of life for different treatment modalities - Ryzek, Don-Felix; Mantsopoulos, Konstantinos; Künzel, Julian; Grundtner, Philipp; Zenk, Johannes; Iro, Heinrich; Psychogios, Georgios (BioMed Research International, 2014)
To compare long-term quality of life outcomes after treating early stage oropharyngeal carcinoma either with surgery, surgery combined with radiotherapy, or surgery combined with chemoradiotherapy.Questionnaire based method: 111 eligible patients agreed to fill out a quality of life questionnaire.Of the 32 scales contained in the EORTC's combined QLQ-C30 and HN35, 11 scales show significantly better results for the surgery-only treatment group when compared to either surgery combined with radiotherapy or surgery combined with any type of adjuvant therapy. These eleven scales are role function (P = 0.019/0.008), social function (P = 0.01/0.034), nausea (P = 0.017/0.025), pain (P = 0.014/0.023), financial problems (P = 0.030/0.012), speech (P = 0.02/0.015), social eating (P = 0.003/<0.001), mouth opening (P = 0.033/0.016), sticky saliva (P = 0.001/<0.001), swallowing (P < 0.001/<0.001), and dry mouth (P < 0.001/0.001).Treatment of early stage oropharyngeal carcinoma with surgery alone has definite advantages over treatments including any form of adjuvant therapy when considering quality of life. Advantages manifest themselves especially in functional aspects of the head and neck realm; however general health aspects as well as psychosocial aspects show improvements as well. This study does not show any indication of QOL-related drawbacks of surgery-only treatment approaches.
EVALuna2:19929

Easy detection of MS-CT-invisible temporal bone fracture via FD-CT: a case report - Eisenhut, Felix; Taha, Lava; Wiesmüller, Marco; Lang, Stefan (Laryngo-Rhino-Otologie, 2023)
CRIS-Team WoS Importer:2023-05-19

Easy-to-Prepare Coating of Standard Cell Culture Dishes for Cell-Sheet Engineering Using Aqueous Solutions of Poly(2-n-propyl-oxazoline) - Ryma, Matthias; Bloehbaum, Julia; Singh, Raminder; Sancho, Ana; Matuszak, Jasmin; Cicha, Iwona; Groll, Juergen (ACS Biomaterials Science and Engineering, 2019)
Cell-sheet technology is a well-known method by which cells are grown on thermoswitchable substrates that become nonadhesive upon cooling, such that a complete layer of adherent cells, along with the produced extracellular matrix, detaches as a sheet. Polymers that exhibit a lower critical solution temperature (LCST) below physiological temperature in water, commonly poly(N-isopropylacrylamide) (PNIPAM), are covalently grafted or, for block copolymers, physisorbed onto substrates in a monomolecular thin film to achieve this. Consequently, such substrates, and the polymers required for film formation, can only be prepared in a chemical lab with profound macromolecular expertise. In this study, we present an easy and robust method to coat standard cell culture dishes with aqueous solutions of commercially available poly(-n-propy1-2-oxazoline) (PnPrOx), a polymer that exhibits LCST behavior. Different standard cell culture dishes were repeatedly coated with 0.1 wt % aqueous solutions of PnPrOx and dried in an oven to create a fully covered and thermoresponsive surface. Using this PnPrOx surface a variety of cell types including endothelial cells, mesenchymal stem cells, and fibroblasts, were seeded and cultured until confluency. By decreasing the temperature to 16 degrees C, viable cell sheets were detached within cell-type dependent time frames and could be harvested for biological analysis. We show that the cytoskeleton rearranges, leading to a more contracted morphology of the cells in the detached cell sheet. The cellular junctions between single cells within the sheet could be detected using immunostainings, indicating that strong and intact intracellular contacts are preserved in the harvested sheets.
CRIS-Team WoS Importer:2019-03-29

Editorial: Auditory perception and phantom perception in brains, minds and machines - Schilling, Achim; Schaette, Roland; Sedley, William; Gerum, Richard Carl; Maier, Andreas; Krauß, Patrick (Frontiers in Neuroscience, 2023)
CRIS-Team Scopus Importer:2023-11-03
Keywords: artificial intelligence; auditory neuroscience; auditory phantom perception; cognitive computational neuroscience; deep neural networks; hearing loss; neuroimaging; tinnitus

Editorial: Brave new world - Focus on nanomedicine - Alexiou, Christoph; Fadeel, Bengt (Biochemical and Biophysical Research Communications, 2015)
EVALuna2:19975

Editorial concerning the 60th birthday of BBRC - Alexiou, Christoph (Biochemical and Biophysical Research Communications, 2019)
CRIS-Team Scopus Importer:2019-10-29

Editorial: Integration of Machine Learning and Computer Simulation in Solving Complex Physiological and Medical Questions - An, Gary; Döllinger, Michael; Li-Jessen, Nicole Y. K. (Frontiers in Physiology, 2022)
CRIS-Team WoS Importer:2022-08-05

Effectiveness of hearing aid provision for severe hearing loss - Engler, Max; Digeser, Frank; Hoppe, Ulrich (HNO, 2022)
Background and objective In practice, the unilateral monosyllabic speech recognition score with hearing aid (WRS65(HA)) is often below the maximum word recognition score with headphones (WRSmax), in particular for subjects with severe hearing loss. The aim of this study was to evaluate the efficiency factor Q of hearing aid provision, the ratio WRS65(HA)/WRSmax, in patients with severe to profound hearing loss. Materials and methods Data from real-ear measurements (REM), pure tone and speech audiogram, and speech recognition with and without hearing aid of 93 ears in 64 patients were examined. The patients visited the authors' hearing center for hearing aid evaluation in 2019. Deviations of the real-ear measured frequency-dependent output level values from the prescription targets NAL-NL2 and DSL v5.0 were analyzed. Spearman correlation coefficients for the speech intelligibility index (SII) were calculated for the parameters WRS65(HA) and Q. Results In more than 67% of the hearing aid fittings, output level values matched the target curves of NAL-NL2 or DSL v5.0 in the range of +/- 5 dB for frequencies from 0.5 to 4 kHz at 65 dB SPL. Nevertheless, WRSmax was not achieved with hearing aid at conversational speech levels of 65 dB SPL (mean deviations: 34.4%). However, WRS65(HA) and Q were best when target values for DSL v5.0 were achieved at 65 dB SPL, which is associated with a higher SII. Conclusion For patients with severe to profound hearing loss, the prescription targets of NAL-NL2 and DSL v5.0 do not provide sufficient amplification for WRSmax to be achieved at a normal speech level of 65 dB SPL. It remains to be investigated whether alternative prescriptions with better audibility for input levels of 50 and 65 dB SPL might improve the effectiveness of hearing aid provision.
CRIS-Team WoS Importer:2022-02-04

Effect of BSA-coated Superparamagnetic Iron Oxide Nanoparticles on Granulosa Cells - Poettler, Marina; Hofmann, Simone; Dürr, Stephan; Unterweger, Harald; Wiest, Irmi; Zaloga, Jan; Alexiou, Christoph; Jeschke, Udo; Janko, Christina (Anticancer Research, 2016)
Since superparamagnetic iron oxide nanoparticles (SPION) possess unique features, they provide a huge platform for medical applications, especially for cancer diagnosis and therapy (e.g. imaging, and drug targeting). However, heterogeneous effects on mammalian cells with regard to reproductive tissue are described. An experimental study was carried out to study the effects of SPIONs on both the expression of steroid hormone receptor and viability of granulosa cells, which play a key role in ovarian health and fertility.Human granulosa cells were cultured in vitro and incubated with different concentrations of SPIONs. After 48 h, steroid receptor expression and cell viability were evaluated.Treatment of granulosa cells with SPIONs did not affect estrogen receptor ?1 or progesterone receptor-A expression and had no significant effect on cell viability.Nanoparticles precoated with bovine serum albumin (BSA) do not alter granulosa cell phenotype, whereas literature suggests that other nanoparticles induce apoptosis and reduce steroid receptor expression. Our data indicate an overall better outcome using SPIONs coated with BSA.
EVALuna2:20012

Effect of Citrate- and Gold-Stabilized Superparamagnetic Iron Oxide Nanoparticles on Head and Neck Tumor Cell Lines during Combination Therapy with Ionizing Radiation - Schreiber, Christoph; Franzen, Tim; Hildebrand, Laura; Stein, René; Friedrich, Bernhard; Tietze, Rainer; Fietkau, Rainer; Distel, Luitpold (Bioengineering, 2022)
Head and neck squamous cell carcinoma (HNSCC) is the sixth most common cancer worldwide. They are associated with alcohol and tobacco consumption, as well as infection with human papillomaviruses (HPV). Therapeutic options include radiochemotherapy, surgery or chemotherapy. Nanoparticles are becoming more and more important in medicine. They can be used diagnostically, but also therapeutically. In order to provide therapeutic alternatives in the treatment of HNSCC, the effect of citrate-coated superparamagnetic iron oxide nanoparticles (Citrate-SPIONs) and gold-coated superparamagnetic iron oxide nanoparticles (Au-SPIONs) in combination with ionizing irradiation (IR) on two HPV positive and two HPV negative HNSCC and healthy fibroblasts and keratinocytes cell lines were tested. Effects on apoptosis and necrosis were analyzed by using flow cytometry. Cell survival studies were performed with a colony formation assay. To better understand where the SPIONs interact, light microscopy images and immunofluorescence studies were performed. The HNSCC and healthy cell lines showed different responses to the investigated SPIONs. The cytotoxic effects of SPIONs, in combination with IR, are dependent on the type of SPIONs, the dose administered and the cell type treated. They are independent of HPV status. Reasons for the different cytotoxic effect are probably the different compositions of the SPIONs and the related different interaction of the SPIONs intracellularly and paramembranously, which lead to different strong formations of double strand breaks.
CRIS-Team WoS Importer:2023-01-13

Effect of functional electric stimulation on phonation in an ex vivo aged ovine model - Jakubaß, Bernhard; Peters, Gregor; Kniesburges, Stefan; Semmler, Marion; Kirsch, Andrijana; Gerstenberger, Claus; Gugatschka, Markus; Döllinger, Michael (Journal of the Acoustical Society of America, 2023)
With age, the atrophy of the thyroarytenoid muscle (TAM), and thus atrophy of the vocal folds, leads to decreased glottal closure, increased breathiness, and a loss in voice quality, which results in a reduced quality of life. A method to counteract the atrophy of the TAM is to induce hypertrophy in the muscle by functional electric stimulation (FES). In this study, phonation experiments were performed with ex vivo larynges of six stimulated and six unstimulated ten-year-old sheep to investigate the impact of FES on phonation. Electrodes were implanted bilaterally near the cricothyroid joint. FES treatment was provided for nine weeks before harvesting. The multimodal measurement setup simultaneously recorded high-speed video of the vocal fold oscillation, the supraglottal acoustic signal, and the subglottal pressure signal. Results of 683 measurements show a 65.6% lower glottal gap index, a 22.7% higher tissue flexibility (measured by the amplitude to length ratio), and a 473.7% higher coefficient of determination (R2) of the regression of subglottal and supraglottal cepstral peak prominence during phonation for the stimulated group. These results suggest that FES improves the phonatory process for aged larynges or presbyphonia.
CRIS-Team Scopus Importer:2023-05-19

Effect of Ligament Fibers on Dynamics of Synthetic, Self-Oscillating Vocal Folds in a Biomimetic Larynx Model - Tur, Bogac; Gühring, Lucia; Wendler, Olaf; Schlicht, Samuel; Drummer, Dietmar; Kniesburges, Stefan (Bioengineering, 2023)
Synthetic silicone larynx models are essential for understanding the biomechanics of physiological and pathological vocal fold vibrations. The aim of this study is to investigate the effects of artificial ligament fibers on vocal fold vibrations in a synthetic larynx model, which is capable of replicating physiological laryngeal functions such as elongation, abduction, and adduction. A multi-layer silicone model with different mechanical properties for the musculus vocalis and the lamina propria consisting of ligament and mucosa was used. Ligament fibers of various diameters and break resistances were cast into the vocal folds and tested at different tension levels. An electromechanical setup was developed to mimic laryngeal physiology. The measurements included high-speed video recordings of vocal fold vibrations, subglottal pressure and acoustic. For the evaluation of the vibration characteristics, all measured values were evaluated and compared with parameters from ex and in vivo studies. The fundamental frequency of the synthetic larynx model was found to be approximately 200–520 Hz depending on integrated fiber types and tension levels. This range of the fundamental frequency corresponds to the reproduction of a female normal and singing voice range. The investigated voice parameters from vocal fold vibration, acoustics, and subglottal pressure were within normal value ranges from ex and in vivo studies. The integration of ligament fibers leads to an increase in the fundamental frequency with increasing airflow, while the tensioning of the ligament fibers remains constant. In addition, a tension increase in the fibers also generates a rise in the fundamental frequency delivering the physiological expectation of the dynamic behavior of vocal folds. <

Effect of postoperative systemic prednisolone on short-term and long-term outcomes in chronic rhinosinusitis with nasal polyps: A multi-centered randomized clinical trial - Mueller, Sarina K.; Wendler, Olaf; Mayr, Susanne; Traxdorf, Maximilian; Hosemann, Werner; Olze, Heidi; Steinhart, Helmut; Wiegand, Susanne; Teymoortash, Afshin; Kuehnel, Thomas; Hackenberg, Stephan; Hummel, Thomas; et al. (Frontiers in Immunology, 2023)
Introduction: The objective of this study was to determine whether postoperative additive systemic steroid administration in chronic rhinosinusitis with nasal polyps (CRSwNP) impacted selected endoscopic, subjective and objective outcome measures. Methods: This was a prospective, randomized, double-blind, placebo-controlled, noninferiority multicenter trial of n=106 patients with CRSwNP. All patients underwent primary functional endoscopic sinus surgery (FESS) followed by topical nasal steroids. Patients were randomized to a systemic steroid or placebo for 1 month. Patients were followed up for 2 years over 9 time points. The primary outcome measures were the differences between groups with respect to the nasal polyp score (NPS) and sinonasal quality of life (SNQoL). Secondary outcome measures included interactions with respect to the Lund-Kennedy score (LKS), sinonasal symptoms, general quality of life (GQoL), 16-item odor identification test scores, recurrence rates, need for revision surgery and mucus biomarker levels. Results: 106 patients were randomized to either the placebo or the systemic steroid group (n=53 per group). Postoperative systemic steroids were not superior to placebo with respect to all primary (p= 0.077) and secondary outcome measures (p>0.05 for all). Reported adverse events were similar between the two groups. Conclusion: In conclusion, the addition of postoperative systemic steroids after primary FESS did not confer a benefit over topical steroid nasal spray alone with respect to NPS, SNQOL, LKS, GQOL, sinonasal symptoms, smell scores, recurrence rates, the need for revision surgery or biomarkers over a short-term follow-up of up to 9 months and a long-term follow-up of up to 24 months in CRSwNP patients. Functional endoscopic surgery did, however, show a strong effect on all outcome measures, which remained relatively stable up to the endpoint at 2 years.
CRIS-Team Scopus Importer:2023-03-31
Keywords: chronic rhinosinusitis; long-term; nasal polyp (NP); postoperative; prednisolone; randomized controlled trial

Effect of Radiotherapy and Chemotherapy on the Immunophenotype of Head and Neck Cancer Cells and the consecutive Activation of dendritic Cells - Grottker, F.; Frey, Benjamin; Gehre, S.; Reichardt, Clara; Sengedorj, Azzaya; Hecht, Markus; Fietkau, Rainer; Rieckmann, T.; Gostian, Antoniu-Oreste; Gaipl, Udo; Rückert, Michael (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Effect of the ventricular folds in a synthetic larynx model - Kniesburges, Stefan; Birk, Veronika; Lodermeyer, Alexander; Schützenberger, Anne; Bohr, Christopher; Becker, Stefan (Journal of Biomechanics, 2017)
EVALuna2:33181

Effects of surgical masks on aerosol dispersion in professional singing - Kniesburges, Stefan; Schlegel, Patrick; Peters, Gregor; Westphalen, Caroline; Jakubaß, Bernhard; Veltrup, Reinhard; Kist, Andreas; Döllinger, Michael; Gantner, Sophia; Kuranova, Liudmila; Benthaus, Tobias; Semmler, Marion; et al. (Journal of Exposure Science and Environmental Epidemiology, 2021)
Background In the CoVID-19 pandemic, singing came into focus as a high-risk activity for the infection with airborne viruses and was therefore forbidden by many governmental administrations. Objective The aim of this study is to investigate the effectiveness of surgical masks regarding the spatial and temporal dispersion of aerosol and droplets during professional singing. Methods Ten professional singers performed a passage of the Ludwig van Beethoven's "Ode of Joy" in two experimental setups-each with and without surgical masks. First, they sang with previously inhaled vapor of e-cigarettes. The emitted cloud was recorded by three cameras to measure its dispersion dynamics. Secondly, the naturally expelled larger droplets were illuminated by a laser light sheet and recorded by a high-speed camera. Results The exhaled vapor aerosols were decelerated and deflected by the mask and stayed in the singer's near-field around and above their heads. In contrast, without mask, the aerosols spread widely reaching distances up to 1.3 m. The larger droplets were reduced by up to 86% with a surgical mask worn. Significance The study shows that surgical masks display an effective tool to reduce the range of aerosol dispersion during singing. In combination with an appropriate aeration strategy for aerosol removal, choir singers could be positioned in a more compact assembly without contaminating neighboring singers all singers.
CRIS-Team WoS Importer:2021-10-15

Effects of the vocal tract on phonation threshold pressure - Fulcher, Lewis; Becker, Stefan; Kniesburges, Stefan; Lodermeyer, Alexander; Kähler, George; Döllinger, Michael (11th Internation conference on voice physiology and biomechanics, 2018)

Efficacy and Safety of a Fixed-Dose Combination of Cinnarizine 20 mg and Dimenhydrinate 40 mg in the Treatment of Patients with Vestibular Vertigo: An Individual Patient Data Meta-Analysis of Randomised, Double-Blind, Controlled Clinical Trials - Scholtz, Arne W.; Hampel, Regina; Weisshaar, Gerhard; Waldfahrer, Frank (Clinical Drug Investigation, 2022)
Background and Objective The source data of four individual randomised, double-blind, reference- and/or placebo-controlled clinical trials with virtually identical study design were pooled for the present meta-analysis. The main objective was to further evaluate the efficacy and safety of the fixed combination of cinnarizine 20 mg and dimenhydrinate 40 mg in comparison to various other antivertigo treatments in patients suffering from central and/or peripheral vestibular vertigo. Methods Adult male and female outpatients were subjected to a 4-week treatment with the fixed combination of cinnarizine 20 mg and dimenhydrinate 40 mg, cinnarizine (20 mg, 50 mg), dimenhydrinate (40 mg, 100 mg), betahistine dimesylate (12 mg), betahistine dihydrochloride (16 mg) and placebo, respectively. The primary efficacy endpoint was the reduction of a validated mean vertigo score (MVS), a composite score of 12 individual vertigo symptoms, the intensities of which were each evaluated by the patients on a 5-point visual analogue scale. For analysis of primary and further secondary efficacy endpoints, baseline-adjusted analysis of covariance (ANCOVA) was used to calculate adjusted least squares means (LSM) with associated two-sided 95% confidence intervals (CIs) for the difference in MVS reductions between treatment groups. Moreover, various sensitivity analyses, responder and subgroup analyses as well as descriptive analyses with respect to safety/tolerability of the treatments were conducted. Results Of 795 randomised patients, 779 belonged to the intent-to treat (ITT) and 723 to the per-protocol (PP) population. The main efficacy analysis was based on the ITT population (mean age 52.1 years, 61% female). The mean decrease of the MVS from baseline to Week 4 in the cinnarizine/dimenhydrinate group (-1.10) proved to be significantly larger than in any of the comparator groups. LSM differences for comparators versus the fixed combination ranged between 0.16 (95% confidence interval (CI) 0.03; 0.30, p = 0.017) for cinnarizine 20 mg and 0.60 (95% CI 0.42; 0.78; p < 0.001) for betahistine dimesylate 12 mg in favour of the fixed combination. Furthermore, after 4 weeks of treatment, 74 patients (24.7%) in the cinnarizine/dimenhydrinate group were completely symptom free (MVS = 0), a significantly greater proportion than in any of the comparator groups. Sensitivity analyses showed that baseline characteristics such as age, sex, duration of vertigo and antivertigo pretreatment had only a very minor and clinically non-relevant impact on the efficacy results regarding the primary efficacy outcome. Subgroup analyses with respect to age groups (< 65 years/>= 65 years) and sex showed no significant differences in efficacy within any of the treatment groups. All treatments were well tolerated. A total of 55 patients (6.9%) reported 75 non-serious adverse events (AEs), and 19 patients (2.4%) discontinued the study prematurely because of AEs. Nearly 95% of the patients (cinnarizine/dimenhydrinate group: 97.9%) rated the tolerability of the study medications as either "good" or "very good". Conclusion The findings of the present meta-analysis indicate that the fixed combination of cinnarizine and dimenhydrinate is a safe and potentially superior treatment option for patients suffering from central and/or peripheral vestibular vertigo, as compared to current standard treatments such as cinnarizine, dimenhydrinate or betahistine given alone in monotherapy.
CRIS-Team WoS Importer:2022-08-05

Efficient Biomedical Image Segmentation on EdgeTPUs at Point of Care - Kist, Andreas; Döllinger, Michael (IEEE Access, 2020)
The U-Net architecture is a state-of-the-art neural network for semantic image segmentation that is widely used in biomedical research. It is based on an encoder-decoder framework and its vanilla version shows already high performance in terms of segmentation quality. Due to its large parameter space, however, it has high computational costs on both, CPUs and GPUs. In a research setting, inference time is relevant, but not crucial for the results. However, especially in mobile, clinical applications a light and fast variant would allow deep-learning assisted, objective diagnosis at the point of care. In this work, we suggest an optimized, tiny-weight U-Net for an inexpensive hardware accelerator. We first mined the U-Net architecture to reduce computational complexity to increase runtime performance by simultaneously keeping the accuracy on a high level. Using an open, biomedical dataset for high-speed videoendoscopy (BAGLS), we show that we can dramatically reduce the parameter space and computations by over 99.8% while keeping the segmentation performance at 95% of our baseline. Using a custom upscaling routine, we further successfully deployed our optimized U-Net to an EdgeTPU hardware accelerator to gain cost-effective speed improvements on conventional computers and to showcase the applicability of EdgeTPUs for biomedical imaging processing of large images on portable devices. Combining the optimized architecture and the EdgeTPU, we gain a speedup of >79-times compared to our initial baseline while keeping high accuracy. This combination allows to provide immediate results to the clinician, especially in constrained computational environments, and an objective diagnosis at the point of care.
CRIS-Team Scopus Importer:2020-08-28
Keywords: convolutional neural network; coral; EdgeTPU; semantic segmentation

Efficient Biomedical Image Segmentation on EdgeTPUs - Kist, Andreas; Döllinger, Michael (Informatik aktuell, 2021)
CRIS-Team Scopus Importer:2021-04-12

Efficient drug-delivery using magnetic nanoparticles–biodistribution and therapeutic effects in tumour bearing rabbits. - Peukert, Wolfgang; Tietze, Rainer; Lyer, Stefan; Dürr, Stephan; Struffert, Tobias; Engelhorn, Tobias; Schwarz, Marc; Eckert, Elisabeth; Göen, Thomas; Vasylyev, Serhiy; Trahms, Lutz; Dörfler, Arnd; et al. (Nanomedicine : nanotechnology, biology, and medicine, 2013)
To treat tumours efficiently and spare normal tissues, targeted drug delivery is a promising alternative to conventional, systemic administered chemotherapy. Drug-carrying magnetic nanoparticles can be concentrated in tumours by external magnetic fields, preventing the nanomaterial from being cleared by metabolic burden before reaching the tumour. Therefore in Magnetic Drug Targeting (MDT) the favoured mode of application is believed to be intra-arterial. Here, we show that a simple yet versatile magnetic carrier-system (hydrodynamic particles diameter <200nm) accumulates the chemotherapeutic drug mitoxantrone efficiently in tumours. With MDT we observed the following drug accumulations relative to the recovery from all investigated tissues: tumour region: 57.2%, liver: 14.4%, kidneys: 15.2%. Systemic intra-venous application revealed different results: tumour region: 0.7%, liver: 14.4 % and kidneys: 77.8%. The therapeutic outcome was demonstrated by complete tumour remissions and a survival probability of 26.7% (P=0.0075). These results are confirming former pilot experiments and implying a milestone towards clinical studies. FROM THE CLINICAL EDITOR This team of investigators studied drug carrying nanoparticles for magnetic drug targeting (MDT), demonstrating the importance of intra-arterial administration resulting in improved clinical outcomes in the studied animal model compared with intra-venous.
Keywords: treatment; drug; delievery; magnetic; nanoparticles

Efficient numerical simulation of the human voice: simVoice – a three-dimensional simulation model based on a hybrid aeroacoustic approach - Maurerlehner, Paul; Schoder, Stefan; Freidhager, Clemens; Wurzinger, Andreas; Hauser, Alexander; Kraxberger, Florian; Falk, Sebastian; Kniesburges, Stefan; Echternach, Matthias; Döllinger, Michael; Kaltenbacher, Manfred (Elektrotechnik und Informationstechnik, 2021)
The process of voice production is a complex process and depends on the correct interaction of the vocal folds and the glottal airstream inducing the primary voice source, which is subsequently modulated by the vocal tract. Due to the restricted access to the glottis, not all aspects of the three-dimensional process can be captured by measurements without influencing the measurement object. Hence, the application of a numerical tool capturing the physical process of phonation can provide an extended database for voice treatment and, therefore, can contribute to an increased effectiveness of voice treatment. However, such numerical models involve complex and demanding procedures to model the material behavior and the mechanical contact of the vocal folds and to realize moving boundaries of the involved physical domains. The present paper proposes a numerical model called simVoice, which circumvents these computational expenses by prescribing the experimentally obtained vocal fold motion within the simulation. Additionally, a hybrid approach for sound computation further enhances the computational efficiency and yields good agreement with acoustic measurements. An analysis of the computational workloads suggests that the key factor for a further increase in efficiency is an optimized flow simulation and source term computation.
CRIS-Team Scopus Importer:2021-04-19
Keywords: computational aeroacoustics (CAA); computational biomechanics; computational fluid dynamics (CFD); human voice production; voice disorders

Efficient Simulation of Macroscopic Molecular Communication: The Pogona Simulator - Drees, Jan Peter; Stratmann, Lukas; Bronner, Fabian; Bartunik, Max; Kirchner, Jens; Unterweger, Harald; Dressler, Falko (Proceedings of the 7th ACM International Conference on Nanoscale Computing and Communication, 2020)
Molecular communication (MC) in pipe networks is a novel technique for wireless data exchange. Simulating such networks accurately is difficult because of the complexity of fluid dynamics at centimeter scales, which existing MC simulators do not model. The new simulator we present combines computational fluid dynamics (CFD) simulation and particle movement predictions. It is optimized to be computationally efficient while offering a high degree of adaptability to complex fluid flows in larger pipe networks. We validate it by comparing the simulation with experimental results obtained in a real-world testbed.<br
Keywords: molecular communication; particle movement; simulation tools; computational fluid dynamics

Elastography of vocal folds - Lamprecht, R.; Maghzinajafabadi, M.; Döllinger, Michael; Semmler, Marion; Sutor, A. (Journal of Physics: Conference Series, 2019)
The diagnosis of changes in the structure of the vocal folds is an important clinical task. There is no approach available, which is capable of getting synchronous spatial and biomechanical properties of them. Whereas biomechanical changes, particularly the elasticity, are a good maker for malignant and benign conditions. To gain the elastic characteristics of the vocal folds we are proposing an endoscopic approach using ultrasound elastography.
CRIS-Team Scopus Importer:2020-02-21

Electrically evoked compound action potentials in cochlear implant users with preoperative residual hearing - Liebscher, Tim; Hornung, Joachim; Hoppe, Ulrich (Frontiers in Human Neuroscience, 2023)
Introduction: Residual hearing in cochlear implant (CI) candidates requires the functional integrity of the nerve in particular regions of the cochlea. Nerve activity can be elicited as electrically evoked compound action potentials (ECAP) after cochlear implantation. We hypothesize that ECAP thresholds depend on preoperative residual hearing ability. Materials and methods: In a retrospective study, we analyzed 84 adult cochlear implant users who had received a Nucleus® CI632 Slim Modiolar Electrode and who preoperatively had had residual hearing. Inclusion criteria were severe to profound hearing loss with preoperative measurable hearing in the ear to receive the implant, postlingual hearing loss, German as native language and correct placement of the electrode, inserted completely into the scala tympani. Electrically evoked compound action potential (ECAP) was recorded intraoperatively. The angular insertion was measured for each electrode contact from postoperative computed tomography to estimate the corresponding spiral ganglion frequency. Pure-tone audiometry and allocated ECAP thresholds were tested to investigate possible correlation. Results: The average of hearing thresholds, tested at 0.5, 1, 2, and 4 kHz (4FPTA) was 82 ± 18 (range 47–129) dB HL. The success rate for recording ECAP thresholds was 96.9%. For all comparable pure-tone frequencies (1, 2, 4, and 8 kHz), there was significant correlation between preoperative hearing levels and intraoperative ECAP thresholds (p < 0.001). Higher hearing thresholds are associated with increased ECAP thresholds. Conclusion: In CI candidates with adequate residual hearing, intraoperative electrophysiological measurement records lower thresholds. This outcome may be explained by the neural survival density of the peripheral system, with less neural degeneration.
CRIS-Team Scopus Importer:2023-10-27
Keywords: cochlear implant; electrically evoked compound action potential; nerve-electrode interface; outcome prediction; peripheral neural survival; pure-tone audiometry; residual hearing

Electrode Translocations in Perimodiolar Cochlear Implant Electrodes: Audiological and Electrophysiological Outcome - Liebscher, Tim; Mewes, Alexander; Hoppe, Ulrich; Hornung, Joachim; Brademann, Goetz; Hey, Matthias (Zeitschrift für Medizinische Physik, 2020)
Introduction: Despite using the soft-surgery technique, cochlear implantation may increase the damage of the intracochlear structures due to a scalar translocation of the electrode. The aim of this work was to investigate the incidence as well as the audiological and electrophysiological outcome for electrode translocations and complete scala tympani insertions of perimodiolar electrodes within a large group of patients. Material and methods: The investigations were performed retrospectively on 255 adult subjects with a Nucleus Contour Advance or Slim Modiolar electrode (Cochlear Ltd.). The scalar position was assessed by postoperative rotational tomography. Intraoperative and one year after CI activation measured ECAP thresholds were examined as well as the postoperative speech recognition in quiet using the Freiburg monosyllable word test. Results: The incidence of a translocation was significantly lower with the Slim Modiolar than with the Contour Advance electrode (5.1% versus 32.3%; p< 0.05). With a scala tympani placement the median speech recognition score was 75% (range: 20- 100%) with the Contour Advance and 72.5% (range: 27.5-95%) with the Slim Modiolar electrode. In cases with an electrode translocation, speech recognition scores show a median of 75% (range: 45-100%) and 73.8% (range: 40-80%), respectively. No significant differences in speech recognition were found between translocations and scala tympani insertions with both electrodes. Compared to scala tympani insertions, electrode translocations yielded higher ECAP thresholds at apical and medial electrode contacts (p< 0.05). Conclusion: The incidence of an electrode translocation is determined for both perimodiolar electrode types analyzed in this work. ECAP measurements provide additional information for detecting translocations compared to radiological imaging. However, the postoperative speech recognition in quiet was not affected by the scalar position in the electrodes examined here.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Cochlear implant; Computed tomography; Electrically evoked compound action potential; Electrode design; Electrode location; Scalar translocation; Speech recognition

Emergency cricothyrotomy in infants - Evaluation of a novel device in an animal model - Metterlein, Tom; Frommer, M.; Kwok, P.; Lyer, Stefan; Graf, B. M.; Sinner, B. (Pediatric Anesthesia, 2011)
Background: According to different algorithms of airway management, emergency cricothyrotomy is the final step in managing an otherwise not accessible airway. As an alternative to an open surgical procedure, minimally invasive approaches exist. Quicktrach baby™ is a commercially available set for a minimal invasive cricothyrotomy in infants. The set consists of a plastic cannula over a metal needle for direct placement in the trachea. So far, this device has not been evaluated for its intended use. Objectives: We hypothesize that Quicktrach baby™ allows the establishment of an emergency airway. The aim was to prove that the device is easy to handle and the cricothyrotomy fast to perform. Methods: After approval of the local ethics committee, the study was performed on the cadavers of 10 adult rabbits. Cricothyrotomy was performed with Quicktrach baby™. Successful placement, performance time, and complication rate were documented. Possible ventilation with a breathing bag was evaluated. Data are reported as mean and interquartile range. Results: Successful placement of Quicktrach baby™ was possible in all attempts. The placement took 31 [23-43] s. In two cases, a fracture of the cricoid's cartilage was seen. In one animal, damage to the posterior wall mucosa was observed. In all cases, sufficient ventilation was possible. Conclusions: Quicktrach™ baby proved to be a reliable technique. In the animal model, it is easy and fast to perform. Only a few minor complications occurred. Sufficient ventilation was possible in all attempts. © 2011 Blackwell Publishing Ltd.
CRIS-Team Scopus Importer:2022-06-27
Keywords: cricothyrotomy; emergency; pediatric airway management; Quicktrach baby™

Endoscopic Laser-Based 3D Imaging for Functional Voice Diagnostics - Semmler, Marion; Kniesburges, Stefan; Parchent, Jonas; Jakubass, Bernhard; Zimmermann, Maik; Bohr, Christopher; Schützenberger, Anne; Döllinger, Michael (Applied Sciences, 2017)
Recently, we reported on the in vivo application of a miniaturized measuring device for 3D visualization of the superior vocal fold vibrations from high-speed recordings in combination with a laser projection unit (LPU). As a long-term vision for this proof of principle, we strive to integrate the further developed laserendoscopy as a diagnostic method in daily clinical routine. The new LPU mainly comprises a Nd:YAG laser source (532nm/CW/2 omega) and a diffractive optical element (DOE) generating a regular laser grid (31 x 31 laser points) that is projected on the vocal folds. By means of stereo triangulation, the 3D coordinates of the laser points are reconstructed from the endoscopic high-speed footage. The new design of the laserendoscope constitutes a compromise between robust image processing and laser safety regulations. The algorithms for calibration and analysis are now optimized with respect to their overall duration and the number of required interactions, which is objectively assessed using binary classifiers. The sensitivity and specificity of the calibration procedure are increased by 40.1% and 22.3%, which is statistically significant. The overall duration for the laser point detection is reduced by 41.9%. The suggested semi-automatic reconstruction software represents an important stepping-stone towards potential real time processing and a comprehensive, objective diagnostic tool of evidence-based medicine.
EVALuna2:33213

Endoscopic laser diverticulotomy in Zenker's diverticulum: Experiences with basal wound sealing using a collagen-fibrin patch - Koch, Michael; Thimsen, Vivian; Traxdorf, Maximilian; Zenk, J.; Iro, Heinrich; Treutlein, Eric; Mantsopoulos, Konstantinos (European Review for Medical and Pharmacological Sciences, 2021)
OBJECTIVE: Very few reports investigated techniques of closure of the basal wound area to reduce severe complications like mediastinitis after endoscopic laser diverticulotomy. In this study, we report our experiences after routine use of a collagen-fibrin sealant patch for basal wound covering after laser diverticulotomy in consideration of postoperative complications and recurrence rates. PATIENTS AND METHODS: This retrospective study was conducted in a tertiary referral center and university hospital. Endoscopic laser diverticulotomies performed in our hospital between January 2006 and July 2018 were included. After complete transection of the laser septum of the diverticulum, we placed a collagen-fibrin patch onto the basal wound area to cover the opening to the mediastinum. Patient records were evaluated to assess the occurrence of perioperative complications, and the data were compared with those reported in the literature. RESULTS: A total of 127 endoscopic laser diverticulotomies were performed in 109 patients (71 men, 38 women) suffering from Zenker's diverticulum. Morality rate was 0%, in particular no mediastinitis was observed. Mediastinal emphysema was observed in two patients (1.6%), and temporary or persistent recurrent nerve palsy in one patient (0.8%) each. The mean follow-up period was 71.6±5.16 months. Recurrent symptomatic diverticulum was observed in 19.3% of the patients. CONCLUSIONS: These findings suggest that use of a collagen-fibrin sealant patch in endoscopic laser diverticulotomy may contribute to the safety of endoscopic controlled laser diverticulotomy without comprising the success rates.
CRIS-Team Scopus Importer:2021-08-06
Keywords: CO; Complications; Endoscopic; Minimally invasive; Treatment; Zenker's diverticulum

Endoscopic management of lateral sphenoid cerebrospinal fluid leaks: Identifying a radiographic parameter for surgical planning - Mueller, Sarina K.; Maxfield, Alice Z.; Mueller, Sarina K.; Raquib, Aaishah R.; Sedaghat, Ahmad R.; Bergmark, Regan W.; Metson, Ralph B.; Holbrook, Eric H.; Bleier, Benjamin S.; Gray, Stacey T. (Laryngoscope Investigative Otolaryngology, 2020)
Objective Repair of cerebrospinal fluid (CSF) leaks of the lateral recess of the sphenoid (LRS) sinus can be challenging to accomplish via an endoscopic transphenoidal approach. The endoscopic transpterygoid approach can improve surgical access to the lateral recess but requires more extensive surgical dissection. We review our experience with LRS CSF leak repair via both techniques to determine whether preoperative radiologic data can help predict the most appropriate surgical approach.
CRIS-Team WoS Importer:2020-06-23

Endoscopic surgery for intraconal orbital tumors Endoskopische Chirurgie bei intrakonalen Orbitatumoren - Mueller, Sarina K.; Bleier, Benjamin S. (HNO, 2022)
Traditionally, external craniofacial approaches have been used for orbital tumor resection. Over the last 30 years, endoscopic sinonasal and skull base techniques have become widely used throughout the world. These experiences paved the way for the extension of transnasal endoscopic techniques to the intraconal orbit. Transnasal endoscopic intraconal surgery has several advantages regarding morbidity and outcome as compared with purely external approaches. However, the anatomical knowledge and experience of the surgeon is crucial for the success of the surgery. Endoscopic approaches for intraconal tumor removal are feasible for medial and inferior lesions as well as for lesions lateral to the optic nerve provided they remain inferior to the “plane of resectability” and no optic nerve retraction is required. As intraorbital tumors are rare, new international staging systems including CHEER (Cavernous Hemangioma Exclusively Endonasal Resection) and ORBIT (Orbital Resection by Intranasal Technique) help to standardize safety, efficacy, and outcome.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Craniofacial; Diplopia; Endoscopy; Intraorbital tumors; Transnasal

Endothelial biocompatibility and accumulation of SPION under flow conditions - Matuszak, Jasmin; Zaloga, Jan; Friedrich, Ralf P.; Lyer, Stefan; Nowak, Johannes; Odenbach, Stefan; Alexiou, Christoph; Cicha, Iwona (Journal of Magnetism and Magnetic Materials, 2015)
Magnetic targeting is considered a promising method to accumulate the nanoparticles at the sites of atherosclerotic lesions, but little is known about the biological effects of magnetic nanoparticles on the vascular wall. Here, we investigated endothelial cell growth and vitality upon treatment with SPION (0-60 μg/mL) using two complementing methods: real-time cell analysis and live-cell microscopy. Moreover, the uptake of circulating superparamagnetic iron oxide nanoparticles (SPIONs) was assessed in an in vitro model of arterial bifurcations. At the tested concentrations, SPIONs were well tolerated and had no major influence on endothelial cell growth. Our results further showed a uniform distribution of endothelial SPION uptake independent of channel geometry or hemodynamic conditions: In the absence of magnetic force, no increase in accumulation of SPIONs at non-uniform shear stress region at the outer walls of bifurcation was observed. Application of external magnet allowed enhanced accumulation of SPIONs at the regions of non-uniform shear stress. Increased uptake of SPIONs at non-uniform shear stress region was well tolerated by endothelial cells (ECs) and did not affect endothelial cell viability or attachment. These findings indicate that magnetic targeting can constitute a promising and safe technique for the delivery of imaging and therapeutic nanoparticles to atherosclerotic lesions.
CRIS-Team Scopus Importer:2022-06-27
Keywords: Atherosclerosis; Biocompatibility; Endothelial cell; Live-cell analysis; Magnetic nanoparticle; SPION uptake

Endothelialization of Whey Protein Isolate-Based Scaffolds for Tissue Regeneration - Genc, Hatice; Friedrich, Bernhard; Alexiou, Christoph; Pietryga, Krzysztof; Cicha, Iwona; Douglas, Timothy E.L. (Molecules, 2023)
Background: Whey protein isolate (WPI) is a by-product from the dairy industry, whose main component is β-lactoglobulin. Upon heating, WPI forms a hydrogel which can both support controlled drug delivery and enhance the proliferation and osteogenic differentiation of bone-forming cells. This study makes a novel contribution by evaluating the ability of WPI hydrogels to support the growth of endothelial cells, which are essential for vascularization, which in turn is a pre-requisite for bone regeneration. Methods: In this study, the proliferation and antioxidant levels in human umbilical vascular endothelial cells (HUVECs) cultured with WPI supplementation were evaluated using real-time cell analysis and flow cytometry. Further, the attachment and growth of HUVECs seeded on WPI-based hydrogels with different concentrations of WPI (15%, 20%, 30%, 40%) were investigated. Results: Supplementation with WPI did not affect the viability or proliferation of HUVECs monitored with real-time cell analysis. At the highest used concentration of WPI (500 µg/mL), a slight induction of ROS production in HUVECs was detected as compared with control samples, but it was not accompanied by alterations in cellular thiol levels. Regarding WPI-based hydrogels, HUVEC adhered and spread on all samples, showing good metabolic activity. Notably, cell number was highest on samples containing 20% and 30% WPI. Conclusions: The demonstration of the good compatibility of WPI hydrogels with endothelial cells in these experiments is an important step towards promoting the vascularization of hydrogels upon implantation in vivo, which is expected to improve implant outcomes in the future.
CRIS-Team Scopus Importer:2023-11-10
Keywords: 3D cell seeding; endothelial cell compatibility; hydrogels; thiol levels; tubular scaffolds; whey protein

Enhancer hijacking activates oncogenic transcription factor NR4A3 in acinic cell carcinomas of the salivary glands - Haller, Florian; Bieg, Matthias; Will, Rainer; Koerner, Cindy; Weichenhan, Dieter; Bott, Alexander; Ishaque, Naveed; Lutsik, Pavlo; Moskalev, Evgeny; Müller, Susanna; Baehr, Marion; Woerner, Angelika; et al. (Nature Communications, 2019)
The molecular pathogenesis of salivary gland acinic cell carcinoma (AciCC) is poorly understood. The secretory Ca-binding phosphoprotein (SCPP) gene cluster at 4q13 encodes structurally related phosphoproteins of which some are specifically expressed at high levels in the salivary glands and constitute major components of saliva. Here we report on recurrent rearrangements [t(4;9)(q13;q31)] in AciCC that translocate active enhancer regions from the SCPP gene cluster to the region upstream of Nuclear Receptor Subfamily 4 Group A Member 3 (NR4A3) at 9q31. We show that NR4A3 is specifically upregulated in AciCCs, and that active chromatin regions and gene expression signatures in AciCCs are highly correlated with the NR4A3 transcription factor binding motif. Overexpression of NR4A3 in mouse salivary gland cells increases expression of known NR4A3 target genes and has a stimulatory functional effect on cell proliferation. We conclude that NR4A3 is upregulated through enhancer hijacking and has important oncogenic functions in AciCC.
EVALuna2:35381

Epidemiology and survival of HPV-related tonsillar carcinoma - Psychogios, Georgios; Alexiou, Christoph; Agaimy, Abbas; Brunner, Kathrin; Koch, Michael; Mantsopoulos, Konstantinos; Tomppert, Andrea; Iro, Heinrich (Cancer Medicine, 2014)
The aim of this study was to determine the proportion of human papilloma virus (HPV)-positive cases in tonsillar carcinomas and investigate its development over the last decade. Further aim was to show the oncologic results in accord to HPV status and various treatment modalities. A retrospective study was conducted between 2000 and 2012 and included 275 patients treated for tonsillar carcinoma. P16 immunohistochemistry was used as a surrogate marker for HPV-associated carcinogenesis. A total of 101 (36.7%) patients proved to be p16 positive and 174 p16 negative. 80.2% of the p16-positive cases presented with T1-2 tumor. Of the early-stage patients, 79% of the p16-positive and 52.3% of the p16-negative presented with lymph node metastases. The percentage of p16-positive patients increased from 23.2% in the period 2005-2007 to 58.6% in the period 2010-2012 in the whole population and from 30.9% to 76.9% in T1-2 carcinomas. Early T-category p16-positive carcinomas had significantly better disease-specific survival (92.4% vs. 75.5%, P = 0.007) and overall survival (OS, 79.6% vs. 54.3%, P < 0.001) compared to p16-negative tumors. This study showed an increase in the percentage of p16-positive patients in tonsillar carcinoma from 23.2% in the years between 2005 and 2007 to 58.6% between 2010 and 2012. The majority (80.2%) of p16-positive patients presented with early T-category tumor but most of these (79.0%) had also lymph node metastases. Nevertheless, p16-positive patients had excellent oncologic results after surgery and adjuvant radiotherapy and could be considered for de-escalation of treatment.
EVALuna2:6679

Erlanger Modell der Tinnitusentstehung – Perspektivwechsel und neue Behandlungsstrategie - Schulze, Holger; Schilling, Achim; Krauß, Patrick; Tziridis, Konstantin (HNO, 2023)
Background: About one sixth of the population of western industrialized nations suffers from chronic, subjective tinnitus, causing socioeconomic treatment and follow-up costs of almost 22 billion euros per year in Germany alone. According to the prevailing view, tinnitus develops as a consequence of a maladaptive neurophysiological process in the brain triggered by hearing loss. Objectives: The Erlangen model of tinnitus development presented here is intended to propose a comprehensive neurophysiological explanation for the initial occurrence of the phantom sound after hearing loss. Based on the model, a new treatment strategy will be developed. Materials and methods: The model summarized here is based on various animal and human physiological studies conducted in recent years. Results: The Erlangen model considers subjective tinnitus as a side effect of a physiological mechanism that permanently optimizes information transmission into the auditory system by means of stochastic resonance (SR) even in the healthy auditory system. In fact, hearing-impaired patients with tinnitus hear better on average than those without tinnitus. This unfamiliar perspective on the phantom percept may already help affected patients to cope better with their suffering. In addition, based on the model, low intensity noise tinnitus suppression (LINTS) has been developed as a new, individually adapted treatment strategy for tonal tinnitus and has already been successfully tested in patients. Conclusions: A possible limiting factor for the model and treatment strategy is the pitch of the tinnitus percept, which may require adjustments to the treatment strategy for frequencies above about 5 kHz.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Autocorrelation; Hearing optimization; Low intensity noise tinnitus suppression (LINTS); Rehabilitation; Stochastic resonance

Erratum to: Validation of a predictive model for speech discrimination after cochlear impIant provision (HNO, (2023), 10.1007/s00106-023-01285-y) - Hoppe, Ulrich; Hast, Anne; Hocke, Thomas (HNO, 2023)
The article Validation of a predictive model for speech discrimination after cochlear impIant provision, written by Ulrich Hoppe et al., was originally published electronically on the publisher’s internet portal on 05.04.2023 without open access. With the author(s)’ decision to opt for Open Choice the copyright of the article changed to © The Author(s) 2023 and the article is forthwith distributed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article’s Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article’s Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence, visit.
CRIS-Team Scopus Importer:2023-08-18

Error detection and filtering of incompressible flow simulations for aeroacoustic predictions of human voice - Schoder, Stefan; Kraxberger, Florian; Falk, Sebastian; Wurzinger, Andreas; Roppert, Klaus; Kniesburges, Stefan; Döllinger, Michael; Kaltenbacher, Manfred (Journal of the Acoustical Society of America, 2022)
The presented filtering technique is proposed to detect errors and correct outliers inside the acoustic sources, respectively, the first time derivative of the incompressible pressure obtained from large eddy simulations with prescribed vocal fold motion using overlay mesh methods. Regarding the perturbed convective wave equation, the time derivative of the incompressible pressure is the primary sound source in the human phonation process. However, the incompressible pressure can be erroneous and have outliers when fulfilling the divergence-free constraint of the velocity field. This error is primarily occurring for non-conserving prescribed vocal fold motions. Therefore, the method based on a continuous stationary random process was designed to detect rare events in the time derivative of the pressure. The detected events are then localized and treated by a defined window function to increase their probability. As a consequence, the data quality of the non-linearly filtered data is enhanced significantly. Furthermore, the proposed method can also be used to assess convergence of the aeroacoustic source terms, and detect regions and time intervals, which show a non-converging behavior by an impulse-like structure.
CRIS-Team Scopus Importer:2022-09-30

Escalation in mucus cystatin 2, pappalysin-A, and periostin levels over time predict need for recurrent surgery in chronic rhinosinusitis with nasal polyps - Mueller, Sarina K.; Wendler, Olaf Dietrich; Nocera, Angela; Grundtner, Philipp; Schlegel, Patrick; Agaimy, Abbas; Iro, Heinrich; Bleier, Benjamin S. (International Forum of Allergy and Rhinology, 2019)
Background: Chronic rhinosinusitis with nasal polyps (CRSwNP) is treated using oral/topical steroids and surgery. Despite maximal medical therapy, some patients remain recalcitrant. Mucus cystatin 2, pappalysin-A, and periostin can predict the presence of CRSwNP and correlate with disease severity. This study was designed to determine whether prospective sampling of these mucus proteins could predict medical failure and the need for revision surgery. Methods: This investigation was an institutional review board‒approved, prospective study of 66 patients with CRSwNP. All patients underwent surgery, administration of topical/oral steroids, and outpatient mucus sampling at 10 time-points over 2 years. Five proteins, including cystatin 2 (CST2), pappalysin-A (PAPP-A), and periostin (PST), were analyzed and correlated with subjective parameters (including scores on the 22-item Sino-Nasal Outcomes Test [SNOT-22]). Variables were then analyzed and compared between those requiring revision surgery within 2 years (n = 5) and those with stable disease (n = 61). Results: All patients demonstrated a significant decline in CST2, PAPP-A, and periostin after their initial surgery. The recalcitrant group demonstrated escalations in all proteins despite steroids, with levels higher than those of the stable group at 1 year (CST2: 258.1 ± 205.2 pg/mL vs 235.3 ± 275.7 pg/mL, p = 0.86; PAPP-A: 170.3 ± 150.4 pg/mL vs 74.6 ± 106.7 pg/mL, p < 0.05; periostin: 188.8 ± 192.4 ng/mL vs 54.5 ± 47.6 ng/mL, p < 0.001). Escalation in all proteins correlated significantly with worsening SNOT-22 score at each time-point (domain 1: 8.2 ± 1.3 vs 5.5 ± 1.1; p < 0.05). Conclusion: Early recurrences and medical recalcitrance in CRSwNP may be predicted noninvasively through the serial, prospective sampling of mucus CST2, PAPP-A, and periostin levels. These biosignatures may help to predict disease course and guide individualized therapy.
CRIS-Team Scopus Importer:2019-08-30
Keywords: biomarker; chronic rhinosinusitis; mucus; noninvasive; recurrence

Estimation of Tinnitus-Related Socioeconomic Costs in Germany - Tziridis, Konstantin; Friedrich, Jana; Brueggemann, Petra; Mazurek, Birgit; Schulze, Holger (International Journal of Environmental Research and Public Health, 2022)
Despite the high prevalence of tinnitus in Germany of nearly 12% of the general population, there have been no systematic studies on the socioeconomic costs for German society caused by tinnitus so far. Here we analyzed data from 258 chronic tinnitus patients-namely tinnitus severity and health utility index (HUI)-and correlated them with their tinnitus-related public health care costs, private expenses, and economic loss due to their tinnitus percept as assessed by questionnaires. We found correlations of the HUI with health care costs and calculated the mean socioeconomic costs per tinnitus patient in Germany. According to our most conservative estimate, these sum up to EUR 4798.91 per year. Of that EUR 2206.95 account for the public health care, EUR 290.45 are carried by the patient privately and the remaining EUR 2301.51 account for economical loss due to sick leave. With a prevalence of 5.5% with at least bothersome tinnitus, this sums up to 21.9 billion Euro per year and with 25.82 sick leave days; tinnitus patients miss work more than double the time of the average German employee (10.9 days). The findings fit within the cost ranges of studies from other European countries and the USA and show that the socioeconomic burden of this disease-like symptom is a global problem. In comparison with the costs of other major chronic diseases in Germany-such as chronic obstructive pulmonary diseases (ca. 16 billion Euro) or diabetes mellitus (ca. 42 billion Euro)-the relevance of the 'symptom' tinnitus for the German social economy becomes even more obvious.
CRIS-Team Scopus Importer:2022-09-09
Keywords: health utility index; hearing loss; socioeconomic costs; tinnitus; tinnitus questionnaire

Evaluation After Cochlear Implant Surgery: Correlation of Clinical Outcome and Imaging Findings using Flat-detector CT - Stock, Annika; Bozzato, Victoria; Kloska, Stephan; Bozzato, Alessandro; Hoppe, Ulrich; Hornung, Joachim; Dörfler, Arnd; Struffert, Tobias (Clinical Neuroradiology, 2020)
Purpose: Assessment of the cochlear implant (CI) electrode array position using flat-detector computed tomography (FDCT) to test dependence of postoperative outcome on intracochlear electrode position. Methods: A total of 102 patients implanted with 107 CIs underwent FDCT. Electrode position was rated as 1) scala tympani, 2) scala vestibuli, 3) scalar dislocation and 4) no deconvolution. Two independent neuroradiologists rated all image data sets twice and the scalar position was verified by a third neuroradiologist. Presurgical and postsurgical speech audiometry by the Freiburg monosyllabic test was used to evaluate auditory outcome after 6 months of speech rehabilitation. Results: Electrode array position was assessed by FDCT in 107 CIs. Of the electrodes 60 were detected in the scala tympani, 21 in the scala vestibuli, 24 electrode arrays showed scalar dislocation and 2 electrodes were not placed in an intracochlear position. There was no significant difference in rehabilitation outcomes between scala tympani and scala vestibuli inserted patients. Rehabilitation was also possible in patients with dislocated electrodes. Conclusion: The use of FDCT is a reliable diagnostic method to determine the position of the electrode array. In our study cohort, the electrode position had no significant impact on postoperative outcome except for non-deconvoluted electrode arrays.
CRIS-Team Scopus Importer:2020-06-26
Keywords: Cochlear implantation; Deafness; Dyna-CT; Misplaced cochlear implant electrode array; Rehabilitation

Evaluation of 2 German Parental Questionnaires: a comparative analysis of the FRAKIS questionnaire for early speech development and the early lexical development inventory ELAN for 2-year-olds - Gleißner, Harald; Eysholdt, U.; Döllinger, Michael; Ziethe, A. (Gesundheitswesen, 2014)
The German parental questionnaires FRAKIS and ELAN are 2 screening instruments, usable in the German preventive paediatric examinations for 2-year-olds. This study investigates the difference between the questionnaires with regard to validity, reliability, time and cost-efficiency and usability in daily clinical practice.The parents of 25 children filled in the questionnaires FRAKIS and ELAN. As a reference test, the German speech development test 2 (SETK-2, Grimm 2000) was applied. Vocabulary results were compared with SETK-2 subtest production I (word production).Both parental questionnaires correlated significantly with the SETK-2 subtest production I. ELAN and FRAKIS showed equal results in classifying patients as "critical-below average" or "uncritical-indifferent".The ELAN as well as FRAKIS are both appropriate screening tools for identifying language developmental delay in 2-year-olds.
EVALuna2:20183

Evaluation of Analytical Modeling Functions for the Phonation Onset Process - Petermann, Simon; Kniesburges, Stefan; Ziethe, Anke; Schützenberger, Anne; Döllinger, Michael (Computational and Mathematical Methods in Medicine, 2016)
The human voice originates from oscillations of the vocal folds in the larynx. The duration of the voice onset (VO), called the voice onset time (VOT), is currently under investigation as a clinical indicator for correct laryngeal functionality. Different analytical approaches for computing the VOT based on endoscopic imaging were compared to determine the most reliable method to quantify automatically the transient vocal fold oscillations during VO. Transnasal endoscopic imaging in combination with a high-speed camera (8000 fps) was applied to visualize the phonation onset process. Two different definitions of VO interval were investigated. Six analytical functions were tested that approximate the envelope of the filtered or unfiltered glottal area waveform (GAW) during phonation onset. A total of 126 recordings from nine healthy males and 210 recordings from 15 healthy females were evaluated. Three criteria were analyzed to determine the most appropriate computation approach: (1) reliability of the fit function for a correct approximation of VO; (2) consistency represented by the standard deviation of VOT; and (3) accuracy of the approximation of VO. The results suggest the computation of VOT by a fourth-order polynomial approximation in the interval between 32.2 and 67.8% of the saturation amplitude of the filtered GAW.
EVALuna2:33202

Evaluation of a Transimpedance Matrix Algorithm to Detect Anomalous Cochlear Implant Electrode Position - Hoppe, Ulrich; Brademann, Goetz; Stöver, Timo; Ramos De Miguel, Angel; Cowan, Robert; Manrique, Manuel; Falcón-González, Juan Carlos; Hey, Matthias; Baumann, Uwe; Huarte, Alicia; Liebscher, Tim; Bennett, Christopher; et al. (Audiology and Neuro-Otology, 2022)
Introduction: Transimpedance measurements from cochlear implant electrodes have the potential to identify anomalous electrode array placement, such as tip fold-over (TFO) or fold-back, basal electrode kinking, or buckling. Analysing transimpedance may thus replace intraoperative or post-operative radiological imaging to detect any potential misplacements. A transimpedance algorithm was previously developed to detect deviations from a normal electrode position with the aim of intraoperatively detecting TFO. The algorithm had been calibrated on 35 forced, tip folded electrode arrays in six temporal bones to determine the threshold criterion required to achieve a sensitivity of 100%. Our primary objective here was to estimate the specificity of this TFO algorithm in patients, in a prospective study, for a series of electrode arrays shown to be normally inserted by post-operative imaging. Methods: Intracochlear voltages were intraoperatively recorded for 157 ears, using Cochlear's Custom Sound™ EP 5 electrophysiological software (Cochlear Ltd., Sydney, NSW, Australia), for both Nucleus® CI512 and CI532 electrode arrays. The algorithm analysed the recorded 22 × 22 transimpedance matrix (TIM) and results were displayed as a heatmap intraoperatively, only visible to the technician in the operating theatre. After all clinical data were collected, the algorithm was evaluated on the bench. The algorithm measures the transimpedance gradients and corresponding phase angles (θ) throughout the TIM and calculates the gradient phase range. If this was greater than the predetermined threshold, the algorithm classified the electrode array insertion as having a TFO. Results: Five ears had no intraoperative TIM and four anomalous matrices were identified from heatmaps and removed from the specificity analysis. Using the 148 remaining data sets (n = 103 CI532 and n = 45 CI512), the algorithm had an average specificity of 98.6% (95.80%-99.75%). Conclusion: The algorithm was found to be an effective screening tool for the identification of TFOs. Its specificity was within acceptable levels and resulted in a positive predictive value of 76%, with an estimated incidence of fold-over of 4% in perimodiolar arrays. This would mean 3 out of 4 cases flagged as a fold-over would be correctly identified by the algorithm, with the other being a false positive. The measurements were applied easily in theatre allowing it to be used as a routine clinical tool for confirming correct electrode placement.
CRIS-Team Scopus Importer:2022-04-22
Keywords: Cochlear implant; Electrical stimulation; Impedance; Intraoperative monitoring; Objective measures; Surgical complications

Evaluation of hearing aid rehabilitation using the Freiburg Monosyllabic Test - Hoppe, Ulrich (HNO, 2016)
The benefit of hearing aids is not always directly subjectively perceivable. Therefore, objective and quantifiable speech audiometric measurements are required. Beside acoustic gain measurements and structured interviews, speech audiometry in quiet and in noise is one of the three pillars of hearing aid evaluation.The Freiburg monosyllabic test has been used for decades for hearing aid prescription and evaluation in German speaking countries. Relative and absolute targets can be individually defined for the rehabilitation of speech perception by hearing aids as assessed by the Freiburg monosyllabic test in quiet and at conversational levels.The general applicability of speech audiometric measurements in noise is limited. Alternative ("modern") methods and the definitions of noise situations relevant to everyday life have been discussed for years. However, the introduction of these methods into everyday use has proven difficult. On one hand, there is comparatively little practical experience; on the other, it has not yet been demonstrated what additional benefits these more complicated measurements might have for standard hearing aid evaluations and hearing aid users.
EVALuna2:33932

Evaluation of hydrogel matrices for vessel bioplotting: Vascular cell growth and viability - Singh, Raminder; Sarker, Bapi; Silva, Raquel; Detsch, Rainer; Dietel, Barbara; Alexiou, Christoph; Boccaccini, Aldo R.; Cicha, Iwona (Journal of Biomedical Materials Research Part A, 2015)
Developing matrices biocompatible with vascular cells is one of the most challenging tasks in tissue engineering. Here, we compared the growth of vascular cells on different hydrogels as potential materials for bioplotting of vascular tissue. Formulations containing alginate solution (Alg, 2%, w/v) blended with protein solutions (silk fibroin, gelatin, keratin, or elastin) at 1% w/v were prepared. Human umbilical vein endothelial cells (ECs), smooth muscle cells (SMCs), and fibroblasts were cultivated on hydrogels for 7 days. Cell number and morphology was visualised using fluorescent staining at day 3 and 7. Cell metabolic activity was analysed using WST assay. Compared to pure Alg, Alg/keratin, Alg/gelatin and Alg/silk fibroin provided superb surfaces for ECs, supporting their attachment, growth, spreading and metabolic activity. SMCs showed best colonization and growth on Alg/silk fibroin and Alg/keratin hydrogels, whereas on elastin-containing hydrogels, cell clustering was observed. Fibroblasts growth was enhanced on Alg/elastin, and strongly improved on silk fibroin- and keratin-containing hydrogels. In contrast to the previous studies with alginate dialdehyde-gelatin crosslinked gels, Alg/gelatin blend hydrogels provided a less favourable scaffold for fibroblasts. Taken together, the most promising results were obtained with silk fibroin- and keratin-containing hydrogels, which supported the growth of all types of vascular cells.
Keywords: alginate-protein hydrogels; biocompatibility; fibroblasts; scaffold endothelialisation; smooth muscle cells

Evaluation of peri-implant bone levels and soft tissue dimensions around zirconia implants-a three-year follow-up study - Kniha, Kim; Schlegel, K. A.; Kniha, H.; Modabber, A.; Hoelzle, F. (International Journal of Oral & Maxillofacial Implants, 2018)
The aim of this study was to measure bone levels around zirconia implants during follow-up of up to 3 years. Additionally, the effect of clinical contact point positions on the papilla deficit was evaluated. Eighty-one patients with 105 zirconia implants were examined at the 3-year follow-up. Bone levels were measured on the date of implant placement and at 3 months, 1year, and 3 years thereafter. Distances between the first bone-implant contact and the contact point of the crowns and between the bone level at the adjacent tooth and the contact point of the crowns were assessed. The effect of the clinical contact point position on the papilla deficit was also assessed. Significant reductions in the distances between the bone-implant contact and the implant shoulder, as well as the contact point of the crowns, and between the bone level at the adjacent tooth and the contact point of the crowns, were found. A significant association was found between the papilla deficit and the height of the contact point. Implant survival was 100% and implant success was 95.4%. While zirconia implants presented little bone loss up to 1year, significant bone apposition was observed up to 3years. Low contact points correlated with full papillae, whereas high contact points were associated with a papilla deficit.
EVALuna2:34228

Evaluation of preoperative Ultrasonography in the Differentiation between Superficial and Deep Parotid Gland Tumors - Mantsopoulos, Konstantinos; Tschaikowsky, Nastasja; Goncalves, Miguel; Mueller, Sarina K.; Iro, Heinrich (Ultrasound in Medicine and Biology, 2020)
Imaging of the intraparotid course of the facial nerve remains a challenge and is not an established routine procedure. The aim of this study was to evaluate ultrasound in localizing a parotid tumor in relation to the facial nerve. The ultrasound findings and operative reports of all patients treated for parotid gland tumors were studied retrospectively. Eight hundred sixty-eight parotid lesions formed our study sample. The unit of measurement was the minimal distance between the parotideomasseteric fascia and the superficial capsule of the tumor, measured in millimeters by means of ultrasound. The mean value for this parameter was 1.3 mm for superficial and 4.6 mm for deep lobe tumors (p < 0.001). When the cutoff value was set at 2.6 mm, the sensitivity and specificity of ultrasound were 89.6 and 88.4%, respectively. Our study revealed that ultrasound can help in the pre-operative differentiation between tumors of the superficial and deep lobes of the parotid gland.
CRIS-Team Scopus Importer:2020-06-09
Keywords: Deep lobe; Facial nerve; Parotid gland; Superficial lobe; Ultrasonography

Evaluation of Respiratory Particle Emission during Otorhinolaryngological Procedures in the Context of the SARS-CoV-2 Pandemic - Veltrup, Reinhard; Kniesburges, Stefan; Döllinger, Michael; Falk, Sebastian; Mueller, Sarina K. (Diagnostics, 2022)
Understanding the risk of infection by routine medical examination is important for the protection of the medical personnel. In this study we investigated respiratory particles emitted by patients during routine otolaryngologic procedures and assessed the risks for the performing physician. We developed two experimental setups to measure aerosol and droplet emission during rigid/flexible laryngoscopy, rhinoscopy, pharyngoscopy, otoscopy, sonography and patient interview for subjects with and without masks. A high-speed-camera setup was used to detect ballistic droplets (approx. > 100 µm) and an aerosol-particle-sizer was used to detect aerosol particles in the range of 0.3 µm to 10 µm. Aerosol particle counts were highly increased for coughing and slightly increased for heavy breathing in subjects without masks. The highest aerosol particle counts occurred during rigid laryngoscopy. During laryngoscopy and rhinoscopy, the examiner was exposed to increased particle emission due to close proximity to the patient’s face and provoked events such as coughing. However, even during sonography or otoscopy without a mask, aerosol particles were expelled close to the examiner. The physician’s exposure to respiratory particles can be reduced by deliberate choice of examination technique depending on medical indication and the use of appropriate equipment for the examiners and the patients (e.g., FFP2 masks for both).
CRIS-Team Scopus Importer:2022-07-15
Keywords: face masks; high-speed visualization; laryngoscopy; optical particle sizer; otoscopy; pharyngoscopy; respiratory particles; rhinoscopy; SARS-CoV-2; sonography

Evidence-based vertigo therapy;Meta-analysis of randomized primary pharmacotherapy trials Evidenzbasierte Schwindeltherapie: Metaanalyse randomisierter Primärstudien zur Pharmakotherapie - Waldfahrer, Frank; Scholtz, Arne W. (Nervenheilkunde, 2022)
The aim of the present meta-analysis was to evaluate the efficacy and safety of the fixed combination of cinnarizine 20 mg and dimenhydrinate 40 mg in comparison with various other antivertigo treatments in patients with central and/or peripheral vestibular vertigo. For this purpose, individual patient data from 4 randomised, double-blind, controlled clinical trials with almost identical study design were pooled. In total, the data of 795 patients with vertigo of different origin (central and/or peripheral-vestibular) were included in the analysis. In all 4 included studies, patients were treated for 4 weeks with the test medication (fixed combination of cinnarizine 20 mg and dimenhydrinate 40 mg), with different comparators (cinnarizine 20 mg, 50 mg, dimenhydrinate 40 mg, 100 mg, betahistine dimesylate 12 mg, betahistine dihydrochloride 16 mg) or a placebo. The main outcome of the meta-analysis was the change in vertigo symptoms after 4 weeks of treatment. Patients' subjective vertigo symptoms were assessed using a validated vertigo score (Mean Vertigo Score, MVS). Secondary outcome measures included various response rates, change in concomitant vegetative symptoms and investigator and patient ratings of efficacy and tolerability. In summary, the results of the present meta-analysis suggest that the fixed combination of cinnarizine 20 mg and dimenhydrinate 40 mg is a potentially superior treatment option for central and/or peripheral vertigo, with significantly better efficacy compared to other antivertigo treatments while being well tolerated.
CRIS-Team Scopus Importer:2022-12-09
Keywords: cinnarizin; dimenhydrinat; evidence-based; Meta-analysis; pharmacotherapy; vertigo

Evolution and changing trends in surgery for benign Parotid tumors - Mantsopoulos, Konstantinos; Koch, Michael; Klintworth, Nils; Zenk, Johannes; Iro, Heinrich (Laryngoscope, 2015)
The ideal extent of surgical intervention for benign parotid tumors remains a matter of controversy. The aim of the study was to trace the development of surgical therapy in a large cohort, explore its changes in a single institution specializing in salivary gland pathologies over the last 12 years, and determine the extent to which a possible shift in the surgical therapy of parotid benign tumors toward less radical methods was correlated with a change in the incidence of facial palsy and Frey's syndrome.Retrospective clinical study.A retrospective evaluation of the records for all patients treated for benign parotid tumors between 2000 and 2012 at a tertiary referral center was carried out. Surgical methods were classified into four groups: extracapsular dissection, partial superficial parotidectomy, superficial parotidectomy, and complete parotidectomy.A total of 1,624 patients were included in the study. Our analysis demonstrated an increase in the total number of parotidectomies for benign lesions from 71 (2000) to 184 (2012), mostly due to the increase in extracapsular dissections (from 9 to 123). Increased performance of less radical surgery was associated with a significantly decreased incidence of temporary and permanent facial palsies (from 22.8% to 9% and 9.8% to 5.9%, respectively) and Frey's syndrome (from 11.3% to 1.6%).One of the most controversial issues in the treatment of benign parotid tumors is the best therapeutic approach to be taken in such patients. Our study showed that increased performance of less radical surgery was associated with better functional outcomes.2b. Laryngoscope, 125:122-127, 2015.
EVALuna2:19934

Evolving a Model for Cochlear Implant Outcome. - Hoppe, Ulrich; Hast, Anne; Hornung, Joachim; Hocke, Thomas (Journal of Clinical Medicine, 2023)
BACKGROUND: Cochlear implantation is an efficient treatment for postlingually deafened adults who do not benefit sufficiently from acoustic amplification. Implantation is indicated when it can be foreseen that speech recognition with a cochlear implant (CI) is superior to that with a hearing aid. Especially for subjects with residual speech recognition, it is desirable to predict CI outcome on the basis of preoperative audiological tests. PURPOSE: The purpose of the study was to extend and refine a previously developed model for CI outcome prediction for subjects with preoperative word recognition to include subjects with no residual hearing by incorporating additional results of routine examinations. RESULTS: By introducing the duration of unaided hearing loss (DuHL), the median absolute error (MAE) of the prediction was reduced. While for subjects with preoperative speech recognition, the model modification did not change the MAE, for subjects with no residual speech recognition before surgery, the MAE decreased from 23.7% with the previous model to 17.2% with the extended model. CONCLUSIONS: Prediction of word recognition with CI is possible within clinically relevant limits. Outcome prediction is particularly important for preoperative counseling and in CI aftercare to support systematic monitoring of CI fitting.
EVALuna2:562054

Excessive noise levels are noted in kindergarten classrooms in the island of Crete - Chatzakis, Nikolaos S.; Karatzanis, Alexander D.; Helidoni, Meropi E.; Velegrakis, Stelios G.; Christodoulou, Panagiotis; Velegrakis, Georgios A. (European Archives of Oto-Rhino-Laryngology, 2014)
Ambient noise in classrooms may present a serious obstacle to the academic achievement of children. There is relatively little information on noise levels in teaching facilities in Greece and particularly in the island of Crete. The purpose of this study was to provide objective data on the internal noise levels inside kindergartens in Crete. The study was conducted in the city of Heraklion in the island of Crete, Greece. Ten kindergartens were selected and a total of 18 classrooms were chosen. Noise levels were measured in occupied and unoccupied classrooms. Noise levels in occupied classrooms ranged from 71.6 to 82.9 dBA with an average of 75.8 dBA. Noise levels in empty classrooms varied from 48.2 to 59.6 dBA with an average of 53.1 dBA. All values are well above international standards. Excessive classroom noise seems to be very common in kindergartens. Results may indicate that school facilities are not built in compliance with international standards. School administrators and local authorities should become aware of the problem, and make any necessary interventions to improve the learning capabilities of children.
EVALuna2:19983

Exosomal serum biomarkers as predictors for laryngeal carcinoma - Mueller, Sarina K.; Schuster, Johannes; Wendler, Olaf; Iro, Heinrich; Gostian, Antoniu-Oreste (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Exosome swarms eliminate airway pathogens and provide passive epithelial immunoprotection through nitric oxide - Nocera, Angela L.; Mueller, Sarina K.; Stephan, Jules R.; Hing, Loretta; Seifert, Philip; Han, Xue; Lin, Derrick T.; Amiji, Mansoor M.; Libermann, Towia; Bleier, Benjamin S. (Journal of Allergy and Clinical Immunology, 2019)
Background: Nasal mucosa-derived exosomes (NMDEs) harbor immunodefensive proteins and are capable of rapid interepithelial protein transfer.
CRIS-Team WoS Importer:2019-04-16

Experiences in the treatment of patients with multiple head and neck paragangliomas - Künzel, Julian; De Tristan, Julie; Mantsopoulos, Konstantinos; Koch, Michael; Baussmerth, Marcela; Zenk, Johannes; Iro, Heinrich (American Journal of Otolaryngology, 2014)
To analyze treatment results in the multidisciplinary management of patients with multiple head and neck paragangliomas (HNPs).Retrospective analysis including all patients with multiple HNPs (VP, vagal paraganglioma; JTP, jugulotympanic paraganglioma; CBT, carotid body tumor) treated between 2000 and 2013 at a tertiary referral center.Ten patients (three men, seven women) had 25 HNPs (two VPs, eight JTPs, and 15 CBTs). The age range at diagnosis was 31-71 years (mean 40.9 years, median 37 years). Nine tumors (four CBTs, three JTPs, two VPs) were treated only with stereotactic radiotherapy (SRT; 50.4-56Gy, mean 55.3Gy) or in one case intensity-modulated radiotherapy (60 Gy). Nine tumors were treated with surgery alone (eight CBTs, one JTP) and three JTPs with subtotal surgery combined with adjuvant SRT. A "wait and scan" strategy was used in three cases (two CBTs, one JTP). The mean follow-up period was 4.3 years (range 0.1-13 years, median 4 years). The rate of tumor control with surgery and/or SRT was 100% (21/21). One patient with a wait-and-scan strategy for CBT had slow asymptomatic progression during a 13-year follow-up.The treatment results in this series of patients with multiple HNPs show that a very high rate of long-term tumor control with low morbidity can be achieved using tailored and individualized approaches. All of the different treatment strategies available should be discussed with the patient. In particular, the treatment should involve a multidisciplinary team of experts in the fields of nuclear medicine, genetics, pathology, radiology, radio-oncology, and surgery.
EVALuna2:18180

Experience with the use of a partial ossicular replacement prosthesis with a ball-and-socket joint between the plate and the shaft - Birk, Stephanie; Brase, Christoph; Hornung, Joachim (Otology & Neurotology, 2014)
In the further development of alloplastic prostheses for use in middle ear surgery, the Dresden and Cologne University Hospitals, working together with a company, introduced a new partial ossicular replacement prosthesis in 2011. The ball-and-socket joint between the prosthesis and the shaft mimics the natural articulations between the malleus and incus and between the incus and stapes, allowing reaction to movements of the tympanic membrane graft, particularly during the healing process.Retrospective evaluationTo reconstruct sound conduction as part of a type III tympanoplasty, partial ossicular replacement prosthesis with a ball-and-socket joint between the plate and the shaft was implanted in 60 patients, with other standard partial ossicular replacement prosthesis implanted in 40 patients and 64 patients. Pure-tone audiometry was carried out, on average, 19 and 213 days after surgery. Results of the partial ossicular replacement prosthesis with a ball-and-socket joint between the plate and the shaft were compared with those of the standard prostheses.Early measurements showed a mean improvement of 3.3 dB in the air-bone gap (ABG) with the partial ossicular replacement prosthesis with a ball-and-socket joint between the plate and the shaft, giving similar results than the standard implants (6.6 and 6.0 dB, respectively), but the differences were not statistically significant. Later measurements showed a statistically significant improvement in the mean ABG, 11.5 dB, compared with 4.4 dB for one of the standard partial ossicular replacement prosthesis and a tendency of better results to 6.9 dB of the other standard prosthesis.In our patients, we achieved similarly good audiometric results to those already published for the partial ossicular replacement prosthesis with a ball-and-socket joint between the plate and the shaft. Intraoperative fixation posed no problems, and the postoperative complication rate was low.
EVALuna2:19989

Experimental flow study of modeled regular and irregular glottal closure types - Kirmse, Clemens; Triep, Michael; Brücker, Christoph; Döllinger, Michael; Stingl, Michael (Logopedics Phoniatrics Vocology, 2010)
The present study shows the results of visualization experiments of the jet formation through a dynamic model of the human vocal folds. The model consists of two counter-rotating, 3D-shaped driven cams covered with a stretched silicone membrane. The 3D contours of the cams are a result of an optimized mapping of observed characteristic clinical vocal fold motions. The experiments are performed by using cams which produce the convex, triangular, rectangular, and concave or sand-glass regular glottis closure types. Two irregular cases are investigated: one of the convex cams is statically closed or opened. These cases cause an oscillating jet which attaches to the ventricular folds and appears to change the part of the aero-acoustic sound spectrum induced by vortices.

Experimental Molecular Communication Testbed Based on Magnetic Nanoparticles in Duct Flow - Unterweger, Harald; Kirchner, Jens; Wicke, Wayan; Ahmadzadeh, Arman; Ahmed, Doaa; Jamali Kooshkghazi, Vahid; Alexiou, Christoph; Fischer, Georg; Weigel, Robert; Schober, Robert (19th IEEE International Workshop on Signal Processing Advances in Wireless Communications, 2018)
Simple and easy to implement testbeds are needed to further advance molecular communication research. To this end, this paper presents an in-vessel molecular communication testbed using magnetic nanoparticles dispersed in an aqueous suspension as they are also used for drug targeting in biotechnology. The transmitter is realized by an electronic pump for injection via a Yconnector. A second pump provides a background flow for signal propagation. For signal reception, we employ a susceptometer, an electronic device including a coil, where the magnetic particles move through and generate an electrical signal. We present experimental results for the transmission of a binary sequence and the system response following a single injection. For this flowdriven particle transport, we propose a simple parameterized mathematical model for evaluating the system response. <br
Keywords: Molecular communication; magnetic nanoparticles

Experimental Molecular Communication Testbed Based on Magnetic Nanoparticles in Duct Flow - Unterweger, Harald; Kirchner, Jens; Wicke, Wayan; Ahmadzadeh, Arman; Ahmed, Doaa; Jamali, Vahid; Alexiou, Christoph; Fischer, Georg; Schober, Robert (2018 IEEE 19th International Workshop on Signal Processing Advances in Wireless Communications (SPAWC), 2018)
Simple and easy to implement testbeds are needed to further advance molecular communication research. To this end, this paper presents an in-vessel molecular communication testbed using magnetic nanoparticles dispersed in an aqueous suspension as they are also used for drug targeting in biotechnology. The transmitter is realized by an electronic pump for injection via a Y-connector. A second pump provides a background flow for signal propagation. For signal reception, we employ a susceptometer, an electronic device including a coil, where the magnetic particles move through and generate an electrical signal. We present experimental results for the transmission of a binary sequence and the system response following a single injection. For this flow-driven particle transport, we propose a simple parameterized mathematical model for evaluating the system Response.<br
Keywords: Electron tubes; Magnetic nanoparticles; Receivers; Molecular communication; Suspensions; Magnetic susceptibility; Transmitters

Experimental Research in Synthetic Molecular Communications - Part I - Lotter, Sebastian; Brand, Lukas; Jamali, Vahid; Schäfer, Maximilian; Loos, Helene; Unterweger, Harald; Greiner, Sandra; Kirchner, Jens; Alexiou, Christoph; Drummer, Dietmar; Fischer, Georg; Büttner, Andrea; et al. (IEEE Nanotechnology Magazine, 2023)
Since its emergence from the communication engineering community around one and a half decades ago, the field of Synthetic Molecular Communication (SMC) has experienced continued growth, both in the number of technical contributions from a vibrant community and in terms of research funding. Throughout this process, the vision of SMC as a novel, revolutionary communication paradigm has constantly evolved, driven by feedback from theoretical and experimental studies, respectively. It is believed that especially the latter ones will be crucial for the transition of SMC towards a higher technology readiness level in the near future. In this spirit, we present here a comprehensive survey of experimental research in SMC. In particular, this survey focuses on highlighting the major drivers behind different lines of experimental research in terms of the respective envisioned applications. This approach allows us to categorize existing works and identify current research gaps that still hinder the development of practical SMC-based applications. Our survey consists of two parts: this paper and a companion paper. While the companion paper focuses on SMC with relatively long communication ranges, this paper covers SMC over short distances of typically not more than a few millimeters.<br

Experimental Research in Synthetic Molecular Communications - Part II - Lotter, Sebastian; Brand, Lukas; Jamali, Vahid; Schäfer, Maximilian; Loos, Helene M.; Unterweger, Harald; Greiner, Sandra; Kirchner, Jens; Alexiou, Christoph; Drummer, Dietmar; Fischer, Georg; Buettner, Andrea; et al. (IEEE Nanotechnology Magazine, 2023)
In this second part of our survey on experimental research in Synthetic Molecular Communication (SMC), we review works on long-range SMC systems, i.e., systems with communication ranges of more than a few millimeters. Despite the importance of experimental research for the evolution of SMC towards a mature communication paradigm that will eventually support revolutionary applications beyond the reach of today’s prevalent communication paradigms, the existing body of literature is still comparatively sparse. Long-range SMC systems have been proposed in the literature for information transmission in two types of fluid media, liquid and air. While both types of SMC systems, i.e., liquid-based and air-based systems, rely on encoding and transmitting information using molecules, they differ substantially in terms of the physical system designs and in the type of applications they are intended for. In this article, we present a systematic characterization of experimental works on long-range SMC that reveals the major drivers of these works in terms of the respective target applications. Furthermore, the physical designs for long-range SMC proposed in the literature are comprehensively reviewed. In this way, our survey will contribute to making experimental research in this field more accessible and identifying novel directions for future research.
CRIS-Team Scopus Importer:2023-05-05
Keywords: Copper; Detectors; Fluorescence; Ions; Liquids; Pipelines; Prototypes

Experimental study of the fluid-structure-acoustic interaction in a human voice model - Kniesburges, Stefan; Becker, Stefan; Müller, Stefan; Delgado, Antonio; Link, Gerhard; Kaltenbacher, Manfred; Döllinger, Michael (Proceedings - European Conference on Noise Control, 2008)
For the investigation of the physical processes of the human phonation a fluid-structure-coupled in-vitro model was developed, which constitutes a copy of the human larynx. With that model one was able to reproduce a manlike process of sound production. The model made it possible to enforce extensive observations of the flow-induced vocal fold vibrations. Many measurement techniques were applied as high-speed flow visualization, particle image velocimetry (PIV) of the time-dependent flow field, unsteady pressure measurement, vibration measurement by a laser-scanning vibrometer as well as the measurement of the acoustic field. Furthermore correlations were done between the acoustic field, the flow velocity and the displacement of the vocal fold models. The results support the existence of the Coanda-effect during phonation. The flow attaches to one vocal fold just past the glottis and forms a spacious vortex behind the vocal folds. That behavior is not linked to one vocal fold and changes stochastically from cycle to cycle. The sound production is presumed to be produced by oscillations of the vocal folds and therefore by the involved oscillating volume flow rate.
UnivIS-Import:2015-04-16:Pub.2008.tech.ITC.stmmec.experi_7

Experimental System for Molecular Communication in Pipe Flow With Magnetic Nanoparticles - Wicke, Wayan; Unterweger, Harald; Kirchner, Jens; Brand, Lukas; Ahmadzadeh, Arman; Ahmed, Doaa; Jamali, Vahid; Alexiou, Christoph; Fischer, Georg; Schober, Robert (IEEE Transactions on Molecular, Biological and Multi-Scale Communications, 2021)
In the emerging field of molecular communication (MC), testbeds are needed to validate theoretical concepts, motivate applications, and guide further modeling efforts. To this end, this paper presents a flexible and extendable in-vessel testbed for flow-based macroscopic MC, abstractly modeling, e.g., a part of a chemical reactor or a blood vessel. Signaling is based on injecting non-reactive superparamagnetic iron oxide nanoparticles (SPIONs) dispersed in an aqueous suspension into a tube with background flow. A commercial magnetic susceptometer is used for non-intrusive downstream signal reception. To shed light on the operation of the testbed, we identify the physical mechanisms governing the transmission, propagation, and reception of the information-carrying SPIONs. Moreover, to facilitate system design, we propose a closed-form parametric expression for the end-to-end channel impulse response (CIR). The proposed CIR model is shown to consistently capture the experimentally observed distance-dependent impulse response peak heights and peak decays for transmission distances from 540. Moreover, to validate our testbed, reliable communication is demonstrated based on experimental data for model-agnostic and model-based detection methods.
Created from Fastlane, Scopus look-up
Keywords: Biology; Chemicals; Coatings; Electron tubes; Experimental system; fluid flow; injection; Iron; magnetic nanoparticles; Magnetic nanoparticles; Magnetic susceptibility; molecular communication; SPIONs; testbed.

Explainable convolutional neural networks for assessing head and neck cancer histopathology - Dörrich, Marion; Hecht, Markus; Fietkau, Rainer; Hartmann, Arndt; Iro, Heinrich; Gostian, Antoniu-Oreste; Eckstein, Markus; Kist, Andreas (Diagnostic Pathology, 2023)
Purpose: Although neural networks have shown remarkable performance in medical image analysis, their translation into clinical practice remains difficult due to their lack of interpretability. An emerging field that addresses this problem is Explainable AI. Methods: Here, we aimed to investigate the ability of Convolutional Neural Networks (CNNs) to classify head and neck cancer histopathology. To this end, we manually annotated 101 histopathological slides of locally advanced head and neck squamous cell carcinoma. We trained a CNN to classify tumor and non-tumor tissue, and another CNN to semantically segment four classes - tumor, non-tumor, non-specified tissue, and background. We applied Explainable AI techniques, namely Grad-CAM and HR-CAM, to both networks and explored important features that contributed to their decisions. Results: The classification network achieved an accuracy of 89.9% on previously unseen data. Our segmentation network achieved a class-averaged Intersection over Union score of 0.690, and 0.782 for tumor tissue in particular. Explainable AI methods demonstrated that both networks rely on features agreeing with the pathologist’s expert opinion. Conclusion: Our work suggests that CNNs can predict head and neck cancer with high accuracy. Especially if accompanied by visual explanations, CNNs seem promising for assisting pathologists in the assessment of cancer sections.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Classification; Explainable AI; Head and neck cancer; Histopathology; Semantic segmentation

Expression of Eukaryotic Translation Initiation Factors in the Urothelial Carcinoma of the Bladder - Luzha, Jeton; Nass, Norbert; Czapiewski, Piotr; Schroeder, Nicolas; Kalinski, Thomas; Schostak, Martin; Schatz, Christoph; Jandrig, Burkhard; Haybaeck, Johannes (Anticancer Research, 2023)
BACKGROUND/AIM: Urothelial carcinoma (UC) of the urinary bladder is the second most common tumor in the field of urology and is characterized by a relatively aggressive growth behavior. New therapeutic approaches are required to improve the prognosis of affected patients. We hypothesized a link between dysregulation of eIFs and the development of UC. Therefore, in the present work, we investigated the expression behavior of eIF1, eIF1AY, eIF1AX, eIF2α, eIF3a, eIF3b, eIF4B, eIF4E, eIF4G, eIF5A, eIF5B, and eIF6 in UC compared with that in urothelial tissue. MATERIALS AND METHODS: Paraffin-embedded tumor tissue samples from 107 patients suffering from UC were examined. Seventy-six patients contained adjacent urothelial tissue. Three tumor tissue cylinders (tumor collective) and two urothelial tissue cylinders (control collective) were collected per patient and embedded in tissue microarray (TMA) blocks. Immunohistochemical staining of the TMA sections was then performed. The staining results were assessed semi-quantitatively. Staining intensities and immunoreactive scores (IRS) of both collectives were compared. In each case, a distinction was made between cytoplasmic and nuclear staining. RESULTS: Significant up-regulation of eIF1AY, eIF2α, eIF3a, eIF3b, eIF4B, eIF4G, eIF5B, and eIF6 was found in the cytoplasm of UC. In contrast, eIF1 and eIF5A were significantly down-regulated in the cytoplasm of UC. eIF5A and eIF6 were significantly down-regulated in the nuclei of UC. CONCLUSION: Dysregulation of eIFs in the urothelium of the urinary bladder is linked to carcinogenesis at this site.
CRIS-Team Scopus Importer:2023-04-07
Keywords: bladder cancer; eukaryotic initiation factors (eIFs); initiation; Translation; urothelial carcinoma

Expression of sex hormone receptors in juvenile angiofibromas and antiproliferative effects of receptor modulators - Schick, Bernhard; Dlugaiczyk, Julia; Wendler, Olaf (Head and Neck-Journal For the Sciences and Specialties of the Head and Neck, 2014)
Predilection of juvenile angiofibromas in adolescent boys has prompted the hypothesis of hormone-dependent tumor growth. However, knowledge on expression and function of sex hormone receptors in juvenile angiofibromas is still sparse and inconsistent.Transcript and protein expression of sex hormone receptors in juvenile angiofibromas was studied by quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR) and immunohistology/fluorescence. A bromodeoxyuridine assay was used to assess the antiproliferative effects of flutamide (androgen receptor antagonist) and tamoxifen (estrogen receptor modulator).Significantly increased transcript levels were observed for androgen receptor, estrogen receptor ?, follicle-stimulating hormone receptor, and luteinizing hormone receptor in juvenile angiofibromas versus the stroma of nasal mucosa. Estrogen receptor ? and progesterone receptor mRNA levels were low and similar for both tissues. Estrogen receptor ? protein was detected in juvenile angiofibroma tumors and mesenchymal cell lines. Flutamide and tamoxifen inhibited proliferation of cultured juvenile angiofibroma mesenchymal cells.These findings contribute to the understanding of juvenile angiofibroma pathophysiology and offer novel therapeutic options.
EVALuna2:19980

Expression of the Tumor-associated Mucin 1 Epitope Analyzed with the Humanized PankoMab-GEX(TM) Antibody in Malignant and Normal Tissues of the Head and Neck - Wiest, Irmi; Alexiou, Christoph; Friese, Klaus; Betz, Peter; Tuebel, Jutta; Goletz, Steffen; Dian, Darius; Jeschke, Udo (Anticancer Research, 2016)
During neoplasia, glycosylation changes. In this setting, mucins, especially mucin 1 (MUC1), become carriers for oncofetal carbohydrates and relieve invasive growth. The recently described tumor-associated MUC1 epitope TA-MUC1 is primarily restricted to malignancies and is overexpressed in these tissues. The humanized monoclonal antibody PankoMab-GEX specifically recognizes TA-MUC1.Laryngeal cancer specimens (n=125) and normal tissue of head and neck (n=7) were used in this study. Paraffin-embedded sections were incubated with PankoMab-GEX. Staining reaction was carried out using peroxidase (POD) labeling and diaminobenzidine (DAB). Breast cancer tissue was used as positive control and negative control used non-specific mouse IgM. Semi-quantitative evaluation by two independent double-blinded investigators, including a pathologist, used the immunoreactive score (IRS) of Remmele and Stegner.A total of 31 out of 125 laryngeal cancer specimens were classified as G1. Of these, 22 (71%) were completely negative for TA-MUC1, the remaining 9 showed very weak staining, with an IRS of 2. A total of 94 cases of cancer specimens were classified as G2 and G3; 34 of them were also negative, but 60 had an IRS of up to 9. All investigated normal tissue of the upper aerodigestive tract was completely negative for TA-MUC1.G1 tumors are completely negative or do not reach an IRS relevant range. The finding that G1 tumors are completely negative for TA-MUC1 or have IRS<=2 can be helpful for histopathological examination, especially concerning tumor grading. Therefore, this antibody holds great potential for use as a therapeutic antibody in laryngeal cancer.
EVALuna2:9426

Extended and treatment-oriented classification of parotid duct stenosis - Koch, Michael; Iro, Heinrich (Laryngoscope, 2017)
OBJECTIVES/HYPOTHESIS: To provide an extended and treatment-oriented classification of parotid duct stenosis that might be useful in the management of this condition. STUDY DESIGN: Retrospective study in a tertiary referral center. METHODS: A total of 550 symptomatic stenoses of the parotid gland excretory duct in 445 patients were analyzed. Sialendoscopy was performed with semirigid endoscopes. The tissue quality, location, grade of luminal narrowing, and length and number of the stenoses were assessed. RESULTS: Inflammation-dominant stenosis (type 1) was found in 8.9% of the patients, web-associated fibrous stenosis (type 2) in 19.5%, and fibrous (type 3) in 71.6%. Multiple stenoses (≥3) were found in 2.8% of patients, and bilateral stenoses in 11.9%. Type 1 stenoses differed significantly from type 3 stenoses, with lower grades. Type 3 stenoses showed significantly higher grades of luminal narrowing than the other two types (P = .0001). Type 2 stenoses were significantly shorter in comparison with the other two types (P = .0001). Multiple stenoses were observed significantly more often in type 2 than in type 3 stenoses (P = .0001). Due to these differences, the type of stenosis appears to be the most important criterion in the treatment-oriented classification. CONCLUSIONS: Significant differences between the different stenoses were observed. Type 1 stenosis may be considered as a precursor of type 3 stenosis, but type 2 stenosis showed significantly different characteristics. The differences prescribed in this classification may be helpful in the management of parotid duct stenoses. LEVEL OF EVIDENCE: 4. Laryngoscope, 2016 127:366-371, 2017.
EVALuna2:33184

Extracapsular dissection as sole therapy for small low-grade malignant tumors of the parotid gland - Mantsopoulos, Konstantinos; Koch, Michael; Iro, Heinrich (Laryngoscope, 2017)
OBJECTIVE: The aim of the study was to investigate whether extracapsular dissection of a primarily unsuspected lesion in the parotid gland could be oncologically sufficient for carefully selected cases of parotid gland malignomas. STUDY DESIGN: Retrospective clinical study. METHODS: The records of all patients treated for primary malignant tumors of the parotid gland solely by means of extracapsular dissection between 2006 and 2013 were studied retrospectively. Patients with manifestation of malignant tumors in the parotid gland that were not of primary salivary gland origin (squamous cell carcinomas, lymphomas, melanomas) or who had had revision surgery or other malignant tumors in their history, as well as patients with insufficient data, were excluded from our study sample. RESULTS: Nine patients, all with low-grade parotid malignancies, were detected. Our study showed acceptable oncologic and functional outcomes throughout. CONCLUSION: Our study was able to show very encouraging preliminary results following primary extracapsular dissection as sole surgical therapy for carefully selected low-stage, low-grade, inferiorly located lesions in patients with high compliance. LEVEL OF EVIDENCE: 4. Laryngoscope, 127:1804-1807, 2017.
EVALuna2:33197

Extracapsular dissection for warthin tumors despite the risk of ipsilateral metachronous occurrence - Mantsopoulos, Konstantinos; Goncalves, Miguel; Koch, Michael; Iro, Heinrich (Laryngoscope, 2018)
OBJECTIVES/HYPOTHESIS: The ideal extent of surgical intervention for cystadenolymphomas of the parotid gland remains a matter of controversy. The aim of our study was to assess the surgical outcome after extracapsular dissection for cystadenolymphomas of the parotid gland. A further purpose of this study was to examine how the number of primary cystadenolymphomas or the size of the primary lesion influences the possibility of an ipsilateral metachronous tumor occurrence. STUDY DESIGN: Retrospective clinical study. METHODS: A retrospective evaluation of the records was carried out for all patients treated for cystadenolymphomas of the parotid gland by means of extracapsular dissection at a tertiary referral center between 2000 and 2012. RESULTS: Three hundred twenty-seven patients were included in the study. Our analysis detected an overall occurrence rate of ipsilateral metachronous tumors of 3.1% (10/327) with a mean follow-up of 108.4 months. A significant difference in the rate of metachronous lesions between unilocular (1.7%) and multilocular (11.6%) tumors could be detected (χ2 (1) = 7.342, P < .001). Our analysis was not able to find any significant influence of the maximal tumor size on the rate of metachronous tumors (χ2 (1) = 0.634, P = .426). CONCLUSIONS: One of the most controversial issues in the treatment of cystadenolymphomas of the parotid gland concerns the question of which is the best therapeutic approach to be taken in such patients. Our analysis was able to demonstrate the benefits of extracapsular dissection in the management of solitary as well as carefully selected multicentric cystadenolymphomas with a consistently acceptable surgical outcome. LEVEL OF EVIDENCE: 4. Laryngoscope, 2521-2524, 2018.
EVALuna2:35386

Extracapsular Dissection in Pleomorphic Adenomas of the Parotid Gland: Results After 13 Years of Follow-up - Schapher, Mirco; Koch, Michael; Goncalves, Miguel; Mantsopoulos, Konstantinos; Iro, Heinrich (Laryngoscope, 2020)
Objectives/Hypothesis: To assess long-term results after the treatment of parotid pleomorphic adenomas (PPAs) using different surgical techniques and focusing on recurrence rates and the risk of adverse effects. Study Design: Retrospective analysis. Methods: Retrospective analysis of 182 patients treated exclusively for PPAs at a tertiary referral center between 2000 and 2004. Thorough follow-up examinations over a mean period of 13 years were possible in 53.8% (n = 98/182). Tumors were categorized according to the European Salivary Gland Society (ESGS) system to improve the comparison of outcomes. After different surgical resection strategies, recurrence rates, postoperative facial nerve paresis (FNP), and incidence of Frey's syndrome were assessed. The follow-up period included clinical examinations and imaging of every patient in the treating department. Results: Of 182 patients, extracapsular dissection (ED) was performed in 29.7%, and other surgical modalities (OSMs), including facial nerve dissection, in 70.3%. After the long-term follow-up, 98% of all the patients (n = 96/98) were recurrence free. When recurrence rates were compared, no significant differences were noted (P <.331). ED resulted in significantly lower FNP rates compared to OSMs (P <.001). FNP rates significantly increased with size and location of the tumors according to ESGS categories (temporary and permanent FNP, P =.04). Surgical invasiveness corresponded to a significant increase in the incidence of Frey's syndrome (P <.001). Conclusions: ED was associated with the lowest complication rates, but not with a higher risk of recurrence, when compared with OSM in the long-term course. As ED can be performed in the majority of PPAs, it can be regarded as the treatment of choice whenever possible. Level of Evidence: 4 Laryngoscope, 2020.
CRIS-Team Scopus Importer:2020-05-22
Keywords: extracapsular dissection; facial nerve dissection; limited surgery; Parotid pleomorphic adenoma; recurrence

Extracapsular dissection in the parapharyngeal space: benefits and potential pitfalls - Mantsopoulos, K.; Müller, Sandra; Agaimy, Abbas; Goncalves, M.; Koch, Matthias; Wüst, Wolfgang; Bohr, Christopher; Iro, Heinrich (British Journal of Oral and Maxillofacial Surgery, 2017)
The aim of this study was to investigate the benefits and potential pitfalls of transcervical extracapsular dissection in the treatment of parotid gland tumours in the parapharyngeal space. We retrospectively evaluated the records of all patients with parapharyngeal parotid gland lesions treated between 2000 and 2015 by transcervical extracapsular dissection. Patients having revision operations and patients whose records were not complete were excluded, leaving 49 patients in the study. We found acceptable oncological and functional outcomes throughout. Special attention should be paid in cases with multilobular growth of the tumour on magnetic resonance imaging, satellite tumours of pleomorphic adenomas, tumours in broad contact with the inner surface of the deep lobe, and lesions suspected of malignancy. Extracapsular dissection in the parapharyngeal region is associated with acceptable oncological and functional outcomes. These outcomes can be expected only after a thorough assessment of patient's history and preoperative imaging.
EVALuna2:6890

Extracapsular dissection versus conventional parotidectomy: comparing ‘apples with oranges’? - Mantsopoulos, Konstantinos; Iro, Heinrich (International Journal of Oral and Maxillofacial Surgery, 2022)
CRIS-Team Scopus Importer:2022-03-25

Extracranial temporal bone paragangliomas: Re-defining the role of otologic surgery within the scope of function-preserving multimodal concepts - Mantsopoulos, Konstantinos; Thimsen, Vivian; Eisenhut, Felix; Weissmann, Thomas; Putz, Florian; Fietkau, Rainer; Iro, Heinrich; Hornung, Joachim; Taha, Lava (American Journal of Otolaryngology, 2022)
Introduction: The aim of this study was to present our concept in the management of extracranial temporal bone paragangliomas and demonstrate the outcome after primary surgical management of the middle ear component, with an individualized indication for adjuvant radiotherapy. Materials and methods: The records of all patients treated for extracranial jugulotympanic paragangliomas by means of primary surgical management between 2010 and 2021 were studied retrospectively. Results: Twenty-nine patients made up our study sample (mean age 58.8 years). 15 cases were managed solely by means of surgery. Out of the remaining 14 cases with reduction of the middle ear component, adjuvant irradiation was performed in 11 cases, whereas a wait-and-scan strategy was adopted at the patient's request in three cases. No further growth was detected in our study cases. Conclusion: Our protocol seems to be associated with an acceptable quality of life and a satisfactory oncologic outcome.
CRIS-Team WoS Importer:2021-10-15

Extracting continuous sleep depth from EEG data without machine learning - Metzner, Claus; Schilling, Achim; Traxdorf, Maximilian; Schulze, Holger; Tziridis, Konstantin; Krauß, Patrick (Neurobiology of Sleep and Circadian Rhythms, 2023)
The human sleep-cycle has been divided into discrete sleep stages that can be recognized in electroencephalographic (EEG) and other bio-signals by trained specialists or machine learning systems. It is however unclear whether these human-defined stages can be re-discovered with unsupervised methods of data analysis, using only a minimal amount of generic pre-processing. Based on EEG data, recorded overnight from sleeping human subjects, we investigate the degree of clustering of the sleep stages using the General Discrimination Value as a quantitative measure of class separability. Virtually no clustering is found in the raw data, even after transforming the EEG signals of each 30-s epoch from the time domain into the more informative frequency domain. However, a Principal Component Analysis (PCA) of these epoch-wise frequency spectra reveals that the sleep stages separate significantly better in the low-dimensional sub-space of certain PCA components. In particular the component C1(t) can serve as a robust, continuous ‘master variable’ that encodes the depth of sleep and therefore correlates strongly with the ‘hypnogram’, a common plot of the discrete sleep stages over time. Moreover, C1(t) shows persistent trends during extended time periods where the sleep stage is constant, suggesting that sleep may be better understood as a continuum. These intriguing properties of C1(t) are not only relevant for understanding brain dynamics during sleep, but might also be exploited in low-cost single-channel sleep tracking devices for private and clinical use.
CRIS-Team Scopus Importer:2023-06-02

Extracting the Auditory Attention in a Dual-Speaker Scenario From EEG Using a Joint CNN-LSTM Model - Kuruvila, Ivine; Muncke, Jan; Fischer, Eghart; Hoppe, Ulrich (Frontiers in Physiology, 2021)
Human brain performs remarkably well in segregating a particular speaker from interfering ones in a multispeaker scenario. We can quantitatively evaluate the segregation capability by modeling a relationship between the speech signals present in an auditory scene, and the listener's cortical signals measured using electroencephalography (EEG). This has opened up avenues to integrate neuro-feedback into hearing aids where the device can infer user's attention and enhance the attended speaker. Commonly used algorithms to infer the auditory attention are based on linear systems theory where cues such as speech envelopes are mapped on to the EEG signals. Here, we present a joint convolutional neural network (CNN)—long short-term memory (LSTM) model to infer the auditory attention. Our joint CNN-LSTM model takes the EEG signals and the spectrogram of the multiple speakers as inputs and classifies the attention to one of the speakers. We evaluated the reliability of our network using three different datasets comprising of 61 subjects, where each subject undertook a dual-speaker experiment. The three datasets analyzed corresponded to speech stimuli presented in three different languages namely German, Danish, and Dutch. Using the proposed joint CNN-LSTM model, we obtained a median decoding accuracy of 77.2% at a trial duration of 3 s. Furthermore, we evaluated the amount of sparsity that the model can tolerate by means of magnitude pruning and found a tolerance of up to 50% sparsity without substantial loss of decoding accuracy.
CRIS-Team Scopus Importer:2021-08-27
Keywords: auditory attention; cocktail party effect; convolutional neural network; EEG; hearing aids; long short term memory networks; speech enhancement; speech separation

Extramedullary plasmacytoma: Tumor occurrence and therapeutic concepts-A follow-up - Holler, Adrian; Cicha, Iwona; Eckstein, Markus; Haderlein, Marlen; Poettler, Marina; Rappl, Anja; Iro, Heinrich; Alexiou, Christoph (Cancer Medicine, 2022)
Background Extramedullary plasmacytoma (EMP) is a solitary tumor consisting of neoplastic plasma cells, with very little to no bone marrow involvement. EMPs are usually located in the head and neck region, but can also occur along the digestive tract, in lungs, or extremities. Methods Following our publication on EMP, which appeared in 1999 (Cancer 85:2305-14), we conducted a literature search for EMP-related reports published between 1999 and 2021. The documented cases, as well as 14 of our own patients from the ENT Clinic Erlangen, were extensively analyzed. Results Between 1998 and 2021, 1134 patients with EMP were reported, for whom information about the tumor localization was available. Among those, 62.4% had EMP in the head and neck area and 37.6% in other body regions. Data on therapy were reported in 897 patients, including 34.3% who received radiation, 28.1% surgery, 22.6% a combination of surgery and radiation, and 15.9% another therapy. In 76.9% patients no recurrence or transformation to multiple myeloma (MM) was reported, 12.8% showed local recurrence and 10.2% developed MM. Radiotherapy alone was associated with a tendency for increased occurrence of MM. In patients with EMP of head and neck area, combination therapy (surgery and radiation) resulted in a 5-year overall survival rate of 98.3%, surgery alone of 92.4%, and radiotherapy of 92.7%. Conclusions Collectively, our analyses indicate that surgical resection alone can achieve long-term tumor control in patients with EMP, if the tumor can be removed within safe limits without causing serious functional impairment. However, if this is not certain, either radiation or a combination of surgery and radiation therapy is suggested as an effective means of local tumor control.
CRIS-Team WoS Importer:2022-05-27
Keywords: extramedullary plasmacytoma; non-Hodgkin lymphoma; survival; therapy; tumor outcomes

Extratubular Polymerized Uromodulin Induces Leukocyte Recruitment and Inflammation In Vivo - Immler, Roland; Lange-Sperandio, Barbel; Steffen, Tobias; Beck, Heike; Rohwedder, Ina; Roth, Jonas; Napoli, Matteo; Hupel, Georg; Pfister, Felix; Popper, Bastian; Uhl, Bernd; Mannell, Hanna; et al. (Frontiers in Immunology, 2020)
Uromodulin (UMOD) is produced and secreted by tubular epithelial cells. Secreted UMOD polymerizes (pUMOD) in the tubular lumen, where it regulates salt transport and protects the kidney from bacteria and stone formation. Under various pathological conditions, pUMOD accumulates within the tubular lumen and reaches extratubular sites where it may interact with renal interstitial cells. Here, we investigated the potential of extratubular pUMOD to act as a damage associated molecular pattern (DAMP) molecule thereby creating local inflammation. We found that intrascrotal and intraperitoneal injection of pUMOD induced leukocyte recruitment in vivo and led to TNF-alpha secretion by F4/80 positive macrophages. Additionally, pUMOD directly affected vascular permeability and increased neutrophil extravasation independent of macrophage-released TNF-alpha. Interestingly, pUMOD displayed no chemotactic properties on neutrophils, did not directly activate beta 2 integrins and did not upregulate adhesion molecules on endothelial cells. In obstructed neonatal murine kidneys, we observed extratubular UMOD accumulation in the renal interstitium with tubular atrophy and leukocyte infiltrates. Finally, we found extratubular UMOD deposits associated with peritubular leukocyte infiltration in kidneys from patients with inflammatory kidney diseases. Taken together, we identified extratubular pUMOD as a strong inducer of leukocyte recruitment, underlining its critical role in mounting an inflammatory response in various kidneys pathologies.
CRIS-Team WoS Importer:2021-01-22

Ex vivo human artery model to investigate magnetic targeting in cardiovascular diseases - Cicha, Iwona; Janikowska, A.; Matuszak, Jasmin; Unterweger, Harald; Zaloga, Jan; Lyer, Stefan; Alexiou, Christoph (2017)
EVALuna2:210099

F18-FDG PET/CT imaging early predicts pathologic complete response to induction chemoimmunotherapy of locally advanced head and neck cancer: preliminary single-center analysis of the checkrad-cd8 trial - Beck, Michael; Hartwich, J.; Eckstein, Markus; Schmidt, D.; Gostian, Antoniu-Oreste; Müller-Hübner, Sarina; Rutzner, Sandra; Gaipl, Udo; Von Der Gruen, J.; Illmer, T.; Hautmann, M. G.; Klautke, G.; et al. (Annals of Nuclear Medicine, 2022)
Aim: In the CheckRad-CD8 trial patients with locally advanced head and neck squamous cell cancer are treated with a single cycle of induction chemo-immunotherapy (ICIT). Patients with pathological complete response (pCR) in the re-biopsy enter radioimmunotherapy. Our goal was to study the value of F-18-FDG PET/CT in the prediction of pCR after induction therapy. Methods: Patients treated within the CheckRad-CD8 trial that additionally received FDG- PET/CT imaging at the following two time points were included: 3–14 days before (pre-ICIT) and 21–28 days after (post-ICIT) receiving ICIT. Tracer uptake in primary tumors (PT) and suspicious cervical lymph nodes (LN +) was measured using different quantitative parameters on EANM Research Ltd (EARL) accredited PET reconstructions. In addition, mean FDG uptake levels in lymphatic and hematopoietic organs were examined. Percent decrease (Δ) in FDG uptake was calculated for all parameters. Biopsy of the PT post-ICIT acquired after FDG-PET/CT served as reference. The cohort was divided in patients with pCR and residual tumor (ReTu). Results: Thirty-one patients were included. In ROC analysis, ΔSUVmax PT performed best (AUC = 0.89) in predicting pCR (n = 17), with a decline of at least 60% (sensitivity, 0.77; specificity, 0.93). Residual SUVmax PT post-ICIT performed best in predicting ReTu (n = 14), at a cutpoint of 6.0 (AUC = 0.91; sensitivity, 0.86; specificity, 0.88). Combining two quantitative parameters (ΔSUVmax ≥ 50% and SUVmax PT post-ICIT ≤ 6.0) conferred a sensitivity of 0.81 and a specificity of 0.93 for determining pCR. Background activity in lymphatic organs or uptake in suspected cervical lymph node metastases lacked significant predictive value. Conclusion: FDG-PET/CT can identify patients with pCR after ICIT via residual FDG uptake levels in primary tumors and the related changes compared to baseline. FDG-uptake in LN + had no predictive value. Trial registry: ClinicalTrials.gov identifier: NCT03426657.
CRIS-Team Scopus Importer:2022-05-20
Keywords: FDG-PET/CT; Head neck cancer; HNSCC; Immunotherapy; Induction therapy

Facile preparation of multifunctional superparamagnetic PHBV microspheres containing SPIONs for biomedical applications - Li, Wei; Zaloga, Jan; Ding, Yaping; Liu, Yufang; Janko, Christina; Pischetsrieder, Monika; Alexiou, Christoph; Boccaccini, Aldo R. (Scientific Reports, 2016)
The promising potential of magnetic polymer microspheres in various biomedical applications has been frequently reported. However, the surface hydrophilicity of superparamagnetic iron oxide nanoparticles (SPIONs) usually leads to poor or even failed encapsulation of SPIONs in hydrophobic polymer microspheres using the emulsion method. In this study, the stability of SPIONs in poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) solution was significantly increased after surface modification with lauric acid. As a result, magnetic PHBV microspheres with high encapsulation efficiencies (71.0-87.4%) were prepared using emulsion-solvent extraction/evaporation method. Magnetic resonance imaging (MRI) showed significant contrast for the magnetic PHBV microspheres. The toxicity of these magnetic PHBV microspheres towards human T-lymphoma suspension cells and adherent colon carcinoma HT-29 cells was investigated using flow cytometry, and they were shown to be non-toxic in a broad concentration range. A model drug, tetracycline hydrochloride, was used to demonstrate the drug delivery capability and to investigate the drug release behavior of the magnetic PHBV microspheres. The drug was successfully loaded into the microspheres using lauric acid-coated SPIONs as drug carrier, and was released from the microspheres in a diffusion controlled manner. The developed magnetic PHBV microspheres are promising candidates for biomedical applications such as targeted drug delivery and MRI.

Factors Influencing the Outcome of Head and Neck Cancer of Unknown Primary (HNCUP) - Rupp, Robin; Mantsopoulos, Konstantinos; Sievert, Matti; Gostian, Magdalena; Allner, Moritz; Grundtner, Philipp; Eckstein, Markus; Iro, Heinrich; Hecht, Markus; Gostian, Antoniu-Oreste; Balk, Matthias (Journal of Clinical Medicine, 2022)
Background: This study on patients with head and neck cancer of unknown primary (HNCUP) assesses the impact of surgical and non-surgical treatment modalities and the tumour biology on the oncological outcome. Methods: A total of 80 patients with HNCUP (UICC I-IV) were treated with simultaneous neck dissection followed by adjuvant therapy, between 1 January 2007 and 31 March 2020. As the primary objective, the influence of treatment modalities on the overall survival (OS), the disease-specific survival (DSS) and the progression-free survival (PFS) were analysed in terms of cox regression and recursive partitioning. The tumour biology served as secondary objectives. Results: The 5-year OS for the entire cohort was 67.7%, (95% CI: 54.2-81.2%), the 5-year DSS was 82.3% (72.1-92.5%) and the 5-year PFS was 72.8% (61.8-83.8%). Cox regression revealed that patients undergoing adjuvant radiotherapy only had a four times higher risk to die compared to patients receiving chemoradiation therapy (HR = 4.45 (1.40; 14.17), p = 0.012). The development of distant metastases had a significantly negative impact on OS (HR = 8.24 (3.21-21.15), p < 0.001) and DSS (HR = 23.79 (6.32-89.56), p < 0.001). Recursive portioning underlined the negative influence of distant metastases on OS (3.2-fold increase in death probability) and DSS (4.3-fold increase in death probability), while an UICC stage of IVb increased the risk for further progression of the disease by a factor of 2. Conclusions: The presence of distant metastases as well as adjuvant treatment with radiation without concomitant chemotherapy, were among others, significant predictors for the overall survival of HNCUP patients, with distant metastases being the most significant predictor.
CRIS-Team WoS Importer:2022-06-10

Failure of pedicled flap reconstruction in the head and neck area: A case report of a bilateral subclavian artery stenosis - Sievert, Matti; Koch, Michael; Mantsopoulos, Konstantinos; Traxdorf, Maximilian; Mueller, Sarina K.; Iro, Heinrich; Scherl, Claudia (International Journal of Surgery Case Reports, 2020)
Introduction: Pedicled flap reconstruction still plays an essential role in head and neck surgery as an alternative to free grafts. Two standard methods are the pectoralis major and the deltopectoral flap, which are generally characterized by their reliable perfusion. This case describes bilateral arteriosclerosis of the subclavian artery as a possible cause of flap failure. Presentation of case: We report on a 65-year-old patient with a multilevel carcinoma of the right pharynx. Due to the unique patient history, a free flap reconstruction was not possible. After resection of the primary, we performed reconstruction with a pedicled pectoralis major flap. Discussion: Postoperatively, we observed necrosis of the pectoralis major flap. Secondary defect reconstructions were performed with a deltopectoral flap first from the right and then, in the case of necrosis, from the left side. Stenosing arteriosclerotic plaques of the subclavian artery on both sides were the cause of flap failure. Conclusion: Preoperative angiography of the subclavian artery is not a standard diagnostic procedure in the surgical planning of pedicled flap reconstruction in the head and neck region. In exceptional cases, we recommend angiographic imaging of the supplying vessels to make a more precise flap selection and avoid complications.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Case report; Deltopectoral flap; Flap failure; Head and neck surgery; Pectoralis major flap; Pedicled flap reconstruction

Fast detection of SARS-CoV2 Antibodies by the use of critical off-set magnetic particle spectroscopy (COMPASS) - Friedrich, Bernhard; Tietze, Rainer; Rückert, M. A.; Kampf, T.; Hennig, T.; Dölken, L.; Behr, V. C.; Alexiou, Christoph; Vogel, P.; Lyer, Stefan (International Journal of Magnetic Particle Imaging, 2023)
Current bioassays for detection of antibodies or antigens such as ELISA (Enzyme-linked Immunosorbent Assay) are relatively inflexible, expensive and time-consuming. Upcoming methods, such as ACS (AC susceptometry) or MPS (Magnetic Particle Spectroscopy), exploit the magnetization response of functionalized magnetic nanoparticles (MNP) ensembles to assess specific information about the MNP mobility as well as conjugations of chemical or biological compounds on their surface. Both methods have shown promising results in the past but cannot reach the sensitivity of above-mentioned techniques. We used a novel method based on a modified MPS being sensitive to minimal changes in mobility of MNP ensembles. This facilitates robust and easy-to-handle measurements of minimal changes in the diameter of MNPs. As an example, we detected SARS-CoV-2 antibodies binding to the S1 antigen on the surface of functionalized MNPs. Without any purification or incubation, we could show a sensitivity of less than 50 ng/mL of SARS-CoV-2 antibodies in samples.
CRIS-Team Scopus Importer:2023-05-05

Feasibility of intraoperative assessment of safe surgical margins during laryngectomy with confocal laser endomicroscopy: A pilot study - Sievert, Matti; Oetter, Nicolai; Aubreville, Marc; Stelzle, Florian; Maier, Andreas; Eckstein, Markus; Mantsopoulos, Konstantinos; Gostian, Antoniu Oreste; Mueller, Sarina K.; Koch, Michael; Agaimy, Abbas; Iro, Heinrich; et al. (Auris Nasus Larynx, 2021)
Objective: This pilot study aimed to assess the feasibility of intraoperative assessment of safe margins with Confocal Laser Endomicroscopy (CLE) during planned partial or total laryngectomy. Methods: Eight patients with confirmed larynx squamous cell carcinoma (SCC) and planned partial or total laryngectomy were included in this study in March 2020. Two head and neck surgeons and one pathologist were asked to classify carcinoma or healthy epithelium in a sample of 94 representative sequences (5.640 images), blinded to the histological results (H&E staining). Results: Healthy mucosa areas showed epithelium with cells of uniform size and shape with distinct cytoplasmic membranes and regular vessel architecture. CLE optical biopsy of SCC demonstrated a disorganized arrangement of variable cellular morphology. We calculated an accuracy, sensitivity, specificity, PPV, and NPV of 80.1%, 72.3%, 87.9%, 85.7%, and 76.1%, respectively. A distinct transition between healthy appearing tissue and suspicious lesions could also be detected. Conclusion: CLE can be easily integrated into the intraoperative setting, generate real-time, in-vivo microscopic images of the larynx for evaluation and demarcation of cancer. If validated in further studies, CLE could eventually contribute to a less radical approach by enabling a more precise evaluation of the cancer margin.
CRIS-Team Scopus Importer:2021-01-29
Keywords: Confocal laser endomicroscopy; Laryngeal cancer; Safe surgical margins

Feasibility of sentinel lymph node detection by near-infrared endoscopy in squamous cell carcinoma of the oral cavity: A pilot study - Sievert, Matti; Goncalves, Miguel; Eckstein, Markus; Iro, Heinrich; Koch, M. (European Review for Medical and Pharmacological Sciences, 2020)
OBJECTIVE: Near-Infrared (NIR) fluorescence imaging is a novel technique for intraoperative sentinel lymph node (SLN) identification. It has demonstrated promising results in several surgical specialties. The study aims to evaluate the feasibility of identifying the SLN by indocyanine green (ICG) enhanced NIR endoscopy in squamous cell carcinoma of the oral cavity (OCSCC). PATIENTS AND METHODS: Seven patients with (cT1-3 N0) OCSCC were included. We injected 1-1.25 ml of ICG (5 mg/ml) at four to five points around the primary. After the elevation of a platysma flap and posterior retraction of the sternocleidomastoid muscle, fluorescence images were taken via IMAGE1 STM NIR/ICG system to define the SLN(s). We sampled fluorescence marked SLN(s) stratified to lymph node levels, followed by level-specified elective neck dissection. RESULTS: The detection of at least one unilateral or bilateral SLN (range 1-5) was possible in every case. The fluorescence signal occurred, on average, 5.0 ± 2.2 minutes after injection. A total of 22 SLN could be identified. Among 331 histo-logically examined lymph nodes we could detect one micrometastasis, which was correctly defined as SLN (1/22). There were no false-negative findings. No adverse reactions to ICG occurred. CONCLUSIONS: Our first results are indicating the concept of SLN concerning OCSCC after the application of real-time NIR fluorescence endoscopy. However, this has to be verified by more extended studies.
CRIS-Team Scopus Importer:2020-12-11
Keywords: Indocyanine green; Near-infrared-imaging; Neck dissection; Oral cavity squamous cell carcinoma; Sentinel node biopsy

Flow cytometry for intracellular SPION quantification: specificity and sensitivity in comparison with spectroscopic methods - Friedrich, Ralf P.; Janko, Christina; Poettler, Marina; Tripal, Philipp; Zaloga, Jan; Cicha, Iwona; Dürr, Stephan; Nowak, Johannes; Odenbach, Stefan; Slabu, Ioana; Liebl, Maik; Trahms, Lutz; et al. (International Journal of Nanomedicine, 2015)
Due to their special physicochemical properties, iron nanoparticles offer new promising possibilities for biomedical applications. For bench to bedside translation of super-paramagnetic iron oxide nanoparticles (SPIONs), safety issues have to be comprehensively clarified. To understand concentration-dependent nanoparticle-mediated toxicity, the exact quantification of intracellular SPIONs by reliable methods is of great importance. In the present study, we compared three different SPION quantification methods (ultraviolet spectrophotometry, magnetic particle spectroscopy, atomic adsorption spectroscopy) and discussed the shortcomings and advantages of each method. Moreover, we used those results to evaluate the possibility to use flow cytometric technique to determine the cellular SPION content. For this purpose, we correlated the side scatter data received from flow cytometry with the actual cellular SPION amount. We showed that flow cytometry provides a rapid and reliable method to assess the cellular SPION content. Our data also demonstrate that internalization of iron oxide nanoparticles in human umbilical vein endothelial cells is strongly dependent to the SPION type and results in a dose-dependent increase of toxicity. Thus, treatment with lauric acid-coated SPIONs (SEON(LA)) resulted in a significant increase in the intensity of side scatter and toxicity, whereas SEON(LA) with an additional protein corona formed by bovine serum albumin (SEON(LA-BSA)) and commercially available Rienso(®) particles showed only a minimal increase in both side scatter intensity and cellular toxicity. The increase in side scatter was in accordance with the measurements for SPION content by the atomic adsorption spectroscopy reference method. In summary, our data show that flow cytometry analysis can be used for estimation of uptake of SPIONs by mammalian cells and provides a fast tool for scientists to evaluate the safety of nanoparticle products.
EVALuna2:19955

Flow-structure-acoustic interaction in a human voice model - Becker, Stefan; Kniesburges, Stefan; Müller, Stefan; Delgado, Antonio; Link, Gerhard; Kaltenbacher, Manfred; Döllinger, Michael (Journal of the Acoustical Society of America, 2009)
UnivIS-Import:2015-03-09:Pub.2009.tech.ITC.stmmec.flowst

Flow-structure-acoustic interaction in a prestressed human larynx model - Kniesburges, Stefan; Becker, Stefan; Delgado, Antonio; Döllinger, Michael (IFMBE Proceedings, 2009)
For investigating the fluid-structure-acoustic coupled (FSA) process of human phonation, synthetic models of the vocal folds (VF) were designed which showed flow-induced oscillations and the sound production process. The models were developed to analyse the flow-induced vibration depending on the prestress similar to human vocal folds. They consisted of a silicon rubber whose Young's moduli corresponds to those found in human vocal folds between 3 and 13.2 kPa. The major aim of this work was to to observe the whole FSA process and to determine the acoustic sources. Therefore two approaches were applied: Firstly the vibration of the VFs was recorded using a high-speed camera triggered by the subglottal pressure to determine the phase shift between the two signals. Secondly synchronous measurements of the subglottal pressure, the flow velocity behind the VFs and the acoustic pressure were performed. In all investigations the influence of tension and stiffness of the VFs were analysed. The results shows that the vibration frequency and the phase shift between the subglottal pressure and the glottal width depended on different boundary conditions. The synchronous measurements determined the pressure fluctuations of the pulsating flow rate as main acoustic source.
UnivIS-Import:2015-04-16:Pub.2009.tech.ITC.stmmec.flowst_1

Fluctuation in electrical hearing in a Morbus Meniere's patient - Hast, Anne; Meßbacher, Maria-Elena; Liebscher, Tim; Hornung, Joachim; Hoppe, Ulrich (Clinical Case Reports, 2021)
The glycerol test is an easy-to-use instrument to elucidate fluctuations of electrical hearing in patients with Meniere's disease and it might be also used as a therapeutic option.
CRIS-Team WoS Importer:2021-08-13

Fluid-structure-acoustic interactions in an ex vivo porcine phonation model - Semmler, Marion; Berry, David A.; Schützenberger, Anne; Döllinger, Michael (Journal of the Acoustical Society of America, 2021)
In the clinic, many diagnostic and therapeutic procedures focus on the oscillation patterns of the vocal folds (VF). Dynamic characteristics of the VFs, such as symmetry, periodicity, and full glottal closure, are considered essential features for healthy phonation. However, the relevance of these individual factors in the complex interaction between the airflow, laryngeal structures, and the resulting acoustics has not yet been quantified. Sustained phonation was induced in nine excised porcine larynges without vocal tract (supraglottal structures had been removed above the ventricular folds). The multimodal setup was designed to simultaneously control and monitor key aspects of phonation in the three essential parts of the larynx. More specifically, measurements will comprise (1) the subglottal pressure signal, (2) high-speed recordings in the glottal plane, and (3) the acoustic signal in the supraglottal region. The automated setup regulates glottal airflow, asymmetric arytenoid adduction, and the pre-phonatory glottal gap. Statistical analysis revealed a beneficial influence of VF periodicity and glottal closure on the signal quality of the subglottal pressure and the supraglottal acoustics, whereas VF symmetry only had a negligible influence. Strong correlations were found between the subglottal and supraglottal signal quality, with significant improvement of the acoustic quality for high levels of periodicity and glottal closure.
CRIS-Team Scopus Importer:2021-03-26

Free Latissimus Dorsi Myocutaneous Flap in a 6-Month-Old Child for Reconstruction of a Temporal Fossa Defect After Teratoma Resection - Fried, Frederik W.; Beier, Justus; Bohr, Christopher; Iro, Heinrich; Horch, Raymund E.; Arkudas, Andreas (Annals of Plastic Surgery, 2019)
Although free flap reconstruction has already gained widespread acceptance in pediatric patients, little is known about the outcome of free tissue transfer in head and neck reconstruction in pediatric patients. We present a case of a 6-month-old boy with a large volume deficit in the right temporal fossa after resection of a teratoma. This led to a large volume deficit with widely undermined skin margins. Therefore, we provided volume augmentation by microsurgical free latissimus dorsi myocutaneous flap transplantation. Intraoperative use of laser-assisted indocyanine green angiography indicated excellent flap perfusion. Postoperative magnetic resonance imaging showed adequate flap perfusion with no signs of flap necrosis. To our best knowledge, this case presents the youngest patient who underwent free flap transplantation in the head and neck region. Our case demonstrates that microvascular surgery can play an important role in particular cases in pediatric oncology, even in very young patients.
EVALuna2:35384

Frequency of Malnutrition in Older Adults: A Multinational Perspective Using the Mini Nutritional Assessment - Kaiser, Matthias; Bauer, Judith; Raemsch, Christiane; Uter, Wolfgang; Guigoz, Yves; Cederholm, Tommy; Thomas, David R.; Anthony, Patricia S.; Charlton, Karen E.; Maggio, Marcello; Tsai, Alan C.; Vellas, Bruno; et al. (Journal of the American Geriatrics Society, 2010)
OBJECTIVESTo provide pooled data on the prevalence of malnutrition in elderly people as evaluated using the Mini Nutritional Assessment (MNA).DESIGNRetrospective pooled analysis of previously published datasets.SETTINGHospital, rehabilitation, nursing home, community.PARTICIPANTSFour thousand five hundred seven people (75.2% female) with a mean age of 82.3.MEASUREMENTSThe prevalence of malnutrition in the combined database and in the four settings was examined.RESULTSTwenty-four data sets with information on full MNA classification from researchers from 12 countries were submitted. In the combined database, the prevalence of malnutrition was 22.8%, with considerable differences between the settings (rehabilitation, 50.5%; hospital, 38.7%; nursing home, 13.8%; community, 5.8%). In the combined database, the "at risk" group had a prevalence of 46.2%. Consequently, approximately two-thirds of study participants were at nutritional risk or malnourished.CONCLUSIONThe MNA has gained worldwide acceptance and shows a high prevalence of malnutrition in different settings, except for the community. Because of its specific geriatric focus, the MNA should be recommended as the basis for nutritional evaluation in older people.
Keywords: malnutrition; undernutrition; Mini Nutritional Assessment; elderly; nutritional screening

From design to the clinic: practical guidelines for translating cardiovascular nanomedicine - Cicha, Iwona; Chauvierre, Cedric; Texier, Isabelle; Cabella, Claudia; Metselaar, Josbert M.; Szebeni, Janos; Dezsi, Laszlo; Alexiou, Christoph; Rouzet, Francois; Storm, Gert; Stroes, Erik; Bruce, Donald; et al. (Cardiovascular Research, 2018)
Cardiovascular diseases (CVD) account for nearly half of all deaths in Europe and almost 30% of global deaths. Despite the improved clinical management, cardiovascular mortality is predicted to rise in the next decades due to the increasing impact of aging, obesity, and diabetes. The goal of emerging cardiovascular nanomedicine is to reduce the burden of CVD using nanoscale medical products and devices. However, the development of novel multicomponent nano-sized products poses multiple technical, ethical, and regulatory challenges, which often obstruct their road to successful approval and use in clinical practice. This review discusses the rational design of nanoparticles, including safety considerations and regulatory issues, and highlights the steps needed to achieve efficient clinical translation of promising nanomedicinal products for cardiovascular applications.
EVALuna2:35449

Frozen Section of Parotid Gland Tumours: The Head and Neck Pathologist as a Key Member of the Surgical Team - Mantsopoulos, Konstantinos; Bessas, Zacharias; Sievert, Matti; Müller-Hübner, Sarina; Koch, Michael; Agaimy, Abbas; Iro, Heinrich (Journal of Clinical Medicine, 2022)
Introduction: The aim of this study was to evaluate the impact of subspecialised head and neck versus general surgical pathologists on the reliability of the histopathologic evaluation during intraoperative consultation. Materials and Methods: The medical records of all patients who underwent a parotidectomy with frozen section between 2006 and 2021 were retrospectively evaluated. The frozen section was evaluated for sensitivity, specificity, accuracy, and predictive value. Assessment by two groups of pathologists (subspecialised head and neck versus general surgical pathologists) was compared, and the nature or types of misdiagnoses compared with final diagnoses on paraffin sections were analysed for the two groups. Results: Our study sample was made up of 669 cases. The mean age of patients was 57.7 years (range: 10–94 years). Of these, 490 patients had a benign lesion (73.2%), whereas 179 patients had a malignant lesion (26.8%). Frozen section had an overall accuracy of 97.6%, sensitivity for malignancy was 91.1%, specificity was 100%, PPV was 100%, and the NPV was 96.8%. The exact histologic subtype in the group of malignant tumours was correctly identified in FS in 89.4% of cases. A comparison of head and neck pathologists versus general surgical pathologists revealed a highly statistically significant difference concerning both overall detection of malignancy (p < 0.001) as well as correct identification of the histologic subtype (p < 0.001). Conclusion: Involvement of subspecialised head and neck pathologists in the intraoperative consultation for salivary gland tumours results in a gain of 19.8% more sensitivity, underlining the importance of specialisation in salivary gland pathology for the optimisation of frozen section quality.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Accuracy; Benign tumour; Frozen section; Head and neck cancer; Malignant tumour; Parotid gland; Predictive value; Sensitivity; Specificity

Full-Thickness Skin Grafts and Quilting Sutures for the Reconstruction of Internal Nasal Lining - Gostian, Antoniu Oreste; Balk, Matthias; Stegmann, Achim; Iro, Heinrich; Wurm, Jochen (Facial Plastic Surgery, 2020)
Restoration of the inner nasal lining is an essential factor in successful nasal reconstruction. Among various methods, free full-thickness skin grafting represents a readily available and feasible technique. A prerequisite for success is a secure and immobile fixation to the undersurface of the nourishing forehead flap. This retrospective study aims to evaluate the results of multiple quilting sutures to secure free full-thickness skin grafts for the reconstruction of the inner nasal lining in partial and extended nasal reconstruction. Between February 1, 2015, and December 31 2018, 16 patients underwent three-stage nasal reconstruction of all three layers using a forehead flap. All full-thickness free flaps were harvested from either the neck or inguinal area and fixated to the undersurface of the distal part of the forehead flap by multiple quilting sutures. All but one free skin grafts healed well (seven ♀; mean: 63 years; range: 52-81). Four patients developed minor complications that resolved completely through conservative treatment. One patient with a history of stroke, extensive nicotine abuse, and arterial hypertension developed flap necrosis that required two surgical revisions and ended up with a stenosis of the left nostril. The follow-up time averaged 18.4 months (range: 3-55 months). Multiple quilting sutures are an effective and feasible option to fixate full-thickness free skin grafts on the undersurface of the forehead flap for the reconstruction of the inner nasal lining. They are not associated with increased risks for necrosis and can be applied even to extended full-thickness nasal defects in selected cases.
CRIS-Team Scopus Importer:2020-06-30

Functionalization of T lymphocytes for magnetically controlled immune therapy: Selection of suitable superparamagnetic iron oxide nanoparticles - Mühlberger, Marina; Janko, Christina; Unterweger, Harald; Schreiber, Eveline; Band, Julia; Lehmann, Christian; Dudziak, Diana; Lee, Geoffrey; Alexiou, Christoph; Tietze, Rainer (Journal of Magnetism and Magnetic Materials, 2019)
According to the World Health Organization, cancer is the second most important cause of death in Europe. Due to its manifold manifestations, it is not possible to treat all patients according to a uniform scheme. However, all solid tumors have one thing in common: independent of the tumor's molecular subgroup and the treatment protocol, the immune status of the tumor, especially the amount of tumor infiltrating lymphocytes (TILs), is important for the patient's clinical outcome - the higher the number of TILs, the better the outcome. For this reason it seems desirable to increase the number of TILs. One way to accumulate T cells in the tumor area is to make them magnetizable and attract them with an external magnetic field. Magnetization can be achieved by superparamagnetic iron oxide nanoparticles (SPIONs) which can be bound to the cells' surface or internalized into the cells. For this study, SPIONs with different coatings were synthesized and incubated with immortalized mouse T lymphocytes. SPIONs only stabilized with lauric acid (LA) coated in situ or afterwards showed high toxicity. Addition of an albumin layer increased the biocompatibility but reduced cellular uptake. To increase the cellular uptake the albumin coated particles were aminated, leading to both higher uptake and toxicity, dependent on the degree of amination. In the presence of an externally applied magnetic field, T cells loaded with selected types and amounts of SPIONs were guidable. With this promising pilot study we already can demonstrate that it is possible to attract SPION bearing T cells by an external magnet. To sum up, biocompatibility and uptake of SPIONs by T cells are opposing events. Thus, for the functionalization of T cells with SPIONs the balance between uptake and toxicity must be evaluated carefully.
EVALuna2:35445

Functionalization Of T Lymphocytes With Citrate-Coated Superparamagnetic Iron Oxide Nanoparticles For Magnetically Controlled Immune Therapy - Mühlberger, Marina; Janko, Christina; Unterweger, Harald; Friedrich, Ralf P.; Friedrich, Bernhard; Band, Julia; Cebulla, Nadine; Alexiou, Christoph; Dudziak, Diana; Lee, Geoffrey; Tietze, Rainer (International Journal of Nanomedicine, 2019)
Purpose: Immune activation with T cell tumor infiltration is beneficial for the prognosis of patients suffering from solid cancer. Depending on their immune status, solid tumors can be immunologically classified into three groups: "hot" tumors are infiltrated with T lymphocytes, "cold" tumors are not infiltrated and "immune excluded" tumors are only infiltrated in the peripheral tumor tissue. Checkpoint inhibitors provide new therapeutic options for "hot" tumors by triggering the immune response of T cells. In order to enable this for cold tumors as well, T cells must be enriched in the tumor. Therefore, we use the principle of magnetic targeting to guide T cells loaded with citrate-coated superparamagnetic iron oxide nanoparticles (SPIONCitrate) to the tumor by an externally applied magnetic field. Methods: SPIONCitrate were produced by alkaline coprecipitation of iron(II) and iron(III) chloride and in situ coating with sodium citrate. The concentration-dependent cytocompatibility of the particles was determined by flow cytometry and blood stability assays. Atomic emission spectroscopy was used for the quantification of the particle uptake into T lymphocytes. The attractability of the loaded cells was observed by live-cell imaging in the presence of an externally applied magnetic field. Results: SPIONCitrate displayed good cytocompatibility to T cells and did not show any sign of aggregation in blood. Finally, SPIONCitrate-loaded T cells were strongly attracted by a small external magnet. Conclusion: T cells can be "magnetized" by incorporation of SPIONCitrate for magnetic targeting. The production of the particle-cell hybrid system is straightforward, as the loading process only requires basic laboratory devices and the loading efficiency is sufficient for cells being magnetically controllable. For these reasons, SPIONCitrate are potential suitable candidates for magnetic T cell targeting.
EVALuna2:209938

Functionalized Superparamagnetic Iron Oxide Nanoparticles (SPIONs) as Platform for the Targeted Multimodal Tumor Therapy - Janko, Christina; Ratschker, Teresa; Nguyen, Khanh; Zschiesche, Lisa; Tietze, Rainer; Lyer, Stefan; Alexiou, Christoph (Frontiers in Oncology, 2019)
Standard cancer treatments involve surgery, radiotherapy, chemotherapy, and immunotherapy. In clinical practice, the respective drugs are applied orally or intravenously leading to their systemic circulation in the whole organism. For chemotherapeutics or immune modulatory agents, severe side effects such as immune depression or autoimmunity can occur. At the same time the intratumoral drug doses are often too low for effective cancer therapy. Since monotherapies frequently cannot cure cancer, due to their synergistic effects multimodal therapy concepts are applied to enhance treatment efficacy. The targeted delivery of drugs to the tumor by employment of functionalized nanoparticles might be a promising solution to overcome these challenges. For multimodal therapy concepts and individualized patient care nanoparticle platforms can be functionalized with compounds from various therapeutic classes (e.g. radiosensitizers, phototoxic drugs, chemotherapeutics, immune modulators). Superparamagnetic iron oxide nanoparticles (SPIONs) as drug transporters can add further functionalities, such as guidance or heating by external magnetic fields (Magnetic Drug Targeting or Magnetic Hyperthermia), and imaging-controlled therapy (Magnetic Resonance Imaging).
CRIS-Team WoS Importer:2019-02-27

Fusion of Preoperative MRI and Postoperative FD-CT for Direct Evaluation of Cochlear Implants: An Analysis at 1.5 T and 3 T - Eisenhut, Felix; Kleibe, Isabella; Hornung, Joachim; Iro, Heinrich; Dörfler, Arnd; Lang, Stefan; Taha, Lava (Clinical Neuroradiology, 2019)
Aim: This study was carried out to evaluate the diagnostic value of merging preoperative magnetic resonance imaging (MRI) with postoperative flat-panel computed tomography (FD-CT) and compare it to standard postoperative FD-CT for assessment of cochlear implant (CI) insertion. Methods: The T2-weighted (T2w) constructive interference in steady state (CISS) data sets of preoperative 1.5 T and 3 T MRI scans of CI patients with both regular and adverse implant spiralization were co-registered with the corresponding postoperative FD-CT data sets using defined anatomic landmarks. These merged FD-CT/MRI volumes (CMV) were compared to the corresponding postoperative FD-CT MPRs in consensus reading with respect to qualitative, i.e. scala tympani spiralization, scala vestibuli spiralization, scalar translocation and quantitative, i.e. distance of the last electrode to the lateral cochlea wall (D1) distance of the 2nd/5th electrode to the basal cochlear wall (D2) and the transition point (TP) of the scalar translocation, parameters. Results: In total 30 patients (n 1.5T MRI = 18 patients; n 3T MRI = 12 patients) were included in the analysis. In all cases both CMVs and FD-CT MPRs were generated. Qualitative analysis of intracochlear CI position with CMVs (both 1.5 T and 3 T) and FD-CT was equivalent: In 20 patients the CI showed a regular implant spiralization, in 10 cases a scalar translocation was identified with both CMVs and FD-CT. Quantitative analysis showed a high level of congruency between CMVs (both 1.5 T and 3T) and FD-CT for fusion accuracy (D1: mean FD-CT D1 = 1.30 ± 0.7 mm; mean CMV D1 = 1.27 ± 0.77 mm, correlation r = 0.94, p < 0.0001; D2: mean FD-CT D2 = 1.17 ± 0.34 mm; mean CMV D2 = 1.10 ± 0.31 mm, correlation r = 0.89, p < 0.0001) and TP of the scalar translocation (mean FD-CT = 126.0 ± 59.25°, mean CMV = 117.0 ± 52.82°, correlation r = 0.95, p < 0.0001). Conclusion: The co-registration of preoperative 1.5 and 3 T MRI with postoperative FD-CT enables a direct evaluation of the position of a CI equivalent to the current standard FD-CT. Despite the fact that CMV provided no additional diagnostic value in this series, regardless whether preoperative 1.5 or 3 T MRI was used for co-registration, it might help to simplify postoperative CI diagnostics.
CRIS-Team Scopus Importer:2019-12-03
Keywords: Cochlear implant; Flat panel computed tomography; Magnetic resonance imaging; Merging; Scalar translocation

Genomic aberrations of MDM2, MDM4, FGFR1 and FGFR3 are associated with poor outcome in patients with salivary gland cancer - Ach, Tobias; Schwarz-Furlan, Stephan; Ach, Stephanie; Agaimy, Abbas; Gerken, Michael; Rohrmeier, Christian; Zenk, Johannes; Iro, Heinrich; Brockhoff, Gero; Ettl, Tobias (Journal of Oral Pathology & Medicine, 2016)
Fibroblast growth factor receptor 1 and 3 (FGFR1, FGFR3) impact on tissue homoeostasis, embryonic development and carcinogenesis. Murine double minute protein 4 (MDM4) and mouse double minute 2 homologue (MDM2) are regulators of p53-protein and may be the origin of an apoptosis overpowering cascade. A collective of 266 carcinomas of salivary glands were investigated for MDM2, MDM4, FGFR1 and FGFR3 aberrations by fluorescence in situ hybridization (FISH). The results were matched with clinicopathological parameters and with expression of PTEN and p53. MDM2 gene amplification (n = 9) and chromosomal aberrations (trisomy, n = 47; high polysomy, n = 7) are linked to high-grade malignancy (P < 0.001), lymph node metastasis (P = 0.001), advanced tumour size (P = 0.013) and stage (P < 0.001), gender (P = 0.002) and age (P = 0.001). MDM4 gene amplification (n = 19) and chromosomal aberrations (trisomy, n = 34; high polysomy, n = 31) are correlated to high-grade malignancy (P < 0.001), lymph node metastasis (P = 0.008), advanced tumour size (P = 0.039), stage (P = 0.004) and loss of PTEN (P < 0.001). Only, high-grade malignancy (P < 0.001), lymph node metastasis (P = 0.036) and advanced tumour stage (P = 0.025) are associated with FGFR3 amplification (n = 1) or chromosomal aberrations (low polysomy, n = 61; high polysomy, n = 55) but not with MDM4 alterations. FGFR1 amplifications (n = 5) and chromosomal aberrations (trisomy, n = 38; high polysomy, n = 30) are associated with high-grade malignancy (P < 0.001), advanced tumour size (P = 0.026) and stage (P = 0.004), gender (P = 0.016) and age (P = 0.023). Aberrations of MDM2, MDM4, FGFR1 and FGFR3 correlate with aggressive tumour growth and nodal metastasis. MDM2 (P < 0.001), MDM4 (P = 0.005) and FGFR3 (P = 0.006) alterations are associated with worse overall survival of patients with salivary gland cancer.
EVALuna2:6776

Genotoxicity of Superparamagnetic Iron Oxide Nanoparticles in Granulosa Cells - Poettler, Marina; Staicu, Andreas; Zaloga, Jan; Unterweger, Harald; Weigel, Bianca; Schreiber, Eveline; Hofmann, Simone; Wiest, Irmi; Jeschke, Udo; Alexiou, Christoph; Janko, Christina (International Journal of Molecular Sciences, 2015)
Nanoparticles that are aimed at targeting cancer cells, but sparing healthy tissue provide an attractive platform of implementation for hyperthermia or as carriers of chemotherapeutics. According to the literature, diverse effects of nanoparticles relating to mammalian reproductive tissue are described. To address the impact of nanoparticles on cyto- and genotoxicity concerning the reproductive system, we examined the effect of superparamagnetic iron oxide nanoparticles (SPIONs) on granulosa cells, which are very important for ovarian function and female fertility. Human granulosa cells (HLG-5) were treated with SPIONs, either coated with lauric acid (SEONLA) only, or additionally with a protein corona of bovine serum albumin (BSA; SEON(LA-BSA)), or with dextran (SEON(DEX)). Both micronuclei testing and the detection of ?H2A.X revealed no genotoxic effects of SEON(LA-BSA), SEON(DEX) or SEON(LA). Thus, it was demonstrated that different coatings of SPIONs improve biocompatibility, especially in terms of genotoxicity towards cells of the reproductive system.
EVALuna2:19986

Gibt es eine neue Kopfspeicheldrüse? – Eher nicht! - Guntinas-Lichius, Orlando; Ihrler, Stephan; Freesmeyer, Martin; Guehne, Falk; Kluge, Regine; Bräuer, Lars; Iro, Heinrich; Paulsen, Friedrich; Dietz, Andreas; Bechmann, Ingo (Laryngo-Rhino-Otologie, 2020)
In October 2020, the lay press, but also some medical journals and websites reported the putative discovery of a new salivary gland in the nasopharynx based on prostate-specific membrane antigen positron emission tomography computed tomography (PSMA-PET/CT) examinations. As an interdisciplinary group from the fields of anatomy, pathology, nuclear medicine and otorhinolaryngology, we come to the view that an accumulation of minor salivary glands has been described here. Minor salivary glands in the nasopharynx and in the peritubar region have been described at least since 1866. The current description in PSMA-PET/CT does not justify the definition of a new, independent salivary gland. The PSMA-PET/CT could, however, be suitable to better protect salivary glands in the nasopharynx when planning radiation therapy. This should be evaluated in clinical trials.
CRIS-Team Scopus Importer:2020-12-04

GlottisNetV2: Temporal Glottal Midline Detection using Deep Convolutional Neural Networks - Kruse, Elina; Döllinger, Michael; Schützenberger, Anne; Kist, Andreas (IEEE Journal of Translational Engineering in Health and Medicine, 2023)
Objective: High-speed videoendoscopy is a major tool for quantitative laryngology. Glottis segmentation and glottal midline detection are crucial for computing vocal fold-specific, quantitative parameters. However, fully automated solutions show limited clinical applicability. Especially unbiased glottal midline detection remains a challenging problem. Methods and procedures: We developed a multitask deep neural network for glottis segmentation and glottal midline detection. We used techniques from pose estimation to estimate the anterior and posterior points in endoscopy images. Neural networks were set up in TensorFlow/Keras and trained and evaluated with the BAGLS dataset. Results: We found that a dual decoder deep neural network termed GlottisNetV2 outperforms the previously proposed GlottisNet in terms of MAPE on the test dataset (1.85% to 6.3%) while converging faster. Using various hyperparameter tunings, we allow fast and directed training. Using temporal variant data on an additional data set designed for this task, we can improve the median prediction accuracy from 2.1% to 1.76% when using 12 consecutive frames and additional temporal filtering. Conclusion: We found that temporal glottal midline detection using a dual decoder architecture together with keypoint estimation allows accurate midline prediction. Clinical impact: We show that our proposed architecture allows stable and reliable glottal midline predictions ready for clinical use and analysis of symmetry measures.
CRIS-Team Scopus Importer:2023-02-10
Keywords: biomedical imaging; Convolution; Decoding; Deep learning; deep learning; deep neural networks; glottis; Image segmentation; Laryngeal endoscopy; midline; Neural networks; Three-dimensional displays; Videos

Glutamic Acid Residues in HIV-1 p6 Regulate Virus Budding and Membrane Association of Gag - Friedrich, Melanie; Setz, Christian; Hahn, Friedrich; Matthaei, Alina; Fraedrich, Kirsten; Rauch, Pia; Henklein, Petra; Traxdorf, Maximilian; Fossen, Torgils; Schubert, Ulrich (Viruses, 2016)
The HIV-1 Gag p6 protein regulates the final abscission step of nascent virions from the cell membrane by the action of its two late (L-) domains, which recruit Tsg101 and ALIX, components of the ESCRT system. Even though p6 consists of only 52 amino acids, it is encoded by one of the most polymorphic regions of the HIV-1 gag gene and undergoes various posttranslational modifications including sumoylation, ubiquitination, and phosphorylation. In addition, it mediates the incorporation of the HIV-1 accessory protein Vpr into budding virions. Despite its small size, p6 exhibits an unusually high charge density. In this study, we show that mutation of the conserved glutamic acids within p6 increases the membrane association of Pr55 Gag followed by enhanced polyubiquitination and MHC-I antigen presentation of Gag-derived epitopes, possibly due to prolonged exposure to membrane bound E3 ligases. The replication capacity of the total glutamic acid mutant E0A was almost completely impaired, which was accompanied by defective virus release that could not be rescued by ALIX overexpression. Altogether, our data indicate that the glutamic acids within p6 contribute to the late steps of viral replication and may contribute to the interaction of Gag with the plasma membrane.
EVALuna2:8333

Going beyond extracapsular dissection in cystadenolymphomas of the parotid gland - Mantsopoulos, Konstantinos; Goncalves, Miguel; Koch, Michael; Traxdorf, Maximilian; Schapher, Mirco; Iro, Heinrich (Oral Oncology, 2019)
BACKGROUND: The aim of this study was to evaluate the potential for reducing surgical invasiveness in parotid cystadenolymphomas by means of capsular dissection based on the experience made in our department and on various aspects of these lesions gained from the relevant literature. METHODS: All patients treated for cystadenolymphomas with extracapsular or capsular dissection at a tertiary referral center between 2000 and 2017 were examined retrospectively. A literature review of various aspects and of different treatment strategies for this lesion was also performed. RESULTS: 629 patients were included in the study. 499 had solitary tumors (79.3%) and 130 had unilateral multicentric lesions (20.7%). 595 patients were managed by means of ED, while 34 patients underwent a CD. Our analysis detected an overall occurrence rate of ipsilateral metachronous tumors of 2.06% (13/629), all after extracapsular dissection, with a mean follow-up of 104.1 months. No statistical difference could be found between ED and CD in the overall occurrence rate of ipsilateral metachronous tumors or in the complication rate. No cases of a malignancy arising from a preexisting Warthin tumor could be detected in our study sample. CONCLUSION: A clear potential for reducing surgical invasiveness could be shown. A reliable imaging diagnosis, appropriate patient counseling and high compliance with close follow-up are the basic prerequisites for an acceptable outcome.
EVALuna2:35382

Graphene-Induced Hyperthermia (GIHT) Combined With Radiotherapy Fosters Immunogenic Cell Death - Podolska, Malgorzata; Shan, Xiaomei; Janko, Christina; Boukherroub, Rabah; Gaipl, Udo; Szunerits, Sabine; Frey, Benjamin; Munoz, Luis Enrique (Frontiers in Oncology, 2021)
Radiotherapy and chemotherapy are the standard interventions for cancer patients, although cancer cells often develop radio- and/or chemoresistance. Hyperthermia reduces tumor resistance and induces immune responses resulting in a better prognosis. We have previously described a method to induce tumor cell death by local hyperthermia employing pegylated reduced graphene oxide nanosheets and near infrared light (graphene-induced hyperthermia, GIHT). The spatiotemporal exposure/release of heat shock proteins (HSP), high group mobility box 1 protein (HMGB1), and adenosine triphosphate (ATP) are reported key inducers of immunogenic cell death (ICD). We hypothesize that GIHT decisively contributes to induce ICD in irradiated melanoma B16F10 cells, especially in combination with radiotherapy. Therefore, we investigated the immunogenicity of GIHT alone or in combination with radiotherapy in melanoma B16F10 cells. Tumor cell death in vitro revealed features of apoptosis that is progressing fast into secondary necrosis. Both HSP70 and HMGB1/DNA complexes were detected 18 hours post GIHT treatment, whereas the simultaneous release of ATP and HMGB1/DNA was observed only 24 hours post combined treatment. We further confirmed the adjuvant potential of these released DAMPs by immunization/challenge experiments. The inoculation of supernatants of cells exposed to sole GIHT resulted in tumor growth at the site of inoculation. The immunization with cells exposed to sole radiotherapy rather fostered the growth of secondary tumors in vivo. Contrarily, a discreet reduction of secondary tumor volumes was observed in mice immunized with a single dose of cells and supernatants treated with the combination of GIHT and irradiation. We propose the simultaneous release of several DAMPs as a potential mechanism fostering anti-tumor immunity against previously irradiated cancer cells.
CRIS-Team Scopus Importer:2021-09-17
Keywords: hyperthermia; immunogenic cell death; melanoma; multimodal; radiotherapy; reduced graphene oxide

Graphene Oxide Nanosheets for Localized Hyperthermia-Physicochemical Characterization, Biocompatibility, and Induction of Tumor Cell Death - Podolska, Malgorzata; Barras, Alexandre; Alexiou, Christoph; Frey, Benjamin; Gaipl, Udo; Boukherroub, Rabah; Szunerits, Sabine; Janko, Christina; Munoz, Luis Enrique (Cells, 2020)
Background: The main goals of cancer treatment are not only to eradicate the tumor itself but also to elicit a specific immune response that overcomes the resistance of tumor cells against chemo- and radiotherapies. Hyperthermia was demonstrated to chemo- and radio-sensitize cancerous cells. Many reports have confirmed the immunostimulatory effect of such multi-modal routines. Methods: We evaluated the interaction of graphene oxide (GO) nanosheets; its derivatives reduced GO and PEGylated rGO, with components of peripheral blood and evaluated its thermal conductivity to induce cell death by localized hyperthermia. Results: We confirmed the sterility and biocompatibility of the graphene nanomaterials and demonstrated that hyperthermia applied alone or in the combination with radiotherapy induced much more cell death in tumor cells than irradiation alone. Cell death was confirmed by the release of lactate dehydrogenase from dead and dying tumor cells. Conclusion: Biocompatible GO and its derivatives can be successfully used in graphene-induced hyperthermia to elicit tumor cell death.
CRIS-Team WoS Importer:2020-05-15

Guideline "Implantable hearing aids"-short version : German S2k guideline of the Working Group of German-speaking Audiologists, Neurootologists and Otologists (ADANO), of the German Society of Oto-Rhino-Laryngology, Head and Neck Surgery (DGHNO) in collaboration with the German Society of Audiology (DGA), the German Society of Phoniatrics and Pediatric Audiology (DGPP), and patient representatives - Beutner, D.; Delb, W.; Frenzel, H.; Hoppe, Ulrich; Huettenbrink, K. B.; Mlynski, R.; Limberger, A.; Schoenweiler, R.; Schwab, B.; Todt, I.; Walger, M.; Wesarg, T.; et al. (HNO, 2018)
EVALuna2:210000

Guideline "Implantable hearing aids"-short version : German S2k guideline of the Working Group of German-Speaking Audiologists, Neurootologists and Otologists (ADANO), of the German Society of Oto-Rhino-Laryngology, Head and Neck Surgery (DGHNO) in collaboration with the German Society of Audiology (DGA), the German Society of Phoniatrics and Pediatric Audiology (DGPP), and patient representatives. - Beutner, D.; Delb, W.; Frenzel, H.; Hoppe, Ulrich; Huettenbrink, K. B.; Mlynski, R.; Limberger, A.; Schoenweiler, R.; Schwab, B.; Todt, I.; Walger, M.; Wesarg, T.; et al. (HNO, 2018)
EVALuna2:210001

Guiding and Accumulation of Magnetic Nanoparticles Employing High Intensity Focused Ultrasound for Drug Targeting Applications - George, Benedikt; Fink, Michael; Ermert, Helmut; Rupitsch, Stefan; Lyer, Stefan; Alexiou, Christoph (Current Directions in Biomedical Engineering, 2019)
Magnetic Drug Targeting (MDT) is a cancer treatment technique that enables a local chemotherapy. In MDT, chemotherapeutic drugs are bound to magnetic nanoparticles and are accumulated in the tumor area by means of an external magnetic field. Unfortunately, a single magnet can only generate a pulling magnetic force. However, in some applications a pushing force on the nanoparticles could be advantageous. One way to realize pushing forces is to exploit the acoustic radiation force based on the nonlinearity of sound propagation in fluid media generated by a high intensity focused ultrasonic transducer. In this context, we built a test setup was built to investigate the utility of High Intensity Focused Ultrasound (HIFU) to generate a pushing force on the magnetic nanoparticles. The results show that the acoustic radiation force can be employed for particle guidance to achieve concentration differences similar to those obtained by using an electromagnet.
CRIS-Team Scopus Importer:2022-06-27
Keywords: acoustic radiation force; drug targeting; nanoparticles; Ultrasound

Guiding and Accumulation of Magnetic Nanoparticles Employing High Intensity Focused Ultrasound for Drug Targeting Applications - George, Benedikt; Fink, Michael; Rupitsch, Stefan; Ermert, Helmut; Alexiou, Christoph; Lyer, Stefan (Current Directions in Biomedical Engineering 2019, 2019)

Haptic Rendering of Soft-Tissue for Training Surgical Procedures at the Larynx - Eixelberger, Thomas; Parchent, Jonas; Janka, Rolf Matthias; Stamminger, Marc; Döllinger, Michael; Wittenberg, Thomas (Bildverarbeitung für die Medizin 2020, Informatik aktuell, 2020)

Head and Neck Kaposi Sarcoma: Clinicopathological Analysis of 11 Cases - Agaimy, Abbas; Mueller, Sarina K.; Harrer, Thomas; Bauer, Sebastian; Thompson, Lester D. R. (Head and Neck Pathology, 2018)
Kaposi sarcoma (KS) of the head and neck area is uncommon with limited published case series. Our routine and consultation files were reviewed for histologically and immunohistochemically proven KS affecting any cutaneous or mucosal head and neck site. Ten males and one female aged 42-78 years (median, 51 years; mean, 52 years) were retrieved. Eight patients were HIV-positive and three were HIV-negative. The affected sites were skin (n = 5), oral/oropharyngeal mucosa (n = 5), and lymph nodes (n = 3) in variable combination. The ear (pinna and external auditory canal) was affected in two cases; both were HIV-negative. Multifocal non-head and neck KS was reported in 50% of patients. At last follow-up (12-94 months; median, 46 months), most of patients were either KS-free (n = 8) or had ongoing remission under systemic maintenance therapy (n = 2). One patient was alive with KS (poor compliance). Histopathological evaluation showed classical features of KS. One case was predominantly sarcomatoid with prominent inflammation mimicking undifferentiated sarcoma. Immunohistochemistry showed consistent expression of CD31, CD34, ERG, D2-40 and HHV8 in all cases. This is one of the few series devoted to head and neck KS showing high prevalence of HIV-positivity, but also unusual presentations in HIV-negative patients with primary origin in the skin of the ear and the auditory canal. KS should be included in the differential diagnosis of difficult-to-classify spindle cell lesions at this uncommon location.
EVALuna2:207378

Hearing aid provision - can the limited obligation of statutory health insurance to provide indemnification only up to the reference price be successfully challenged in the social courts in cases of medical indication? - Lottner, Anna; Iro, Heinrich; Schützenberger, Anne; Hoppe, Ulrich (Laryngo-Rhino-Otologie, 2019)
OBJECTIVE: When patients are provided with hearing aids, the question may arise whether they are entitled to technically advanced and therefore more expensive hearing aids in cases of medical indication, or just to hearing aids for the reference price. This work provides an overview of decisions rendered by the German social courts. We investigated whether it is advisable for a patient to go to court if the statutory health insurance has disputed a claim, and how long the proceedings may take. MATERIAL AND METHODS: We looked for decisions in the commercial legal database "juris", using the search parameters "Hörgerät" (hearing aid) and "Zuzahlung" (additional payment). The reviewed decisions were issued between 2009 and 2019. RESULTS: A total of 97 relevant decisions were found. The results varied according to the specifics of the individual case. 63 % of the patients won their cases. The court procedures took between 0.3 years and 10.4 years. CONCLUSIONS: The study shows that it is uncertain whether the costs for hearing aids that exceed the reference price will be covered or reimbursed. As each case is in principle unique, the results vary. Nevertheless, taking legal action is recommended after thorough consideration in cases where statutory health insurances or other providers refuse to meet expenses incurred despite indication.
EVALuna2:209866

Hearing restoration with cochlear implants after translabyrinthine vestibular schwannoma resection - Bohr, Christopher; Müller, Susanna; Hornung, Joachim; Hoppe, Ulrich; Iro, Heinrich (HNO, 2017)
BACKGROUND: Hearing restoration after translabyrinthine vestibular schwannoma resection is a challenge. Because the cochlea can begin to ossify a few months after cochlear or labyrinthine injury, the time interval for cochlear implant surgery is limited. To avoid complete ossification and to prolong the time interval until cochlear implantation, it is possible to insert a placeholder (depth gauge) into the cochlea and perform the cochlear implant surgery at a later time point (two-stage approach). OBJECTIVE: The aim of this retrospective case series was to present the outcomes after restoration of hearing with cochlea implants in six patients and to evaluate the use of the depth gauge in practice. METHODS: The hearing outcome of all patients with (n = 3) and without (n = 3) insertion of a depth gauge was measured with the Freiburg monosyllabic test without background noise at 65 dB. The first measurement was performed prior to the translabyrinthine vestibular schwannoma resection, the last measurement was performed up to 48 months after cochlear implantation. RESULTS: All 6 patients reached 22.5 ± 36.57% prior to vestibular schwannoma resection and 41.3 ± 26% 12 months after cochlear implantation. The understanding values of the patients with a depth gauge were 25.8 ± 16% after 12 months which is below the values of the other patients with 56.6 ± 25.0%. No severe intraoperative or postoperative complications occurred in any patient. CONCLUSION: The two-stage approach for cochlear implantation with depth gauge insertion following labrynthine incision and intact nerve appears to represent a very promising and safe variation for hearing restoration. Intensified research on this approach seems to be justified and necessary.
EVALuna2:33160

High-grade histology as predictor of early distant metastases and decreased disease-free survival in salivary gland cancer irrespective of tumor subtype - Haderlein, Marlen; Scherl, Claudia; Semrau, Sabine; Lettmaier, Sebastian; Uter, Wolfgang; Neukam, Friedrich Wilhelm; Iro, Heinrich; Agaimy, Abbas; Fietkau, Rainer (Head and Neck-Journal For the Sciences and Specialties of the Head and Neck, 2016)
The purpose of this study was to evaluate risk factors that influence overall survival (OS)/disease-free survival (DFS)/locoregional recurrence-free survival (LRFS), and distant metastases-free survival (DMFS) in patients with high-risk primary salivary gland carcinoma who underwent surgery and postoperative (chemo)radiotherapy with curative intention.We reviewed data of 63 patients with high-risk primary salivary gland carcinoma in a retrospective single-center audit.At a median follow-up of 31 months (range, 5-145 months), cumulative OS and DFS were 91.7%, 77.6%, and 62.9%, and 82.1%, 65.6%, and 57.7%, respectively, after 1, 2, and 5 years. LRFS and DMFS were 92%, 86%, and 86%, and 83.4%, 70.4%, and 62.3% after 1, 2, and 5 years, respectively. Of all patient-related, tumor-related, and treatment-related factors, high-grade histology (G3) was the only factor in univariate and multivariate analysis that was predictive for a shorter DMFS (low/intermediate vs high-grade: 100%, 100%, and 89.4% vs 72.9%, 54.3%, and 42.8% after 1, 2, and 5 years, respectively) and a shorter DFS (low/intermediate vs high-grade: 100%, 90%, and 84.4% vs 71.2%, 50.1%, and 39.4% after 1, 2, and 5 years, respectively) and OS (low/intermediate vs high-grade: 100%, 100%, and 86.5% vs 86.5%, 63.2%, and 46.5% after 1, 2, and 5 years, respectively).High-grade tumor histology is a highly significant predictor of a shorter DMFS, OS, and DFS in salivary gland carcinoma, irrespective of histological subtype. © 2016 Wiley Periodicals, Inc. Head Neck 38: E2041-E2048, 2016.
EVALuna2:5539

High-grade salivary gland cancer: is surgery followed by radiotherapy an adequate treatment to reach tumor control? Results from a tertiary referral centre focussing on incidence and management of distant metastases - Freitag, Viola; Lettmaier, Sebastian; Semrau, Sabine; Hecht, Markus; Mantsopoulos, Konstantinos; Müller-Hübner, Sarina; Traxdorf, Maximilian; Iro, Heinrich; Agaimy, Abbas; Fietkau, Rainer; Haderlein, Marlen (European Archives of Oto-Rhino-Laryngology, 2021)
Purpose: Salivary Gland cancer (SGC) is a rare and heterogenous group of tumors. Standard therapeutic options achieve high local but poor distant control rates, especially in high-grade SGC. The aim of this monocentric study was to evaluate patterns of recurrence and its treatment options (local ablative vs. systemic) in a homogenously treated patient population with high-grade SGC after surgery and radio(chemo)therapy. Methods: Monocentric, retrospective study of patients with newly diagnosed high-grade salivary gland cancer. We retrospectively reviewed clinical reports from 69 patients with high-grade salivary gland cancer in a single-center audit. Survival rates were calculated using the Kaplan–Meier method and prognostic variables were analyzed (univariate analysis: log-rank test; multivariate analysis: Cox regression analysis). Results: The median time of follow-up was 31 months. After 5 years, the cumulative overall survival was 65.2%, cumulative incidence of local recurrence was 7.2%, whereas the cumulative incidence of distant metastases was 43.5% after 5 years. 30 of 69 patients developed distant metastases during the time of follow-up, especially patients with adenoid cystic carcinoma, salivary duct carcinoma, adenocarcinoma NOS and acinic cell carcinoma with high-grade transformation. The most common type of therapy therefore was chemotherapy (50%). 85.7% of patients with local ablative therapy of distant metastases show disease progression during follow-up afterwards. Conclusion: With surgery and radio-chemotherapy, a high rate of loco-regional control is reached, but over 40% of patients develop distant metastases in the further follow-up which usually present a diffuse pattern involving in a diffuse metastases. Therefore, in the future, intensified interdisciplinary combination therapies even in the first-line treatment in certain subtypes of high-grade SGC should be investigated.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Chemotherapy; Distant metastases; High-grade; Radiotherapy; Salivary gland cancer

Highlights from the 2021 ASCO and ESMO annual meetings on radiotherapy of head and neck cancer Highlights der ASCO- und ESMO-Jahrestagungen 2021 zur Strahlentherapie von Kopf-Hals-Tumoren - Hecht, Markus; von der Grün, Jens; Semrau, Sabine; Müller, Susanna; Weissmann, Thomas; Gaipl, Udo; Iro, Heinrich; Fietkau, Rainer; Gostian, Antoniu-Oreste (HNO, 2022)
At this year’s annual meetings of the American Society of Clinical Oncology (ASCO) and the European Society for Medical Oncology (ESMO), several studies on radiotherapy of locally advanced head and neck cancer were presented. For the indication of definitive radiochemotherapy, particularly the administration of immune checkpoint inhibitors concomitant to radiotherapy was investigated. In the phase III GORTEC-REACH trial, combined inhibition of epidermal growth factor receptor (EGFR) and programmed death-ligand (PD-L1) concomitant to radiotherapy of locally advanced head and neck cancer was inferior to platinum-based chemoradiotherapy. However, this therapeutic approach may be more efficient than radiotherapy with simultaneous EGFR inhibition alone. The concept of the phase II CheckRad-CD8 trial with induction chemoimmunotherapy followed by chemotherapy-free radioimmunotherapy after appropriate patient selection also proved to be highly efficient. In initial phase II trials, dose de-escalation of radiotherapy seems feasible for HPV-positive oropharyngeal cancer after appropriate patient selection both postoperatively (ECOG-ACRIN E3311 trial) and after induction therapy (Optima II trial). However, dose de-escalation should currently not be performed outside of clinical trials. In addition, first studies indicate a benefit of functional imaging (diffusion-weighted magnetic resonance imaging [MRI] or F‑fluoromisonidazole positron-emission tomography [FMISO-PET]) to establish personalized dose concepts in radiotherapy.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Chemoradiotherapy; Head and neck squamous cell carcinoma; Human papillomavirus; Immunotherapy; Oropharyngeal cancer

Highlights from the latest articles in nanoparticles, nanomaterials and nanotoxicity testing - Lyer, Stefan; Cicha, Iwona; Friedrich, Ralf; Janko, Christina; Alexiou, Christoph (Nanomedicine, 2015)
EVALuna2:19966

High locoregional Control Rates after Radio (chemo) Therapy in anaplastic Thyroid Carcinoma - a monocentric Analysis - Schmied, M.; Semrau, Sabine; Hecht, Markus; Lettmaier, Sebastian; Mantsopoulos, K.; Traxdorf, Maximilian; Iro, Heinrich; Denz, Axel; Grützmann, Robert; Fietkau, Rainer; Haderlein, Marlen (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

High-speed and Phase-averaged PIV in a synthetic human larynx model - a comparative analysis - Lodermeyer, Alexander; Kniesburges, Stefan; Tautz, Matthias; Döllinger, Michael; Birk, Veronika; Becker, Stefan (18th International symposium on applications of laser techniques to fluid mechanics, 2016)

High-speed flat-detector computed tomography for temporal bone imaging and postoperative control of cochlear implants - Eisenhut, Felix; Manhart, Michael; Thimsen, Vivian; Mantsopoulos, Konstantinos; Iro, Heinrich; Hornung, Joachim; Dörfler, Arnd; Lang, Stefan; Taha, Lava (Neuroradiology, 2022)
Purpose: Flat-detector computed tomography (FD-CT) is the standard for cochlear implant (CI) imaging. FD-CT systems differ in technical characteristics. Our aim was an evaluation of two different FD-CT generations with different protocols and hardware regarding image quality, radiation dose, and scan time. Methods: Two temporal bone specimens (− / + CI = TB0/TB1) were scanned using three different scanners: two FD-CT systems with different scanning protocols (standard FD-CT: 20 s 70 kV, 20 s 109 kV; high-speed FD-CT [HS-FD-CT]: 7 s 109 kV, 9 s 109 kV, 14 s 72 kV) and MS-CT (5 s 120 kV). Acquired datasets were evaluated in consensus reading regarding qualitative and quantitative parameters: addressing CI- and cochlea-specific parameters, cochlea delineation, lamina spiralis ossea visibility, distinction of single CI electrodes, determination of intracochlear implant position, stapes delineation, and mastoidal septation were assessed. Addressing protocol-specific parameters, radiation dose (dose-length-product/DLP), and scan time were assessed. Results: Two HS-FD-CT protocols (14 s/9 s) provide higher or equivalent diagnostic information regarding CI- and cochlea-specific parameters compared to both standard FD-CT protocols. The fastest HS-FD-CT protocol (7 s)—providing inferior diagnostic information compared to all other FD-CT protocols—still exceeds MS-CT. The highest DLP was recorded for the 14 s HS-FD-CT protocol (TB1 = 956 mGycm); the lowest DLPs were recorded for the 7 s HS-FD-CT protocol (TB0 = 188 mGycm) and for MS-CT (TB0 = 138 mGycm), respectively. HS-FD-CT allows a significant reduction of scan time compared to standard FD-CT. Conclusion: High-speed FD-CT improves visualization of temporal bone anatomy and postoperative assessment of CIs by combining excellent image quality, fast scan time, and reasonable radiation exposure.
CRIS-Team Scopus Importer:2022-04-22
Keywords: Anatomy; Cochlear implant; Flat-detector computed tomography; Postoperative control; Temporal bone

High-speed video endoscopy to improve the diagnosis of voice disorders - Dürr, Stephan; Schützenberger, Anne; Kist, Andreas; Semmler, Marion; Schraut, Tobias; Arias Vergara, Tomás; Döllinger, Michael (2022)
Introduction A voice disorder causes a significant loss of quality of life. Today, stroboscopy is the standard diagnostic method. Causes are incomplete glottis closure and/or irregular, aperiodic vocal fold oscillations, which can only be made visible to a limited extent by stroboscopy. Methods High-speed video endoscopy (HSV) is a new examination method that significantly improves the temporal resolution and thus allows a clearer assessment of vocal fold vibrations. Current, clinically applicable HSV systems allow a temporal representation of 4000-8000 images per second with sufficiently good spatial resolution. Using image processing, it is possible to calculate quantitative parameters regarding the vocal fold vibration characteristics (i.e. glottis closure, periodicity, symmetry). Results The presented high-speed system (OpenHSV) in combination with the analysis software "Glottis Analysis Tools" (GAT) allows both the visualisation and the quantification of the disturbance of vocal fold vibrations. The HSV thus provides objective support in making a diagnosis and assessing the course of therapy. Conclusions HSV is a new innovative method that allows quantitative analysis and thus better diagnosis of voice disorders. For example, both phonatory vocal fold arrest, which is crucial for distinguishing between simple leukoplakia or carcinoma in situ or carcinoma, and irregular oscillations in functional dysphonia can be assessed more accurately and appropriate therapy can be initiate

Histopathological comparison of pleomorphic adenomas of the parotid and submandibular gland - Mantsopoulos, Konstantinos; Sievert, Matti; Iro, Ann Kristin; Müller, Susanna; Koch, Michael; Schapher, Mirco; Agaimy, Abbas; Iro, Heinrich (Oral Diseases, 2021)
Objective: The aim of this study was to investigate and compare the histopathological findings in pleomorphic adenomas (PA) of the parotid and submandibular gland with emphasis on the histological subtype and capsular characteristics. Materials and Methods: The histopathological specimens of all patients with PAs of the parotid and submandibular gland between 2000 and 2020 were re-examined by an experienced head and neck pathologist. Patients without representative slides allowing evaluation of the whole periphery of the PA were excluded from our study sample. Results: Nine hundred and thirty-four patients formed our study sample (327 men, 607 women, male-to-female ratio: 0.53:1). Eight hundred and forty-four cases had a PA in the parotid gland and the remaining 90 in the submandibular gland. Our comparative analysis showed that submandibular PAs are characterized by the consistent presence of an intact anatomical capsule, infrequent occurrence of pseudopodia and satellite nodules, and a low proportion of the high-risk myxoid subtype. Conclusion: Our study highlights significant differences between PAs of the parotid and submandibular glands in their histopathological characteristics. Their differences likely underlie the favorable surgical outcome observed in PAs of the submandibular glands and may explain the propensity of PAs of the parotid glands for local recurrences.
CRIS-Team Scopus Importer:2021-04-16
Keywords: capsule; parotid gland; pleomorphic adenoma; satellite nodules; submandibular gland

Histopathology of Parotid Pleomorphic Adenomas: A "Pleomorphic Approach" to a Demanding Lesion - Mantsopoulos, Konstantinos; Thimsen, Vivian; Gostian, Antoniu-Oreste; Mueller, Sarina K.; Sievert, Matti; Iro, Ann-Kristin; Agaimy, Abbas; Iro, Heinrich (Laryngoscope, 2021)
Objectives/Hypothesis The aim of this study was to identify potential associations between epidemiologic, morphologic, and histopathologic features in pleomorphic adenomas (PAs) of the parotid gland in order to extract information about the natural course and biologic behavior of these lesions on the basis of a single-center series of 845 cases within a period of 15 years. Study Design Retrospective study in a tertiary academic center. Methods For this study, an experienced head and neck pathologist critically re-evaluated the histological slides of the pathological specimens of all patients who underwent a parotidectomy for PA of the parotid gland between 2006 and 2020. Results A total of 845 cases made up our study sample. Our analysis showed a statistically significant association of the histologic subtype with younger age (P = .001) and maximal diameter (P = .044), with the hypocellular type being encountered more often in younger patients and in smaller lesions. The same subtype was significantly associated with an incomplete capsule (P = .001), pseudopodia (P = .006), and satellite nodules (P = .001). An incomplete capsule was associated with the presence of pseudopodia (P = .001) and satellite nodules (P = .001). Conclusion It seems that various histologic subtypes have different capsule-producing properties. Apparently, over the course of time, tumor material builds a finger-like projection still inside the capsule, separates itself from the parenchyma with fibrous tissue still remaining enclosed within the capsule (pseudopodium), slowly penetrates the capsule (incomplete capsule), and leaves the main lesion taking a part of the capsule with it (satellite nodules). Laryngoscope, 2021
CRIS-Team WoS Importer:2021-07-16

HMGA2-WIF1 Rearrangements Characterize a Distinctive Subset of Salivary Pleomorphic Adenomas With Prominent Trabecular (Canalicular Adenoma-like) Morphology - Agaimy, Abbas; Ihrler, Stephan; Baneckova, Martina; Martineau, Valerie Costes; Mantsopoulos, Konstantinos; Hartmann, Arndt; Iro, Heinrich; Stöhr, Robert; Skalova, Alena (American Journal of Surgical Pathology, 2022)
Most of salivary gland neoplasms (benign and malignant) are characterized by recurrent gene fusions. Pleomorphic adenoma (PA), the most frequent salivary gland tumor, is driven by chromosomal rearrangements involving PLAG1 mapped to 8q12 and HMGA2 mapped to 12q13-15 in most cases. Multiple fusion partners have been identified including CTNNB1, FGFR1, LIFR, CHCHD7 and TCEA for PLAG1 fusions and NFIB, WIF1 and FHIT for HMGA2 fusions. To date, no data exist on the morphology of the few reported HMGA2-WIF1-rearranged PAs. We present 28 major salivary gland adenomas displaying distinctive trabecular and canalicular morphology associated with recurrent genotype. Patients were 15 females and 13 males aged 43 to 87 (median: 65). All tumors originated from the parotid. Their size range was 1 to 4 cm (mean: 2.3). Histologically, all tumors showed elongated or columnar cells arranged into bilayered to multilayered communicating and branching strands and trabeculae in a manner similar to canalicular adenoma of minor salivary glands or trabecular myoepithelioma with variable solid confluent intercalated duct-like areas. Fifteen tumors were exclusively canalicular/trabecular while 13 had intermingled or well-demarcated conventional (chondromyxoid) PA component comprising 5 to >50% of the tumor. The monomorphic areas expressed uniformly CK7 (28/28), vimentin (21/21), S100 (24/24), SOX10 (16/17) and variably p63 (8/21) and mammaglobin (6/16) but were negative with p40 (0/24), smooth muscle actin (0/24) and MUC4 (0/16). Targeted RNA sequencing revealed HMGA2 fusions in 14/16 (87%) assessable cases. Fusion partner was WIF1 (12), RPSAP52 (1) and HELB (1). Separate testing of the 2 components in 1 hybrid tumor showed same HMGA2/WIF1 fusion. HMGA2 immunohistochemistry was homogeneously positive in all cases including the 2 fusion-negative cases. A control cohort of 12 genuine canalicular adenomas revealed no HMGA2 fusions (0/4) and lacked HMGA2 immunoreactivity (0/12). This study highlights a distinctive variant in the spectrum of PA characterized by prominent trabecular and canalicular adenoma-like morphology. Our data confirm that canalicular adenomas in major salivary glands (either monomorphic or part of hybrid tumors) are distinct from canalicular adenoma of minor salivary glands. Their uniform genotype irrespective of presence or absence of a conventional PA component argues for classifying those tumors lacking a conventional PA component as "monomorphic variants of PA" rather than canalicular/basal cell adenomas, intercalated duct adenoma, trabecular myoepithelioma or true hybrid tumors.
CRIS-Team WoS Importer:2022-01-21

Hörgeräte: Indikationen, Technologie, Anpassung und Qualitätskontrolle - Hoppe, Ulrich; Hesse, Gerhard (Laryngo-Rhino-Otologie, 2017)
Hearing loss can be caused by a number of different pathological conditions. Some of them can be successfully treated, mainly by surgery, depending on the individual's disease process. However, the treatment of chronic sensorineural hearing loss with damaged cochlear structures usually needs hearing rehabilitation by means of technical amplification. During the last 2 decades tremendous improvements in hearing aid technology led to a higher quality in the hearing rehabilitation process. For example, due to sophisticated signal processing the acoustic feedback path could be reduced and hence open fitting options are available for even more subjects. In particular for high-frequency hearing loss the use of open fitting is an option. Both the users' acceptance and the perceived sound quality were significantly increased by open fittings.However, we are still faced with a low level of readiness in many hearing impaired subjects to accept acoustic amplification. Since ENT specialists play a key-role in hearing aid provision, they should promote early hearing aid rehabilitation and include this in the counselling even in subjects with mild and moderate hearing loss. Recent investigations demonstrated the benefit of early hearing aid use in this group of patients since this may help to reduce subsequent damages as auditory deprivation, social isolation, development of dementia, and cognitive decline. For subjects with tinnitus, hearing aids may also support masking by environmental sounds and enhance cortical inhibition.The present paper describes the latest development of hearing aid technology and the current state of the art for amplification modalities. Implications for both hearing aid indication and provision are discussed.
EVALuna2:35529

Hörgeräteversorgung – Kann die Begrenzung der Leistungspflicht der Krankenkassen durch Festbeträge bei medizinischer Indikation erfolgreich vor den Sozialgerichten angefochten werden? - Lottner, Anna; Iro, Heinrich; Schützenberger, Anne; Hoppe, Ulrich (Laryngo-Rhino-Otologie, 2019)
OBJECTIVE: When patients are provided with hearing aids, the question may arise whether they are entitled to technically advanced and therefore more expensive hearing aids in cases of medical indication, or just to hearing aids for the reference price. This work provides an overview of decisions rendered by the German social courts. We investigated whether it is advisable for a patient to go to court if the statutory health insurance has disputed a claim, and how long the proceedings may take. MATERIAL AND METHODS: We looked for decisions in the commercial legal database "juris", using the search parameters "Hörgerät" (hearing aid) and "Zuzahlung" (additional payment). The reviewed decisions were issued between 2009 and 2019. RESULTS: A total of 97 relevant decisions were found. The results varied according to the specifics of the individual case. 63 % of the patients won their cases. The court procedures took between 0.3 years and 10.4 years. CONCLUSIONS: The study shows that it is uncertain whether the costs for hearing aids that exceed the reference price will be covered or reimbursed. As each case is in principle unique, the results vary. Nevertheless, taking legal action is recommended after thorough consideration in cases where statutory health insurances or other providers refuse to meet expenses incurred despite indication.
CRIS-Team Scopus Importer:2019-10-22

Hörtherapeutische Gruppenkonzepte in der Cochleaimplantat-Rehabilitation bei Erwachsenen - Glaubitz, Cynthia; Lehmann, E. K.; Weber, Lena; Kulke, A. ‑.M.; Hoppe, Ulrich (HNO, 2019)
Background: Auditory training is an established intervention in adult cochlear implant (CI) aural rehabilitation. In most cases, training is implemented in an individual therapy setting. Increasing patient numbers and the associated time-economic and cost-related demands as well as psychosocial and communicative aspects support the use of aural group interventions. Objectives: This study aimed 1) to describe concepts and contents of group interventions for adult CI users and 2) to present results of a questionnaire-based evaluation. Methods: Group interventions have been offered at the CI Centre Erlangen CICERO for several years. In Auditory Training Groups, exercises have priority, while Thematic Group Workshops focus on psychosocial aspects and provide information for the participants. The Auditory Training Groups were evaluated based on a patient questionnaire. Additionally, the reliability of the questionnaire was analyzed. Results: The median overall satisfaction of CI users participating in Auditory Training Groups was rated as good. Training of speech perception in noise as well as communicative exchange are of great importance for CI users. They rated the therapeutic design as very good to good. Reliability analysis showed significant positive intercorrelations of the questionnaire items. Conclusion: Group interventions are well accepted by CI users and represent a useful complement to individual therapy during the rehabilitation process. As group interventions place special demands on patients and therapists, structured and well-proven concepts should be used in practice.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Auditory training; Aural therapy; Cochlear implant; Group therapy; Questionnaire evaluation

Human laryngeal mucus from the vocal folds: Rheological characterization by particle tracking microrheology and oscillatory shear rheology - Peters, Gregor; Wendler, Olaf; Böhringer, David; Gostian, Antoniu Oreste; Müller, Susanna; Canziani, Herbert; Hesse, Nicolas; Semmler, Marion; Berry, David A.; Kniesburges, Stefan; Peukert, Wolfgang; Döllinger, Michael (Applied Sciences, 2021)
Mucus consistency affects voice physiology and is connected to voice disorders. Neverthe-less, the rheological characteristics of human laryngeal mucus from the vocal folds remain unknown. Knowledge about mucus viscoelasticity enables fabrication of artificial mucus with natural properties, more realistic ex-vivo experiments and promotes a better understanding and improved treatment of dysphonia with regard to mucus consistency. We studied human laryngeal mucus samples from the vocal folds with two complementary approaches: 19 samples were successfully applied to particle tracking microrheology (PTM) and five additional samples to oscillatory shear rheology (OSR). Mucus was collected by experienced laryngologists from patients together with demographic data. The analysis of the viscoelasticity revealed diversity among the investigated mucus samples according to their rigidity (absolute G’ and G”). Moreover some samples revealed throughout solid-like character (G’ > G”), whereas some underwent a change from solid-like to liquid-like (G’ < G”). This led to a subdivision into three groups. We assume that the reason for the differences is a variation in the hydration level of the mucus, which affects the mucin concentration and network formation factors of the mucin mesh. The demographic data could not be correlated to the differences, except for the smoking behavior. Mucus of predominant liquid-like character was associated with current smokers.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Human laryngeal mucus; Oscillatory shear rheology; Particle tracking microrheology; Viscoelasticity; Vocal folds

Human lymphoid organ dendritic cell identity is predominantly dictated by ontogeny, not tissue microenvironment - Heidkamp, Gordon Frederik; Sander, Jil; Lehmann, Christian; Heger, Lukas; Eissing, Nathalie; Baranska, Anna; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Lux, Anja; Söder, Stephan; Hartmann, Arndt; et al. (Science immunology, 2016)
In mice, conventional and plasmacytoid dendritic cells (DCs) derive from separate hematopoietic precursors before they migrate to peripheral tissues. Moreover, two classes of conventional DCs (cDC1 and cDC2 DCs) and one class of plasmacytoid DCs (pDCs) have been shown to be transcriptionally and functionally distinct entities. In humans, these three DC subtypes can be identified using the cell surface markers CD1c (cDC2), CD141 (cDC1), and CD303 (pDCs), albeit it remains elusive whether DC functionality is mainly determined by ontogeny or the tissue microenvironment. By phenotypic and transcriptional profiling of these three DC subtypes in different human tissues derived from a large number of human individuals, we demonstrate that DC subpopulations in organs of the lymphohematopoietic system (spleen, thymus, and blood) are strongly defined by ontogeny rather than by signals from the microenvironment. In contrast, DC subsets derived from human lung or skin differed substantially, strongly arguing that DCs react toward modulatory signals from tissue microenvironments. Collectively, the data obtained in this study may serve as a major resource to guide further studies into human DC biology during homeostasis and inflammatio
EVALuna2:6852

Human lymphoid organ dendritic cell identity is predominantly dictated by ontogeny, not tissue microenvironment - Heidkamp, Gordon Frederik; Sander, J.; Lehmann, C. H. K.; Heger, Lukas; Eissing, N.; Baranska, A.; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Lux, Anja; Söder, Stephan; Hartmann, Arndt; et al. (2017)
EVALuna2:33137

Human Papillomavirus (HPV) Prevalence in Nasal and Antrochoanal Polyps and Association with Clinical Data - Knör, Mareike; Tziridis, Konstantin; Agaimy, Abbas; Zenk, Johannes; Wendler, Olaf (PLoS ONE, 2015)
The pathogenesis of sinonasal polyposis remains unclear, in spite of several investigative approaches. Antrochoanal polyps, a subgroup of sinonasal polyposis along with allergic- and chronic-inflammatory nasal polyps, mostly originate from the maxillary sinus and develop as a unilateral, pedunculated mass towards the nasopharynx. The human papillomavirus (HPV) is discussed as a possible causative and influencing factor in development and progression of sinonasal polyposis. This study aims to elucidate HPV frequency in nasal polyps and antrochoanal polyps.Genomic DNA from 257 tissue specimens (166 nasal polyps, 39 antrochoanal polyps and 52 nasal turbinates) was subjected to three different established HPV- polymerase chain reaction assays, testing for 37 low- and high-risk HPV. In addition, immunohistochemical analyses for HPV16 were carried out, as well as immunohistochemistry and western blots of p16, a biomarker for HPV induced cancer.HPV-DNA was detected in 53.8% of antrochoanal polyps, 15.1% of nasal polyps, and 5.8% of nasal turbinates. HPV16 was the predominant type with a detection rate of 76% in nasal polyps and 62% in antrochoanal polyps. Immunohistochemically, HPV positive tissues stained positive for HPV16 antigens and p16 in epithelial cell layers. No significant p16 overexpression was traceable in antrochoanal polyps, nasal polyps and nasal turbinates by western blot. There was no correlation of HPV-status with sex, age, smoking, alcohol consumption or allergic background.The present study shows a significant frequency of high-risk type HPV16 in antrochoanal polyps. Absence of oncogenic transformation or correlation of the HPV-status with clinical data suggests a latent superinfection, possibly because of anatomical proximity to the oropharynx.
EVALuna2:6739

Human T cells loaded with superparamagnetic iron oxide nanoparticles retain antigen-specific TCR functionality. - Pfister, Felix; Dörrie, Jan; Schaft, Niels; Buchele, Vera; Unterweger, Harald; Carnell, Lucas R.; Schreier, Patrick; Stein, René; Kubánková, Markéta; Guck, Jochen; Hackstein, Holger; Alexiou, Christoph; et al. (Frontiers in Immunology, 2023)
BACKGROUND: Immunotherapy of cancer is an emerging field with the potential to improve long-term survival. Thus far, adoptive transfer of tumor-specific T cells represents an effective treatment option for tumors of the hematological system such as lymphoma, leukemia or myeloma. However, in solid tumors, treatment efficacy is low owing to the immunosuppressive microenvironment, on-target/off-tumor toxicity, limited extravasation out of the blood vessel, or ineffective trafficking of T cells into the tumor region. Superparamagnetic iron oxide nanoparticles (SPIONs) can make cells magnetically controllable for the site-specific enrichment. METHODS: In this study, we investigated the influence of SPION-loading on primary human T cells for the magnetically targeted adoptive T cell therapy. For this, we analyzed cellular mechanics and the T cell response after stimulation via an exogenous T cell receptor (TCR) specific for the melanoma antigen MelanA or the endogenous TCR specific for the cytomegalovirus antigen pp65 and compared them to T cells that had not received SPIONs. RESULTS: SPION-loading of human T cells showed no influence on cellular mechanics, therefore retaining their ability to deform to external pressure. Additionally, SPION-loading did not impair the T cell proliferation, expression of activation markers, cytokine secretion, and tumor cell killing after antigen-specific activation mediated by the TCR. CONCLUSION: In summary, we demonstrated that SPION-loading of T cells did not affect cellular mechanics or the functionality of the endogenous or an exogenous TCR, which allows future approaches using SPIONs for the magnetically enrichment of T cells in solid tumors.
EVALuna2:539766
Keywords: Adoptive T cell therapy; superparamagnetic iron oxide nanoparticles (SPIONs); antigen-specific T cell response; targeted immune therapy; cell deformability

Hybrid aeroacoustic approach for the efficient numerical simulation of human phonation - Schoder, Stefan; Weitz, Michael; Maurerlehner, Paul; Hauser, Alexander; Falk, Sebastian; Kniesburges, Stefan; Döllinger, Michael; Kaltenbacher, Manfred (Journal of the Acoustical Society of America, 2020)
A hybrid aeroacoustic approach was developed for the efficient numerical computation of human phonation. In the first step, an incompressible flow simulation on a three-dimensional (3 D) computational grid, which is capable of resolving all relevant turbulent scales, is performed using STARCCM+ and finite volume method. In the second step, the acoustic source terms on the flow grid are computed and a conservative interpolation to the acoustic grid is performed. Finally, the perturbed convective wave equation is solved to obtain the acoustic field in 3 D with the finite element solver CFS++. Thereby, the conservative transformation of the acoustic sources from the flow grid to the acoustic grid is a key step to allow coarse acoustic grids without reducing accuracy. For this transformation, two different interpolation strategies are compared and grid convergence is assessed. Overall, 16 simulation setups are compared. The initial (267 000 degrees of freedom) and the optimized (21 265 degrees of freedom) simulation setup were validated by measurements of a synthetic larynx model. To conclude, the total computational time of the acoustic simulation is reduced by 95% compared to the initial simulation setup without a significant reduction of accuracy, being 7%, in the frequency range of interest.
CRIS-Team Scopus Importer:2020-03-10

Hydroxyapatite bone cement in the reconstruction of defects of the long process of the incus: Personal experience and literature review - Mantsopoulos, Konstantinos; Thimsen, Vivian; Wohlleben, Felix; Sievert, Matti; Mueller, Sarina K.; Goncalves, Miguel; Iro, Heinrich; Hornung, Joachim; Taha, Lava (American Journal of Otolaryngology, 2021)
Objective: Erosion of the long process of the incus is the most common ossicular chain pathology occurring in the course of chronic middle ear disease. The aim of this study was to evaluate our experience in the reconstruction of short-length defects of the long process of the incus using hydroxyapatite bone cement over a period of 15 years. Methods: The medical records of all patients treated with hydroxyapatite bone cement for an isolated short-length erosion of the long process of the incus or the lenticular process at an academic tertiary referral center between 2005 and 2019 were studied retrospectively. Results: 48 patients made up our study sample (19 men, 29 women). The mean age at the time of surgery was 38.1 years. The mean preoperative air-bone gap (ABG) was 21.36 dB. The mean postoperative ABG was 15.89 dB within 8 weeks of surgery and 11.81 dB at least 6 months after surgery. The postoperative ABG had significantly improved compared to preoperative ABG values at both the short- and middle-term follow-up (p < 0.001 for both). An ABG ≤ 20 dB was achieved in 68% in the short term and 83% in the middle term. The mean ABG in the long term (< 12 months) was 11.1 dB. Conclusion: Restoration of the anatomic and functional continuity of the ossicular chain using hydroxyapatite cement in defects of the long process of the incus seems to warrant a satisfactory audiologic outcome in the majority of cases.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Bone cement; Hydroxyapatite; Incus; Long process; Ossicular chain

Hydroxyapatite-Coated SPIONs and Their Influence on Cytokine Release - Friedrich, Bernhard; Auger, Jean-Philippe; Dutz, Silvio; Cicha, Iwona; Schreiber, Eveline; Band, Julia; Boccaccini, Aldo R.; Krönke, Gerhard; Alexiou, Christoph; Tietze, Rainer (International Journal of Molecular Sciences, 2021)
Hydroxyapatite- or calcium phosphate-coated iron oxide nanoparticles have a high potential for use in many biomedical applications. In this study, a co-precipitation method for the synthesis of hydroxyapatite-coated nanoparticles (SPIONHAp), was used. The produced nanoparticles have been characterized by dynamic light scattering, X-ray diffraction, vibrating sample magnetometry, Fourier transform infrared spectrometry, atomic emission spectroscopy, scanning electron microscopy, transmission electron microscopy, selected area diffraction, and energy-dispersive X-ray spectroscopy. The results showed a successful synthesis of 190 nm sized particles and their stable coating, resulting in SPIONHAp. Potential cytotoxic effects of SPIONHAp on EL4, THP-1, and Jurkat cells were tested, showing only a minor effect on cell viability at the highest tested concentration (400 mu g Fe/mL). The results further showed that hydroxyapatite-coated SPIONs can induce minor TNF-alpha and IL-6 release by murine macrophages at a concentration of 100 mu g Fe/mL. To investigate if and how such particles interact with other substances that modulate the immune response, SPIONHAp-treated macrophages were incubated with LPS (lipopolysaccharides) and dexamethasone. We found that cytokine release in response to these potent pro- and anti-inflammatory agents was modulated in the presence of SPIONHAp. Knowledge of this behavior is important for the management of inflammatory processes following in vivo applications of this type of SPIONs.
CRIS-Team WoS Importer:2021-05-14

Hypericin-bearing magnetic iron oxide nanoparticles for selective drug delivery in photodynamic therapy - Unterweger, Harald; Subatzus, Daniel; Tietze, Rainer; Janko, Christina; Poettler, Marina; Stiegelschmitt, Alfons; Schuster, Matthias; Maake, Caroline; Boccaccini, Aldo R.; Alexiou, Christoph (International Journal of Nanomedicine, 2015)
Combining the concept of magnetic drug targeting and photodynamic therapy is a promising approach for the treatment of cancer. A high selectivity as well as significant fewer side effects can be achieved by this method, since the therapeutic treatment only takes place in the area where accumulation of the particles by an external electromagnet and radiation by a laser system overlap. In this article, a novel hypericin-bearing drug delivery system has been developed by synthesis of superparamagnetic iron oxide nanoparticles (SPIONs) with a hypericin-linked functionalized dextran coating. For that, sterically stabilized dextran-coated SPIONs were produced by coprecipitation and crosslinking with epichlorohydrin to enhance stability. Carboxymethylation of the dextran shell provided a functionalized platform for linking hypericin via glutaraldehyde. Particle sizes obtained by dynamic light scattering were in a range of 55-85 nm, whereas investigation of single magnetite or maghemite particle diameter was performed by transmission electron microscopy and X-ray diffraction and resulted in approximately 4.5-5.0 nm. Surface chemistry of those particles was evaluated by Fourier transform infrared spectroscopy and ζ potential measurements, indicating successful functionalization and dispersal stabilization due to a mixture of steric and electrostatic repulsion. Flow cytometry revealed no toxicity of pure nanoparticles as well as hypericin without exposure to light on Jurkat T-cells, whereas the combination of hypericin, alone or loaded on particles, with light-induced cell death in a concentration and exposure time-dependent manner due to the generation of reactive oxygen species. In conclusion, the combination of SPIONs’ targeting abilities with hypericin’s phototoxic properties represents a promising approach for merging magnetic drug targeting with photodynamic therapy for the treatment of cancer.
Keywords: Hypericin; Magnetic drug targeting; Photodynamic therapy; SPION

Hypofractionated Radiotherapy Upregulates Several Immune Checkpoint Molecules in Head and Neck Squamous Cell Carcinoma Cells Independently of the HPV Status While ICOS-L Is Upregulated Only on HPV-Positive Cells - Wimmer, Sebastian; Deloch, Lisa; Hader, Michael; Derer, Anja; Grottker, Fridolin; Weissmann, Thomas; Hecht, Markus; Gostian, Antoniu-Oreste; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (International Journal of Molecular Sciences, 2021)
While the treatment of squamous cell carcinoma of the head and neck (HNSCC) with radiotherapy (RT) is complemented more and more by immunotherapy in clinical trials, little is known about the impact of the human papillomavirus (HPV) status or the applied RT scheme on the immune phenotype of the tumor cells. Therefore, we aimed to examine the impact of the HPV status of four human HNSCC cell lines on cell death and the expression of immune checkpoint molecules (ICMs) after RT with either hypofractionation irradiation (5x3.0Gy) or a high single dose (1x19.3Gy) via multicolor flow cytometry and quantitative PCR at an early time point after therapy. In our study, 5x3.0Gy RT induced high numbers of early and late apoptotic cells independent of the HPV status, but necrosis was only increased in the HPV-positive UM-Scc-47 cells. Generally, the immune stimulatory ICMs (CD70, CD137-L, ICOS-L) were less affected by RT compared to the immune suppressive ones (PD-L1, PD-L2, and the herpesvirus entry mediator (HVEM)). A significant higher surface expression of the analyzed ICMs was found after hypofractionated RT compared to a single high dose; however, regardless of the HPV status, with the exception of ICOS-L. Here, HPV-positive HNSCC tumor cells showed a stronger response to 5x3.0Gy than HPV-negative ones. On the RNA level, only minor alterations of ICMs were observed following RT, with the exception of the HPV negative cell line CAL33 treated with 5x3.0Gy, where PD-L2, HVEM and CD70 were significantly increased. We conclude that the HPV status may not distinctly predict immunological responses following RT, and thus cannot be used as a single predictive marker for therapy responses in HNSCC. In contrast, the patient-specific individual expression of ICMs following RT is preferable for the targeted patient selection for immune therapy directed against distinct ICM.
CRIS-Team WoS Importer:2021-09-17

ICAR: endoscopic skull-base surgery - Wang, Eric W.; Zanation, Adam M.; Gardner, Paul A.; Schwartz, Theodore H.; Eloy, Jean Anderson; Adappa, Nithin D.; Bettag, Martin; Bleier, Benjamin S.; Cappabianca, Paolo; Carrau, Ricardo L.; Casiano, Roy R.; Cavallo, Luigi M.; et al. (International Forum of Allergy and Rhinology, 2019)
Background Endoscopic skull-base surgery (ESBS) is employed in the management of diverse skull-base pathologies. Paralleling the increased utilization of ESBS, the literature in this field has expanded rapidly. However, the rarity of these diseases, the inherent challenges of surgical studies, and the continued learning curve in ESBS have resulted in significant variability in the quality of the literature. To consolidate and critically appraise the available literature, experts in skull-base surgery have produced the International Consensus Statement on Endoscopic Skull-Base Surgery (ICAR:ESBS). Methods Using previously described methodology, topics spanning the breadth of ESBS were identified and assigned a literature review, evidence-based review or evidence-based review with recommendations format. Subsequently, each topic was written and then reviewed by skull-base surgeons in both neurosurgery and otolaryngology. Following this iterative review process, the ICAR:ESBS document was synthesized and reviewed by all authors for consensus. Results The ICAR:ESBS document addresses the role of ESBS in primary cerebrospinal fluid (CSF) rhinorrhea, intradural tumors, benign skull-base and orbital pathology, sinonasal malignancies, and clival lesions. Additionally, specific challenges in ESBS including endoscopic reconstruction and complication management were evaluated. Conclusion A critical review of the literature in ESBS demonstrates at least the equivalency of ESBS with alternative approaches in pathologies such as CSF rhinorrhea and pituitary adenoma as well as improved reconstructive techniques in reducing CSF leaks. Evidence-based recommendations are limited in other pathologies and these significant knowledge gaps call upon the skull-base community to embrace these opportunities and collaboratively address these shortcomings.
CRIS-Team WoS Importer:2019-08-09

Identification of anatomic risk factors for scalar translocation in cochlear implant patients - Eisenhut, Felix; Lang, Stefan; Hölter, Philip; Wiesmüller, Marco; Uder, Michael; Iro, Heinrich; Dörfler, Arnd; Hornung, Joachim; Taha, Lava (Zeitschrift für Medizinische Physik, 2021)
Aim: Microanatomical evaluation of cochlear implant (CI) patients to identify anatomical risk factors for a scalar translocation. Methods: CI patients with both a regular scala tympani spiralization (group A) and a scalar translocation (group B) were identified via postoperative flat-detector computed tomography (FD-CT). Then, the corresponding preoperative multislice computed tomography (MS-CT) and postoperative FD-CT datasets were assessed: First, the cochleae were separated in 6 segments of 45° each. Next, quantitative (cochlea height, length, depth, cochlear duct diameter [CD] per segment; percentual tapering of the CD per segment named cochlear geometry index [CGI]) and qualitative (identifiability of the CI model; CI-integrity; intracochlear array position) parameters were evaluated and compared for both groups. Receiver-operating-characteristics (ROC) analysis was performed for the CGI. Results: In total, 40 preoperative MS-CT and postoperative FD-CT datasets (nA = 20; nB = 20) were analysed. Model “CI 512” was successfully identified and CI-integrity has been confirmed in all cases. Quantitative analysis showed a significant difference of both the CD at 0° (CDA 0°= 2.06 ± 0.23 mm; CDB 0°= 2.19 ± 0.18 mm; p0°= 0.04) and the CGI of the first segment (CGIA 0° -45°= 18.87 ± 6.04%; CGIB 0°-45°= 28.89 ± 8.58%; p0°-45°= 0.0001). For all other 5 cochlear segments there was no significant difference of CD and CGI; there was no significant difference of external cochlea diameters. The area under the curve (AUC) of the CGI0-45° was 0.864 with 24.50° as the optimal cut-off value to discriminate patients with a scala tympani spiralization and a scalar translocation. CGI0-45° of > 24.50° allowed the correct identification of 85% of patients with a scalar translocation. Conclusion: CI insertion trauma is associated with a significantly higher narrowing of the proximal basal cochlea turn (BCT). The CGI as percentual tapering of the BCT turned out as reliable, clinically applicable parameter for identification of patients with an increased risk for a scalar translocation.
CRIS-Team Scopus Importer:2021-03-12
Keywords: anatomical parameters; Cochlear implant; flat-detector computed tomography; insertion trauma; scalar translocation

IgA Complexes Induce Neutrophil Extracellular Trap Formation More Potently Than IgG Complexes - Gimpel, Anna-Katharina; Maccataio, Antonio; Unterweger, Harald; Sokolova, Maria; Schett, Georg; Steffen, Ulrike (Frontiers in Immunology, 2022)
Neutrophil extracellular trap (NET) formation is a powerful instrument to fight pathogens, but may induce collateral damage in the affected tissues. Besides pathogen-derived factors, immune complexes are potent inducers of NET formation. Neutrophils express IgA and IgG specific Fc receptors (FcRs) and therefore respond to complexed IgA and IgG. Especially in the context of autoimmune diseases, IgA and IgG immune complexes have been shown to trigger NET formation, a process that putatively contributes to disease severity. However, it is of question if both antibody classes stimulate neutrophils to the same extent. In this study, we compared the capability of IgA and IgG complexes formed by heat aggregation to induce NET formation. While stimulation of neutrophils with IgA complexes robustly induced NET formation, complexed IgG only marginally increased the amount of NETs compared to the unstimulated control. Mixing IgA with IgG before heat aggregation did not increase the effect of complexed IgA on neutrophils. By contrast, the presence of IgG complexes seemed to disturb neutrophil stimulation by IgA complexes. The capacity of complexed IgG to induce NET formation could not be increased by the addition of autologous serum or the removal of terminal sialic acid in the Fc glycan. Together, our data show that IgA is a much more potent inducer of NET formation than IgG. IgA may thus be the main driving force in (auto)immune complex-mediated NET formation.
CRIS-Team Scopus Importer:2022-02-11
Keywords: IgA; IgG; immune complex; NET; neutrophil

IgA subclasses have different effector functions associated with distinct glycosylation profiles - Steffen, Ulrike; Koeleman, Carolien A.; Sokolova, Maria V.; Bang, Holger; Kleyer, Arnd; Rech, Jürgen; Unterweger, Harald; Schicht, Martin; Garreis, Fabian; Hahn, Jonas; Andes, Fabian T.; Hahn, Madelaine; et al. (Nature Communications, 2020)
Monomeric serum immunoglobulin A (IgA) can contribute to the development of various autoimmune diseases, but the regulation of serum IgA effector functions is not well defined. Here, we show that the two IgA subclasses (IgA1 and IgA2) differ in their effect on immune cells due to distinct binding and signaling properties. Whereas IgA2 acts pro-inflammatory on neutrophils and macrophages, IgA1 does not have pronounced effects. Moreover, IgA1 and IgA2 have different glycosylation profiles, with IgA1 possessing more sialic acid than IgA2. Removal of sialic acid increases the pro-inflammatory capacity of IgA1, making it comparable to IgA2. Of note, disease-specific autoantibodies in patients with rheumatoid arthritis display a shift toward the pro-inflammatory IgA2 subclass, which is associated with higher disease activity. Taken together, these data demonstrate that IgA effector functions depend on subclass and glycosylation, and that disturbances in subclass balance are associated with autoimmune disease.
CRIS-Team Scopus Importer:2020-01-21

Imaging modalities using magnetic nanoparticles - overview of the developments in recent years - Schwarz, Marc; Dörfler, Arnd; Engelhorn, Tobias; Struffert, Tobias; Tietze, Rainer; Janko, Christina; Tripal, Philipp; Cicha, Iwona; Dürr, Stephan; Alexiou, Christoph; Lyer, Stefan (Nanotechnology Reviews, 2013)
The use of nanoparticles in tumor imaging, molecular imaging, and drug delivery has significantly expanded in the last few years. The relatively new field of "theranostics" combines their capacity for drug delivery with their potential as contrast agents. Depending on the imaging modality used, several types of nanoparticles are available, such as gold for optical imaging or superparamagnetic iron oxide for magnetic resonance imaging. This review will give a short overview of the different types of nanoparticles as well as their development and potential application in recent years. Furthermore, it describes the research on classic imaging modalities as well as on new techniques to image nanoparticles in vivo and focuses on magnetic-based imaging modalities.
EVALuna2:19967

Imaging of the head and neck region - Lell, Michael; Mantsopoulos, K.; Uder, Michael; Wüst, Wolfgang (HNO, 2016)
Tumors of the head and neck are predominantly squamous cell carcinomas and those of the salivary glands are predominantly adenocarcinomas, adenoid cystic carcinomas and mucoepidermoid carcinomas. In 2011 the incidence of tumors of the oral cavity and pharynx in Germany was 6839 (5026 male and 1813 female) and of the larynx 1878 (1642 male and 236 female). The incidence of tumors of the nose and paranasal sinuses (467) and salivary glands (470) were much lower (www.krebsdaten.de/abfrage). The primary aim of imaging in head and neck cancer is staging of the disease and a precise assessment of tumor invasion. This information is essential for therapy decision-making (i. e. surgery or radiochemotherapy), planning of the extent of resection and subsequent reconstructive measures and also estimation of functional deficits after therapy. Computed tomography (CT) and magnetic resonance imaging (MRI) are the imaging modalities of choice but both have specific advantages and disadvantages. In certain cases both CT and MRI need to be performed for accurate treatment planning.
EVALuna2:14585

Imaging of the head and neck region - Lell, Michael; Mantsopoulos, K.; Uder, Michael; Wüst, Wolfgang (Radiologe, 2016)
Tumors of the head and neck are predominantly squamous cell carcinomas and those of the salivary glands are predominantly adenocarcinomas, adenoid cystic carcinomas and mucoepidermoid carcinomas. In 2011 the incidence of tumors of the oral cavity and pharynx in Germany was 6839 (5026 male and 1813 female) and of the larynx 1878 (1642 male and 236 female). The incidence of tumors of the nose and paranasal sinuses (467) and salivary glands (470) were much lower ( www.krebsdaten.de/abfrage ). The primary aim of imaging in head and neck cancer is staging of the disease and a precise assessment of tumor invasion. This information is essential for therapy decision-making (i. e. surgery or radiochemotherapy), planning of the extent of resection and subsequent reconstructive measures and also estimation of functional deficits after therapy. Computed tomography (CT) and magnetic resonance imaging (MRI) are the imaging modalities of choice but both have specific advantages and disadvantages. In certain cases both CT and MRI need to be performed for accurate treatment planning.
EVALuna2:14586

Immediate effects of water resistance therapy on patients with vocal fold mass lesions - Echternach, Matthias; Raschka, Julius; Kuranova, Liudmila; Köberlein, Marie; Richter, Bernhard; Döllinger, Michael; Kainz, Marie Anne (European Archives of Oto-Rhino-Laryngology, 2020)
Introduction: Semi-occluded vocal tract exercises, such as water resistance therapy (WRT), are widely used in voice therapy. However, the potential positive effects of such a therapy on vocal fold oscillation patterns in patients indicating a need for phonomicrosurgery have not yet been explored. The presented study aims to analyze the effect of WRT in patients suffering from vocal fold mass lesions. Materials and methods: Eight participants with vocal fold mass lesions were asked to sustain a phonation on the vowel /i/ at a comfortable loudness and a fundamental frequency of 250 Hz (females) or 125 Hz (males). During phonation the subjects were simultaneously recorded with transnasal high-speed videoendoscopy (HSV, 20.000 fps), electroglottography, and audio signals. These subjects then performed a WRT (phonation in a silicone tube of 30 cm length, 5 cm below the water surface) for 10 min. Repeated measurements of sustained phonation were performed 0, 10, and 30 min after exercising. From the HSV data the glottal area waveform (GAW) was segmented and GAW parameters were computed. Results: During WRT there was an increase of the GAW related open quotient and closing quotient. Immediately after WRT, there was a drop of both values followed by a rise of these parameters up to 30 min after the intervention. Furthermore, there was no correlation between GAW and electroglottographical open quotients. Conclusions: The effects observed after a single session of WRT on participants with vocal fold mass lesions showed a similar pattern to vocal fatigue.
CRIS-Team Scopus Importer:2020-03-27
Keywords: EGG; High-speed imaging; Vocal fold mass lesion; Water resistance therapy

Immunohistochemical Evaluation of E6/E7 HPV Oncoproteins Staining in Cervical Cancer - Stiasny, Annika; Kuhn, Christina; Mayr, Doris; Alexiou, Christoph; Janko, Christina; Wiest, Irmi; Jeschke, Udo; Kost, Bernd (Anticancer Research, 2016)
High-risk human papillomavirus (HPV) subtypes (i.e. 16 and 18) lead to uterine cervical cancer as well as HPV-positive oropharyngeal cancer (OSCC), a form of head and neck cancer. The induction of HPV-induced cancer is driven by virus-specific oncoproteins E6 and E7. E6 protein of HPV types 16 and 18 interacts with the E3 ubiquitin protein ligase, resulting in ubiquitination and proteolysis of tumor protein p53. E7 inactivates retinoblastoma protein (Rb) by phosphorylation followed by an increase of free eukaryotic transcription factor E2F (E2F) in the cell. This leads to an increase of cyclin-dependent kinase inhibitor p16, that is used as an immunohistochemical marker of HPV-associated OSCC. Unfortunately, p16 is not exclusively increased by E7 oncoprotein in carcinogenesis. Therefore, the aim of this study was to develop an immunohistochemical approach for the direct detection of E6/E7 oncoproteins in uterine cervical cancer as well as in OSCC.Paraffin sections of uterine cervical cancer and 130 were analyzed. Immunohistochemical staining protocols were evaluated with tissue slides from patients with cervical dysplasia (CIN III) and squamous epithelial carcinoma tissue with HPV infection. Liver and placental tissues were used as negative controls. E6-Specific antibody (Biorbyt) was used as primary antibody. The polymer staining method and diaminobenzidine were applied for further development. Panels of E7-specific antibodies were tested. Again, the polymer staining method and diaminobenzidine were applied for further development.E6-Specific antibody revealed specific and intense staining after pre-incubation of tissue slides with citrate buffer solution. Only the E7 antibody obtained from Chemicon showed intense and specific staining in patients with CIN III and squamous epithelial carcinoma tissue. Pre-incubation with proteinase K diminished non-specific reaction.Our results revealed a useful staining protocol for the immunohistochemical evaluation of E6/E7 oncoprotein expression in uterine cervical cancer, as well as in HPV-positive oropharyngeal cancer. Advantages of this method compared to mRNA in situ hybridization of E6/E7 are the much lower costs, as well as the broader applicability in pathological practice.
EVALuna2:20013

Immunohistochemical Evaluation of the Role of p53 Mutation in Cervical Cancer: Ser-20 p53-Mutant Correlates with Better Prognosis - Freier, Christoph P.; Stiasny, Annika; Kuhn, Christina; Mayr, Doris; Alexiou, Christoph; Janko, Christina; Wiest, Irmi; Jeschke, Udo; Kost, Bernd (Anticancer Research, 2016)
Cervical cancer is driven by human papillomavirus virus-specific oncoprotein E6. E6 interacts with E3 ubiquitin-protein ligase, resulting in the proteolysis of p53 protein. The aim of this study was to analyze one TP53 mutation in patients with cervical cancer and to correlate it to prognosis.A total of 248 paraffin-embedded tumor samples were stained for mutated p53 protein. The distribution and intensity of staining both in the nucleus and cytoplasm were evaluated with a semi-quantitative immunohistochemical score.A total of 66% of studied cervical carcinomas expressed the mutated p53 protein. The overall survival was better for patients expressing the mutated p53 protein in the nucleus.Interestingly, we found a very high mutation rate of TP53 in a cancer type where p53 is initially inactivated via E6 during the development of cervical cancer. An unexpected finding is the correlation of this mutation with better survival, possibly due to better response to therapy.
EVALuna2:20011

IMP3 and p16 expression in squamous cell carcinoma of the head and neck: A comparative immunohistochemical analysis - Riener, Marc-Oliver; Hoegel, Josef; Iro, Heinrich; Hartmann, Arndt; Agaimy, Abbas (Oncology Letters, 2017)
Expression of p16 has been established as a good surrogate marker for high-risk human papillomavirus (HPV) infection in oropharyngeal squamous cell carcinoma (OPSCC) patients, and it has been associated with an improved prognosis, irrespective of the actual HPV status. Conversely, the human insulin-like growth factor II mRNA binding protein 3 (IMP3) has been related to aggressiveness in several types of tumors. The aim of the present study was to investigate and compare p16 and IMP3 as markers of favorable and unfavorable behavior, respectively, in head and neck SCC (HNSCC), with particular reference to the HPV status. Both markers were analyzed by immunohistochemical analysis of 156 HNSCC samples originating from the oropharynx (n=81), oral cavity (n=44), larynx (n=15), hypopharynx (n=10) and nasopharynx (n=6). The HPV status was examined in a randomly selected representative subcohort (n=38) using polymerase chain reaction. Of the 156 HNSCC samples, 81 (51.9%) and 54 (34.6%) were positive for IMP3 and p16, respectively. IMP3 expression (P=0.022), p16 expression (P<0.001) and the combination of these markers (P<0.001) were significantly associated with tumor site. In particular, 69/81 (85%) OPSCC samples were positive for either one or both markers compared with 36/75 (48%) SCC samples from other sites. p16 expression was significantly associated with HPV infection (P=0.017) and a trend towards a negative association between IMP3 expression and HPV infection was observed (P=0.053). The results of the present study suggested that IMP3 and p16 are more frequently expressed in OPSCC compared with other HNSCCs. The prognostic impact of IMP3 on OPSCC remains to be investigated in a larger series with an extended follow-up period.
EVALuna2:6894

Impact of Citrate-stabilized superparamagnetic Iron Oxide-Nanoparticles on Head and Neck Tumor Cell Lines in Combination Therapy with ionizing Radiation - Schreiber, C.; Franzen, T.; Fietkau, Rainer; Tietze, Rainer; Stein, René; Friedrich, Bernhard; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Impact of CI use and CI fitting on speech production in very early cochlear-implanted infants Bedeutung von CI-Nutzungsverhalten und CI-Anpassung für sprachproduktive Leistungen sehr früh cochleaimplantierter Kinder - Glaubitz, Cynthia; Liebscher, Tim; Hoppe, Ulrich (HNO, 2020)
Background: Children’s age at implantation is an important factor for their outcome in auditory and language skills with a cochlear implant (CI). CI use and frequency of CI fitting may also influence speech performance. Purpose of this study was to evaluate CI use and CI fitting of very early implanted infants and its potential influence on age-related speech production performance. Methods: Data of 34 bilaterally cochlea-implanted infants (age at CI in months: M = 8,8; SD = 1,7) were included. During the third year of life speech production performance was evaluated and related to datalogging-based CI use and number of CI fitting sessions. Results: About half of the cohort achieved speech production level within the normal range of hearing peers. Daily time of CI use was approximately 8 h. Analysis of listening environment showed that infants were exposed most of the time to quiet environment and least amount of time to speech in noise. Daily time of CI use seems to be a significant predictor of speech production, speech-exposition particularly predicts word production. Number of daily disconnection between CI-processor and implant as well as the monthly number of CI fitting sessions were not correlated with speech production. Conclusion: Very early cochlear implanted infants may achieve age-appropriate speech production performance in the third year of life. Time of daily CI use in the study cohort is comparable to results of other studies. Time of daily CI use and exposure to speech seem to be important factors for early speech production. These findings should be integrated in pre- and postoperative parent counselling.
CRIS-Team Scopus Importer:2020-09-25
Keywords: CI use; Cochlear implant; Data logging; Language development; Speech production

Impact of delayed adjuvant therapy after surgery in p16 positive oropharyngeal cancer: a retrospective analysis - Sievert, Matti; Goncalves, Miguel; Mueller, Sarina K.; Hecht, M.; Pflaum, A.; Grundtner, P.; Iro, H.; Gostian, A. O.; Iro, Heinrich (European Review for Medical and Pharmacological Sciences, 2020)
OBJECTIVE: This study aimed to clarify the impact of delayed adjuvant therapy on the outcome of HPV associated oropharyngeal squamous cell carcinoma (HPV-OPSCC). PATIENTS AND METHODS: A total of 157 patients with HPV-OPSCC treated by surgery and adjuvant radiotherapy or chemoradiation therapy were analyzed retrospectively. We divided participants into two groups implementing adjuvant therapy within or after 50 days. Primary endpoints were the rates of locoregional recurrence and distant metastases, overall survival, and disease-specific survival. RESULTS: Adjuvant treatment began within 50 days (average: 38.8 days) in 79 cases compared to 78 cases after 50 days (average: 71.5 days). Five-year overall survival was 85.7% and 87.4% (p=0.588), the rates of local and regional recurrence were 3.8% and 6.4% (p=0.455) and of distant metastases 5.1% and 9% (p=0.369) implementing adjuvant treatment within or later than 50 days, respectively. CONCLUSIONS: These results suggest that adjuvant therapy initiated later than seven weeks after primary ablative surgery may still be effective HPV-OPSCC.
CRIS-Team Scopus Importer:2020-03-06

Impact of functional mass lesions in professional female singers : Biomechanics of vocal fold oscillation in the register transition regions - Echternach, M.; Burk, F.; Rose, F.; Herbst, C. T.; Burdumy, M.; Döllinger, Michael; Richter, B. (HNO, 2017)
BACKGROUND: The influence of functional mass lesions on vocal fold oscillation patterns in vocally challenging tasks is not yet understood in detail. MATERIALS UND METHODS: Glissandi on the vowel [a:] from 220 to 440 Hz and 440 to 880 Hz were analyzed in three groups of four professional female singers: without a mass lesion or dysphony (group A), with a functional mass lesion (swellings without a great impact on oscillation patterns during stroboscopy; group B), and with organic dysphony (group C). High-speed digital imaging (HSDI; 20,000 fps), and acoustic and electroglottographic (EGG) signals were used for analysis. Based on the EGG sample entropy, time windows for analysis of register transition phenomena were constructed. The voice signals (glottal area waveform, GAW; acoustic and EGG signals) were perceptually rated in terms of the noticeability of registration events. RESULTS: The absolute sample entropy revealed maxima in fundamental frequency regions where register transitions typically occur. Groups A and B could be distinguished neither by perceptual rating nor based on sample entropy values. In comparison to the other two groups, the absolute sample entropy values of group C were greater in the lower glissando. However, the larger vocal fold oscillatory irregularities were observable for the upper glissando in this group. CONCLUSION: Functional mass lesions do not influence biomechanics adversely in vocally challenging tasks such as register transitions. The use of sample entropy as a criterion for detection of register transitions is promising, but needs further validation.
EVALuna2:33367

Impact of intraepithelial capillary loops and atypical vessels in confocal laser endomicroscopy for the diagnosis of laryngeal and hypopharyngeal squamous cell carcinoma - Sievert, Matti; Eckstein, Markus; Mantsopoulos, Konstantinos; Mueller, Sarina K.; Stelzle, Florian; Aubreville, Marc; Oetter, Nicolai; Maier, Andreas; Iro, Heinrich; Goncalves, Miguel (European Archives of Oto-Rhino-Laryngology, 2021)
Purpose Confocal laser endomicroscopy (CLE) allows surface imaging of the laryngeal and pharyngeal mucosa in vivo at a thousand-fold magnification. This study aims to compare irregular blood vessels and intraepithelial capillary loops in healthy mucosa and squamous cell carcinoma (SCC) via CLE.
CRIS-Team WoS Importer:2021-07-23

Impact of postoperative radiotherapy and HER2/new overexpression in salivary duct carcinoma : A monocentric clinicopathologic analysis - Haderlein, Marlen; Scherl, Claudia; Semrau, Sabine; Lettmaier, Sebastian; Hecht, Markus; Erber, Ramona; Iro, Heinrich; Agaimy, Abbas; Fietkau, Rainer (Strahlentherapie und Onkologie, 2017)
Retrospective Investigation of the prognostic relevance of clinicopathologic parameters in patients with salivary duct carcinoma (SDC).An experienced pathologist reviewed 67 patients with de novo SDC or SDC ex pleomorphic adenoma. Paraffin-embedded tumor samples were examined by immunohistochemistry for expression of HER2/neu, androgen (AR), progesterone (PR), estrogen (ER), epidermal growth factor (EGFR) and programmed death ligand 1 (PD-L1-R) receptor. In 45 patients who had cM0 and follow-up data available, survival rates were calculated (Kaplan-Meier method) and prognostic variables were analyzed (univariate analysis: log-rank test; multivariate analysis: Cox-regression analysis).Overexpression of HER2/neu, AR, ER, PR, EGFR, PD-L1-R was found in 25.4%, 84%, 0%, 0%, 17.9%, 16.4% of patients. Overall (OS), disease-free (DFS), distant-metastases-free survival (DMFS) and locoregional control (LRC) were 92.3/72.4/56.9%, 78.2/58.1/58.1%, 85.4/65.2/65.2% and 89.7/81.9/81.9% after 1/3/5 years (medial follow-up 26 months). In univariate analysis a positive resection margin (p = 0.008) and no postoperative radiotherapy (p = 0.001) predict an increased locoregional recurrence rate. In multivariate analysis only postoperative radiotherapy is statistically significant (p = 0.004). Presence of lymph node metastases, a lymph node density >4 and HER2/neu overexpression predict decreased DFS and DMFS. In multivariate HER2/neu overexpression was the only significant predictor for reduced DFS (p = 0.04) and DMFS (p = 0.02).Postoperative radiotherapy is the only significant predictor for LRC. HER2/neu receptor expression is an independent prognostic factor for decreased DFS and DMFS in patients with SDC. In addition to radio(chemo)therapy, intensified first-line treatment regimens should also be evaluated in the future.
EVALuna2:6895

Impact of subharmonic and aperiodic laryngeal dynamics on the phonatory process analyzed in ex vivo rabbit models - Thornton, Fabian; Döllinger, Michael; Kniesburges, Stefan; Berry, David; Alexiou, Christoph; Schützenberger, Anne (Applied Sciences, 2019)
Normal voice is characterized by periodic oscillations of the vocal folds. On the other hand, disordered voice dynamics (e.g., subharmonic and aperiodic oscillations) are often associated with voice pathologies and dysphonia. Unfortunately, not all investigations may be conducted on human subjects; hence animal laryngeal studies have been performed for many years to better understand human phonation. The rabbit larynx has been shown to be a potential model of the human larynx. Despite this fact, only a few studies regarding the phonatory parameters of rabbit larynges have been performed. Further, to the best of our knowledge, no ex vivo study has systematically investigated phonatory parameters from high-speed, audio and subglottal pressure data with irregular oscillations. To remedy this, the present study analyzes experiments with sustained phonation in 11 ex vivo rabbit larynges for 51 conditions of disordered vocal fold dynamics. (1) The results of this study support previous findings on non-disordered data, that the stronger the glottal closure insufficiency is during phonation, the worse the phonatory characteristics are; (2) aperiodic oscillations showed worse phonatory results than subharmonic oscillations; (3) in the presence of both types of irregular vibrations, the voice quality (i.e., cepstral peak prominence) of the audio and subglottal signal greatly deteriorated compared to normal/periodic vibrations. In summary, our results suggest that the presence of both types of irregular vibration have a major impact on voice quality and should be considered along with glottal closure measures in medical diagnosis and treatment.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Aperiodic dynamics; Ex vivo phonation; High-speed digital imaging; Rabbit model; Subharmonic dynamics

Impact of Superparamagnetic Iron Oxide Nanoparticles on Vocal Fold Fibroblasts: Cell Behavior and Cellular Iron Kinetics - Poettler, Marina; Fliedner, Anna; Schreiber, Eveline; Janko, Christina; Friedrich, Ralf P.; Bohr, Christopher; Döllinger, Michael; Alexiou, Christoph; Dürr, Stephan (Nanoscale Research Letters, 2017)
PURPOSE: The voice is the most important instrument of communication. Tissue defects in the vocal fold (VF) area lead to serious reduction in quality of life, but thus far, no satisfactory VF implant exists. Therefore, we aim to establish a functional VF implant in a rabbit model by magnetic tissue engineering (MTE) using superparamagnetic iron oxide nanoparticles (SPION). Hence, iron quantification over time as well as cell behavior studies upon SPION treatment are of great importance. METHODS: Rabbit VF fibroblasts (VFF) were treated with different concentrations of SPIONs (20, 40, and 80 μg/cm2), and iron content was examined for up to 40 days using microwave plasma-atom emission spectroscopy. The effects of SPION treatment on VFF (adhesion, spreading, and migration), which are important for the formation of 3D structures, were tested. RESULTS: Cellular SPION quantification revealed that there was no residual iron remaining in VFFs after 40 days. SPIONs had a dose-dependent effect on cell adhesion, with good tolerability observed up to 20 μg/cm2. Migration and spreading were not significantly influenced by SPION treatment up to 80 μg/cm2. DISCUSSION AND CONCLUSION: To develop 3D structures, cell behavior should not be affected by SPION uptake. After 40 days, cells were free of iron as a result of metabolism or rarefication during cell division. Cell functions including adhesion, spreading, and migration were proven to be intact in a dose-dependent manner after SPION treatment, suggesting a safe usage of MTE for voice rehabilitation. Our results thus constitute a solid basis for a successful transfer of this technique into 3D constructs, in order to provide an individual and personalized human VF implant in the future.
EVALuna2:33203

Implementation of double immune checkpoint blockade increases response rate to induction chemotherapy in head and neck cancer - Semrau, Sabine; Gostian, Antoniu Oreste; Traxdorf, Maximilian; Eckstein, Markus; Rutzner, Sandra; von der Grün, Jens; Illmer, Thomas; Hautmann, Matthias; Klautke, Gunther; Laban, Simon; Brunner, Thomas; Tamaskovics, Bálint; et al. (Cancers, 2021)
To determine whether a single dose of double immune checkpoint blockade (induction chemoimmunotherapy (ICIT)) adds benefit to induction single-cycle platinum doublet (induction chemotherapy (IC)) in locally advanced head and neck squamous cell carcinoma (HNSCC), patients treated with cisplatin 30 mg/m2 d1-3 and docetaxel 75 mg/m2 d1 combined with durvalumab 1500 mg fixed dose d5 and tremelimumab 75 mg fixed dose d5 (ICIT) within the CheckRad-CD8 trial were compared with a retrospective cohort receiving the same chemotherapy (IC) without immunotherapy. The endpoint of this analysis was the complete response rate (CR). A total of 53 patients were treated with ICIT and 104 patients with IC only. CR rates were 60.3% for ICIT and 40.3% for IC (p = 0.018). In the total population (n = 157), the most important predictor to achieve a CR was treatment type (OR: 2.21 for ICIT vs. IC; p = 0.038, multivariate analysis). The most diverse effects in CR rates between ICIT and IC were observed in younger (age ≤ 60) patients with HPV-positive OPSCCs (82% vs. 33%, p = 0.176), while there was no difference in older patients without HPV-positive OPSCCs (53% vs. 48%). The analysis provides initial evidence that ICIT could result in higher CR rates than IC. Young patients with HPV-positive OPSCCs may have the greatest benefit from additional immune checkpoint inhibitors.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Combined modality therapy; Double immune checkpoint inhibition; Head and neck neoplasms; HPV-positive OPSCC; Immunotherapy; Induction therapy; Organ preservation

Implementation of Study Results in Guidelines and Adherence to Guidelines in Clinical Practice - Waldfahrer, F. (Laryngo-Rhino-Otologie, 2016)
Guidelines were introduced in hospital and practice-based otorhinolaryngology in the 1990s, and have been undergoing further development ever since. There are currently 20 guidelines on file at the German Society of Oto-Rhino-Laryngology, Head and Neck Surgery. The Society has cooperated in a further 34 guidelines. The quality of the guidelines has been continually improved by concrete specifications put forward by the Association of the Scientific Medical Societies in Germany [Arbeitsgemeinschaft der Wissenschaftlichen Medizinischen Fachgesellschaften e.V.]. Since increasing digitalisation has made access to scientific publications quicker and more simple, relevant study results can be incorporated in guidelines more easily today than in the analogue world. S2e and S3 guidelines must be based on a formal literature search with subsequent evaluation of the evidence. The consensus procedure for S2k guidelines is also regulated. However, the implementation of guidelines in routine medical practice must still be considered inadequate, and there is still a considerable need for improvement in adherence to these guidelines.
EVALuna2:20020

Improved Postoperative Facial Nerve and Hearing Function in Retrosigmoid Vestibular Schwannoma Surgery Significantly Associated with Semisitting Position - Roessler, Karl; Krawagna, Maximilian; Bischoff, Barbara; Rampp, Stefan; Ganslandt, Oliver Thomas; Iro, Heinrich; Schmitt, Hubert; Buchfelder, Michael (World Neurosurgery, 2016)
The pros and cons of semisitting positioning (SSP) versus lateral, horizontal positioning (LP) during retrosigmoid vestibular schwannoma (VS) surgery, especially concerning postoperative cranial nerve and brain stem preservation, are under continuous discussion.In a single-center retrospective cohort study, 30 VSs operated on in SSP compared with 30 operated on in LP with comparable demography were analyzed. During SSP surgery, transesophageal echocardiographic monitoring for venous air embolism was used continuously. Electrophysiologic cranial nerve monitoring was used in both groups.Length of surgery was significantly different between both groups: 183 minutes mean in SSP surgery versus 365 minutes mean in LP surgery (P = 0.0001). Postoperative rates of facial palsy and hearing loss were also significantly different. Six months postoperatively, 63% had normal facial nerve function after SSP surgery, whereas in LP surgery, 40% had no facial palsy (P = 0.02). Hearing preservation rate was also significantly different: 44% in SSP surgery compared with 14% in LP surgery who had preserved hearing (P = 0.006). Because of cerebrospinal fluid leaks, there were 3 operative revisions in the LP group (10%) and 1 (3.3%) in the SSP group. A clinically insignificant venous air embolism rate was found in 3.3% of patients (1/30) during SSP surgery. The neurologic outcome after 6 months was 1.2 on the Rankin Scale in the LP group and 1.0 in the SSP group, with zero mortality.SSP compared with LP surgery was associated with significantly shorter operation time and better facial and cochlear nerve function in VS surgery postoperatively, without differences in complication rate
EVALuna2:16715

Improvement in Phoneme Discrimination in Noise in Normal Hearing Adults - Schumann, A.; Garea Garcia, Larissa; Hoppe, Ulrich (Laryngo-Rhino-Otologie, 2017)
Objective: The study's aim was to examine the possibility to train phoneme-discrimination in noise with normal hearing adults, and its effectivity on speech recognition in noise. A specific computerised training program was used, consisting of special nonsense-syllables with background noise, to train participants' discrimination ability.Material and Methods:46 normal hearing subjects took part in this study, 28 as training group participants, 18 as control group participants. Only the training group subjects were asked to train over a period of 3 weeks, twice a week for an hour with a computer-based training program. Speech recognition in noise were measured pre- to posttraining for the training group subjects with the Freiburger Einsilber Test. The control group subjects obtained test and restest measures within a 2-3 week break. For the training group follow-up speech recognition was measured 2-3 months after the end of the training.Results:The majority of training group subjects improved their phoneme discrimination significantly. Besides, their speech recognition in noise improved significantly during the training compared to the control group, and remained stable for a period of time.Conclusions:Phonem-Discrimination in noise can be trained by normal hearing adults. The improvements have got a positiv effect on speech recognition in noise, also for a longer period of time.
EVALuna2:33210

Improving cancer imaging with magnetic nanoparticles: where are we now? - Tietze, Rainer; Alexiou, Christoph (Nanomedicine, 2017)
EVALuna2:33217

Impulse dispersion of aerosols during playing the recorder and evaluation of safety measures - Köberlein, Marie; Hermann, Laila; Gantner, Sophia; Tur, Bogac; Peters, Gregor; Westphalen, Caroline; Benthaus, Tobias; Döllinger, Michael; Kniesburges, Stefan; Echternach, Matthias (PLoS ONE, 2022)
INTRODUCTION: Group musical activities using wind instruments have been restricted during the CoVID19 pandemic due to suspected higher risk of virus transmission. It was presumed that the aerosols exhaled through the tubes while playing would be ejected over larger distances and spread into the room due to jet stream effects. In particular, the soprano recorder is widely used as an instrument in school classes, for beginners of all age groups in their musical education, in the context of leisure activities and in professional concert performances. Understanding the aerosol impulse dispersion characteristics of playing the soprano recorder could assist with the establishment of concepts for safe music-making. METHODS: Five adult professionally trained soprano recorder players (4 female, 1 male) played four bars of the main theme of L. van Beethoven's "Ode to Joy" in low and in high octaves, as well as with 3 different potential protection devices in the high octave. For comparison they spoke the corresponding text by F. Schiller. Before each task, they inhaled .5 L of vapor from an e-cigarette filled with base liquid. The vapor cloud escaping during speaking or playing was recorded by cameras and its spread was measured as a function of time in the three spatial dimensions. The potential safety devices were rated for practicability with a questionnaire, and their influence on the sound was compared, generating a long-term average spectrum from the audio data. RESULTS: When playing in the high octave, at the end of the task the clouds showed a median distance of 1.06 m to the front and .57 m diameter laterally (maxima: x: 1.35 m and y: .97 m). It was found that the clouds' expansion values in playing the recorder with and without safety measures are mostly lower when compared to the ordinary, raised speaking voice of the same subjects. The safety devices which covered the instrument did not show clear advantages and were rated as unpractical by the subjects. The most effective reduction of the cloud was reached when playing into a suction funnel. CONCLUSION: The aerosol dispersion characteristics of soprano recorders seem comparable to clarinets. The tested safety devices which covered holes of the instrument did not show clear benefits.
CRIS-Team Scopus Importer:2022-10-07

Impulse dispersion of aerosols during playing wind instruments - Gantner, Sophia; Echternach, Matthias; Veltrup, Reinhard; Westphalen, Caroline; Köberlein, Marie Christine; Kuranova, Liudmila; Peters, Gregor; Jakubaß, Bernhard; Benthaus, Tobias; Döllinger, Michael; Kniesburges, Stefan (PLoS ONE, 2022)
Musical activities, especially singing and playing wind instruments, have been singled out as potentially high-risk activities for the transmission of SARS CoV-2, due to a higher rate of aerosol production and emission. Playing wind instruments can produce condensation, droplets of saliva, and aerosol particles, which hover and spread in the environmental air's convectional flows and which can be potentially infectious. The aim of this study is to investigate the primary impulse dispersion of aerosols that takes place during the playing of different wind instruments as compared to breathing and to speaking. Nine professional musicians (3 trumpeters, 3 flautists and 3 clarinetists) from the Bavarian Symphony Orchestra performed the main theme from the 4th movement of Ludwig van Beethoven's 9th symphony in different pitches and loudness. The inhaled air volume was marked with small aerosol particles produced using a commercial e-cigarette. The expelled aerosol cloud was recorded by cameras from different perspectives. Afterwards, the dimensions and dynamics of the aerosol cloud were measured by segmenting the video footage at every time point. Overall, the flutes produced the largest dispersion at the end of the task, reaching maximum forward distances of 1.88 m. An expulsion of aerosol was observed in different directions: Upwards and downwards at the mouthpiece, at the end of the instrument, and along the flute at the key plane. In comparison, the maximum impulse dispersions generated by the trumpets and clarinets were lower in frontal and lateral direction (1.2 m and 1.0 m towards the front, respectively). Also, the expulsion to the sides was lower.
CRIS-Team Scopus Importer:2022-03-11

Impulse Dispersion of Aerosols during Singing and Speaking: A Potential COVID-19 Transmission Pathway - Echternach, Matthias; Gantner, Sophia; Peters, Gregor; Westphalen, Caroline; Benthaus, Tobias; Jakubaß, Bernhard; Kuranova, Liudmila; Döllinger, Michael; Kniesburges, Stefan (American Journal of Respiratory and Critical Care Medicine, 2020)
CRIS-Team Scopus Importer:2020-12-11

Increasing the Channel Capacity: Parallel Data Transmission in a Testbed for Molecular Communication - Bartunik, Max; Streb, Matthias; Unterweger, Harald; Haller, Jakob; Kirchner, Jens (NANOCOM '21: Proceedings of the Eight Annual ACM International Conference on Nanoscale Computing and Communication, 2021)
In the field of molecular communication, molecules or other parti-cles in the nanoscale are used to transmit information. This rather new communication paradigm has a large application potential,ranging from medicine to industrial systems. As testbeds are essential for evaluating the capabilities of this new form of communication, we improve an existing water-based testbed to achieve parallel data transmission within one communication channel in this work. To this end, two different information carriers, superparamagnetic iron oxide nanoparticles and fluorescent particles, are used to simultaneously transmit independent data streams. A detection system for fluorescent particles was specifically developed for the fluid molecular communication testbed. Using parallel data transmission in the modified testbed the channel capacity was nearly doubled in comparison to a transmission using only a single type of information particle
CRIS-Team Scopus Importer:2021-10-08
Keywords: molecular communication; fluorescence detection; nanoparticles; spions

Induction chemoimmunotherapy followed by CD8+ immune cell-based patient selection for chemotherapy-free radioimmunotherapy in locally advanced head and neck cancer - Hecht, Markus; Eckstein, Markus; Rutzner, Sandra; Von Der Grun, Jens; Illmer, Thomas; Klautke, Gunther; Laban, Simon; Hautmann, Matthias G.; Brunner, Thomas B.; Tamaskovics, Balint; Hinke, Axel; Zhou, Jianguo; et al. (Journal for ImmunoTherapy of Cancer, 2022)
Purpose The first aim of the trial is to study feasibility of combined programmed death protein ligand 1/cytotoxic T-lymphocyte-associated protein 4 inhibition concomitant to radiotherapy. In addition, efficacy of the entire treatment scheme consisting of induction chemoimmunotherapy followed by chemotherapy-free radioimmunotherapy (RIT) after intratumoral CD8 +immune cell-based patient selection will be analyzed. Methods Patients with stage III-IVB head and neck squamous cell carcinoma were eligible for this multicenter phase II trial. Treatment consisted of a single cycle of cisplatin 30 mg/m² days 1-3, docetaxel 75 mg/m² day 1, durvalumab 1500 mg fix dose day 5 and tremelimumab 75 mg fix dose day 5. Patients with increased intratumoral CD8 +immune cell density or pathological complete response (pCR) in the rebiopsy entered RIT up to a total dose of 70 Gy. Patients received further three cycles of durvalumab/tremelimumab followed by eight cycles of durvalumab mono (every 4 weeks). The intended treatment for patients not meeting these criteria was standard radiochemotherapy outside the trial. Primary endpoint was a feasibility rate of patients entering RIT to receive treatment until at least cycle 6 of immunotherapy of ≥80%. Results Between September 2018 and May 2020, 80 patients were enrolled (one excluded). Out of these, 23 patients had human papilloma virus (HPV)-positive oropharyngeal cancer. Median follow-up was 17.2 months. After induction chemoimmunotherapy 41 patients had pCR and 31 had increased intratumoral CD8 +immune cells. Of 60 patients entering RIT (primary endpoint cohort), 10 experienced imiting toxic (mainly hepatitis) and four discontinued for other reasons, resulting in a feasibility rate of 82%. The RIT cohort (n=60) had a progression-free survival (PFS) rate at one and 2 years of 78% and 72%, respectively, and an overall survival rate at one and 2 years of 90% and 84%, respectively. Patients with HPV-positive oropharyngeal cancers had greater benefit from RIT with a 2-year PFS rate of 94% compared with 64% for HPV-negative oropharyngeal cancers and other locations. In the entire study cohort (n=79) the 2-year PFS rate was 68% (91% for HPV-positive oropharynx vs 59% for others). Toxicity grade 3-4 mainly consisted of dysphagia (53%), leukopenia (52%) and infections (32%). Conclusions The trial met the primary endpoint feasibility of RIT. Induction chemo-immunotherapy followed by chemotherapy-free RIT after intratumoral CD8 +immune cell-based patient selection has promising PFS. Trial registration number The trial was registered with ClinicalTrials.gov (identifier: NCT03426657). The trial was conducted as investigator-sponsored trial (IST).
CRIS-Team Scopus Importer:2022-02-11
Keywords: radioimmunotherapy

Induction of immunogenic cell death by chemotherapeutics-loaded nanoparticles for targeted tumor therapy - Janko, Christina; Alev, Magdalena; Mühleisen, Laura; Weigel, B.; Zaloga, Jan; Alexiou, Christoph (2017)
EVALuna2:35460

Inefficient clearance of dying cells in patients with SLE: Anti-dsDNA autoantibodies, MFG-E8, HMGB-1 and other players - Kruse, Kristin; Janko, Christina; Urbonaviciute, Vilma; Mierke, Claudia T.; Winkler, Thomas; Voll, Reinhard E.; Schett, Georg; Munoz, Luis E.; Herrmann, Martin (Apoptosis, 2010)
Systemic lupus erythematosus (SLE) is a complex disease resulting from inflammatory responses of the immune system against several autoantigens. Inflammation is conditioned by the continuous presence of autoantibodies and leaked autoantigens, e.g. from not properly cleared dying and dead cells. Various soluble molecules and biophysical properties of the surface of apoptotic cells play significant roles in the appropriate recognition and further processing of dying and dead cells. We exemplarily discuss how Milk fat globule epidermal growth factor 8 (MFG-E8), biophysical membrane alterations, High mobility group box 1 (HMGB1), C-reactive protein (CRP), and anti-nuclear autoantibodies may contribute to the etiopathogenesis of the disease. Up to date knowledge about these key elements may provide new insights that lead to the development of new treatment strategies of the disease. © 2010 Springer Science+Business Media, LLC.
Keywords: ANA; Biophysical features; Clearance; CRP; HMGB-1; MFG-E8; Phosphatidylserine; Plasma membrane

Inert Coats of Magnetic Nanoparticles Prevent Formation of Occlusive Intravascular Co-aggregates With Neutrophil Extracellular Traps - Bilyy, Rostyslav; Unterweger, Harald; Weigel, Bianca; Dumych, Tetiana; Paryzhak, Solomiya; Vovk, Volodymyr; Liao, Ziyu; Alexiou, Christoph; Herrmann, Martin; Janko, Christina (Frontiers in Immunology, 2018)
If foreign particles enter the human body, the immune system offers several mechanisms of response. Neutrophils forming the first line of the immune defense either remove pathogens by phagocytosis, inactivate them by degranulation or release of reactive oxygen species or immobilize them by the release of chromatin decorated with the granular proteins from cytoplasm as neutrophil extracellular traps (NETs). Besides viable microbes like fungi, bacteria or viruses, also several sterile inorganic particles including nanoparticles reportedly activate NET formation. The physicochemical nanoparticle characteristics fostering NET formation are still elusive. Here we show that agglomerations of non-stabilized superparamagnetic iron oxide nanoparticles (SPIONs) induce NET formation by isolated human neutrophils, in whole blood experiments under static and dynamic conditions as well as in vivo. Stabilization of nanoparticles with biocompatible layers of either human serum albumin or dextran reduced agglomeration and NET formation by neutrophils. Importantly, this passivation of the SPIONs prevented vascular occlusions in vivo even when magnetically accumulated. We conclude that higher order structures formed during nanoparticle agglomeration primarily trigger NET formation and the formation of SPION-aggregated NET-co-aggregates, whereas colloid-disperse nanoparticles behave inert and are alternatively cleared by phagocytosis.
EVALuna2:35450

Inference of the Selective Auditory Attention using Sequential LMMSE Estimation - Kuruvila, Ivine; Demir, Kubilay; Fischer, Eghart; Hoppe, Ulrich (IEEE transactions on bio-medical engineering, 2021)
Attentive listening in a multispeaker environment such as a cocktail party requires suppression of the interfering speakers and the noise around. People with normal hearing perform remarkably well in such situations. Analysis of the cortical signals using electroencephalography (EEG) has revealed that the EEG signals track the envelope of the attended speech stronger than that of the interfering speech. This has enabled the development of algorithms that can decode the selective attention of a listener in controlled experimental settings. However, often these algorithms require longer trial duration and computationally expensive calibration to obtain a reliable inference of attention. In this paper, we present a novel framework to decode the attention of a listener within trial durations of the order of two seconds. It comprises of three modules: 1) Dynamic estimation of the temporal response functions (TRF) in every trial using a sequential linear minimum mean squared error (LMMSE) estimator, 2) Extract the N1-P2 peak of the estimated TRF that serves as a marker related to the attentional state and 3) Obtain a probabilistic measure of the attentional state using a support vector machine followed by a logistic regression. The efficacy of the proposed decoding framework was evaluated using EEG data collected from 27 subjects. The total number of electrodes required to infer the attention was four: One for the signal estimation, one for the noise estimation and the other two being the reference and the ground electrodes. Our results make further progress towards the realization of neuro-steered hearing aids.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Auditory system; Brain modeling; Decoding; Electrodes; Electroencephalography; Estimation; Signal resolution

Inflamed benign tumors of the parotid gland: Diagnostic pitfalls from a potentially misleading entity - Mantsopoulos, Konstantinos; Psychogios, Georgios; Agaimy, Abbas; Künzel, Julian; Zenk, Johannes; Iro, Heinrich; Bohr, Christopher (Head and Neck-Journal For the Sciences and Specialties of the Head and Neck, 2015)
The purpose of this study was to evaluate our experience in the diagnostic approach to inflamed benign tumors of the parotid gland at a single tertiary center.A retrospective evaluation was carried out for all patients with signs of inflammation in the parotid gland on the ground of a benign parotid tumor, as confirmed by permanent histology.Sixteen patients were detected for our study. Histopathologic examination confirmed cystadenolymphoma in 11 cases (with metaplastic changes in 2 cases), 2 pleomorphic adenomas, 2 monomorphic adenomas, and 1 oncocytic cystadenoma. Diverse clinical signs (inflammation signs, facial palsy), ultrasound and MRI findings (poorly defined lesion margins), and the presence of squamous metaplastic changes on cytology often raised the suspicion of parotid malignancy or abscess.In most cases, a high suspicion index combined with close monitoring of the patient may allow prompt and successful diagnosis and therapy. © 2014 Wiley Periodicals, Inc. Head Neck 37: 23-29, 2015.
EVALuna2:6639

Influence of Analyzed Sequence Length on Parameters in Laryngeal High-Speed Videoendoscopy - Schlegel, Patrick; Semmler, Marion; Kunduk, Melda; Döllinger, Michael; Bohr, Christopher; Schützenberger, Anne (Applied Sciences, 2018)
Laryngeal high-speed videoendoscopy (HSV) allows objective quantification of vocal fold vibratory characteristics. However, it is unknown how the analyzed sequence length affects some of the computed parameters. To examine if varying sequence lengths influence parameter calculation, 20 HSV recordings of healthy females during sustained phonation were investigated. The clinical prevalent Photron Fastcam MC2 camera with a frame rate of 4000 fps and a spatial resolution of 512 x 256 pixels was used to collect HSV data. The glottal area waveform (GAW), describing the increase and decrease of the area between the vocal folds during phonation, was extracted. Based on the GAW, 16 perturbation parameters were computed for sequences of 5, 10, 20, 50 and 100 consecutive cycles. Statistical analysis was performed using SPSS Statistics, version 21. Only three parameters (18.8%) were statistically significantly influenced by changing sequence lengths. Of these parameters, one changed until 10 cycles were reached, one until 20 cycles were reached and one, namely Amplitude Variability Index (AVI), changed between almost all groups of different sequence lengths. Moreover, visually observable, but not statistically significant, changes within parameters were observed. These changes were often most prominent between shorter sequence lengths. Hence, we suggest using a minimum sequence length of at least 20 cycles and discarding the parameter AVI.
EVALuna2:118644

Influence of F0 and Sequence Length of Audio and Electroglottographic Signals on Perturbation Measures for Voice Assessment - Hohm, Julian; Döllinger, Michael; Bohr, Christopher; Kniesburges, Stefan; Ziethe, Anke (Journal of Voice, 2015)
Within the functional assessment of voice disorders, an objective analysis of measured parameters from audio, electroglottographic (EGG), or visual signals is desired. In a typical clinical situation, reliable objective analysis is not always possible due to missing standardization and unknown stability of the clinical parameters. The aim of this study was to investigate the robustness/stability of measured clinical parameters of the audio and EGG signals in a typical clinical setting to ensure a reliable objective analysis. In particular, the influence of F0 and of the sequence length on several definitions of jitter and shimmer will be analyzed.Seventy-four young healthy women produced a sustained vowel /a/ and an upward triad with abrupt changeovers. Different sequence lengths (100, 150, 500, and 1000 ms) of sustained phonation and triads (100 and 150 ms) were extracted from the audio and EGG signals. In total, six variations of jitter and four variations of shimmer parameters were analyzed.Jitter%, Jitter11p, and JitterPPQ of the audio signal as well as Jittermean, Shimmer, and Shimmer11p of the EGG signal are unaffected by both sequence length and F0.Influence of F0 and sequence length on several perturbation measures of the audio and EGG signals was identified. For an objective clinical voice assessment, unaffected definitions of jitter and shimmer should be preferred and applied to enable comparability between different recordings, examinations, and studies.
EVALuna2:19996

Influence of glottal closure on the phonatory process in ex vivo porcine larynges - Birk, Veronika; Kniesburges, Stefan; Semmler, Marion; Berry, David A.; Bohr, Christopher; Döllinger, Michael; Schützenberger, Anne (Journal of the Acoustical Society of America, 2017)
Many cases of disturbed voice signals can be attributed to incomplete glottal closure, vocal fold oscillation asymmetries, and aperiodicity. Often these phenomena occur simultaneously and interact with each other, making a systematic, isolated investigation challenging. Therefore, ex vivo porcine experiments were performed which enable direct control of glottal configurations. Different pre-phonatory glottal gap sizes, adduction levels, and flow rates were adjusted. The resulting glottal closure types were identified in a post-processing step. Finally, the acoustic quality, aerodynamic parameters, and the characteristics of vocal fold oscillation were analyzed in reference to the glottal closure types. Results show that complete glottal closure stabilizes the phonation process indicated through a reduced left-right phase asymmetry, increased amplitude and time periodicity, and an increase in the acoustic quality. Although asymmetry and periodicity parameter variation covers only a small range of absolute values, these small variations have a remarkable influence on the acoustic quality. Due to the fact that these parameters cannot be influenced directly, the authors suggest that the (surgical) reduction of the glottal gap seems to be a promising method to stabilize the phonatory process, which has to be confirmed in future studies.
EVALuna2:33158

Influence of hearing aids on monosyllabic test score and subjective everyday hearing - Thümmler, Rebecca; Liebscher, Tim; Hoppe, Ulrich (HNO, 2016)
BACKGROUND: Pure tone and speech audiometry are essential methods for examining the indication for hearing aids, as well as for hearing aid evaluation. Additionally, the subjective benefit of hearing aids has to be evaluated with appropriate questionnaires. The aim of the present study was to investigate the correlation between speech audiometry data and the results of a simple and user-friendly questionnaire, as well as to provide normative data for subjective benefit. MATERIALS AND METHODS: Data from 136 hearing aid users with bilateral sensorineural hearing loss were analyzed retrospectively. Pure tone thresholds and Freiburg monosyllabic speech perception in the binaural situation were measured at 65 dB in quiet and in noise (signal-to-noise ratio, SNR = +5 dB), with and without hearing aids. Additionally, subjective hearing in everyday life was recorded using the 12-item Oldenburg Inventory. RESULTS: Improvement of speech perception with hearing aids for the Freiburg monosyllabic test in quiet was 32.0 percentage points on average; in noise, there was an average improvement of 16.4 percentage points. There was a strong correlation between the results of pure tone and speech audiometry. With hearing aids, patients scored their everyday hearing using the Oldenburg Inventory on average 1.4 scale points better than without hearing aids. Results of the Oldenburg Inventory correlate with both pure tone and speech audiometry. CONCLUSION: Hearing aid evaluation should include both speech audiometry and systematic measurement of the subjective benefit using a suitable questionnaire. In combination, the Freiburg monosyllabic test and the Oldenburg Inventory allow for quick and comprehensive evaluation.
EVALuna2:33933

Influence of Loudness on Vocal Stability in the Male Passaggio - Echternach, Matthias; Döllinger, Michael; Köberlein, Marie; Kuranova, Liudmila; Kainz, Marie Anne (Journal of Voice, 2021)
Introduction: Vocal registers and the frequency region where registration events occur, the passaggio, have been in focus of scientific research for almost 200 years. In professional tenors, it has been shown before that singing across the passaggio avoiding a register shift and therefore using their stage voice above the passaggio (SVaP) is associated with greater vocal stability than a register change to the falsetto. However, it is unclarified how much different loudness conditions contribute to this vocal stability. Material and methods: Six professional tenors were asked to perform four pitch glides from A3 to A4 (220-440 Hz) on the vowel [i:]. These glides included (1) the passaggio from modal register to falsetto. The following glides into SVaP were performed under different loudness conditions, (2) mezzoforte (average loudness), (3) pianissimo (as quietly as possible), and (4) fortissimo (the loudest possible). During phonation, high speed videoendoscopy (HSV), electroglottography, and audio signals were recorded simultaneously. The glottal area waveform was derived based on the HSV material. Results: Modal to falsetto transitions were associated with relatively low sound pressure level and rise of open quotients (OQ) for the falsetto. Transitions to SVaP showed a clear dependence on the intended loudness. The OQs were lower the louder the task was. There was no clear evidence that transitions with softer voice showed greater stability of vocal fold oscillation patterns than louder tasks. Conclusions: The vocal fold oscillation pattern show- differences among various loudness conditions within the tenors’ passaggio but no clear differences with regard to oscillatory stability.
CRIS-Team Scopus Importer:2021-01-29
Keywords: EGG; High-speed imaging; Loudness; Tenors

Influence of Naturally Occurring Tissue Movements on Magnetomotive Ultrasound Detection of Iron Oxide Nanoparticles for Magnetic Drug Targeting - Fink, Michael; Ermert, Helmut; Lyer, Stefan; Alexiou, Christoph (Proceedings of the Ultrasonics Symposium (IUS), 2017)

Influence of p16 status on indication and outcome of salvage neck dissection in oropharyngeal cancer - Mueller, Sarina K.; Mantsopoulos, Konstantinos; Semrau, Sabine; Agaimy, Abbas; Eckstein, Markus; Traxdorf, Maximilian; Gostian, Antoniu Oreste; Goncalves, Miguel; Sievert, Matti; Haderlein, Marlen; Grundtner, Philipp; Hecht, Markus; et al. (Acta Oto-Laryngologica, 2020)
Background: Human papillomavirus (HPV)+ and HPV– oropharyngeal squamous cell carcinomas (OPSCC) are separate tumor entities. Aims/Objectives: The aim of this study was to examine if the p16 status influences the need and outcome of a salvage neck dissection (SND) after primary radiochemotherapy (pRCT). Material and methods: Retrospective study of 164 patients (n = 108 p16–, n = 56 p16+) who underwent pRCT for OPSCC between 2009 and 2016. HPV status was defined via p16 immunohistochemical staining. Clinical nodal status was assessed using ultrasound and computed tomography of the neck with contrast. Results: Of the 56 p16+ patients, 17 (30.4%) patients were given an indication for a SND after pRCT with 4 (23.5%) patients showing persistent malignant nodes. Of the 108 p16– patients, 24 (22.2%) patients underwent a SND with 8 (33.3%) patients showing persistent malignant nodes. There was no significant association of the p16 status and neither the indication for SND (p(Chi2(two-sided)-Test) = 0.25, ϕ = 0.34) nor the occurrence of positive nodes (p(Chi2(two-sided)-Test) = 0.74, ϕ = 0.50). The probability for persistence of the ypN + nodal status independent of HPV-status was 29.2%(12/41). Conclusions and significance: There was neither a significant association between the p16 status and the indication for a SND nor for persistent malignant nodal disease after pRCT.
CRIS-Team Scopus Importer:2020-11-06
Keywords: de-escalation; HPV; Oropharyngeal cancer; p16; radiochemotherapy

Influence of Perspective Distortion in Laryngoscopy - Veltrup, Reinhard; Kniesburges, Stefan; Semmler, Marion (Journal of Speech Language and Hearing Research, 2023)
OBJECTIVE: An experiment with controllable boundaries was designed to assess the influence of the recording angle and distance on two-dimensional (2D) imaging in laryngoscopy and resulting 2D parameter calculation derived from the glottal area waveform (GAW). METHOD: Two high-speed camera setups were used to synchronously record an oscillating synthetic vocal fold (VF) model, simulating a high-speed videoendoscopy. One camera recorded at variable lateral recording angles and a reference camera in superior perspective. This was performed at different physiological recording distances and for two oscillation modes (with/without contacting VFs). The GAW was derived from the segmented glottis, and two parameters each for the categories of symmetry, periodicity, and closure were calculated, as well as two derivative measures. The percentage difference between the variable and reference camera value pairs was calculated, and the angle and height dependencies were quantified using linear regression. RESULTS: The visual perception of a laryngoscopy was found to be influenced by the lateral recording angle, which may lead to misinterpretation of VF symmetry among inexperienced observers. The strongest influence of recording angle was observed for symmetry parameters, the strongest being the Amplitude Symmetry Index with up to 2.6%/° (p < .05). A dependence on the recording distance was only found for the Maximum Area Declination Rate. CONCLUSIONS: The recording angle in 2D laryngoscopy should be carefully considered during visual inspection of the VF dynamics. Most of the investigated objective parameters were unaffected by the examined perspective distortion. However, especially left-right symmetry measures should only be used under controlled boundary conditions to avoid misdiagnosis and misinterpretation. SUPPLEMENTAL MATERIAL: https://doi.org/10.23641/asha.23961183.
CRIS-Team Scopus Importer:2023-09-22

Influence of Reduced Saliva Production on Phonation in Patients With Ectodermal Dysplasia - Semmler, Marion; Kniesburges, Stefan; Pelka, Franziska; Ensthaler, Maria; Wendler, Olaf Dietrich; Schützenberger, Anne (Journal of Voice, 2021)
Objective: Patients with ectodermal dysplasia (ED) suffer from an inherited disorder in the development of the ectodermal structures. Besides the main symptoms, i.e. significantly reduced formation/expression of teeth, hair and sweat glands, a decreased saliva production is objectively accounted. In addition to difficulties with chewing/swallowing, ED patients frequently report on the subjective impression of rough and hoarse voices. A correlation between the reduced production of saliva and an affliction of the voice has not yet been investigated objectively for this rare disease. Methods: Following an established measurement protocol, a study has been conducted on 31 patients with ED and 47 controls (no ED, healthy voice). Additionally, the vocal fold oscillations were recorded by high-speed videoendoscopy (HSV@4 kHz). The glottal area waveform was determined by segmentation and objective glottal dynamic parameters were calculated. The generated acoustic signal was evaluated by objective and subjective measures. The individual impairment was documented by a standardized questionnaire (VHI). Additionally, the amount of generated saliva was measured for a defined period of time. Results: ED patients displayed a significantly reduced saliva production compared to the control group. Furthermore, the auditory-perceptual evaluation yielded significantly higher ratings for breathiness and hoarseness in the voices of male ED patients compared to male controls. The majority of male ED patients (67%) indicated at least minor impairment in the self-evaluation. Objective acoustic measures like Jitter and Shimmer confirmed the decreased acoustic quality in male ED patients, whereas none of the investigated HSV parameters showed significant differences between the test groups. Statistical analysis did not confirm a statistically significant correlation between reduced voice quality and amount of saliva. Conclusions: An objective impairment of the acoustic outcome was demonstrated for male ED patients. However, the vocal folds dynamics in HSV recordings seem unaffected.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Ectodermal Dysplasia; Evidence-based Medicine; Saliva Production; Standardized Voice Evaluation

Influence of Reverberation on Automatic Evaluation of Intelligibility with Prosodic Features - Haderlein, Tino; Döllinger, Michael; Schützenberger, Anne; Nöth, Elmar (Proc. Text, Speech and Dialogue; 19th International Conference, TSD 2016, 2016)
UnivIS-Import:2017-12-18:Pub.2016.tech.IMMD.IMMD5.influe
Keywords: Sprache

Influence of spatial camera resolution in highspeed videoendoscopy on laryngeal parameters - Schlegel, Patrick; Kunduk, Melda; Stingl, Michael; Semmler, Marion; Döllinger, Michael; Bohr, Christopher; Schützenberger, Anne (PLoS ONE, 2019)
In laryngeal high-speed videoendoscopy (HSV) the area between the vibrating vocal folds during phonation is of interest, being referred to as glottal area waveform (GAW). Varying camera resolution may influence parameters computed on the GAW and hence hinder the comparability between examinations. This study investigates the influence of spatial camera resolution on quantitative vocal fold vibratory function parameters obtained from the GAW. In total 40 HSV recordings during sustained phonation (20 healthy males and 20 healthy females) were investigated. A clinically used Photron Fastcam MC2 camera with a frame rate of 4000 fps and a spatial resolution of 512×256 pixels was applied. This initial resolution was reduced by pixel averaging to (1) a resolution of 256×128 and (2) to a resolution of 128×64 pixels, yielding three sets of recordings. The GAW was extracted and in total 50 vocal fold vibratory parameters representing different features of the GAW were computed. Statistical analyses using SPSS Statistics, version 21, was performed. 15 Parameters showing strong mathematical dependencies with other parameters were excluded from the main analysis but are given in the Supporting Information. Data analysis revealed clear influence of spatial resolution on GAW parameters. Fundamental period measures and period perturbation measures were the least affected. Amplitude perturbation measures and mechanical measures were most strongly influenced. Most glottal dynamic characteristics and symmetry measures deviated significantly. Most energy perturbation measures changed significantly in males but were mostly unaffected in females. In females 18 of 35 remaining parameters (51%) and in males 22 parameters (63%) changed significantly between spatial resolutions. This work represents the first step in studying the impact of video resolution on quantitative HSV parameters. Clear influences of spatial camera resolution on computed parameters were found. The study results suggest avoiding the use of the most strongly affected parameters. Further, the use of cameras with high resolution is recommended to analyze GAW measures in HSV data.
CRIS-Team Scopus Importer:2019-05-02

Inhibitors of Deubiquitinating Enzymes Block HIV-1 Replication and Augment the Presentation of Gag-Derived MHC-I Epitopes - Setz, Christian; Friedrich, Melanie; Rauch, Pia; Fraedrich, Kirsten; Matthaei, Alina; Traxdorf, Maximilian; Schubert, Ulrich (Viruses, 2017)
In recent years it has been well established that two major constituent parts of the ubiquitin proteasome system (UPS)-the proteasome holoenzymes and a number of ubiquitin ligases-play a crucial role, not only in virus replication but also in the regulation of the immunogenicity of human immunodeficiency virus type 1 (HIV-1). However, the role in HIV-1 replication of the third major component, the deubiquitinating enzymes (DUBs), has remained largely unknown. In this study, we show that the DUB-inhibitors (DIs) P22077 and PR-619, specific for the DUBs USP7 and USP47, impair Gag processing and thereby reduce the infectivity of released virions without affecting viral protease activity. Furthermore, the replication capacity of X4- and R5-tropic HIV-1NL4-3in human lymphatic tissue is decreased upon treatment with these inhibitors without affecting cell viability. Most strikingly, combinatory treatment with DIs and proteasome inhibitors synergistically blocks virus replication at concentrations where mono-treatment was ineffective, indicating that DIs can boost the therapeutic effect of proteasome inhibitors. In addition, P22077 and PR-619 increase the polyubiquitination of Gag and thus its entry into the UPS and the major histocompatibility complex (MHC)-I pathway. In summary, our data point towards a model in which specific inhibitors of DUBs not only interfere with virus spread but also increase the immune recognition of HIV-1 expressing cells.
EVALuna2:33758

Innervation pattern of the preocular human central retinal artery - Bergua, Antonio; Kapsreiter, Markus; Neuhuber, Winfried; Reitsamer, Herbert A.; Schroedl, Falk (Experimental Eye Research, 2013)
The central retinal artery (CRA) is the main vessel for inner retinal oxygen and nutrition supply. While the intraocular branches lack autonomic innervation, the innervation pattern of the extra-ocular part of this vessel along its course within the optic nerve is poorly investigated. This part however is essential for maintenance of retinal blood supply, in physiological and pathological conditions. Therefore, the aim of this study was the characterization of the autonomic innervation of the preocular CRA in humans with morphological methods. Meeting the Declaration of Helsinki, eyes of body or cornea donors were processed for single or double immunohistochemistry against tyrosine hydroxilase (TH), dopamine-?-hydroxylase (DBH), choline acetyl-transferase (ChAT), vesicular acetylcholine transporter (VAChT), neuronal nitric oxide synthase (nNOS), calcitonin gene-related peptide (CGRP), substance P (SP), vasoactive intestinal polypeptide (VIP), and cytochemistry for NADPH-diaphorase (NADPH-d). For documentation, light-, fluorescence-, and confocal laser-scanning microscopy were used. TH and DBH immunoreactive nerve fibres were detected in the CRA vessel wall, although a distinct perivascular plexus was missing. Further, nerve fibres immunoreactive for ChAT and VAChT were found, while CGRP, SP, and VIP were not detected. NADPH-d staining revealed scattered nerve fibres in the adventitia of the CRA and in close vicinity; however, nNOS-immunostaining could not confirm this finding. The CRA receives adrenergic and cholinergic innervations, indicating sympathetic and parasympathetic components, respectively. Remarkably, a peptidergic primary afferent innervation was missing. Since clinical results suggest an autoregulation of intraretinal vessels, further studies are needed to clarify the impact of CRA innervation for retinal perfusion.
EVALuna2:4135

Innovative Toxicological Investigation Methods for Iron Oxide Nanoparticles in Nanomedicine - Janko, Christina; Pöttler, Marina; Matuszak, Jasmin; Unterweger, Harald; Hornung, Annkathrin; Friedrich, Ralf P.; Alexiou, Christoph (Chemie Ingenieur Technik, 2017)
Superparamagnetic iron oxide nanoparticles (SPIONs) offer various possibilities for application in medicine. Comprehensive toxicological investigations based on proper physicochemical nanoparticle characterizations are a prerequisite for translation from bench to bedside. Since nanoparticles are prone to interfere with several classical toxicological readout systems, alternative methods are necessary. Multiparameter stainings for flow cytometry and fluorescence microscopy, label-free real-time cell analyses, 3D cell culture, and flow models will be discussed here.
EVALuna2:33180

Innovative toxikologische Untersuchungsmethoden für Eisenoxidnanopartikel in der Nanomedizin - Janko, Christina; Pottler, Marina; Matuszak, Jasmin; Unterweger, Harald; Hornung, Annkathrin; Friedrich, Ralf P.; Alexiou, Christoph (Chemie Ingenieur Technik, 2017)
Superparamagnetische Eisenoxidnanopartikel (SPIONs) bieten vielfältige Anwendungsmöglichkeiten in der Medizin. Toxikologische Untersuchungen, die auf der physikochemischen Charakterisierung der Nanopartikel aufbauen, sind eine wesentliche Voraussetzung für die zukünftige Translation in die klinische Anwendung. Da Nanopartikel mit zahlreichen klassischen toxikologischen Nachweismethoden interferieren, sind Alternativmethoden notwendig. Multiparameterfärbungen für Durchflusszytometrie und Fluoreszenzmikroskopie, markierungsfreie Echtzeitanalysen, 3D-Zellkultur und Flussmodelle werden diskutiert.
EAM Import::2019-03-13

Insight COMPASS – the physics behind - Günther, J.; Kampf, T.; Rückert, M. A.; Friedrich, Bernhard; Tietze, Rainer; Lyer, Stefan; Hennig, T.; Dölken, L.; Alexiou, Christoph; Behr, V. C.; Vogel, P. (International Journal of Magnetic Particle Imaging, 2023)
Critical Offset Magnetic PArticle SpectroScopy (COMPASS) is a new method that allows to detect slight changes in the mobility of particles in a solution very sensitively. While first applications in detecting biomarkers such as SARS CoV 2 antibodies show very promising results, the full potential of the technique and the underlying physical effects were yet only considered superficially. Here we present the first results of a detailed study of the behavior of the particle signal under variations of relevant system parameters with a focus on particle size, viscosity and temperature of the solution to win more information about the behavior of the effect and find new interesting application possibilities.
CRIS-Team Scopus Importer:2023-04-14

Integration of Leaky-Integrate-and-Fire Neurons in Standard Machine Learning Architectures to Generate Hybrid Networks: A Surrogate Gradient Approach - Gerum, Richard C.; Schilling, Achim (Neural Computation, 2021)
Up to now, modern machine learning (ML) has been based on approximating big data sets with high-dimensional functions, taking advantage of huge computational resources. We show that biologically inspired neuron models such as the leaky-integrate-and-fire (LIF) neuron provide novel and efficient ways of information processing. They can be integrated in machine learning models and are a potential target to improve ML performance. Thus, we have derived simple update rules for LIF units to numerically integrate the differential equations. We apply a surrogate gradient approach to train the LIF units via backpropagation. We demonstrate that tuning the leak term of the LIF neurons can be used to run the neurons in different operating modes, such as simple signal integrators or coincidence detectors. Furthermore, we show that the constant surrogate gradient, in combination with tuning the leak term of the LIF units, can be used to achieve the learning dynamics of more complex surrogate gradients. To prove the validity of our method, we applied it to established image data sets (the Oxford 102 flower data set, MNIST), implemented various network architectures, used several input data encodings and demonstrated that the method is suitable to achieve state-of-the-art classification performance. We provide our method as well as further surrogate gradient methods to train spiking neural networks via backpropagation as an open-source KERAS package to make it available to the neuroscience and machine learning community. To increase the interpretability of the underlying effects and thus make a small step toward opening the black box of machine learning, we provide interactive illustrations, with the possibility of systematically monitoring the effects of parameter changes on the learning characteristics.
CRIS-Team WoS Importer:2021-09-24

Integration of Molecular Communications into Future Generation Wireless Networks - Haselmayr, Werner; Springer, Andreas; Fischer, Georg; Alexiou, Christoph; Boche, Holger; Höher, Peter Adam; Dressler, Falko; Schober, Robert (6G Wireless Summit, 2019)

[Intelligibility of children with bilateral and unilateral cleft lip and palate]. - Maier, Andreas; Holst, Alexandra; Schuster, Maria; Schützenberger, Anne; Eysholdt, Ulrich; Nöth, Elmar; Dames, F.; Stelzle, Florian (Laryngo-Rhino-Otologie, 2009)
OBJECTIVE Data about the effect of unilateral or bilateral cleft lip and palate (CLP) on speech quality are inconsistent. In this study we firstly quantify the intelligibility of children with unilateral and bilateral CLP objectively by means of automatic speech recognition system (ASR). METHODS Speech data of 72 German speaking children (8.7+/-3.0 years) with CLP thereof 17 children with bilateral CLP, 23 with CLP on the right side, and 32 on the left, were compared. A group of 159 children aged 9.1+/-2.9 years served as control group. To quantify intelligibility we calculated the word recognition rate (WR) as the percentage of correctly recognized words of a standardized speech test (PLAKSS). RESULTS Between the 3 cleft groups, there was no significant difference in WR. Compared to the control group (WR mean 63.5%+/-12.1%), the patient group (WR mean 48.1%+/-16.3%) shows significant lower WR (p< 0.001). The WR rises with increasing age in the control group and in the patient groups with unilateral cleft significantly. This couldn't be observed in the children with bilateral CLP. In this group the males showed a significantly higher WR than the females. In the control group as in the patient groups with unilateral cleft there is no significant difference between girls and boys. CONCLUSIONS Despite the greater extent of the malformation of children with a bilateral CLP, there is no significant difference to the children with only a unilateral cleft lip and palate.
Keywords: Automatic speech recognition; Cleft lip and palate; Intelligibility; Objective evaluation

Interactive Image Segmentation for Cochlea Implant Planning based on DVT Data - Killguß, Nathalie; Wittenberg, Thomas; Franz, Daniela; Eixelberger, Thomas; Rupp, Robin; Hofer, Mathias (Current Directions in Biomedical Engineering, 2019)
Cochlea Implant (CI) planning is usually based on preoperative obtained CT or MRI data, visualising risk structures in the petrosal bone. In the past years, Digital Volume Tomography (DVT) with an increased spatial resolution and reduced radiation has become more important in the clinical routine for otology. In this work we propose an extension of our interactive "wizard"-guided approach for the interactive segmentation of the middle and inner ear structures for the use with DVT data. Different filter pipelines enable the user to interactive segment the acoustic canal, ossicles, tympanic cavity, facial nerve, chorda tympani, round window, cochlea and semicircular canals. The approach has been evaluated on six pre-operative acquired DVT datasets by an ENT expert. Results imply that the proposed method can handle DVT well and can potentially be used for interactive OR planning.
CRIS-Team Scopus Importer:2019-10-08
Keywords: Cochlea Implant planning; Digital Volume Tomography; Image processing; Interactive Segmentation

Interdependencies between acoustic and high-speed videoendoscopy parameters - Schlegel, Patrick; Kist, Andreas; Kunduk, Melda; Dürr, Stephan; Döllinger, Michael; Schützenberger, Anne (PLoS ONE, 2021)
In voice research, uncovering relations between the oscillating vocal folds, being the sound source of phonation, and the resulting perceived acoustic signal are of great interest. This is especially the case in the context of voice disorders, such as functional dysphonia (FD). We investigated 250 high-speed videoendoscopy (HSV) recordings with simultaneously recorded acoustic signals (124 healthy females, 60 FD females, 44 healthy males, 22 FD males). 35 glottal area waveform (GAW) parameters and 14 acoustic parameters were calculated for each recording. Linear and non-linear relations between GAW and acoustic parameters were investigated using Pearson correlation coefficients (PCC) and distance correlation coefficients (DCC). Further, norm values for parameters obtained from 250 ms long sustained phonation data (vowel /i/) were provided. 26 PCCs in females (5.3%) and 8 in males (1.6%) were found to be statistically significant (|corr.| 0.3). Only minor differences were found between PCCs and DCCs, indicating presence of weak non-linear dependencies between parameters. Fundamental frequency was involved in the majority of all relevant PCCs between GAW and acoustic parameters (19 in females and 7 in males). The most distinct difference between correlations in females and males was found for the parameter Period Variability Index. The study shows only weak relations between investigated acoustic and GAW-parameters. This indicates that the reduction of the complex 3D glottal dynamics to the 1D-GAW may erase laryngeal dynamic characteristics that are reflected within the acoustic signal. Hence, other GAW parameters, 2D-, 3D-laryngeal dynamics and vocal tract parameters should be further investigated towards potential correlations to the acoustic signal.
CRIS-Team Scopus Importer:2021-03-05

Interrater Reliability of Ultrasound in the Diagnosis of Sialolithiasis - Goncalves, Miguel; Mantsopoulos, Konstantinos; Schapher, Mirco; Zenk, Johannes; Bozzato, Alessandro; Kuenzel, Julian; Zengel, Pamela; Iro, Heinrich; Koch, Michael (Ultraschall in der Medizin, 2019)
Purpose The aim of this study was to assess the interrater reliability of ultrasound for diagnosing sialolithiasis. Materials and Methods A total of 100 consecutive patients with signs of obstructive sialadenopathy were evaluated. The patients all underwent ultrasound examinations in a standardized manner conducted by one specialist with extensive experience in the management of salivary gland disorders and proficiency in head and neck ultrasonography. The video recordings were sent to six colleagues with comparable experience without providing any further information about the patients' medical history and physical examination. Results The overall agreement between the seven observers was substantial, with a κ of 0.765 for the 100 cases and a percentage agreement level of 88.29 ± 3.01 % (range: 83-94 %). The range of agreement on this video set for observer pairs varied from substantial to almost perfect agreement (0.663 to 0.878). Among the few false-negative findings (5.4 %), 71.8 % were due to distal sialolithiasis. Two-thirds of the false-positive findings (3.7 %) were due to fibrotic stenosis. Conclusion The study confirmed the diagnostic value of ultrasound in sialolithiasis and demonstrated a very high level of interrater agreement, even in the absence of additional clinical patient information, thus further underscoring the importance of ultrasound as the examination of first choice in sialolithiasis.
CRIS-Team Scopus Importer:2019-08-16
Keywords: interrater; parotid; sialolithiasis; submandibular; ultrasound

Intersegmenter Variability in High-Speed Laryngoscopy-Based Glottal Area Waveform Measures - Maryn, Youri; Verguts, Monique; Demarsin, Hannelore; Van Dinther, Joost; Gómez, Pablo; Schlegel, Patrick; Döllinger, Michael (Laryngoscope, 2019)
Objectives/Hypothesis High-speed videoendoscopy (HSV) has potential to objectively quantify vibratory vocal fold characteristics during phonation. Glottal Analysis Tools (GAT) version 2018, developed in Erlangen, Germany, is software for determining various glottal area waveform (GAW) quantities. Before having GAT analyze HSV videos, segmenters have to define glottis manually across videos in a semiautomatic segmentation protocol. Such interventions are hypothesized to induce variability of subsequent GAW measure computation across segmenters and may attenuate GAT measures' reliability to a certain point. This study explored intersegmenter variability in GAT's GAW measures based on semiautomatic image processing. Study Design Cohort study of rater reliability. Methods In total, 20 HSV videos from normophonic and dysphonic subjects with various laryngeal disorders were selected for this study and segmented by three trained segmenters. They separately segmented glottis areas in the same frame sets of the videos. Upon analysis of GAW, GAT offers 46 measures related to topologic GAW dynamic characteristics, GAW periodicity and perturbation characteristics, and GAW harmonic components. To address GAT's reliability, intersegmenter-based variability in these measures was examined with intraclass correlation coefficient (ICC). Results In general, ICC behavior of the 46 GAW measures across three raters was highly acceptable. ICC of one parameter was moderate (0.5 < ICC < 0.75), good for seven parameters (0.75 < ICC < 0.9), and excellent for 38 parameters (0.9 < ICC). Conclusions Overall, high ICC values confirm clinical applicability of GAT for objective and quantitative assessment of HSV. Small intersegmenter differences with actual small parameter differences suggest that manual or semiautomatic segmentation in GAT does not noticeably influence clinical assessment outcome. To guarantee the software's performance, we suggest segmentation training before clinical application. Level of Evidence 2b Laryngoscope, 2019
CRIS-Team WoS Importer:2019-12-27

Intracellular amplifiers of reactive oxygen species affecting mitochondria as radiosensitizers - Xu, Honggui; Reshetnikov, Viktor; Wondrak, Marit; Eckhardt, Lisa; Kunz-Schughart, Leoni A.; Janko, Christina; Tietze, Rainer; Alexiou, Christoph; Borchardt, Hannes; Aigner, Achim; Gong, Wenjie; Schmitt, Michael; et al. (Cancers, 2022)
Radiotherapy (RT) efficacy can be improved by using radiosensitizers, i.e., drugs enhancing the effect of ionizing radiation (IR). One of the side effects of RT includes damage of normal tissue in close proximity to the treated tumor. This problem can be solved by applying cancer specific radiosensitizers. N-Alkylaminoferrocene-based (NAAF) prodrugs produce reactive oxygen species (ROS) in cancer cells, but not in normal cells. Therefore, they can potentially act as cancer specific radiosensitizers. However, early NAAF prodrugs did not exhibit this property. Since functional mitochondria are important for RT resistance, we assumed that NAAF prodrugs affecting mitochondria in parallel with increasing intracellular ROS can potentially exhibit synergy with RT. We applied sequential Cu+-catalyzed alkyne-azide cycloadditions (CuAAC) to obtain a series of NAAF derivatives with the goal of improving anticancer efficacies over already existing com-pounds. One of the obtained prodrugs (2c) exhibited high anticancer activity with IC50 values in the range of 5–7.1 µM in human ovarian carcinoma, Burkitt’s lymphoma, pancreatic carcinoma and T-cell leukemia cells retained moderate water solubility and showed cancer specificity. 2c strongly affects mitochondria of cancer cells, leading to the amplification of mitochondrial and total ROS production and thus causing cell death via necrosis and apoptosis. We observed that 2c acts as a radiosensitizer in human head and neck squamous carcinoma cells. This is the first demonstration of a synergy between the radiotherapy and NAAF-based ROS amplifiers.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Cancer; Mitochondrion; N-alkylaminoferrocene; Prodrug; Radiotherapy; Reactive oxygen species

Intracellular Quantification and Localization of Label-Free Iron Oxide Nanoparticles by Holotomographic Microscopy - Friedrich, Ralf P.; Schreiber, Eveline; Tietze, Rainer; Yang, Hai; Pilarsky, Christian; Alexiou, Christoph (Nanotechnology, Science and Applications, 2020)
Background: The limitations of optical microscopy to determine the cellular localization of label-free nanoparticles prevent a solid prediction of the cellular effect of particles intended for medical applications. To avoid the strong physicochemical changes associated with fluorescent labelling, which often result in differences in cellular uptake, efficiency and toxicity of particles, novel detection techniques are required.
CRIS-Team WoS Importer:2021-01-29

Intraductal Fragmentation in Sialolithiasis Using Pneumatic Lithotripsy: Initial Experience and Results - Koch, Michael; Schapher, Mirco; Sievert, Matti; Mantsopoulos, Konstantinos; Iro, Heinrich (Otolaryngology-Head and Neck Surgery, 2021)
Objective: To report initial experience in using a pneumatic lithotripter to treat salivary stones. Study Design: Level IV retrospective study. Setting: University hospital and tertiary referral center. Methods: A pneumatic lithotripter was used to treat salivary stones after these were diagnosed. Probes with diameters of 0.7 mm were used. Total fragmentation was intended in all stones. Stone fragments were removed using several instruments in serial sialendoscopies to achieve complete stone clearance. Results: A total of 62 patients with 77 stones were treated. Forty-three submandibular stones were treated in 34 patients, and 34 parotid stones were treated in 28 patients. An operating pressure of 2.5 bar and a single frequency mode were used. Complete fragmentation was achieved in all but one of the treated stones in both glands (98.7%). Among the patients, 90.32% became stone free and 100% symptom free. Multiple stones were treated in 24.19% of the patients, and multimodal therapy was also carried out in 24.19%. All of the glands were preserved. Conclusions: The pneumatic lithotripter proved to be effective in the treatment of sialolithiasis. Stone size, location, and the gland involved were important clinical factors. The device was sufficient to achieve success without any increased risk for complications in the patients or damage to the sialendoscopes.
CRIS-Team Scopus Importer:2021-10-22
Keywords: intraductal lithotripsy; pneumatic lithotripsy; salivary gland; sialendoscopy; sialolithiasis; treatment

Intraductal Lithotripsy in Sialolithiasis Using the Calculase III™ Ho:YAG Laser: First Experiences - Koch, Michael; Schapher, Mirco; Mantsopoulos, Konstantinos; Iro, Heinrich (Lasers in Surgery and Medicine, 2020)
Background and Objectives: To report the first experiences with a newly available Ho:YAG laser system for the treatment of salivary stones. Study Design/Materials and Methods: A retrospective study in a tertiary referral center was conducted. Patients diagnosed with sialolithiasis were treated in Erlangen using the Calculase III™ Ho:YAG laser (Karl Storz, Tuttlingen, Germany). Preset parameters had a frequency of 4 Hz and energy of 0.8–1.2 J, resulting in 3.2–4.8 W. Following total fragmentation, one to two serial sialendoscopies were performed to achieve complete fragment clearance. Results: A total of 55 stones in 49 patients were treated; 17 stones in 15 submandibular glands and 38 in 34 parotids. In total, 61 laser lithotripsies (range 1–3 per stone) were performed using various modes (long, short, and burst) and with preset parameters of 4 Hz and energy of 0.8–1.2 J, resulting in effective power of 3.2–4.8 W. Complete fragmentation was achieved in all the accessible stones. Sialendoscopes, fibers, or the mode used had no significant influence on success rates. A multimodal therapy concept was employed to treat stones in 12.24% of the cases; 95.92% of the patients were ultimately stone-free, and all became symptom-free. All glands were preserved. Conclusions: The new Calculase III™ Ho:YAG laser was effective in the treatment of sialolithiasis with no increased risk of complications in the patients or damage to the sialendoscopes. Clinical factors such as the type of gland involved, or the location and size of stones had a greater impact on success rates than the technical or preset parameters. Lasers Surg. Med. © 2020 Wiley Periodicals LLC.
CRIS-Team Scopus Importer:2020-10-09
Keywords: intraductal lithotripsy; laser; salivary gland; sialendoscopy; sialolithiasis; treatment

Intraductal lithotripsy in sialolithiasis with two different Ho:YAG lasers: presetting parameters, effectiveness, success rates. - Koch, Matthias; Hung, S. H.; Su, C. H.; Lee, K. S.; Iro, Heinrich; Mantsopoulos, Konstantinos (European Review for Medical and Pharmacological Sciences, 2019)
OBJECTIVE: To compare two different Ho:YAG laser systems in relation to the preset parameters and their effectiveness for intraductal fragmentation of the salivary stones. PATIENTS AND METHODS: We made a retrospective study in two tertiary referral centers (Department of ENT, Head and Neck Surgery, University of Erlangen-Nuremberg, Germany and the MacKay Memorial Hospital, Taipei, Taiwan). Patients with a diagnosis of sialolithiasis were treated in Erlangen and Taipei. The Erlangen patients were treated using the Calculase II™ Ho:YAG laser (Karl Storz, Tuttlingen, Germany) at 4 Hz, 1.2 J (4.8 W) and the MacKay patients were treated using the VersaPulse® PowerSuite™ Ho:YAG laser (Lumenis Ltd., Yokneam, Israel) at 6 Hz, 0.5 J (3 W). RESULTS: A total of 12 patients with 12 stones were treated in Erlangen and 54 with 75 stones in Taipei. The submandibular stones were present in 50% and 86.7% of cases, respectively. The complete fragmentation was achieved in all of the treated stones in both groups; 100% and 92.6% of the patients were stone-free, 100% and 94.4% of the patients became symptom-free, respectively. 33% of the Erlangen patients had multimodal treatments. The glands were preserved in all cases in both centers. CONCLUSIONS: The Ho:YAG laser proved to be effective in the treatment of sialolithiasis. Stone size, location, and involved gland were important additional parameters. Our experience and the literature results show that the laser presetting with a frequency of 3-6 Hz, an energy level of 0.5-1.2 J, and effective power of between 3 and 4.8 W is sufficient to achieve maximum success without any increased risk for complications.
EVALuna2:209872

Intraductal lithotripsy in sialolithiasis with two different Ho:YAG lasers: Presetting parameters, effectiveness, success rates - Koch, M.; Hung, S. H.; Su, C. H.; Lee, K. S.; Iro, Heinrich; Mantsopoulos, K. (European Review for Medical and Pharmacological Sciences, 2019)
OBJECTIVE: To compare two different Ho:YAG laser systems in relation to the preset parameters and their effectiveness for intraductal fragmentation of the salivary stones. PATIENTS AND METHODS: We made a retrospective study in two tertiary referral centers (Department of ENT, Head and Neck Surgery, University of Erlangen-Nuremberg, Germany and the MacKay Memorial Hospital, Taipei, Taiwan). Patients with a diagnosis of sialolithiasis were treated in Erlangen and Taipei. The Erlangen patients were treated using the Calculase II™ Ho:YAG laser (Karl Storz, Tuttlingen, Germany) at 4 Hz, 1.2 J (4.8 W) and the MacKay patients were treated using the VersaPulse® PowerSuite™ Ho:YAG laser (Lumenis Ltd., Yokneam, Israel) at 6 Hz, 0.5 J (3 W). RESULTS: A total of 12 patients with 12 stones were treated in Erlangen and 54 with 75 stones in Taipei. The submandibular stones were present in 50% and 86.7% of cases, respectively. The complete fragmentation was achieved in all of the treated stones in both groups; 100% and 92.6% of the patients were stone-free, 100% and 94.4% of the patients became symptom-free, respectively. 33% of the Erlangen patients had multimodal treatments. The glands were preserved in all cases in both centers. CONCLUSIONS: The Ho:YAG laser proved to be effective in the treatment of sialolithiasis. Stone size, location, and involved gland were important additional parameters. Our experience and the literature results show that the laser presetting with a frequency of 3-6 Hz, an energy level of 0.5-1.2 J, and effective power of between 3 and 4.8 W is sufficient to achieve maximum success without any increased risk for complications.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Intraductal lithotripsy; Laser; Salivary gland; Sialendoscopy; Sialolithiasis; Treatment

Intraductal Papillary Mucinous Neoplasms of Minor Salivary Glands With AKT1 p.Glu17Lys Mutation - Agaimy, Abbas; Müller, Susanna; Bumm, Klaus; Iro, Heinrich; Moskalev, Evgeny; Hartmann, Arndt; Stoehr, Robert; Haller, Florian (American Journal of Surgical Pathology, 2018)
The spectrum of low-grade intraductal papillary proliferations of the salivary glands is heterogenous, and reproducible morphologic diagnostic criteria have not yet been established. Recognized types are sialadenoma papilliferum, inverted ductal papilloma, and intraductal papilloma, but some lesions have been possibly included in the morphologic spectrum of cystadenoma or low-grade intraductal carcinomas. We herein present detailed morphologic, immunophenotypic, and genotypic features of 3 minor salivary gland neoplasms affecting 2 men (aged 65 and 71 y) and 1 woman (aged 78 y). They ranged in size from 1 to 2.5 cm. All tumors showed atypical papillary intraductal growth that presented either as uninodular/unicystic lesions (intraductal papilloma-like; n=2) or as a discontinuous growth along the ductal system in a manner similar to pancreatic intraductal papillary mucinous neoplasm (n=1). Variable cytologic and architectural atypia was observed, ranging from bland intraductal papilloma-like features, to areas mimicking atypical ductal hyperplasia and low-grade ductal carcinoma in situ of the breast. Amplicon-based massive parallel sequencing revealed an identical AKT1 p.Glu17Lys mutation in all 3 cases, but absence of concurring mutations in other genes of the RAS or PI3K pathway. This small series represents the first genetic study on salivary intraductal papillary neoplasms. Our cases showed significant variation in the degree of cytologic and architectural atypia, which overlaps with intraductal papillomas at the one end and with low-grade intraductal carcinoma at the other end of the spectrum, suggesting a disease continuum. As the full biological and morphologic characteristics of these ductal papillary lesions remain to be defined, the noncommitted term "intraductal papillary neoplasms" might be more appropriate. Our novel genetic findings mirror similar activating mutations of AKT1 and other PI3K pathway members in intraductal papillary lesions of the breast and anogenital glands.
EVALuna2:34605

Intraductal Pneumatic Lithotripsy after Extended Transoral Duct Surgery in Submandibular Sialolithiasis - Koch, Michael; Schapher, Mirco; Mantsopoulos, Konstantinos; Goncalves, Miguel; Iro, Heinrich (Otolaryngology-Head and Neck Surgery, 2018)
Objective Persistent, residual, or recurrent stones after transoral duct surgery are always associated with hilar to intraparenchymal and/or multiple sialolithiasis, causing difficulties in the treatment. This study was performed to assess the value of intraductal lithotripsy in the treatment of persistent, residual, or recurrent sialolithiasis after extended duct surgery in the submandibular gland. Study Design Retrospective study covering February 2015 to June 2018. Study Setting Tertiary referral center for salivary gland diseases. Subjects and Methods After extended ductal surgery, 39 patients presenting with persistent, residual, or recurrent stones were treated. Four patients had persistent stones; 16 had residual stones; and 19 presented with recurrent stones. Among these patients, 50 stones were treated with intraductal pneumatic lithotripsy. Fragmentation rate, stone-free rate, and symptom-free rate after treatment with intraductal lithotripsy were outcome measures. Results Of the 39 patients, 97.4% became stone-free, and all were symptom-free. Ninety-eight percent of the stones were completely fragmented. For 23.1% of the patients, >1 stone was treated with intraductal lithotripsy. All patients with persistent stones, 93.7% of those with residual stones, and all with recurrent stones became stone-free and symptom-free. No severe complications developed. Conclusions This study shows that patients presenting with difficult and/or multiple sialolithiasis after extended transoral submandibular duct surgery can be treated with success rates >97%. For multiple sialolithiasis in particular, a multimodal treatment approach with interventional sialendoscopy and intraductal lithotripsy as a central element is a prerequisite for success, as this enables the most difficult part to be performed with high success rates.
EVALuna2:35383

Intraductal pneumatic lithotripsy for salivary stones with the StoneBreaker: Preliminary experience - Koch, Michael; Mantsopoulos, Konstantinos; Schapher, Mirco; Von Scotti, Felix; Iro, Heinrich (Laryngoscope, 2016)
OBJECTIVES/HYPOTHESIS: To test the effectiveness of a newly approved pneumatic lithotripter for fragmentation of salivary stones. STUDY DESIGN: Retrospective study in a tertiary referral center. METHODS: In 44 patients, 49 stones were primarily treated with direct endoscopic guidance using the StoneBreaker. Twenty-three stones were located in the parotid gland and 26 in the submandibular gland. RESULTS: Complete fragmentation was achieved combined extracorporeal in 97.7% of the stones. All of the patients became symptom free, and 97.7% were stone free. Three patients underwent lithotripsy procedures. Altogether additional treatment was necessary in five cases to achieve stone clearance. The reason for residual sialolithiasis was intraparenchymal repulsion of a residual fragment (n = 1). The glands were preserved in all cases. CONCLUSIONS: Endoscopically guided intraductal pneumatic lithotripsy using the StoneBreaker is an effective and promising procedure for the treatment of sialolithiasis. LEVEL OF EVIDENCE: 4 Laryngoscope, 126:1545-1550, 2016.
EVALuna2:33186

Intranasal delivery of nanoparticles - Friedrich, Ralf P.; Cicha, Iwona; Tietze, Rainer; Unterweger, Harald; Lyer, Stefan; Janko, Christina; Alexiou, Christoph (Nanomedicine, 2022)
CRIS-Team WoS Importer:2022-01-14

Intraoperative free margins assessment of oropharyngeal squamous cell carcinoma with confocal laser endomicroscopy: a pilot study - Sievert, Matti; Stelzle, Florian; Aubreville, Marc; Mueller, Sarina K.; Eckstein, Markus; Oetter, Nicolai; Maier, Andreas; Mantsopoulos, Konstantinos; Iro, Heinrich; Goncalves, Miguel (European Archives of Oto-Rhino-Laryngology, 2021)
Purpose: This pilot study aimed to assess the feasibility of intraoperative assessment of safe margins with confocal laser endomicroscopy (CLE) during oropharyngeal squamous cell carcinoma (OPSCC) surgery. Methods: We included five consecutive patients confirmed OPSCC and planned tumor resection in September and October 2020. Healthy appearing mucosa in the marginal zone, and the tumor margin, were examined with CLE and biopsy during tumor resection. A total of 12,809 CLE frames were correlated with the gold standard of hematoxylin and eosin staining. Three head and neck surgeons and one pathologist were asked to identify carcinoma in a sample of 169 representative images, blinded to the histological results. Results: Healthy mucosa showed epithelium with uniform size and shape with distinct cytoplasmic membranes and regular vessel architecture. CLE optical biopsy of OPSCC demonstrated a disorganized arrangement of variable cellular morphology. We calculated an accuracy, sensitivity, specificity, PPV, and NPV of 86%, 90%, 79%, 88%, and 82%, respectively, with inter-rater reliability and κ-value of 0.60. Conclusion: CLE can be easily integrated into the intraoperative setting, generate real-time, in-vivo microscopic images of the oropharynx for evaluation and demarcation of cancer. It can eventually contribute to a less radical approach by enabling a more precise evaluation of the cancer margin.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Confocal laser endomicroscopy; Head and neck malignancies; Oropharyngeal squamous cell carcinoma; Safe surgical margins

Intrinsic Noise Improves Speech Recognition in a Computational Model of the Auditory Pathway - Schilling, Achim; Gerum, Richard; Metzner, Claus; Maier, Andreas; Krauß, Patrick (Frontiers in Neuroscience, 2022)
Noise is generally considered to harm information processing performance. However, in the context of stochastic resonance, noise has been shown to improve signal detection of weak sub- threshold signals, and it has been proposed that the brain might actively exploit this phenomenon. Especially within the auditory system, recent studies suggest that intrinsic noise plays a key role in signal processing and might even correspond to increased spontaneous neuronal firing rates observed in early processing stages of the auditory brain stem and cortex after hearing loss. Here we present a computational model of the auditory pathway based on a deep neural network, trained on speech recognition. We simulate different levels of hearing loss and investigate the effect of intrinsic noise. Remarkably, speech recognition after hearing loss actually improves with additional intrinsic noise. This surprising result indicates that intrinsic noise might not only play a crucial role in human auditory processing, but might even be beneficial for contemporary machine learning approaches.
CRIS-Team Scopus Importer:2022-07-15
Keywords: auditory perception; deep artificial neural networks; dorsal cochlear nucleus; hearing loss; speech processing; stochastic resonance; tinnitus mechanisms; Zwicker tone

Investigation of arguments against properly indicated extracapsular dissection in the parotid gland - Mantsopoulos, Konstantinos; Scherl, Claudia; Iro, Heinrich (Head and Neck-Journal For the Sciences and Specialties of the Head and Neck, 2017)
BACKGROUND: The ideal extent of surgical intervention for benign parotid tumors remains a matter of controversy. The purpose of this study was to examine the existing arguments against extracapsular dissection and present our experience over the last 16 years. METHODS: A retrospective evaluation was carried out on the records of all patients who underwent extracapsular dissection for benign parotid tumors at a tertiary referral center between 2000 and 2015. RESULTS: A total of 1359 cases were included in the study. Temporary postoperative facial palsy was detected in 68 cases (5%), permanent facial palsy in 5 cases (0.37%), and postoperative Frey's syndrome in 31 cases (2.3%). Recurrences of pleomorphic adenomas were shown in 4 cases (0.87%). CONCLUSION: Our analysis could not justify the arguments against correctly indicated implementation of extracapsular dissection and showed that increased performance of this modality was associated with excellent oncologic and functional outcomes. © 2016 Wiley Periodicals, Inc. Head Neck 39: 498-502, 2017.
EVALuna2:33198

Investigation of locoregional metastatic behavior in low-grade malignant tumors of the parotid gland - Kapsalas, Andreas; Thimsen, Vivian; Varga, Regina; Agaimy, Abbas; Sievert, Matti; Balk, Matthias; Rupp, Robin; Koch, Michael; Iro, Heinrich; Mantsopoulos, Konstantinos (American Journal of Otolaryngology, 2023)
Background: The aim of the study was to investigate primary locoregional metastatic behavior in a large sample of low-grade malignant tumors of the parotid gland following surgical treatment consisting of complete parotidectomy and neck dissection. Methods: The records of all patients treated for low-grade malignant tumors of the parotid gland by complete parotidectomy and neck dissection between 2007 and 2022 were studied retrospectively. Results: 94 patients formed our study sample (50 females, 44 males, female to male ratio: 1.14). The mean age was 59 years (range 15–95 years). The mean number of lymph nodes in the specimen from complete parotidectomy was 3.33 (range: 0–12). The mean number of involved lymph nodes in the parotid gland was 0.05 (range: 0–1). The mean number of lymph nodes in the specimen from the ipsilateral neck dissection was 16.2 (range 4–42). The mean number of involved lymph nodes in the neck dissection specimen was 0.09 (range: 0–2). Comparison of T1-T2 vs. T3-T4 cases revealed no statistically significant difference concerning the tumorous involvement of the lymphatic network (x2 = 0.719, p = 0.396). Conclusion: Low-grade primary malignant tumors of the parotid gland are characterized by an initially low metastatic potential, which justifies conservative forms of surgical treatment.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Low-grade; Malignant tumor; Neck dissection; Parotid gland; Parotidectomy

Investigation of phonatory characteristics using ex vivo rabbit larynges - Döllinger, Michael; Kniesburges, Stefan; Berry, David A.; Birk, Veronika; Wendler, Olaf; Dürr, Stephan; Alexiou, Christoph; Schützenberger, Anne (Journal of the Acoustical Society of America, 2018)
Quantitative analysis of phonatory characteristics of rabbits has been widely neglected. However, preliminary studies established the rabbit larynx as a potential model of human phonation. This study reports quantitative data on phonation using ex vivo rabbit larynx models to achieve more insight into dependencies of three main components of the phonation process, including airflow, vocal fold dynamics, and the acoustic output. Sustained phonation was induced in 11 ex vivo rabbit larynges. For 414 phonatory conditions, vocal fold vibrations, acoustic, and aerodynamic parameters were analyzed as functions of longitudinal vocal fold pre-stress, applied air flow, and glottal closure insufficiency. Dimensions of the vocal folds were measured and histological data were analyzed. Glottal closure characteristics improved for increasing longitudinal pre-stress and applied airflow. For the subglottal pressure signal only the cepstral peak prominence showed dependency on glottal closure. In contrast, vibrational, acoustic, and aerodynamic parameters were found to be highly dependent on the degree of glottal closure: The more complete the glottal closure during phonation, the better the aerodynamic and acoustic characteristics. Hence, complete or at least partial glottal closure appears to enhance acoustic signal quality. Finally, results validate the ex vivo rabbit larynx as an effective model for analyzing the phonatory process.
EVALuna2:35453

Investigation of Sonographic Criteria for Reliable Identification of T1–T2 Low-Grade Malignant Tumors of the Parotid Gland - Berner, Ferdinand; Koch, Michael; Mueller, Sarina K.; Schapher, Mirco; Grundtner, Philipp; Iro, Heinrich; Mantsopoulos, Konstantinos (Ultrasound in Medicine and Biology, 2020)
The aim of this study was to investigate sonographic findings of low-grade malignant tumors of the parotid gland. The sonographic findings of all patients treated for T1–T2 low-grade carcinomas of the parotid gland between 2003 and 2018 were retrospectively examined and compared with those of patients with pleomorphic adenomas for the following parameters: definition of tumor margins, echotexture, echogenicity, shape and vascularization. Statistical analysis was performed using the χ2 test. A p value of <0.05 was considered statistically significant. A total of 310 patients (62 with T1–T2 low-grade malignant tumors, 248 with pleomorphic adenomas) were evaluated. Our analysis detected a statistically significant difference in the definition of margins, echotexture, echogenicity and shape. Furthermore, we could detect a specific pattern (anechoic islets in a small hypoechoic lesion with distal enhancement) appearing far more frequently in low-grade malignant lesions. It seems that there is still potential to reduce the incidence of the false working hypothesis “benign lesion” on imaging of low-grade malignant tumors.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Acinic cell carcinoma; Mucoepidermoid carcinoma; Parotid gland; Pleomorphic adenoma; Ultrasound

Investigation of the surgical strategies for unilateral multifocal cystadenolymphomas of the parotid gland - Mantsopoulos, Konstantinos; Koch, Michael; Goncalves, Miguel; Iro, Heinrich (Oral Oncology, 2018)
OBJECTIVES: The aim of the study was to compare multifocal extracapsular dissection with complete parotidectomy in the treatment of unilateral multifocal cystadenolymphomas of the parotid gland. MATERIALS AND METHODS: The records from all patients treated for unilateral multifocal cystadenolymphomas of the parotid gland at a tertiary referral center between 2000 and 2016 were retrospectively analyzed. RESULTS: 203 patients were included in the study. 96 patients were managed by multifocal extracapsular dissection, 107 patients underwent complete parotidectomy. Metachronous tumors were detected in 7 cases (3.4%) with a significant difference in the occurrence rate between multifocal extracapsular dissection (7/96, 7.3%) and complete parotidectomy (0/107, 0%) (p = 0.004). Permanent facial palsy was significantly more common after complete parotidectomy (21/107, 19.6%) than multifocal extracapsular dissection (2/96, 2.1%) (p = 0.000). CONCLUSIONS: The functional benefit of multifocal extracapsular dissection was counterbalanced by the advantage of complete parotidectomy, in terms of recurrences. Extracapsular dissection is at its limit in cases of multifocal cystadenolymphomas and the indication for it should be thoroughly verified in each and every case.
EVALuna2:35388

In Vitro Analysis of Superparamagnetic Iron Oxide Nanoparticles Coated with APTES as Possible Radiosensitizers for HNSCC Cells - Emer, Clara; Hildebrand, Laura; Friedrich, Bernhard; Tietze, Rainer; Fietkau, Rainer; Distel, Luitpold (Nanomaterials, 2023)
Superparamagnetic iron oxide nanoparticles (SPION) are being investigated for many purposes, e.g., for the amplification of ionizing radiation and for the targeted application of therapeutics. Therefore, we investigated SPIONs coated with (3-Aminopropyle)-Triethoxysilane (SPION-APTES) for their influence on different head and neck squamous cell carcinoma (HNSCC) cell lines, as well as for their suitability as a radiosensitizer. We used 24-well microscopy and immunofluorescence microscopy for cell observation, growth curves to determine cytostatic effects, and colony formation assays to determine cytotoxicity. We found that the APTES-SPIONs were very well taken up by the HNSCC cells. They generally have a low cytotoxic effect, showing no significant difference in clonogenic survival between the control group and cells treated with 20 µg Fe/mL (p > 0.25) for all cell lines. They have a cytostatic effect on some cell lines cells (e.g., Cal33) that is visible across different radiation doses (1, 2, 8 Gy, p = 0.05). In Cal33, e.g., SPION-APTES raised the doubling time at 2 Gy from 24.53 h to 41.64 h. Importantly, these findings vary notably between the cell lines. However, they do not significantly alter the radiation effect: only one out of eight cell lines treated with SPION-APTES showed a significantly reduced clonogenic survival after ionizing radiation with 2 Gy, and only two showed significantly reduced doubling times. Thus, although the APTES-SPIONs do not qualify as a radiosensitizer, we were still able to vividly demonstrate and analyze the effect that the APTES-SPIONs have on various cell lines as a contribution to further functionalization.
CRIS-Team Scopus Importer:2023-02-03
Keywords: cell survival; doubling time; head and neck cancer cell lines; HNSCC; nanoparticles; SPION; time lapse

In Vitro Setup for Determination of Nanoparticle-Mediated Magnetic Cell and Drug Accumulation in Tumor Spheroids under Flow Conditions - Behr, Jessica; Carnell, Lucas R. R.; Stein, Rene; Pfister, Felix; Friedrich, Bernhard; Huber, Christian; Lyer, Stefan; Band, Julia; Schreiber, Eveline; Alexiou, Christoph; Janko, Christina (Cancers, 2022)
Simple Summary Magnetic nanoparticles can render therapeutics or drugs magnetically guidable, which enables their targeted transport to the diseased tissue in the patient`s body. Before its translation into patients, the efficacy of magnetic accumulation must be tested in cell culture systems. To analyze magnetic enrichment under conditions similar to blood flow, we established an experimental in vitro setup with a tumor spheroid placed in a perfused chamber: with this, we showed that it is possible to accumulate cells or chemotherapeutics at the tumor, increasing their therapeutic efficacy. Superparamagnetic iron oxide nanoparticles (SPIONs) are used in nanomedicine as transporter systems for therapeutic cargos, or to magnetize cells to make them magnetically guidable. In cancer treatment, the site-directed delivery of chemotherapeutics or immune effector cells to the tumor can increase the therapeutic efficacy in the target region, and simultaneously reduce toxic side-effects in the rest of the body. To enable the transfer of new methods, such as the nanoparticle-mediated transport from bench to bedside, suitable experimental setups must be developed. In vivo, the SPIONs or SPION-loaded cells must be applied into the blood stream, to finally reach the tumor: consequently, targeting and treatment efficacy should be analyzed under conditions which are as close to in vivo as possible. Here, we established an in vitro method, including tumor spheroids placed in a chamber system under the influence of a magnetic field, and adapted to a peristaltic pump, to mimic the blood flow. This enabled us to analyze the magnetic capture and antitumor effects of magnetically targeted mitoxantrone and immune cells under dynamic conditions. We showed that the magnetic nanoparticle-mediated accumulation increased the anti-tumor effects, and reduced the unspecific distribution of both mitoxantrone and cells. Especially for nanomedical research, investigation of the site-specific targeting of particles, cells or drugs under circulation is important. We conclude that our in vitro setup improves the screening process of nanomedical candidates for cancer treatment.
CRIS-Team WoS Importer:2022-12-30
Keywords: superparamagnetic iron oxide nanoparticles (SPION); magnetic drug targeting (MDT); magnetic cell targeting (MCT)

In Vivo Study on Magnetomotive Ultrasound Imaging in the Framework of Nanoparticle based Magnetic Drug Targeting - Fink, Michael; Rupitsch, Stefan; Ermert, Helmut; Lyer, Stefan (Current Directions in Biomedical Engineering, 2020)
Various medical procedures make use of magnetic nanoparticles, such as Magnetic Drug Targeting (MDT), which boosts the demand for imaging modalities that are capable of in vivo visualizing this kind of particles. Magnetomotive Ultrasound is an imaging technique that can detect tissue, which is perfused by magnetic nanoparticles. In this contribution, we investigate the suitability of Magnetomotive Ultrasound to serve as a monitoring system during MDT. With the conducted measurements, it was possible for the first time to observe in vivo the accumulation of iron-oxide nanoparticles during a Magnetic Drug Targeting cancer treatment applied to a small animal (rabbit).
CRIS-Team Scopus Importer:2021-04-19
Keywords: iron-oxide nanoparticles; Magnetic Drug Targeting; Magnetomotive Ultrasound; ultrasonic imaging

Iron oxide nanoparticles in regenerative medicine and tissue engineering - Friedrich, Ralf P.; Cicha, Iwona; Alexiou, Christoph (Nanomaterials, 2021)
In recent years, many promising nanotechnological approaches to biomedical research have been developed in order to increase implementation of regenerative medicine and tissue engineering in clinical practice. In the meantime, the use of nanomaterials for the regeneration of diseased or injured tissues is considered advantageous in most areas of medicine. In particular, for the treatment of cardiovascular, osteochondral and neurological defects, but also for the recovery of functions of other organs such as kidney, liver, pancreas, bladder, urethra and for wound healing, nanomaterials are increasingly being developed that serve as scaffolds, mimic the extracellular matrix and promote adhesion or differentiation of cells. This review focuses on the latest developments in regenerative medicine, in which iron oxide nanoparticles (IONPs) play a crucial role for tissue engineering and cell therapy. IONPs are not only enabling the use of non-invasive observation methods to monitor the therapy, but can also accelerate and enhance regeneration, either thanks to their inherent magnetic properties or by functionalization with bioactive or therapeutic compounds, such as drugs, enzymes and growth factors. In addition, the presence of magnetic fields can direct IONP-labeled cells specifically to the site of action or.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Magnetic drug delivery; Magnetic particles; Magnetic resonance imaging; Nanomedicine; SPION; Superparamagnetic iron oxide nanoparticles

Is Dissection of the Facial Verve avoidable during Surgery for benign Parotid Tumors? Parotid Surgery without Facial Nerve Dissection - Mantsopoulos, K.; Baer, B.; Iro, Heinrich (HNO, 2020)
CRIS-Team WoS Importer:2020-03-13

Is extracapsular dissection for pleomorphic adenoma rather a euphemism for enucleation that jeopardises the intactness of the capsule? - Mantsopoulos, Konstantinos; Iro, A. K.; Sievert, Matti; Mueller, Sarina K.; Agaimy, Abbas; Schapher, Mirco; Koch, Matthias; Iro, Heinrich (British Journal of Oral and Maxillofacial Surgery, 2021)
The aim of this study was to compare several surgical modalities with respect to the incidence of positive margins and focal capsular exposure of pleomorphic adenoma of the parotid gland. The clinical records and histopathological findings of all patients who underwent parotidectomy for pleomorphic adenoma between 2006 and 2020 were retrospectively evaluated (n = 845). The lesion was removed by extracapsular dissection in 577 cases (68%) and facial nerve dissection in 268 (32%). Our analysis did not reveal a statistically significant difference between the examined modalities regarding positive margins (p=0.648) or capsular exposure (p=0.112). Recurrences were detected in 7/845 cases (0.82%) with a mean (range) follow-up time of 82.3 (6-183) months. The choice of surgical method does not seem to have a significant effect on the incidence of positive margins, or on the capsular exposure of a pleomorphic adenoma.
CRIS-Team Scopus Importer:2021-07-30
Keywords: capsule; complete parotidectomy; extracapsular dissection; partial superficial parotidectomy; pleomorphic adenoma; superficial parotidectomy

.: Is Magneto Inductive Testing a Satisfactory Substitute For Destructive Tensile Test of Steel Sheet and Plate?. - Lutz, Barbara; Engel, Ulf; Schwind, Michael (Proc.6th Europ. Conf. on Nondestructive Testing ECNDT'94, Vol. 2, 1994)
None
LFT Import::2019-08-05 (1985)

Is phase locking crucial to improve hearing thresholds in tinnitus patients? - Schulze, Holger; Tziridis, Konstantin (European Journal of Neuroscience, 2023)
Temporal processing of auditory data plays a crucial role in our proposed model of tinnitus development through stochastic resonance (SR). The model assumes a physiological mechanism optimizing auditory information transmission (as quantified by autocorrelation [AC] analysis) into the brain by adding the optimal amount of neuronal noise to otherwise subthreshold signals. We hypothesize that this takes place at the second synapse of the auditory pathway in the dorsal cochlear nucleus (DCN). We propose that after hearing loss, this neuronal noise is increased in the affected frequency band to improve hearing thresholds at the cost of upward propagation of this added noise, which finally may be perceived as tinnitus. We already showed the improvement of hearing thresholds in a large population of patients. Until now, we did not investigate the differences in hearing thresholds based on the biological constraints of early auditory temporal processing (phase locking) that is only possible up to frequencies of 5 kHz. In this report, we grouped our patient database (N = 47,986) according to tinnitus pitch (TP) of below (TP<5kHz) or above (TP>5kHz) the 5 kHz limit or having no tinnitus (NT) and compared their mean audiograms. We found that TP<5kHz patients showed significantly better hearing thresholds than all other patient groups independent of age. No improvement was seen for TP>5kHz patients who even showed worse thresholds than NT patients for high frequencies. These results are further evidence for our SR model of tinnitus development and the existence of AC analysis at the level of the DCN.
CRIS-Team Scopus Importer:2023-06-02
Keywords: audiometry; autocorrelation; dorsal cochlear nucleus; stochastic resonance

Is there a patient population with squamous cell carcinoma of the head and neck region who might benefit from de-intensification of postoperative radiotherapy? - Onbasi, Yonca; Lettmaier, Sebastian; Hecht, Markus; Semrau, Sabine; Iro, Heinrich; Kesting, Marco Rainer; Fietkau, Rainer; Haderlein, Marlen (Strahlentherapie und Onkologie, 2019)
Purpose: The aim of this retrospective study was to evaluate the clinical outcome of a previously defined low-risk patient population with completely resected (R0) squamous cell carcinoma of the oral cavity, oropharynx, larynx (pT1–3, pN0–pN2b), hypopharynx (pT1–2, pN0–pN1), and the indication for postoperative radio(chemo)therapy. Patients and methods: According to predefined criteria, 99 patients with head and neck squamous cell carcinoma (SCC) who were treated at our institution from January 1, 2005 to December 31, 2014, were available for analysis. The Kaplan–Meier method was used for calculating survival and incidence rates. For univariate comparative analysis, the log-rank test was used for analyzing prognostic clinicopathologic parameters. Results: Median follow-up was 67 months. Cumulative overall (OS) and disease-free survival (DFS) were 97.9%/94.7%/88.0% and 96.9%/92.6%/84.7% after 1, 2, and 5 years, respectively. Cumulative incidence of loco-regional recurrence (LRR), distant metastases (DM), and second cancer (SC) were 1.0%/1.0%/4.9%, 0.0%/3.4%/5.8%, and 2.1%/4.2%/13.1%, respectively. In univariate comparative analysis, location of the primary tumor in the oropharynx was a significant predictor for increased OS (p = 0.043) and DFS (p = 0.048). Conclusion: Considering the low disease relapse rates and high rates of therapy-induced late side effects, as well as the increased risk of developing SC, a prospective multicentric trial investigating de-escalation of radiotherapy in this clearly defined low-risk patient population was started and is still recruiting patients (DIREKHT-Trial, NCT02528955).
CRIS-Team Scopus Importer:2019-06-04
Keywords: Disease-free survival; Late side effect; Overall survival; Radio(chemo)therapy; Second cancer

Is there a patient population with squamous cell carcinoma of the head and neck region who might benefit from de-intensification of postoperative radiotherapy? - Onbasi, Yonca; Lettmaier, Sebastian; Hecht, Markus; Semrau, Sabine; Iro, Heinrich; Kesting, Marco Rainer; Fietkau, Rainer; Haderlein, Marlen (Strahlentherapie und Onkologie, 2019)
PURPOSE: The aim of this retrospective study was to evaluate the clinical outcome of a previously defined low-risk patient population with completely resected (R0) squamous cell carcinoma of the oral cavity, oropharynx, larynx (pT1-3, pN0-pN2b), hypopharynx (pT1-2, pN0-pN1), and the indication for postoperative radio(chemo)therapy. PATIENTS AND METHODS: According to predefined criteria, 99 patients with head and neck squamous cell carcinoma (SCC) who were treated at our institution from January 1, 2005 to December 31, 2014, were available for analysis. The Kaplan-Meier method was used for calculating survival and incidence rates. For univariate comparative analysis, the log-rank test was used for analyzing prognostic clinicopathologic parameters. RESULTS: Median follow-up was 67 months. Cumulative overall (OS) and disease-free survival (DFS) were 97.9%/94.7%/88.0% and 96.9%/92.6%/84.7% after 1, 2, and 5 years, respectively. Cumulative incidence of loco-regional recurrence (LRR), distant metastases (DM), and second cancer (SC) were 1.0%/1.0%/4.9%, 0.0%/3.4%/5.8%, and 2.1%/4.2%/13.1%, respectively. In univariate comparative analysis, location of the primary tumor in the oropharynx was a significant predictor for increased OS (p = 0.043) and DFS (p = 0.048). CONCLUSION: Considering the low disease relapse rates and high rates of therapy-induced late side effects, as well as the increased risk of developing SC, a prospective multicentric trial investigating de-escalation of radiotherapy in this clearly defined low-risk patient population was started and is still recruiting patients (DIREKHT-Trial, NCT02528955).
EVALuna2:184476

Is There Sufficient Evidence for Continuous Local Anesthetic Wound Infusions as Postoperative Standard of Care in Patients with Head and Neck Cancer - Reply - Gostian, Magdalena; Gostian, Antoniu-Oreste (JAMA Otolaryngology - Head and Neck Surgery, 2021)
CRIS-Team Scopus Importer:2021-09-10

Joint Segmentation and Sub-pixel Localization in Structured Light Laryngoscopy - Henningson, Jann-Ole; Semmler, Marion; Döllinger, Michael; Stamminger, Marc (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2023)
In recent years, phoniatric diagnostics has seen a surge of interest in structured light-based high-speed video endoscopy, as it enables the observation of oscillating human vocal folds in vertical direction. However, structured light laryngoscopy suffers from practical problems: specular reflections interfere with the projected pattern, mucosal tissue dilates the pattern, and lastly the algorithms need to deal with huge amounts of data generated by a high-speed video camera. To address these issues, we propose a neural approach for the joint semantic segmentation and keypoint detection in structured light high-speed video endoscopy that improves the robustness, accuracy, and performance of current human vocal fold reconstruction pipelines. Major contributions are the reformulation of one channel of a semantic segmentation approach as a single-channel heatmap regression problem, and the prediction of sub-pixel accurate 2D point locations through weighted least squares in a fully-differentiable manner with negligible computational cost. Lastly, we expand the publicly available Human Laser Endoscopic dataset to also include segmentations of the human vocal folds itself. The source code and dataset are available at: github.com/Henningson/SSSLsquared
CRIS-Team Scopus Importer:2023-11-03
Keywords: Human Vocal Folds; Keypoint Detection; Laryngoscopy; Semantic Segmentation

Journal watch: diagnostic nanoparticles - Poettler, Marina; Cicha, Iwona; Lyer, Stefan; Janko, Christina; Friedrich, Ralf P.; Alexiou, Christoph (Nanomedicine, 2017)
EVALuna2:33204

Juvenile Larynxpapillomatose: Therapieoptionen und Literaturübersicht - Hübner, Matthias; Schützenberger, Anne; Traxdorf, Maximilian; Dittrich, Sven; Iro, Heinrich; Mueller, Sarina K. (Monatsschrift Kinderheilkunde, 2022)
Background: Despite various therapeutic options, there is currently no cure for juvenile onset recurrent respiratory laryngeal papillomatosis (JORRP). Additionally, for the majority of these therapeutic options mild to severe side effects have been described. Objective: Analysis of the effects and side effects of previous and current therapeutic options. Discussion of active ingredients, dosage and administrative form of the available drugs. Material and methods: Review of literature and analysis of the therapeutic options concerning effects and side effects, active ingredients, dosage and administrative form. Results: Surgery remains the gold standard of all treatment options. There are multiple therapeutic options in the literature; however, no treatment options currently lead to a complete remission. Maintaining the function, increasing the time interval between interventions and diminishing the papilloma load in cases of recurrence remain the utmost priority. Conclusion: There are several promising therapeutic options for the treatment of JORRP; however, the current data situation is not sufficient for a general recommendation or guidelines. In the future, further prospective studies with a larger patient population/juvenile population are necessary.
CRIS-Team Scopus Importer:2022-09-20
Keywords: Bevacizumab; Human papillomavirus; Laryngeal papillomatosis; Programmed cell death 1 receptor; Vaccine

Juvenile Ovine Ex Vivo Larynges: Phonatory, Histologic, and Micro CT Based Anatomic Analyses - Döllinger, Michael; Wendler, Olaf; Gerstenberger, Claus; Grossmann, Tanja; Semmler, Marion; Sadeghi, Hossein; Gugatschka, Markus (BioMed Research International, 2019)
It is well known that the phonatory process changes during the life span. However, detailed investigations on potential factors concerned are rare. To deal with this issue, we performed extended biomechanical, macro anatomical, and histological analyses of the contributing laryngeal structures in ex vivo juvenile sheep models. Altogether twelve juvenile sheep larynges were analyzed within the phonatory experiments. Three different elongation levels and 16 different flow levels were applied to achieve a large variety of phonatory conditions. Vocal fold dynamics and acoustical and subglottal signals could be analyzed for 431 experimental runs. Subsequently, for six juvenile larynges microcomputed tomography following virtual 3D reconstruction was performed. The remaining six juvenile larynges as well as six ex vivo larynges from old sheep were histologically and immunohistologically analyzed. Results for juveniles showed more consistent dynamical behavior compared to old sheep larynges due to vocal fold tissue alterations during the life span. The phonatory process in juvenile sheep seems to be more effective going along with a greater dynamic range. These findings are supported by the histologically detected higher amounts of elastin and hyaluronic acid in the lamina propria of the juvenile sheep. The 3D reconstructions of the thyro-arytenoid muscles (TAM) showed a symmetrical shape. Intraindividual volume and surface differences of the TAM were small and comparable to those of aged sheep. However, TAM dimensions were statistically significant smaller for juvenile larynges. Finally, topographical landmarks were introduced for later comparison with other individuals and species. This work resulted in detailed functional, immunohistological, and anatomical information that was not yet reported. This data will also provide reference information for therapeutic strategies regarding aging effects, e.g. laryngeal muscle treatment by functional electrical stimulation.
CRIS-Team WoS Importer:2019-03-29

Juvenile recurrent parotitis: a retrospective comparison of sialendoscopy versus conservative therapy - Schneider, Helgard; Koch, Michael; Künzel, Julian; Gillespie, M. Boyd; Grundtner, Philipp; Iro, Heinrich; Zenk, Johannes (Laryngoscope, 2014)
There are several therapeutic approaches to treat juvenile recurrent parotitis. The aim of this study was to compare sialendoscopy, including prophylactic cortisone irrigation, with observation and a conservative approach of antibiotic therapy alone.Retrospective study, tertiary clinical center.The charts of patients treated for juvenile recurrent parotitis between November 2004 and June 2011 were reviewed. Initial acute flares were always treated with a course of antibiotics. Subsequent treatment consisted of either salivary gland endoscopy including cortisone irrigation or additional pure antibiotic therapy. Patients treated with salivary endoscopy were compared to patients treated with antibiotics alone with regard to the number of inflammatory episodes and pain intensity pre- and posttreatment.Thirty-six patients were treated during the period of study, 15 with salivary endoscopy with cortisone irrigation and 21 with antibiotic therapy alone. A significant reduction in recurrent episodes and pain intensity following therapy was found in both groups. With respect to these two outcomes, the comparison showed two therapeutic options of equal merit.Salivary gland endoscopy is an option in the management of juvenile recurrent parotitis that helps in confirming the diagnosis and that also provides therapeutic intervention. However, although there are further advantages, the definitive value of salivary gland endoscopy requires ongoing evaluation in further prospective studies.4.
EVALuna2:19939

Kehlkopfmodelle in der Stimmforschung und ihre Anwendung - Kniesburges, Stefan (Sprache, Stimme, Gehör, 2023)
In this work, different types of larynx models are introduced and their applications with regard to voice generation are shown with two examples: ventricular folds impact and endoscopic evaluation of vocal fold tissue characteristics.
CRIS-Team Scopus Importer:2023-09-22
Keywords: computer simulation; laryngeal endoscopy; Larynx models; voice generation

Kinetic Effects of Transferrin-Conjugated Gold Nanoparticles on the Antioxidant Glutathione-Thioredoxin Pathway - Sebastian, Sonia; Hoffmann, Manuela Klingler; Howard, Douglas; Young, Clifford; Washington, Jenni; Unterweger, Harald; Alexiou, Christoph; Turnbull, Tyron; D’Andrea, Richard; Hoffmann, Peter; Kempson, Ivan (Antioxidants, 2023)
Nanoparticle-based therapeutics are being clinically translated for treating cancer. Even when thought to be biocompatible, nanoparticles are being increasingly identified as altering cell regulation and homeostasis. Antioxidant pathways are important for maintaining cell redox homeostasis and play important roles by maintaining ROS levels within tolerable ranges. Here, we sought to understand how a model of a relatively inert nanoparticle without any therapeutic agent itself could antagonize a cancer cell lines’ antioxidant mechanism. A label-free protein expression approach was used to assess the glutathione-thioredoxin antioxidative pathway in a prostate cancer cell line (PC-3) after exposure to gold nanoparticles conjugated with a targeting moiety (transferrin). The impact of the nanoparticles was also corroborated through morphological analysis with TEM and classification of pro-apoptotic cells by way of the sub-G0/G1 population via the cell cycle and annexin V apoptosis assay. After a two-hour exposure to nanoparticles, major proteins associated with the glutathione-thioredoxin antioxidant pathway were downregulated. However, this response was acute, and in terms of protein expression, cells quickly recovered within 24 h once nanoparticle exposure ceased. The impact on PRDX-family proteins appears as the most influential factor in how these nanoparticles induced an oxidative stress response in the PC-3 cells. An apparent adaptive response was observed if exposure to nanoparticles continued. Acute exposure was observed to have a detrimental effect on cell viability compared to continuously exposed cells. Nanoparticle effects on cell regulation likely provide a compounding therapeutic advantage under some circumstances, in addition to the action of any cytotoxic agents; however, any therapeutic advantage offered by nanoparticles themselves with regard to vulnerabilities specific to the glutathione-thioredoxin antioxidative pathway is highly temporal.
CRIS-Team Scopus Importer:2023-09-08
Keywords: antioxidant; glutathione-thioredoxin; nanoparticle; proteomics; reactive oxygen species; TEM

Kommentar zu „Sialendoskopie bei Sjögren-Syndrom und nach Radiojodtherapie - Iro, Heinrich (Laryngo-Rhino-Otologie, 2023)
CRIS-Team Scopus Importer:2023-08-25

KRAS codon 12 mutations characterize a subset of de novo proliferating “metaplastic” Warthin tumors - Agaimy, Abbas; Mantsopoulos, Konstantinos; Iro, Heinrich; Stöhr, Robert (Virchows Archiv, 2023)
Warthin tumor (WT; synonym: cystadenolymphoma) represents one of the most frequent salivary gland tumors with a frequency equaling or even outnumbering that of pleomorphic adenomas in some series. Histologically, the tumor displays tall columnar oncocytic cells, arranged into two cell-thick layers lining variably cystic glands within an organoid lymphoid stroma. Tumors with exuberant squamous metaplasia in response to FNA-induced or other types of tissue injury/infarction have been referred to as “metaplastic WTs.” However, the same terminology was used for tumors with variable mucinous cell and solid or stratified epidermoid proliferations (occasionally mimicking mucoepidermoid carcinoma), although the “metaplasia concept” has never been proven for the latter. We herein investigated 22 WTs showing prominent mucoepidermoid-like or solid oncocytoma-like proliferations without prior FNA or histological evidence of infarction/ trauma using the TruSight Tumor 15 gene panel and KRAS pyrosequencing. As a control, we tested 11 conventional WTs. No statistically significant differences were observed between the two subcohorts regarding patient’s age and tumor size. Six of 22 (27%) proliferating/ metaplastic WTs revealed oncogenic KRAS mutations clustering at codon 12 (exon 2), while all conventional tumors lacked these mutations. Our findings are in line with a neoplastic nature of the epidermoid/ mucoepidermoid proliferations in non-injured “metaplastic” Warthin tumors. We propose the descriptive term “de novo proliferating Warthin tumor” for this variant to distinguish it from infarcted/inflamed genuine metaplastic Warthin tumor.
CRIS-Team Scopus Importer:2023-02-17
Keywords: Cystadenolymphoma; KRAS mutations; Metaplastic Warthin tumor; Mucoepidermoid carcinoma; Salivary glands; Warthin tumor

Language-Independent Age Estimation from Speech Using Phonological and Phonemic Features - Haderlein, Tino; Middag, Catherine; Hönig, Florian Thomas; Martens, Jean-Pierre; Döllinger, Michael; Schützenberger, Anne; Nöth, Elmar (Springer-verlag, 2015)
Language-independent and alignment-free phonological and phonemic features were applied for automatic age estimation based on voice and speech properties. 110 persons (average: 75.7 years) read the German version of the text "The North Wind and the Sun". For comparison with the automatic approach, five listeners estimated the speakers' age perceptually. Support Vector Regression and feature selection were used to compute the best model of aging. This model was found to use the following features: (a) the percentage of voiced frames, (b) eight phonological features, representing vowel height, nasality in consonants, turbulence, and position of the lips, and finally, (c) seven phonemic features. The latter features might be relevant due to altered articulation because of dentures. The mean absolute error between computed and chronological age was 5.2 years (RMSE: 7.0). It was 7.7 years (RMSE: 9.6) for an optimistic trivial estimator and 10.5 years (RMSE: 11.9) for the average listener.
Keywords: Age estimation; Phonological features; Phonemic features; SVR

Language-Independent Automatic Evaluation of Intelligibility of Chronically Hoarse Persons - Haderlein, Tino; Middag, Catherine; Martens, Jean-Pierre; Döllinger, Michael; Nöth, Elmar (Folia Phoniatrica Et Logopaedica, 2014)
UnivIS-Import:2015-03-09:Pub.2014.tech.IMMD.IMMD5.langua

Laryngeal evidence for the first and second passaggio in professionally trained sopranos - Echternach, Matthias; Burk, Fabian; Koeberlein, Marie; Selamtzis, Andreas; Döllinger, Michael; Burdumy, Michael; Richter, Bernhard; Herbst, Christian Thomas (PLoS ONE, 2017)
INTRODUCTION: Due to a lack of empirical data, the current understanding of the laryngeal mechanics in the passaggio regions (i.e., the fundamental frequency ranges where vocal registration events usually occur) of the female singing voice is still limited. MATERIAL AND METHODS: In this study the first and second passaggio regions of 10 professionally trained female classical soprano singers were analyzed. The sopranos performed pitch glides from A3 (ƒo = 220 Hz) to A4 (ƒo = 440 Hz) and from A4 (ƒo = 440 Hz) to A5 (ƒo = 880 Hz) on the vowel [iː]. Vocal fold vibration was assessed with trans-nasal high speed videoendoscopy at 20,000 fps, complemented by simultaneous electroglottographic (EGG) and acoustic recordings. Register breaks were perceptually rated by 12 voice experts. Voice stability was documented with the EGG-based sample entropy. Glottal opening and closing patterns during the passaggi were analyzed, supplemented with open quotient data extracted from the glottal area waveform. RESULTS: In both the first and the second passaggio, variations of vocal fold vibration patterns were found. Four distinct patterns emerged: smooth transitions with either increasing or decreasing durations of glottal closure, abrupt register transitions, and intermediate loss of vocal fold contact. Audible register transitions (in both the first and second passaggi) generally coincided with higher sample entropy values and higher open quotient variance through the respective passaggi. CONCLUSIONS: Noteworthy vocal fold oscillatory registration events occur in both the first and the second passaggio even in professional sopranos. The respective transitions are hypothesized to be caused by either (a) a change of laryngeal biomechanical properties; or by (b) vocal tract resonance effects, constituting level 2 source-filter interactions.
EVALuna2:33368

Laryngeal High-Speed Videoendoscopy: Sensitivity of Objective Parameters towards Recording Frame Rate - Schützenberger, Anne; Kunduk, Melda; Döllinger, Michael; Alexiou, Christoph; Dubrovskiy, Denis; Semmler, Marion; Seger, Anja; Bohr, Christopher (BioMed Research International, 2016)
The current use of laryngeal high-speed videoendoscopy in clinic settings involves subjective visual assessment of vocal fold vibratory characteristics. However, objective quantification of vocal fold vibrations for evidence-based diagnosis and therapy is desired, and objective parameters assessing laryngeal dynamics have therefore been suggested. This study investigated the sensitivity of the objective parameters and their dependence on recording frame rate. A total of 300 endoscopic high-speed videos with recording frame rates between 1000 and 15 000 fps were analyzed for a vocally healthy female subject during sustained phonation. Twenty parameters, representing laryngeal dynamics, were computed. Four different parameter characteristics were found: parameters showing no change with increasing frame rate; parameters changing up to a certain frame rate, but then remaining constant; parameters remaining constant within a particular range of recording frame rates; and parameters changing with nearly every frame rate. The results suggest that (1) parameter values are influenced by recording frame rates and different parameters have varying sensitivities to recording frame rate; (2) normative values should be determined based on recording frame rates; and (3) the typically used recording frame rate of 4000 fps seems to be too low to distinguish accurately certain characteristics of the human phonation process in detail.
EVALuna2:33209

Laryngeal pressure estimation with a recurrent neural network - Gómez, Pablo; Schützenberger, Anne; Semmler, Marion; Döllinger, Michael (IEEE Journal of Translational Engineering in Health and Medicine, 2019)
Quantifying the physical parameters of voice production is essential for understanding the process of phonation and can aid in voice research and diagnosis. As an alternative to invasive measurements, they can be estimated by formulating an inverse problem using a numerical forward model. However, high-fidelity numerical models are often computationally too expensive for this. This paper presents a novel approach to train a long short-term memory network to estimate the subglottal pressure in the larynx at massively reduced computational cost using solely synthetic training data. We train the network on synthetic data from a numerical two-mass model and validate it on experimental data from 288 high-speed ex vivo video recordings of porcine vocal folds from a previous study. The training requires significantly fewer model evaluations compared with the previous optimization approach. On the test set, we maintain a comparable performance of 21.2% versus previous 17.7% mean absolute percentage error in estimating the subglottal pressure. The evaluation of one sample requires a vanishingly small amount of computation time. The presented approach is able to maintain estimation accuracy of the subglottal pressure at significantly reduced computational cost. The methodology is likely transferable to estimate other parameters and training with other numerical models. This improvement should allow the adoption of more sophisticated, high-fidelity numerical models of the larynx. The vast speedup is a critical step to enable a future clinical application and knowledge of parameters such as the subglottal pressure will aid in diagnosis and treatment selection.
CRIS-Team Scopus Importer:2019-07-16
Keywords: High-speed video; inverse problem; recurrent neural networks; vocal fold dynamics; voice physiology

Letter to the Editor-1 regarding "Extracapsular dissection versus superficial parotidectomy in benign parotid gland tumors: The Vienna Medical School experience" - Mantsopoulos, Konstantinos; Iro, Heinrich (Head and Neck-Journal For the Sciences and Specialties of the Head and Neck, 2018)
EVALuna2:33196

Letter to the editor regarding the "Functional outcomes after extracapsular dissection with partial facial nerve dissection for small and large parotid neoplasms" - Mantsopoulos, Konstantinos; Iro, Heinrich (American Journal of Otolaryngology, 2021)
CRIS-Team WoS Importer:2021-06-25

Limited parotid surgery as sole form of treatment for carefully selected malignant tumours of the parotid gland: Still sufficient on the long-term? - Mantsopoulos, Konstantinos; Thimsen, Vivian; Sievert, Matti; Balk, Matthias; Grundtner, Philipp; Gostian, Antoniu-Oreste; Koch, Michael; Iro, Heinrich (American Journal of Otolaryngology, 2023)
Background: The aim of the study was to investigate the oncological and functional outcome following extracapsular dissection as the sole form of treatment in locally limited low-grade malignant parotid tumours in the long term. Methods: The records of all patients treated for T1-T2 low-grade malignant tumours of the parotid gland solely by means of extracapsular dissection between 2005 and 2017 were studied retrospectively. Results: A total of 16 cases formed our study sample (7 men, 9 women). Their mean age was 50.2 years (21–84 years). Mean follow-up was 107 months (60–201 months). In 6 cases the tumour was an acinic cell carcinoma, in 9 cases a mucoepidermoid carcinoma and in one case a basal cell adenocarcinoma. Regarding the T category, the tumour was Tis in one case, T1 in 12 cases and T2 in three cases. The five-year disease-specific survival rate was 100 %, as was local disease control. Facial nerve function was House-Brackmann grade I without exception. Conclusions: Our study showed very encouraging long-term results following primary extracapsular dissection as the sole surgical therapy for carefully selected low-stage, low-grade, inferiorly located lesions in patients with high compliance. Lay summary: The “one-size-fits-all” strategy of complete parotidectomy with neck dissection might be tantamount to overtreatment by less aggressive cases of parotid cancer. Extracapsular dissection seems to be oncologically sufficient for carefully selected T1-T2 low-grade cases in the long-term in patients with ensured follow-up.
CRIS-Team Scopus Importer:2023-01-06
Keywords: Extracapsular dissection; Facial nerve; Low-grade; Malignant tumour; Parotid gland

Lipiodol injections for optimization of target volume delineation in a patient with a second tumor of the oropharynx: A case report - Haderlein, Marlen; Merten, Ricarda; Stojanovic, Andrea; Speer, Stefan; Scherl, Claudia; Fietkau, Rainer; Ott, Oliver J. (Strahlentherapie und Onkologie, 2015)
Lipiodol injections were administered in the head and neck area to improve gross tumor volume (GTV) definition for small-volume re-irradiation of a 63-year-old previously irradiated patient with a second tumor of the oropharynx in the posterior wall with longitudinal ligament infiltration (cT4cN0cM0).The patient had dialysis-depending renal failure. On diagnostic computed tomography (CT), which was performed with intravenous contrast agent, the tumor in the oropharynx was not detectable. Because of dialysis-depending renal failure comorbidity, no contrast agent was applied in the planning CT and in the diagnostic magnetic resonance imaging (MRI) study. In each cross-sectional imaging study performed, the GTV, especially in craniocaudal extensions, was not safely delineable. Therefore, craniocaudal tumor margins were pharyngoscopically marked with Lipiodol injections, an iodine-containing contrast agent.In a second planning CT, the GTV could be defined with the help of the Lipiodol marks and small-volume re-irradiation was performed. No Lipiodol-associated side effects occurred in the patient.In the present case, the use of Lipiodol injections at the tumor margins facilitated the definition of the GTV.
EVALuna2:18277

Lipotransfer führt zu Verbesserung von Schluck- und Artikulationsstörungen nach mikrochirurgischer Zungenrekonstruktion – ein Fallbericht - Cai, Aijia; Iro, Heinrich; Horch, Raymund E. (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2021)
Atrophy of tongue after free-flap reconstruction often leads to functional problems like dysphagia and articulation disorders. Lipotransfer might resolve this issue. We describe a case of repeated lipotransfer into an atrophied reconstructed tongue. A 66-year-old patient with a squamous cell carcinoma of the tongue underwent hemiglossectomy and reconstruction of the tongue by a free radial forearm flap. After atrophy of the reconstructed tissue, repeated sessions of lipotransfer were undertaken to augment the atrophic tissue. Three sessions of lipotransfer resulted in satisfactory augmentation of the atrophied reconstructed tongue, leading to improvement of dysphagia and articulation. To our knowledge, this is the first report of lipotransfer used to augment a flap inside the oral cavity. We propose this tool as a potential aid to improve typical tongue reconstruction sequelae.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Lipotransfer; Neozunge; Schluckstörung; Sprechstörung; Zungenrekonstruktion

Loading of nuclear autoantigens prototypically recognized by systemic lupus erythematosus sera into late apoptotic vesicles requires intact microtubules and myosin light chain kinase activity - Zirngibl, Matthias; Fuernrohr, B. G.; Janko, Christina; Munoz, L. E.; Voll, R. E.; Gregory, C. D.; Schett, Georg; Herrmann, Martin; Munoz Becerra, Luis (Clinical and Experimental Immunology, 2015)
Most cases of systemic lupus erythematosus (SLE) are characterized by an impaired clearance of apoptotic cells in various tissues. Non-cleared apoptotic waste is considered an immunogen driving the autoimmune response in patients with SLE. During the execution of apoptosis, membrane blebs are formed and filled with cellular components. Here, we evaluate the cytoskeletal pathway(s) responsible for the loading of SLE prototypic nuclear autoantigens into the apoptotic cell-derived membranous vesicles (ACMV) generated during late phases of apoptosis. HeLa cells expressing a fusion protein of histone H2B with green fluorescent protein (GFP) were irradiated with ultraviolet (UV)-B to induce apoptosis. The appearance and trafficking of chromatin-derived material was monitored by fluorescence microscopy. Specific inhibitors of cytoskeletal pathways were employed to identify the motile elements involved in translocation and trafficking of the nuclear components. We observed that immediately after their appearance the ACMV did not contain histone H2B(GFP) ; in this phase the fluorescence was contained in the nuclear remnants and the cytoplasm. Within consecutive minutes the ACMV were loaded with chromatin-derived material, whereas the loading of simultaneously created ACMV with histone H2B(GFP) was not uniform. Some ACMV were preferentially filled and, consequently, showed a remarkably higher histone H2B(GFP) accumulation. Inhibitors of the cytoskeleton revealed that functional microtubules and myosin light chain kinase are required for nuclear shrinkage and loading of nuclear material into the ACMV, respectively.
EVALuna2:12985

Loading of Primary Human T Lymphocytes with Citrate-Coated Superparamagnetic Iron Oxide Nanoparticles Does Not Impair Their Activation after Polyclonal Stimulation - Mühlberger, Marina; Unterweger, Harald; Band, Julia; Lehmann, Christian; Heger, Lukas; Dudziak, Diana; Alexiou, Christoph; Lee, Geoffrey; Janko, Christina (Cells, 2020)
For the conversion of immunologically cold tumors, characterized by a low T cell infiltration, into hot tumors, it is necessary to enrich T cells in the tumor area. One possibility is the use of magnetic fields to direct T cells into the tumor. For this purpose, primary T cells that were freshly isolated from human whole blood were loaded with citrate-coated superparamagnetic iron oxide nanoparticles (SPIONCitrate). Cell toxicity and particle uptake were investigated by flow cytometry and atomic emission spectroscopy. The optimum loading of the T cells without any major effect on their viability was achieved with a particle concentration of 75 mu g Fe/mL and a loading period of 24 h. The cellular content of SPIONCitrate was sufficient to attract these T cells with a magnet which was monitored by live-cell imaging. The functionality of the T cells was only slightly influenced by SPIONCitrate, as demonstrated by in vitro stimulation assays. The proliferation rate as well as the expression of co-stimulatory and inhibitory surface molecules (programmed cell death 1 (PD-1), lymphocyte activation gene 3 (LAG-3), T cell immunoglobulin and mucin domain containing 3 (Tim-3), C-C motif chemokine receptor 7 (CCR7), CD25, CD45RO, CD69) was investigated and found to be unchanged. Our results presented here demonstrate the feasibility of loading primary human T lymphocytes with superparamagnetic iron oxide nanoparticles without influencing their viability and functionality while achieving sufficient magnetizability for magnetically controlled targeting. Thus, the results provide a strong fundament for the transfer to tumor models and ultimately for new immunotherapeutic approaches for cancer treatment.
CRIS-Team WoS Importer:2020-04-21

Local Anesthetic Infusion for Improving Pain From Head and Neck Cancer Surgery Reply - Gostian, Magdalena; Loeser, Johannes; Gostian, Antoniu-Oreste (JAMA Otolaryngology - Head and Neck Surgery, 2021)
CRIS-Team WoS Importer:2021-11-12

Local cancer therapy with magnetic nanoparticles - Tietze, Rainer; Lyer, Stefan; chreiber, Eveline; Mann, Johannes; Dürr, Stephan; Alexiou, Christoph (S. Karger AG, 2011)
The application of nanotechnology for treatment, diagnosis, and monitoring of diseases is summarized under the term nanomedicine. A particularly promising application is attributed to nanoparticular drug delivery systems. The goal of these carrier systems is the selective enrichment of active substances into diseased tissue structures, an increase in bioavailability, a decrease in active substance degradation, and above all the reduction and/or avoidance of unwanted side effects. Apart from numerous nanosystems acting as carriers, the use of iron oxide nanoparticles has to be particularly emphasized. On the one hand those particles are the carriers of the active substance and on the other hand they are also visualizable with conventional imaging techniques (X-ray and magnetic resonance tomography) and can therefore be used for 'theranostic' purposes. Beyond that, they can be employed for hyperthermia, a further important supporting pillar of nanomedicine. Both procedures should lead to personalized and specific therapy, which has medical and socioeconomic relevance in view of the worldwide increasing number of cancer patients.
CRIS-Team Scopus Importer:2022-06-27

Localization of group II and III metabotropic glutamate receptors at pre- and postsynaptic sites of inner hair cell ribbon synapses - Klotz, Lisa; Wendler, Olaf; Frischknecht, Renato; Shigemoto, Ryuichi; Schulze, Holger; Enz, Ralf (The FASEB Journal, 2019)
Glutamate is the major excitatory neurotransmitter in the CNS binding to a variety of glutamate receptors. Metabotropic glutamate receptors (mGluR1 to mGluR8) can act excitatory or inhibitory, depending on associated signal cascades. Expression and localization of inhibitory acting mGluRs at inner hair cells (IHCs) in the cochlea are largely unknown. Here, we analyzed expression of mGluR2, mGluR3, mGluR4, mGluR6, mGluR7, and mGluR8 and investigated their localization with respect to the presynaptic ribbon of IHC synapses. We detected transcripts for mGluR2, mGluR3, and mGluR4 as well as for mGluR7a, mGluR7b, mGluR8a, and mGluR8b splice variants. Using receptor-specific antibodies in cochlear wholemounts, we found expression of mGluR2, mGluR4, and mGluR8b close to presynaptic ribbons. Super resolution and confocal microscopy in combination with 3-dimensional reconstructions indicated a postsynaptic localization of mGluR2 that overlaps with postsynaptic density protein 95 on dendrites of afferent type I spiral ganglion neurons. In contrast, mGluR4 and mGluR8b were expressed at the presynapse close to IHC ribbons. In summary, we localized in detail 3 mGluR types at IHC ribbon synapses, providing a fundament for new therapeutical strategies that could protect the cochlea against noxious stimuli and excitotoxicity.-Klotz, L., Wendler, O., Frischknecht, R., Shigemoto, R., Schulze, H., Enz, R. Localization of group II and III metabotropic glutamate receptors at pre- and postsynaptic sites of inner hair cell ribbon synapses.
CRIS-Team Scopus Importer:2019-12-17
Keywords: cochlea; IHC; mGlu receptor; mGluR

Locoregional metastatic behavior in a complex mosaic of primary malignant tumors of the parotid gland - Varga, Regina; Iro, Ann Kristin; Thimsen, Vivian; Sievert, Matti; Agaimy, Abbas; Balk, Matthias; Rupp, Robin; Grundtner, Philipp; Koch, Michael; Iro, Heinrich; Mantsopoulos, Konstantinos (American Journal of Otolaryngology, 2023)
Background: The aim of the study was to investigate primary locoregional metastatic behavior in a large sample of various malignant tumors of the parotid gland with varying grades following surgical treatment consisting of complete parotidectomy and neck dissection. Methods: The records of all patients treated for primary malignant tumors of the parotid gland by means of complete parotidectomy and neck dissection between 2007 and 2022 were studied retrospectively. Results: 196 patients formed our study sample (98 females, 98 males). The mean age was 65.7 years (22–101 years). 92 cases presented with low-grade subtypes, 19 with intermediate-grade, and 85 with high-grade carcinomas. The locoregional lymphatic network had been invaded in a total of 66/196 cases (33.6 %). The intraparotid lymph nodes were positive in 54/196 cases (27.5 %) and the cervical lymph nodes in 41/196 cases (20.9 %). In 12 out of the 66 cases with a pN+ status, the neck had been invaded without involvement of the intraparotideal lymph nodes (18.2 %). Male patients tended to suffer from more aggressive carcinomas, and high-grade subtypes presented significantly more frequently as locally advanced tumors. Higher grading was significantly associated with the involvement of the parotid (p < 0.001) and cervical (p < 0.001) lymph nodes. Intermediate and low-grade cases presented similar behavior concerning tumorous invasion of the lymphatic network of the parotid gland (p = 0.522) and the neck (p = 0.467). Conclusion: The locoregional metastatic potential of parotid malignant tumors depends upon a variety of histopathologic factors, which have to be considered in the decision-making process concerning the management of locoregional lymph nodes.
CRIS-Team Scopus Importer:2023-07-21
Keywords: High-grade; Low-grade; Malignant tumor; Neck dissection; Parotid gland; Parotidectomy

Long-term follow-up as an indispensable parameter for reliable assessment of the audiologic outcome after middle ear surgery - Mantsopoulos, Konstantinos; Thimsen, Vivian; Goncalves, Miguel; Sievert, Matti; Mueller, Sarina K.; Iro, Heinrich; Hornung, Joachim (American Journal of Otolaryngology, 2021)
CRIS-Team WoS Importer:2021-10-22

Long-term impact of endoscopic orbital decompression on sinonasal-specific quality of life - Mueller, Sarina K.; Miyake, Marcel M.; Lefebvre, Daniel R.; Freitag, Suzanne K.; Bleier, Benjamin S. (Laryngoscope, 2018)
OBJECTIVE: Endoscopic orbital decompression (EOD) is the workhorse surgical intervention for severe thyroid eye disease in Graves disease. Although EOD is a safe and effective procedure, the objective of this study is to determine the impact of orbital decompression on long-term sinonasal-pecific quality of life. METHODS: Retrospective study of 27 patients who underwent EOD by a single surgeon. The primary endpoint was change in preoperative 22-item Sinonasal Outcomes Test (SNOT-22) score at a minimum of 1 year. The secondary endpoint was to determine whether the performance of septoplasty for surgical access in patients without nasal obstruction impacted domain 1 (i.e., rhinologic domain) and total SNOT-22 scores. RESULTS: The mean follow-up was 25.7 ± 11.4 months. Domain 1 scores significantly increased at the first postoperative visit (P ≤ 0.01) and returned to baseline values between 1 and 3 months. At 1 year, significant improvements in both total score and domain 4 and 5 (psychological and sleep dysfunction, respectively) scores were seen (P < 0.01 for all scores). Septoplasty was not associated with a significant change in SNOT-22 score at 1 year (P = 0.48). CONCLUSION: Endoscopic orbital decompression is associated at 1 year with a significant improvement in sinonasal-specific quality of life, which is driven by the psychological and sleep dysfunction domains. Adjunctive septoplasty has no significant impact on SNOT-22 scores. LEVEL OF EVIDENCE: 4. Laryngoscope, 128:785-788, 2018.
EVALuna2:210638

Long-term oncologic and functional outcome in pleomorphic adenomas of the submandibular gland - Mantsopoulos, Konstantinos; Goncalves, Miguel; Schapher, Mirco; Iro, Heinrich (Laryngoscope, 2017)
Objectives: The aim of the study was to evaluate the oncologic and functional long-term outcome after surgical therapy of pleomorphic adenomas of the submandibular gland. Methods: The medical charts of all patients treated for pleomorphic adenomas of the submandibular gland by means of submandibulectomy between 2000 and 2016 were studied retrospectively. Patients who had had revision after external primary surgery, as well as patients with insufficient data were excluded from our study sample. Results: A total of 75 patients formed our study sample (28 men, 47 women, male:female ratio 0.59:1). Their mean age was 48 years (14-78 years). Mean follow-up was 82 months (12-170 months). No recurrences of a pleomorphic adenoma could be detected in our study cases. Normal facial nerve function (House-Brackmann grade I) in the direct postoperative phase was shown in 54/75 cases (72%). In the remaining 21/75 cases (28%), mild paresis of the marginal mandibular branch of the facial nerve (House-Brackmann II) could be detected in the direct postoperative phase. All cases with facial palsy had recovered with normal facial nerve function (House-Brackmann I) in 3-6 months. Conclusion: Our study was able to show oncologic and consistently acceptable oncologic and functional outcomes after submandibulectomy for pleomorphic adenomas of the submandibular gland. Level of Evidence: 4.
EVALuna2:33360

Long-term performance assessment of fully automatic biomedical glottis segmentation at the point of care - Groh, René; Dürr, Stephan; Schützenberger, Anne; Semmler, Marion; Kist, Andreas (PLoS ONE, 2022)
Deep Learning has a large impact on medical image analysis and lately has been adopted for clinical use at the point of care. However, there is only a small number of reports of long-term studies that show the performance of deep neural networks (DNNs) in such an environment. In this study, we measured the long-term performance of a clinically optimized DNN for laryngeal glottis segmentation. We have collected the video footage for two years from an AI-powered laryngeal high-speed videoendoscopy imaging system and found that the footage image quality is stable across time. Next, we determined the DNN segmentation performance on lossy and lossless compressed data revealing that only 9% of recordings contain segmentation artifacts. We found that lossy and lossless compression is on par for glottis segmentation, however, lossless compression provides significantly superior image quality. Lastly, we employed continual learning strategies to continuously incorporate new data into the DNN to remove the aforementioned segmentation artifacts. With modest manual intervention, we were able to largely alleviate these segmentation artifacts by up to 81%. We believe that our suggested deep learning-enhanced laryngeal imaging platform consistently provides clinically sound results, and together with our proposed continual learning scheme will have a long-lasting impact on the future of laryngeal imaging.
CRIS-Team Scopus Importer:2022-10-07

Long-term results and subjective outcome after gland-preserving treatment in parotid duct stenosis - Koch, Michael; Künzel, Julian; Iro, Heinrich; Psychogios, Georgios; Zenk, Johannes (Laryngoscope, 2014)
To assess the objective long-term results and subjective outcome after treatment of Stensen's duct stenosis.Retrospective study at a tertiary center.The long-term results after treatment with a minimally invasive regimen focusing on sialendoscopy were assessed in 82 patients with 98 parotid duct stenoses after primary gland-preserving treatment. A questionnaire was used to assess the patients' perception of success, including clinical parameters and a visual analogue scale (VAS) assessing pain, symptoms, and salivary gland-related quality of life (QOL). Patients were invited to present for clinical and ultrasound examinations and sialendoscopy.The average follow-up period was 98.48 months. Fifty percent of the patients reported having recurrent gland swelling; but only 19.5% reported recurrent pain and the VAS scores for current symptoms and pain were low. Independent of the type of stenosis, the VAS scores showed a significant reduction in symptoms and improvement in the perceived QOL after the treatment (P = 0.0001 each). Follow-up examinations were carried out in 20.73% of the patients, and sialendoscopy was performed in 12.1% of the patients. After diagnosis, recurrent stenoses (n = 8, 9.75%) were successfully reopened in all cases. The glands were preserved in all of the patients.Long-term evaluation after minimally invasive treatment of stenoses of the parotid duct indicates that high success rates, high rates of gland preservation, and an acceptable subjective patient outcome can be achieved.
EVALuna2:19940

Longterm Results of a Screening Procedure for Adult Cochlear Implant Candidates - Hoppe, Ulrich; Hocke, Thomas; Hast, Anne; Hornung, Joachim (Laryngo-Rhino-Otologie, 2017)
This study gives an estimation of the long term outcome of a screening procedure for cochlear implant candidacy in hearing aid users.In a recent retrospective study, hearing aid performance and audiometric measures in 185 subjects (318 ears) were analyzed. In the context of 2 years follow-up, the outcome of the ipsilateral screening procedure was analyzed. For patients who did receive a cochlear implant, their audiometric outcome measures were viewed into relation to their preoperative results.From the 96 ears identified as cochlear implant candidates, 34 were provided with a cochlear implant. 222 ears were identified as hearing aid users. Only 4 of these 222 ears were provided with a cochlear implant. Cochlear implant recipients with a preoperative speech recognition score with hearing aids above zero showed a mean improvement of 65% points in Freiburg monosyllabics.The audiometry-based screening procedure enables an effective management of the referral process of cochlear implant candidates.
EVALuna2:33174

Long-term stable measurement phantoms for magnetic particle imaging - Woeckel, Lucas; Wells, James; Kosch, Olaf; Lyer, Stefan; Alexiou, Christoph; Gruettner, Cordula; Wiekhorst, Frank; Dutz, Silvio (Journal of Magnetism and Magnetic Materials, 2019)
Magnetic particle imaging (MPI) is a tomographic imaging method to determine the spatial distribution of magnetic nanoparticles (MNP) within a defined volume. To evaluate the imaging capabilities of existing MPI scanners, their sensitivity and image resolution limits have to be analyzed. Therefore, precisely defined structures (phantoms) with various tracer concentrations are required to enable comparative studies between existing MPI systems. To support the development of capable MPI phantoms, we developed a method to incorporate different commercially available MNP into a long-term stable synthetic polymer with an iron concentration of up to 200 mmol/l. The properties of each type of polymer matrix embedded MNP were tested by magnetic particle spectroscopy (MPS). For shaping the particle loaded polymer to a phantom, we used 3-D printed molds with a structure cross section of 2 x 2 mm(2). The particle loads within the phantoms were then imaged using MPI. The particle-loaded polymer is very suitable for preparation of measurement phantoms that could be visualized by MPI. Repeated shore hardness and MPS measurements up to one year did not reveal any changes in the mechanical and magnetic properties of the used material. In conclusion, we developed long-term stable measurement phantoms for magnetic particle imaging. Further work will focus on more detailed particle loaded structures in phantoms and water based polymers with a more homogeneous particle distribution.
CRIS-Team WoS Importer:2019-02-21

Low-grade (polymorphous) adenocarcinoma of the middle ear mimicking a jugulotympanic paraganglioma - Mantsopoulos, Konstantinos; Fietkau, Rainer; Hornung, Joachim; Agaimy, Abbas; Iro, Heinrich; Taha, Lava (HNO, 2021)
A 64-year-old female patient presented with otalgia and hearing loss in the right ear. On otoscopy, the right tympanic membrane was highly vascularized and bulged into the anteroinferior quadrant. High-resolution computed tomography revealed an osteolytic lesion with occupation of the hypotympanum extending into the petrous apex and right parapharyngeal space as well as infiltration of the wall of the right internal carotid artery. MRI strengthened the suspicion of a jugulotympanic paraganglioma. The biopsy material obtained through exploratory tympanotomy was assessed as a low-grade polymorphic adenocarcinoma. The tumor was treated with definitive chemoradiotherapy. Posttherapeutic imaging after 4 months did not show any evidence of tumor progression.
CRIS-Team WoS Importer:2021-06-18

Low-grade (polymorphous) adenocarcinoma of the middle ear mimicking a jugulotympanic paraganglioma. German version - Mantsopoulos, Konstantinos; Fietkau, Rainer; Hornung, Joachim; Agaimy, Abbas; Iro, Heinrich; Taha, Lava (HNO, 2021)
A 64-year-old female patient presented with otalgia and hearing loss in the right ear. On otoscopy, the right tympanic membrane was highly vascularized and bulged into the anteroinferior quadrant. High-resolution computed tomography revealed an osteolytic lesion with occupation of the hypotympanum extending into the petrous apex and right parapharyngeal space as well as infiltration of the wall of the right internal carotid artery. MRI strengthened the suspicion of a jugulotympanic paraganglioma. The biopsy material obtained through exploratory tympanotomy was assessed as a low-grade polymorphic adenocarcinoma. The tumor was treated with definitive chemoradiotherapy. Posttherapeutic imaging after 4 months did not show any evidence of tumor progression.
CRIS-Team WoS Importer:2021-05-07

Low-light image enhancement of high-speed endoscopic videos using a convolutional neural network - Gómez, Pablo; Semmler, Marion; Schützenberger, Anne; Bohr, Christopher; Döllinger, Michael (Medical & Biological Engineering & Computing, 2019)
Laryngeal endoscopy is one of the primary diagnostic tools for laryngeal disorders. The main techniques are videostroboscopy and lately high-speed video endoscopy. Unfortunately, due to the restricting anatomy of the larynx and technical limitations of the recording equipment, many videos suffer from insufficient illumination, which complicates clinical examination and analysis. This work presents an approach to enhance low-light images from high-speed video endoscopy using a convolutional neural network. We introduce a new technique to generate realistically darkened training samples using Perlin noise. Extensive data augmentation is employed to cope with the limited training data allowing training with just 55 videos. The approach is compared against four state-of-the-art low-light enhancement methods and statistically significantly outperforms each on a no-reference (NIQE) and two full-reference (PSNR, SSIM) image quality metrics. The presented approach can be run on consumer-grade hardware and is thereby directly applicable in a clinical context. It is likely transferable to similar techniques such as videostroboscopy.
CRIS-Team WoS Importer:2019-07-12

Lymphatic Vessels in Chronic Rhinosinusitis - Pesold, Vanessa; Wendler, Olaf; Gröhn, Franziska; Mueller, Sarina K. (Journal of Inflammation Research, 2024)
Purpose: The purpose of this study was to analyze the nasal lymphatic system in order to uncover novel factors that might be involved in pathogenesis of chronic rhinosinusitis (CRS) with (CRSwNP) and without nasal polyps (CRSsNP). Patients and Methods: Lymphatic vessels (LVs) and macrophages were localized and counted in the inferior and middle turbinate, the uncinate process and the ethmoid of CRSwNP and CRSsNP patients, the NP and the inferior turbinate of controls (n≥6 per group). Lysates of the same tissue types (n=7 per group) were analyzed for lymphatic vessel endothelial receptor 1 (LYVE-1), for matrix metalloproteinase 14 (MMP-14) and for Hyaluronic acid (HA) using ELISA. HA was localized in sections of CRSwNP NP, CRSsNP ethmoid and control inferior turbinate (n=6 per group). The results of HA levels were correlated to the number of macrophages in tissues. The nasal secretions of CRSwNP (n=28), CRSsNP (n=30), and control (n=30) patients were analyzed for LYVE-1 and HA using ELISA. Results: The number of LVs was significantly lower in tissues of both CRS groups compared to the control. In the tissue lysates, LYVE-1 expression differed significantly between the CRSwNP tissues with a particularly high level in the NP. MMP-14 was significantly overexpressed in CRSwNP uncinate process. There were no significant differences in tissue HA expression. In the mucus LYVE-1 was significantly underexpressed in CRSsNP compared to CRSwNP and control, while HA was significantly underexpressed in both CRS groups. In the NP, HA and macrophages were accumulated particularly below the epithelium. Tissue levels of HA revealed a significant positive correlation with the number of macrophages. Conclusion: CRS might be associated with an insufficient clearing of the nasal mucosa through the lymphatics. The accumulation of HA and macrophages might promote inflammation, fluid retention, and polyp formation. These results may provide novel CRS-associated factors.
CRIS-Team Scopus Importer:2024-03-15
Keywords: chronic rhinosinusitis; chronic rhinosinusitis with nasal polyps; hyaluronic acid; inflammation; lymphangiogenesis; mucus

Lymph node ratio as a predictor of outcome in patients with oropharyngeal cancer - Künzel, Julian; Psychogios, Georgios; Mantsopoulos, Konstantinos; Grundtner, Philipp; Waldfahrer, Frank; Iro, Heinrich (European Archives of Oto-Rhino-Laryngology, 2014)
To evaluate the utility of lymph node ratio (LNR) as a potential prognostic predictor and to test whether LNR may be useful as a potential selection criterion for adjuvant treatment in patients with oropharyngeal squamous cell carcinoma (OPSSC). This retrospective study included 384 patients with regionally metastasized OPSCC who underwent primary surgery with or without adjuvant therapy from 1980 to 2010. LNR was calculated as the ratio of positive lymph nodes to the total number of lymph nodes removed during neck dissection. Statistical analysis using a Cox regression model was carried out. The 5-year disease-specific survival (DSS) was 73%. An individual LNR peak at 0.1 was closest to the median of 0.0909, and both were set as cut-off values. Patients in the group greater than median had a hazard ratio (HR) of 2.472 for a DSS event; this was close to an HR of 2.513 for LNR >0.1. In multivariate analysis, LNR showed a markedly stronger HR with regard to survival in comparison with the grouped pN classification. The covariate treatment modality did not meet the assumption of the Cox regression, and it was therefore not possible to comment reasonably on the issue of whether LNR could be a potential selection criterion for adjuvant treatment. Lymph node ratio is in itself a valuable additional prognostic factor for risk stratification. According to the current results, the most valuable LNR for OPSSC is expected to be located in the range from 0.09 to 0.1. Further investigations in large prospective trials will be required to allow evidence-based recommendations for treatment decisions based on the LNR.
EVALuna2:19931

Lymph node ratio is of limited value for the decision-making process in the treatment of patients with laryngeal cancer - Kuenzel, Julian; Mantsopoulos, Konstantinos; Psychogios, Georgios; Agaimy, Abbas; Grundtner, Philipp; Koch, Michael; Iro, Heinrich (European Archives of Oto-Rhino-Laryngology, 2015)
The lymph node ratio (LNR) combines two types of information–about the extent of neck dissection and about the extent of the pathological examination of the specimen–and thus represents an interesting variable for risk assessment in patients with head and neck cancer. This retrospective study with data from January 1, 1980, to December 31, 2010, evaluates the utility of the LNR as a potential prognostic predictor in patients with laryngeal squamous cell carcinoma (LSCC). A total of 202 consecutive patients with regionally metastasized LSCC who underwent primary surgery with or without adjuvant treatment were included. The mean follow-up period was 4.4 years. The LNR was calculated as the ratio of positive nodes to the total number of nodes removed during neck dissection. Multivariate analysis was carried out. Peak values as averaged clusters of individual LNRs were registered at three points (LNR 0.05, 0.07, and 0.09). LNR 0.09 was a significant prognostic parameter in the Cox regression model (P = 0.007). Patients with an LNR > 0.09 had a hazard ratio of 2.065 for a disease-specific survival event in comparison with LNR < 0.09. The most accurate LNR for LSCC is expected to be located in the range of 0.08-0.1. The LNR seems to be of limited value for the decision-making process in the treatment of patients with LSCC, in comparison with other locations. Prospective trials will be required in order to allow evidence-based recommendations for treatment decisions based on the LNR.
EVALuna2:6680

Lysosome-targeting amplifiers of reactive oxygen species as anticancer prodrugs - Daum, Steffen; Reshetnikov, Viktor; Sisa, Miroslav; Dumych, Tetyana; Lootsik, Maxim D.; Bilyy, Rostyslav; Bila, Evgenia; Janko, Christina; Alexiou, Christoph; Herrmann, Martin; Sellner, Leopold; Mokhir, Andriy (Angewandte Chemie-International Edition, 2017)
Cancer cells produce elevated amounts of reactive oxygen species that has been used to design cancer specific prodrugs. Their activation relies on at least a bimolecular process, where a prodrug reacts with ROS. However, at low µM concentrations of the prodrugs and ROS the activation is usually inefficient. Herein we suggested and validated a potentially general approach for solving this intrinsic problem of ROS-dependent prodrugs. In particular, known 4-(N-ferrocenyl-N-benzylaminocarbonyloxymethyl)phenylboronic acid pinacol ester was converted to its lysosome specific analogue. Since lysosomes contain the higher concentration of active ROS than cytoplasm, activation of the latter prodrug was facilitated with respect to the parent compound. In particular, it was found to exhibit high anticancer activity in a variety of cancer cell lines (IC50 3.5-7.2 µM) and in vivo (40 mg/kg, NK/Ly murine model), but remained weakly toxic towards non-malignant cells (IC50 15-30 µM).
EVALuna2:13450

Machine Learning-assisted immunophenotyping of peripheral blood identifies innate immune cells as best predictor of response to induction chemo-immunotherapy in head and neck squamous cell carcinoma – knowledge obtained from the CheckRad-CD8 trial - Hecht, Markus; Frey, Benjamin; Gaipl, Udo; Tianyu, Xie; Eckstein, Markus; Donaubauer, Anna-Jasmina; Klautke, Gunther; Illmer, Thomas; Fleischmann, Maximilian; Laban, Simon; Hautmann, Matthias G.; Tamaskovics, Bálint; et al. (Neoplasia, 2024)
Purpose: Individual prediction of treatment response is crucial for personalized treatment in multimodal approaches against head-and-neck squamous cell carcinoma (HNSCC). So far, no reliable predictive parameters for treatment schemes containing immunotherapy have been identified. This study aims to predict treatment response to induction chemo-immunotherapy based on the peripheral blood immune status in patients with locally advanced HNSCC. Methods: The peripheral blood immune phenotype was assessed in whole blood samples in patients treated in the phase II CheckRad-CD8 trial as part of the pre-planned translational research program. Blood samples were analyzed by multicolor flow cytometry before (T1) and after (T2) induction chemo-immunotherapy with cisplatin/docetaxel/durvalumab/tremelimumab. Machine Learning techniques were used to predict pathological complete response (pCR) after induction therapy. Results: The tested classifier methods (LDA, SVM, LR, RF, DT, and XGBoost) allowed a distinct prediction of pCR. Highest accuracy was achieved with a low number of features represented as principal components. Immune parameters obtained from the absolute difference (lT2-T1l) allowed the best prediction of pCR. In general, less than 30 parameters and at most 10 principal components were needed for highly accurate predictions. Across several datasets, cells of the innate immune system such as polymorphonuclear cells, monocytes, and plasmacytoid dendritic cells are most prominent. Conclusions: Our analyses imply that alterations of the innate immune cell distribution in the peripheral blood following induction chemo-immuno-therapy is highly predictive for pCR in HNSCC.
CRIS-Team Scopus Importer:2024-01-26
Keywords: Chemotherapy; HNSCC; Immune phenotyping; Immunotherapy; Induction therapy

Machine learning based estimation of hoarseness severity from sustained vowels - Schraut, Tobias; Schützenberger, Anne; Arias Vergara, Tomás; Kunduk, Melda; Echternach, Matthias; Döllinger, Michael (Journal of the Acoustical Society of America, 2022)
Acoustic assessment of voice impairment is commonly performed by subjective perceptual evaluation of continuous speech based on a grading system such as the roughness, breathiness, hoarseness (RBH) scale. Here, we present an automatic approach to objectively quantify hoarseness severity based on sustained vowels. For this study, a total of 635 recordings of the sustained vowel /a/ were collected. Temporal, spectral and cepstral features were extracted from one second of each recording. All recordings have an assigned RBH value, which was determined subjectively by an expert based on continuous speech of the respective subject. In order to account for the label noise introduced by different valuation bases, subjects were divided into two levels of hoarseness H < 2 and H ≥ 2. Logistic Regression was employed as classification model, using the resulting output probabilities as continuous severity rating. Relevant features were selected using a sequence of filter methods and backward elimination. The original feature set was reduced from 50 to 5 features. A classification accuracy of 86.73% was achieved on the test set. Detailed evaluation of output probabilities shows strong correlation (r = 0.81) with H values, allowing to capture and quantify individual improvement, deterioration or no change of hoarseness at different points in time, e.g. before and after voice therapy. The presented method describes a promising approach for objective evaluation of hoarseness, allowing to quantify treatment progress for patients with voice disorders.<br
Keywords: Speech communication; Acoustics; Vowel systems; Machine learning

Machine learning based estimation of hoarseness severity using sustained vowelsa) - Schraut, Tobias; Schützenberger, Anne; Arias Vergara, Tomás; Kunduk, Melda; Echternach, Matthias; Döllinger, Michael (Journal of the Acoustical Society of America, 2024)
Auditory perceptual evaluation is considered the gold standard for assessing voice quality, but its reliability is limited due to inter-rater variability and coarse rating scales. This study investigates a continuous, objective approach to evaluate hoarseness severity combining machine learning (ML) and sustained phonation. For this purpose, 635 acoustic recordings of the sustained vowel /a/ and subjective ratings based on the roughness, breathiness, and hoarseness scale were collected from 595 subjects. A total of 50 temporal, spectral, and cepstral features were extracted from each recording and used to identify suitable ML algorithms. Using variance and correlation analysis followed by backward elimination, a subset of relevant features was selected. Recordings were classified into two levels of hoarseness, H < 2 and H ≥ 2 , yielding a continuous probability score y ̂ ∈ [ 0 , 1 ] . An accuracy of 0.867 and a correlation of 0.805 between the model's predictions and subjective ratings was obtained using only five acoustic features and logistic regression (LR). Further examination of recordings pre- and post-treatment revealed high qualitative agreement with the change in subjectively determined hoarseness levels. Quantitatively, a moderate correlation of 0.567 was obtained. This quantitative approach to hoarseness severity estimation shows promising results and potential for improving the assessment of voice quality.
CRIS-Team Scopus Importer:2024-02-02

Machine learning based identification of relevant parameters for functional voice disorders derived from endoscopic high-speed recordings - Schlegel, Patrick; Kniesburges, Stefan; Dürr, Stephan; Schützenberger, Anne; Döllinger, Michael (Scientific Reports, 2020)
In voice research and clinical assessment, many objective parameters are in use. However, there is no commonly used set of parameters that reflect certain voice disorders, such as functional dysphonia (FD); i.e. disorders with no visible anatomical changes. Hence, 358 high-speed videoendoscopy (HSV) recordings (159 normal females (NF), 101 FD females (FDF), 66 normal males (NM), 32 FD males (FDM)) were analyzed. We investigated 91 quantitative HSV parameters towards their significance. First, 25 highly correlated parameters were discarded. Second, further 54 parameters were discarded by using a LogitBoost decision stumps approach. This yielded a subset of 12 parameters sufficient to reflect functional dysphonia. These parameters separated groups NF vs. FDF and NM vs. FDM with fair accuracy of 0.745 or 0.768, respectively. Parameters solely computed from the changing glottal area waveform (1D-function called GAW) between the vocal folds were less important than parameters describing the oscillation characteristics along the vocal folds (2D-function called Phonovibrogram). Regularity of GAW phases and peak shape, harmonic structure and Phonovibrogram-based vocal fold open and closing angles were mainly important. This study showed the high degree of redundancy of HSV-voice-parameters but also affirms the need of multidimensional based assessment of clinical data.
CRIS-Team Scopus Importer:2020-07-10

Magnetic accumulation of spions under arterial flow conditions: Effect of serum and red blood cells - Hennig, Till L.; Unterweger, Harald; Lyer, Stefan; Alexiou, Christoph; Cicha, Iwona (Molecules, 2019)
Magnetic drug targeting utilizes an external magnetic field to target superparamagnetic iron oxide nanoparticles (SPIONs) and their cargo to the diseased vasculature regions. In the arteries, the flow conditions affect the behavior of magnetic particles and the efficacy of their accumulation. In order to estimate the magnetic capture of SPIONs in more physiological-like settings, we previously established an ex vivo model based on human umbilical cord arteries. The artery model was employed in our present studies in order to analyze the effects of the blood components on the efficacy of magnetic targeting, utilizing 2 types of SPIONs with different physicochemical characteristics. In the presence of freshly isolated human plasma or whole blood, a strong increase in iron content measured by AES was observed for both particle types along the artery wall, in parallel with clotting activation due to endogenous thrombin generation in plasma. Subsequent studies therefore utilized SPION suspensions in serum and washed red blood cells (RBCs) at hematocrit 50%. Interestingly, in contrast to cell culture medium suspensions, magnetic accumulation of circulating SPION-3 under the external magnet was achieved in the presence of RBCs. Taken together, our data shows that the presence of blood components affects, but does not prevent, the magnetic accumulation of circulating SPIONs.
CRIS-Team Scopus Importer:2019-08-02
Keywords: Blood cells; Ex vivo flow model; Magnetic targeting; Nanoparticle accumulation; SPIONs

Magnetically responsive composites: Electron beam assisted magnetic nanoparticle arrest in gelatin hydrogels for bioactuation - Deuflhard, Marie; Eberbeck, Dietmar; Hietschold, Philine; Wilharm, Nils; Mühlberger, Marina; Friedrich, Ralf P.; Alexiou, Christoph; Mayr, Stefan G. (Physical Chemistry Chemical Physics, 2019)
As emerging responsive materials, ferrogels have become highly attractive for biomedical and technical applications in terms of soft actuation, tissue engineering or controlled drug release. In the present study, bioderived ferrogels were fabricated and successfully deformed within moderate, heterogeneous magnetic fields. Synthesis was realized by arresting iron oxide nanoparticles in porcine gelatin by introduction of covalent crosslinks via treatment with energetic electrons for mesh refinement. This approach also allows for tuning thermal and mechanical stability of the gelatin matrix. Operating the bioferrogel in compression, magnetic forces on the nanoparticles are counterbalanced by the stiffness of the hydrogel matrix that is governed by a shift in thermodynamic equilibrium of swelling, as derived in the framework of osmosis. As gelatin and iron oxide nanoparticles are established as biocompatible constituents, these findings promise potential for in vivo use as contactless mechanical transducers.
CRIS-Team Scopus Importer:2019-07-23

Magnetic drug targeting reduces the chemotherapeutic burden on circulating leukocytes - Janko, Christina; Dürr, Stephan; Munoz, Luis Enrique; Lyer, Stefan; Chaurio, Ricardo; Tietze, Rainer; Von Loehneysen, Sarah; Schorn, Christine; Herrmann, Martin; Alexiou, Christoph (International Journal of Molecular Sciences, 2013)
Magnetic drug targeting (MDT) improves the integrity of healthy tissues and cells during treatment with cytotoxic drugs. An anticancer drug is bound to superparamagnetic iron oxide nanoparticles (SPION), injected into the vascular supply of the tumor and directed into the tumor by means of an external magnetic field. In this study, we investigated the impact of SPION, mitoxantrone (MTO) and SPIONMTO on cell viability in vitro and the nonspecific uptake of MTO into circulating leukocytes in vivo. MDT was compared with conventional chemotherapy. MTO uptake and the impact on cell viability were assessed by flow cytometry in a Jurkat cell culture. In order to analyze MTO loading of circulating leukocytes in vivo, we treated tumor-bearing rabbits with MDT and conventional chemotherapy. In vitro experiments showed a dose-dependent MTO uptake and reduction in the viability and proliferation of Jurkat cells. MTO and SPIONMTO showed similar cytotoxic activity. Non-loaded SPION did not have any effect on cell viability in the concentrations tested. Compared with systemic administration in vivo, MDT employing SPIONMTO significantly decreased the chemotherapeutic load in circulating leukocytes. We demonstrated that MDT spares the immune system in comparison with conventional chemotherapy. © 2013 by the authors; licensee MDPI, Basel, Switzerland.
CRIS-Team Scopus Importer:2022-06-27
Keywords: Chemotherapy; Immune system; Iron oxide nanoparticles; Leukocytes; Magnetic drug targeting; Mitoxantrone

Magnetic drug targeting to vascular injury regions and atherosclerotic lesions: in vivo pilot study - Cicha, Iwona; Matuszak, Jasmin; Lutz, Barbara; Alexiou, Christoph; Lyer, Stefan (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

Magnetic hybrid materials interact with biological matrices - Gräfe, Christine; Müller, Elena K.; Gresing, Lennart; Weidner, Andreas; Radon, Patricia; Friedrich, Ralf P.; Alexiou, Christoph; Wiekhorst, Frank; Dutz, Silvio; Clement, Joachim H. (Physical Sciences Review, 2020)
Magnetic hybrid materials are a promising group of substances. Their interaction with matrices is challenging with regard to the underlying physical and chemical mechanisms. But thinking matrices as biological membranes or even structured cell layers they become interesting with regard to potential biomedical applications. Therefore, we established in vitro blood-organ barrier models to study the interaction and processing of superparamagnetic iron oxide nanoparticles (SPIONs) with these cellular structures in the presence of a magnetic field gradient. A one-cell-type-based blood-brain barrier model was used to investigate the attachment and uptake mechanisms of differentially charged magnetic hybrid materials. Inhibition of clathrin-dependent endocytosis and F-actin depolymerization led to a dramatic reduction of cellular uptake. Furthermore, the subsequent transportation of SPIONs through the barrier and the ability to detect these particles was of interest. Negatively charged SPIONs could be detected behind the barrier as well as in a reporter cell line. These observations could be confirmed with a two-cell-type-based blood-placenta barrier model. While positively charged SPIONs heavily interact with the apical cell layer, neutrally charged SPIONs showed a retarded interaction behavior. Behind the blood-placenta barrier, negatively charged SPIONs could be clearly detected. Finally, the transfer of the in vitro blood-placenta model in a microfluidic biochip allows the integration of shear stress into the system. Even without particle accumulation in a magnetic field gradient, the negatively charged SPIONs were detectable behind the barrier. In conclusion, in vitro blood-organ barrier models allow the broad investigation of magnetic hybrid materials with regard to biocompatibility, cell interaction, and transfer through cell layers on their way to biomedical application.
CRIS-Team Scopus Importer:2021-04-19
Keywords: biocompatibility; magnetic nanoparticles; particle-cell interaction

Magnetic microgels for drug targeting applications: Physical–chemical properties and cytotoxicity evaluation - Turcu, Rodica; Craciunescu, Izabell; Garamus, Vasil M.; Janko, Christina; Lyer, Stefan; Tietze, Rainer; Alexiou, Christoph; Vekas, Ladislau (Journal of Magnetism and Magnetic Materials, 2014)
Magnetoresponsive microgels with high saturation magnetization values have been obtained by a strategy based on the miniemulsion method using high colloidal stability organic carrier ferrofluid as primary material. Hydrophobic nanoparticles Fe3O4/oleic acid are densely packed into well-defined spherical nanoparticle clusters coated with polymers with sizes in the range 40–350 nm. Physical– chemical characteristics of magnetic microgels were investigated by TEM, SAXS, XPS and VSM measurements with the focus on the structure–properties relationship. The impact of magnetic microgels loaded with anticancer drug mitoxantrone (MTO) on the non-adherent human T cell leukemia loaded MTO penetrate into cells and both induce apoptosis and later secondary necrosis in a time- and dose dependent manner. In contrast, microgels without MTO are not cytotoxic in the corresponding concentrations. Our results show that MTO-loaded microgels are promising structures for application in magnetic drug targeting.
EAM Import::2019-03-12

Magnetic nanoparticle-based drug delivery for cancer therapy - Tietze, Rainer; Zaloga, Jan; Unterweger, Harald; Lyer, Stefan; Friedrich, Ralf P.; Janko, Christina; Pöttler, Marina; Dürr, Stephan; Alexiou, Christoph (Biochemical and Biophysical Research Communications, 2015)
Nanoparticles have belonged to various fields of biomedical research for quite some time. A promising site-directed application in the field of nanomedicine is drug targeting using magnetic nanoparticles which are directed at the target tissue by means of an external magnetic field. Materials most commonly used for magnetic drug delivery contain metal or metal oxide nanoparticles, such as superparamagnetic iron oxide nanoparticles (SPIONs). SPIONs consist of an iron oxide core, often coated with organic materials such as fatty acids, polysaccharides or polymers to improve colloidal stability and to prevent separation into particles and carrier medium [1]. In general, magnetite and maghemite particles are those most commonly used in medicine and are, as a rule, well-tolerated. The magnetic properties of SPIONs allow the remote control of their accumulation by means of an external magnetic field. Conjugation of SPIONs with drugs, in combination with an external magnetic field to target the nanoparticles (so-called "magnetic drug targeting", MDT), has additionally emerged as a promising strategy of drug delivery. Magnetic nanoparticle-based drug delivery is a sophisticated overall concept and a multitude of magnetic delivery vehicles have been developed. Targeting mechanism-exploiting, tumor-specific attributes are becoming more and more sophisticated. The same is true for controlled-release strategies for the diseased site. As it is nearly impossible to record every magnetic nanoparticle system developed so far, this review summarizes interesting approaches which have recently emerged in the field of targeted drug delivery for cancer therapy based on magnetic nanoparticles.
EVALuna2:19928

Magnetic nanoparticle based molecular communication in microfluidic environments - Wicke, Wayan; Ahmadzadeh, Arman; Jamali Kooshkghazi, Vahid; Unterweger, Harald; Alexiou, Christoph; Schober, Robert (IEEE Transactions on Nanobioscience, 2019)
The possibility to guide and control magnetic nanoparticles in a non-invasive manner has spawned various applications in biotechnology, such as targeted drug deliveryandsensingofbiologicalsubstances.Theseapplications are facilitated by the engineering of the size, selective chemical reactivity, and general chemical composition of the employed particles. Motivated by their widespread useandfavorableproperties,inthispaper,weprovideatheoreticalstudyofthepotentialbeneﬁtsofmagneticnanoparticles for the design of molecular communication systems. In particular, we consider a magnetic nanoparticle-based communication in a microﬂuidic channel where an external magnetic ﬁeld is employed to attract the informationcarrying particles to the receiver. We show that the particle transport affected by the Brownian motion, ﬂuid ﬂow, and an external magnetic ﬁeld can be mathematically modeled as diffusion with drift. Thereby, we reveal that the key parameters determining the magnetic force are the particle size and the magnetic ﬁeld gradient. Moreover, we derive an analyticalexpressionfor the channel impulse response, which is used to evaluatethe potentialgain in the expected number of observed nanoparticles due to the magnetic ﬁeld.Furthermore,adoptingthesymbolerrorrateasperformance metric, we show that using magnetic nanoparticles can enable a reliable communication in the presence of disruptive ﬂuid ﬂow. The numerical results obtained by the particle-based simulation validate the accuracy of the derived analyticalexpressions.<br

Magnetic nanoparticle-based molecular communication in microfluidic environments - Wicke, Wayan; Ahmadzadeh, Arman; Jamali, Vahid; Unterweger, Harald; Alexiou, Christoph; Schober, Robert (IEEE Transactions on Nanobioscience, 2019)
The possibility to guide and control magnetic nanoparticles in a non-invasive manner has spawned various applications in biotechnology, such as targeted drug delivery and sensing of biological substances. These applications are facilitated by the engineering of the size, selective chemical reactivity, and general chemical composition of the employed particles. Motivated by their widespread use and favorable properties, in this paper, we provide a theoretical study of the potential benefits of magnetic nanoparticles for the design of molecular communication systems. In particular, we consider a magnetic nanoparticle-based communication in a microfluidic channel where an external magnetic field is employed to attract the information-carrying particles to the receiver. We show that the particle transport affected by the Brownian motion, fluid flow, and an external magnetic field can be mathematically modeled as diffusion with drift. Thereby, we reveal that the key parameters determining the magnetic force are the particle size and the magnetic field gradient. Moreover, we derive an analytical expression for the channel impulse response, which is used to evaluate the potential gain in the expected number of observed nanoparticles due to the magnetic field. Furthermore, adopting the symbol error rate as performance metric, we show that using magnetic nanoparticles can enable a reliable communication in the presence of disruptive fluid flow. The numerical results obtained by the particle-based simulation validate the accuracy of the derived analytical expressions.
CRIS-Team Scopus Importer:2019-05-14
Keywords: Analytical solution; diffusion; fluid flow; magnetic nanoparticles; microfluidic channel; molecular communication

Magnetic nanoparticles for cancer therapy - Dürr, Stephan; Janko, Christina; Lyer, Stefan; Tripal, Philipp; Schwarz, Marc; Zaloga, Jan; Tietze, Rainer; Alexiou, Christoph (Nanotechnology Reviews, 2013)
Cancer is one of the biggest challenges facing the medical research in our time. The goals are to improve not only the therapeutic outcome, even in the cases of advanced and metastatic cancer, but also the methods of treatment, which often have considerable adverse effects. In addition, the current developments, such as demographic change, population growth, and increasing healthcare costs, have to be taken into consideration. In all likelihood, nanotechnology and, in particular, the use of magnetic nanoparticles consisting of the elements nickel, cobalt, and iron can make a significant contribution. The greatest potential can be ascribed to the drug delivery systems: magnetic nanoparticles are functionalized by binding them to various substances, including chemotherapeutic agents, radionuclides, nucleic acids, and antibodies. They can then be guided and accumulated using a magnetic field. Hyperthermia can be induced with an alternating magnetic field, providing another therapeutic option. Magnetic nanoparticles may be useful in overcoming cancer drug resistance. They also contribute to realizing a combination of diagnostic investigation and therapy in the field of " theranostics ". The multifaceted and promising results of research in the recent years offer the prospect of a real advance in cancer therapy in the near future.
Created from Fastlane, Scopus look-up
Keywords: Cancer drug resistance; Cancer therapy; Drug delivery; Hyperthermia; Magnetic nanoparticles

Magnetic nanoparticles for magnetic drug targeting - Lyer, Stefan; Singh, Raminder; Tietze, Rainer; Alexiou, Christoph (Biomedizinische Technik, 2015)
Nanomedicine and superparamagnetic iron oxide nanoparticles (SPIONs) are thought to have an important impact on medicine in the future. Especially in cancer therapy, SPIONs offer the opportunity of improving the effectivity of the treatment and reduce side effects by magnetic accumulation of SPION-bound chemotherapeutics in the tumor area. Although still some challenges have to be overcome, before the new treatment concept of magnetic drug targeting will reach the patients, substantial progress has been made, and promising results were shown in the last years.
EVALuna2:20014

Magnetic nanoparticles for medical applications - Cicha, Iwona; Lyer, Stefan; Janko, Christina; Friedrich, Ralf P.; Poettler, Marina; Alexiou, Christoph (Nanomedicine, 2017)
EVALuna2:33163

Magnetic Removal of Candida albicans Using Salivary Peptide-Functionalized SPIONs - Friedrich, Bernhard; Tietze, Rainer; Dümig, Michaela; Sover, Alexandru; Boca, Marius Andrei; Schreiber, Eveline; Band, Julia; Janko, Christina; Krappmann, Sven; Alexiou, Christoph; Lyer, Stefan (International Journal of Nanomedicine, 2023)
Purpose: Magnetic separation of microbes can be an effective tool for pathogen identification and diagnostic applications to reduce the time needed for sample preparation. After peptide functionalization of superparamagnetic iron oxide nanoparticles (SPIONs) with an appropriate interface, they can be used for the separation of sepsis-associated yeasts like Candida albicans. Due to their magnetic properties, the magnetic extraction of the particles in the presence of an external magnetic field ensures the accumulation of the targeted yeast. Materials and Methods: In this study, we used SPIONs coated with 3-aminopropyltriethoxysilane (APTES) and functionalized with a peptide originating from GP340 (SPION-APTES-Pep). For the first time, we investigate whether this system is suitable for the separation and enrichment of Candida albicans, we investigated its physicochemical properties and by thermogravimetric analysis we determined the amount of peptide on the SPIONs. Further, the toxicological profile was evaluated by recording cell cycle and DNA degradation. The separation efficiency was investigated using Candida albicans in different experimental settings, and regrowth experiments were carried out to show the use of SPION-APTES-Pep as a sample preparation method for the identification of fungal infections. Conclusion: SPION-APTES-Pep can magnetically remove more than 80% of the microorganism and with a high selective host-pathogen distinction Candida albicans from water-based media and about 55% in blood after 8 minutes processing without compromising effects on the cell cycle of human blood cells. Moreover, the separated fungal cells could be regrown without any restrictions.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Candida albicans; fungal sepsis; GP340; microbiological identification; SPIONs

Magnetic Steering of Superparamagnetic Nanoparticles in Duct Flow for Molecular Communication: A Feasibility Study - Schlechtweg, Niklas; Meyer, Sebastian; Unterweger, Harald; Bartunik, Max; Ahmed, Doaa; Wicke, Wayan; Jamali, Vahid; Alexiou, Christoph; Fischer, Georg; Weigel, Robert; Schober, Robert; Kirchner, Jens (Lecture Notes of the Institute for Computer Sciences, Social-Informatics and Telecommunications Engineering, LNICST, 2019)
Molecular communication (MC) denotes information transmission by use of molecules and nanosized particles. For the realization of testbeds, superparamagnetic iron oxide nanoparticles (SPIONs) in duct flow have recently been proposed. Here, an experimental setup is provided to direct these particles at a branching of a tube into a specific direction by use of magnetic fields. For that purpose, gold-coated SPIONs suspended in water at constant flow rate are considered at a Y-shaped connector of tubes. The particles are attracted by use of a custom-made electromagnet, while change of particle concentration in either of the branches is measured by a commercial susceptometer. The approach is evaluated for different flow rates and with the electromagnet both at a fixed position and moving along the tube. Exemplary measurements show that an information transmission is feasible in both approaches and with all tested flow rates. The feasibility study hence shows that particle steering by use of magnetic fields is a viable approach, which is even robust against flow rate variations. It can thus be used in MC to address different transmission channels as well as to realize differential signal transmission. Furthermore, it might help to improve magnetic drug targeting in future applications.
CRIS-Team Scopus Importer:2019-12-27
Keywords: Duct flow; Magnetic field; Molecular communication; Particle steering; Superparamagnetic nanoparticles

Magnetic Tissue Engineering for Voice Rehabilitation - First Steps in a Promising Field - Dürr, Stephan; Bohr, Christopher; Poettler, Marina; Lyer, Stefan; Friedrich, Ralf P.; Tietze, Rainer; Döllinger, Michael; Alexiou, Christoph; Janko, Christina (Anticancer Research, 2016)
The voice is one of the most important instruments of communication between humans. It is the product of intact and well-working vocal folds. A defect of these structures causes dysphonia, associated with a clear reduction of quality of life. Tissue engineering of the vocal folds utilizing magnetic cell levitation after nanoparticle loading might be a technique to overcome this challenging problem.Vocal fold fibroblasts (VFFs) were isolated from rabbit larynges and cultured. For magnetization, cells were incubated with superparamagnetic iron oxide nanoparticles (SPION) and the loading efficiency was determined by Prussian blue staining. Biocompatibility was analyzed in flow cytometry by staining with annexin V-fluorescein isothiocyanate propidium iodide, 1,1',3,3,3',3'-hexamethylindodicarbo-cyanine iodide [DiIC1(5)] and propidium idodide-Triton X-100 to monitor phosphatidylserine exposure, plasma membrane integrity, mitochondrial membrane potential and DNA degradation.Isolated VFFs can be successfully loaded with SPION, and optimal iron loading associated with minimized cytotoxicity represents a balancing act in magnetic tissue engineering.Our data are a firm basis for the next steps of investigations. Magnetic tissue engineering using magnetic nanoparticle-loaded cells which form three-dimensional structures in a magnetic field will be a promising approach in the future.
EVALuna2:20008

Magnetic Tissue Engineering of the Vocal Fold Using Superparamagnetic Iron Oxide Nanoparticles - Poettler, Marina; Fliedner, Anna; Bergmann, Julia; Bui, Linh Katrin; Mühlberger, Marina; Braun, Christian; Graw, Matthias; Janko, Christina; Friedrich, Oliver; Alexiou, Christoph; Lyer, Stefan (Tissue Engineering: Parts A, B, and C, 2019)
Losing one's ability to speak, because of tissue deficiency at the vocal fold (VF), leads to serious impairment in the quality of life. Until now, there is no successful approach for regenerating the VF. The aim of this study was to show the advantage of magnetic nanoparticles in the generation of scaffold-free three-dimensional (3D) VF cell constructs by magnetic tissue engineering (MTE). Rabbit VF fibroblasts were used to establish MTE: after cellular uptake of superparamagnetic iron oxide nanoparticles (SPIONs), cells can be controlled with a magnetic field thereby forming solid 3D cell structures. To transfer this method into human cells, SPIONs were adapted accordingly and tested for their influence on human VF (hVF) cells and for their ability to perform MTE with hVF cells. Of interest, the cell number and the magnet's shape influence the form of the rabbit VF cell construct. After successful characterization of hVF cells, biocompatibility analyses revealed no significant influence of SPIONs on them, thus 3D hVF cell constructs could be successfully generated by MTE. These basic results are important to develop MTE as an innovative method to regenerate functional VFs. We expect that in vivo studies, including MTE as an elegant, far-field controlled and touchless technology, will translate MTE VF bioconstructs into reconstructive laryngeal medicine. Impact Statement This study aims at nanotechnology for regenerative medicine by magnetic tissue engineering (MTE). New approaches for vocal fold (VF) reconstruction are desperately needed. Superparamagnetic iron oxide nanoparticles offer innovative, scaffold-free potentials for tissue engineering: MTE. By using MTE we could generate functional multilayered human VF cell constructs, which can consequently be used to regenerate the voice in patients with VF injuries.
CRIS-Team WoS Importer:2019-05-14

Magnetite-arginine nanoparticles as a multifunctional biomedical tool - Reichel, Victoria E.; Matuszak, Jasmin; Bente, Klaas; Heil, Tobias; Kraupner, Alexander; Dutz, Silvio; Cicha, Iwona; Faivre, Damien (Nanomaterials, 2020)
Iron oxide nanoparticles are a promising platform for biomedical applications, both in terms of diagnostics and therapeutics. In addition, arginine-rich polypeptides are known to penetrate across cell membranes. Here, we thus introduce a system based on magnetite nanoparticles and the polypeptide poly-l-arginine (polyR-Fe3O4). We show that the hybrid nanoparticles exhibit a low cytotoxicity that is comparable to Resovist®, a commercially available drug. PolyR-Fe3O4 particles perform very well in diagnostic applications, such as magnetic particle imaging (1.7 and 1.35 higher signal respectively for the 3rd and 11th harmonic when compared to Resovist®), or as contrast agents for magnetic resonance imaging (R2/R1 ratio of 17 as compared to 11 at 0.94 T for Resovist®). Moreover, these novel particles can also be used for therapeutic purposes such as hyperthermia, achieving a specific heating power ratio of 208 W/g as compared to 83 W/g for Feridex®, another commercially available product. Therefore, we envision such materials to play a role in the future theranostic applications, where the arginine ability to deliver cargo into the cell can be coupled to the magnetite imaging properties and cancer fighting activity.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Hyperthermia; Iron oxide; MRI; Nanoparticle; Theranostics

Magnetorelaxometry for in-vivo quantification of magnetic nanoparticle distributions after magnetic drug targeting in a rabbit carcinoma model - Wiekhorst, Frank; Liebl, Maik; Steinhoff, Uwe; Trahms, Lutz; Lyer, Stefan; Dürr, Stephan; Alexiou, Christoph (Springer Proceedings in Physics, 2012)
Multi-channel magnetorelaxometry (MRX) is demonstrated to locate and quantify several foci of a magnetic nanoparticle (MNP) distribution after magnetic drug targeting (MDT) in an in-vivo rabbit carcinoma model. By this non-invasively technique MNP accumulations of lateral extensions up to 20 x 30 cm2 can easily be accessed in biological tissue. The total measurement duration of about 20 min including preparation of the rabbit and measurement of two regions of interests (ROI), tumor and thorax (liver, lung and spleen), enables a high throughput of animals. Modelling the MNP distribution either by magnetic point dipoles (ROI tumor) or by an extended, homogenously magnetized body (ROI thorax) of simple geometry, e.g. cuboid, the total magnetic moment and location of each focus is determined by minimum norm estimation. Simultaneously, vital functions like respiration and heart activity can be monitored directly and non-invasively during the MRX measurements. Thus, our MRX procedure gains valuable information for monitoring of MDT procedures in large scale animal models.
CRIS-Team Scopus Importer:2022-06-27

Malignant teratoid tumor of the thyroid gland: an aggressive primitive multiphenotypic malignancy showing organotypical elements and frequent DICER1 alterations—is the term “thyroblastoma” more appropriate? - Agaimy, Abbas; Witkowski, Leora; Stöhr, Robert; Cuenca, Joseph Christopher Castillo; González-Muller, Carlos Alberto; Brütting, Alfred; Bährle, Markus; Mantsopoulos, Konstantinos; Amin, Randa M.S.; Hartmann, Arndt; Metzler, Markus; Amr, Samir S.; et al. (Virchows Archiv, 2020)
Primary thyroid teratomas are exceedingly rare. Mature and immature variants recapitulate their gonadal counterparts (predilection for infants/children, triphasic germ layer differentiation, and favorable outcome). On the other hand, the so-called malignant teratomas affect predominantly adults and elderly, are highly aggressive, and, according to a few published cases, harbor DICER1 mutations. We describe three highly aggressive sporadic malignant teratoid thyroid tumors in 2 females (17 and 45 years) and one male (17 years). Histology showed triphasic neoplasms composed of solid nests of small primitive monomorphic cells embedded in a cellular stroma with primitive immature rhabdomyosarcoma-like (2) or pleomorphic sarcoma-like (1) phenotype. The third component was represented by TTF1+/PAX8+ primitive teratoid epithelial tubules reminiscent of primitive thyroid follicles and/or Wilms tumor, admixed with scattered respiratory- or enteric-type tubules, neuroepithelial rosettes, and fetal-type squamoid nests. Foci of cartilage were seen in two cases, but none contained mature organoid adult-type tissue or skin adnexa. SALL4 was expressed in the small cell (2) and stromal (1) component. Other germ cell markers were negative. Molecular testing revealed a known “hotspot” pathogenic DICER1 mutation in two cases. In addition, case 1 had a missense TP53 variant. This type of thyroid malignancy is distinct from genuine teratomas. The immunoprofile suggests primitive thyroid- or branchial cleft-like differentiation. Given that “blastoma” is a well-accepted terminology in the spectrum of DICER1-associated malignancies, the term “thyroblastoma” might be more convenient for these malignant teratoid tumors of the thyroid gland. Relationship of thyroblastoma to the DICER1 syndrome remains to be addressed.
CRIS-Team Scopus Importer:2020-06-16
Keywords: DICER1; Germ cell tumor; Head and neck; Malignant teratoma; Rhabdomyosarcoma; Teratocarcinosarcoma; Thyroblastoma; Thyroid

Management of advanced hypopharyngeal and laryngeal cancer with and without cartilage invasion - Scherl, Claudia; Mantsopoulos, Konstantinos; Semrau, Sabine; Fietkau, Rainer; Kapsreiter, Markus; Koch, Michael; Traxdorf, Maximilian; Grundtner, Philipp; Iro, Heinrich (Auris Nasus Larynx, 2016)
To compare efficacy, in terms of disease control/survival in advanced hypopharyngeal and laryngeal lesions, according to treatment strategy (primary surgery, PS or primary chemoradiotherapy, CRT) and invasion pattern (cartilage, CAI or soft tissue involvement, STI).Records from 463 patients with T3 and T4a carcinoma with CAI (n=221) or STI (n=242) treated at a university clinic over 18 years were retrospectively reviewed.Disease-specific survival (DSS) for the CAI group was 70.1% (PS) and 38.4% (CRT), and 76.6% and 46% for the STI group, respectively. Overall survival (OS) for STI was 56.4% (PS) and 30.6% (CRT), and for CAI 51.1% (PS) and 28.5% (CRT) respectively. Positive resection margins and regional neck metastases reduced survival. T3 lesions treated non-operatively still had significantly improved survival versus T4a by >20%.Surgery remains an indispensable part of treatment in local advanced hypopharyngeal and laryngeal cancer with high survival results. It should be part of a concept that includes adjuvant (C)RT. For T3 lesions, primary CRT is also acceptable and CAI is not a contraindication for primary CRT. Regional disease is a strong prognostic factor. In spite of adjuvant treatment, DSS deteriorates by about 20% in cases with positive resection margins.
EVALuna2:18360

Management of spontaneous enophthalmos due to silent sinus syndrome: a case report - Nkenke, Emeka; Alexiou, Christoph; Iro, Heinrich; Amann, Kerstin Ute; Kirchner, Thomas; Häusler, Gerd; Neukam, Friedrich Wilhelm; Holbach, Benedict (International Journal of Oral and Maxillofacial Surgery, 2005)
UnivIS-Import:2015-04-14:Pub.2005.nat.dphy.optik.1optik.manage

Management von Patienten mit Tracheostoma während der COVID-19-Pandemie: Literaturüberblick und Demonstration - Kempfle, J. S.; Löwenheim, H.; Hübner, Matthias; Iro, Heinrich; Mueller, Sarina K. (HNO, 2020)
Background: Since emergence of the new coronavirus in China in December 2019, many countries have been struggling to control skyrocketing numbers of infections, including among healthcare personnel. It has now been clearly demonstrated that SARS-CoV‑2 resides in the upper airways and transmits easily via aerosols and droplets, which significantly increases the risk of infection when performing upper airway procedures. Ventilated COVID-19 patients in a critical condition in the intensive care unit may require tracheotomy for long-term ventilation and to improve weaning. However, the risk of secondary infection of medical personnel performing subsequent tracheostomy care remains unclear. Objective: This study aimed to evaluate the risk of droplet dispersion during tracheostomy tube change and overview tracheostomy tube change in COVID-19 patients. Materials and methods: The current literature was reviewed, quantitative and qualitative analyses of droplet formation during tracheostomy tube change in n = 8 patients were performed, and an overview of and checklist for tracheostomy tube change were compiled. Results: This study demonstrates that tracheostomy tube change, in particular insertion of the new tube, may cause significant droplet formation. The aerosolization of particles smaller than 5 µm was not analyzed. Conclusion: Our data, together with the current literature, clearly emphasize that tracheostomy care is associated with a high infection risk and should only be performed by a small group of well-trained, maximally protected healthcare personnel.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Aerosols; COVID-19; Droplets; PPE; Tracheostomy tube change

Material and shape optimization for multi-layered vocal fold models using transient loadings - Schmidt, Bastian; Leugering, Günter; Stingl, Michael; Hüttner, Björn; Agaimy, Abbas; Döllinger, Michael (Journal of the Acoustical Society of America, 2013)
Commonly applied models to study vocal fold vibrations in combination with air flow distributions are self-sustained physical models of the larynx consisting of artificial silicone vocal folds. Choosing appropriate mechanical parameters and layer geometries for these vocal fold models while considering simplifications due to manufacturing restrictions is difficult but crucial for achieving realistic behavior. In earlier work by Schmidt et al. [J. Acoust. Soc. Am. 129, 2168-2180 (2011)], the authors presented an approach in which material parameters of a static numerical vocal fold model were optimized to achieve an agreement of the displacement field with data retrieved from hemilarynx experiments. This method is now generalized to a fully transient setting. Moreover in addition to the material parameters, the extended approach is capable of finding optimized layer geometries. Depending on chosen material restriction, significant modifications of the reference geometry are predicted. The additional flexibility in the design space leads to a significantly more realistic deformation behavior. At the same time, the predicted biomechanical and geometrical results are still feasible for manufacturing physical vocal fold models consisting of several silicone layers. As a consequence, the proposed combined experimental and numerical method is suited to guide the construction of physical vocal fold models. (C) 2013 Acoustical Society of America.

Material parameter computation for multi-layered vocal fold models - Schmidt, Bastian; Stingl, Michael; Leugering, Günter; Berry, David A.; Döllinger, Michael (Journal of the Acoustical Society of America, 2011)
Today, the prevention and treatment of voice disorders is an ever-increasing health concern. Since many occupations rely on verbal communication, vocal health is necessary just to maintain one's livelihood. Commonly applied models to study vocal fold vibrations and air flow distributions are self sustained physical models of the larynx composed of artificial silicone vocal folds. Choosing appropriate mechanical parameters for these vocal fold models while considering simplifications due to manufacturing restrictions is difficult but crucial for achieving realistic behavior. In the present work, a combination of experimental and numerical approaches to compute material parameters for synthetic vocal fold models is presented. The material parameters are derived from deformation behaviors of excised human larynges. The resulting deformations are used as reference displacements for a tracking functional to be optimized. Material optimization was applied to three-dimensional vocal fold models based on isotropic and transverse-isotropic material laws, considering both a layered model with homogeneous material properties on each layer and an inhomogeneous model. The best results exhibited a transversal-isotropic inhomogeneous (i.e., not producible) model. For the homogeneous model (three layers), the transversal-isotropic material parameters were also computed for each layer yielding deformations similar to the measured human vocal fold deformations. (C) 2011 Acoustical Society of America. [DOI:10.1121/1.3543988]

Maximum monosyllabic score as a predictor for cochlear implant outcome - Hoppe, Ulrich; Hocke, T.; Hast, A.; Iro, Heinrich (HNO, 2019)
ObjectiveThis study investigated the speech perception of cochlear implant (CI) recipients with measurable preoperative ipsilateral speech perception. These data should support improved individual counselling of CI candidates.Materials and methodsPre- and postoperative speech audiometric parameters were analyzed, including maximum score for phonemically balanced words (PBmax) and monosyllabic score at anormal conversational level of 65dB(SPL), with hearing aids one hand and CI on the other. Data of 284 experienced adult CI wearers were grouped and evaluated in terms of preoperative PBmax.ResultsThe preoperative PBmax was exceeded by the postoperative monosyllabic score in 96% of cases. The overall median postoperative score was 72.5%. The groups with preoperative PBmax>0% showed significantly better speech perception scores with CI than the group with PBmax=0%. Median improvement compared to the preoperative monosyllabic score with hearing aids was 65percentage points, independent of preoperative PBmax.ConclusionThe preoperatively measured PBmax may be used as apredictor for the minimum speech perception obtained with CI. This is of high clinical relevance for CI candidates with a PBmax above zero.
CRIS-Team WoS Importer:2019-03-26

Maximum preimplantation monosyllabic score as predictor of cochlear implant outcome - Hoppe, Ulrich; Hocke, Thomas; Hast, Anne; Iro, Heinrich (HNO, 2019)
ObjectiveThis study investigated the speech perception of cochlear implant (CI) recipients with measurable preoperative ipsilateral speech perception. These data should support improved individual counselling of CI candidates.Materials and methodsPre- and postoperative speech audiometric parameters were analyzed, including maximum score for phonemically balanced words (PBmax) and monosyllabic score at anormal conversational level of 65dB(SPL), with hearing aids one hand and CI on the other. Data of 284 experienced adult CI wearers were grouped and evaluated in terms of preoperative PBmax.ResultsThe preoperative PBmax was exceeded by the postoperative monosyllabic score in 96% of cases. The overall median postoperative score was 72.5%. The groups with preoperative PBmax>0% showed significantly better speech perception scores with CI than the group with PBmax=0%. Median improvement compared to the preoperative monosyllabic score with hearing aids was 65percentage points, independent of preoperative PBmax.ConclusionThe preoperatively measured PBmax may be used as apredictor for the minimum speech perception obtained with CI. This is of high clinical relevance for CI candidates with a PBmax above zero.
CRIS-Team WoS Importer:2019-06-28

Measurement of glottal cycle characteristics between children and adults: physiological variations - Patel, Rita R.; Dubrovskiy, Denis; Döllinger, Michael (Journal of Voice, 2014)
The aim of this study was to quantify phases of the vibratory cycle using measurements of glottal cycle quotients and glottal cycle derivatives, in typically developing prepubertal children and young adults with the use of high-speed digital imaging (HSDI).Vocal fold vibrations were recorded from 27 children (age range 5-9 years) and 35 adults (age range 21-45 years), with HSDI at 4000 frames per second for sustained phonation. Glottal area waveform measures of Open Quotient, Closing Quotient, Speed Index (SI), Rate Quotient, and Asymmetry Quotient (AsyQ) were computed. Glottal cycle derivatives of Amplitude Quotient (AQ) and Maximum Area Declination Rate (MADR) were also computed. Group differences (adult females, adult males, and children) were statistically investigated for mean and standard deviation values of the glottal cycle quotients and glottal cycle derivatives.Children exhibited higher values of SI and AsyQ and lower values of MADR compared with adult males. Children exhibited the highest mean value and lowest variability in AQ compared with adult males and females. Adult males showed lower values of SI, AsyQ, AQ, and higher values of MADR compared with adult females.Glottal cycle vibratory motion in children is functionally different compared with adult males and females, suggesting the need for development of children specific norms for both normal and disordered voice qualities.
EVALuna2:20184

Measurement of the elasticity modulus of soft tissues - Zoerner, S.; Kaltenbacher, M.; Lerch, Reinhard; Sutor, Alexander; Döllinger, Michael (Journal of Biomechanics, 2010)
A measurement setup combined with a Finite Element (FE) simulation is presented to determine the elasticity modulus of soft materials as a function of frequency. The longterm goal of this work is to measure in vitro the elasticity modulus of human vocal folds over a frequency range that coincides with the range of human phonation. The results will assist numerical simulations modeling the phonation process by providing correct material parameters. Furthermore, the measurements are locally applied, enabling to determine spatial differences along the surface of the material. In this work the method will be presented and validated by applying it to silicones with similar characteristics as human vocal folds. Three silicone samples with different consistency were tested over a frequency range of 20-250 Hz. The results of the pipette aspiration method revealed a strong frequency dependency of the elasticity modulus, especially below 100 Hz. In this frequency range the elasticity moduli of the samples varied between 5 and 27 kPa. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Material parameter simulation; Pipette aspiration; Elasticity modulus; Finite-element simulation

Mechanical Parameters Based on High-Speed Videoendoscopy of the Vocal Folds in Patients With Ectodermal Dysplasia - Pelka, Franziska; Ensthaler, Maria; Wendler, Olaf; Kniesburges, Stefan; Schützenberger, Anne; Semmler, Marion (Journal of Voice, 2023)
Objective: Patients suffering from ectodermal dysplasia (ED), which is an inherited disorder in the development of the ectodermal structures, have a significantly reduced expression of teeth, hair, sweat glands, and salivary glands in the respiratory tract including the larynx. Previous studies within the framework of the present project showed a significantly reduced saliva production and an impairment of the acoustic outcome in ED patients compared to the control group. However, until now, no statistically significant difference between EDs and controls could be found regarding vocal fold dynamics in the high-speed videoendoscopy (HSV) recordings using representative parameters on closure, symmetry, and periodicity. The aim of this study is to examine the role of tissue characteristics by means of objective mechanical parameters derived from HSV recordings. Methods: This study includes 28 ED patients and 42 controls (no ED, healthy voice). The vocal fold oscillations were recorded by high-speed videoendoscopy (HSV@4kHz). Based on the dynamical measures of the glottal area waveform (GAW), objective glottal dynamic parameters associated with tissue properties like flexibility and stiffness were computed. Results: The present evaluation displays a significant difference between male ED patients and male controls concerning the HSV-based mechanical parameters indicating reduced stiffness and increased deformability for the vocal folds of male ED patients. In contrast to strongly amplitude-dependent parameters, the primarily velocity-based parameters showed no statistically significant deviation. Conclusions: The presented data provides the first promising indication toward the underlying causes on the laryngeal level leading to the voice conspicuities in ED patients. The significant difference concerning the mechanical parameters suggests a different composition of the extracellular matrix of the tissue of the vocal folds of ED patients compared to controls.
CRIS-Team Scopus Importer:2023-04-14
Keywords: Ectodermal Dysplasia; Genetics; High-speed videoendoscopy; Mechanical parameters; Tissue properties; Vocal fold mobility

Melt Electrowriting of Isomalt for High-Resolution Templating of Embedded Microchannels - Nadernezhad, Ali; Ryma, Matthias; Genc, Hatice; Cicha, Iwona; Jüngst, Tomasz; Groll, Jürgen (Advanced Materials Technologies, 2021)
Fabrication of microchannels using 3D printing of sugars as fugitive material is explored in different fields, including microfluidics. However, establishing reproducible methods for the controlled production of sugar structures with sub-100 μm dimensions remains a challenge. This study pioneers the processing of sugars by melt electrowriting (MEW) enabling the fabrication of structures with so far unprecedented resolution from Isomalt. Based on a systematic variation of process parameters, fibers with diameters down to 20 μm can be fabricated. The flexibility in the adjustment of fiber diameter by on-demand alteration of MEW parameters enables generating constructs with perfusable channels within polydimethylsiloxane molds. These channels have a diameter that can be adjusted from 30 to 200 μm in a single design. Taken together, the experiments show that MEW strongly benefits from the thermal and physical stability of Isomalt, providing a robust platform for the fabrication of small-diameter embedded microchannel systems.
CRIS-Team Scopus Importer:2021-07-02
Keywords: embedded templating; melt electrowriting; microfibers; microfluidics; sacrificial printing; sugar glass printing

Ménage-à-Trois: The Ratio of Bicarbonate to CO2 and the pH Regulate the Capacity of Neutrophils to Form NETs - Maueröder, Christian; Mahajan, Aparna; Paulus, Susanne; Goesswein, Stefanie; Hahn, Jonas; Kienhoefer, Deborah; Biermann, Mona H.; Tripal, Philipp; Friedrich, Ralf P.; Munoz Becerra, Luis; Neurath, Markus; Becker, Christoph; et al. (Frontiers in Immunology, 2016)
In this study, we identified and characterized the potential of a high ratio of bicarbonate to CO2 and a moderately alkaline pH to render neutrophils prone to undergo neutrophil extracellular trap (NET) formation. Both experimental settings increased the rate of spontaneous NET release and potentiated the NET-inducing capacity of phorbol esters (phorbol-2-myristate-13-acetate), ionomycin, monosodium urate, and LPS. In contrast, an acidic environment impaired NET formation both spontaneous and induced. Our findings indicate that intracellular alkalinization of neutrophils in response to an alkaline environment leads to an increase of intracellular calcium and neutrophil activation. We further found that the anion channel blocker DIDS strongly reduced NET formation induced by bicarbonate. This finding suggests that the effects observed are due to a molecular program that renders neutrophils susceptible to NET formation. Inflammatory foci may be characterized by an acidic environment. Our data indicate that NET formation is favored by the higher pH at the border regions of inflamed areas. Moreover, our findings highlight the necessity for strict pH control during assays of NET formation.
EVALuna2:2182

Merged Volume Rendered Flat-panel Computed Tomography for Postoperative Cochlear Implant Assessment - Eisenhut, Felix; Lang, Stefan; Dörfler, Arnd; Iro, Heinrich; Hornung, Joachim; Taha, Lava (Clinical Neuroradiology, 2019)
Purpose: Evaluation of a new postprocessing method for postoperative control of cochlear implants (CI) based on a single flat detector computed tomography (FD-CT) run and volume rendering of 3D models of the inner ear. Methods: The FD-CT datasets of CIs were selected and postprocessed to generate both standard multiplanar reconstructions (MPR) and merged volume-rendered 3D datasets (MRD) of the CIs. The MRDs consisted of two different reconstructions (bone/implant) that are automatically layered to avoid manual coregistration inaccuracy. Corresponding datasets were evaluated in consensus reading in terms of qualitative (integrity, position, configuration) and quantitative (insertion depth angle) CI parameters. Results: In total 20 FD-CTs with 20 CIs were successfully postprocessed. Qualitative evaluation of MPR and MRD demonstrated complete congruency (integrity: narray integrity = 20; position: nscala tympani = 13, nscalar translocation = 7; configuration: nharmonic spiralization = 16, ntip fold over = 3, nlooped implant = 1). Adverse intracochlear implant spiralization was identified in all 10 cases with MRD and MPR. Measurement of the insertion depth angle in MRD was equivalent to that in MPR (r = 0.99; P = <0.0001). Conclusion: The use of MRD is a helpful method for precise postoperative CI assessment and provides easy detection of incorrect intracochlear spiralization.
CRIS-Team Scopus Importer:2019-09-20
Keywords: CI; FD-CT; Postprocessing; Temporal bone; Three-dimensional

Metabolic Response of Short-term Induction Chemotherapy (IC) for Therapy Selection as well as Prediction of long-term local and systemic Therapy Success for Head and Neck cancer. The Results of 100 Patients - Semrau, S.; Haderlein, Marlen; Schmidt, Daniela; Waldfahrer, F.; Scherl, C.; Lettmaier, S.; Kuwert, Torsten; Iro, Heinrich; Fietkau, Rainer (2017)
EVALuna2:32895

Microcystic adnexal carcinoma (MAC)-like squamous cell carcinoma as a differential diagnosis to Bell´s palsy: review of guidelines for refractory facial nerve palsy - Müller, Sandra; Iro, Heinrich; Lell, M.; Seifert, F.; Bohr, Christopher; Scherl, C.; Agaimy, Abbas; Traxdorf, Maximilian (Journal of Otolaryngology-Head & Neck Surgery, 2017)
Bell´s palsy is the most common cause of facial paralysis worldwide and the most common disorder of the cranial nerves. It is a diagnosis of exclusion, accounting for 60-75% of all acquired peripheral facial nerve palsies. Our case shows the first case of a microcystic adnexal carcinoma-like squamous cell carcinoma as a cause of facial nerve palsy.The patient, a 70-year-old Caucasian male, experienced subsequent functional impairment of the trigeminal and the glossopharyngeal nerve about 1½ years after refractory facial nerve palsy. An extensive clinical work-up and tissue biopsy of the surrounding parotid gland tissue was not able to determine the cause of the paralysis. Primary infiltration of the facial nerve with subsequent spreading to the trigeminal and glossopharyngeal nerve via neuroanastomoses was suspected. After discussing options with the patient, the main stem of the facial nerve was resected to ascertain the diagnosis of MAC-like squamous cell carcinoma, and radiochemotherapy was subsequently started.This case report shows that even rare neoplastic etiologies should be considered as a cause of refractory facial nerve palsy and that it is necessary to perform an extended diagnostic work-up to ascertain the diagnosis. This includes high-resolution MRI imaging and, as perilesional parotid biopsies might be inadequate for rare cases like ours, consideration of a direct nerve biopsy to establish the right diagnosis.
EVALuna2:6836

Microstructure of cortical activity during sleep reflects respiratory events and state of daytime vigilance - Traxdorf, Maximilian; Krauß, Patrick; Schilling, Achim; Schulze, Holger; Tziridis, Konstantin (Somnologie, 2019)
Background: Besides visual sleep stage scoring, it is possible to separate sleep stages by analyzing spatially distributed three-channel electroencephalogram (EEG) root mean square (RMS) amplitudes. This approach allows qualitative and quantitative evaluation of sleep architecture. The aim of this study was to analyze the effect of apnea–hypopnea index (AHI) and state of vigilance on the microstructure of cortical activity during sleep using EEG cluster analysis. Materials and methods: In 31 obstructive sleep apnea (OSA) patients, cortical EEG patterns were recorded during polysomnography and subjected to EEG cluster analysis. The results were subsequently correlated to AHI as well as to subjective (Epworth Sleepiness Scale) and objective (pupillographic sleepiness test) daytime sleepiness using linear regression. In 18/31 patients, cortical EEG patterns were recorded again the following night during continuous positive airway pressure (CPAP) titration and compared to the results of the first night. Results: Linear regression analyses revealed dependencies of specific cortical EEG patterns on AHI (intra-cluster distance of N2 [p = 0.019], N3 [p = 0.024]; inter-cluster distance of wake-N2 [p = 0.046], wake-N3 [p = 0.047], N2–N3 [p = 0.021]) and on objective daytime sleepiness (wake intra-cluster distance [p = 0.047], inter-cluster distance of wake-N3 [p = 0.042]), but not on subjective daytime sleepiness. Specifically, an increase in EEG pattern variability was found in patients with high AHI values, which could be reduced by CPAP therapy. Conclusion: This new approach enables objective analysis and visualization of sleep macro- and microstructure. The variance of neuronal EEG signal patterns enables conclusions on the presence of pathological respiratory events and objectively measured daytime sleepiness.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Continuous positive airway pressure; Daytime sleepiness; Electroencephalography; Root mean square; Sleep apnea; obstructive

Mitoxantrone and Mitoxantrone-Loaded Iron Oxide Nanoparticles Induce Cell Death in Human Pancreatic Ductal Adenocarcinoma Cell Spheroids - Dinter, Jonas; Friedrich, Ralf P.; Yang, Hai; Pilarsky, Christian; Mangge, Harald; Pöttler, Marina; Janko, Christina; Alexiou, Christoph; Lyer, Stefan (Materials, 2023)
Pancreatic ductal adenocarcinoma is a hard-to-treat, deadly malignancy. Traditional treatments, such as surgery, radiation and chemotherapy, unfortunately are still not able to significantly improve long-term survival. Three-dimensional (3D) cell cultures might be a platform to study new drug types in a highly reproducible, resource-saving model within a relevant pathophysiological cellular microenvironment. We used a 3D culture of human pancreatic ductal adenocarcinoma cell lines to investigate a potential new treatment approach using superparamagnetic iron oxide nanoparticles (SPIONs) as a drug delivery system for mitoxantrone (MTO), a chemotherapeutic agent. We established a PaCa DD183 cell line and generated PANC-1SMAD4 (−/−) cells by using the CRISPR-Cas9 system, differing in a prognostically relevant mutation in the TGF-β pathway. Afterwards, we formed spheroids using PaCa DD183, PANC-1 and PANC-1SMAD4 (−/−) cells, and analyzed the uptake and cytotoxic effect of free MTO and MTO-loaded SPIONs by microscopy and flow cytometry. MTO and SPION–MTO-induced cell death in all tumor spheroids in a dose-dependent manner. Interestingly, spheroids with a SMAD4 mutation showed an increased uptake of MTO and SPION–MTO, while at the same time being more resistant to the cytotoxic effects of the chemotherapeutic agents. MTO-loaded SPIONs, with their ability for magnetic drug targeting, could be a future approach for treating pancreatic ductal adenocarcinomas.
CRIS-Team Scopus Importer:2023-04-28
Keywords: 3D cell culture; magnetic drug targeting; nanomedicine; pancreatic ductal adenocarcinoma; superparamagnetic iron oxide nanoparticles

Mitoxantrone-loaded nanoparticles for magnetically controlled tumor therapy–induction of tumor cell death, release of danger signals and activation of immune cells - Ratschker, Teresa; Egenberger, Laura; Alev, Magdalena; Zschiesche, Lisa; Band, Julia; Schreiber, Eveline; Frey, Benjamin; Derer, Anja; Alexiou, Christoph; Janko, Christina (Pharmaceutics, 2020)
Stimulating the patient`s immune system represents a promising therapeutic strategy to fight cancer. However, low immunogenicity of the tumor cells within an immune suppressive milieu often leads to weak anti-tumor immune responses. Additionally, the immune system may be impaired by accompanying aggressive chemotherapies. We show that mitoxantrone, bound to superparamagnetic iron oxide nanoparticles (SPIONs) as the transport system, can be magnetically accumulated in adherent HT-29 colon carcinoma cells, thereby inducing the same cell death phenotype as its soluble counterpart, a chemotherapeutic agent and prototypic inductor of immunogenic cell death. The nanoparticle-loaded drug induces cell cycle stop, apoptosis and secondary necrosis in a dose-and time-dependent manner comparable to the free drug. Cell death was accompanied by the release of interleukin-8 and damage-associated molecular patterns (DAMPs) such as HSP70 and ATP, which fostered chemotactic migration of monocytes and maturation of dendritic cells. We furthermore ensured absence of endotoxin contaminations and compatibility with erythrocytes and platelets and investigated the influence on plasma coagulation in vitro. Summarizing, with magnetic enrichment, mitoxantrone can be accumulated at the desired place, sparing healthy peripheral cells and tissues, such as immune cells. Conserving immune competence in cancer patients in the future might allow combined therapeutic approaches with immune therapies (e.g. checkpoint inhibitors).
CRIS-Team Scopus Importer:2020-10-09
Keywords: Cell death; Chemotherapy; Iron oxide nanoparticles; Magnetic drug targeting; Nanomedicine

Mitoxantrone-loaded superparamagnetic iron oxide nanoparticles as drug carriers for cancer therapy: Uptake and toxicity in primary human tubular epithelial cells - Cicha, Iwona; Scheffler, Laura; Ebenau, Astrid; Lyer, Stefan; Alexiou, Christoph; Goppelt-Strübe, Margarete (Nanotoxicology, 2016)
Superparamagnetic iron oxide nanoparticles (SPIONs) are in use for many clinical diagnostic and experimental therapeutic applications, for example, for targeted drug delivery. To analyze the cellular responses to mitoxantrone-carrying SPIONs (SPION-MTO), and to the drug released from SPIONs, we used an in vitro system that allows comparison of primary human cells with different endocytotic capacities, namely, epithelial cells from proximal and distal parts of the nephron. SPIONs were selectively and rapidly internalized by proximal tubular cells with high endocytotic potential, but not by distal tubular cells. Uptake did not affect cell viability or morphology. In both cell types, free MTO (10-100 nM) induced double-strand DNA breaks and senescence, cell hypertrophy and reduced cell proliferation. However, cadherin-mediated cell-cell adhesion, cytoskeletal structures or polarity of the cells were not affected. Interestingly, a comparable response was also observed upon treatment with SPION-MTO and was independent of uptake of the particles. The effect of SPION-MTO on cells which did not internalize particles was primarily related to the release of MTO from drug-coated particles upon incubation in serum-containing cell growth medium. In conclusion, we show that whereas the uptake of SPIONs does not affect cellular functions or viability, the toxicity of drug-loaded SPIONs depends essentially on the type of drug bound to nanoparticles. Due to the relatively low systemic toxicity of MTO, the effects of MTO-SPIONs on human tubular cells were moderate, but they may become clinically relevant when more nephrotoxic drugs are bound to SPIONs.
EVALuna2:3835

Mitoxantrone loaded superparamagnetic nanoparticles for drug targeting: A versatile and sensitive method for quantification of drug enrichment in rabbit tissues using HPLC-UV - Tietze, Rainer; Schreiber, Eveline; Lyer, Stefan; Alexiou, Christoph (Journal of Biomedicine and Biotechnology, 2010)
In medicine, superparamagnetic nanoparticles bound to chemotherapeutics are currently investigated for their feasibility in local tumor therapy. After intraarterial application, these particles can be accumulated in the targeted area by an external magnetic field to increase the drug concentration in the region of interest (Magnetic-Drug-Targeting). We here present an analytical method (HPLC-UV), to detect pure or ferrofluid-bound mitoxantrone in a complex matrix even in trace amounts in order to perform biodistribution studies. Mitoxantrone could be extracted in high yields from different tissues. Recovery of mitoxantrone in liver tissue (5000ng/g) was 76 ± 2 . The limit of quantification of mitoxantrone standard was 10ng/mL ± 1 2 . Validation criteria such as linearity, precision, and stability were evaluated in ranges achieving the FDA requirements. As shown for pilot samples, biodistribution studies can easily be performed after application of pure or ferrofluid-bound mitoxantrone. Copyright © 2010 Rainer Tietze et al.
CRIS-Team Scopus Importer:2022-06-27

Modeling the pre-phonatory vocal fold posture in the larynx model SynthVOICE - Kniesburges, Stefan; Veltrup, Reinhard; Fattoum, Sahar; Schützenberger, Anne (Proceedings of the International Congress on Acoustics, 2019)
This work presents a synthetic larynx model that includes the adduction motion and the elongation of the vocal folds. Beside the description of the model, validation measurements and their results will be presented.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Fluid-structure interaction; Phonation; Synthetic larynx model

Models of tinnitus development. From cochlea to cortex - Krauß, Patrick; Schilling, Achim; Tziridis, Konstantin; Schulze, Holger (HNO, 2019)
The development of subjective tinnitus is still not mechanistically understood and existing models are controversially discussed. In this overview, the authors discuss three of the main models, all of which propose damage to the cochlea as the initial step in tinnitus development. Based on these models, apossible manifestation of tinnitus-related neuronal activity at the perceptually relevant level of the auditory pathway, the auditory cortex, is presented. Furthermore, it is demonstrated that one of the models offers anew view on the phenomenon, which could potentially help patients to better cope with their condition.
CRIS-Team WoS Importer:2019-03-26

Modulation of immune responses by nanoparticles - Janko, Christina; Friedrich, Ralf P.; Cicha, Iwona; Unterweger, Harald; Lyer, Stefan; Alexiou, Christoph (Nanomedicine, 2021)
CRIS-Team WoS Importer:2021-08-27

Modulation of immune responses to liposomal vaccines by intrastructural help - Damm, Dominik; Suleiman, Ehsan; Wagner, Jannik; Klessing, Stephan; Pfister, Felix; Elsayed, Hassan; Walkenfort, Bernd; Stobrawe, Jule; Mayer, Julia; Lehner, Elisabeth; Müller-Schmucker, Sandra; Hasenberg, Mike; et al. (European Journal of Pharmaceutics and Biopharmaceutics, 2023)
The encapsulation of HIV-unrelated T helper peptides into liposomal vaccines presenting trimers of the HIV-1 envelope glycoprotein (Env) on the surface (T helper liposomes) may recruit heterologous T cells to provide help for Env-specific B cells. This mechanism called intrastructural help can modulate the HIV-specific humoral immune response. In this study, we used cationic T helper liposomes to induce intrastructural help effects in a small animal model. The liposomes were functionalized with Env trimers by a tag-free approach designed to enable a simplified GMP production. The pre-fusion conformation of the conjugated Env trimers was verified by immunogold electron microscopy (EM) imaging and flow cytometry. The liposomes induced strong activation of Env-specific B cells in vitro. In comparison to previously established anionic liposomes, cationic T helper liposomes were superior in CD4+ T cell activation after uptake by dendritic cells. Moreover, the T helper liposomes were able to target Env-specific B cells in secondary lymphoid organs after intramuscular injection. We also observed efficient T helper cell activation and proliferation in co-cultures with Env-specific B cells in the presence of cationic T helper liposomes. Mouse immunization experiments with cationic T helper liposomes further revealed a modulation of the Env-specific IgG subtype distribution and enhancement of the longevity of antibody responses by ovalbumin- and Hepatitis B (HBV)-specific T cell help. Thus, clinical evaluation of the concept of intrastructural help seems warranted.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Env trimer; Functionalization; HIV vaccine; IgG subtype; Intrastructural help; Nanoparticle; Peptide encapsulation; T helper liposomes

Molecular communication using magnetic nanoparticles - Wicke, Wayan; Ahmadzadeh, Arman; Jamali Kooshkghazi, Vahid; Unterweger, Harald; Alexiou, Christoph; Schober, Robert (Proceedings of IEEE Wireless Communications and Networking Conference (WCNC), 2018)

Monitoring of balloon test occlusion of the internal carotid artery by parametric color coding and perfusion imaging within the angio suite: first results - Struffert, Tobias; Deuerling-Zheng, Y.; Engelhorn, Tobias; Kloska, Stephan; Gölitz, Philipp; Bozzato, A.; Kapsreiter, M.; Strother, C. M.; Dörfler, Arnd (Clinical Neuroradiology, 2013)
Temporary balloon test occlusion (BTO) might be performed prior to procedures in which occlusion of the internal carotid artery (ICA) might be necessary. We tested the hypothesis that parametric color coding (PCC) of angiographic series (digital subtraction angiography (DSA)) along with the assessment of cerebral blood volume (CBV) in the angiography suite would simplify and enhance the identification of candidates who are most likely to tolerate occlusion.Fifteen patients underwent angiographic series (DSA) and perfusion imaging before and during BTO. Pre- and postocclusion DSA acquisitions were evaluated for venous delay by conventional methods ("eye balling") and by PCC measurements. Comparison of CBV values between the left and right hemisphere in 6 defined regions was performed.Values of venous delay by eye balling and PCC showed a high correlation (r = 0.87, p < 0.01). Bland-Altman plot indicated slightly lower values (-0.05 s) by the PCC method. One of the 15 patients developed an asymmetrical CBV map with an increase in CBV of more than one standard deviation in 3 of the 6 regions of interest (ROIs). Acquisition of angiographic series and perfusion imaging did not prolong the test occlusion time.PCC and CBV mapping are feasible during BTO. The use of PCC seems to simplify the ability to measure changes in venous filling delay. Perfusion imaging may show an increase in CBV in patients reaching the limits of cerebral autoregulation. These patients may be at risk for delayed infarction, even though they seem to tolerate temporary occlusion, and could be unsuitable candidates for permanent ICA occlusion.
EVALuna2:22981

Moonlighting chromatin: when DNA escapes nuclear control - Singh, Jeeshan; Boettcher, Michael; Dölling, Maximilian; Heuer, Annika; Hohberger, Bettina; Leppkes, Moritz; Naschberger, Elisabeth; Schapher, Mirco; Schauer, Christine; Schoen, Janina; Stürzl, Michael; Vitkov, Ljubomir; et al. (Cell Death and Differentiation, 2023)
Extracellular chromatin, for example in the form of neutrophil extracellular traps (NETs), is an important element that propels the pathological progression of a plethora of diseases. DNA drives the interferon system, serves as autoantigen, and forms the extracellular scaffold for proteins of the innate immune system. An insufficient clearance of extruded chromatin after the release of DNA from the nucleus into the extracellular milieu can perform a secret task of moonlighting in immune-inflammatory and occlusive disorders. Here, we discuss (I) the cellular events involved in the extracellular release of chromatin and NET formation, (II) the devastating consequence of a dysregulated NET formation, and (III) the imbalance between NET formation and clearance. We include the role of NET formation in the occlusion of vessels and ducts, in lung disease, in autoimmune diseases, in chronic oral disorders, in cancer, in the formation of adhesions, and in traumatic spinal cord injury. To develop effective therapies, it is of utmost importance to target pathways that cause decondensation of chromatin during exaggerated NET formation and aggregation. Alternatively, therapies that support the clearance of extracellular chromatin are conceivable. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-02-17

Multicentric analysis of the use behavior of cochlear implant users - Oberhoffner, Tobias; Hoppe, Ulrich; Hey, Matthias; Hecker, Dietmar; Bagus, Heike; Voigt, Peter; Schicktanz, Silvia; Braun, Astrid; Hocke, Thomas (Laryngo-Rhino-Otologie, 2018)
INTRODUCTION: Novel cochlear implant speech processors are capable of storing data logs. With the help of this information a more individualized patient care can be provided. However, standard data are missing to a greater extent to the individual usage behavior. MATERIALS AND METHODS: In a retrospective study, the use data of 2687 patients were evaluated. All patients had the Nucleus 6 system from Cochlear Ltd. RESULTS: The data allow a normal range to be defined for the duration of use of cochlear implant speech processors. Likewise, the identification of conspicuous usage behavior is possible.
EVALuna2:35456

Multilayered blow-spun vascular prostheses with luminal surfaces in Nano/Micro range: the influence on endothelial cell and platelet adhesion - Łopianiak, Iwona; Rzempołuch, Wiktoria; Civelek, Mehtap; Cicha, Iwona; Ciach, Tomasz; Butruk-Raszeja, Beata A. (Journal of Biological Engineering, 2023)
Background: In this study, two types of polyurethane-based cylindrical multilayered grafts with internal diameters ≤ 6 mm were produced by the solution blow spinning (SBS) method. The main aim was to create layered-wall prostheses differing in their luminal surface morphology. Changing the SBS process parameters, i.e. working distance, rotational speed, volume, and concentration of the polymer solution allowed to obtain structures with the required morphologies. The first type of prostheses, termed Nano, possessed nanofibrous luminal surface, and the second type, Micro, presented morphologically diverse luminal surface, with both solid and microfibrous areas. Results: The results of mechanical tests confirmed that designed prostheses had high flexibility (Young’s modulus value of about 2.5 MPa) and good tensile strength (maximum axial load value of about 60 N), which meet the requirements for vascular prostheses. The influence of the luminal surface morphology on platelet adhesion and the attachment of endothelial cells was investigated. Both surfaces did not cause hemolysis in contact with blood, the percentage of platelet-occupied area for Nano and Micro surfaces was comparable to reference polytetrafluoroethylene (PTFE) surface. However, the change in morphology of surface-adhered platelets between Nano and Micro surfaces was visible, which might suggest differences in their activation level. Endothelial coverage after 1, 3, and 7 days of culture on flat samples (2D model) was higher on Nano prostheses as compared with Micro scaffolds. However, this effect was not seen in 3D culture, where cylindrical prostheses were colonized using magnetic seeding method. Conclusions: We conclude the produced scaffolds meet the material and mechanical requirements for vascular prostheses. However, changing the morphology without changing the chemical modification of the luminal surface is not sufficient to achieve the appropriate effectiveness of endothelialization in the 3D model.
CRIS-Team Scopus Importer:2023-03-31
Keywords: Endothelial cells; Hemocompatibility; Magnetic seeding; Multilayered small-diameter vascular grafts; Nanofibers; Solution blow spinning

Multimodal treatment in difficult sialolithiasis: Role of extracorporeal shock-wave lithotripsy and intraductal pneumatic lithotripsy - Schapher, Mirco; Koch, Michael; Schapher, Mirco; Mantsopoulos, Konstantinos; von Scotti, Felix; Goncalves, Miguel; Iro, Heinrich (Laryngoscope, 2017)
OBJECTIVES: To assess results after treatment of difficult/complex sialolithiasis with extracorporeal shock-wave lithotripsy (ESWL) and intraductal pneumatic lithotripsy (IPL). STUDY DESIGN: Retrospective study in a tertiary referral center. METHODS: Altogether, 63 stones were diagnosed in 38 patients with difficult/complex sialolithiasis. Forty-nine stones were treated with fragmentation using both ESWL and IPL. Stones accessible with the sialendoscope were treated primarily with IPL in multiple sialolithiasis. RESULTS: Seventy-one ESWL procedures and 57 IPL were performed in our patients. Forty-nine stones were treated by 67 ESWL procedures and 52 IPL. ESWL converted sialoliths from sialendoscopically untreatable into sialendoscopically treatable cases in 94.7%; the treatment then was completed by a total of 52 IPL procedures. ESWL was performed before IPL (81.6%), in combination with IPL (7.9%) and after (10.5%). Complete fragmentation was achieved in 97.9%. Four stones each were treated with ESWL and IPL alone in multiple sialolithiasis. Altogether, 53 stones were treated by 57 IPL procedures. Complete fragmentation was achieved in 98.1% of the 53 stones. ESWL and IPL were the dominant treatment modalities in 84.1% of all 63 stones treated. Of all 38 patients, 92.1% became stone-free and all became symptom-free. All the glands were preserved. Multiple stones were treated in 34.2% of the patients; of these, 92.3% became stone-free. CONCLUSION: These results show that patients with difficult and complex sialolithiasis can be treated with high success rates of > 90% using a multimodal, minimally invasive, and gland-preserving treatment approach. ESWL and IPL played a key role in this multimodal treatment regime in > 80% of stones. LEVEL OF EVIDENCE: 4. Laryngoscope, 2017.
EVALuna2:33362

Myringoplasty for pediatric chronic otitis media: An uncritical closure of a natural middle ear drainage? - Mantsopoulos, Konstantinos; Thimsen, Vivian; Richter, Daniel; Müller-Hübner, Sarina; Sievert, Matti; Iro, Heinrich; Hornung, Joachim (American Journal of Otolaryngology, 2021)
Background: Performing tympanoplasty for tympanic perforations in children and adolescents is often considered to be less successful than in adults. Objectives: The aim of our study was to evaluate the surgical outcome of tympanoplasty type I in patients under 15 years of age with chronic otitis media and to identify potential factors that influence the success rate. Materials und methods: The present study was based on a retrospective analysis of the medical records of all patients under the age of 15 who were treated for chronic otitis media by means of type I tympanoplasty between 2005 and 2020. The minimum follow-up period was 6 months. The data were analyzed with regard to epidemiological parameters, tube-related pathologies in the contralateral ear, the local condition and the extent of the eardrum perforation as well as the extent of the surgical intervention (tympanoplasty type I with or without adenotomy). Results: 83 cases were included in our study. The mean age at the time of the surgery was 8.9 years. The mean follow-up time was 46 months (6–182 months). The anatomical closure rate was 88.0%. Children with “dry” tympanic perforations tended to perform better (p = 0.052). The average improvement in the air bone gap was 2.0 dB. Conclusion: Detailed preoperative counseling about the advantages and disadvantages as well as the expected success rate of an early myringoplasty in this age group is just as important as an individualized approach for a high level of patient satisfaction.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Cartilage; Chronic otitis media; Myringoplasty; Tympanic perforation; Tympanoplasty

N-Alkylaminoferrocene-Based Prodrugs Targeting Mitochondria of Cancer Cells - Reshetnikov, Viktor; Özkan, Hülya; Daum, Steffen; Janko, Christina; Alexiou, Christoph; Sauer, Caroline; Heinrich, Markus; Mokhir, Andriy (Molecules, 2020)
Intracellular concentration of reactive oxygen species (e.g., H2O2) in cancer cells is elevated over 10-fold as compared to normal cells. This feature has been used by us and several other research groups to design cancer specific prodrugs, for example, N-alkylaminoferrocene (NAAF)-based prodrugs. Further improvement of the efficacy of these prodrugs can be achieved by their targeting to intracellular organelles containing elevated reactive oxygen species (ROS) amounts. For example, we have previously demonstrated that lysosome-targeted NAAF-prodrugs exhibit higher anticancer activity in cell cultures, in primary cells and in vivo (Angew. Chem. Int. Ed. 2017, 56, 15545). Mitochondrion is an organelle, where electrons can leak from the respiratory chain. These electrons can combine with O2, generating O2-• that is followed by dismutation with the formation of H2O2. Thus, ROS can be generated in excess in mitochondria and targeting of ROS-sensitive prodrugs to these organelles could be a sensible possibility for enhancing their efficacy. We have previously reported on NAAF-prodrugs, which after their activation in cells, are accumulated in mitochondria (Angew. Chem. Int. Ed. 2018, 57, 11943). Now we prepared two hybrid NAAF-prodrugs directly accumulated in mitochondria and activated in these organelles. We studied their anticancer activity and mode of action. Based on these data, we concluded that ROS produced by mitochondria is not available in sufficient quantities for activation of the ROS-responsive prodrugs. The reason for this can be efficient scavenging of ROS by antioxidants. Our data are important for the understanding of the mechanism of action of ROS-activatable prodrugs and will facilitate their further development.
CRIS-Team Scopus Importer:2020-06-16
Keywords: cancer; mitochondrion; N-alkylaminoferrocene; prodrug; reactive oxygen species

Nano-biomaterials for cardiovascular applications: Clinical perspective - Cicha, Iwona; Singh, Raminder; Garlichs, Christoph D.; Alexiou, Christoph (Journal of Controlled Release, 2016)
Cardiovascular diseases, including ischemic heart disease and stroke, are responsible for nearly 25% of all deaths worldwide. Globally, their prevalence continues to increase, in spite of enormous progress in cardiovascular diagnostics and therapy. For therapeutic and regenerative purposes, biomaterials promise solutions with multiple advantages over synthetic materials. Furthermore, their easy availability as nanoformulations recommends their application as drug carriers or protective nanoshells improving the biocompatibility of imaging agents. In this work, we review the most promising and clinically meaningful scientific reports with regard to (nano)biomaterials with particular focus on potential improvements of existing, and development of novel constructs for cardiovascular applications.
EVALuna2:20019

'Nano-lysing' the disease process: novel diagnostic and therapeutic nanoparticles - Janko, Christina; Friedrich, Ralf P.; Poettler, Marina; Cicha, Iwona; Lyer, Stefan; Unterweger, Harald; Alexiou, Christoph (Nanomedicine, 2018)
EVALuna2:35455

Nanomaterial-based ophthalmic therapies - Unterweger, Harald; Janko, Christina; Civelek, Mehtap; Cicha, Iwona; Spielvogel, Helmut; Tietze, Rainer; Friedrich, Bernhard; Alexiou, Christoph (Nanomedicine, 2023)
CRIS-Team Scopus Importer:2023-09-01
Keywords: age-related macular degeneration; diabetic retinopathy; eye infections; glaucoma; keratitis; nanoparticles

Nanomedical innovation: the SEON-concept for an improved cancer therapy with magnetic nanoparticles - Lyer, Stefan; Tietze, Rainer; Unterweger, Harald; Zaloga, Jan; Singh, Raminder; Matuszak, Jasmin; Poettler, Marina; Friedrich, Ralf P.; Dürr, Stephan; Cicha, Iwona; Janko, Christina; Alexiou, Christoph (Nanomedicine, 2015)
Nanomedicine offers tremendous opportunities for the development of novel therapeutic and diagnostic tools. During the last decades, extensive knowledge was gained about stabilizing and the coating of nanoparticles, their functionalization for drug binding and drug release and possible strategies for therapies and diagnostics of different diseases. Most recently, more and more emphasis has been placed on nanotoxicology and nanosafety aspects. The section of experimental oncology and nanomedicine developed a concept for translating this knowledge into clinical application of magnetic drug targeting for the treatment of cancer and other diseases using superparamagnetic iron oxide nanoparticles. This approach includes reproducible synthesis, detailed characterization, nanotoxicological testing, evaluation in ex vivo models, preclinical animal studies and production of superparamagnetic iron oxide nanoparticles according to good manufacturing practice regulations.
EVALuna2:19990

Nanomedicine for cardiovascular disorders - Cicha, Iwona; Unterweger, Harald; Lyer, Stefan; Janko, Christina; Friedrich, Ralf P.; Pöttler, Marina; Alexiou, Christoph (Nanomedicine, 2019)
CRIS-Team Scopus Importer:2019-12-31
Keywords: aneurysm; atherothrombosis; cardiovascular diseases; metabolic disease; myocardial infarction; stroke

Nanomedicine for neuroprotection - Friedrich, Ralf P.; Poettler, Marina; Cicha, Iwona; Unterweger, Harald; Janko, Christina; Alexiou, Christoph (Nanomedicine, 2018)
EVALuna2:35446

Nanomedicine for vaccination and diagnosis of diseases - Lyer, Stefan; Janko, Christina; Friedrich, Ralf P.; Cicha, Iwona; Tietze, Rainer; Unterweger, Harald; Alexiou, Christoph (Nanomedicine, 2021)
CRIS-Team Scopus Importer:2021-03-05
Keywords: cancer; disease detection; immunotherapy; vaccinations; viral infections

Nanomedicine in diagnostics and therapy of cardiovascular diseases: Beyond atherosclerotic plaque imaging - Cicha, Iwona; Lyer, Stefan; Alexiou, Christoph; Garlichs, Christoph (Nanotechnology Reviews, 2013)
Atherosclerosis results from the accumulation of the modified lipoproteins within the artery walls, which triggers complex vascular inflammatory processes. Although the pharmacologic agents for the treatment of clinical manifestations of atherosclerosis are available, their systemic delivery has serious disadvantages, such as considerable side effects or low efficacy at tolerated doses. Moreover, the treatment of atherosclerosis using the interventional techniques bears further shortcomings: the implanted stents require a lengthy antiplatelet therapy and carry the risk of in-stent restenosis. In the surgical approach to atherosclerosis, apart from the overall risk of open heart surgery, the lack of adequate venous material for bypasses constitutes a common problem. The nanotechnology has the potential to overcome the disadvantages of the current therapy of atherosclerosis, e.g., by the formation of nanosized assemblies for the earlier detection of atherosclerotic lesions and for cell-specific delivery of therapeutics. Replacing the current systemic pharmacological approach by a locally targeted treatment of plaques can substantially minimize the adverse effects, by lowering the drug cytotoxicity and reducing the required dosage. Moreover, a new generation of nanotechnological approaches to the revascularization procedures is now emerging, e.g., vascular tissue engineering utilizing the magnetic nanoparticles or the design of stents with the reduced risk of thrombosis and restenosis. This review discusses the possible applications of the nanomedical approaches in the treatment of cardiovascular diseases.
CRIS-Team Scopus Importer:2022-06-27
Keywords: Atherosclerosis; Nanoparticles; Plaque imaging; Stent design; Vascular tissue engineering

Nanomedicine in otorhinolaryngology future prospects Nanomedizin in der HNO-Heilkunde ein Ausblick - Dürr, Stephan; Tietze, Rainer; Lyer, Stefan; Alexiou, Christoph (Laryngo-Rhino-Otologie, 2012)
Nanomedicine in Otorhinolaryngology Future Prospects Background: Nanotechnology becomes more and more important in the world of today. Equally, it does generally in medicine and of course specifically in otorhinolaryngology. Essentially, there are the following fields: Diagnostics, new therapies and agents, drug delivery and medical implants. Material and Methods: An extensive literature research on nanomedicine in otorhinolaryngology was carried out in the standard online medical reference databases PubMed/Medline and Web of Science. Furthermore, we are giving an overview of the work of the Department of Otorhinolaryngology, Head and Neck Surgery, Section of Experimental Oncology and Nanomedicine (SEON), University Hospital Erlangen. Results: A lot of new and innovative studies on nanotechnology in diagnostics and therapy were recovered. Depending on the variety in otorhinolaryngology, there are numerous versatile approaches, according to the different areas. The main part is engaged in drug delivery. Conclusions: The efforts to exploit the potential of nanotechnology in otorhinolaryngology are multifaceted, innovative and seminal. The best perspective of success is attributed to nanoparticulate drug delivery systems. © Georg Thieme Verlag KG Stuttgart . New York.
CRIS-Team Scopus Importer:2022-06-27
Keywords: drug delivery; magnetic drug targeting; nanomedicine; nanoparticles; otorhinolaryngology

Nanomedicine. Magnetic nanoparticles for drug delivery and hyperthermia - New chances for cancer therapy Pharmakotherapie mittels nanomedizin. Magnetische nanopartikel für drug delivery und hyperthermie - Neue chancen für die krebsbehandlung - Alexiou, Christoph; Tietze, Rainer; Schreiber, Eveline; Lyer, Stefan (Onkologe, 2011)
The application of nanotechnology for the treatment, diagnosis, and monitoring of illnesses is summarized under the term nanomedicine. A particularly promising application is attributed to nanoparticular drug delivery systems. The goal of these new carrier systems is the selective enrichment of active substances in diseased tissue structures, an increase in bioavailability, the decrease of the active substance degradation and, above all, the reduction and/or avoidance of unwanted side effects. Apart from numerous nanosystems acting as carriers, the use of iron oxide nanoparticles has to be particularly emphasized. On the one hand, those particles are the carriers of the active substance and, on the other hand, can also be visualized with conventional imaging techniques (x-ray tomography, magnetic resonance imaging), called theranostic. In addition, they can be used for hyperthermia, another important supporting pillar of nanomedicine. Both procedures should lead to a personalized and goal-oriented therapy, which is of special medical and socioeconomic importance in view of the increasing number of cancer patients worldwide. © 2011 Springer-Verlag.
CRIS-Team Scopus Importer:2022-06-27
Keywords: Drug delivery; Hyperthermia; Magnetic drug targeting; Nanomedicine; Nanoparticles

Nanoparticles for cancer therapy using magnetic forces - Tietze, Rainer; Lyer, Stefan; Dürr, Stephan; Alexiou, Christoph (Nanomedicine, 2012)
The term 'nanomedicine' refers to the use of nanotechnology in the treatment, diagnosis and monitoring of diseases. Magnetic drug targeting is a particularly promising application in this field. The goal of the carrier systems involved is to achieve active enrichment of effective substances in diseased tissue. Numerous nanosystems can be used as carriers, but magnetic iron oxide nanoparticles are particularly important. On the one hand, the particles serve as carriers for the active substance, while on the other hand they can also be visualized using conventional imaging techniques and can therefore be used for 'theranostic' purposes. They can also be used in hyperthermia, another important pillar of nanomedicine. Both procedures are intended to lead to specific forms of treatment, which is of medical and economic relevance in view of the increasing numbers of cancer patients worldwide. This study offers a brief overview of current developments in medical applications for magnetic nanoparticles in cancer therapy. © 2012 Future Medicine Ltd.
CRIS-Team Scopus Importer:2022-06-27
Keywords: cancer therapy; chemotherapy; drug delivery; iron oxide nanoparticles; magnetic drug targeting

Nanoparticles for intravascular applications: physicochemical characterization and cytotoxicity testing - Matuszak, Jasmin; Baumgartner, Jens; Zaloga, Jan; Juenet, Maya; Da Silva, Acarilia Eduardo; Franke, Danielle; Almer, Gunter; Texier, Isabelle; Faivre, Damien; Metselaar, Josbert M.; Navarro, Fabrice P.; Chauvierre, Cedric; et al. (Nanomedicine, 2016)
We report the physicochemical analysis of nanosystems intended for cardiovascular applications and their toxicological characterization in static and dynamic cell culture conditions.Size, polydispersity and ?-potential were determined in 10 nanoparticle systems including liposomes, lipid nanoparticles, polymeric and iron oxide nanoparticles. Nanoparticle effects on primary human endothelial cell viability were monitored using real-time cell analysis and live-cell microscopy in static conditions, and in a flow model of arterial bifurcations.The majority of tested nanosystems were well tolerated by endothelial cells up to the concentration of 100 ?g/ml in static, and up to 400 ?g/ml in dynamic conditions. Pilot experiments in a pig model showed that intravenous administration of liposomal nanoparticles did not evoke the hypersensitivity reaction. These findings are of importance for future clinical use of nanosystems intended for intravascular applications.
EVALuna2:20021

Nanoparticles for radiooncology: Mission, vision, challenges - Kunz-Schughart, Leoni A.; Dubrovska, Anna; Peitzsch, Claudia; Ewe, Alexander; Aigner, Achim; Schellenburg, Samuel; Muders, Michael H.; Hampel, Silke; Cirillo, Giuseppe; Iemma, Francesca; Tietze, Rainer; Alexiou, Christoph; et al. (Biomaterials, 2017)
Cancer is one of the leading non-communicable diseases with highest mortality rates worldwide. About half of all cancer patients receive radiation treatment in the course of their disease. However, treatment outcome and curative potential of radiotherapy is often impeded by genetically and/or environmentally driven mechanisms of tumor radioresistance and normal tissue radiotoxicity. While nanomedicine-based tools for imaging, dosimetry and treatment are potential keys to the improvement of therapeutic efficacy and reducing side effects, radiotherapy is an established technique to eradicate the tumor cells. In order to progress the introduction of nanoparticles in radiooncology, due to the highly interdisciplinary nature, expertise in chemistry, radiobiology and translational research is needed. In this report recent insights and promising policies to design nanotechnology-based therapeutics for tumor radiosensitization will be discussed. An attempt is made to cover the entire field from preclinical development to clinical studies. Hence, this report illustrates (1) the radio- and tumor-biological rationales for combining nanostructures with radiotherapy, (2) tumor-site targeting strategies and mechanisms of cellular uptake, (3) biological response hypotheses for new nanomaterials of interest, and (4) challenges to translate the research findings into clinical trials.
EVALuna2:33374

Nanoparticles for regenerative medicine - Pöttler, Marina; Cicha, Iwona; Unterweger, Harald; Janko, Christina; Friedrich, Ralf P.; Alexiou, Christoph (Nanomedicine, 2019)
CRIS-Team Scopus Importer:2019-08-20
Keywords: cilia restoration; nanoparticles for functional recovery; osteogenesis; remyelination; tissue regeneration

Nanoparticles for the treatment of inflammatory conditions - Janko, Christina; Civelek, Mehtap; Cicha, Iwona; Spielvogel, Helmut; Unterweger, Harald; Alexiou, Christoph (Nanomedicine, 2024)
CRIS-Team Scopus Importer:2024-02-16
Keywords: cytokine storm; drug delivery; hypertension; inflammation; ischemia–reperfusion injury; nanosystems; periodontitis; pneumonia

Nanoparticles size-dependently initiate self-limiting NETosis-driven inflammation - Munoz, Luis E.; Bilyy, Rostyslav; Biermann, Mona H. C.; Kienhoefer, Deborah; Maueröder, Christian; Hahn, Jonas; Brauner, Jan M.; Weidner, Daniela; Chen, Juan; Scharin-Mehlmann, Marina; Janko, Christina; Friedrich, Ralf P.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2016)
The critical size for strong interaction of hydrophobic particles with phospholipid bilayers has been predicted to be 10 nm. Because of the wide spreading of nonpolar nanoparticles (NPs) in the environment, we aimed to reveal the ability of living organisms to entrap NPs via formation of neutrophil extracellular traps (NETs). Upon interaction with various cell types and tissues, 10- to 40-nm-sized NPs induce fast (<20 min) damage of plasma membranes and instability of the lysosomal compartment, leading to the immediate formation of NETs. In contrast, particles sized 100-1,000 nm behaved rather inertly. Resulting NET formation (NETosis) was accompanied by an inflammatory reaction intrinsically endowed with its own resolution, demonstrated in lungs and air pouches of mice. Persistence of small NPs in joints caused unremitting arthritis and bone remodeling. Small NPs coinjected with antigen exerted adjuvant-like activity. This report demonstrates a cellular mechanism that explains how small NPs activate the NETosis pathway and drive their entrapping and resolution of the initial inflammatory response.
EVALuna2:13106

Nanotechnologies in tissue engineering - Bigdeli, Amir K.; Lyer, Stefan; Detsch, Rainer; Boccaccini, Aldo R.; Beier, Justus; Kneser, Ulrich; Horch, Raymund E.; Arkudas, Andreas (Nanotechnology Reviews, 2013)
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.nanote

Near-infrared sentinel diagnostics in head and neck squamous cell carcinoma: a systematic review - Sievert, Matti; Mantsopoulos, Konstantinos; Iro, Heinrich; Koch, Michael (Laryngo-Rhino-Otologie, 2021)
Zusammenfassung
CRIS-Team WoS Importer:2021-06-25

Nearly 3,000 salivary stones: some clinical and epidemiologic aspects - Sigismund, Paolo E.; Zenk, Johannes; Koch, Michael; Schapher, Mirco; Rudes, Mihael; Iro, Heinrich (Laryngoscope, 2015)
To investigate epidemiological features and symptoms of sialolithiasis and their implications for diagnosis and management.Retrospective cohort study.Retrospective analysis on 2,322 patients with sialolithiasis, between 1987 and 2009. The statistical significance between two sample distributions was computed using analysis of variance Student t test for two-tailed distribution.A total of 2,959 calculi were identified by means of ultrasound. Of those, 80.4% were located in the submandibular duct system (53% hilar/proximal, 37% distal, 10% intraparenchymal) and 19.6% were parotid stones (83% in Stensen's duct, 17% intraparenchymal). Sialoliths had been discovered beforehand in the submandibular gland (P = 0.00024; t test). Symptoms, measured from first visit, lasted on average 26 months (range: 1 day-30 years). The main group suffered from swelling (50.3%), followed by painful swelling (41.6%) and pain (3.1%). Multiple stones were found in 16.9% of patients (18.1% in the submandibular gland; 14.3% in the parotid). Average stone diameter in the submandibular gland was 8.3 mm (range 1-35 mm), and the stones were in Lustmann group II (46%). In the parotid gland, the average diameter was 6.4 mm (range 1-31 mm), and 51% were in Lustmann group I.Nowadays, epidemiologic features and clinical manifestations of sialolithiasis play an important role, assisting not only in diagnosis but also in determining appropriate treatment. Due to their location and smaller diameter, parotid stones in some cases can only be treated using a mini-invasive endoscopic technique. Submandibular stones more often require a combined approach.4
EVALuna2:19993

Negatively charged magnetic nanoparticles pass the blood-placenta barrier under continuous flow conditions in a time-dependent manner - Gresing, Lennart J.; Radon, Patricia; Friedrich, Ralf P.; Zahn, Diana; Raasch, Martin; Mosig, Alexander S.; Dutz, Silvio; Alexiou, Christoph; Wiekhorst, Frank; Hochhaus, Andreas; Clement, Joachim H. (Journal of Magnetism and Magnetic Materials, 2021)
The transfer of substances via the blood-placenta barrier is tightly regulated and critical for the fetus and the expecting mother. In case of necessary medical interventions during pregnancy a comprehensive knowledge about the interaction of the drugs with this barrier is indispensable. Therefore well-engineered test systems are needed and valuable transport systems are helpful. We developed an in vitro microfluidic blood-placenta barrier system consisting of the human trophoblast cell line BeWo and human primary placental pericytes. The integrity and stability of the model was verified by a permeability assay and immunocytochemistry. As potential drug carriers magnetic nanoparticles with various coatings were applied and their ability to pass the barrier was quantified by magnetic particle spectroscopy. We could demonstrate that up to 4% of negatively charged nanoparticles pass the barrier in a time-dependent manner.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Blood-placenta barrier; Magnetic particle spectroscopy; Microfluidics; Placental pericyte

Neural correlates of linguistic collocations during continuous speech perception - Garibyan, Armine; Schilling, Achim; Boehm, Claudia; Zankl, Alexandra; Krauß, Patrick (Frontiers in Psychology, 2022)
Language is fundamentally predictable, both on a higher schematic level as well as low-level lexical items. Regarding predictability on a lexical level, collocations are frequent co-occurrences of words that are often characterized by high strength of association. So far, psycho- and neurolinguistic studies have mostly employed highly artificial experimental paradigms in the investigation of collocations by focusing on the processing of single words or isolated sentences. In contrast, here we analyze EEG brain responses recorded during stimulation with continuous speech, i.e., audio books. We find that the N400 response to collocations is significantly different from that of non-collocations, whereas the effect varies with respect to cortical region (anterior/posterior) and laterality (left/right). Our results are in line with studies using continuous speech, and they mostly contradict those using artificial paradigms and stimuli. To the best of our knowledge, this is the first neurolinguistic study on collocations using continuous speech stimulation.
CRIS-Team WoS Importer:2023-01-27

Neural network-based estimation of biomechanical vocal fold parameters - Donhauser, Jonas; Tur, Bogac; Döllinger, Michael (Frontiers in Physiology, 2024)
Vocal fold (VF) vibrations are the primary source of human phonation. High-speed video (HSV) endoscopy enables the computation of descriptive VF parameters for assessment of physiological properties of laryngeal dynamics, i.e., the vibration of the VFs. However, underlying biomechanical factors responsible for physiological and disordered VF vibrations cannot be accessed. In contrast, physically based numerical VF models reveal insights into the organ’s oscillations, which remain inaccessible through endoscopy. To estimate biomechanical properties, previous research has fitted subglottal pressure-driven mass–spring–damper systems, as inverse problem to the HSV-recorded VF trajectories, by global optimization of the numerical model. A neural network trained on the numerical model may be used as a substitute for computationally expensive optimization, yielding a fast evaluating surrogate of the biomechanical inverse problem. This paper proposes a convolutional recurrent neural network (CRNN)-based architecture trained on regression of a physiological-based biomechanical six-mass model (6 MM). To compare with previous research, the underlying biomechanical factor “subglottal pressure” prediction was tested against 288 HSV ex vivo porcine recordings. The contributions of this work are two-fold: first, the presented CRNN with the 6 MM handles multiple trajectories along the VFs, which allows for investigations on local changes in VF characteristics. Second, the network was trained to reproduce further important biomechanical model parameters like VF mass and stiffness on synthetic data. Unlike in a previous work, the network in this study is therefore an entire surrogate of the inverse problem, which allowed for explicit computation of the fitted model using our approach. The presented approach achieves a best-case mean absolute error (MAE) of 133 Pa (13.9%) in subglottal pressure prediction with 76.6% correlation on experimental data and a re-estimated fundamental frequency MAE of 15.9 Hz (9.9%). In-detail training analysis revealed subglottal pressure as the most learnable parameter. With the physiological-based model design and advances in fast parameter prediction, this work is a next step in biomechanical VF model fitting and the estimation of laryngeal kinematics.
CRIS-Team Scopus Importer:2024-03-15
Keywords: convolutional recurrent neural network; high-speed video; mass–spring–damper system; vocal fold dynamics; voice physiology

Neural network based formation of cognitive maps of semantic spaces and the putative emergence of abstract concepts - Stöwer, Paul; Schilling, Achim; Maier, Andreas; Krauß, Patrick (Scientific Reports, 2023)

Neural network based successor representations to form cognitive maps - Stöwer, Paul; Krauß, Patrick; Maier, Andreas (Bernstein Conference, 2022)

Neural network based successor representations to form cognitive maps of space and language - Stöwer, Paul; Schliecker, Christian; Schilling, Achim; Metzner, Claus; Maier, Andreas; Krauß, Patrick (Scientific Reports, 2022)

Neural Networks with Fixed Binary Random Projections Improve Accuracy in Classifying Noisy Data - Yang, Zijin; Schilling, Achim; Maier, Andreas; Krauß, Patrick (Informatik aktuell, 2021)
CRIS-Team Scopus Importer:2021-04-19

'Neuroendocrine' middle ear adenomas: consistent expression of the transcription factor ISL1 further supports their neuroendocrine derivation - Agaimy, Abbas; Lell, Michael; Schaller, Tina; Märkl, Bruno; Hornung, Joachim (Histopathology, 2015)
Neuroendocrine middle ear adenoma (MEA) is a rare epithelial neoplasm of uncertain histogenesis that frequently shows neuroendocrine features. To date, <120 cases have been reported. The aims of the current study were to describe our experience with neuroendocrine MEA, to assess the frequency of specific neuroendocrine differentiation, and to test these lesions for transcription factors known to be expressed in a variety of other neuroendocrine tumours.We investigated six cases of neuroendocrine MEA, and stained them, for the first time, for the transcription factors CDX2, TTF1, PAX8, and ISL1 (islet-1). The patients were four men and two women (mean age, 39 years; range, 27-53 years). Two of four patients with extended follow-up (4.5-22 years) experienced recurrence at 92 months, and at 9 and 22 years, respectively. One case extending into the external ear coexisted with cholesteatoma. Histological examination showed trabecular, solid, acinar, glandular, cribriform, organoid, nested, diffuse non-cohesive plasmacytoid and pseudoalveolar patterns in varying combinations. Immunohistochemistry showed consistent expression of vimentin (4/4), pancytokeratin (6/6), synaptophysin (6/6), CD56 (4/4), and ISL1 (6/6). A CK7 antibody stained scattered cells in two of five cases. The myoepithelial markers and transcription factors TTF1, CDX2 or PAX8 were not expressed in any of the cases.Middle ear adenoma is an indolent, locally recurring, but generally non-metastasizing neoplasm with uniform expression of synaptophysin and ISL1, indicating true neuroendocrine differentiation. Because of its highly varied cellular and architectural appearance, MEA should be distinguished from tympanic paraganglioma and a variety of rare benign and malignant lesions at this site.
EVALuna2:6634

Neutrophil Extracellular Traps Drive Dacryolithiasis - Zlatar, Leticija; Timm, Thomas; Lochnit, Günter; Bilyy, Rostyslav; Bäuerle, Tobias; Munoz Becerra, Marco; Schett, Georg; Knopf, Jasmin; Heichel, Jens; Ali, Mohammad Javed; Schapher, Mirco; Paulsen, Friedrich; et al. (Cells, 2023)
Mucopeptide concretions, previously called dacryoliths, are macroscopic stones that commonly obstruct the lacrimal sac. The mechanism behind dacryolithiasis remains unclear; however, the involvement of various immune cells, including neutrophils, has been confirmed. These findings remain limited, and no information on neutrophil extracellular traps (NETs), essentially involved in the pathogenesis of other lithiases, is available yet. Here, we employ microcomputed tomography, magnetic resonance tomography, histochemistry, mass spectrometry, and enzyme activity analyses to investigate the role of neutrophils and NETs in dacryolithiasis. We classify mucopeptide concretions into three types, with respect to the quantity of cellular and acellular material, polysaccharides, and mucosubstances. We propose the role of neutrophils and NETs within the existing model of gradual formation and growth of mucopeptide concretions, with neutrophils contributing to the initial stages of dacryolithiasis, as they localized on the inner (older) parts of the tissue. As NETs localized on the outer (newer) parts of the tissue, we link their role to the late stages of dacryolithiasis, presumably maintaining the proinflammatory environment and preventing efficient clearance. An abundance of IgG on the surface indicates the involvement of the adaptive immune system later as well. These findings bring new perspectives on dacryolithiasis, in which the innate and adaptive immune system are essentially involved.
CRIS-Team Scopus Importer:2023-08-11
Keywords: dacryolithiasis; dacryoliths; lacrimal sac; mucopeptide concretions; neutrophil extracellular traps; neutrophils

Neutrophil Extracellular Traps Promote the Development and Growth of Human Salivary Stones - Schapher, Mirco; Koch, Michael; Weidner, Daniela; Scholz, Michael; Wirtz, Stefan; Mahajan, Aparna; Herrmann, Irmgard; Singh, Jeeshan; Knopf, Jasmin; Leppkes, Moritz; Grüneboom, Anika; Alexiou, Christoph; et al. (Cells, 2020)
Salivary gland stones, or sialoliths, are the most common cause of the obstruction of salivary glands. The mechanism behind the formation of sialoliths has been elusive. Symptomatic sialolithiasis has a prevalence of 0.45% in the general population, is characterized by recurrent painful periprandial swelling of the affected gland, and often results in sialadenitis with the need for surgical intervention. Here, we show by the use of immunohistochemistry, immunofluorescence, computed tomography (CT) scans and reconstructions, special dye techniques, bacterial genotyping, and enzyme activity analyses that neutrophil extracellular traps (NETs) initiate the formation and growth of sialoliths in humans. The deposition of neutrophil granulocyte extracellular DNA around small crystals results in the dense aggregation of the latter, and the subsequent mineralization creates alternating layers of dense mineral, which are predominantly calcium salt deposits and DNA. The further agglomeration and appositional growth of these structures promotes the development of macroscopic sialoliths that finally occlude the efferent ducts of the salivary glands, causing clinical symptoms and salivary gland dysfunction. These findings provide an entirely novel insight into the mechanism of sialolithogenesis, in which an immune system-mediated response essentially participates in the physicochemical process of concrement formation and growth.
CRIS-Team Scopus Importer:2020-10-09
Keywords: lithogenesis; neutrophil extracellular traps; neutrophils; salivary glands; salivary stones; sialadenitis; sialolithiasis; stone development; stone growth

New Diagnostic and Therapeutic Aspects of Pancreatic Ductal Adenocarcinoma - Mangge, Harald; Niedrist, Tobias; Renner, Wilfried; Lyer, Stefan; Alexiou, Christoph; Haybaeck, Johannes (Current Medicinal Chemistry, 2017)
BACKGROUND: Pancreatic ductal adenocarcinoma (PDAC) is devastating. Because of its silent nature, the disease is often only diagnosed once it has reached an advanced, frequently inoperable stage. To date, we have no biomarkers that facilitate earlier diagnosis, leaving sufficient time for curative therapy that effectively lowers the very high mortality rate of this cancer entity. Because of this, the life expectancy of patients with PDAC is low (i.e. ≤ 6% five-year survival rates). New data, including particular genetic signatures and features of the stromal architecture of PDAC tumors, may better explain their aggressiveness, their relatively long-lasting painless expansion, and why chemotherapy so frequently fails. The typical tumor-induced stromal desmoplasia is characterized by cancer-associated fibroblasts (CAFs), decreased immune surveillance, cancer-associated neural remodeling, and a very low vascular density. This stromal microenvironment generates hypoxia, nutrient deficiency, immune suppression, and chemoresistance. The combination of factors results in a vicious disease that begins with the long-lasting, asymptomatic development of a large tumor mass, followed by a delayed diagnosis with a high percentage of inoperable states, exhibiting a poor response to all conservative therapeutic options, including radiation, and which ends with metastasis resulting in a rapid fatal outcome. OBJECTIVE: In this article, we review coherences on genetic, cellular, immunological, Nano medical and stromal characteristics of PDAC tissue, and discuss metabolic abnormalities associated with and/or preceding the tumor progression rate. CONCLUSION: A more comprehensive understanding of the underlying mechanisms can improve the diagnostic and therapeutic management of patients suffering from this devastating type of cancer.
EVALuna2:33376

NiTiBOND an optimized self-crimping stapes prosthesis for treatment of otosclerosis - Huber, A. M.; Hornung, Joachim; Plontke, S.; Roeoesli, C.; Iro, Heinrich; Strutz, J.; Rahne, T.; Pezier, T. F.; Kwok, P. (Laryngo-Rhino-Otologie, 2014)
Compared to traditional stapes prostheses, self-crimping prostheses have been shown to result in similar, if not better, closure of the air bone gap in patients undergoing stapedotomy for otosclerosis. To achieve self-crimping, nitinol, a shape memory alloy, has been used for several years but concerns have been raised regarding possible damage to the incus and its muco-periosteum. We investigate these concerns with regard to the newer NiTiBOND stapes prosthesis in an observational multi-centre study.In a multicentre, prospective observational study, 76 patients undergoing stapedotomy with the NiTiBond prosthesis across 4 centres were compared to 75 -retrospectively selected control SMart patients. Complications, intra-operative user-friendliness and audiological results at 3 months were documented.Audiological improvement and the rate of complications were similar in both groups. Non inferiority was shown at all frequencies and in the pure-tone average. The NiTiBOND prosthesis was described as very user-friendly.By eliminating manual crimping, stapedotomy using the NiTiBOND prosthesis can be facilitated and standardized. Furthermore, intraoperative handling characteristics of the prosthesis are very good which may further reduce operative risk. Importantly, we show that these benefits are not to the detriment of audiological outcome. Larger and longer-term studies are required to further evaluate results.
EVALuna2:19925

Noise Trauma Induced Neural Plasticity Throughout the Auditory System of Mongolian Gerbils: Differences between Tinnitus Developing and Non-Developing Animals - Tziridis, Konstantin; Ahlf, Sönke; Jeschke, Marcus; Happel, Max F. K.; Ohl, Frank W.; Schulze, Holger (Frontiers in Neurology, 2015)
In this study, we describe differences between neural plasticity in auditory cortex (AC) of animals that developed subjective tinnitus (group T) after noise-induced hearing loss (NIHL) compared to those that did not [group non-tinnitus (NT)]. To this end, our analysis focuses on the input activity of cortical neurons based on the temporal and spectral analysis of local field potential (LFP) recordings and an in-depth analysis of auditory brainstem responses (ABR) in the same animals. In response to NIHL in NT animals we find a significant general reduction in overall cortical activity and spectral power as well as changes in all ABR wave amplitudes as a function of loudness. In contrast, T-animals show no significant change in overall cortical activity as assessed by root mean square analysis of LFP amplitudes, but a specific increase in LFP spectral power and in the amplitude of ABR wave V reflecting activity in the inferior colliculus (IC). Based on these results, we put forward a refined model of tinnitus prevention after NIHL that acts via a top-down global (i.e., frequency-unspecific) inhibition reducing overall neuronal activity in AC and IC, thereby counteracting NIHL-induced bottom-up frequency-specific neuroplasticity suggested in current models of tinnitus development.
EVALuna2:19969

Non-immunogenic dextran-coated superparamagnetic iron oxide nanoparticles: a biocompatible, size-tunable contrast agent for magnetic resonance imaging - Unterweger, Harald; Janko, Christina; Schwarz, Marc; Dezsi, Laszlo; Urbanics, Rudolf; Matuszak, Jasmin; Orfi, Erik; Fülöp, Tamás; Bäuerle, Tobias; Szebeni, Janos; Journe, Clement; Boccaccini, Aldo R.; et al. (International Journal of Nanomedicine, 2017)

Noninvasive exosomal proteomic biosignatures, including cystatin SN, peroxiredoxin-5, and glycoprotein VI, accurately predict chronic rhinosinusitis with nasal polyps - Mueller, Sarina K.; Nocera, Angela L.; Dillon, Simon T.; Gu, Xuesong; Wendler, Olaf; Otu, Hasan H.; Libermann, Towia A.; Bleier, Benjamin S. (International Forum of Allergy and Rhinology, 2019)
Background Exosomes are secreted epithelial-derived vesicles that contain a conserved protein array representative of their parent cell. Exosomes may be reproducibly and noninvasively purified from nasal mucus. The exosomal proteome can be quantified using SOMAscan(TM), a highly multiplexed, aptamer-based proteomic platform. The purpose of this study was to determine whether chronic rhinosinusitis with nasal polyps (CRSwNP) has a unique predictive exosomal proteomic biosignature. Methods Exosomes were isolated from whole mucus sampled from control and CRSwNP patients (n = 20 per group) by differential ultracentrifugation. The SOMAscan(TM) platform was used to simultaneously quantify 1310 biologically relevant human proteins. Matched tissue and whole mucus proteomes were also analyzed. Differential protein expression and discriminatory power were calculated using the unweighted pair group method with arithmetic-mean and principal component analysis, respectively. Bioinformatic analysis was performed using Ingenuity Pathway, MetaCore, and GeneMANIA analyses. Results The exosomal proteome demonstrated 123 significantly (p < 0.05) differentially regulated proteins in CRSwNP relative to control. Eighty of these proteins overlapped with the matched CRSwNP tissue proteome as compared with only 4 among matched whole mucus samples. Forty-three significantly dysregulated pathway networks overlapped between the exosomal and tissue proteome in CRSwNP as compared with only 3 among matched whole mucus samples. The best-performing protein set (cystatin-SN, peroxiredoxin-5, and glycoprotein VI) achieved an area under the curve (AUC) value of up to 99%. Conclusion Our data contribute a significant advance in the development of a reproducible, noninvasive, serial, and quantitative "liquid biopsy" for rhinosinusitis. The exosomal proteomic approach has revealed a unique biosignature associated with CRSwNP, which outperforms whole mucus sampling, and thus provides a method of noninvasive disease detection and proposes new potential therapeutic targets.
CRIS-Team WoS Importer:2019-02-21

Non-magnetic chromatographic separation of colloidally metastable superparamagnetic iron oxide nanoparticles and suspension cells - Mühlberger, Marina; Janko, Christina; Unterweger, Harald; Band, Julia; Schreiber, Eveline; Lehmann, Christian; Dudziak, Diana; Lee, Geoffrey; Alexiou, Christoph; Tietze, Rainer (Journal of Chromatography B-Analytical Technologies in the Biomedical and Life Sciences, 2019)
For magnetic control of cells for biomedical applications such as targeting of immune cells to tumors, cells must be magnetizable. For that, cells are incubated with superparamagnetic iron oxide nanoparticles (SPIONs)to take them up and thus become magnetizable. When using adherent cells, non-ingested SPIONs can be easily removed by rinsing of the particles regardless of their colloidal stability in cell culture medium. However, if suspension cells such as T cells are to be loaded with SPIONs, established methods to separate excess nanoparticles from cells are based on physicochemical parameters such as density, size or magnetizability. Thus, colloidal stability of the particles is of great importance, since only colloidally stable SPIONs can be completely separated from the cells due to their physicochemical differences. Aggregates of colloidally meta- or unstable particles cannot, however, be separated from cells due to their overlapping sizes and densities. Thus, development of an alternative method for the separation of nanoparticle aggregates from suspension cells is urgently needed. Here, we present an affinity chromatographic separation method based on immunohistochemical properties of the respective cells. A desthiobiotinylated antibody against a cellular surface antigen (here CD90.2 receptor on EL4 T cells)is immobilized on a streptavidin agarose column optimized for cell purification. Subsequently the column is loaded with the particle/cell suspension so that the cells bind to the column. After removing the particles by washing, the cells can be gently eluted with biotin solution under physiological conditions. This allows >95% of the excess iron concentration to be removed while maintaining cell viability.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Affinity chromatography; Antibody; Biotin; Cell viability; Desthiobiotin; Streptavidin

Nonsebaceous lymphadenoma of salivary glands: proposed development from intraparotid lymph nodes and risk of misdiagnosis - Weiler, Christoph; Agaimy, Abbas; Zengel, Pamela; Zenk, Johannes; Kirchner, Thomas; Ihrler, Stephan (Virchows Archiv, 2012)
Nonsebaceous lymphadenoma (NSLA) is a rare benign salivary gland tumor composed of lymphoid and epithelial components. By definition, the epithelial component lacks sebaceous differentiation and instead displays a wide range of histological differentiation. In this study, we have collected nine cases of NSLA to characterize their histological and immunohistochemical profiles. The samples were histologically reviewed and immunohistochemical stains for CK5/6, CK7, CK14, CK18, p63, and Ki67 performed. Patients were six males and three females (mean age, 50 years). All tumors were located in the parotid gland and showed intimate intermingling of lymphoid tissue with islands or strands of epithelium with a wide spectrum of histological differentiation. The immunohistochemical profiles mirrored the epithelial differentiation; hence, areas with basaloid or lymphoepithelial differentiation strongly expressed CK5/6, CK14, and p63, while areas with ductal differentiation showed strong positivity for CK18/CK7 and CK5/6/CK14/p63 in luminal and basal cell layers, respectively. A hilus structure with salivary inclusions or D2-40 (podoplanin)-positive marginal sinus was identifiable in four and nine of the cases, respectively, supporting origin within intra-/periparotid lymph nodes. Six cases were initially misdiagnosed as other benign (n = 4) or malignant tumors (n = 2). Our study on the second largest series of NSLA reported to date provides strong evidence that NSLA belongs to the group of salivary gland tumors that pathogenetically develop from embryonic salivary gland inclusions in intra-/periparotid lymph nodes. Knowledge of the wide histological spectrum of this rare and presumably underreported tumor is important in order to avoid misdiagnosis, particularly as malignant tumor.
EVALuna2:6440

Novel dextran-coated ultrasmall superparamagnetic iron oxide nanoparticles (USPIOs) - a safe contrast agent for magnetic resonance imaging of atherosclerosis - Cicha, Iwona; Matuszak, Jasmin; Sekita, A.; Bäuerle, Tobias; Dezsi, L.; Szebeni, J.; Lyer, Stefan; Alexiou, Christoph; Unterweger, Harald (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

Novel nanoparticulate drug delivery systems - Friedrich, Ralf P.; Pöttler, Marina; Cicha, Iwona; Lyer, Stefan; Janko, Christina; Alexiou, Christoph (Nanomedicine, 2016)
EVALuna2:33375

Novel nanosystems to combat atherosclerosis: Functional effects on human endothelial and monocytic cells - Cicha, Iwona; Matuszak, Jasmin; Juenet, M.; Chauvierre, Cedric; Texier, I.; Almer, G.; Prassl, R.; Metselaar, J.; Dezsi, L.; Urbanics, R.; Szebeni, J.; Alexiou, Christoph; et al. (2016)
EVALuna2:33162

Novel Receiver for Superparamagnetic Iron Oxide Nanoparticles in a Molecular Communication Setting - Bartunik, Max; Lübke, Maximilian; Unterweger, Harald; Alexiou, Christoph; Meyer, Sebastian; Ahmed, Doaa; Fischer, Georg; Wicke, Wayan; Jamali Kooshkghazi, Vahid; Schober, Robert; Kirchner, Jens (Proceedings of the 6th ACM International Conference on Nanoscale Computing and Communication, NANOCOM 2019, 2019)
Superparamagnetic iron oxide nanoparticles (SPIONs) have recently been introduced as information carriers in a testbed for molecular communication (MC) in duct flow. Here, a new receiver for this testbed is presented, based on the concept of a Wheatstone bridge. The capability for a reliable transmission using the testbed and detection of the proposed receiver was evaluated by sending a text message and a 80 bit random sequence at a bit rate of 1/s, which resulted in a bit error rate of 0 %. Furthermore, the sensitivity of the device was assessed by a dilution series, which gave a limit of detectability of peaks between 0:1 to 0:5 mg/mL. Compared to the commercial susceptometer that was previously used as receiver, the new detector provides an increased sampling rate of 100 samples/s and flexibility in the dimensions of the propagation channel. Furthermore, it allows to implement both single-ended and differential signaling in SPION-bases MC testbeds <br
CRIS-Team Scopus Importer:2019-10-29
Keywords: Molecular communication; superparamagnetic iron oxide nanoparticles; SPION; differtial signaling; receiver

NSD3-NUTM1-rearranged carcinoma of the median neck/thyroid bed developing after recent thyroidectomy for sclerosing mucoepidermoid carcinoma with eosinophilia: report of an extraordinary case - Agaimy, Abbas; Tögel, Lars; Stöhr, Robert; Meidenbauer, Norbert; Semrau, Sabine; Hartmann, Arndt; Mantsopoulos, Konstantinos (Virchows Archiv, 2021)
Sclerosing mucoepidermoid carcinoma with eosinophilia (SMECE) is an exceedingly rare low-grade thyroid malignancy of unknown histogenesis. NUT carcinoma is another rare, highly aggressive neoplasm with predilection for the midline, defined by recurrent NUTM1 fusions. The bromodomain family genes (BRD4 or BRD3) and rarely NSD3, ZNF532, or others are known fusion partners. We describe an extraordinary case of a 42-year-old female with a thyroid SMECE treated by thyroidectomy and neck dissection. She presented 6 months later with extensive midline recurrence encasing/compressing the trachea. Biopsy revealed poorly differentiated carcinoma with abrupt squamous differentiation, suggestive of NUT carcinoma. Immunohistochemistry confirmed expression of monoclonal NUT antibody. Targeted RNA sequencing revealed the NSD3-NUTM1 fusion in the NUT carcinoma, but not in the SMECE. This unique case highlights unusual sequential origin of two exceptionally rare entities at same anatomic site and underlines the necessity of sampling unexpectedly aggressive recurrences of otherwise indolent malignancies.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Head and neck; Midline carcinoma; NSD3; NUT carcinoma; NUTM1; Sclerosing mucoepidermoid carcinoma with eosinophilia; Thyroid gland

Nuclear NR4A2 (Nurr1) Immunostaining is a Novel Marker for Acinic Cell Carcinoma of the Salivary Glands Lacking the Classic NR4A3 (NOR-1) Upregulation - Haller, Florian; Moskalev, Evgeny; Kuck, Sarina; Bieg, Matthias; Winkelmann, Christa; Müller, Susanna; Ihrler, Stephan; Märkl, Bruno; Eils, Roland; Wiemann, Stefan; Iro, Heinrich; Hartmann, Arndt; et al. (American Journal of Surgical Pathology, 2020)
CRIS-Team Scopus Importer:2020-05-22

Nuclear NR4A3 Immunostaining Is a Specific and Sensitive Novel Marker for Acinic Cell Carcinoma of the Salivary Glands - Haller, Florian; Skálová, Alena; Ihrler, Stephan; Märkl, Bruno; Bieg, Matthias; Moskalev, Evgeny; Erber, Ramona; Blank, Susanne; Winkelmann, Christa; Hebele, Simone; Baněčková, Martina; Wiemann, Stefan; et al. (American Journal of Surgical Pathology, 2019)
Recently, we discovered the recurrent genomic rearrangement [t(4;9)(q13;q31)] enabling upregulation of the transcription factor Nuclear Receptor Subfamily 4 Group A Member 3 (NR4A3) through enhancer hijacking as the oncogenic driver event in acinic cell carcinoma (AciCC) of the salivary glands. In the current study, we evaluated the usefulness of NR4A3 immunostaining and NR4A3 fluorescence in situ hybridization (FISH) in the differential diagnosis of AciCC, comparing a total of 64 AciCCs including 17% cases with high-grade transformation, 29 secretory (mammary analog) carcinomas (MASC), and 70 other salivary gland carcinomas. Nuclear NR4A3 immunostaining was a highly specific (100%) and sensitive (98%) marker for AciCC with only 1 negative case, whereas NR4A3 FISH was less sensitive (84%). None of the MASCs or other salivary gland carcinomas displayed any nuclear NR4A3 immunostaining. The recently described HTN3-MSANTD3 gene fusion was observed in 4 of 49 (8%) evaluable AciCCs, all with nuclear NR4A3 immunostaining. In summary, NR4A3 immunostaining is a highly specific and sensitive marker for AciCC, which may be especially valuable in cases with high-grade transformation and in "zymogen granule"-poor examples within the differential diagnostic spectrum of AciCC and MASC.
CRIS-Team Scopus Importer:2019-09-03
Keywords: acinic cell carcinoma; HTN3-MSANTD3; immunohistochemistry; NR4A3; salivary glands; translocation

Numerical investigation of the hydrodynamics of changing fin positions within a 4-fin surfboard configuration - Falk, Sebastian; Kniesburges, Stefan; Janka, Rolf Matthias; O'Keefe, Tom; Grosso, Roberto; Döllinger, Michael (Applied Sciences, 2020)
Most sports like surfing are highly developed. It is necessary to tease the last percentages out of the competitors and equipment-in the case of surfing the surfboard-fin-system-to win competitions or championships. In this computational investigation, a parameter study of the positioning of the two rear fins within a 4-fin configuration with fixed front fins on a surfboard is executed to find appropriate fin positions for specific surf situations. Four different inflow velocities are investigated. The RANS and URANS models combined with the SST k-ω turbulence model, which is available within the computational fluid dynamics (CFD) package STAR-CCM+, are used to simulate the flow field around the fins for angles of attack (AoA) between 0° and 45°. The simulation results show that shifting the rear fins toward the longitudinal axis of the surfboard lowers the maximum lift. Surfboards with 4-fin configurations are slower in nearly the whole range of AoA due to a higher drag force but produce a higher lift force compared to the 3-fin configuration. The lift and drag forces increase significantly with increasing inflow velocity. This study shows a significant influence of the rear fin positioning and the inflow velocity on lift and drag performance characteristics.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Computational fluid dynamics (CFD); Fins; Hydrodynamics; Quad; STAR-CCM+®; Surfboard

Nyquist Plot Parametrization for Quantitative Analysis of Vibration of the Vocal Folds - Arias Vergara, Tomás; Döllinger, Michael; Schraut, Tobias; Mohd Khairuddin, Khairy Anuar; Schützenberger, Anne (Journal of Voice, 2023)
Objectives: The Nyquist plot provides a graphical representation of the glottal cycles as elliptical trajectories in a 2D plane. This study proposes a methodology to parameterize the Nyquist plot with application to support the quantitative analysis of voice disorders. Methods: We considered high-speed videoendoscopy recordings of 33 functional dysphonia (FD) patients and 33 normophonic controls (NC). Quantitative analysis was performed by computing four shape-based parameters from the Nyquist plot: Variability, Size (Perimeter and Area), and Consistency. Additionally, we performed automatic classification using a linear support vector machine and feature importance analysis by combining the proposed features with state-of-the-art glottal area waveform (GAW) parameters. Results: We found that the inter-cycle variability was significantly higher in FD patients compared to NC. We achieved a classification accuracy of 83% when the top 30 most important features were used. Furthermore, the proposed Nyquist plot features were ranked in the top 12 most important features. Conclusions: The Nyquist plot provides complementary information for subjective and objective assessment of voice disorders. On the one hand, with visual inspection it is possible to observe intra- and inter-glottal cycle irregularities during sustained phonation. On the other hand, shaped-based parameters allow quantifying such irregularities and provide complementary information to state-of-the-art GAW parameters.
CRIS-Team Scopus Importer:2023-03-03
Keywords: Functional dysphonia; High-speed videoendoscopy; Laryngeal imaging; Machine learning; Nyquist plot; Voice disorders

Objective, audiological and quality of life measures with the CI532 slim modiolar electrode - Hey, Matthias; Wesarg, Thomas; Mewes, Alexander; Helbig, Silke; Hornung, Joachim; Lenarz, Thomas; Briggs, Robert; Marx, Mathieu; Ramos, Angel; Stöver, Timo; Escudé, Bernard; James, Chris J.; et al. (Cochlear Implants International, 2019)
Objectives: To report on electrode array measurements for the Nucleus® CI532 Slim Modiolar Electrode device including: ECAP thresholds, electrode impedances, and psychophysical comfort levels, as well as speech perception results pre- and post-operatively and standardized evaluations of quality of life. Methods: Forty-four subjects were implanted with the CI532. Electrically evoked compound action potential (ECAP) thresholds and impedances were measured using automatic Neural Response Telemetry intra-operatively, at activation and at six months post implant. Pre- and post-operative measures of words in quiet and sentences in noise were made in multiple languages. Quality of life was assessed using The Speech Spatial Qualities questionnaire (SSQ) and Glasgow Benefit Inventory (GBI). Results: Intra-operative ECAP thresholds were recorded successfully from 90% of electrodes tested. ECAP thresholds varied across the array and a post-hoc Dunn’s test showed that median thresholds for electrodes E1–E13 were significantly greater than those for E17–E22 (all P < 0.001). Impedances increased significantly between surgery and activation. Speech recognition scores for words in quiet and sentences in noise showed a significant improvement for the group at six months, when using the cochlear implant, compared with pre-operative performance (P < 0.001). There was a significant increase compared to pre-operative ratings for all sections of the SSQ at six months post activation (P < 0.001). The GBI gave scores significantly above zero for the ‘general’ subscale and total score. Conclusion: Objective ECAP and impedance measures for this new electrode array were as expected and similar to results reported for other array types. Speech perception and quality of life improved significantly following implantation. (Registered as NCT02392403 on ClinicalTrials.gov PRS).
CRIS-Team Scopus Importer:2019-06-18
Keywords: Cochlear implant; Expanding criteria; Hearing preservation; Neural response; Perimodiolar

Objective estimation of sensory thresholds based on neurophysiological parameters. - Schilling, Achim; Gerum, Richard; Krauß, Patrick; Metzner, Claus; Tziridis, Konstantin; Schulze, Holger (Frontiers in Neuroscience, 2019)

Objective estimation of sensory thresholds based on neurophysiological parameters - Schilling, Achim; Gerum, Richard; Krauß, Patrick; Metzner, Claus; Tziridis, Konstantin; Schulze, Holger (Frontiers in Neuroscience, 2019)
Reliable determination of sensory thresholds is the holy grail of signal detection theory. However, there exists no assumption-independent gold standard for the estimation of thresholds based on neurophysiological parameters, although a reliable estimation method is crucial for both scientific investigations and clinical diagnosis. Whenever it is impossible to communicate with the subjects, as in studies with animals or neonates, thresholds have to be derived from neural recordings or by indirect behavioral tests. Whenever the threshold is estimated based on such measures, the standard approach until now is the subjective setting-either by eye or by statistical means-of the threshold to the value where at least a “clear” signal is detectable. These measures are highly subjective, strongly depend on the noise, and fluctuate due to the low signal-to-noise ratio near the threshold. Here we show a novel method to reliably estimate physiological thresholds based on neurophysiological parameters. Using surrogate data we demonstrate that fitting the responses to different stimulus intensities with a hard sigmoid function, in combination with subsampling, provides a robust threshold value as well as an accurate uncertainty estimate. This method has no systematic dependence on the noise and does not even require samples in the full dynamic range of the sensory system. We prove that this method is universally applicable to all types of sensory systems, ranging from somatosensory stimulus processing in the cortex to auditory processing in the brain stem.
CRIS-Team Scopus Importer:2019-07-16
Keywords: Auditory cortex; Auditory neuroscience; Automated threshold estimation; Electrophysiology; Hearing; Psychometric function; Somatosensation; Somatosensory cortex

Offset responses in primary auditory cortex are enhanced after notched noise stimulation - Schilling, Achim; Choi, Byunghee; Parameshwarappa, Vinay; Norena, Arnaud J. (Journal of Neurophysiology, 2023)
Sensory "aftereffects" are a subgroup of sensory illusions that can be defined as an illusory phenomenon triggered after prolonged exposure to a given sensory inducer. These phenomena are interesting because they can provide insights into the mechanisms of perception. In auditory modality, there is a special interest in the so-called "Zwicker tone" (ZT), an auditory aftereffect triggered after the presentation of a notched noise (NN, broadband noise with a missing frequency band). The ZT has been considered a plausible model of a specific tinnitus subtype since it presents some key characteristics in common with tinnitus. Indeed, both the tinnitus percept and ZT can be triggered by a relative "sensory deprivation," and their pitch corresponds to the frequency region that has been sensory deprived. The effects of a NN presentation on the central auditory system are still barely investigated, and the mechanisms of the ZT are elusive. In this study, we analyzed the laminar structure of the neural activity in the primary cortex of anesthetized and awake guinea pigs during and after white noise (WN) and NN stimulation. We found significantly increased offset responses, in terms of both spiking activity and local field potential amplitude, after NN compared with WN presentation. The offset responses were circumscribed to the granular and upper infragranular layers (input layers) and were maximal when the neuron's best frequency was within or near the missing frequency band. The mechanisms of the offset response and its putative link with the ZT are discussed.NEW & NOTEWORTHY Notched noise (white noise with embedded spectral gap) causes significant excitatory offset responses in the auditory cortex of awake and anesthetized guinea pigs. The largest offset responses were located in the infragranular/granular layers, and current source density analysis revealed that offset responses were associated with an early current sink localized in the upper infragranular layers. We discuss the possibility that the offset responses might be associated with an auditory phantom percept (Zwicker tone).
CRIS-Team Scopus Importer:2023-05-26
Keywords: electrophysiology; notched noise; offset response; primary auditory cortex; Zwicker tone

Older Patients Are Less Affected by Radiochemotherapeutic Treatment than Younger - Welling, Max J.; Losensky, Wencke; Wächter, Katharina; Schilling, Teresa; Frank, Friedrich; Haas, Matthias; Fietkau, Rainer; Distel, Luitpold; Weiß, Stephanie (BioMed Research International, 2018)
Purpose: The general assumption is that cancer therapy impairs the quality of life in elderly patients more than in younger ones. We were interested in the effects of radiochemotherapeutic treatment on the quality of life of elderly patients compared to younger patients and compared to normative data of a general German population. Methods and Materials: A total of 465 patients completed the EORTC QLQ-C30 questionnaire. Repetitive completion of the questionnaire over time led to 1407 datasets. Our patient cohort contained 197 (42.4%) patients with colorectal cancer followed by 109 (23.4%) patients with head and neck cancer, 43 (9.2%) patients with lung cancer, and 116 (25%) with other types of cancer. Patients were categorized into five age groups, the respective cut-offs being 40, 50, 60, and 70 years. Normative data were drawn from a population study of a general German population. Results: Functional scores and symptom scores were approximately stable between the different age groups. Our data does not suggest a significant difference between the investigated age groups. Advancing age evened out the differences between the normative data of the general German population and the cancer patients in 11 of 15 scores. Conclusions: The general belief about younger patients having fewer physical and psychological problems related to radiochemotherapy needs to be reconsidered. Overall resilience of older patients is apparently underestimated.
EVALuna2:36461

Olfactory Neuroblastomas: What Actually Happens in the Long-Term? - Mantsopoulos, Konstantinos; Koch, Michael; Iro, Heinrich; Constantinidis, Jannis (Journal of Clinical Medicine, 2022)
Objective: The aim of this study was to investigate the long-term oncologic outcome and review the state of the art in the management of olfactory neuroblastomas. Material and Methods: The records of all patients treated for olfactory neuroblastomas in two academic departments between 1975 and 2012 were evaluated retrospectively. Data on epidemiological parameters were collected (age, gender), along with staging (Kadish, Morita), histologic grading (Hyams), time and form of treatment, locoregional control, and disease-specific and overall survival. Patients with other malignant diseases, distant metastases of olfactory neuroblastomas at the time of initial diagnosis, a follow-up time of less than 5 years, or insufficient clinical-pathological data were excluded from further analysis. Results: In total, 53 cases made up our final study sample (26 men, 27 women; male–female ratio 0.96:1). Their mean age was 48.6 years (range: 10–84 years). The mean follow-up time was 137.5 months (4–336 months, SD: 85.0). A total of 5 out of 53 study cases (9.4%) showed metastatic involvement of the neck at the time of initial presentation. Local recurrence was detected in 8/53 (15.1%) and regional recurrence in 7/53 of our study cases (13.2%). Three patients (42.8%) from the group of cases with surgery as the sole form of management (7/53, 13.2%) died due to the disease. The cumulative disease-specific survival and overall survivalfor the whole group of patients were 88.6% and 63.6%, respectively. The cumulative disease-specific survival stratified by Kadish A/B vs. Kadish C/D as well as Hyams I/II vs. Hyams III/IV showed superior results for limited tumors, albeit without significance, and low-grade tumors (highly significant difference). Conclusion: Craniofacial or sometimes solely endoscopically controlled resection can warrant resection of the olfactory neuroblastoma with wide margins. However, locoregional failures and distant metastases can occur after a long period of time. The non-negligible incidence of regional recurrences, partly in unusual localizations, leads us to consider the need to identify the “recurrence-friendly” cases and to perform individualized elective irradiation of the neck in cases with high-risk features.
CRIS-Team Scopus Importer:2022-05-20
Keywords: endoscopic surgery; esthesioneuroblastoma; Hyams; Kadish; olfactory neuroblastoma; recurrence; survival

Oligometastatic head and neck cancer: Which patients benefit from radical local treatment of all tumour sites? - Weissmann, Thomas; Höfler, Daniel; Hecht, Markus; Semrau, Sabine; Haderlein, Marlen; Filimonova, Irina; Frey, Benjamin; Bert, Christoph; Lettmaier, Sebastian; Mantsopoulos, Konstantinos; Iro, Heinrich; Fietkau, Rainer; et al. (Radiation Oncology, 2021)
Background: There is a large lack of evidence for optimal treatment in oligometastatic head and neck cancer and it is especially unclear which patients benefit from radical local treatment of all tumour sites. Methods: 40 patients with newly diagnosed oligometastatic head and neck cancer received radical local treatment of all tumour sites from 14.02.2008 to 24.08.2018. Primary endpoint was overall survival. Time to occurrence of new distant metastases and local control were evaluated as secondary endpoints as well as prognostic factors in univariate und multivariate Cox’s regression analysis. To investigate the impact of total tumour volume on survival, all tumour sites were segmented on baseline imaging. Results: Radical local treatment included radiotherapy in 90% of patients, surgery in 25% and radiofrequency ablation in 3%. Median overall survival from first diagnosis of oligometastatic disease was 23.0 months, 2-year survival was 48%, 3-year survival was 37%, 4-year survival was 24% and 5-year survival was 16%. Median time to occurrence of new distant metastases was 11.6 months with freedom from new metastases showing a tail pattern after 3 years of follow-up (22% at 3, 4- and 5-years post-treatment). In multivariate analysis, better ECOG status, absence of bone and brain metastases and lower total tumour volume were significantly associated with improved survival, whereas the number of metastases and involved organ sites was not. Conclusions: Radical local treatment in oligometastatic head and neck cancer shows promising outcomes and needs to be further pursued. Patients with good performance status, absence of brain and bone metastases and low total tumour volume were identified as optimal candidates for radical local treatment in oligometastatic head and neck cancer and should be considered for selection in future prospective trials.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Head and neck cancer; Local treatment; Oligometastatic disease; Radiotherapy; SBRT

Open(G)PIAS: An open-source solution for the construction of a high-precision acoustic startle response setup for tinnitus screening and threshold estimation in rodents - Gerum, Richard; Rahlfs, Hinrich; Streb, Matthias; Krauß, Patrick; Grimm, Jannik; Metzner, Claus; Tziridis, Konstantin; Günther, Michael; Schulze, Holger; Kellermann, Walter; Schilling, Achim (Frontiers in Behavioral Neuroscience, 2019)
The modulation of the acoustic startle reflex (ASR) by a pre-stimulus called pre-pulse inhibition (PPI, for gap of silence pre-stimulus: GPIAS) is a versatile tool to, e.g., estimate hearing thresholds or identify subjective tinnitus percepts in rodents. A proper application of these paradigms depends on a reliable measurement of the ASR amplitudes and an exact stimulus presentation in terms of frequency and intensity. Here, we introduce a novel open-source solution for the construction of a low-cost ASR setup. The complete software for data acquisition and stimulus presentation is written in Python 3.6 and is provided as an Anaconda package. Furthermore, we provide a construction plan for the sensor system based on low-cost hardware components. Exemplary GPIAS data from two animal models (Mus musculus, Meriones unguiculatus) show that the ratio histograms (1-GPIAS) of the gap-pre-stimulus and no pre-stimulus ASR amplitudes can be well described by a log-normal distribution being in good accordance to previous studies with already established setups. Furthermore, it can be shown that the PPI as a function of pre-stimulus intensity (threshold paradigm) can be approximated with a hard-sigmoid function enabling a reproducible sensory threshold estimation. Thus, we show that the open-source solution could help to further establish the ASR method in many laboratories and, thus, facilitate and standardize research in animal models of tinnitus and/or hearing loss.
CRIS-Team Scopus Importer:2019-07-16
Keywords: 3D acceleration sensor; Anaconda package; Animal model; Low-cost setup; Startle; Tinnitus

OpenHSV: an open platform for laryngeal high-speed videoendoscopy - Kist, Andreas; Dürr, Stephan; Schützenberger, Anne; Döllinger, Michael (Scientific Reports, 2021)
High-speed videoendoscopy is an important tool to study laryngeal dynamics, to quantify vocal fold oscillations, to diagnose voice impairments at laryngeal level and to monitor treatment progress. However, there is a significant lack of an open source, expandable research tool that features latest hardware and data analysis. In this work, we propose an open research platform termed OpenHSV that is based on state-of-the-art, commercially available equipment and features a fully automatic data analysis pipeline. A publicly available, user-friendly graphical user interface implemented in Python is used to interface the hardware. Video and audio data are recorded in synchrony and are subsequently fully automatically analyzed. Video segmentation of the glottal area is performed using efficient deep neural networks to derive glottal area waveform and glottal midline. Established quantitative, clinically relevant video and audio parameters were implemented and computed. In a preliminary clinical study, we recorded video and audio data from 28 healthy subjects. Analyzing these data in terms of image quality and derived quantitative parameters, we show the applicability, performance and usefulness of OpenHSV. Therefore, OpenHSV provides a valid, standardized access to high-speed videoendoscopy data acquisition and analysis for voice scientists, highlighting its use as a valuable research tool in understanding voice physiology. We envision that OpenHSV serves as basis for the next generation of clinical HSV systems.
CRIS-Team Scopus Importer:2021-07-16

Optical 3-D Metric Measurements of Local Vocal Fold Deformation Characteristics in an In Vitro Setup - Hüttner, Björn; Sutor, Alexander; Luegmair, Georg; Rupitsch, Stefan; Lerch, Reinhard; Döllinger, Michael (IEEE Transactions on Biomedical Engineering, 2011)
Understanding vocal fold dynamics presents an essential part in treating voice disorders as it is the prerequisite to appropriate medical therapy. Various physical and numerical models exist for simulation purposes, all relying on simplified material parameters. To improve current approaches, data of realistic tissue behavior, i.e., in natural surroundings, have to be considered in model development. An in vitro setup was proposed for tensile tests combined with an optical method for precise, local and metrical 3-D measurements of distinctive surface points. Compared to previous 3-D reconstruction methods, the accuracy was improved tenfold. Vertically applied forces versus resulting deformation were measured for ten porcine vocal folds. Deformation characteristics of mucosa and the two-layer structure of mucosa and muscle (MM) were investigated at three distinctive locations along the vocal fold edge. The spring rates were represented by an exponential function. For equal deflections, an increasing spring rate from posterior to anterior for MM was measured. For solely mucosa, the spring rate decreased from the posterior to the middle and subsequently increased again. The MM-layer presented a stiffer deformation behavior than mucosa. For deformations higher than 1.5 mm, the spring rates for MM were more than twice as high as for mucosa. The investigations display the importance of considering both multilayers and local differences for the improvement of vocal fold models.
Keywords: Image processing; optical measurement; stereo triangulation; tensile test; vocal fold deformation characteristics

Optical Microscopy Systems for the Detection of Unlabeled Nanoparticles - Friedrich, Ralf P.; Kappes, Mona; Cicha, Iwona; Tietze, Rainer; Braun, Christian; Schneider-Stock, Regine; Nagy, Roland; Alexiou, Christoph; Janko, Christina (International Journal of Nanomedicine, 2022)
Label-free detection of nanoparticles is essential for a thorough evaluation of their cellular effects. In particular, nanoparticles intended for medical applications must be carefully analyzed in terms of their interactions with cells, tissues, and organs. Since the labeling causes a strong change in the physicochemical properties and thus also alters the interactions of the particles with the surrounding tissue, the use of fluorescently labeled particles is inadequate to characterize the effects of unlabeled particles. Further, labeling may affect cellular uptake and biocompatibility of nanoparticles. Thus, label-free techniques have been recently developed and implemented to ensure a reliable characterization of nanoparticles. This review provides an overview of frequently used label-free visualization techniques and highlights recent studies on the development and usage of microscopy systems based on reflectance, darkfield, differential interference contrast, optical coherence, photothermal, holographic, photoacoustic, total internal reflection, surface plasmon resonance, Rayleigh light scattering, hyperspectral and reflectance structured illumination imaging. Using these imaging modalities, there is a strong enhancement in the reliability of experiments concerning cellular uptake and biocompatibility of nanoparticles, which is crucial for preclinical evaluations and future medical application
Keywords: label free imaging; nanoparticle detection; non-fluorescent imaging; reflectance imaging; holotomography; scattering microscopy

Optical Reconstruction of High-Speed Surface Dynamics in an Uncontrollable Environment - Luegmair, Georg; Kniesburges, Stefan; Zimmermann, Maik; Sutor, Alexander; Eysholdt, Ulrich; Döllinger, Michael (IEEE Transactions on Medical Imaging, 2010)
The ability to communicate with our voice can be regarded as the concatenation of the two processes "phonation" and "modulation." These take place in the larynx and palatal and oral region, respectively. During phonation the audible primary voice signal is created by mutual reaction of vocal folds with the exhaled air stream of the lungs. The underlying interactions of masses, fluids and acoustics have yet to be identified and understood. One part of the primary signal's acoustical source are vortex induced vibrations, as e. g., created by the Coandaeffect in the air stream. The development of these vorteces is determined by the shape and 3-D movements of the vocal folds in the larynx. Current clinical in vivo research methods for vocal folds do not deliver data of satisfactory quality for fundamental research, e. g., an endoscope is limited to 2-D image information. Based hereupon, a few improved methods have been presented, however delivering only selective 3-D information, either for a single point or a line. This stands in contrast to the 3-D motions of the entire vocal fold surface. More complex imaging methods, such as MRI, do not deliver information in real-time. Thus, it is necessary to develop an easily applicable, more improved examination method, which allows for 3-D data of the vocal folds surfaces to be obtained. We present a method to calibrate a 3-D reconstruction setup including a laser projection system and a high-speed camera. The setup is designed with miniaturization and an in vivo application in mind. The laser projection system generates a divergent grid of 196 laser dots by diffraction gratings. It is calibrated with a planar calibration target through planar homography. In general, the setup allows to reconstruct the topology of a surface at high frame rates (up to 4000 frames per second) and in uncontrollable environments, as e. g., given by the lighting situation (little to no ambient light) and varying texture (e. g., varying grade of reflection) in the human larynx. In particular, this system measures the 3-D vocal fold surface dynamics during phonation. Applied to synthetic data, the calibration is shown to be robust (error approximately 0.5 mu m) regarding noise and systematic errors. Experimental data gained with a linear z-stage proved that the system reconstructs the 3-D coordinates of points with an error at approximately 15 mu m. The method was applied exemplarily to reconstruct porcine and artificial vocal folds' surfaces during phonation. Local differences such as asymmetry between left and right fold dynamics, as well as global parameters, such as opening and closing speed and maximum displacements, were identified and quantified.
Keywords: Biomedical imaging; laser projection system calibration; planar homography; surface reconstruction

Optimization of cell seeding on electrospun PCL-silk fibroin scaffolds - Singh, Raminder; Eitler, David; Morelle, René; Friedrich, Ralf P.; Dietel, Barbara; Alexiou, Christoph; Boccaccini, Aldo R.; Liverani, Liliana; Cicha, Iwona (European Polymer Journal, 2020)
The availability of cell growth-supporting materials for regenerative medicine is limited. Here, we aimed to improve the attachment and growth of endothelial cells (HUVECs) and fibroblasts on electrospun poly(ε-caprolactone) (PCL) mats with different fiber diameters and on newly-established PCL and silk fibroin (PCL/SF) blended fibers obtained by using benign solvents (mixture of acetic acid and formic acid) for electrospinning. PCL mats were produced in two different average fiber diameters, namely micro and nano range. The electrospinning method was optimized to produce PCL/SF blended fibers. Morphology (F-actin), viability (calcein) and metabolic activity (WST-8 assay) of HUVECs and fibroblasts cultured in 2D on the mats of different fiber size and composition were compared. Subsequently, cylindrical PCL/SF scaffolds were produced and colonized with cells using 3D radial magnetic cell seeding. Both PCL and PCL/SF nanofibers provided better support for initial cell adhesion (day 1) compared with PCL microfibers. At day 7, the highest metabolic activity in HUVECs and fibroblasts was observed on PCL/SF mats. Microscopic studies confirmed that on day 7, the best support for cell growth was observed on PCL/SF. Tubular PCL/SF scaffolds were successfully colonized using magnetic nanoparticles and 3D radial magnetic cell seeding. Taken together, the fibers obtained by blending SF with PCL combine the mechanical benefits of PCL with improved biological functionality of SF. Electrospun PCL/SF nanofibers represent a promising material to produce both flat and 3D structures with potential for enhanced cell attachment and tissue regeneration.
CRIS-Team Scopus Importer:2020-06-26
Keywords: Benign solvents; Electrospinning; Magnetic cell seeding; Nanofibers; Poly(ε-caprolactone); Silk fibroin

Optimized transformation of the glottal motion into a mechanical model - Triep, Michael; Brücker, Christoph; Stingl, Michael; Döllinger, Michael (Medical Engineering & Physics, 2011)
During phonation the human vocal folds exhibit a complex self-sustained oscillation which is a result of the transglottic pressure difference, of the characteristics of the tissue of the folds and of the flow in the gap between the vocal folds (Van den Berg J. Myoelastic-aerodynamic theory of voice production. J Speech Hearing Res 1958;1:227-44 [1]). Obviously, extensive experiments cannot be performed in vivo. Therefore, in literature a variety of model experiments that try to replicate the vocal folds kinematics for specific studies within the vocal tract can be found. Here, we present an experimental model to visualize the fluid dynamics which result from the complex motions of real human vocal folds. An existing up-scaled glottal cam model with approximate glottal kinematics is extended to replicate more realistically observed glottal closure types. This extension of the model is a further step in understanding the fluid dynamical mechanisms contributing to the quality of human voice during phonation, in particular the cause (changed glottal kinematics) and its effect (changed aero-acoustic field). For four typical glottal closure types cam geometries of varying profile are generated. Two counter rotating cams covered with a silicone membrane reproduce as well as possible the observed glottal movements. (C) 2010 IPEM. Published by Elsevier Ltd. All rights reserved.
Keywords: 3D vocal fold kinematics; 3D glottal cam model; Applied optimization

Orally administered nanoparticles for gastrointestinal applications - Tietze, Rainer; Unterweger, Harald; Janko, Christina; Civelek, Mehtap; Cicha, Iwona; Spielvogel, Helmut; Alexiou, Christoph (Nanomedicine, 2023)
CRIS-Team WoS Importer:2023-03-24

Oscillatory Characteristics of the Vocal Folds Across the Tenor Passaggio - Echternach, Matthias; Burk, Fabian; Koeberlein, Marie; Herbst, Christian T.; Döllinger, Michael; Burdumy, Michael; Richter, Bernhard (Journal of Voice, 2017)
INTRODUCTION: Recent research has revealed that classically trained tenors tend to constrict epilaryngeal structures when singing in and above the passaggio (ie, the frequency region where register events typically occur). These constrictions complicate visibility of vocal fold oscillatory patterns with transoral rigid high-speed video endoscopy, thus limiting the current understanding of laryngeal dynamics in the passaggio region of tenors. MATERIALS AND METHODS: This investigation analyzed seven professionally trained western classical tenors using high-speed digital imaging (HSDI) at 20,000 frames per second via transnasal flexible endoscopy. The participants produced transitions (a) from modal to falsetto register and (b) from modal to stage voice above the passaggio (SVaP) during ascending pitch glides from A3 (220 Hz) to A4 (440 Hz) on vowel /i/. HSDI data were complemented by simultaneous acoustic and electroglottographic recordings. RESULTS: For many subjects both transition types were associated with constrictions of the epilaryngeal structures during the pitch glide. These constrictions appeared to be more distinct for the SVaP than for falsetto. No major irregularities of vocal fold oscillations in the sense of fundamental frequency jumps were observed for either transition type. However, during the transitions, the open quotient derived from the glottal area waveform (OQGAW) increased; in falsetto, the OQGAWwas greater and the electroglottographic cepstral peak prominence was lower than in SVaP. CONCLUSIONS: Epilaryngeal constrictions should be considered typical for tenors singing at high fundamental frequencies. Vocal fold oscillatory patterns are changing not only for the register shift from modal to falsetto but also for the transition from modal to SVaP, indicating a need for laryngeal adjustments during these transitions.
EVALuna2:33369

Oscillatory Onset and Offset in Young Vocally Healthy Adults Across Various Measurement Methods - Patel, Rita R.; Walker, Reuben; Döllinger, Michael (Journal of Voice, 2017)
OBJECTIVE: This study aimed to investigate the relationship between (1) oscillatory onset-offset time across various approaches that use different measurement criteria and (2) oscillatory onset and offset times in vocally healthy young adults. METHOD: Oscillatory onset-offset times were obtained from 71 vocally normal adults, using high-speed videoendoscopy. Comparisons between the different onset methods involved measurement of the oscillatory onset time (OOT), voice initiation period (VIP), and the phonation onset time (POT), and for offset methods involved computation of the oscillatory offset time (OOToff) and the phonation offset time. RESULTS: Correlation of the OOT with the VIP was 0.240 (P = 0.04) and with the POT form glottal area waveform was 0.248 (P = 0.04); however, correlation between the VIP and the POT glottal area waveform was 0.661 (P < 0.001). For offset, there was a moderate correlation (rS = 0.503, P < 0.001) across OOToff and vocal offset period. The onset time was longest for the OOT followed by the VIP and the POT. There was no correlation between onset and offset for all methods. CONCLUSIONS: A framework for quantification of oscillatory onset-offset time was developed for /hi/ tasks, which can be used for future measurements of disordered voice. A positive relationship was observed between VIP and POT and between OOToff and vocal offset period. There was a nonlinear relationship between the OOT, VIP, and POT measures. Onset-offset times are strongly influenced by the calculation method used, the pros and cons of which are discussed in this paper. Vibratory onset and offset represent physiologically different phenomena.
EVALuna2:35531

Ossicular osteoma of the malleus—A rare diagnosis of middle ear mass - Sievert, Matti; Mantsopoulos, Konstantinos; Hornung, Joachim; Thimsen, Vivian; Heiß, Rafael; Kopp, Markus; Wetzl, Matthias; Iro, Heinrich; Uder, Michael; Wiesmüller, Marco (Radiology Case Reports, 2022)
Osteoma of the middle ear (MEO) is a rarity. Due to the benign nature and slow growth rate, MEO are often occasionally found by chance. Possible unspecific clinical symptoms may be conductive hearing loss, tinnitus, effusion, and a sense of fullness. If the osteoma is small and not visible in the otoscopic inspection, it may be confused with other conductive hearing loss etiologies, such as otosclerosis. Nevertheless, one should be aware of this rare but important differential diagnosis of middle ear lesions. This article presents an MEO case causing conductive hearing loss and outlines the diagnostic approach with computed tomography.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Computed tomography; Conductive hearing loss; Middle ear lesion; Middle ear osteoma; Temporal bone osteoma

Osteitis is associated with dysregulated pro-osteoblastic activity in patients with nasal polyps - Wu, Dawei; Nocera, Angela L.; Mueller, Sarina K.; Finn, Kristen; Libermann, Towia A.; Bleier, Benjamin S. (Laryngoscope, 2019)
Objectives/Hypothesis The overlying inflammatory mucosa plays a crucial role in the initiation of osteitis; however, the molecular mechanism is unclear. The objective of this study was to explore the bone morphogenetic protein (BMP) pathway and to correlate the expression of key signaling molecules with the degree of osteitis in patients with chronic rhinosinusitis with nasal polyps (CRSwNP). Study Design Prospective experimental analysis. Methods This was an institutional review board-approved study in which mucosal samples were obtained from sites of osteitis in CRSwNP and compared to nonosteitic healthy controls (n = 10/group). Protein expression of key BMP pathway was quantified by aptamer-based protein array and confirmed by a set of selected mRNA analyses. Degree of osteitis was assessed using both Kennedy Osteitis Score and Global Osteitis Score (GOS). Results Pro-osteoblastic expression of BMP7 (fold change [FC] = -1.18, P = .017) and BMP9 (FC = -1.32, P = .023), their receptors, BMP receptor type-1A (BMPR1A) (FC = -2.56, P = .005) and BMP receptor type-2 (FC = -1.28, P = .022), and two enhancers of BMP signaling pathway, the repulsive guidance molecule domain family member B (FC = -1.13, P = .008) and the chordin-like protein 1 (FC = -1.18, P = .027), were all significantly downregulated in CRSwNP. Conversely, the pro-osteoclastic factor, tartrate-resistant acid phosphatase type 5 (ACP5) (FC = 2.36, P = .001), was significantly increased in CRSwNP. GOS was inversely correlated with levels of BMP7 (r = -0.684, P = .005) and BMPR1A (r = -0.864, P = .005) and positively correlated with levels of ACP5 (r = 0.815, P = .004). The FCs among the proteins studied significantly and positively correlated with the FCs of their mRNA expression (r = 0.908, P = .002). Conclusions Downregulated pro-osteoblastic mucosal BMP signaling is strongly and significantly associated with increased osteitis in CRSwNP.
CRIS-Team WoS Importer:2019-03-06

Outcome and management of rare high-grade “salivary” adenocarcinoma: the important role of adjuvant (chemo)radiotherapy - Scherl, Claudia; Haderlein, Marlen; Agaimy, Abbas; Mantsopoulos, Konstantinos; Koch, Michael; Traxdorf, Maximilian; Fietkau, Rainer; Grundtner, Philipp; Iro, Heinrich (Strahlentherapie und Onkologie, 2019)
Purpose: To determine survival and management strategies for high-grade adenocarcinoma of salivary glands (ASG). Methods: A retrospective analysis of cases diagnosed between 1998 and 2015 from our single tertiary referral center was performed. Multivariable logistic regression was used to determine factors associated with survival. Results: Thirty-eight cases of high-grade ASG were identified. Most patients were men (68.4%) with a median age of 65.5 years (range 23–84 years). Most tumors were T3 and T4 (65.8%). Regional metastases were common (55.2%), and 42.1% developed distant metastases. The mean follow-up was 60.5 months. All patients received surgery as primary treatment, with 84.2% of patients receiving adjuvant radiation therapy or chemoradiotherapy ([C]RT). Cumulative overall survival was 89.1%, 50.9%, and 20.7% after 1, 5, and 10 years, respectively. Disease-specific survival was 94.4%, 69.8%, and 42.8%, and distant-metastases-free survival (DMFS) was 80.5%, 50.1%, and 40.1% after 1, 5, and 10 years. On multivariable analysis, advanced T status correlated with DMFS (hazard ratio 2.75, 95% CI 0.93–8.16). Postsurgical (C)RT reduced the locoregional recurrence rate by 23.9%, and it improved the locoregional-recurrence-free survival by 39% (p = 0.094). Conclusion: High-grade ASG is considered to have an unfavorable prognosis. Adjuvant (C)RT reduces the rate of locoregional recurrences. Distant metastases are common, and an advanced T stage has increased prognostic value for development of early distant lesions.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Head and neck cancer; Salivary gland cancer; Salivary gland malignancy; Survival salivary gland cancer; Treatment salivary gland cancer

Outcome and prognostic factors in T4a oropharyngeal carcinoma, including the role of HPV infection - Psychogios, Georgios; Mantsopoulos, Konstantinos; Agaimy, Abbas; Brunner, Kathrin; Mangold, Elisabeth; Zenk, Johannes; Iro, Heinrich (BioMed Research International, 2014)
The prognosis of patients with advanced oropharyngeal carcinoma (OPSCC) is generally poor. The aim of this study is to investigate the different therapeutic approaches and identify prognostic factors associated with a worse outcome for patients treated for T4a OPSCC, in order to improve treatment selection for the individual.A retrospective study was conducted on 426 patients with T4a OPC treated between 1980 and 2010. Eleven prognostic factors including treatment modality, lymph node staging, and p16 status as a surrogate marker for human papillomavirus (HPV) infection were analyzed.Univariate analysis showed a significant difference in DSS between N0 and N+ (57.1% versus 26.9%, P < 0.001), primary surgical and primary nonsurgical treatment (52.7% versus 31.4%, P < 0.001), and perinodal invasion (51.7% versus 19.9%, P = 0.011). P16-negative patients tended towards a worse DSS than p16-positive patients (40.2% versus 64.6%, P = 0.126) but responded better to primary surgery than to nonsurgical treatment (71.4% versus 34.0%, P = 0.113). Multivariate analysis identified the N category as an independent prognostic factor for survival.The survival of p16-negative patients was worse than p16-positive patients, although they seem to respond better to primary surgery. The strongest independent prognostic factor for T4a carcinomas proved to be the presence of lymph node metastases.
EVALuna2:6638

Outcomes for a clinically representative cohort of hearing-impaired adults using the Nucleus® CI532 cochlear implant - Hey, Matthias; Neben, Nicole; Stöver, Timo; Baumann, Uwe; Mewes, Alexander; Liebscher, Tim; Schüssler, Mark; Aschendorff, Antje; Wesarg, Thomas; Büchner, Andreas; Greenham, Paula; Hoppe, Ulrich (European Archives of Oto-Rhino-Laryngology, 2020)
Purpose: Hearing performance data was collected from a large heterogeneous group of subjects implanted with the Cochlear™ Nucleus® CI532 with Slim Modiolar Electrode, for the purposes of postmarket clinical follow-up. Data was analysed for factors which may predict postoperative speech recognition scores. Methods: Data was collected retrospectively from five German clinics for 159 subjects from March 2017 to August 2018. Hearing thresholds and recognition scores for monosyllabic words in quiet and sentences in noise were measured preoperatively and at 3 and 6 months postoperatively. Results: There was a mean gain of 44% points (95% CI 39–49%) at 6 months in monosyllable scores in quiet for implanted ears. Preoperative hearing thresholds in implant ears increased systematically with decreasing age; however, younger subjects had better baseline monosyllable scores with hearing aids compared with older subjects. Baseline performance alone explained 14% of the variation in postoperative scores. Residual hearing was preserved on average to within 22 dB at 250 Hz and 30 dB at 500 Hz of preoperative levels. Conclusions: In a large and varied cohort of routinely treated hearing-impaired adults, speech recognition with the CI532 for German monosyllabic words in quiet at 6 months was equivalent to performance reported at one year or more in other published studies. Although younger subjects had poorer preoperative pure-tone thresholds, they had better preoperative word recognition scores compared with older subjects, and also had higher post implant scores. Further research is required to identify if this phenomenon is just applicable to German health system assessment and referral practices.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Congenital hearing loss; Data logging; Elderly; Hearing aids; Perimodiolar; Speech perception

Outcomes of transoral laser microsurgery and transoral robotic surgery in oropharyngeal squamous cell carcinoma - Sievert, Matti; Goncalves, Miguel; Zbidat, Ali; Traxdorf, Maximilian; Mueller, Sarina K.; Iro, Heinrich; Gostian, Antoniu Oreste (Auris Nasus Larynx, 2020)
Objective: Transoral robotic surgery (TORS) has evolved to a standard therapy modality for oropharyngeal carcinoma, especially in T1/ T2 tumors involving the base of the tongue due to its advantages compared with open surgery. However, knowledge about its benefits compared with transoral laser microsurgery (TLM) are scarce. This study compares oncological and functional results of TLM or TORS in the treatment of oropharyngeal squamous cell carcinoma (OPSCC). Methods: This retrospective analysis comprises all patients with OPSCC treated with TLM (n = 30) or TORS (n = 24) between April 2003 and May 2018 (follow-up 43 ± 38.3 months). Both treatment groups (TLM and TORS) were comparable in terms of the stage of the disease, prognosis-determining factors, and adjuvant therapy modalities. Results: There were no significant differences regarding to the resection status (p = 0.272), the rate of local- (p = 0.834) and distant- recurrence (p = 0.416), with a disease-free survival of 86.7 % and 87.5 %, respectively (p = 0.892). In addition, we could not confirm any differences regarding to operating time (p = 0.860), intraoperative blood loss (p = 0.660), inpatient stay (p = 0.585) and postoperative bleeding rate (p = 0.245). The frequency of tracheostomy and percutaneous endoscopic gastrostomy between both groups is comparable, with a longer duration of tube feeding in patients who have received TLM (p = 0.030). Conclusion: In conclusion, TORS allows for similar oncological outcomes compared with TLM at comparable perioperative risks. The postoperative swallowing function may benefit from TORS.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Head and neck cancer; Oropharyngeal cancer; Primary ablative surgery; Transoral laser microsurgery; Transoral robotic surgery

Overview on state-of-the-art numerical modeling of the phonation process - Döllinger, Michael; Zhang, Zhaoyan; Schoder, Stefan; Šidlof, Petr; Tur, Bogac; Kniesburges, Stefan (Acta Acustica, 2023)
Numerical modeling of the human phonatory process has become more and more in focus during the last two decades. The increase in computational power and the use of high-performance computation (HPC) yielded more complex models being closer to the actual fluid-structure-acoustic interaction (FSAI) within the human phonatory process. However, several different simulation approaches with varying mathematical complexity and focus on certain parts of the phonatory process exist. Currently, models are suggested based on ordinary differential equations (reduced order models) but also on partial differential equations based on continuum mechanics as e.g. the Navier-Stokes equations for the flow discretized by Finite-Volume or Finite-Element-Methods. This review will illuminate current trends and recent progress within the area. In summary, the ultimate simulation model satisfying all physiological needs and scientific opinions still has to be developed.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Computational fluid dynamics; Fluid-structure-acoustic-interaction; Fluid-structure-interaction; Machine learning; Numerical modeling

Pain after External and Endonasal Septorhinoplasty-A Propensity Score Matching Analysis - Gostian, Magdalena; Loeser, Johannes; Heindl, Ludwig; Gostian, Antoniu Oreste (Facial Plastic Surgery, 2020)
Guidelines for pain management following septorhinoplasty are lacking, leading to a wide range of therapy regimes even including opioid medication. Thus, the presented study strived to investigate and compare postoperative pain intensities after external and endonasal septorhinoplasty and evaluate whether pain perception is potentially related to patient satisfaction with the aesthetic result. In addition, the effectiveness of an escalating pain treatment protocol was evaluated sparing the necessity of opioid medication. This retrospective study performed at a tertiary referral medical center includes two well-balanced groups of 54 patients each created by propensity score matching out of a total of 161 patients following external or endonasal functional septorhinoplasty performed by a single surgeon between October 1, 2011 and March 31, 2017. Pain intensity was assessed using the visual analogue scale (0-10) on the first three postoperative days (PODs) alongside with the evaluation of the analgesic score. Patients' self-reported outcome was measured with the Utrecht questionnaire, preoperatively, and 3 and 12 months, postoperatively. Postoperative mean pain sensations were similarly high following the external and endonasal approach (F(2;190) = 2.166, p = 0.118) followed by a linear decrease over the first three PODs (F(2;190) = 16.84, p < 0.001). Pain sensations were not related to the duration of surgery, gender, patients' age, revision surgery, and the preoperative and postoperative assessment of the nasal appearance. The consumption of metamizole (F(1,76;172,15) = 2.83, p = 0.065) and ibuprofen (F(2;196) = 1.037, p = 0.356) were similarly high regardless of the surgical approach. Accordingly, both the endonasal and the external approaches led to comparable postoperative pain intensities and analgesic scores. Pain was treated effectively using a standardized escalating pain treatment protocol sparing the administration of opioids. Pain was not related to patient satisfaction with the nasal appearance pre- and postsurgery.
CRIS-Team Scopus Importer:2020-06-30

Pain management after tonsillectomy—by demand or by-the-clock—is there a difference? - Gostian, Magdalena; Stilkerich, Lisa; Pauly, Anne; Balk, Matthias; Rupp, Robin; Allner, Moritz; Iro, Heinrich; Gostian, Antoniu-Oreste; Waldfahrer, Frank (Ent-Ear Nose & Throat Journal, 2022)
Purpose: To improve pain management after tonsillectomy (TE) by comparing individual analgesic management by demand versus a fixed-scheduled analgesic treatment protocol in a prospective trial. Patients and Methods: Forty consecutive patients received individual pain treatment by demand (control group) followed by 40 patients who were treated by a fixed-scheduled four-staged escalating analgesic protocol (intervention group) after TE. Minimum and maximum pain as well as pain on ambulation (NRS 0-10) on the first postoperative day were defined as primary objectives. Secondary endpoints comprised the analgesic score, treatment-related side effects/pain-associated impairments, wish for more pain medication, and patient satisfaction. Patients were surveyed using the standardized and validated “Quality Improvement in Postoperative Pain Treatment” (QUIPS) questionnaire. Results: Patients of the control group reported comparable minimum (2.03 ± 1.42 vs 2.38 ± 1.79, P = 0.337, r = 0.110) and maximum pain (6.65 ± 2.10 vs 6.93 ± 1.86, P = 0.536, r = 0.07) and pain on ambulation (4.73 ± 2.26 vs 5.18 ± 2.19, P = 0.370, r = 0.10) compared to the intervention group. Patients in both groups were comparably well satisfied with the pain treatment (7.53 ± 2.40 vs 7.73 ± 2.30, P = 0.704, r = 0.04), experienced similar side effects and functional impairments (P > 0.050, Φ < 0.3), and did not ask for much more analgesic medication (P = 0.152, Φ = 0.160). Conclusion: Pain control following TE was not distinctly affected by applying a fixed-scheduled analgesic treatment protocol compared to individual analgesic therapy. In conclusion, analgesic treatment after TE remains unsatisfying. Consequently, further efforts are needed to achieve a standardized and effective approach to the underlying pathophysiological causes of pain following TE.
CRIS-Team Scopus Importer:2022-08-05
Keywords: patient reported outcome measure; postoperative pain; quality management; QUIPS

Panel sequencing in head and neck oncology: Sinonasal and salivary gland malignancies as an example - Agaimy, Abbas; Mueller, Sarina K. (Die Onkologie, 2022)
Background: As a result of the increasing implementation of innovative molecular technologies during the last two decades, the pathology of salivary gland carcinomas and sinonasal carcinomas has witnessed a tremendous revolution. Aim: With the introduction of molecular tumor boards as a central opportunity exploring the possibility of actionable molecular targets in head and neck oncology, the question has been frequently raised as to which entities/patients might represent good or best candidates for OncoPanel sequencing in the context of these regularly implemented molecular tumor boards. The main aim of this review is to address this question considering recent developments and in context of the current World Health Organization (WHO) classification. Materials and methods: This review is based on a selective literature search (PubMed) using the terms salivary gland malignancy, sinonasal carcinoma and targeted therapies as well as the authors' own data and observations. Results and conclusion: As a result of several recent seminal studies on salivary and sinonasal carcinomas, some old concepts have been reconceptualized, some new concepts introduced, and some old, established entities became better defined molecularly. These achievements have influenced not only diagnostics (they enable a much refined, mostly molecular-based classification of many entities that were previously unclassified) but they also have a significant therapeutic impact (they enable better histology-tailored therapeutic stratification, at the same time some of them represent valuable biomarkers predicting response to targeted therapies).
CRIS-Team WoS Importer:2022-12-23

Papillary-cystic neoplasms of the middle ear are distinct from endolymphatic sac tumours - Taverna, Cecilia; Pollastri, Federica; Pecci, Rudi; Giannoni, Beatrice; Fattorini, Caterina; Santucci, Marco; Mueller, Sarina K.; Stöhr, Robert; Franchi, Alessandro; Agaimy, Abbas (Histopathology, 2020)
Aims Papillary neoplasms of the middle and inner ear are rare and poorly characterised. The current World Health Organization classification divides them into two major subtypes: aggressive papillary tumours (APTs) and endolymphatic sac tumours (ELSTs). The aim of this article is to present two papillary neoplasms of the middle ear that do not fit into either the classic APT category or the classic ELST category, and compare them with three ELSTs.
CRIS-Team WoS Importer:2020-11-27

Papillary stenosis of the submandibular gland caused by dental prostheses - Schapher, Mirco; Goncalves, Miguel; Mantsopoulos, Konstantinos; Iro, Heinrich; Koch, Michael (Oral Surgery, Oral Medicine, Oral Pathology and Oral Radiology, 2020)
Objectives: The aim of this study was to assess diagnosis and treatment of submandibular duct stenosis caused by dental prostheses. Study Design: This retrospective study included 9 patients with papillary stenosis caused by physical irritation of the Wharton duct ostium by a mandibular dental prosthesis. Diagnostics included physical examination, as well as transcutaneous and transoral ultrasound examinations. Treatment consisted of duct incision, papillotomy, and subsequent sialendoscopy. After surgery, patients were advised to have the dental prosthesis altered by the dentist and to have regular gland massage. Follow-up data were obtained via telephone interviews. The most important outcome parameter was a symptom-free state. Results: In all 9 patients, the insertion of the sialendoscope was initially impossible because of the stenosis. After duct incision, sialendoscopy ruled out other obstructive causes and inflammatory states, leaving the dental prosthesis as the only underlying cause of the obstruction. Seven of the 9 treated patients were interviewed after a follow-up period of 28.1 (± 25.4) months. The procedures had resulted in all patients being symptom-free, without any reported complications. Conclusions: Mandibular prostheses can cause stenosis of the papillary region with subsequent submandibular duct obstruction. Surgical therapy is easy to perform and results in excellent long-term outcomes.
CRIS-Team Scopus Importer:2020-03-06

Paradigm shift in surgery for benign parotid tumors: 19 years of experience with almost 3000 cases - Bär, Bianca; Mantsopoulos, Konstantinos; Iro, Heinrich (Laryngoscope, 2019)
Objectives: The aim of this study was to explore the changes in philosophy in the surgical therapy of benign parotid tumors over a period of 19 years. Methods: The records of all patients treated for benign parotid tumors between 2000 and 2018 were evaluated. Data were analyzed with respect to the number of procedures carried out per year of the study according to each of the different surgical modalities and the incidence of postoperative complications. Statistical analysis was performed using the x2 test. A P value of <.05 was considered statistically significant. Results: A total of 2988 patients were included in this study. Our analysis showed that the increasing performance of extracapsular dissection was associated with a progressive reduction in the incidence of temporary facial nerve palsy and Frey's syndrome, while the rate of permanent facial nerve palsy remained consistently low. Conclusion: One of the most controversial issues in head and neck surgery is which therapeutic approach is best in patients with benign parotid tumors. Our analysis demonstrated that a change of strategy towards reducing invasiveness was possible, with exceptional functional results. Avoidance of facial nerve dissection is feasible in more than two-thirds of cases with benign tumors. Level of Evidence: 4b. Laryngoscope, 2019.
CRIS-Team Scopus Importer:2019-12-17
Keywords: complete parotidectomy; Extracapsular dissection; facial nerve; Frey's syndrome; superficial parotidectomy

Paragangliomas of the Head and Neck: Local Control and Functional Outcome Following Fractionated Stereotactic Radiotherapy - Weissmann, Thomas; Lettmaier, Sebastian; Roesch, Johannes; Mengling, Veit; Bert, Christoph; Iro, Heinrich; Hornung, Joachim; Janka, Rolf Matthias; Semrau, Sabine; Fietkau, Rainer; Putz, Florian (American Journal of Clinical Oncology-Cancer Clinical Trials, 2019)
Objectives: To investigate local control and functional outcome following state-of-the-art fractionated stereotactic radiotherapy (FSRT) for paragangliomas of the head and neck. Methods: In total, 40 consecutive patients with paragangliomas of the head and neck received conventionally FSRT from 2003 to 2016 at the Department of Radiation Oncology of the University Hospital Erlangen. Local control, toxicities, and functional outcome were examined during follow-up. In total, 148 magnetic resonance imaging studies were subjected to longitudinal volumetric analysis using whole tumor segmentation in a subset of 22 patients. Results: A total of 80.0% (32/40) of patients received radiotherapy as part of their primary treatment. In 20.0% (8/40) of patients, radiation was used as salvage treatment after tumor recurrence in patients initially treated with surgery alone. The median dose applied was 54.0 Gy (interdecile range, 50.4 to 56.0 Gy) in single doses of 1.8 or 2 Gy. Local control was 100% after a median imaging follow-up of 52.2 months (range, 0.8 to 152.9 mo). The volumetric analysis confirmed sustained tumor control in a subset of 22 patients and showed transient enlargement (range, 129.6% to 151.2%) in 13.6% of cases (3/22). After a median volumetric follow-up of 24.6 months mean tumor volume had diminished to 86.1% compared with initial volume. In total, 52.5% (21/40) of patients reported improved symptoms after radiotherapy, 40% (16/40) observed no subjective change with only 7.5% (3/40) reporting significant worsening. Conclusions: State-of-the-art FSRT provides excellent control and favorable functional outcome in patients with paragangliomas of the head and neck. The volumetric analysis provides improved evidence for sustained tumor control.
CRIS-Team Scopus Importer:2019-10-22
Keywords: fractionated stereotactic radiotherapy; functional outcomes; paraganglioma; tumor control; volumetric analysis

Parameterization of voice onset for automatic assessment of Parkinson’s disease - Arias Vergara, Tomás; Schraut, Tobias; Orozco-Arroyave, Juan R.; Döllinger, Michael (Journal of the Acoustical Society of America, 2022)
Acoustic analysis of Parkinson’s disease (PD) usually focuses on sustained oscillations of the vocal folds; however, the voice onset (transition from the rest state to a saturation value) is often neglected. In this study, we investigated the parameterization of the voice onset for the objective evaluation of PD. 50 PD patients (25 females) and 50 healthy controls (25 females) performed the sustained phonation of the vowels /ah/, /ih/, and /uh/. Three experts listened to the recordings and assessed the dysarthria level according to a modified version of the Frenchay dysarthria assessment scale (mFDA). We extracted the voice onset automatically, considering the time needed for the amplitude envelope of the acoustic signal to go from 10% up to 90% of the maximum value. Then, we computed filter bank features from the voice onset and pitch, loudness, and perturbation features from the sustained phonation. We performed automatic classification and regression analyses using support vector machines. We obtained a classification accuracy of 89% (AUC: 0.93) when we used feature importance analysis to reduce the feature set. In addition, the regression analysis showed a significant correlation (r: 0.583, p-value < 0.001) between the acoustic features and the mFDA scale. These results show the suitability of the voice onset for objective clinical evaluation of PD.<br
Keywords: Phonetics; Vocal folds; Acoustic modeling; simulation and analysis; Speech perception; Acoustic signal processing; Vowel systems; Machine learning; Regression analysis

Parameterization of voice onset for automatic assessment of Parkinson’s disease - Arias Vergara, Tomás; Schraut, Tobias; Orozco-Arroyave, Juan R.; Döllinger, Michael (Journal of the Acoustical Society of America, 2022)
Acoustic analysis of Parkinson’s disease (PD) usually focuses on sustained oscillations of the vocal folds; however, the voice onset (transition from the rest state to a saturation value) is often neglected. In this study, we investigated the parameterization of the voice onset for the objective evaluation of PD. 50 PD patients (25 females) and 50 healthy controls (25 females) performed the sustained phonation of the vowels /ah/, /ih/, and /uh/. Three experts listened to the recordings and assessed the dysarthria level according to a modified version of the Frenchay dysarthria assessment scale (mFDA). We extracted the voice onset automatically, considering the time needed for the amplitude envelope of the acoustic signal to go from 10% up to 90% of the maximum value. Then, we computed filter bank features from the voice onset and pitch, loudness, and perturbation features from the sustained phonation. We performed automatic classification and regression analyses using support vector machines. We obtained a classification accuracy of 89% (AUC: 0.93) when we used feature importance analysis to reduce the feature set. In addition, the regression analysis showed a significant correlation (r: 0.583, p-value < 0.001) between the acoustic features and the mFDA scale. These results show the suitability of the voice onset for objective clinical evaluation of PD.<br

Parotid pleomorphic adenomas: Factors influencing surgical techniques, morbidity, and long-term outcome relative to the new ESGS classification in a retrospective study - Schapher, Mirco; Koch, Michael; Agaimy, Abbas; Goncalves, Miguel; Mantsopoulos, Konstantinos; Iro, Heinrich (Journal of Cranio-Maxillofacial Surgery, 2019)
Purpose: To assess long-term results after treatment of parotid pleomorphic adenomas (PPAs) with different surgical techniques, standardized according to the European Salivary Gland Society (ESGS) classification system. Methods: We analyzed ESGS categories, occurrence of facial nerve paresis (FNP), Frey's syndrome, histopathology, and recurrences. Surgical modalities were compared, differentiating techniques with and without facial nerve dissection. A strict protocol ensured a postoperative follow-up-period of more than 7 years. Results: 205 patients were included. A complete follow-up was possible in 138 patients, 77 of whom underwent extracapsular dissection (ED) and 61 of whom had other surgical modalities (OSMs). ESGS categories correlated with the extent of surgery, significantly with the risk for FNP and Frey's syndrome, but not with recurrences. Recurrences did not differ significantly between ED and OSMs, whereas the risks for FNP (p < 0.001 each) and Frey's syndrome (p = 0.000) were significantly higher after OSMs in comparison with ED. Young women with a stroma-rich (myxoid) tumor subtype appear to have the greatest risk for recurrences. Conclusion: ED is the treatment of choice for PPAs, if possible, resulting in similar recurrence rates but significantly fewer comorbidities in comparison with more extensive surgery. After the treatment of PPAs, a long-term follow-up is needed, including imaging.
CRIS-Team Scopus Importer:2019-08-02
Keywords: Extracapsular dissection; Facial nerve paresis; Follow-up; Frey's syndrome; Pleomorphic adenoma; Recurrence

Patch-based Carcinoma Detection on Confocal Laser Endomicroscopy Images - A Cross-Site Robustness Assessment - Aubreville, Marc; Goncalves, Miguel; Knipfer, Christian; Oetter, Nicolai; Würfl, Tobias; Neumann, Helmut; Stelzle, Florian; Bohr, Christopher; Maier, Andreas (Proceedings of the 11th International Joint Conference on Biomedical Engineering Systems and Technologies (BIOSTEC 2018), 2018)
Deep learning technologies such as convolutional neural networks (CNN) provide powerful methods for image recognition and have recently been employed in the field of automated carcinoma detection in confocal laser endomicroscopy (CLE) images. CLE is a (sub-)surface microscopic imaging technique that reaches magnifications of up to 1000x and is thus suitable for in vivo structural tissue analysis. In this work, we aim to evaluate the prospects of a priorly developed deep learning-based algorithm targeted at the identification of oral squamous cell carcinoma with regard to its generalization to further anatomic locations of squamous cell carcinomas in the area of head and neck. We applied the algorithm on images acquired from the vocal fold area of five patients with histologically verified squamous cell carcinoma and presumably healthy control images of the clinically normal contra-lateral vocal cord. We find that the network trained on the oral cavity data reaches an accura

Pathologic response after induction chemo-immunotherapy with single or double immune checkpoint inhibition in locally advanced head and neck squamous cell carcinoma (HNSCC): Expansion cohorts of the CheckRad-CD8 trial. - Hecht, Markus; Eckstein, Markus; Kallies, Annett; Klautke, Gunther; Illmer, Thomas; von der Grün, Jens; Laban, Simon; Hautmann, Matthias; Tamaskovics, Bálint; Hinke, Axel; Brunner, Thomas; Frey, Benjamin; et al. (JOURNAL OF CLINICAL ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-11-04

Patients with COVID-19: in the dark-NETs of neutrophils - Ackermann, Maximilian; Anders, Hans-Joachim; Bilyy, Rostyslav; Bowlin, Gary L.; Daniel, Christoph; De Lorenzo, Rebecca; Egeblad, Mikala; Henneck, Timo; Hidalgo, Andres; Hoffmann, Markus; Hohberger, Bettina; Kanthi, Yogendra; et al. (Cell Death and Differentiation, 2021)
SARS-CoV-2 infection poses a major threat to the lungs and multiple other organs, occasionally causing death. Until effective vaccines are developed to curb the pandemic, it is paramount to define the mechanisms and develop protective therapies to prevent organ dysfunction in patients with COVID-19. Individuals that develop severe manifestations have signs of dysregulated innate and adaptive immune responses. Emerging evidence implicates neutrophils and the disbalance between neutrophil extracellular trap (NET) formation and degradation plays a central role in the pathophysiology of inflammation, coagulopathy, organ damage, and immunothrombosis that characterize severe cases of COVID-19. Here, we discuss the evidence supporting a role for NETs in COVID-19 manifestations and present putative mechanisms, by which NETs promote tissue injury and immunothrombosis. We present therapeutic strategies, which have been successful in the treatment of immunο-inflammatory disorders and which target dysregulated NET formation or degradation, as potential approaches that may benefit patients with severe COVID-19.
CRIS-Team Scopus Importer:2021-06-04

Peak-bone-mass development in young adults: effects of study program related levels of occupational and leisure time physical activity and exercise. A prospective 5-year study - Kemmler, Wolfgang; Bebenek, Michael; von Stengel, Simon; Bauer, Judith (Osteoporosis international, 2015)
Young adulthood is characterized by profound life-style changes. This study suggests that reduction of sport or exercise, induced by alteration of the occupational situation, negatively impacts generation/maintenance of peak bone mass. In order to compensate occupational-related reductions of physical activity, workplace exercise programs will be helpful.Only few studies have determined the effect of physical activity or physical exercise on bone mineral density (BMD) in the period of late skeletal maturation, i.e. around peak bone mass. The aim of this article was to determine the long-term effect of different levels of physical activity and exercise directly and indirectly derived by occupation during young adulthood.Sixty-one male and female dental students (DES) and 53 male and female sport students (SPS) 21 ± 2 years old were accompanied over the course (4.8 ± 0.5 years) of their study program. BMD at the lumbar spine (LS), hip, and whole body (WB) were determined using dual-energy X-ray absorptiometry.Parameters of physical activity increased non-significantly in both groups with no relevant differences between the groups. Indices of exercise, however, increased significantly in the SPS group while a significant decrease was assessed for the DES group. Independent of gender, BMD of the SPS increased significantly (p <= 0.007) at all skeletal sites (LS, 2.4 ± 3.9 %; hip, 1.6 ± 3.5 %; WB, 1.8 ± 2.8 %) while BMD of the DES remained unchanged at LS (-0.6 ± 4.4 %, p = 0.432) and WB (0.5 ± 1.9 %, p = 0.092) but decreased significantly at the hip (-1.9 ± 4.3 %, p = 0.010). BMD-changes at LS, hip, and WB differ significantly between SPS and DES (p <= 0.017). Results remained unchanged after adjusting for baseline BMD-values that differed (p = 0.030 to p = 0.082) in favor of the SPS group.Changes of exercise levels directly or indirectly caused by occupational factors during young adulthood significantly affected generation and/or maintenance of peak bone mass. Compensatory exercise is thus highly relevant for bone health of young adults.
EVALuna2:10101

Pediatric salivary gland tumors and tumor-like lesions - Agaimy, Abbas; Iro, Heinrich; Zenk, J. (Pathologe, 2017)
Salivary gland tumors and tumor-like lesions in the pediatric population are uncommon. They comprise a heterogeneous group of infectious/inflammatory and neoplastic conditions. Pediatric salivary neoplasms include benign tumors of mesenchymal or epithelial origin as well as malignancies of epithelial (carcinomas), mesenchymal (sarcoma) or hematolymphoid (lymphoma) derivation. Infectious/inflammatory conditions and hematolymphoid malignancies may represent either genuine parenchymal pathology or conditions involving intraglandular lymph nodes of the parotid glands (intraglandular lymphadenopathy and intraglandular nodal lymphomas). Pediatric sialadenitis may be of diverse etiologies including viral (mumps, CMV, HIV, etc.), bacterial, autoimmune (juvenile Sjögren syndrome) or idiopathic (chronic recurrent juvenile sialectatic sialadenitis). Angiomatous lesions (juvenile capillary hemangioma, lymphangioma and vascular malformation) and pleomorphic adenomas represent the most common pediatric benign mesenchymal and benign epithelial tumors, respectively. The vast majority of salivary gland carcinomas in children and adolescents represent low-grade mucoepidermoid carcinomas followed by acinic cell and adenoid cystic carcinomas (together >80% of carcinomas). Other malignant neoplasms include (rhabdomyo-) sarcomas, malignant lymphomas and very rarely sialoblastomas. This long differential diagnosis list of etiologically and biologically highly heterogeneous entities, their shared clinical presentation as "salivary gland enlargement" and the significant differences in their therapeutic strategies and prognosis underline the need for careful assessment to identify the correct diagnosis. Diagnosis is mainly based on a set of typical clinical and imaging features, serological/microbiological findings and, in selected cases, histomorphological characteristics in biopsy specimens.
EVALuna2:6863

Pedicled Transplantation of Axially Vascularized Bone Constructs in a Critical Size Femoral Defect - Arkudas, Andreas; Lipp, Amelie; Bührer, Gregor; Arnold, Isabel; Davinova, Diana; Brandl, Andreas; Beier, Justus; Körner, Carolin; Lyer, Stefan; Alexiou, Christoph; Kneser, Ulrich; Horch, Raymund E. (Tissue Engineering: Parts A, B, and C, 2017)
Introduction: Axial vascularization represents a mandatory requirement for clinically applied larger scale vascularized bone grafts. The aim of this study was to combine the arteriovenous (AV) loop model in the rat with a critically sized femoral bone defect and to successfully transplant axially vascularized bone constructs into the defect. Materials and Methods: In Groups A and C, an AV loop together with a clinically approved hydroxyapatite and beta-tricalcium phosphate (HA/β-TCP) matrix, mesenchymal stem cells, and recombinant human bone morphogenetic protein 2 were implanted into a newly designed porous titanium chamber with an integrated osteosynthesis plate in the thighs of rats, whereas in Groups B and D, the same matrix composition without AV loop and, in Group E, only the HA/β-TCP matrix were implanted. After 6 weeks, the constructs were transplanted into a 10 mm femoral defect created in the same leg, in Groups A and C, under preservation of the AV loop pedicle. Group F served as a control group with an empty chamber. Ten days (Groups A and B) and 12 weeks (Groups C–F) after transplantation, the femora together with the constructs were explanted and investigated using computed tomography (CT), micro-CT, X-ray, histology, and real-time polymerase chain reaction (RT-PCR). Results: Ten days after transplantation, Group A showed a maintained vascular supply leading to increased vascularization, cell survival in the scaffold center, and bone generation compared to Group B. After 12 weeks, there was no difference detectable among all groups regarding total vessel number, although Group C, using the AV loop, still showed increased vascularization of the construct center compared to Groups D and E. In Group C, there was still enhanced bone generation detectable compared to the other groups and increased bony fusion rate at the proximal femoral stump. Conclusions: This study shows the combination of the AV loop model in the rat with a critically sized femoral defect. By maintenance of the vascular supply, the constructs initially showed increased vascularization, leading to increased bone formation and bony fusion in the long term.
Keywords: AV loop; femur defect model; critically sized bone defect; bone tissue engineering

Peptide functionalized magnetic nanoparticles for experimental sepsis therapy - Friedrich, Bernhard; Unterweger, Harald; Lyer, Stefan; Janko, Christina; Alexiou, Christoph; Tietze, Rainer (INFECTION, 2019)
CRIS-Team WoS Importer:2019-09-06

[Perceptual and automatic voice and speech analysis of chronic laryngitis and T1 vocal cord cancer]. - Bartke, Betina; Haderlein, Tino; Döllinger, Michael; Nöth, Elmar; Graf, S.; Eysholdt, Ulrich; Ziethe, A. (HNO, 2013)
BACKGROUND Patients with chronic laryngitis and T1 vocal cord cancer were compared using perceptual and text-based objective voice and speech analyses in order to determine which group is more affected in its ability to communicate and whether a distinction between the two pathologies is possible. PATIENTS AND METHODS In all, 13 patients with histologically proven chronic laryngitis and 13 patients with T1 vocal cord cancer were compared perceptually by five speech therapists on the basis of seven criteria and objectively by a speech recognition system and prosodic analysis. RESULTS Both, the data of the five speech therapists and the results of the automatic analysis revealed no significant differences between the two patient groups. CONCLUSION A distinction between chronic laryngitis and T1 vocal cord carcinoma by mere voice and speech analysis is not possible, because the patient groups do not show significant differences in their voice quality.
Keywords: Automatic pattern recognition; Comparative study; Laryngitis; Perceptual and objective voice and speech analysis; Vocal folds

Peripheral signaling pathways contributing to non-histaminergic itch in humans - Fiebig, Andrea; Leibl, Victoria; Oostendorf, David; Lukaschek, Saskia; Frömbgen, Jens; Masoudi, Maral; Kremer, Andreas E.; Strupf, Marion; Reeh, Peter; Düll, Miriam; Namer, Barbara (Journal of Translational Medicine, 2023)
Background: Chronic itch (chronic pruritus) is a major therapeutic challenge that remains poorly understood despite the extensive recent analysis of human pruriceptors. It is unclear how the peripheral nervous system differentiates the signaling of non-histaminergic itch and pain. Methods: Here we used psychophysical analysis and microneurography (single nerve fiber recordings) in healthy human volunteers to explore the distinct signaling mechanisms of itch, using the pruritogens β-alanine, BAM 8-22 and cowhage extract. Results: The mode of application (injection or focal application using inactivated cowhage spicules) influenced the itch/pain ratio in sensations induced by BAM 8-22 and cowhage but not β-alanine. We found that sensitizing pre-injections of prostaglandin E2 increased the pain component of BAM 8-22 but not the other pruritogens. A-fibers contributed only to itch induced by β-alanine. TRPV1 and TRPA1 were necessary for itch signaling induced by all three pruritogens. In single-fiber recordings, we found that BAM 8-22 and β-alanine injection activated nearly all CM-fibers (to different extents) but not CMi-fibers, whereas cowhage extract injection activated only 56% of CM-fibers but also 25% of CMi-fibers. A “slow bursting discharge pattern” was evoked in 25% of CM-fibers by β-alanine, in 35% by BAM 8-22, but in only 10% by cowhage extract. Conclusion: Our results indicate that no labeled line exists for these pruritogens in humans. A combination of different mechanisms, specific for each pruritogen, leads to itching sensations rather than pain. Notably, non-receptor-based mechanisms such as spatial contrast or discharge pattern coding seem to be important processes. These findings will facilitate the discovery of therapeutic targets for chronic pruritus, which are unlikely to be treated effectively by single receptor blockade.
CRIS-Team Scopus Importer:2023-12-22
Keywords: BAM 8-22; Cowhage; Discharge patterns; Microneurography; Nociceptor; Pruriceptor; Single-fiber recording; Spatial contrast; β-Alanine

Phantom-based prospective analysis of the accuracy of photo registration technology in electromagnetic navigation of the frontal skull base - Schilke, Paul; Anderssohn, S.; Tziridis, K.; Mantsopoulos, K.; Mueller, S.; Sievert, M.; Gostian, A. O.; Iro, H.; Bohr, C.; Traxdorf, M. (European Review for Medical and Pharmacological Sciences, 2022)
OBJECTIVE: This prospective study compared the accuracy of two different company-specific registration methods (Fiagon GmbH, Hennigsdorf, Germany) in the electromagnetic navigation of the frontal skull base. A newly developed photo registration technology (Fiagon tracey©) promises an increase in accuracy and user-friendliness, but there is no phantom-based prospective study comparing the new method with the classic approach of tactile surface registration. MATERIALS AND METHODS: A phantom skull was prepared with 27 markers in the sagittal, axial and coronary planes, and their reference coordinates were determined using a navigational CT (low dose, slice 0.6 mm). Subsequently, 20 runs of automatic photo registration and tactile surface registration were carried out, and the resulting marker coordinates were compared with the reference coordinates. The target registration error (TRE) of the 27 markers was assessed and compared between the two methods using a 2-factor ANOVA with repeated measures. RESULTS: The mean TRE using surface registration was 1.97 mm ± 0.57, while the mean TRE of the automatic photo registration was 1.54 mm ± 0.24 (p < 0.001). In a subgroup analysis limited to markers in anatomical regions of clinical relevance in terms of paranasal sinus surgery, the mean TRE for the photo registration procedure can even be reduced to 1.29 mm (± 0.43) compared to tactile registration (1.80 mm; ±0.50; p=0.01). CONCLUSIONS: Photo registration is a promising new technology in the field of electromagnetic navigation in paranasal sinus surgery. This prospective phantom-based study showed that the photo registration method achieves a significantly lower target registration error (1.29 mm) compared to the surface-based tactile registration procedure (1.80 mm).
CRIS-Team Scopus Importer:2022-04-01

Phantom Studies of Neutron Capture of Boron Containing Magnetic Nanoparticles - Tietze, Rainer; Dürr, Stephan; Lyer, Stefan; Taccardi, Nicola; Wasserscheid, Peter; Canella, Lea; Wagner, Franz M.; Petry, Winfried; Alexiou, Christoph (Biomedizinische Technik, 2013)
The main burden that hinders the translation of neutron capture therapy drafts to human trials is the difficulty to deposit a sufficient amount of boron in the targeted tumour areas. Magnetic nanoparticles containing B-10 isotopes attempt to be enriched in tumour tissues selectively by the means of external magnetic fields to overcome these restrictions. First pilot measurements of the neutron depth penetration investigated the neutron flux density in dependence of depth, presence of boron and additional presence of iron oxide nanoparticles. These irradiation experiments on different phantoms evidenced no disturbing attenuation effects of the applied boron and the co-present nanoparticles in the samples.
EVALuna2:19968

Pharmaceutical formulation of HSA hybrid coated iron oxide nanoparticles for magnetic drug targeting - Zaloga, Jan; Poettler, Marina; Leitinger, Gerd; Friedrich, Ralf P.; Almer, Gunter; Lyer, Stefan; Baum, Eva; Tietze, Rainer; Heimke-Brinck, Ralph; Mangge, Harald; Dörje, Frank; Lee, Geoffrey; et al. (European Journal of Pharmaceutics and Biopharmaceutics, 2016)
In this work we present a new formulation of superparamagnetic iron oxide nanoparticles (SPIONs) for magnetic drug targeting. The particles were reproducibly synthesized from current good manufacturing practice (cGMP) - grade substances. They were surface coated using fatty acids as anchoring molecules for human serum albumin. We comprehensively characterized the physicochemical core-shell structure of the particles using sophisticated methods. We investigated biocompatibility and cellular uptake of the particles using an established flow cytometric method in combination with microwave-plasma assisted atomic emission spectroscopy (MP-AES). The cytotoxic drug mitoxantrone was adsorbed on the protein shell and we showed that even in complex media it is slowly released with a close to zero order kinetics. We also describe an in vitro proof-of-concept assay in which we clearly showed that local enrichment of this SPION-drug conjugate with a magnet allows site-specific therapeutic effects.
EVALuna2:20018

Pharmacologic treatments in preclinical tinnitus models with special focus on Ginkgo biloba leaf extract EGb 761® - Barth, Stephan W.; Lehner, Martin D.; Dietz, Gunnar P.H.; Schulze, Holger (Molecular and Cellular Neuroscience, 2021)
Tinnitus is defined as the perception of sound in the absence of external acoustic stimuli. Frequent comorbidities or associated factors are depression, anxiety, concentration problems, insomnia, resignation, helplessness, headache, bruxism, or social isolation, just to name a few. Although many therapeutic approaches have already been tested with varying success, there still is no cure available for tinnitus. The search for an effective treatment has been hampered by the fact that the mechanisms of tinnitus development are still not fully understood, although several models are available and discussed in this review. Our review will give a brief overview about preclinical models, presenting the heterogeneity of tinnitus sub-types depending on the different inner ear and brain structures involved in tinnitus etiology and pathogenesis. Based on these models we introduce the different target structures and transmitter systems implicated in tinnitus development and provide an extensive overview on preclinical drug-based therapeutic approaches that have been explored in various animal models. As the special extract from Ginkgo biloba leaves EGb 761® has been the most widely tested drug in both non-clinical tinnitus models as well as in clinical trials, a special focus will be given to EGb 761®. The efficacy of terpene lactones, flavone glycosides and proanthocyanidines with their distinct contribution to the overall efficacy profile of the multi-constituent drug EGb 761® will be discussed.
CRIS-Team Scopus Importer:2021-10-08
Keywords: Gerbil; Hearing research; Inner ear; Medication; Mouse; Pharmacology; Plant extract; ginkgo; translational; Rat; Rodent model

Phase I safety and tolerability study of topical verapamil HCl in chronic rhinosinusitis with nasal polyps - Workman, Alan D.; Mueller, Sarina K.; Mcdonnell, Kristen; Goldfarb, Jeremy W.; Bleier, Benjamin S. (International Forum of Allergy and Rhinology, 2022)
CRIS-Team WoS Importer:2022-02-04

Phase-locked flow field analysis in a synthetic human larynx model - Lodermeyer, Alexander; Becker, Stefan; Döllinger, Michael; Kniesburges, Stefan (Experiments in Fluids, 2015)

Phase-locked flow field analysis in a synthetic human larynx model - Lodermeyer, Alexander; Becker, Stefan; Kniesburges, Stefan; Döllinger, Michael (17th International symposium on applications of laser techniques to fluid mechanics, 2014)

Phenotypical and molecular distinctness of sinonasal haemangiopericytoma compared to solitary fibrous tumour of the sinonasal tract - Agaimy, Abbas; Barthelmeß, Sarah; Geddert, Helene; Boltze, Carsten; Moskalev, Evgeny; Koch, Michael; Wiemann, Stefan; Hartmann, Arndt; Haller, Florian (Histopathology, 2014)
Sinonasal haemangiopericytoma (SN-HPC) is a rare sinonasal mesenchymal neoplasm of perivascular myoid cell origin. Solitary fibrous tumour (SFT) occurs only very rarely in the sinonasal tract. SFT and soft tissue HPC have been considered a single entity. Recently, recurrent gene fusions involving NAB2-STAT6 resulting in differential expression of STAT6 were characterized as central molecular events in SFT. However, no data exist for NAB2-STAT6 status or STAT6 expression in SN-HPC.We examined six SN-HPCs and two sinonasal SFTs by immunohistochemistry and RT-PCR for NAB2-STAT6 fusions. SN-HPC affected three females and three males (mean age: 72 years). They expressed smooth muscle actin, lacked strong CD34 reactivity and were negative for nuclear STAT6 expression. RT-PCR analysis confirmed the absence of NAB2-STAT6 fusions in all cases. Conversely, both sinonasal SFTs (in males aged 39 and 52 years) displayed classical features of pleuropulmonary and soft-tissue SFTs (uniformly CD34-positive with strong nuclear expression of STAT6). RT-PCR revealed NAB2-STAT6 fusions in both cases.These findings confirm the molecular and phenotypical distinctness of these two entities. While SN-HPC is a site-specific sinonasal neoplasm of as yet unknown molecular pathogenesis, sinonasal SFTs show phenotypical and molecular identity to their pleural/extrapleural counterparts.
EVALuna2:6649

Phonation Analysis Combined with 3D Reconstruction of the Thyroarytenoid Muscle in Aged Ovine Ex Vivo Larynx Models - Gerstenberger, Claus; Döllinger, Michael; Kniesburges, Stefan; Bubalo, Vladimir; Karbiener, Michael; Schlager, Hansjoerg; Sadeghi, Hossein; Wendler, Olaf; Gugatschka, Markus (Journal of Voice, 2017)
OBJECTIVE: The aim of the study was to establish a basic data set of combined functional and anatomical measures of aged sheep larynges using ex vivo models. Combining these two approaches in one and the same larynx is an unmet goal so far yet is important as newer treatment strategies aim to preserve the organ structure and new assessment tools are required. Ovine larynges were used as their dimensions, and muscle fiber type distribution highly resemble the human larynx. STUDY DESIGN: Ex vivo animal study. METHODS: Larynges of six sheep ( 9 years of age) were subjected to ex vivo functional phonatory experiments. Phonatory characteristics were analyzed as a function of longitudinal vocal fold (VF) prestress. Anatomical measurements of the same larynges comprised micro-computed tomography scans followed by three-dimensional (3D) reconstructions. Using specially adapted radiological scan protocols with subsequent 3D reconstruction, muscle volumes, surface areas, and anatomical measurements were computed. RESULTS: Increasing longitudinal prestress yielded higher subglottal pressure (PS) for the same airflow. Quantitative differences to previous studies-such as the increased PSand increased phonation threshold pressure-were detected. We achieved excellent visualization of the laryngeal muscles and framework, resulting in accurate 3D reconstructions for quantitative analysis. We found no significant intraindividual volume differences of the thyroarytenoid muscles. CONCLUSION: The established protocol allows precise functional and anatomical measures. The data created provide a reference data set for upcoming therapeutic strategies (eg, growth factor therapy, functional electrical stimulation) that target essential structures of the VFs such as the laryngeal muscles and/or the VF mucosa.
EVALuna2:33370

Phonation threshold pressure and the properties of the vocal tract - Fulcher, Lewis; Lodermeyer, Alexander; Kniesburges, Stefan; Kähler, George; Döllinger, Michael; Becker, Stefan (Journal of the Acoustical Society of America, 2017)

Phoneme discrimination training with experienced cochlear implant listeners - Schumann, A.; Liebscher, Tim; Hoppe, Ulrich (HNO, 2016)
BACKGROUND: Computer-based auditory training programmes seem to be a useful tool in the process of auditory rehabilitation after cochlear implantation (CI). Currently, little is known about the learning mechanism and efficiency of such programs. The aim of the study was to evaluate a specific auditory training programme for phoneme discrimination in experienced CI listeners. MATERIALS AND METHODS: A total of 15 CI adult listeners with more than 2 years' CI experience participated in the auditory training. Over a period of 3 weeks they were instructed to train their phoneme discrimination via computer twice a week. Training material consisted of special syllables for consonants (vCv) and vowels (cVc) discrimination. RESULTS: The discrimination abilities for consonants and vowels improved significantly over the training period for training group participants, whereas the changes for the consonants were higher. In addition, the improvement for voiced and unvoiced consonants was significant. CONCLUSION: Computerised auditory training with phonemes improves CI listeners' discrimination abilities for consonants and vowels.
EVALuna2:33211

Photoinducible penetration enhancement and drug release for cancer treatment - Cicha, Iwona; Lyer, Stefan; Dürr, Stephan; Schwarz, Marc; Tietze, Rainer; Tripal, Philipp; Alexiou, Christoph (Nanomedicine, 2014)
EVALuna2:19949

Physical parameter estimation from porcine ex vivo vocal fold dynamics in an inverse problem framework - Gómez, Pablo; Schützenberger, Anne; Kniesburges, Stefan; Bohr, Christopher; Döllinger, Michael (Biomechanics and Modeling in Mechanobiology, 2017)
This study presents a framework for a direct comparison of experimental vocal fold dynamics data to a numerical two-mass-model (2MM) by solving the corresponding inverse problem of which parameters lead to similar model behavior. The introduced 2MM features improvements such as a variable stiffness and a modified collision force. A set of physiologically sensible degrees of freedom is presented, and three optimization algorithms are compared on synthetic vocal fold trajectories. Finally, a total of 288 high-speed video recordings of six excised porcine larynges were optimized to validate the proposed framework. Particular focus lay on the subglottal pressure, as the experimental subglottal pressure is directly comparable to the model subglottal pressure. Fundamental frequency, amplitude and objective function values were also investigated. The employed 2MM is able to replicate the behavior of the porcine vocal folds very well. The model trajectories' fundamental frequency matches the one of the experimental trajectories in [Formula: see text] of the recordings. The relative error of the model trajectory amplitudes is on average [Formula: see text]. The experiments feature a mean subglottal pressure of 10.16 (SD [Formula: see text]) [Formula: see text]; in the model, it was on average 7.61 (SD [Formula: see text]) [Formula: see text]. A tendency of the model to underestimate the subglottal pressure is found, but the model is capable of inferring trends in the subglottal pressure. The average absolute error between the subglottal pressure in the model and the experiment is 2.90 (SD [Formula: see text]) [Formula: see text] or [Formula: see text]. A detailed analysis of the factors affecting the accuracy in matching the subglottal pressure is presented.
EVALuna2:33371

Pipette aspiration applied to the characterization of nonhomogeneous, transversely isotropic materials used for vocal fold modeling - Weiß, Sandra; Thomson, S. L.; Lerch, Reinhard; Döllinger, Michael; Sutor, Alexander (Journal of the Mechanical Behavior of Biomedical Materials, 2013)
The etiology and treatment of voice disorders are still not completely understood. Since the vibratory characteristics of vocal folds are strongly influenced by both anatomy and mechanical material properties, measurement methods to analyze the material behavior of vocal fold tissue are required. Due to the limited life time of real tissue in the laboratory, synthetic models are often used to study vocal fold vibrations. In this paper we focus on two topics related to synthetic and real vocal fold materials. First, because certain tissues within the human vocal folds are transversely isotropic, a fabrication process for introducing this characteristic in commonly used vocal fold modeling materials is presented. Second, the pipette aspiration technique is applied to the characterization of these materials. By measuring the displacement profiles of stretched specimens that exhibit varying degrees of transverse isotropy, it is shown that local anisotropy can be quantified using a parameter describing the deviation from an axisymmetric profile. The potential for this technique to characterize homogeneous, anisotropic materials, including soft biological tissues such as those found in the human vocal folds, is supplemented by a computational study. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Vocal fold modeling; Pipette aspiration technique; Material characterization

Pipette aspiration applied to the measurement of anisotropic materials used for vocal fold modeling - Weiß, Sandra; Thomson, Scott; Sutor, Alexander; Bohr, Christopher; Lerch, Reinhard (Proceedings of 8th International Conference on Voice Physiology and Biomechanics (ICVPB) 2012, 2012)

Plasmid-DNA Delivery by Covalently Functionalized PEI-SPIONs as a Potential ‘Magnetofection’ Agent - Stein, René; Pfister, Felix; Friedrich, Bernhard; Blersch, Pascal-Raphael; Unterweger, Harald; Arkhypov, Anton; Mokhir, Andriy; Kolot, Mikhail; Alexiou, Christoph; Tietze, Rainer (Molecules, 2022)
Nanoformulations for delivering nucleotides into cells as vaccinations as well as treatment of various diseases have recently gained great attention. Applying such formulations for a local treatment strategy, e.g., for cancer therapy, is still a challenge, for which improved delivery concepts are needed. Hence, this work focuses on the synthesis of superparamagnetic iron oxide nanoparticles (SPIONs) for a prospective “magnetofection” application. By functionalizing SPIONs with an active catechol ester (CafPFP), polyethyleneimine (PEI) was covalently bound to their surface while preserving the desired nanosized particle properties with a hydrodynamic size of 86 nm. When complexed with plasmid-DNA (pDNA) up to a weight ratio of 2.5% pDNA/Fe, no significant changes in particle properties were observed, while 95% of the added pDNA was strongly bound to the SPION surface. The transfection in A375-M cells for 48 h with low amounts (10 ng) of pDNA, which carried a green fluorescent protein (GFP) sequence, resulted in a transfection efficiency of 3.5%. This value was found to be almost 3× higher compared to Lipofectamine (1.2%) for such low pDNA amounts. The pDNA-SPION system did not show cytotoxic effects on cells for the tested particle concentrations and incubation times. Through the possibility of additional covalent functionalization of the SPION surface as well as the PEI layer, Caf-PEI-SPIONs might be a promising candidate as a magnetofection agent in future.
CRIS-Team Scopus Importer:2022-11-25
Keywords: cytotoxicity; ligand exchange; magnetofection; pentafluorophenyl ester; plasmid-DNA; superparamagnetic iron oxide nanoparticles (SPIONs); surface functionalization; transfection

Pleomorphic adenoma - become more common in women - Iro, Heinrich (HNO, 2018)
EVALuna2:35390

Pleomorphic adenoma compared with cystadenolymphoma of the parotid gland: which is more common? - Mantsopoulos, K.; Iro, Heinrich (British Journal of Oral and Maxillofacial Surgery, 2020)
The aim of this single-institution, observational study was to detect and explain any potential changes in the incidence of pleomorphic adenoma and cystadenolymphoma over a period of 19 years. The records of all patients who were treated for benign parotid tumours between 2000 and 2018 were evaluated and the data analysed to detect any potential changes in the incidence over time. A total of 2988 patients were studied, 1150 of whom had cystadenolymphomas (39%), and 1047 pleomorphic adenomas (35%). The dominance of cystadenolymphomas was first noted during the period 2004–2007 and remained stable throughout the following years (p = 0.05). The predominant incidence of cystadenolymphomas has increased over time and is not expected to change in the next decades.
CRIS-Team Scopus Importer:2020-02-07
Keywords: cystadenolymphoma; parotid gland; pleomorphic adenoma

Pleomorphic adenoma of the parotid gland and the parapharyngeal space: two diametrically opposing surgical philosophies for the same histopathologic entity? - Hornung, Benita; Constantinidis, Jannis; Thimsen, Vivian; Agaimy, Abbas; Koch, Michael; Gostian, Antoniu-Oreste; Sievert, Matti; Müller, Susanna; Iro, Heinrich; Mantsopoulos, Konstantinos (Journal of Clinical Medicine, 2022)
Background: The aim of this study was to investigate the histopathologic findings in parotid and parapharyngeal pleomorphic adenomas and draw conclusions concerning the surgical strategy. Methods: Retrospective study of medical charts of patients with resected pleomorphic adenomas (PA) between 2005 and 2020 at two tertiary medical referral centers. Histologic specimens were reexamined by an experienced head and neck pathologist. Patients with insufficient/incomplete data were excluded from our study sample. Results: A total of 844 patients formed our study sample (291 men, 553 women, average age 48.9 years); 786 cases had a PA in the parotid gland (PG) (93.1%), and the remaining 58 cases had a PA in the parapharyngeal space (PS) (6.9%). Recurrences were detected in 8/844 cases (7/786 in the PG, 1/58 in the PS, 0.94% in total) with a mean follow-up time of 86.7 months (10–189 months) with no statistically significant differences between the study groups (p = 0.527). Our analysis showed that parapharyngeal pleomorphic adenomas are characterized by a lower incidence of an intact anatomical capsule (71.4% vs. 82.6%, p = 0.035) and a remarkably more frequent occurrence of satellite nodules (20.7% vs. 7.5%, p < 0.001). Conclusions: The more challenging histopathologic profile of parapharyngeal pleomorphic adenomas points towards the fact that parapharyngeal surgery should remain in the hands of experienced surgeons at high-volume centers.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Capsule; Parapharyngeal space; Parotid gland; Pleomorphic adenoma; Pseudopodium; Satellite

Pleomorphic liposarcoma of the head and neck: Presentation of two cases and literature review - Agarwal, Jay; Kadakia, Sameep; Agaimy, Abbas; Ogadzanov, Anna; Khorsandi, Azita; Chai, Raymond L. (American Journal of Otolaryngology, 2017)
Pleomorphic liposarcoma (PL) is an exceedingly rare tumor of the head and neck. This aggressive liposarcoma variant portends a poorer prognosis compared to more typical sarcomatous tumors.Multi-institutional study including two cases of PL, the first case occurring in the post-auricular region and the second in the cheek with later recurrence within the parotid bed.Both patients were treated surgically with wide local excision. One patient required reoperation to obtain negative margins. The other patient underwent a total parotidectomy with neck dissection for recurrent intraparotid nodal disease. Both patients underwent adjuvant radiotherapy. No patient had evidence of recurrent disease with minimum one year follow-up.Although the literature is sparse on this disease, wide surgical extirpation with negative margins and adjuvant radiation is recommended. Increased reports of this pathology can be helpful in providing practitioners with experienced-based information that can aid in early detection and treatment. We present the first case series of PL of the head and neck in the literature.
EVALuna2:6855

Pneumoparotid: Practical impact of Surgeon performed Ultrasound in an effective Diagnostic Approach - Goncalves, Miguel; Sievert, Matti; Mantsopoulos, Konstantinos; Schapher, Mirco; Mueller, Sarina K.; Iro, Heinrich; Koch, Michael (Oral Diseases, 2022)
Objectives: Pneumoparotid is characterized by air inclusions in the parotid duct system. Use of ultrasound has proved valuable for evaluating air inclusions in various parts of the body; the diagnostics of this condition has not been systematically analyzed, however. The aim of this study was to evaluate the value of ultrasound in the detection of air inclusions along the parotid duct system and its closer characterization. Methods: Retrospective analysis was carried out of patients diagnosed with pneumoparotid between 2005 and 2020 in a salivary gland center. Ultrasound was performed in all cases, and features of air inclusions were described. Reference standard was the clinical demonstration of foamy saliva after gland massage and/or sialendoscopic evidence of intraductal air inclusions. Results: Twenty-one patients were identified (48.8 ± 3.8 years). Two were associated with wind instruments; seven were iatrogenic, following treatment for duct stenosis; one after radiotherapy; four with known bruxism and seven were idiopathic and without associated conditions. On ultrasound examination, pneumoparotid was characterized by three phenomena: flattened, mobile hyperechoic reflexes, dirty shadows with reverberation or “sunbeam effect,” and shifting shadows during gland massage. Conclusions: Ultrasound was useful for characterizing pneumoparotid in a fast and practical way and could serve as imaging tool of first choice.
CRIS-Team Scopus Importer:2022-07-15
Keywords: diagnostics; parotid gland; pneumoparotid; ultrasound

Polydopamine and gelatin coating for rapid endothelialization of vascular scaffolds - Kopeć, Kamil; Wojasiński, Michał; Eichler, Mathis; Genc, Hatice; Friedrich, Ralf P.; Stein, René; Singh, Raminder; Alexiou, Christoph; Hlawaty, Hanna; Ciach, Tomasz; Cicha, Iwona (Materials Science and Engineering C, 2021)
Rapid endothelialization helps overcome the limitations of small-diameter vascular grafts. To develop biomimetic non-thrombogenic coatings supporting endothelialization, medical-grade polyurethane (PU) nanofibrous mats and tubular scaffolds with a diameter below 6 mm prepared by solution blow spinning were coated with polydopamine (PDA), or PDA and gelatin (PDA/Gel). The scaffolds were characterized by scanning electron microscopy, porosity measurement, tensile testing, wettability, Fourier Transform Infrared spectroscopy, and termogravimetric analysis, followed by the measurement of coating stability on the tubular scaffolds. The effect of coating on scaffold endothelialization and hemocompatibility was evaluated using human umbilical vein endothelial cells (HUVECs) and human platelets, showing low numbers of adhering platelets and significantly higher numbers of HUVECs on PDA- and PDA/Gel-coated mats compared to control samples. Tubular PU scaffolds and commercial ePTFE prostheses coated with PDA or PDA/Gel were colonized with HUVECs using radial magnetic cell seeding. PDA/Gel-coated samples achieved full endothelial coverage within 1–3 days post-endothelialization. Altogether, PDA and PDA/Gel coating significantly enhance the endothelialization on the flat surfaces, tubular small-diameter scaffolds, and commercial vascular prostheses. The presented approach constitutes a fast and efficient method of improving scaffold colonization with endothelial cells, expected to work equally well upon implantation.
CRIS-Team Scopus Importer:2021-12-03
Keywords: Human endothelial cell; Magnetic cell seeding; Polydopamine coating; Polyurethane scaffolds; Tubular grafts

Poresizes in random line networks - Metzner, Claus; Krauß, Patrick; Fabry, Ben (arXiv, 2011)

Positive factors on survival of head and neck cancer of unknown primary: what the clinician can do - Khalil, Firas; Koch, Michael; Iro, Heinrich; Sievert, Matti; Haderlein, Marlen; Semrau, Sabine; Fietkau, Rainer; Agaimy, Abbas; Scherl, Claudia (Acta Oto-Laryngologica, 2023)
Background: Management of patients with head and neck cancer of unknown primary (HNCUP) is challenging. Aims/Objectives: To provide a long-term analysis focusing on protective survival factors for clinical decision-making. Furthermore, the prognostic value of the current N classification system was evaluated. Material and methods: We retrospectively analyzed patients with HNCUP between 2003 and 2016. Univariate and multivariate analyses were used to investigate predictors of overall survival (OS). Results: A primary tumor was found in 67 of 290 patients with suspected HNCUP, leaving after exclusion 141 HNCUP cases for analysis, who received multi-step therapy (MST) (n = 108) or single therapy (n = 28). Chemotherapy (CT) (n = 101), curative MST, ≤3 positive lymph nodes (LN) (n = 33), squamous cell carcinoma (SCC) (n = 123), HPV+ (n = 21), M0 (n = 70) increased OS by 21.8%, 24.4%, 12.7%, 6.8%, 18.7%, 29.6%, respectively. 5- and 10-year OS was 78.1%/66.6%. The number of metastatic LNs predicted OS is better than N classification. Conclusion and significance: Aspects for clinical decision-making: Curative MST and SCC histology were the most significant predictors for improved OS. Categorizing LN into 1, 2-3, and >3 LNs was more significant than the traditional N classification. The addition of CT to curative MST has a stronger impact on survival than HPV and N classifications.
CRIS-Team Scopus Importer:2023-10-27
Keywords: cancer; cancer of unknown primary; CUP; head and neck; hNCUP; hNSCC; squamous cell carcinoma; survival

Postinflammatory Medial Meatal Fibrosis: Histopathologic Features and Outcomes of Surgical Management - Mantsopoulos, Konstantinos; Thimsen, Vivian; Müller-Hübner, Sarina; Sievert, Matti; Goncalves, Miguel; Iro, Heinrich; Agaimy, Abbas; Hornung, Joachim (Ent-Ear Nose & Throat Journal, 2021)
Objectives: The aims of our study were to investigate the clinical and audiometric outcome of the surgical treatment of postinflammatory medial meatal fibrosis (PIMMF) and to review the histopathologic changes in the specimens of the fibrotic plug, in order to try to shed light on the pathogenesis of the disease. Materials and Methods: The clinical records and the histopathologic specimens of all patients who underwent tympanomeatoplasty for PIMMF at the ENT Clinic of the University of Erlangen between 2006 and 2020 were evaluated retrospectively. Results: Thirty-four patients (41 primary surgical procedures) made up our study cohort. Of this, 28 cases were managed by means of meatoplasty and 13 cases with tympanomeatoplasty. The mean preoperative air–bone gap (ABG) was 27.8 dB (10-44 dB). Postoperative ABG was significantly improved compared to preoperative values at both short- and long-term follow-ups (P <.001 for both). No significant difference was noted between short-term and long-term ABG (P =.240). An ABG ≤20 dB was achieved in 65.8% of patients (short term) and 50% (long term). The overall rate of revision surgery for restenosis was 29.3% (12/41). Histopathologic reevaluation of the fibrotic plugs revealed a mosaic of patterns with frequent occurrence of secondary cholesteatoma-like lesions and keloid-like tissue changes. Lichenoid submucosal inflammation and increased ectopic ceruminous gland lobules were seen less frequently. Discussion: The moderate long-term outcome of surgical management and the identification of histologic changes with therapeutic implications might pave the way for alternative nonsurgical treatment options.
CRIS-Team Scopus Importer:2021-04-19
Keywords: air–bone gap; cholesteatoma; keloid; lichen; postinflammatory medial meatal fibrosis

Postlaryngectomy sinonasal squamous cell carcinoma: Case report and review of the literature - Mantsopoulos, Konstantinos; Agaimy, Abbas; Iro, Heinrich; Taha, Lava (Clinical Case Reports, 2020)
Postlaryngectomy sinonasal squamous cell carcinoma, being theoretically associated with exposure to the same risk factors or development of precancerous lesions due to altered nasal physiology, should warrant a thorough head and neck examination.
CRIS-Team WoS Importer:2020-01-21

Postoperative legal disputes involving patients with cochlear implants - Lottner, Anna; Iro, Heinrich; Schützenberger, Anne; Hoppe, Ulrich (HNO, 2018)
BACKGROUND: After the implantation of one or two cochlear implants additional problems often arise concerning the question which further costs have to be covered by statutory insurances or other insurance providers, e.g. within the framework of integration aid. OBJECTIVE: This article provides an overview of judgments rendered by the German social courts. It was investigated whether and in which cases it is advisable for a patient to go to court, and how long the proceedings may take. MATERIAL AND METHODS: A search was made for judgments in the two biggest commercial legal databases and in the database of the German social courts, using combinations of the search parameters "Cochlear", "Cochlea", "Implant", and "Implantat". The reviewed judgments were issued between 2002 and 2017. RESULTS: A total of 13 judgments were found. The results varied according to the specifics of the individual case and 54% of the patients won their cases. The court procedures took between 2 months (starting from the filing of a complaint, date of application in this case unknown), and 6 years and 11 months. CONCLUSION: This study showed that it is uncertain whether costs that are not caused directly by the surgery or the postoperative treatment will be remunerated. As each case is in principle unique, the results vary. Nevertheless, taking legal action is recommended after thorough consideration in cases where statutory insurances or other providers refuse to meet expenses incurred.
EVALuna2:35385

Postoperative management of antithrombotic medication in microvascular head and neck reconstruction: a comparative analysis of unfractionated and low-molecular-weight heparin - Sievert, Matti; Goncalves, Miguel; Tamse, Rosalie; Mueller, Sarina K.; Koch, Michael; Gostian, Antoniu Oreste; Iro, Heinrich; Scherl, Claudia (European Archives of Oto-Rhino-Laryngology, 2020)
Purpose: Free flap reconstruction is a valuable technique to preserve function in oncological head and neck surgery. Postoperative graft thrombosis is a dreaded risk. This study aims to compare low-dose unfractionated heparin (UFH) and low-molecular-weight heparin (LMWH) in perioperative thrombosis prophylaxis. Methods: This is a retrospective analysis of 266 free flaps performed at our academic center. A comparison was made between 2 patient groups, based on their respective postoperative prophylaxis protocols either with UFH (n = 87) or LMWH (n = 179). Primary endpoints were the frequency of transplant thrombosis and the number of flap failures. Secondary endpoints were the occurrence of peri- and postoperative complications. Results: The flap survival rate was 96.6% and 93.3% for the groups UFH and LMWH, respectively (P = 0.280). The rate of postoperative bleeding requiring revision was 4.6% and 6.7% for each group, respectively (P = 0.498). We found a hematoma formation in 4.6% and 3.9% (P = 0.792). Conclusion: The free-flap survival rate using low-dose UFH seems to be equivalent to LMWH regimens without compromising the postoperative outcome. Consequently, for risk-adapted thrombosis prophylaxis, either LMWH or UFH can be administrated.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Antithrombotic agent; Flap failure; Free-flap reconstruction; Head and neck; Thrombosis

Postoperative pain after tonsillectomy – the value of standardized analgesic treatment protocols - Gostian, Antoniu Oreste; Loeser, Johannes; Tholen, Christian; Wolber, Philipp; Otte, Martin; Schwarz, David; Heindl, Ludwig Maximilian; Balk, Matthias; Gostian, Magdalena (Auris Nasus Larynx, 2020)
Objective: To alleviate pain after tonsillectomy (TE) with escalating gradual treatment protocols in a prospective trial. Materials & Methods: Following TE, 83 consecutive adult patients were treated with two different four-staged escalating analgesic protocols. Metamizole served as basic medication in protocol 1 (PT1; n = 44), whereas with protocol 2 (PT2; n = 39) ibuprofen was applied as baseline analgesic. Both protocols were escalated according to the patient´s needs to metamizole and ibuprofen vice versa and additional weak to strong opioids. The primary efficacy endpoint was defined as the minimum and maximum pain as well as pain on ambulation (NRS, 0–10). Secondary endpoints comprised analgesic score, patient satisfaction and treatment-related side-effects. Results: Both patient groups exhibited similar demographic characteristics (PT1: Ø 28.8 years; 64% ♀ and PT2: Ø 26.6 years; 56% ♀). Maximum pain (6.7 ± 1.9 vs. 7.6 ± 1.6, t(81) = −2.254, p = 0.027) and pain on ambulation (5.0 ± 1.8 vs. 5.8 ± 1.8, t(81) = -2.114, p = 0.038) were significantly higher with PT2. 68.2% of patients with PT1 needed an escalation of analgesic treatment compared to 100% with PT2 (p < 0.001). The opioid consumption was also significantly higher with PT2 (43.2% vs. 71.8%, p < 0.001). There were no significant differences regarding functional impairments, side-effects and patient satisfaction (7.0 ± 2.0 vs. 7.4 ± 2.4, t(79) = −0.897, p = 0.373). Conclusion: Both treatment protocols yielded in a high degree of patient satisfaction but dissatisfactory pain relief following TE. Metamizole can be recommended as a basic medication allowing for improved pain relief. Reported pain intensities were independent of the amount of opioid intake. Further research is mandatory to standardize and improve analgesic treatment after TE.
CRIS-Team Scopus Importer:2020-06-23
Keywords: Non-opioid; Opioid; Pain therapy; Postoperative pain; Quality management; QUIPS; Tonsillectomy

Postoperative pain following Descemet membrane endothelial keratoplasty (DMEK): a prospective study - Loeser, Johannes; Schwemmer, Julian; Gostian, Antoniu Oreste; Gostian, Magdalena; Bachmann, Björn; Cursiefen, Claus; Heindl, Ludwig M. (Graefes Archive For Clinical and Experimental Ophthalmology, 2019)
Purpose: To evaluate postoperative pain following Descemet membrane endothelial keratoplasty (DMEK). Methods: Seventy-one patients completed perioperatively (day before surgery, day of surgery, 1st, 2nd, and 3rd day after surgery) four different questionnaires (a hospital internal protocol, QUIPS, PainDETECT®, and SF36) regarding their pain and other clinical parameters such as constipation, tiredness, vertigo, sleep disorders, concentration disorders, nausea, and emesis. All standardised questionnaires were evaluated to quantify average pain intensity as well as maximum pain intensity (NRS, 0 [no pain] to 10 [maximal pain], respectively). Analgesic treatment and intraocular pressure (IOP) during the perioperative stay were documented. Results: Mean average pain intensity was 0.70 ± 1.64 before surgery, 1.97 ± 2.05 on the day of surgery, 1.39 ± 1.68 on day 1, 0.87 ± 1.36 on day 2, and 0.81 ± 1.24 on day 3 after surgery. Maximum pain intensity was 0.65 ± 1.81 before surgery, 3.35 ± 2.98 on the day of surgery, 2.68 ± 2.99 on day 1, 1.49 ± 2.15 on day 2, and 1.26 ± 2.02 on day 3 after surgery. During the first three postoperative days, over 90% of the patients stated no or well tolerable pain. Eighty-three percent had postoperatively no need for analgesics at all. On the first two postoperative days, maximum IOP correlated significantly with reported increased maximum pain intensity (p = 0.043 and p = 0.029, respectively). All patients had very little problems with constipation, tiredness, vertigo, sleep disorder, concentration disorders, nausea, and emesis. Conclusions: DMEK is associated with low postoperative pain intensity. Strong pain increase may indicate IOP elevation and should be further investigated and treated. Clinical trial registration: German Clinical Trial Register (DRKS00013995).
CRIS-Team Scopus Importer:2019-08-16
Keywords: Cornea; Descemet membrane endothelial keratoplasty (DMEK); Keratoplasty; Pain; Quality management; Transplantation

Postoperative Pain Treatment with Continuous Local Anesthetic Wound Infusion in Patients with Head and Neck Cancer: A Nonrandomized Clinical Trial - Gostian, Magdalena; Loeser, Johannes; Albert, Carola; Wolber, Philipp; Schwarz, David; Grosheva, Maria; Veith, Stephanie; Goerg, Christoph; Balk, Matthias; Gostian, Antoniu Oreste (JAMA Otolaryngology - Head and Neck Surgery, 2021)
Importance: Up to 80% of patients with head and neck cancer undergoing ablative surgery and neck dissection develop postoperative pain with detrimental effects on quality of life that also contributes to neuropathic and chronic postoperative pain. Objective: To investigate the association of continuous local anesthetic wound infusion with pain management after head and neck surgery. Design, Setting, and Participants: This prospective, longitudinal, nonrandomized clinical study carried out in a single tertiary referral center (December 1, 2015, to July 1, 2017) included 2 groups of 30 patients. Patients were consecutively enrolled and presented for ablative head and neck surgery including selective neck dissection and studied from the preoperative through the fourth postoperative day. Interventions: The control group was treated according to a standardized escalating oral treatment protocol (ibuprofen, metamizole, opioids). The intervention group was treated with an intraoperatively applied pain catheter (InfiltraLong plus FuserPump, Pajunk, ropivacaine, 0.2%, 3 mL/h) that was removed 72 hours after operating. Main Outcomes and Measures: Average and maximum pain intensities on a numeric rating scale; quality of life using the acute version of the validated 36-Item Short Form Survey; and neuropathic pain using the validated 12-Item painDETECT questionnaire. Consumption of opioid and nonopioid analgesics and evaluation of catheter-associated complications. Results: During postoperative days 1 through 4, patients of the intervention group (mean [SD] age, 63.2 [13.3 years; 9 [30%] women) experienced lower mean (SD) (1.6 [1.4] vs 2.7 [1.8]; η2p= 0.09 [0.01-0.21]) and maximum (2.4 [2.2] vs 4.2 [2.0]; η2p= 0.11 [0.01-0.24]) pain intensities compared with the control group (mean [SD] age, 62.5 [13.6] years; 5 [17%] women). The intervention group also reported less neuropathic pain (mean [SD], 5.4 [3.4] vs 7.6 [5.1]; η2p= 0.09 [0.004 - 0.22]) and higher quality of life regarding vitality (56.2 [21.5] vs 43.8 [20.9], r = 0.29; 95% CI, 0.01-0.52) and pain (66.8 [27.3] vs 49.5 [27.7], r = 0.31; 95% CI, 0.04-0.54). Patients from the intervention group requested nonopioid analgesics considerably less often (n = 17 [57%] vs n = 29 [97%]; φ = 0.47; 95% CI, 0.30-0.67) associated with a noticeably lower need to escalate pain treatment (n = 3 [10%] vs n = 9 [30%]; mean [SD] ibuprofen dose: 500 [173] mg vs 1133 [650] mg; r = 0.64; 95% CI, 0.02-0.91). No catheter-associated complications were observed. Conclusions and Relevance: Continuous anesthetic wound infusion is associated with reduced postoperative pain and decreased demand for analgesics. It therefore expands the treatment options for postoperative pain in head and neck cancer. Trial Registration: German Clinical Trials Register: DRKS00009378.
CRIS-Team Scopus Importer:2021-04-19

Precautionary documents in patients with head and neck cancer - status quo and factors influencing their creation - Allner, Moritz; Gostian, M.; Balk, Matthias; Rupp, Robin; Hecht, Markus; Ostgathe, Christoph; Mueller, Sarina K.; Iro, Heinrich; Gostian, Antoniu-Oreste (ORAL ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-07-16

Predicting Hearing Aid Fittings Based on Audiometric and Subject-Related Data: A Machine Learning Approach - Seifer, Ann-Kristin; Schinkel-Bielefeld, Nadja; Schröter, Hendrik; Escalante Banuelos, Alberto; Hoppe, Ulrich; Maier, Andreas (Virtual Conference on Computational Audiology (VCCA2020), 2020)
Hearing aids (HA) are configured to the wearer’s individual needs, which might vary greatly from user to user. Currently, it is common practice, that the initial HA gain settings are based on generic fitting formulas that link a user’s pure-tone hearing threshold to amplification characteristics. Subsequently, a time-consuming fine-tuning process follows, in which a hearing care professional (HCP) adjusts the HA settings to the user’s individual demands. An advanced, more personalized gain prescription procedure could support HCPs by reducing fine-tuning effort and facilitate over-the-counter HAs. We propose a machine learning based prediction for HA gain to minimize subsequent fine-tuning effort. The data-driven approach takes audiometic and personal variables into account, such as age, gender, and the user’s acoustical environment. A random forest regression model was trained on real-world HA fittings from the Connexx database (fitting software provided by Sivantos GmbH). Three months of data from Connexx version 9.1.0.364 were used. A data cleaning framework was implemented to extract a representative data set based on a list of machine learning and audiological criteria. These criteria include, for instance, using only ‘informative’ HCPs who perform fine-tuning for at least some patients. Furthermore, ‘informative’ HCPs are those who perform diagnostics beyond air conduction audiograms, use new technologies and special features. The resulting training data comprised 20,000 HA fittings and a 10-fold cross validation was used to train the random forest.
Keywords: Hearing Aids; Machine Learning

Prediction of Hearing Preservation in Vestibular Schwannoma Surgery According to Tumor Size and Anatomic Extension - Bozhkov, Yavor; Shawarba, Julia; Feulner, Julian; Winter, Fabian; Rampp, Stefan; Hoppe, Ulrich; Dörfler, Arnd; Iro, Heinrich; Buchfelder, Michael; Rössler, Karl (Otolaryngology-Head and Neck Surgery, 2021)
Objective: Vestibular schwannoma (VS) surgery is feasible for various tumor sizes that are inappropriate for wait and scan or radiosurgery. The predictive value of 2 grading systems was investigated for postoperative hearing preservation (HP) in a large series. Study Design: Retrospective analysis. Setting: Neurosurgical patient database of the University of Erlangen was queried between 2014 and 2017. Methods: Retrospective single-center analysis on 138 VSs operated on via a retrosigmoidal approach. The mean tumor size was 20.4 mm (SD, 7.6 mm) with fundal infiltration in 67.4%. The overall resection rate was 93.5%. Tumors were classified preoperatively by the 3-tier Erlangen grading system depending on size or the anatomically based 4-tier Koos grading system. Results: Preoperative hearing preservation was found in 70.3% of patients and was significantly correlated to tumor size (P =.001). For Erlangen grading, a mean postoperative serviceable hearing preservation rate of 32% was achieved: 83.3% for tumors <12 mm, 30.3% for tumors between 12 and 25 mm, and 5.3% for tumors >25 mm. In contrast, according to Koos grading, postoperative serviceable hearing preservation was 100% for grade 1 tumors (meatal), 35.6% for grade 2 (cisternal), 23.1% for grade 3 (brainstem contact), and 21.7% for grade 4 (brainstem compression). Of the total cohort, 86% had normal or nearly normal postoperative facial function (House-Brackmann grades 1 and 2). Conclusion: Surgery on small VSs can achieve excellent hearing preservation. Different grading has a significant influence on and correlates with postoperative hearing preservation. Tumor size seems more important than anatomic relationship.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Erlangen vestibula schwannoma grading; grading systems; hearing preservation; Koos vestibular schwannoma grading; vestibular schwannoma surgery

Prediction of Speech Intelligibility by Means of EEG Responses to Sentences in Noise - Muncke, Jan; Kuruvila, Ivine; Hoppe, Ulrich (Frontiers in Neuroscience, 2022)
ObjectiveUnderstanding speech in noisy conditions is challenging even for people with mild hearing loss, and intelligibility for an individual person is usually evaluated by using several subjective test methods. In the last few years, a method has been developed to determine a temporal response function (TRF) between speech envelope and simultaneous electroencephalographic (EEG) measurements. By using this TRF it is possible to predict the EEG signal for any speech signal. Recent studies have suggested that the accuracy of this prediction varies with the level of noise added to the speech signal and can predict objectively the individual speech intelligibility. Here we assess the variations of the TRF itself when it is calculated for measurements with different signal-to-noise ratios and apply these variations to predict speech intelligibility. MethodsFor 18 normal hearing subjects the individual threshold of 50% speech intelligibility was determined by using a speech in noise test. Additionally, subjects listened passively to speech material of the speech in noise test at different signal-to-noise ratios close to individual threshold of 50% speech intelligibility while an EEG was recorded. Afterwards the shape of TRFs for each signal-to-noise ratio and subject were compared with the derived intelligibility. ResultsThe strongest effect of variations in stimulus signal-to-noise ratio on the TRF shape occurred close to 100 ms after the stimulus presentation, and was located in the left central scalp region. The investigated variations in TRF morphology showed a strong correlation with speech intelligibility, and we were able to predict the individual threshold of 50% speech intelligibility with a mean deviation of less then 1.5 dB. ConclusionThe intelligibility of speech in noise can be predicted by analyzing the shape of the TRF derived from different stimulus signal-to-noise ratios. Because TRFs are interpretable, in a manner similar to auditory evoked potentials, this method offers new options for clinical diagnostics.
CRIS-Team WoS Importer:2022-07-01

Predictive coding and stochastic resonance as fundamental principles of auditory phantom perception - Schilling, Achim; Sedley, William; Gerum, Richard C.; Metzner, Claus; Tziridis, Konstantin; Maier, Andreas; Schulze, Holger; Zeng, Fan Gang; Friston, Karl J.; Krauß, Patrick (Brain, 2023)
Mechanistic insight is achieved only when experiments are employed to test formal or computational models. Furthermore, in analogy to lesion studies, phantom perception may serve as a vehicle to understand the fundamental processing principles underlying healthy auditory perception. With a special focus on tinnitus-as the prime example of auditory phantom perception-we review recent work at the intersection of artificial intelligence, psychology and neuroscience. In particular, we discuss why everyone with tinnitus suffers from (at least hidden) hearing loss, but not everyone with hearing loss suffers from tinnitus. We argue that intrinsic neural noise is generated and amplified along the auditory pathway as a compensatory mechanism to restore normal hearing based on adaptive stochastic resonance. The neural noise increase can then be misinterpreted as auditory input and perceived as tinnitus. This mechanism can be formalized in the Bayesian brain framework, where the percept (posterior) assimilates a prior prediction (brain's expectations) and likelihood (bottom-up neural signal). A higher mean and lower variance (i.e. enhanced precision) of the likelihood shifts the posterior, evincing a misinterpretation of sensory evidence, which may be further confounded by plastic changes in the brain that underwrite prior predictions. Hence, two fundamental processing principles provide the most explanatory power for the emergence of auditory phantom perceptions: predictive coding as a top-down and adaptive stochastic resonance as a complementary bottom-up mechanism. We conclude that both principles also play a crucial role in healthy auditory perception. Finally, in the context of neuroscience-inspired artificial intelligence, both processing principles may serve to improve contemporary machine learning techniques.
CRIS-Team Scopus Importer:2023-12-15
Keywords: artificial intelligence; Bayesian brain; phantom perception; predictive coding; stochastic resonance; tinnitus

Predictive factors for abscessing tonsillitis: a retrospective analysis - Sievert, Matti; Miksch, M.; Hinken, N.; Mantsoupoulos, K.; Gostian, A. O.; Thimsen, V.; Mueller, S. K.; Balk, M.; Rupp, R.; Iro, H.; Koch, M. (European Review for Medical and Pharmacological Sciences, 2023)
OBJECTIVE: In clinical practice, identifying abscesses in tonsillar infections is crucial for early therapeutic management. Diagnosis of a peritonsillar abscess is usually based on clinical symptoms. Complementary examination procedures, such as laboratory parameters and imaging, are available for confirmation. PATIENTS AND METHODS: A retrospective analysis was carried out of data for 752 patients who presented with acute tonsillar infection and were hospitalized between January 2012 and February 2021. The data analyses involved evaluating the patient's clinical symptoms, inflammatory parameters, and previous medical history in relation to the predictive power of these factors for the presence of an abscess. RESULTS: Predictor analysis for the presence of an abscess showed significant values for trismus (OR 2.392; 95% CI, 1.305 to 4.383; p=0.005) and palatal arch protrusion (OR 29.679; 95% CI, 17.460 to 50.447; p=0.000). The inflammatory parameter C-reactive protein and the leukocyte count were not statistically significant as predictors. CONCLUSIONS: The presence of a tonsillar abscess can be diagnosed from the clinical presentation alone if the findings are clear. Further diagnostic procedures are indicated in case of inconclusive findings, and ultrasound should be the primary noninvasive method. Computed tomography is only required in selected cases. Inflammatory parameters can be assessed in order to monitor therapy, but do not predict the presence of an abscess. However, if defined action sequences are being considered, tonsillar abscesses can be differentiated at an early point.
CRIS-Team Scopus Importer:2023-12-01

Predictive value of FHIT, p27, and pERK1/ERK2 in salivary gland carcinomas: a retrospective study - Fiedler, Mathias; Renner, Patty; Schubert, Juergen; Weber, Florian; Hartmann, Arndt; Iro, Heinrich; Vielsmeier, Veronika; Bohr, Christopher; Gerken, Michael; Reichert, Torsten E.; Ettl, Tobias (Clinical Oral Investigations, 2019)
Objectives: The aim of this study was to investigate the predictive value of the biomarkers FHIT, p27, and pERK1/ERK2 in salivary gland carcinomas. Material and methods: Immunohistochemical staining of FHIT, p27, and pERK1/ERK2 of 265 patients with salivary gland carcinomas was conducted, and associations with clinico-histopathological data, overall survival, and disease-specific survival were examined. Results: Expression of FHIT (quick score 98.7 vs. 206.4) and p27 (QS 187.3 vs. 244.8) was significantly lower in carcinomas compared to non-tumor control tissue. Loss of FHIT frequently occurred in ACC (55.2%), SDC (68.2%), and SCC (100%). In the totality of tumors, loss of FHIT expression was found in 46.7% (106/227) and was significantly associated with advanced T stage and UICC stage, high-grade histology, loss of p27, PI3K, and survivin. FHIT positivity went along with significantly better overall and disease-specific survival. Negativity of p27 occurred in 28.7% (70/244) of tumors, particularly in SDC (54.4%) and SCC (50%). In the totality of tumors, p27 was associated with advanced patient age, high-grade histology, PI3K, survivin as well as better overall and disease-specific survival (p < 0.05). Positive pERK1/ERK2 expression correlated with positive survivin expression but did not affect overall survival in the totality of tumors. In mucoepidermoid carcinomas, pERK1/ERK2 expression was associated with low-grade malignancy, positive nuclear survivin, and better disease-specific survival. Conclusions: Loss of FHIT and p27 characterizes aggressive tumor growth and unfavorable prognosis in salivary gland cancer. Clinical relevance: The results may help to stratify patient-specific therapies according to individual tumor characteristics.
CRIS-Team Scopus Importer:2019-10-25
Keywords: FHIT; p27; pERK1/ERK2; Salivary gland carcinoma

Predictive Value of Multiparametric MRI for Response to Single-Cycle Induction Chemo-Immunotherapy in Locally Advanced Head and Neck Squamous Cell Carcinoma - Hellwig, Konstantin; Ellmann, Stephan; Eckstein, Markus; Wiesmüller, Marco; Rutzner, Sandra; Semrau, Sabine; Frey, Benjamin; Gaipl, Udo; Hartmann, Arndt; Iro, Heinrich; Fietkau, Rainer; Uder, Michael; et al. (Frontiers in Oncology, 2021)
Objectives
CRIS-Team WoS Importer:2021-11-19

Predictors of cervical lymph node metastasis in salivary gland cancer - Ettl, Tobias; Gosau, Martin; Brockhoff, Gero; Schwarz-Furlan, Stephan; Agaimy, Abbas; Reichert, Torsten E.; Rohrmeier, Christian; Zenk, Johannes; Iro, Heinrich (Head and Neck-Journal For the Sciences and Specialties of the Head and Neck, 2014)
This study compares clinicopathological parameters with novel molecular markers for predicting cervical lymph node metastasis in salivary gland cancer.Three hundred sixteen salivary gland carcinomas were included in this study. Genomic epidermal growth factor receptor (EGFR), human epidermal growth factor receptor 2 (HER2), phosphatase and tensin homolog (PTEN), and hepatocyte growth factor receptor (MET) was determined by fluorescence in situ hybridization (FISH). Chi-square tests, multivariate regression, and Kaplan-Meier survival analysis were used for statistics.Nodal staging determines long-term survival. Clinicopathological parameters associated with positive neck nodes are advanced age (p = .006), T3/T4 classification, histological high-grade malignancy, and diagnosis of salivary duct carcinoma (p < .001 each). Neck node metastases also correlate with copy number gain of EGFR (p = .004) and HER2, aberration of MET, and deletion of PTEN (p < .001 each). Multivariate analysis showed SDC (p = .002) to be the strongest predictor of lymph node metastasis, followed by MET aberration (p = .009), T3/T4 classification (p = .017), PTEN deletion (p = .042), and adenocarcinoma not otherwise specified (NOS; p = .047).The histological subtype is crucial for decisions regarding neck dissection. New molecular parameters may also indicate elective treatment of the neck.
EVALuna2:6596

Predictors of olfactory improvement after endoscopic sinus surgery in chronic rhinosinusitis with nasal polyps - Hernandez, A. K.; Wendler, Olaf; Mayr, Susanne; Iro, Heinrich; Hummel, T.; Mueller, Sarina K. (Journal of Laryngology and Otology, 2022)
Objective. This study aimed to determine the predictors of olfactory improvement after endoscopic sinus surgery among patients with chronic rhinosinusitis with nasal polyps.
CRIS-Team WoS Importer:2023-04-21

Preface: Recent Advances in Understanding the Human Phonatory Process - Döllinger, Michael; Kaltenbacher, M. (Acta Acustica United With Acustica, 2016)
Human phonation is a complex interaction of fluid mechanics, solid mechanics and acoustics. The air flow forces the vocal folds to vibrate which in turn create a pulsating air stream. Based on aeroacoustic principles, the sound is generated by the pulsating air jet and supraglottal turbulent structures. Fundamental knowledge and understanding of the processes and Mechanisms which lead to healthy voice production is thus important and may have extensive applications, e.g., for the development of voice prostheses for patients after total laryngectomy, training of voice professionals, pre-surgical predictions of voice quality, development of examination and therapeutic devices, etc. Despite all efforts to date, the full details of the aeroacoustic sound production mechanisms in the human larynx are still not entirely understood. The DFG interdisciplinary group FOR894, funded for six years, involved different scientific knowledge from laryngology, applied mathematics, sensor technology, and fluid dynamics. Due to the involved different scientific expertise, synergy effects evolved that yielded new innovative approaches and results that would have not been possible in standalone projects. Thereby, three new complementary numerical models and three physical models were developed focusing on different aspects in the phonatory process. This article will provide a detailed description of the state-of-art knowledge towards a clearer understanding of the human phonation process, will summarize the main outcome of six years interdisciplinary research,. and will discuss the obtained results in the context of recent advances of other research groups.
EVALuna2:33164

Preliminary results on the influence of engineered artificial mucus layer on phonation - Döllinger, Michael; Gröhn, Franziska; Berry, David A.; Eysholdt, Ulrich; Luegmair, Georg (Journal of Speech Language and Hearing Research, 2014)
PURPOSE Previous studies have confirmed the influence of dehydration and an altered mucus (e.g., due to pathologies) on phonation. However, the underlying reasons for these influences are not fully understood. This study was a preliminary inquiry into the influences of mucus architecture and concentration on vocal fold oscillation. METHOD Two excised human larynges were investigated in an in vitro setup. The oscillations of the vocal folds at various airflow volume rates were recorded through the use of high-speed imaging. Engineered mucus containing polymers (interconnected polymers and linear polymers) was applied to the vocal folds. From the high-speed footage, glottal parameters were extracted through the use of objective methods and were compared to a gold standard (physiological saline solution). RESULTS Variations were found for all applications of mucus. Fundamental frequency dropped and the oscillatory behavior (speed quotient [SQ], closing quotient [CQ]) changed for both larynges. The 2 applied mucus architectures displayed different effects on the larynges. The interconnected polymer displayed clear low-pass filter characteristics not found for the linear polymer. Increase of polymer concentration affected parameters to a certain point. CONCLUSION The data confirm results found in previous studies. Furthermore, the different effects-comparing architecture and concentration-suggest that, in the future, synthetic mucus can be designed to improve phonation.
EVALuna2:20187

Preliminary Studies and Prototypes for Machine Learning Based Evaluation of Surfers’ Performance on River Waves - Zöllner, Michael; Kniesburges, Stefan; Döllinger, Michael; Gemeinhardt, Jan; Krause, Moritz (HCI International 2023 – Late Breaking Posters. HCII 2023, 2023)
In this paper we are describing our preliminary studies and prototypes for evaluating a surfer’s performance on a stationary wave. We are briefly describing the sport’s environment and development and the current state-of-the-art of machine learning based single camera tracking approaches we have evaluated and applied. The main part of the paper deals with the first implementation, the tracking and the results of the evaluation of the movements of two surfers. We are closing with our lessons learned and our next steps.
CRIS-Team Scopus Importer:2024-01-05
Keywords: Data Visualization; Interactive Systems; Machine Learning

Prenatal and adult androgen activities in alcohol dependence - Lenz, Bernd; Mühle, Christiane; Braun, B.; Weinland, C.; Bouna-Pyrrou, Polyxeni; Behrens, Juliane; Kubis, S.; Mikolaiczik, Katrin; Muschler, M. -R.; Saigali, Sarah; Sibach, M.; Tanovska, P.; et al. (Acta Psychiatrica Scandinavica, 2017)
OBJECTIVE: Alcohol dependence is more prevalent in men than in women. The evidence for how prenatal and adult androgens influence alcohol dependence is limited. We investigated the effects of prenatal and adult androgen activity on alcohol dependence. Moreover, we studied how the behaviours of pregnant women affect their children's prenatal androgen load. METHOD: We quantified prenatal androgen markers (e.g., second-to-fourth finger length ratio [2D : 4D]) and blood androgens in 200 early-abstinent alcohol-dependent in-patients and 240 controls (2013-2015, including a 12-month follow-up). We also surveyed 134 women during pregnancy (2005-2007) and measured the 2D : 4D of their children (2013-2016). RESULTS: The prenatal androgen loads were higher in the male alcohol-dependent patients compared to the controls (lower 2D : 4D, P = 0.004) and correlated positively with the patients' liver transaminase activities (P < 0.001) and alcohol withdrawal severity (P = 0.019). Higher prenatal androgen loads and increasing androgen levels during withdrawal predicted earlier and more frequent 12-month hospital readmission in alcohol-dependent patients (P < 0.005). Moreover, stress levels (P = 0.002), alcohol (P = 0.010) and tobacco consumption (P = 0.017), and lifetime stressors (P = 0.019) of women during pregnancy related positively to their children's prenatal androgen loads (lower 2D : 4D). CONCLUSION: Androgen activities in alcohol-dependent patients and behaviours of pregnant women represent novel preventive and therapeutic targets of alcohol dependence.
EVALuna2:33408

Pressure-driven collective growth mechanism of planar cell colonies. - Metzner, Claus; Lange, Janina; Krauß, Patrick; Wunderling, Nico; Übelacker, Julian; Martin, Florian; Fabry, Ben (Journal of Physics D-Applied Physics, 2018)

Pressure-driven collective growth mechanism of planar cell colonies. - Metzner, Claus; Lange, Janina; Krauß, Patrick; Wunderling, Nico; Übelacker, Julian; Martin, Florian; Fabry, Ben (Journal of Physics D: Applied Physics, 2018)
The growth of cell colonies is determined by the migration and proliferation of the individual cells. This is often modeled with the Fisher-Kolmogorov (FK) equation, which assumes that cells diffuse independently from each other, but stop to proliferate when their density reaches a critial limit. However, when using measured, cell-line specific parameters, we find that the FK equation drastically underestimates the experimentally observed increase of colony radius with time. Moreover, cells in real colonies migrate radially outward with superdiffusive trajectories, in contrast to the assumption of random diffusion. We demonstrate that both dicrepancies can be resolved by assuming that cells in dense colonies are driven apart by repulsive, pressure-like forces. Using this model of proliferating repelling particles (PRP), we find that colony growth exhibits different dynamical regimes, depending on the ratio between a pressure-related equilibrium cell density and the critial density of proliferation arrest.
EVALuna2:210450

Prevalence of Mental Distress Among Syrian Refugees With Residence Permission in Germany: A Registry-Based Study. - Georgiadou, Ekaterini; Zbidat, Ali; Schmitt, Gregor M.; Erim, Yesim (Frontiers in Psychiatry, 2018)
Background: High rates of prevalence of mental distress among the Syrian refugee population have been repeatedly confirmed. However, little is known about the influence of length of stay, living conditions, and residence permission in the host country or about the duration of the escape journey and travel conditions on mental health in this refugee population. This study examines the mental health of Syrian refugees, taking into account the circumstances in their country of origin and host country, as well as their escape conditions. Methods: This investigation formed part of a registry-based study. A sample of 518 adult Syrian refugees in Erlangen, Germany, who have residence permission was identified. The response rate was 38.6%; a total of 200 Syrian refugees thus participated in the study. The respondents were investigated for post-traumatic stress disorder (ETI), depression (PHQ-9), generalized anxiety (GAD-7) and post-migration variables. Results: The prevalence of participants who had personally experienced and/or witnessed traumatic events was 75.3%. Symptoms of PTSD were found in 11.4% of the participants. Moderate to severe depression was confirmed in 14.5% and moderate to severe generalized anxiety in 13.5% of the sample. The criteria for at least one diagnosis were met by 30.5% of the participants. More severe PTSD symptoms were associated with older age, shorter validity of the residence permit, larger number of traumatic events (TEs) and higher generalized anxiety symptoms. Depression symptoms were associated with younger age, shorter duration of escape journey, larger number of TEs and higher generalized anxiety symptoms. Generalized anxiety symptoms correlated with female gender, PTSD, and depression symptoms. Conclusions: These findings suggest that Syrian refugees in Germany are a vulnerable population, especially if they have experienced and/or witnessed multiple traumatic events. However, post-migration conditions and positive future prospects in the host country can be protective factors for this population.
EVALuna2:214429

Preventive Effects of Ginkgo-Extract EGb 761® on Noise Trauma-Induced Cochlear Synaptopathy - Tziridis, Konstantin; Schulze, Holger (Nutrients, 2022)
Noise trauma-induced loss of ribbon synapses at the inner hair cells (IHC) of the cochlea may lead to hearing loss (HL), resulting in tinnitus. We are convinced that a successful and sustainable therapy of tinnitus has to treat both symptom and cause. One of these causes may be the mentioned loss of ribbon synapses at the IHC of the cochlea. In this study, we investigated the possible preventive and curative effects of the Ginkgo biloba extract EGb 761® on noise-induced synaptopathy, HL, and tinnitus development in Mongolian gerbils (Meriones unguiculatus). To this end, 37 male animals received EGb 761® or placebo orally 3 weeks before (16 animals) or after (21 animals) a monaural acoustic noise trauma (2 kHz, 115 dB SPL, 75 min). Animals' hearing thresholds were determined by auditory brainstem response (ABR) audiometry. A possible tinnitus percept was assessed by the gap prepulse inhibition acoustic startle reflex (GPIAS) response paradigm. Synaptopathy was quantified by cochlear immunofluorescence histology, counting the ribbon synapses of 15 IHCs at 11 different cochlear frequency locations per ear. We found a clear preventive effect of EGb 761® on ribbon synapse numbers with the surprising result of a significant increase in synaptic innervation on the trauma side relative to placebo-treated animals. Consequently, animals treated with EGb 761® before noise trauma did not develop a significant HL and were also less affected by tinnitus compared to placebo-treated animals. On the other hand, we did not see a curative effect (EGb 761® treatment after noise trauma) of the extract on ribbon synapse numbers and, consequently, a significant HL and no difference in tinnitus development compared to the placebo-treated animals. Taken together, EGb 761® prevented noise-induced HL and tinnitus by protecting from noise trauma-induced cochlear ribbon synapse loss; however, in our model, it did not restore lost ribbon synapses.
CRIS-Team Scopus Importer:2022-08-12
Keywords: auditory brainstem response; gap prepulse inhibition of the acoustic startle response; hearing loss; immunohistology; pharmacological treatment; rodents; synaptopathy; tinnitus

Primary and Secondary/ Metastatic Salivary Duct Carcinoma Presenting within the Sinonasal Tract - Agaimy, Abbas; Mueller, Sarina K.; Bishop, Justin A.; Chiosea, Simion I. (Head and Neck Pathology, 2021)
Traditionally, sinonasal adenocarcinomas have been subdivided into intestinal (ITAC) and non-intestinal (non-ITAC) categories. The latter encompasses salivary-type adenocarcinomas originating from the seromucinous glands of the sinonasal mucosa and non-salivary adenocarcinomas. The non-salivary adenocarcinoma category is further subdivided into low-and high-grade variants. Among salivary-type sinonasal adenocarcinomas, tumors recapitulating salivary duct carcinoma (SDC) are exceedingly rare, but some might have been lumped into the high-grade non-ITAC category. To date, only three primary SDCs originating in the sinonasal tract have been reported. We herein describe 7 cases of SDC including one previously reported case (4 primary sinonasal, 3 metastatic/ extension from parotid gland SDC). The primary tumors affected 3 males and one female aged 60 – 75. Different sites were involved by the primary tumors while the secondary tumors affected the sphenoidal (2) and the frontal + maxillary (1) sinuses. Three primary tumors were de novo high-grade SDC and one was confined to contours of a pre-existing pleomorphic adenoma. All 3 secondary tumors were SDC ex pleomorphic adenoma of the parotid with a long history of recurrences, ultimately involving the sinonasal tract. Androgen receptor was positive in 7/7 cases. Four of 6 cases were strongly HER2/neu + (either score 3 + or with verified amplification). This small case series adds to the delineation of primary sinonasal SDC highlighting that almost half of invasive SDC presenting within sinonasal tract indeed represents extension or metastasis from a parotid gland primary. There is a tendency towards overrepresentation of HER2/neu-positive cases in both categories (primary and metastatic), but this needs clarification in larger studies.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Carcinoma ex pleomorphic adenoma; Ductal adenocarcinoma; HER2/neu; Non-intestinal adenocarcinoma; Salivary duct carcinoma; Sinonasal tract

Primary parotid gland lymphoma: pitfalls in the use of ultrasound imaging by a great pretender - Mantsopoulos, Konstantinos; Koch, M.; Fauck, Vanessa; Schinz, Katharina; Schapher, Mirco; Constantinidis, J.; Rösler, Wolf; Iro, Heinrich (International journal of oral and maxillofacial surgery, 2020)
The aim of this study was to highlight several misleading imaging and clinical aspects of parotid gland lymphoma, taking our personal experience and relevant literature reports into consideration. The records of all patients diagnosed with lymphoma in the parotid gland between 2005 and 2017 were examined retrospectively. Sixty-seven patients were included in this study. The mean age was 61.4 years. The most frequent histological entities were marginal zone B-cell lymphoma (31.3%) and follicular lymphoma (28.4%). The tumour was stage I in 35 cases (52.2%), stage II in 13 cases (19.4%), stage III in 11 cases (16.4%), and stage IV in eight cases (11.9%). B symptoms were seen in only three patients (4.5%). The diagnosis was made after parotidectomy in 51 cases (76.1%), by core needle biopsy in 14 cases (20.9%), and by means of open biopsy in the remaining two cases (3.0%). Parotid gland lymphoma represents a diagnostically challenging, multifaceted entity that can easily mimic both benign and malignant conditions. This entity should be included in the differential diagnosis of almost all types of parotid lesion, as it seems to play the role of a great pretender.
CRIS-Team Scopus Importer:2021-04-19
Keywords: diffuse large B-cell lymphoma; follicular lymphoma; lymphoma; MALT lymphoma; marginal zone B-cell lymphoma; parotid gland; parotidectomy; ultrasound

Primary Results of the phase II CheckRad-CD8 Trial: First-Line Treatment of locally advanced Head and Neck Tumors with double Checkpoint Blockade and Radiotherapy dependent on intratumoral CD8+T-Cell Infiltration - Hecht, Markus; Eckstein, Markus; Rutzner, Sandra; Von Der Gruen, J.; Illmer, T.; Klautke, G.; Laban, S.; Hautmann, M.; Brunner, T.; Tamaskovics, B.; Hinke, A.; Frey, Benjamin; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Primary surgical therapy for locally limited oral tongue cancer - Mantsopoulos, Konstantinos; Psychogios, Georgios; Kuenzel, Julian; Waldfahrer, Frank; Zenk, Johannes; Iro, Heinrich (BioMed Research International, 2014)
The aim of this study was to assess the efficacy of primary surgical treatment in the management of locally limited oral tongue carcinoma.A retrospective evaluation was carried out for all patients treated with primary surgery for pT1-pT2 oral tongue carcinomas at a tertiary referral center between 1980 and 2005. All cases were assessed for disease-specific survival and local control rates in relation to T classification, N classification, infiltration depth of the primary tumor, and decision making on neck management and adjuvant therapy. The cases were additionally evaluated for the incidence of major complications and tracheotomies.263 cases were assessed. The 5-year disease-specific survival rate was 75.2%. Positive neck disease was shown to be a significant negative prognostic factor. The occult metastasis rate was 20.2%.Primary surgical treatment is a very effective modality against T1-T2 oral tongue carcinoma, and a low rate of complications can be anticipated.
EVALuna2:19930

Principal moments of a multipole expansion to quantify the magnetic nanoparticle distributions in arteries - Wiekhorst, Frank; Haberkorn, W.; Steinhoff, Uwe; Lyer, Stefan; Alexiou, Christoph; Baer, M.; Trahms, L. (Biomedizinische Technik, 2012)
We present a multipole based approach to model linearly extended nanoparticle distributions in an artery and to reconstruct these distributions from their distant magnetic field. The multipole moments of a spherical harmonic multipole expansion are evaluated for an arbitrary nanoparticle distribution in an artery magnetized perpendicular to its axis. It is shown that each multipole order is determined by only one principal multipole moment. All other possible moments of the respective multipole order can be related to the principal moment and carry the same information about the linear model. Consequently each multipole order is characterized by a typical field pattern. For both homogeneous and inhomogeneous nanoparticle distributions in the artery model the distribution parameters are determined from the principal multipole moments. © 2012 by Walter de Gruyter Berlin Boston.
CRIS-Team Scopus Importer:2022-06-27

Priority setting in the German healthcare system: results from a discrete choice experiment - Meusel, Vera; Mentzakis, E.; Baji, P.; Fiorentini, G.; Paolucci, F. (International Journal of Health Economics and Management, 2023)
Worldwide, social healthcare systems must face the challenges of a growing scarcity of resources and of its inevitable distributional effects. Explicit criteria are needed to define the boundaries of public reimbursement decisions. As Germany stands at the beginning of such a discussion, more formalised priority setting procedures seem in order. Recent research identified multi-criteria decision analysis (MCDA) as a promising approach to inform and to guide decision-making in healthcare systems. In that regard, this paper aims to analyse the relative weight assigned to various criteria in setting priority interventions in Germany. A discrete choice experiment (DCE) was employed in 2015 to elicit equity and efficiency preferences of 263 decision makers, through six attributes. The experiment allowed us to rate different policy interventions based on their features in a composite league table (CLT). As number of potential beneficiaries, severity of disease, individual health benefits and cost-effectiveness are the most relevant criteria for German decision makers within the sample population, the results display an overall higher preference towards efficiency criteria. Specific high priority interventions are mental disorders and cardiovascular diseases.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Decision making; Discrete choice experiment; Efficiency; Germany; Healthcare; Innovation; Priority setting

Probe-based confocal laser endomicroscopy in detecting malignant lesions of vocal folds. - Goncalves, Miguel; Aubreville, Marc; Mueller, Sarina K.; Sievert, Matti; Maier, Andreas; Iro, Heinrich; Bohr, Christopher (Acta Otorhinolaryngologica Italica, 2019)
Probe-based confocal laser endomicroscopy (CLE) is an innovative technique for real-time, non-invasive analysis of the surface epithelium. While being successfully used for diagnosis by experts, this method has not yet been established in clinical routine, partly due to the lack of standards and criteria for classifying various lesions. Our aim was to determine the diagnostic value and inter-rater reliability of CLE in detecting malignant lesions of the vocal cords. 58 video sequences were extracted from the probe-based CLE (GastroFlex probe with a Cellvizio® laser system) examinations of 3 patients with squamous cell carcinomas and 4 patients with benign alterations of the vocal folds. Two ENT surgeons, who were blinded to the histological result, were asked to identify the sequences representing a carcinoma. We showed an accuracy, sensitivity, specificity, PPV and NPV of 91.38-96.55%, 100%, 87.8-95.2%, 77.27-89.47% and 100%, respectively, with an inter-rater reliability of k = 0.89 ("almost perfect agreement"). Probe-based CLE is a promising method for diagnosis and assessment of vocal fold lesions in vivo. Our results suggest that, with adequate training, the diagnostic value of this technique can be improved and potentially provide important information during oncological surgery.

Process Evaluation of a Medical Student-Delivered Smoking Prevention Program for Secondary Schools: Protocol for the Education Against Tobacco Cluster Randomized Trial - Brinker, Titus Josef; Buslaff, Fabian; Suhre, Janina Leonie; Silchmueller, Marc Philipp; Divizieva, Evgenia; Wilhelm, Jilada; Hillebrand, Gabriel; Penka, Dominik; Gaim, Benedikt; Swoboda, Susanne; Baumermann, Sonja; Walther, Joerg Werner; et al. (JMIR Research Protocols, 2019)
Background: Most smokers start smoking during their early adolescence under the impression that smoking entails positive attributes. Given the addictive nature of cigarettes, however, many of them might end up as long-term smokers and suffering from tobacco-related diseases. To prevent tobacco use among adolescents, the large international medical students' network Education Against Tobacco (EAT) educates more than 40,000 secondary school students per year in the classroom setting, using evidence-based self-developed apps and strategies.
CRIS-Team WoS Importer:2019-06-04

Prognostic value of O-6-methylguanine-DNA methyltransferase loss in salivary gland carcinomas - Scesnaite, Asta; Jarmalaite, Sonata; Müller, Maximilian; Agaimy, Abbas; Zenk, Johannes; Hartmann, Arndt; Iro, Heinrich; Peters, Brigitte; Schwarz, Susanne; Schneider-Stock, Regine (Head and Neck-Journal For the Sciences and Specialties of the Head and Neck, 2014)
The purpose of this study was to determine the prognostic value of O-6-methylguanine-DNA methyltransferase (MGMT) inactivation in a group of 286 patients with salivary gland carcinoma and matched histologically normal tissues.MGMT promoter methylation was studied in 36 patients with salivary gland carcinoma and 19 histologically matched normal tissues by pyrosequencing. MGMT protein expression was examined in 286 patients with salivary gland carcinomas and histologically matched normal tissues by immunohistochemistry on tissue microarrays. The results were correlated to demographic, clinicopathologic parameters, and disease follow-up data.MGMT hypermethylation was significantly (p = .021) associated with the protein loss. MGMT loss was found in 39.2% of salivary gland carcinomas and was predominant in aggressive tumors (poorly differentiated, grade III, regional lymph node involved). MGMT loss significantly (p = .004) predicted poor clinical outcome of salivary gland carcinomas and defined high-risk subgroups in clinically favorable tumor groups.We suggest that immunohistochemical evaluation of nuclear MGMT protein might serve as a tool for the prediction of overall survival in patients with salivary gland carcinoma.
EVALuna2:6616

Proposal for standardized ultrasound analysis of the salivary glands: Part 1 submandibular gland - Hoffman, Henry T.; Koch, Michael; Witt, Robert Lee; Ryan, William R.; Zenk, Johannes; Katz, Philippe; Rahmati, Rahmatullah; Rassekh, Christopher; Donato, Francisco; McCulloch, Timothy M.; Joshi, Arjun S.; Chang, Jolie Lien; et al. (Laryngoscope Investigative Otolaryngology, 2024)
Objectives: The Salivary Gland Committee of the American Academy of Otolaryngology-Head and Neck Surgery seeks to standardize terminology and technique for ultrasonograpy used in the evaluation and treatment of salivary gland disorders. Methods: Development of expert opinion obtained through interaction with international practitioners representing multiple specialties. This committee work includes a comprehensive literature review with presentation of case examples to propose a standardized protocol for the language used in ultrasound salivary gland assessment. Results: A multiple segment proposal is initiated with this focus on the submandibular gland. We provide a concise rationale for recommended descriptive language highlighted by a more extensive supplement that includes an extensive literature review with additional case examples. Conclusion: Recommendations are provided to improve consistency both in performing and reporting submandibular gland ultrasound.
CRIS-Team Scopus Importer:2024-03-01
Keywords: anatomic subsites; color doppler; salivary glands; shear wave elastography; submandibular; ultrasound

Prospective Assessment of the Inflammation Parameters in Blood Counts and Blood Serum as prognostic/predictive Parameters for Treatment with Immune Checkpoint-Inhibitors - Schweizer, Claudia; Haderlein, Marlen; Schubert, Philipp; Zhou, Jianguo; Semrau, Sabine; Rutzner, Sandra; Gostian, Antoniu-Oreste; Frey, Benjamin; Donaubauer, Anna-Jasmina; Eckstein, Markus; Becker, Ina; Fietkau, Rainer; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Prospective evaluation of the prognostic value of immune-related adverse events in patients with non-melanoma solid tumour treated with PD-1/PD-L1 inhibitors alone and in combination with radiotherapy - Schweizer, Claudia; Schubert, Philipp; Rutzner, Sandra; Eckstein, Markus; Haderlein, Marlen; Lettmaier, Sebastian; Semrau, Sabine; Gostian, Antoniu Oreste; Frey, Benjamin; Gaipl, Udo; Zhou, Jianguo; Fietkau, Rainer; et al. (European Journal of Cancer, 2020)
Background: Prospective data about the prognostic value of immune-related adverse events (irAEs) in non-melanoma solid tumours are rare. The prognostic value of irAEs in patients treated with combined radiotherapy and immunotherapy is currently unknown. Patients and methods: The prospective non-interventional ST-ICI trial investigates treatment response of tumour patients to anti–programmed cell death-ligand 1 (PD-L1) immune checkpoint inhibitors alone and in combination with radiotherapy and possible predictive markers. Patients undergoing immunotherapy or immunoradiotherapy were surveyed for irAEs. Results: A total of 104 patients were included of whom 29 patients (28%) developed irAEs. Additional radiotherapy was performed in 50 patients (48%). Main tumour entities within the entire cohort were non–small cell lung cancer (NSCLC) (44%) and head and neck squamous cell carcinoma (42%). The rate of irAEs did not differ in patients with and without radiotherapy (p = 0.668). Patients who developed irAEs had longer overall survival (OS) (median: 22.8 months versus 9.0 months without irAEs, p = 0.001) and progression-free survival (PFS) (median: 7.8 months versus 3.2 months without irAEs, p = 0.002). In the subgroup with combined radiotherapy, patients with irAEs also had longer OS (median: 22.8 months versus 7.1 months without irAEs, p = 0.005) and PFS (median: 8.8 months versus 3.0 months without irAEs, p = 0.005). On multivariate analysis only PD-L1 on tumour cells (p = 0.049) and irAEs (p = 0.001) remained independent predictors of OS. Conclusion: The development of irAEs represents a favourable prognostic parameter in patients undergoing immunotherapy and immunoradiotherapy for solid tumours.
CRIS-Team Scopus Importer:2020-10-16
Keywords: Immune checkpoint inhibitors; Immune-related adverse events; Non-melanoma solid tumours; Prognostic parameters; Radiotherapy

Protective effects of Ginkgo biloba extract EGb 761 against noise trauma-induced hearing loss and tinnitus development - Tziridis, Konstantin; Korn, Sabine; Ahlf, Sönke; Schulze, Holger (Neural Plasticity, 2014)
Noise-induced hearing loss (NIHL) and resulting comorbidities like subjective tinnitus are common diseases in modern societies. A substance shown to be effective against NIHL in an animal model is the Ginkgo biloba extract EGb 761. Further effects of the extract on the cellular and systemic levels of the nervous system make it a promising candidate not only for protection against NIHL but also for its secondary comorbidities like tinnitus. Following an earlier study we here tested the potential effectiveness of prophylactic EGb 761 treatment against NIHL and tinnitus development in the Mongolian gerbil. We monitored the effects of EGb 761 and noise trauma-induced changes on signal processing within the auditory system by means of behavioral and electrophysiological approaches. We found significantly reduced NIHL and tinnitus development upon EGb 761 application, compared to vehicle treated animals. These protective effects of EGb 761 were correlated with changes in auditory processing, both at peripheral and central levels. We propose a model with two main effects of EGb 761 on auditory processing, first, an increase of auditory brainstem activity leading to an increased thalamic input to the primary auditory cortex (AI) and second, an asymmetric effect on lateral inhibition in AI.
EVALuna2:19933

Prototype of a Coupling Device to Investigate Focused Ultrasound-Induced Inertial Cavitation for Drug Delivery Applications - George, Benedikt; Wittenbrink, Michel; Rupitsch, Stefan J.; Savešk, Ula; Koh, Christian; Fischer, Dagmar; Ermert, Helmut (Current Directions in Biomedical Engineering, 2023)
Focused ultrasound (FUS) can be used as a drug delivery application for localized chemotherapy to treat cancer. The effect of ultrasound-induced inertial cavitation is promising to trigger drug release from nanocarriers. To investigate this effect, usually, a passive cavitation detection setup is employed. However, applying such a setup is challenging for in vivo experiments, as the test object may need to be fixed inside the water tank. Thus, we present a prototype of a coupling device that could significantly simplify experiments. Since this setup favors undesired sound wave interference and their resulting exceedance of the Mechanical Index, we additionally investigated different signal lengths. The occurrence of standing waves at a signal length of 44 cycles can both be derived from a changing cavitation activity and our calculations. The appearing interference also results in a mean increase of the cavitation activity by ≈ 5.1 %, verified by our experiments as well.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Coupling device; drug delivery; focused ultrasound; inertial cavitation

Qualität in der Befundung von Kopf- und Halssonographien an Universitätskliniken – eine Stichprobe - Künzel, J.; Bozzato, A.; Ernst, B. P.; Fuhrmann, T.; Ugele, I.; Scherl, C.; Schapher, Mirco; Volk, G. F.; Mansour, N.; Knopf, A.; Bohr, C.; Hamann, K. F. (HNO, 2021)
Background: Ultrasound diagnostics are widely used and are standard for radiologists, otolaryngologists, and oral and maxillofacial surgeons in the diagnostic work-up of various pathologies. There is agreement that digital documentation is urgently needed at present to improve and standardize the quality of sonographic documentation. There are more and more publications on the implementation of standardized documentation of findings in imaging diagnostics, including head and neck sonography. Objective: The present work aims to determine the quality of routine head and neck sonography findings on a random basis, according to the criteria of the Bavarian Association of Statutory Health Insurance Physicians (KVB) at a selection of German university otolaryngology departments (ENT). Materials and methods: A total of 70 randomly selected anonymized written findings including image documentation from seven ENT departments were retrospectively analyzed by an experienced KVB examiner concerning fulfilment of KVB criteria. The data were evaluated descriptively. Results: Of the 70 reports, 69 were eligible for evaluation. The average documentation completeness was 80.6%. A total of 9 findings were correctly documented in full (13%). The documentation completeness of the individual departments was sorted in ascending order from 68.1% to 93%. With 88.5% vs. 75%, the hospitals with a structured report showed a higher level of completeness. In 75% of the cases the hospitals with structured reports also had digital solutions for reporting and image archiving. Conclusion: In general, there is potential for optimization regarding the completeness and quality of routinely prepared head and neck sonography findings at the selected university ENT departments. The implementation of structured reporting masks and the conversion of analogue documentation into digital solutions as well as digital networking with the hospital information systems, picture archiving and communication systems should be promoted. Supervision by senior doctors is required to ensure the quality of findings of inexperienced colleagues and to help to achieve standards in reporting.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Completeness of findings; Digital documentation of findings; Quality of findings; Structured reporting; Ultrasound training

Quantification of drug-loaded magnetic nanoparticles in rabbit liver and tumor after in vivo administration - Tietze, Rainer; Jurgons, Roland; Lyer, Stefan; Schreiber, Eveline; Wiekhorst, Frank; Eberbeck, Dietmar; Richter, Heike; Steinhoff, Uwe; Trahms, Lutz; Alexiou, Christoph (Journal of Magnetism and Magnetic Materials, 2009)
Magnetic nanoparticles have been investigated for biomedical applications for more than 30 years. The development of biocompatible nanosized drug delivery systems for specific targeting of therapeutics is imminent in medical research, especially for treating cancer and vascular diseases. We used drug-labeled magnetic iron oxide nanoparticles, which were attracted to an experimental tumor in rabbits with an external magnetic field (magnetic drug targeting, MDT). Aim of this study was to detect and quantify the biodistribution of the magnetic nanoparticles by magnetorelaxometry. The study shows higher amount of nanoparticles in the tumor after intraarterial application and MDT compared to intravenous administration.
CRIS-Team Scopus Importer:2022-06-27
Keywords: Chemotherapy; Magnetic drug targeting; Magnetic nanoparticle; magnetorelaxometry; VX-2-tumor

Quantitative Determination of Local Density of Iron Oxide Nanoparticles Used for Drug Targeting Employing Inverse Magnetomotive Ultrasound - Fink, Michael; Rupitsch, Stefan Johann; Lyer, Stefan; Ermert, Helmut (IEEE Transactions on Ultrasonics Ferroelectrics and Frequency Control, 2021)
Numerous medical applications make use of magnetic nanoparticles, which increase the demand for imaging procedures that are capable of visualizing this kind of particles. Magnetomotive Ultrasound (MMUS) is an ultrasound-based imaging modality that can detect tissue, which is permeated by magnetic nanoparticles. However, currently MMUS can only provide a qualitative mapping of the particle density in the particle-loaded tissue. In this contribution, we present an enhanced MMUS procedure, which enables an estimation of the quantitative level of the local nanoparticle concentration in tissue. The introduced modality involves an adjustment of simulated data to measurement data. To generate these simulated data, the physical processes that arise during the MMUS imaging procedure have to be emulated which can be a computing-intensive proceeding. Since this considerable calculation effort may handicap clinical applications, we further present an efficient approach to calculate the decisive physical quantities as well as a suitable way to adjust these simulated quantities to the measurement data with only moderate computational effort. For this purpose, we use the result data of a conventional MMUS measurement as well as the knowledge on the magnetic field quantities and on the mechanical parameters describing the biological tissue, namely the density, the longitudinal wave velocity and the shear wave velocity. Experiments on tissue-mimicking phantoms demonstrate that the presented technique can indeed be utilized to determine the local nanoparticle concentration in tissue quantitatively in the correct order of magnitude. By investigating test phantoms of simple geometry, the mean particle concentration of the particle-laden area could be determined with less than 22% deviation to the nominal value.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Acoustics; Drugs; Imaging; inverse problem; iron oxide nanoparticles; Magnetic Drug Targeting; Magnetic nanoparticles; Magnetic resonance imaging; Magnetoacoustic effects; Magnetomotive Ultrasound; ultrasonic imaging; Ultrasonic imaging

Quantitative Imaging of the Iron-Oxide Nanoparticle- Concentration for Magnetic Drug Targeting Employing Inverse Magnetomotive Ultrasound - Fink, Michael; Lyer, Stefan; Alexiou, Christoph; Rupitsch, Stefan; Ermert, Helmut (Current Directions in Biomedical Engineering, 2019)
Magnetomotive Ultrasound is an imaging technique that is capable to detect tissue, which is perfused by magnetic nanoparticles. However, this modality is restricted to qualitative imaging only. Therefore, we present an extended Magnetomotive Ultrasound algorithm, which allows the quantitative determination of the spatial distribution of magnetic nanoparticle density in tissue. The algorithm is based on an iterative adjustment of simulated data to measurements. Experiments with tissue-mimicking phantoms reveal that the presented method leads to the spatial particle concentration in the correct order of magnitude.
CRIS-Team Scopus Importer:2019-10-08
Keywords: Iron-Oxide Nanoparticles; Iterative Method; Magnetic Drug Targeting; Magnetomotive Ultrasound; Ultrasonic Imaging

Quantitative Imaging of the Iron-Oxide Nanoparticle-Concentration for Magnetic Drug Targeting Employing Inverse Magnetomotive Ultrasound - Fink, Michael; Rupitsch, Stefan; Lyer, Stefan; Alexiou, Christoph; Ermert, Helmut (Current Directions in Biomedical Engineering 2019, 2019)

Questionnaire-based detection of immune-related adverse events in cancer patients treated with PD-1/PD-L1 immune checkpoint inhibitors - Griewing, Luisa Maria; Schweizer, Claudia; Schubert, Philipp; Rutzner, Sandra; Eckstein, Markus; Frey, Benjamin; Haderlein, Marlen; Weissmann, Thomas; Semrau, Sabine; Gostian, Antoniu Oreste; Mueller, Sarina K.; Traxdorf, Maximilian; et al. (BMC Cancer, 2021)
Background: Immune checkpoint inhibitors (ICI) have become standard treatment in different tumor entities. However, safe treatment with ICI targeting the PD-1/PD-L1 axis requires early detection of immune-related adverse events (irAE). There exist different questionnaires of drug manufacturers for the detection of irAE that have not been validated so far. Methods: The prospective non-interventional ST-ICI trial studied treatment with PD-1/PD-L1 ICI alone or combined with radiotherapy. In the current analysis, the detection rate of self-reported irAE with a patient questionnaire containing 41 different questions was compared to clinician-reported irAE. Results: Between April 2017 and August 2019, a total of 104 patients were prospectively enrolled. NSCLC (44%) and HNSCC (42%) were the most frequent tumor entities. A total of 784 questionnaires were collected. A total of 29 irAE were reported by clinicians. The most frequent irAE was hypothyroidism (9%), followed by skin reactions (5%), hepatitis (4%), diarrhea (3%), and pneumonitis (3%). Questions that became significantly more often positive at time points of clinician-reported irAE were “weight change”, “difficulty to grip things”, “bloody or mucous stool” and “insomnia”. Self-reported organ-specific questions detected at least 50% of clinician-reported irAE of gastrointestinal, lung, endocrine, and skin irAE. It was not possible to detect hepatic irAE with the questionnaire. Conclusion: Questionnaires can help to detect gastrointestinal, lung, endocrine, or skin irAE, but not hepatic irAE. Questions on “weight change” and “insomnia” may help to increase the detection rate of irAE, besides organ-specific questions. These results are a valuable contribution to the future development of a specific and practicable questionnaire for early self-reported detection of irAE during ICI therapy in cancer patients. Trial registration: ClinicalTrials.gov, NCT03453892. Registered on 05 March 2018.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Immune checkpoint inhibitors; Immune-related adverse events; Patient-reported irAE; PD-1; PD-L1; Questionnaire; Side effects; Solid tumors; Toxicity

Radio(chemo)therapy in anaplastic thyroid cancer—high locoregional but low distant control rates—a monocentric analysis of a tertiary referral center - Schmied, Matthias; Lettmaier, Sebastian; Semrau, Sabine; Traxdorf, Maximilian; Mantsopoulos, Konstantinos; Müller-Hübner, Sarina; Iro, Heinrich; Denz, Axel; Grützmann, Robert; Fietkau, Rainer; Haderlein, Marlen (Strahlentherapie und Onkologie, 2022)
Background: Anaplastic thyroid cancer (ATC) is a lethal disease with highly aggressive disease progression. This study analyses the influence of radio(chemo)therapy, R(C)T, on disease control, survival rates and predictors for survival. Patients and methods: A total of 33 patients with ATC, treated at a tertiary referral center between May 2001 and April 2020 were included. Univariate and multivariate analysis were used to investigate correlates of R(C)T and predictors on disease control and survival rates. Results: Median follow-up was 4 months. In UICC stage IVA and IVB median overall survival (OS) was 8 months, median progression-free survival (PFS) was 6 months. Patients with UICC stage IVA and IVB and patients being irradiated with a radiation dose of more than 60 Gy showed increased OS. Of these patients, 3 were alive and free from disease. All of them receiving cisplatin-based radiochemotherapy and a minimum radiation dose of 66 Gy. UICC stage IVC showed a median OS of 2.5 months and a median PFS of 1 month. Only 2 of 16 patients had local failure. Conclusion: Depending on UICC stage, RT with high radiation dose can lead to improved OS or at least higher locoregional control. A limiting factor is the high incidence of distant metastases; therefore modern systemic treatment options should be integrated into multimodal therapy concepts.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Anaplastic thyroid cancer; Chemotherapy; Multimodal treatment; Radiation dose; Radiotherapy

Radiotherapy combined with docetaxel alters the immune phenotype of HNSCC cells and results in increased surface expression of CD137 and release of HMGB1 of specifically HPV-positive tumor cells - Grottker, Fridolin; Gehre, Simon; Reichardt, Clara; Sengedorj, Azzaya; Jost, Tina; Rieckmann, Thorsten; Hecht, Markus; Gostian, Antoniu-Oreste; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo; Rückert, Michael (Neoplasia, 2023)
Purpose: Human papilloma virus (HPV) positive head and neck squamous cell carcinoma (HNSCC) tumors respond significantly better to anticancer treatments. It is assumed to be due to a better response to radiotherapy (RT), and presumably to an increased immunogenicity. However, little is known how the immune phenotype of HNSCC tumor cells is modulated by standard treatment, namely by radiochemotherapy (RCT). Methods: Therefore, we aimed to examine the impact of the HPV status on the immune phenotype of HNSCC cell lines following RCT with 5 × 3Gy or 1 × 19.3Gy and/or docetaxel, by analyzing cell death, release of damage-associated molecular patterns (DAMPs), surface expression of immune checkpoint molecules (ICMs) and the impact on activation of human monocyte-derived dendritic cells (hmDCs). Results: Cell death induction and Hsp70 release following RCT was independent of the HPV status, and RCT significantly increased the expression of the immune suppressive ICMs PD-L1, PD-L2 and HVEM. An immune stimulatory ICM, CD137, was significantly increased following RCT only on HPV-positive cell lines, as well as the release of HMGB1. Although the treatment increased cell death and modulated ICM expression in HNSCC, the hmDCs were not activated after co-incubation with treated tumor cells. Conclusion: Our data with the HPV-dependent release of HMGB1 and increased expression of CD137 following RCT provide a hint for increased immunogenicity underlining the better prognosis for HPV positive tumors following RCT.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Anti-tumor immunity; Dendritic cells; Docetaxel; Head and neck squamous cell carcinoma; HMGB1; HPV status; Immune checkpoint molecules; Radiotherapy

Radiotherapy for the elderly Patient with Head and Neck Squamous Cell Carcinoma - Experience of a Center for ENT-Tumors - Winkler, Leah-Sophie; Lettmaier, Sebastian; Semrau, Sabine; Mueller, Sarina K.; Traxdorf, Maximilian; Iro, Heinrich; Kesting, Marco Rainer; Fietkau, Rainer; Haderlein, Marlen (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Radiotherapy with paclitaxel/cisplatin vs. fluorouracil/cisplatin for head and neck cancer - Fietkau, Rainer; Hecht, Markus; Hofner, Benjamin; Iro, Heinrich; Gefeller, Olaf; Roedel, C.; Hautmann, M.; Koelbl, O.; Salay, A.; Ruebe, C.; Breinl, P.; Krings, W.; et al. (RADIOTHERAPY AND ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-06-18

Randomized phase-III-trial of concurrent chemoradiation for locally advanced head and neck cancer comparing dose reduced radiotherapy with paclitaxel/cisplatin to standard radiotherapy with fluorouracil/cisplatin: The PacCis-trial - Fietkau, Rainer; Hecht, Markus; Hofner, Benjamin; Lubgan, Dorota; Iro, Heinrich; Gefeller, Olaf; Rödel, Claus; Hautmann, Matthias G.; Kölbl, Oliver; Salay, Attila; Rübe, Christian; Melchior, Patrick; et al. (Radiotherapy and Oncology, 2020)
Background and purpose: This multicenter, phase 3 trial investigates whether the incorporation of concurrent paclitaxel and cisplatin together with a reduced total dose of radiotherapy is superior to standard fluorouracil–cisplatin based CRT. Materials and methods: Patients with SCCHN, stage III–IVB, were randomized to receive paclitaxel/cisplatin (PacCis)–CRT (arm A; paclitaxel 20 mg/m2 on days 2, 5, 8, 11 and 25, 30, 33, 36; cisplatin 20 mg/m2, days 1–4 and 29–32; RT to a total dose of 63.6 Gy) or fluorouracil/cisplatin (CisFU)–CRT (arm B; fluorouracil 600 mg/m2; cisplatin 20 mg/m2, days 1–5 and 29–33; RT: 70.6 Gy). Endpoint was 3-year-disease free survival (3y-DFS). Results: A total of 221 patients were enrolled between 2010 and 2015. With a median follow-up of 3.7 years, 3y-DFS in the CisFU arm and PacCis arm was 58.2% and 48.4%, respectively (HR 0.82, 95% CI 0.56–1.21, p = 0.52). The 3y-OS amounted to 64.6% in the CisFU arm, and to 59.2% in the PacCis arm (HR 0.82, 95% CI 0.54–1.24, p = 0.43). In the subgroup of p16-positive oropharyngeal carcinomas, 3y-DFS and 3y-OS was 84.6% vs 83.9% (p = 0.653), and 92.3% vs. 83.5% (p = 0.76) in arm A and B, respectively. Grade 3–4 hematological toxicities were significantly reduced in arm A (anemia, p = 0.01; leukocytopenia, p = 0.003), whereas grade 3 infections were reduced in arm B (p = 0.01). Conclusion: Paclitaxel/cisplatin–CRT with a reduced RT-dose is not superior to standard fluorouracil/cisplatin–CRT. Subgroup analyses indicate that a reduced radiation dose seems to be sufficient for p16+ oropharyngeal cancer or non-smokers. Clinical trial information: NCT01126216; EudraCT Number 2005-003484-23.
CRIS-Team Scopus Importer:2020-02-14
Keywords: Chemoradiotherapy; Cisplatin; Fluorouracil; Head and neck cancer; Paclitaxel

Real-Time 3D Reconstruction of Human Vocal Folds via High-Speed Laser-Endoscopy - Henningson, Jann-Ole; Stamminger, Marc; Döllinger, Michael; Semmler, Marion (Medical Image Computing and Computer Assisted Intervention – MICCAI, 2022)
Conventional video endoscopy and high-speed video endosc-opy of the human larynx solely provides practitioners with information about the two-dimensional lateral and longitudinal deformation of vocal folds. However, experiments have shown that vibrating human vocal folds have a significant vertical component. Based upon an endoscopic laser projection unit (LPU) connected to a high-speed camera, we propose a fully-automatic and real-time capable approach for the robust 3D reconstruction of human vocal folds. We achieve this by estimating laser ray correspondences by taking epipolar constraints of the LPU into account. Unlike previous approaches only reconstructing the superior area of the vocal folds, our pipeline is based on a parametric reinterpretation of the M5 vocal fold model as a tensor product surface. Not only are we able to generate visually authentic deformations of a dense vibrating vocal fold model, but we are also able to easily generate metric measurements of points of interest on the reconstruced surfaces. Furthermore, we drastically lower the effort needed for visualizing and measuring the dynamics of the human laryngeal area during phonation. Additionally, we publish the first publicly available labeled in-vivo dataset of laser-based high-speed laryngoscopy videos.<br

Real-time cell analysis of human cancer cell lines after chemotherapy with functionalized magnetic nanoparticles - Dürr, Stephan; Lyer, Stefan; Mann, Johannes; Janko, Christina; Tietze, Rainer; Schreiber, Eveline; Herrmann, Martin; Alexiou, Christoph (Anticancer Research, 2012)
Background: Magnetic drug targeting is a new and innovative approach in cancer treatment. In order to avoid the adverse effects of chemotherapy, the therapeutic agent is linked to superparamagnetic nanoparticles which are injected into a tumour-supporting artery and is focused by an external magnetic field to the tumour region in order to provoke maximum local impact. Analysis of nanoparticles and chemotherapeutic substances in human cancer cell culture is necessary to provide respective information for in vivo applications. Materials and Methods: The effect of pure mitoxantrone and mitoxantrone bound to nanoparticles was tested on human cancer cell lines using real-time cell analysis (RTCA) and lactate dehydrogenase (LDH) assays. RTCA was performed by impedance measuring. The impedance is expressed as the cell index (CI), which is a parameter of cell viability. Results: RTCA showed that mitoxantrone when bound to nanoparticles was more toxic than the drug alone. The CI clearly decreased faster after adding the chemotherapeutic bound to nanoparticles than when adding the pure drug alone. However, in the first experiments, the particles themselves showed no toxicity at therapeutically relevant concentrations. These results were confirmed by LDH assays. Conclusion: The toxic effects of chemotherapeutic agents (e.g. mitoxantrone) on human cancer cell lines (e.g. MCF-7) can be enhanced if these drugs are bound to magnetic nanoparticles. These preliminary data show a dependency on the different application modes of RTCA. The results presented here are a first step for a better understanding of the effectiveness of magnetic drug targeting as a new and innovative cancer treatment.
CRIS-Team Scopus Importer:2022-06-27
Keywords: Cell culture; Magnetic drug targeting MCF-7 breast cancer cells; Magnetic nanoparticles; Real-time cell analysis

Recent nanomedicine articles of outstanding interest: nanoparticle functionalization for disease diagnostics and therapy - Janko, Christina; Pöttler, Marina; Friedrich, Ralf P.; Lyer, Stefan; Cicha, Iwona; Alexiou, Christoph (Nanomedicine, 2015)
EVALuna2:19956

Reconstruction of the Oral Commissure With the Zisser Flap - Mantsopoulos, Konstantinos; Iro, Heinrich; Constantinidis, Jannis (Journal of Oral and Maxillofacial Surgery, 2019)
The aim of this study was to investigate the role of the Zisser flap in the reconstruction of defects of the oral commissure. We describe our personal experience with this method and present some interesting aspects from the relevant literature. We retrospectively evaluated the records, from the period between 2003 and 2017, of all patients with defects of the oral commissure after resection of malignant tumors, traumas, or burns and reconstruction by means of the Zisser flap. We looked for information on the origin of the commissural defect, method of vermillion reconstruction using the lingual or buccal mucosa, functional result, esthetic outcome, and postoperative complications. The functional result of the reconstruction of the oral commissure was assessed regarding postoperative subjective speech integrity, preservation of competence of the oral sphincter, and lip sensation. The esthetic outcome was evaluated regarding limitations in facial expression and scar formation. The study included 13 patients. The follow-up period in the oncologic cases was 63.2 months (range, 10 to 140 months). No tumor recurrences were detected. Vermillion reconstruction was achieved by means of a buccal mucosal flap in 11 cases and a lingual mucosal flap in 2. All patients achieved normal oral competence and mouth opening except for 1 case, in which secondary commissuroplasty with restoration of sphincter function was needed. No cases of blunting or microstomia were detected. Reconstruction of the oral commissure with the Zisser flap is associated with an outstanding functional outcome that is cosmetically very acceptable.
CRIS-Team Scopus Importer:2019-05-24

Reconstruction of Vocal Fold Medial Surface 3D Trajectories: Effects of Neuromuscular Stimulation and Airflow - Schlegel, Patrick; Chung, Hye Rhyn; Döllinger, Michael; Chhetri, Dinesh K. (Laryngoscope, 2023)
Introduction: Analysis of medial surface dynamics of the vocal folds (VF) is critical to understanding voice production and treatment of voice disorders. We analyzed VF medial surface vibratory dynamics, evaluating the effects of airflow and nerve stimulation using 3D reconstruction and empirical eigenfunctions (EEF). Study Design: In vivo canine hemilarynx phonation. Methods: An in vivo canine hemilarynx was phonated while graded stimulation of the recurrent and superior laryngeal nerves (RLN and SLN) was performed. For each phonatory condition, vibratory cycles were 3D reconstructed from tattooed landmarks on the VF medial surface at low, medium, and high airflows. Parameters describing medial surface trajectory shape were calculated, and underlying patterns were emphasized using EEFs. Fundamental frequency and smoothed cepstral peak prominence (CPPS) were calculated from acoustic data. Results: Convex-hull area of landmark trajectories increased with increasing flow and decreasing nerve activation level. Trajectory shapes observed included circular, ellipsoid, bent, and figure-eight. They were more circular on the superior and anterior VF, and more elliptical and line-like on the inferior and posterior VF. The EEFs capturing synchronal opening and closing (EEF1) and alternating convergent/divergent (EEF2) glottis shapes were mostly unaffected by flow and nerve stimulation levels. CPPS increased with higher airflow except for low RLN activation and very dominant SLN stimulation. Conclusion: We analyzed VF vibration as a function of neuromuscular stimulation and airflow levels. Oscillation patterns such as figure-eight and bent trajectories were linked to high nerve activation and flow. Further studies investigating longer sections of 3D reconstructed oscillations are needed. Level of Evidence: N/A, Basic Science Laryngoscope, 2023.
CRIS-Team Scopus Importer:2023-09-15
Keywords: hemilarynx; in vivo canine phonation; neuromuscular stimulation; vocal fold medial surface; vocal fold vibration; voice quality

"Recurrence Resonance" in Three-Neuron Motifs - Krauß, Patrick; Prebeck, Karin; Schilling, Achim; Metzner, Claus (Frontiers in Computational Neuroscience, 2019)
Stochastic Resonance (SR) and Coherence Resonance (CR) are non-linear phenomena, in which an optimal amount of noise maximizes an objective function, such as the sensitivity for weak signals in SR, or the coherence of stochastic oscillations in CR. Here, we demonstrate a related phenomenon, which we call "Recurrence Resonance" (RR): noise can also improve the information flux in recurrent neural networks. In particular, we show for the case of three-neuron motifs with ternary connection strengths that the mutual information between successive network states can be maximized by adding a suitable amount of noise to the neuron inputs. This striking result suggests that noise in the brain may not be a problem that needs to be suppressed, but indeed a resource that is dynamically regulated in order to optimize information processing.
CRIS-Team WoS Importer:2019-10-01

Recurrent Mutations within the Amino-Terminal Region of ?-Catenin Are Probable Key Molecular Driver Events in Sinonasal Hemangiopericytoma - Haller, Florian; Bieg, Matthias; Moskalev, Evgeny; Barthelmeß, Sarah; Geddert, Helene; Boltze, Carsten; Diessl, Nicolle; Braumandl, Karin; Brors, Benedikt; Iro, Heinrich; Hartmann, Arndt; Wiemann, Stefan; et al. (American Journal of Pathology, 2015)
Sinonasal hemangiopericytoma (SN-HPC) is an uncommon, site-specific, low-grade mesenchymal neoplasm of probable perivascular myoid cell origin. In contrast to solitary fibrous tumors of soft tissue and sinonasal tract origin, SN-HPCs were recently shown to lack recurrent NAB2-STAT6 fusion variants. Other molecular alterations known to occur in some of soft tissue perivascular myoid cell neoplasms were also absent in SN-HPC; thus, the molecular pathogenesis of SN-HPCs remained unknown. Guided by whole-genome sequencing combined with RNA sequencing of an index case, we analyzed a total of six SN-HPCs for mutations within the amino-terminal region of the gene CTNNB1 (cadherin-associated protein), ? 1, 88 kDa, encoding ?-catenin. All six cases showed missense mutations, with amino acid substitutions clustering at positions 33 to 45, corresponding to the recognition site of the ?-catenin destruction complex. Similar CTNNB1 mutations have been described in a variety of epithelial and mesenchymal neoplasms. These mutations prevent ?-catenin phosphorylation and proteasomal degradation but promote its nuclear accumulation and subsequent increased transcription of Wingless-related integration site target genes. Consistent with these molecular findings, ?-catenin IHC showed consistent diffuse and strong nuclear staining of the tumor cells in all six SN-HPCs. Our results highlight, for the first time, CTNNB1 mutations as the likely initiating molecular events driving SN-HPC tumorigenesis, which places SN-HPC among the growing family of ?-catenin-driven mesenchymal neoplasms.
EVALuna2:6646

Reduction of elective radiotherapy treatment volume in definitive treatment of locally advanced head and neck cancer—comparison of a prospective trial with a revised simulated contouring approach - Weissmann, Thomas; Speer, Stefan; Putz, Florian; Lettmaier, Sebastian; Schubert, Philipp; Shariff, Maya; Semrau, Sabine; Gostian, Antoniu-Oreste; Traxdorf, Maximilian; Mueller, Sarina K.; Eckstein, Markus; Hautmann, Matthias; et al. (Journal of Clinical Medicine, 2021)
Definitive radiochemotherapy of locally advanced head and neck squamous cell cancer (HNSCC) achieves high locoregional tumor control rates; but is frequently associated with long-term toxicity. A future direction could be a de-escalation strategy focusing on treated volume rather than radiotherapy dose. This analysis evaluates radiotherapy dose and volume parameters of patients treated with a standard contouring approach in a clinical trial context compared with a revised volume-reduced contouring approach. In this case, 30 consecutive patients from the CheckRad-CD8 trial treated at a single study center were included in this analysis. Treatment toxicity and quality of life were assessed at the end of radiotherapy. Standard treatment plans (ST) following state of the art contouring guidelines that were used for patient treatment and volume reduced treatment plans (VRT) according to a revised simulated approach were calculated for each patient. Planning target volumes (PTV) and mean doses to 38 organs-at-risk structures were compared. At the end of radiotherapy patients reported high rates of mucositis; dysphagia and xerostomia. In addition; patient reported quality of life as assessed by the EORTC QLQ-HN35 questionnaire deteriorated. Comparing the two contouring approaches; the elective PTV_56 Gy and the high risk PTV_63 Gy (shrinking field) were significantly smaller in the VRT group. Significant reduction of mean dose to structures of the oral cavity; the larynx as well as part of the swallowing muscles and the submandibular glands was achieved in the simulated VRT-plan. Treatment de-intensification by reduction of the irradiated volume could potentially reduce treatment volume and mean doses to organs at risk. The proposed contouring approach should be studied further in the context of a clinical trial.
CRIS-Team Scopus Importer:2021-10-22
Keywords: De-intensification; Definitive treatment; Head neck cancer; Radiotherapy; Salivary glands; Swallowing function; Volume reduc-tion

Reduktion der Tinnituslautstärke: Pilotstudie zur Abschwächung von tonalem Tinnitus mit schwellennahem, individuell spektral optimiertem Rauschen - Schilling, Anne; Krauß, Patrick; Hannemann, R.; Schulze, Holger; Tziridis, Konstantin (HNO, 2020)
Background: Around 15% of the general population is affected by tinnitus, but no real cure exists despite intensive research. Based on our recent causal model for tinnitus development, we here test a new treatment aimed at counteracting the perception. This treatment is based on the stochastic resonance phenomenon at specific auditory system synapses that is induced by externally presented near-threshold noise. Objective: This pilot study will investigate whether individually spectrally adapted noise can successfully reduce chronic tonal/narrow-band tinnitus during stimulation. Materials and methods: Hearing loss (HL) as well as tinnitus pitch (TP) and loudness (TL) were audiometrically measured in 22 adults (46.6±16.3 years; 4 women) with tinnitus. Based on these measurements, up to eight different noise stimuli with five intensities (−20 to +20 dB SL) were generated. These were presented for 40 s each via audiologic headphones in a soundproof chamber. After each presentation, the change in TL was rated on a five-level scale (−2 to +2). Results: We found patients (n = 6) without any improvement in their TL perception as well as patients with improvement (n = 16), where stimulation around the TP was most effective. The groups differed in post-hoc analysis of their audiograms: the effectiveness of our new therapeutic strategy obviously depends on the individual HL, and was most effective in normal-hearing tinnitus patients and those with mild HL. Conclusion: Subjective TL could be reduced in 16 out of 22 patients during stimulation. For a possible success of a future therapy, the HL seems to be of relevance.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Hearing loss; Individualized therapy; Pure tone audiometry; Stochastic resonance; Tinnitus questionnaires

Refinement of the surgical indication and increasing expertise are associated with a better quality of pathology specimen in pleomorphic adenomas - Mantsopoulos, Konstantinos; Iro, Ann Kristin; Sievert, Matti; Mueller, Sarina K.; Agaimy, Abbas; Koch, Michael; Iro, Heinrich (Acta Oto-Laryngologica, 2021)
Background: Traditional surgical philosophy condemns extracapsular dissection for pleomorphic adenoma as a euphemism for the enucleation of this lesion. Objectives: The aims of the study were to trace the development of surgical treatment by pleomorphic adenomas of the parotid gland over the last 15 years and explore its effects on the histopathology specimen. Materials and Methods: The medical records of all cases with pleomorphic adenomas of the parotid gland between 2006 and 2020 were examined for information on age, gender, and type of surgery. An experienced head and neck pathologist re-evaluated the histology slides from all the cases. Results: The study included 844 patients. Our analysis showed an increase in the performance of extracapsular dissection from 52.8% (2006) to 63.3% (2020), and an increase in histopathology specimens with tumours completely covered by healthy tissue from 27.7% (2006) to 50% (2020). Conclusions: Our decision-making process reached its peak in the last study years, in terms of reduced surgical invasiveness and quality of the pathology specimen. Significance: Extracapsular dissection has gained a firm hold as an indispensable tool for the experienced parotid surgeon. Proper indication is based on careful selection of cases and the correct interpretation of preoperative features on palpation and imaging.
CRIS-Team Scopus Importer:2021-01-29
Keywords: capsule; extracapsular dissection; facial nerve; Parotid gland; pathology; pleomorphic adenoma; pleomorphic adenoma

Relevance of the time interval between surgery and adjuvant radio (chemo) therapy in HPV-negative and advanced head and neck carcinoma of unknown primary (CUP) - Balk, Matthias; Rupp, Robin; Mantsopoulos, Konstantinos; Allner, Moritz; Grundtner, Philipp; Müller-Hübner, Sarina; Traxdorf, Maximilian; Eckstein, Markus; Speer, Stefan; Semrau, Sabine; Fietkau, Rainer; Iro, Heinrich; et al. (BMC Cancer, 2021)
Introduction In contrast to head and neck squamous cell carcinoma (HNSCC), the effect of treatment duration in HNSCC-CUP has not been thoroughly investigated. Thus, this study aimed to assess the impact of the time interval between surgery and adjuvant therapy on the oncologic outcome, in particular the 5-year overall survival rate (OS), in advanced stage, HPV-negative CUPs at a tertiary referral hospital. 5-year disease specific survival rate (DSS) and progression free survival rate (PFS) are defined as secondary objectives. Material and methods Between January 1st, 2007, and March 31st, 2020 a total of 131 patients with CUP were treated. Out of these, 59 patients with a confirmed negative p16 analysis were referred to a so-called CUP-panendoscopy with simultaneous unilateral neck dissection followed by adjuvant therapy. The cut-off between tumor removal and delivery of adjuvant therapy was set at the median, i.e. patients receiving adjuvant therapy below or above the median time interval. Results Depending on the median time interval of 55 days (d) (95% CI 51.42-84.52), 30 patients received adjuvant therapy within 55 d (mean 41.69 d, SD = 9.03) after surgery in contrast to 29 patients at least after 55 d (mean 73.21 d, SD = 19.16). All patients involved in the study were diagnosed in advanced tumor stages UICC III (n = 4; 6.8%), IVA (n = 27; 45.8%) and IVB (n = 28; 47.5%). Every patient was treated with curative neck dissection. Adjuvant chemo (immune) radiation was performed in 55 patients (93.2%), 4 patients (6.8%) underwent adjuvant radiation only. The mean follow-up time was 43.6 months (SD = 36.7 months). The 5-year OS rate for all patients involved was 71% (95% CI 0.55-0.86). For those patients receiving adjuvant therapy within 55 d (77, 95% CI 0.48-1.06) the OS rate was higher, yet not significantly different from those with delayed treatment (64, 95% CI 0.42-0.80; X-(1)(2) = 1.16, p = 0.281). Regarding all patients, the 5-year DSS rate was 86% (95% CI 0.75-0.96). Patients submitted to adjuvant treatment in less than 55 d the DSS rate was 95% (95% CI 0.89-1.01) compared to patients submitted to adjuvant treatment equal or later than 55 d (76% (95% CI 0.57-0.95; X-(1)(2) = 2.32, p = 0.128). The 5-year PFS rate of the entire cohort was 72% (95% CI 0.59-0.85). In the group < 55 d the PFS rate was 78% (95% CI 0.63-0.94) and thus not significantly different from 65% (95% CI 0.45-0.85) of the group >= 55 d; (X-(1)(2) = 0.29, p = 0.589). Conclusions The results presented suggest that the oncologic outcome of patients with advanced, HPV-negative CUP of the head and neck was not significantly affected by a prolonged period between surgery and adjuvant therapy. Nevertheless, oncologic outcome tends to be superior for early adjuvant therapy.
CRIS-Team WoS Importer:2021-12-03

Relevance of the time interval between surgery and adjuvant radio (chemo) therapy in HPV-negative and advanced head and neck carcinoma of unknown primary (CUP) - Balk, Matthias; Rupp, Robin; Mantsopoulos, Konstantinos; Allner, Moritz; Grundtner, Philipp; Mueller, Sarina K.; Traxdorf, Maximilian; Eckstein, Markus; Speer, Stefan; Semrau, Sabine; Fietkau, Rainer; Iro, Heinrich; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Reply to Philip et al. - Echternach, Matthias; Westphalen, Caroline; Koeberlein, Marie Christine; Gantner, Sophia; Peters, Gregor; Benthaus, Tobias; Jakubaß, Bernhard; Kuranova, Liudmila; Döllinger, Michael; Kniesburges, Stefan (American Journal of Respiratory and Critical Care Medicine, 2021)
CRIS-Team Scopus Importer:2021-05-21

Response to Letter to the editor: Interrater Reliability of Ultrasound in the Diagnosis of Sialolithiasis: Methodological Issues. Interrater Reliability of Ultrasound: Methodological Issues - Goncalves, Miguel; Mantsopoulos, Konstantinos; Schapher, Mirco; Iro, Heinrich; Koch, Michael (Ultraschall in der Medizin, 2019)
CRIS-Team Scopus Importer:2019-10-18

Restoration of function after cortical lesion: does it require an internal template? - Schulze, Holger; Tziridis, Konstantin (Neural Regeneration Research, 2014)
EVALuna2:19970

Results of contralateral anastomosis of microvascular free flaps in head and neck reconstruction - Gschoßmann, Juliane; Balk, Matthias; Rupp, Robin; Müller-Hübner, Sarina; Allner, Moritz; Sievert, Matti; Mantsopoulos, Konstantinos; Koch, Michael; Iro, Heinrich; Gostian, Antoniu-Oreste (Ent-Ear Nose & Throat Journal, 2022)
Objectives: Despite various solutions to the issue of ipsilateral vessel-depleted neck in microvascular head and neck reconstruction, concrete data on its safety and implementation are scarce. This paper focuses on the feasibility and success rates of contralateral anastomosis in free flap reconstruction in the head and neck region. Methods: This single-center retrospective study at a tertiary referral center includes all patients who underwent free flap reconstruction of the head and neck with contralateral anastomosis between January 1st, 2007 and February 28th, 2021. Primary objectives were frequency, success, and flap-associated complication rates. Secondary objectives were recipient vessels and flap type. Results: Of 318 patients who underwent microvascular reconstruction, anastomosis was performed on the contralateral side of the neck in 32 patients (10.0%). Recipient vessels involved mainly the superior thyroid artery (74.2%; n = 23) and the facial vein (51.1%; n = 23). Thirty patients (93.8%) received a radial forearm free flap. Flap-associated complications occurred in 12.5% of included cases (n = 4): one partial flap necrosis (3.1%), one anastomotic insufficiency (3.1%), one venous thrombosis of the microvascular pedicle (3.1%), and one wound dehiscence (3.1%). All of these complications were resolved without complete flap loss. Conclusion: This study demonstrates that contralateral anastomosis is a successful and safe option in microvascular head and neck reconstruction, especially using a radial forearm free flap. Thus, anastomosing to the contralateral side of the neck can be advocated as a valuable option in the ipsilateral vessel-depleted neck.
CRIS-Team Scopus Importer:2022-07-15
Keywords: contralateral anastomosis; free flaps; head and neck cancer; microvascular reconstruction; recipient vessels; vessel-depleted neck

Rethinking glottal midline detection - Kist, Andreas; Zilker, Julian; Gómez, Pablo; Schützenberger, Anne; Döllinger, Michael (Scientific Reports, 2020)
A healthy voice is crucial for verbal communication and hence in daily as well as professional life. The basis for a healthy voice are the sound producing vocal folds in the larynx. A hallmark of healthy vocal fold oscillation is the symmetric motion of the left and right vocal fold. Clinically, videoendoscopy is applied to assess the symmetry of the oscillation and evaluated subjectively. High-speed videoendoscopy, an emerging method that allows quantification of the vocal fold oscillation, is more commonly employed in research due to the amount of data and the complex, semi-automatic analysis. In this study, we provide a comprehensive evaluation of methods that detect fully automatically the glottal midline. We used a biophysical model to simulate different vocal fold oscillations, extended the openly available BAGLS dataset using manual annotations, utilized both, simulations and annotated endoscopic images, to train deep neural networks at different stages of the analysis workflow, and compared these to established computer vision algorithms. We found that classical computer vision perform well on detecting the glottal midline in glottis segmentation data, but are outperformed by deep neural networks on this task. We further suggest GlottisNet, a multi-task neural architecture featuring the simultaneous prediction of both, the opening between the vocal folds and the symmetry axis, leading to a huge step forward towards clinical applicability of quantitative, deep learning-assisted laryngeal endoscopy, by fully automating segmentation and midline detection.
CRIS-Team Scopus Importer:2020-12-04

Re-Training of Convolutional Neural Networks for Glottis Segmentation in Endoscopic High-Speed Videos - Döllinger, Michael; Schraut, Tobias; Henrich, Lea A.; Chhetri, Dinesh; Echternach, Matthias; Johnson, Aaron M.; Kunduk, Melda; Maryn, Youri; Patel, Rita R.; Samlan, Robin; Semmler, Marion; Schützenberger, Anne (Applied Sciences, 2022)
Endoscopic high-speed video (HSV) systems for visualization and assessment of vocal fold dynamics in the larynx are diverse and technically advancing. To consider resulting “concepts shifts” for neural network (NN)-based image processing, re-training of already trained and used NNs is necessary to allow for sufficiently accurate image processing for new recording modalities. We propose and discuss several re-training approaches for convolutional neural networks (CNN) being used for HSV image segmentation. Our baseline CNN was trained on the BAGLS data set (58,750 images). The new BAGLS-RT data set consists of additional 21,050 images from previously unused HSV systems, light sources, and different spatial resolutions. Results showed that increasing data diversity by means of preprocessing already improves the segmentation accuracy (mIoU + 6.35%). Subsequent re-training further increases segmentation performance (mIoU + 2.81%). For re-training, finetuning with dynamic knowledge distillation showed the most promising results. Data variety for training and additional re-training is a helpful tool to boost HSV image segmentation quality. However, when performing re-training, the phenomenon of catastrophic forgetting should be kept in mind, i.e., adaption to new data while forgetting already learned knowledge.
CRIS-Team Scopus Importer:2022-10-28
Keywords: catastrophic forgetting; concept shifts; convolutional neural networks; finetuning; glottis; high-speed imaging; medical image segmentation; re-training; voice

Revision eDCR using a superior pedicled mucosal flap - Mueller, Sarina K.; Freitag, Suzanne K.; Lefebvre, Daniel R.; Lee, Nahyoung G.; Bleier, Benjamin S. (Orbit, 2019)
Background: Endoscopic dacryocystorhinostomies (eDCRs) show patency rates between 81% and 94%. However, dacryocystorhinostomy (DCR) failure and the need for revision remain a significant challenge. One of the principal challenges in revision eDCR is the need to surgically identify the correct osteotomy site and maintain long-term patency in the setting of previously instrumented and potentially scarred tissue. At the same time, the surgeon must assume that the blood supply to the commonly described anterior and posteriorly pedicled flaps has been compromised.
CRIS-Team WoS Importer:2019-04-23

Rezidivierende retroaurikuläre Entzündungen - Rupp, Robin; Iro, Heinrich; Hornung, Joachim (Laryngo-Rhino-Otologie, 2020)
CRIS-Team Scopus Importer:2020-06-30

Risk of magnetic resonance imaging-induced magnet dislocation for different types of cochlear implants: a single-center retrospective study - Rupp, Robin; Balk, Matthias; Sievert, Matti; Leibl, Victoria; Schleder, Stephan; Allner, Moritz; Iro, Heinrich; Hoppe, Ulrich; Hornung, Joachim; Gostian, Antoniu-Oreste (Journal of Otolaryngology-Head & Neck Surgery, 2023)
Background: When performing magnetic resonance imaging (MRI) in patients with a cochlear implant (CI), complication rates vary widely in the literature. The primary objective of this retrospective study was to determine the prevalence of complications, in particular magnet dislocation, in patients with CI undergoing 1.5 Tesla (T) MRI. As a secondary objective, the prevalence of magnet dislocation for specific cochlear implant device types was elaborated. Methods: In a single-center retrospective study, all patients with a cochlear implant presenting for an MRI examination at 1.5 T at our institution between January 1st, 2010 and December 31st, 2020 were included. Implants with axial and diametrical magnets were included in the study. MRI safety measures were applied before imaging. The prevalence of complications was evaluated. Magnet dislocation rates were calculated for device types with at least 20 MRI exposures. Results: During the study period, 196 MRI examinations were performed in a total of 128 patients, accounting for 149 different implants (21 implanted bilaterally) with a total of 231 implant exposures to MRI (average 1.69 ± 1.57; min. 1, max. 12). Complications were reported in 50 out of 231 cochlear implant exposures (21.6%). Magnet dislocation occurred in a total of 27 cases (11.7%). Dislocation rates were 29.6% for the Cochlear® CI500 series (24 dislocations from 81 exposures), 1.1% for the Cochlear® CI24RE series (1 from 87) and 0% for the MED-EL® Synchrony (0 from 36). The dislocation rate for the CI500 was significantly higher than for the CI24RE (χ2(1) = 26.86; p < 0.001; ϕ = 0.40) or the Synchrony (χ2(1) = 13.42; p < 0.001; ϕ = 0.34). Conclusions: For 1.5 T MRI, the risk of magnet dislocation ranges from 0 to 29.6% and depends on the CI device type. Implants with a diametrical magnet can be considered potentially MRI-safe, whereas in CIs with axial magnets, the CI500 is at high risk of magnet dislocation. Therefore, apart from a strict indication for an MRI and adherence to safety protocols, post-MRI follow-up examination to rule out magnet dislocation is recommended. Graphical Abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-05-05
Keywords: CI24RE; CI500; Cochlear implant; Complication; Magnet dislocation; Magnet repositioning; Magnetic resonance imaging; Synchrony

Risk stratification of thyroid nodules: Assessing the suitability of ChatGPT for text-based analysis - Sievert, Matti; Conrad, Olaf; Mueller, Sarina K.; Rupp, Robin; Balk, Matthias; Richter, Daniel; Mantsopoulos, Konstantinos; Iro, Heinrich; Koch, Michael (American Journal of Otolaryngology, 2024)
Purpose: Accurate risk stratification of thyroid nodules is essential for optimal patient management. This study aimed to assess the suitability of ChatGPT for risk stratification of thyroid nodules using a text-based evaluation. Methods: A dataset was compiled comprising 50 anonymized clinical reports and associated risk assessments for thyroid nodules. The Chat Generative Pre-trained Transformer (ChatGPT) was used to classify sonographic patterns in accordance with the Thyroid Imaging Reporting and Data System (TI-RADS). The model's performance was assessed using various criteria, including sensitivity, specificity, and accuracy. A comparative analysis was conducted, evaluating the model against investigator-based risk stratification as well as histology. Results: With an overall agreement rate of 42 % in comparison with examiner-based evaluation (TI-RADS 1–5), the results show that ChatGPT has moderate potential for predicting the risk of malignancy in thyroid nodules using text-based reports. The chatbot model achieved a sensitivity of 86.7 %, a specificity of 10.7 %, and an overall accuracy of 68 % when distinguishing between low-risk (TI-RADS 2 and 3) and high-risk (TI-RADS 4 and 5) categories. Interrater reliability was calculated with a Cohen's kappa of 0.686. Conclusion: This study highlights the potential of ChatGPT in assisting clinicians with risk stratification of thyroid nodules. The results suggest that ChatGPT can facilitate personalized treatment decisions, although the agreement rate is still low. Further research and validation studies are necessary to establish the clinical applicability and generalizability of ChatGPT in routine practice. The integration of ChatGPT into clinical workflows has the potential to enhance thyroid nodule risk assessment and improve patient care.
CRIS-Team Scopus Importer:2024-01-19
Keywords: AI; ChatGPT; Risk stratification; Thyroid nodules; Ultrasound

Robust Automatic Evaluation of Intelligibility in Voice Rehabilitation Using Prosodic Analysis - Haderlein, Tino; Schützenberger, Anne; Döllinger, Michael; Nöth, Elmar (Proc. Text, Speech and Dialogue; 20th International Conference, TSD 2017, 2017)
UnivIS-Import:2017-12-18:Pub.2017.tech.IMMD.IMMD5.robust_5
Keywords: Automatic assessment; Intelligibility; Prosody; Reading errors

Role of extracapsular dissection in surgical management of benign parotid tumors - Iro, Heinrich; Zenk, Johannes (JAMA Otolaryngology - Head and Neck Surgery, 2014)
Hypothesis: Extracapsular dissection is a safe and effective surgical technique in the management of benign parotid neoplasms.
EVALuna2:19938

Role of ultrasonography in the detection of a subperiosteal abscess secondary to mastoiditis in pediatric patients - Mantsopoulos, Konstantinos; Wurm, Jochen; Iro, Heinrich; Zenk, Johannes (Ultrasound in Medicine and Biology, 2015)
The aim of the study described here was to evaluate experience in the diagnosis of a subperiosteal abscess secondary to mastoiditis by means of ultrasound. Ten consecutive cases in which an ultrasound examination of the retro-auricular region was performed for suspected mastoiditis were identified. In nine cases, we found a poorly demarcated, inhomogeneous, irregular, poorly perfused lesion abutting the outer table of the cranial vault, with elevation of the outer periosteum and a clearly delineated defect of the cortical layer. In one case, there was additional invasion of the insertion of the sternocleidomastoid muscle on the mastoid process of the temporal bone, raising the suspicion of Bezold mastoiditis. Ultrasound may help in selecting patients for further imaging and might spare computer tomography, especially in sensitive patient groups such as children and pregnant women, if a defect of the outer cortex of the temporal bone can be excluded with certainty.
EVALuna2:19981

ROS-Responsive N-Alkylaminoferrocenes for Cancer-Cell-Specific Targeting of Mitochondria - Reshetnikov, Viktor; Daum, Steffen; Janko, Christina; Karawacka, Weronika; Tietze, Rainer; Alexiou, Christoph; Paryzhak, Solomiya; Dumych, Tetiana; Bilyy, Rostyslav; Tripal, Philipp; Schmid, Benjamin; Palmisano, Ralf; et al. (Angewandte Chemie International Edition, 2018)
Mitochondrial membrane potential is more negative in cancer cells than in normal cells, allowing cancer targeting by delocalized lipophilic cations (DLCs). However, as the difference is rather small, these drugs affect also normal cells. Now a concept of pro-DLCs is proposed based on an N-alkylaminoferrocene structure. These prodrugs are activated by the reaction with reactive oxygen species (ROS) forming ferrocenium-based DLCs. Since ROS are overproduced in cancer, the high-efficiency cancer-cell-specific targeting of mitochondria could be achieved as demonstrated by fluorescence microscopy in combination with two fluorogenic pro-DLCs in vitro and in vivo. We prepared a conjugate of another pro-DLC with a clinically approved drug carboplatin and confirmed that its accumulation in mitochondria was higher than that of the free drug. This was reflected in the substantially higher anticancer effect of the conjugate.
EVALuna2:35451

S100B in serum and saliva: a valid invasive or non-invasive biomarker in obstructive sleep apnea? - Traxdorf, Maximilian; Wendler, O.; Tziridis, Konstantin; Bauer, Judith; Scherl, C. (European Review for Medical and Pharmacological Sciences, 2016)
OBJECTIVE: The aim of this prospective study was to determine whether serum or saliva S100B could be established as an invasive or non-invasive biomarker of cerebrovascular stress due to chronic intermittent hypoxia in obstructive sleep apnea (OSA). PATIENTS AND METHODS: S100B levels in serum and saliva were measured by an enzyme-linked immunosorbent assay (ELISA) in 40 patients with polysomnographically confirmed OSA (n=34) or ronchopathy (n=6) and 20 control subjects (n=20). We also investigated four healthy volunteers (n=4) to determine whether the S100B levels in serum and saliva are dependent on the time of day. RESULTS: Serum S100B was significantly higher in OSA than in healthy control subjects (p=0.007), although it was not related to the severity of OSA and was independent of age, sex, and subjective daytime symptoms. Values of S100B in saliva showed a marked scatter, so there was no significant difference between the OSA group and controls (p=0.62). We did not find that S100B levels in either serum or saliva depended on the time of day (p=0.53; p=0.91). CONCLUSIONS: Serum S100B allows us to discriminate healthy subjects from patients with OSA. However, it does not live up to its promise as a valid invasive predictor of OSA, since it does not correlate with the severity of the disease. Also, S100B in saliva is not suitable for use as a non-invasive biomarker to detect hypoxia-induced cerebrovascular stress in OSA. This finding prevents an S100B saliva-based assessment of risk or possible extent of structural brain damage, ruling out the possibility of non-invasive home monitoring of compliance and therapeutic efficacy in cases of OSA on treatment.
EVALuna2:33219

Safety and efficacy of single cycle induction treatment with cisplatin/docetaxel/ durvalumab/tremelimumab in locally advanced HNSCC: first results of CheckRad-CD8 - Hecht, Markus; Gostian, Antoniu Oreste; Eckstein, Markus; Rutzner, Sandra; Von Der Grün, Jens; Illmer, Thomas; Hautmann, Matthias G.; Klautke, Gunther; Laban, Simon; Brunner, Thomas; Hinke, Axel; Becker, Ina; et al. (Journal for ImmunoTherapy of Cancer, 2020)
BACKGROUND: To determine safety and efficacy of single cycle induction treatment with cisplatin/docetaxel and durvalumab/tremelimumab in stage III-IVB head and neck cancer. METHODS: Patients received a single cycle of cisplatin 30 mg/m² on days 1-3 and docetaxel 75 mg/m² on day 1 combined with durvalumab 1500 mg fix dose on day 5 and tremelimumab 75 mg fix dose on day 5. Patients with pathologic complete response (pCR) in the rebiopsy after induction treatment or at least 20% increase of intratumoral CD8+ cell density in the rebiopsy compared with baseline entered radioimmunotherapy with concomitant durvalumab/tremelimumab. The objective of this interim analysis was to analyze safety and efficacy of the chemoimmunotherapy-induction treatment before radioimmunotherapy. RESULTS: A total of 57 patients were enrolled, 56 were treated. Median pretreatment intratumoral CD8+ cell density was 342 cells/mm². After induction treatment, 27 patients (48%) had a pCR in the rebiopsy and further 25 patients (45%) had a relevant increase of intratumoral CD8+ cells (median increase by a factor of 3.0). Adverse event (AE) grade 3-4 appeared in 38 patients (68%) and mainly consisted of leukopenia (43%) and infections (29%). Six patients (11%) developed grade 3-4 immune-related AE. Univariate analysis computed p16 positivity, programmed death ligand 1 immune cell area and intratumoral CD8+ cell density as predictors of pCR. On multivariable analysis, intratumoral CD8+ cell density predicted pCR independently (OR 1.0012 per cell/mm², 95% CI 1.0001 to 1.0022, p=0.016). In peripheral blood CD8+ cells, the coexpression of programmed death protein 1 significantly increased especially in patients with pCR. CONCLUSIONS: Single cycle induction treatment with cisplatin/docetaxel and durvalumab/tremelimumab is feasible and achieves a high biopsy-proven pCR rate.
CRIS-Team Scopus Importer:2020-10-23
Keywords: CD8-Positive T-lymphocytes; clinical trials; combined modality therapy; head and neck neoplasms; Phase II as topic; radioimmunotherapy

Salicylate-Induced Changes in Hearing Thresholds in Mongolian Gerbils Are Correlated With Tinnitus Frequency but Not With Tinnitus Strength - Lanaia, Veralice; Tziridis, Konstantin; Schulze, Holger (Frontiers in Behavioral Neuroscience, 2021)
Tinnitus is an auditory phantom percept without external sound sources. Despite the high prevalence and tinnitus-associated distress of affected patients, the pathophysiology of tinnitus remains largely unknown, making prevention and treatments difficult to develop. In order to elucidate the pathophysiology of tinnitus, animal models are used where tinnitus is induced either permanently by noise trauma or transiently by the application of salicylate. In a model of trauma-induced tinnitus, we have suggested a central origin of tinnitus-related development of neuronal hyperactivity based on stochastic resonance (SR). SR refers to the physiological phenomenon that weak subthreshold signals for given sensors (or synapses) can still be detected and transmitted if appropriate noise is added to the input of the sensor. The main objective of this study was to characterize the neurophysiological and behavioral effects during salicylate-induced tinnitus and compare these to the conditions within the trauma model. Our data show, in line with the pharmacokinetics, that hearing thresholds generally increase 2 h after salicylate injections. This increase was significantly stronger within the region of best hearing compared to other frequencies. Furthermore, animals showed behavioral signs of tinnitus during that time window and frequency range as assessed by gap prepulse inhibition of the acoustic startle reflex (GPIAS). In contrast to animals with noise trauma-induced tinnitus, salicylate-induced tinnitus animals showed no correlation between hearing thresholds and behavioral signs of tinnitus, indicating that the development of tinnitus after salicylate injection is not based on SR as proposed for the trauma model. In other words, salicylate-induced tinnitus and noise trauma-induced tinnitus are not based on the same neurophysiological mechanism.
CRIS-Team WoS Importer:2021-08-27

Salivary duct carcinoma of the sinonasal cavity: A case report and review of the literature - Müller, Sandra; Mantsopoulos, Konstantinos; Iro, Heinrich; Agaimy, Abbas (Head and Neck-Journal For the Sciences and Specialties of the Head and Neck, 2016)
Salivary duct carcinoma is a rare, aggressive tumor entity first described by Kleinsasser et al in 1968, as a group of malignant salivary gland tumors characterized by duct formation and central necrosis. A case with an unusual localization in the nasal cavity and maxillary sinus is being described in our report.A 60-year-old patient presented with difficulty of nasal breathing and recurrent episodes of epistaxis from the left nasal cavity over the previous 3 months. On endoscopy, a vulnerable lesion in the left inferior nasal meatus could be seen. Biopsy showed salivary duct carcinoma. Treatment consisted of tumor resection by means of a combined endoscopic-osteoplastic surgical approach to the maxillary sinus, bilateral neck dissection, partial parotidectomy, and adjuvant radiochemotherapy.The patient is 6 months after completion of treatment and is free of disease.As salivary duct carcinoma of the sinonasal tract is extremely rare, no therapeutic standards have been developed and treatment essentially is based upon experience with ductal adenocarcinoma of the salivary glands. Surgery therapy should be radical, aiming at eradicating locoregional disease with the role of adjuvant radiotherapy lying in the management of cases with negative prognostic factors. © 2016 Wiley Periodicals, Inc. Head Neck 38:E2464-E2466, 2016.
EVALuna2:6924

Salivary duct stenosis: diagnosis and treatment - Koch, Matthias; Iro, Heinrich (Acta Otorhinolaryngologica Italica, 2017)
The management of stenoses of the major salivary glands had undergone a significant change during the last 15-20 years. Accurate diagnosis forms the basis of adapted minimal invasive therapy. Conventional sialography and MR-sialography are useful examination tools, and ultrasound seems to be a first-line investigational tool if salivary duct stenosis is suspected as cause of gland obstruction. Sialendoscopy is the best choice to establish final diagnosis and characterise the stenosis in order to plan accurate treatment. In all major salivary glands, inflammatory stenosis can be distinguished from fibrotic stenosis. In the parotid duct system, an additional stenosis associated with various abnormalities of the duct system has been reported. Conservative therapy is not sufficient in the majority of cases. The development of a minimally invasive treatment regime, in which sialendoscopy plays a major role, has made the preservation of the gland and its function possible in over 90% of cases. Ductal incision procedures are the most important measure in submandibular duct stenoses, but sialendoscopy becomes more important in the more centrally located stenoses. Sialendoscopic controlled opening and dilation is the dominating method in parotid duct stenoses. In 10-15% of cases, success can be achieved after a combined treatment regime had been applied. This review article aims to give an overview on the epidemiology, diagnostics and current state of the art of the treatment of salivary duct stenoses.
EVALuna2:33183

Salivary gland carcinoma (SGC) with perineural spread and/or positive resection margin - High locoregional control rates after photon (chemo) radiotherapy - Experience from a monocentric analysis - Haderlein, Marlen; Scherl, Claudia; Semrau, Sabine; Lettmaier, Sebastian; Hecht, Markus; Putz, Florian; Iro, Heinrich; Agaimy, Abbas; Fietkau, Rainer (Radiation Oncology, 2019)
Background: The aim was to evaluate the outcome, especially locoregional control of patients with locally advanced salivary gland carcinoma (SGC) with perineural spread (Pn1) and/or positive resection margins (R1/2) after postoperative photon (chemo) radiotherapy in a single centre. Methods: We retrospectively reviewed data of 65 patients with newly diagnosed locally advanced SGC without distant metastases who underwent radio (chemo) therapy in the department of radiation oncology of the university hospital of Erlangen from January 2000 until April 2017. Kaplan Meier method was used to calculate survival and recurrence rates. In univariate analysis the log-rank test was used to correlate patient-/tumor- and treatment-related parameters to survival and recurrence rates. Results: Median follow-up was 45 months (range: 6; 215). After 1, 3, 5 years cumulative incidence of local and locoregional failure was 3.1, 7.0, 7.0% and 3.1, 9.7, 12.9%, whereas cumulative incidence of distant metastases (DM) was 15.6, 36.0, 44.0%. After 1,3, 5 years cumulative Overall (OS) and Disease-free survival (DFS) was 90.5, 74.9, 63.9% and 83.0, 54.8, 49.4%. The only significant predictor for decreased local and locoregional control was a macroscopic resection margin(R2) (p = 0.002 and p = 0.04). High-grade histology (p = 0.006), lymph node metastases with extracapsular spread (p = 0.044) and an advanced T-stage (p = 0.031) were associated with an increased rate of DM. High-grade histology was the only factor predicting for a decreased DFS (p = 0.014). Conclusion: Photon radiotherapy leads to high local and locoregional control rates in a high-risk patient population with SGC with microscopically positive resection margins and/or perineural spread. The most common site of disease recurrence was distant metastases. Therefore the real challenge for the future should be to prevent distant metastases.
CRIS-Team Scopus Importer:2019-05-03
Keywords: Locoregional control; Perineural spread; Photon radiotherapy; Positive resection margin; Salivary gland cancer

Salvage laryngectomy after primary radio- and radiochemotherapy : A retrospective study - Sievert, Matti; Goncalves, Miguel; Binder, Benedicta; Mueller, Sarina K.; Rupp, Robin; Koch, Michael; Dürr, Stephan; Traxdorf, Maximilian; Hecht, Markus; Iro, Heinrich; Gostian, Antoniu-Oreste (HNO, 2021)
BACKGROUND: Recurrent and residual laryngeal cancer after organ-preserving radio- or radiochemotherapy is associated with a poor prognosis. Salvage surgery is the most important therapeutic option in these cases. OBJECTIVE: The study assessed rates of recurrence and residual tumor as well as survival and complication rates after salvage laryngectomy at the authors' academic cancer center. MATERIALS AND METHODS: A retrospective examination of all patients receiving laryngectomy between 2001 and 2019 due to tumor residuals or recurrence after primary radio- and radiochemotherapy was conducted. RESULTS: A total of 33 salvage procedures were performed. Defect reconstruction was performed by free flap surgery in 30.3% (n = 10) and regional flap surgery in 15.2% (n = 5) . One patient received regional flap surgery and free flap surgery simultaneously. Overall survival after 1, 2, and 5 years was 68.7, 47.9, and 24.2%, and disease-free survival was 81.6, 47.8, and 24.2%, respectively, with 48.5% (n = 16) postoperative tumor recurrences overall. Disease-free survival was significantly shorter for tumor extension into or onto the hypopharynx (p = 0.041). Postoperatively, 72.7% of patients developed a pharyngocutaneous fistula, of which 24.2% required surgical treatment. The hospital stay was 28.0 ± 16.1 days. CONCLUSION: Salvage laryngectomy is associated with a high rate of treatable complications and high morbidity. Nevertheless, considering the advanced tumor stages treated, it allows for respectable oncological results.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Laryngeal neoplasms; Postoperative complications; Recurrence; Salvage therapy; Treatment outcome

Salvage-Laryngektomie nach primärer Radio- und Radiochemotherapie: Eine retrospektive Fallzusammenfassung - Sievert, Matti; Goncalves, Miguel; Binder, Benedicta; Mueller, Sarina K.; Rupp, Robin; Koch, Michael; Dürr, Stephan; Traxdorf, Maximilian; Hecht, Markus; Iro, Heinrich; Gostian, Antoniu-Oreste (HNO, 2021)
Background: Recurrent and residual laryngeal cancer after organ-preserving radio- or radiochemotherapy is associated with a poor prognosis. Salvage surgery is the most important therapeutic option in these cases. Objective: The study assessed rates of recurrence and residual tumor as well as survival and complication rates after salvage laryngectomy at the authors’ academic cancer center. Materials and methods: A retrospective examination of all patients receiving laryngectomy between 2001 and 2019 due to tumor residuals or recurrence after primary radio- and radiochemotherapy was conducted. Results: A total of 33 salvage procedures were performed. Defect reconstruction was performed by free flap surgery in 30.3% (n = 10) and regional flap surgery in 15.2% (n = 5). One patient received regional flap surgery and free flap surgery simultaneously. Overall survival after 1, 2, and 5 years was 68.7, 47.9, and 24.2%, and disease-free survival was 81.6, 47.8, and 24.2%, respectively, with 48.5% (n = 16) postoperative tumor recurrences overall. Disease-free survival was significantly shorter for tumor extension into or onto the hypopharynx (p = 0.041). Postoperatively, 72.7% of patients developed a pharyngocutaneous fistula, of which 24.2% required surgical treatment. The hospital stay was 28.0 ± 16.1 days. Conclusion: Salvage laryngectomy is associated with a high rate of treatable complications and high morbidity. Nevertheless, considering the advanced tumor stages treated, it allows for respectable oncological results.
CRIS-Team Scopus Importer:2021-04-23
Keywords: Laryngeal neoplasms; Postoperative complications; Recurrence; Salvage therapy; Treatment outcome

Sample collection for laboratory-based study of the nasal airway and sinuses: a research compendium - Massey, Conner J.; Del Valle, Fernando Diaz; Abuzeid, Waleed M.; Levy, Joshua M.; Mueller, Sarina K.; Levine, Corrina G.; Smith, Stephanie S.; Bleier, Benjamin S.; Ramakrishnan, Vijay R. (International Forum of Allergy and Rhinology, 2019)
Background Collection of biologic samples from the nasal cavity and paranasal sinuses is of critical importance to the study of infectious or inflammatory conditions that affect both upper and lower airways. Numerous techniques for the study of ex-vivo samples exist, with specific applications, strengths, and weaknesses associated with each of them. In this compendium we summarize the available methods for collection of primary human samples and incorporate expert discussion of the pros, cons, and applications associated with each technique. Methods An expert panel containing members of the American Rhinologic Society's Research and Grants Committee compiled this educational reference. Rationale for use and the potential advantages and disadvantages are discussed. Research protocols and key references are enumerated. Results Sampling of the nasal cavity and paranasal sinuses can be achieved through a number of methods. Nonspecific sinonasal secretions may be collected via forced exhalation, nasal lavage, and nasal spray aspiration. Targeted collection of sinonasal secretions may be achieved via endoscopic placement of absorbent matrices. Nasal cytology or collection of superficial epithelium may be completed via brushing or scraping of endonasal structures. Collection of mucosal biopsies may be completed via sinonasal explant or full-thickness biopsy. Conclusion Multiple sampling techniques are available to collect biologic samples from the sinonasal cavity. These techniques differ in their ease of application, reproducibility, sample yield, and utility for different sinonasal pathologies or research goals. An appreciation of the benefits and drawbacks of each approach will allow investigators to select the techniques most appropriate for achieving research objectives.
CRIS-Team WoS Importer:2019-12-27

Sarcopenia and frailty: A clinician's controversial point of view - Bauer, Judith; Sieber, Cornel (Experimental Gerontology, 2008)
Sarcopenia and frailty are both highly relevant entities with regard to functionality and independence in the elderly. The term sarcopenia has been introduced already in the late 80s and since then attracted the interest of many researchers, the majority being interested in its pathophysiology. Nevertheless there is still no consensus on the definition of sarcopenia and its diagnosis. Despite its relevance for functionality and autonomy most clinicians caring for the elderly are not familiar with sarcopenia and it has not become part of the routine geriatric evaluation.The concept of frailty has recently been supported by the introduction of two new working definitions. Since then clinical research on frailty has steeply increased. The influence of frailty on different age-associated diseases has been investigated and populations at risk for complications of medical or operative therapy are identified with the help of this concept. Simultaneously the pathophysiologic mechanisms involved in the development of frailty are explored.While sarcopenia may be regarded as a clinical sign that is not specific for the elderly, frailty may be seen as a multidimensional geriatric syndrome which implies a greater relevance for the clinician than the one dimensional approach of sarcopenia. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: sarcopenia; frailty; definition; diagnosis; pathophysiology

Sarcopenia in Nursing Home Residents - Bauer, Judith; Kaiser, Matthias; Sieber, Cornel (Journal of the American Medical Directors Association, 2008)
The age-associated loss of muscle mass and muscle strength described by the term sarcopenia is highly relevant for functionality among nursing home residents. Nevertheless, the scientific literature concentrating on sarcopenia in this population is scarce. For practical reasons, common definitions of this entity, which rely on dual energy x-ray absorptiometry (DEXA) and bioimpedance analysis (BIA), cannot be applied in this setting. Anthropometric measurements like arm muscle circumference and calf circumference seem to be most suitable. Handgrip may be used as an alternative. Prevalence data show a wide range but are mostly high. There is a close association of the degree of sarcopenia with dependence among residents. The pathophysiology of sarcopenia in this population is strongly influenced by comorbidity and often there is significant overlap with the cachexia syndrome.At present, physical exercise is regarded to be the most promising therapeutic option, with resistance training being superior to endurance programs. Physical exercise has been successful even among Alzheimer patients and physically restrained residents. It has to be accompanied by the provision of adequate and diverse meals based on individual energy and nutrient requirements. Special attention should be paid to the treatment of vitamin D deficiency if present. New therapeutic options include Whole Body Vibration, oral supplements with essential amino acids and leucine, ACE-inhibitors, and cytokine-modifying drugs.
Keywords: Sarcopenia; nursing home; pathophysiology; diagnosis; treatment

Satellite nodules in pleomorphic adenomas of the parotid gland: A nightmare for less invasive parotid surgery? - Iro, Ann Kristin; Agaimy, Abbas; Mueller, Sarina K.; Sievert, Matti; Iro, Heinrich; Mantsopoulos, Konstantinos (Oral Oncology, 2021)
Objectives: The aim of this study was to thoroughly investigate the incidence of satellite nodules (SN) and some of their characteristics (number, distance to main lesion) in a large series of pleomorphic adenomas (PA) and to compare several surgical modalities regarding their efficacy in addressing this critical morphological feature. Materials and methods: The records of all patients treated for primary PA of the parotid gland between 2006 and 2020 were studied retrospectively. All the histological slides of all tumours were critically re-evaluated for this study by an experienced head and neck pathologist. Results: 845 cases made up our initial study sample. SNs were detected in 68/845 cases (8%). No statistically significant difference could be detected in the incidence of SNs in the surgical specimens between the patient groups managed by extracapsular dissection (46/577, 7.9%) and facial nerve dissecting surgery (22/268, 8.2%, p = 0.502). In the group of cases with SNs, no recurrences were detected (mean follow-up time: 71.4 months). The mean distance from the main lesion to the most distant SN was 1.1 mm (0.08–6.3 mm). The mean size of the SN was 1.9 mm (0.1–9.7 mm). Altogether, the mean distance from the main lesion to the outer periphery of the most distant SN was 3.1 mm (0.4–10.5 mm). Conclusion: Our analysis could not award SNs the title of an “extracapsular dissection's nightmare”. In the majority of cases, their favourable histological patterns offer the ideal circumstances for their surgical inclusion in a tumour specimen.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Capsule; Extracapsular dissection; Parotidectomy; Pleomorphic adenoma; Satellite nodule

Scavenging of bacteria or bacterial products by magnetic particles functionalized with a broad-spectrum pathogen recognition receptor motif offers diagnostic and therapeutic applications - Friedrich, Bernhard; Lyer, Stefan; Janko, Christina; Unterweger, Harald; Brox, Regine; Cunningham, Sarah; Dutz, Silvio; Taccardi, Nicola; Bikker, Floris J.; Hurle, Katrin; Sebald, Heidi; Lenz, Malte; et al. (Acta Biomaterialia, 2022)
Sepsis is a dysregulated host response of severe bloodstream infections, and given its frequency of occurrence and high mortality rate, therapeutic improvements are imperative. A reliable biomimetic strategy for the targeting and separation of bacterial pathogens in bloodstream infections involves the use of the broad-spectrum binding motif of human GP-340, a pattern-recognition receptor of the scavenger receptor cysteine rich (SRCR) superfamily that is expressed on epithelial surfaces but not found in blood. Here we show that these peptides, when conjugated to superparamagnetic iron oxide nanoparticles (SPIONs), can separate various bacterial endotoxins and intact microbes (E. coli, S. aureus, P. aeruginosa and S. marcescens) with high efficiency, especially at low and thus clinically relevant concentrations. This is accompanied by a subsequent strong depletion in cytokine release (TNF, IL-6, IL-1β, Il-10 and IFN-γ), which could have a direct therapeutic impact since escalating immune responses complicates severe bloodstream infections and sepsis courses. SPIONs are coated with aminoalkylsilane and capture peptides are orthogonally ligated to this surface. The particles behave fully cyto- and hemocompatible and do not interfere with host structures. Thus, this approach additionally aims to dramatically reduce diagnostic times for patients with suspected bloodstream infections and accelerate targeted antibiotic therapy. Statement of significance: Sepsis is often associated with excessive release of cytokines. This aspect and slow diagnostic procedures are the major therapeutic obstacles. The use of magnetic particles conjugated with small peptides derived from the binding motif of a broad-spectrum mucosal pathogen recognition protein GP-340 provides a highly efficient scavenging platform. These peptides are not found in blood and therefore are not subject to inhibitory mechanisms like in other concepts (mannose binding lectine, aptamers, antibodies). In this work, data are shown on the broad bacterial binding spectrum, highly efficient toxin depletion, which directly reduces the release of cytokines. Host cells are not affected and antibiotics not adsorbed. The particle bound microbes can be recultured without restriction and thus be used directly for diagnostics.
CRIS-Team Scopus Importer:2022-03-11
Keywords: GP-340; Magnetic nanoparticles; Pathogen binding; Sepsis; SRCR domain

Schlafstadienbestimmung mit Hilfe bewegungsbasierter Sensortechnologie - Traxdorf, Maximilian; Gradl, Stefan; Kugler, Patrick; Leutheuser, Heike; Lauten, Juliane; Eskofier, Björn; Angerer, Florian; Iro, Heinrich (Proceedings of the 84th Annual Meeting of the German Society of Oto-Rhino-Laryngology, Head and Neck Surgery, 2013)

Secondary Tracheoesophageal Puncture After Laryngectomy Increases Complications With Shunt and Voice Prosthesis - Scherl, Claudia; Kauffels, Julia; Schützenberger, Anne; Döllinger, Michael; Bohr, Christopher; Dürr, Stephan; Fietkau, Rainer; Haderlein, Marlen; Koch, Michael; Traxdorf, Maximilian; Mantsopoulos, Konstantinos; Mueller, Sarina K.; et al. (Laryngoscope, 2020)
Objectives/Hypothesis To evaluate the demographics, clinical features, management, and prognostic indicators of tracheoesophageal puncture complications in patients undergoing placement of voice prosthesis following cancer treatment.
CRIS-Team WoS Importer:2020-02-21

Selection of potential iron oxide nanoparticles for breast cancer treatment based on in vitro cytotoxicity and cellular uptake - Poller, Johanna; Zaloga, Jan; Schreiber, Eveline; Unterweger, Harald; Janko, Christina; Radon, Patricia; Eberbeck, Dietmar; Trahms, Lutz; Alexiou, Christoph; Friedrich, Ralf P. (International Journal of Nanomedicine, 2017)
Superparamagnetic iron oxide nanoparticles (SPIONs) are promising tools for the treatment of different diseases. Their magnetic properties enable therapies involving magnetic drug targeting (MDT), hyperthermia or imaging. Depending on the intended treatment, specific characteristics of SPIONs are required. While particles used for imaging should circulate for extended periods of time in the vascular system, SPIONs intended for MDT or hyperthermia should be accumulated in the target area to come into close proximity of, or to be incorporated into, specific tumor cells. In this study, we determined the impact of several accurately characterized SPION types varying in size, zeta potential and surface coating on various human breast cancer cell lines and endothelial cells to identify the most suitable particle for future breast cancer therapy. We analyzed cellular SPION uptake, magnetic properties, cell proliferation and toxicity using atomic emission spectroscopy, magnetic susceptometry, flow cytometry and microscopy. The results demonstrated that treatment with dextran-coated SPIONs (SPIONDex) and lauric acid-coated SPIONs (SPIONLA) with an additional protein corona formed by human serum albumin (SPIONLA-HSA) resulted in very moderate particle uptake and low cytotoxicity, whereas SPIONLAhad in part much stronger effects on cellular uptake and cellular toxicity. In summary, our data show significant dose-dependent and particle type-related response differences between various breast cancer and endothelial cells, indicating the utility of these particle types for distinct medical applications.
EVALuna2:33205

Sensory cortex lesion triggers compensatory neuronal plasticity - Depner, Manfred; Tziridis, Konstantin; Heß, Andreas; Schulze, Holger (BMC Neuroscience, 2014)
Lesions to the human brain often cause dramatic impairments in the life of patients because of the very limited capacity of the mammalian nervous system to regenerate. On the other hand, neuronal tissue has a high capacity to reorganize itself so that loss of function due to brain damage may be compensated through neuroplastic reorganization of undamaged tissue in brain regions adjacent or contralateral to the lesion site. In this study we investigated the effect of serial lesions of the auditory cortices (AC) in both hemispheres of Mongolian gerbils on discrimination performance for fast amplitude modulated tones (AM). Healthy animals were trained to discriminate two fast AM, an ability that has previously been shown to critically depend on cortical processing. Their ability to maintain significant discrimination performance was retested after unilateral AC lesion, and again after lesion of the contralateral AC, with 15 days of continuing training in between the two lesions.After bilateral cortical ablation of both AC and 45 days of training the animals show no change in pure tone detection threshold as measured with modulation of the acoustic startle reflex which has been shown to rely on subcortical structures. In contrast to simultaneous bilateral ablation of AC that results in complete loss of AM discrimination ability in this paradigm we found compensatory plasticity that seems to be triggered by unilateral cortical ablation with subsequent training and that is able to almost fully compensate for the lost cortical functions.Our results demonstrate that AM discrimination ability that normally depends on AC may be transferred to other brain regions when the brain has time to activate compensatory plasticity between the lesions of the two AC hemispheres. For this process to take place obviously one intact AC hemisphere is needed. This finding may open perspectives for new therapeutic strategies that may alleviate the impairments after multiple ischemic strokes.
EVALuna2:8518

Severe Chronic Upper Airway Disease (SCUAD) in children. Definition issues and requirements - Karatzanis, A.; Kalogjera, L.; Scadding, G.; Velegrakis, S.; Kawauchi, H.; Cingi, C.; Prokopakis, E. (International Journal of Pediatric Otorhinolaryngology, 2015)
Upper airway diseases are extremely common, and a significant proportion of patients are not adequately controlled by contemporary treatment algorithms. The term SCUAD (Severe Chronic Upper Airway Disease) has been previously introduced to describe such cases. However, this term has not been adequately focused on children.This study aims to address the necessity of the term, as well as further details specifically for children. For this purpose, a review was performed of the current literature, with specific focus on issues regarding SCUAD in children.Paediatric SCUAD represents a heterogeneous group of patients and has significant clinical and socioeconomic implications. Relevant literature is generally lacking and questions regarding definition and pathogenesis remain unanswered.Accurate definition and acknowledgement of paediatric SCUAD cases may lead to better design of future clinical and molecular research protocols. This may provide improved understanding of the underlying disease processes, more accurate data regarding socioeconomic burden, and, above all, more successful treatment and prevention strategies.
EVALuna2:19994

SFTA3, a novel protein of the lung: three-dimensional structure, characterisation and immune activation - Schicht, Martin; Rausch, Felix; Finotto, Susetta; Mathews, Martina; Mattil, Anja; Schubert, Melanie; Koch, Beate; Traxdorf, Maximilian; Bohr, Christopher; Worlitzsch, Dieter; Brandt, Wolfgang; Garreis, Fabian; et al. (European Respiratory Journal, 2014)
The lung constantly interacts with numerous pathogens. Thus, complex local immune defence mechanisms are essential to recognise and dispose of these intruders. This work describes the detection, characterisation and three-dimensional structure of a novel protein of the lung (surfactant-associated protein 3 (SFTA3/SP-H)) with putative immunological features. Bioinformatics, biochemical and immunological methods were combined to elucidate the structure and function of SFTA3. The tissue-specific detection and characterisation was performed by using electron microscopy as well as fluorescence imaging. Three-dimensional structure generation and analysis led to the development of specific antibodies and, as a consequence, to the localisation of a novel protein in human lung under consideration of cystic fibrosis, asthma and sepsis. In vitro experiments revealed that lipopolysaccharide induces expression of SFTA3 in the human lung alveolar type II cell line A549. By contrast, the inflammatory cytokines interleukin (IL)-1? and IL-23 inhibit expression of SFTA3 in A549. Sequence- and structure-based prediction analysis indicated that the novel protein is likely to belong to the family of lung surfactant proteins. The results suggest that SFTA3 is an immunoregulatory protein of the lung with relevant protective functions during inflammation at the mucosal sites.
EVALuna2:4400

Shedding Light on Metal-Based Nanoparticles in Zebrafish by Computed Tomography with Micrometer Resolution - Corek, Emre; Rodgers, Griffin; Siegrist, Stefan; Einfalt, Tomaz; Detampel, Pascal; Schleputz, Christian M.; Sieber, Sandro; Fluder, Pascal; Schulz, Georg; Unterweger, Harald; Alexiou, Christoph; Mueller, Bert; et al. (Small, 2020)
Metal-based nanoparticles are clinically used for diagnostic and therapeutic applications. After parenteral administration, they will distribute throughout different organs. Quantification of their distribution within tissues in the 3D space, however, remains a challenge owing to the small particle diameter. In this study, synchrotron radiation-based hard X-ray tomography (SRμCT) in absorption and phase contrast modes is evaluated for the localization of superparamagnetic iron oxide nanoparticles (SPIONs) in soft tissues based on their electron density and X-ray attenuation. Biodistribution of SPIONs is studied using zebrafish embryos as a vertebrate screening model. This label-free approach gives rise to an isotropic, 3D, direct space visualization of the entire 2.5 mm-long animal with a spatial resolution of around 2 µm. High resolution image stacks are available on a dedicated internet page (http://zebrafish.pharma-te.ch). X-ray tomography is combined with physico-chemical characterization and cellular uptake studies to confirm the safety and effectiveness of protective SPION coatings. It is demonstrated that SRμCT provides unprecedented insights into the zebrafish embryo anatomy and tissue distribution of label-free metal oxide nanoparticles.
CRIS-Team Scopus Importer:2020-07-03
Keywords: digital histology; nanoparticle detection; superparamagnetic iron oxide nanoparticles; synchrotron radiation-based micro computed tomography; zebrafish embryos

Shell matters: Magnetic targeting of SPIONs and in vitro effects on endothelial and monocytic cell function - Matuszak, Jasmin; Doerfler, Philipp; Zaloga, Jan; Unterweger, Harald; Lyer, Stefan; Dietel, Barbara; Alexiou, Christoph; Cicha, Iwona (Clinical Hemorheology and Microcirculation, 2015)
Superparamagnetic iron oxide nanoparticles (SPIONs) are versatile and easily functionalized agents with high potential for diagnostic and therapeutic intravascular applications. In this study, we analyzed the responses of endothelial (ECs) and monocytic cells to three different types of SPIONs, in order to assess the influence of physico-chemical properties on the biological reactions to SPIONs. The following formulations were used: (1) Lauric acid-coated and BSA-stabilized SPION-1,(2) Lauric acid/BSA-coated SPION-2 and (3) dextran-coated SPION-3. SPION-1 were strongly internalized by ECs and reduced their viability in static conditions. Additionally, they had a dose-dependent inhibitory effect on monocytic cell chemotaxis to MCP-1, but did not affect monocytic cell recruitment by ECs. SPION-2 uptake was less pronounced, both in ECs and monocytic cells, and these particles were better tolerated by the vascular cells. Not being internalized by endothelial or monocytic cells, SPION-3 did not induce relevant effects on cell viability, motility or endothelial-monocytic cell interactions.Taken together, localized accumulation of circulating SPION under physiologic-like flow conditions and their cellular uptake depends on the physicochemical characteristics. Our findings suggest that SPION-2 are suitable for magnetic targeting of atherosclerotic plaques. Due to their excellent biocompatibility and low internalization, SPION-3 may represent a suitable imaging agent for intravascular applications.
EVALuna2:12025

Shifting cancer care towards Multidisciplinarity: the cancer center certification program of the German cancer society - Kowalski, Christoph; Graeven, Ullrich; Von Kalle, Christof; Lang, Hauke; Beckmann, Matthias; Blohmer, Jens-Uwe; Burchardt, Martin; Ehrenfeld, Michael; Fichtner, Jan; Grabbe, Stephan; Hoffmann, Hans; Iro, Heinrich; et al. (BMC Cancer, 2017)
BACKGROUND: Over the last decades numerous initiatives have been set up that aim at translating the best available medical knowledge and treatment into clinical practice. The inherent complexity of the programs and discrepancies in the terminology used make it difficult to appreciate each of them distinctly and compare their specific strengths and weaknesses. To allow comparison and stimulate dialogue between different programs, we in this paper provide an overview of the German Cancer Society certification program for multidisciplinary cancer centers that was established in 2003. MAIN BODY: In the early 2000s the German Cancer Society assessed the available information on quality of cancer care in Germany and concluded that there was a definite need for a comprehensive, transparent and evidence-based system of quality assessment and control. This prompted the development and implementation of a voluntary cancer center certification program that was promoted by scientific societies, health-care providers, and patient advocacy groups and based on guidelines of the highest quality level (S3). The certification system structures the entire process of care from prevention to screening and multidisciplinary treatment of cancer and places multidisciplinary teams at the heart of this program. Within each network of providers, the quality of care is documented using tumor-specific quality indicators. The system started with breast cancer centers in 2003 and colorectal cancer centers in 2006. In 2017, certification systems are established for the majority of cancers. Here we describe the rationale behind the certification program, its history, the development of the certification requirements, the process of data collection, and the certification process as an example for the successful implementation of a voluntary but powerful system to ensure and improve quality of cancer care. CONCLUSION: Since 2003, over 1 million patients had their primary tumors treated in a certified center. There are now over 1200 sites for different tumor entities in four countries that have been certified in accordance with the program and transparently report their results from multidisciplinary treatment for a substantial proportion of cancers. This led to a fundamental change in the structure of cancer care in Germany and neighboring countries within one decade.
EVALuna2:33190

Short-term safety and effectiveness of the mCLIP partial prosthesis - Rasse, Thomas; Niederwanger, Lisa; Hornung, Joachim; Taha, Lava; Arndt, Susan; Offergeld, Christian; Beutner, Dirk; Bevis, Nicholas; Lenarz, Thomas; Teschner, Magnus; Schimanski, Esther; Georg Sprinzl,; et al. (European Archives of Oto-Rhino-Laryngology, 2023)
Purpose: This multicentric, retrospective study aimed to analyze the short-term safety and effectiveness of the mCLIP Partial Prosthesis. Methods: Patients underwent tympanoplasty with implantation of a mCLIP Partial Prosthesis. Follow-up examination included ear microscopy and pure-tone audiometry to determine the post-operative pure tone average of the frequencies 0.5, 1, 2 and 3 kHz (PTA4). The post-operative PTA4 air bone gap (ABG) was used to evaluate the audiological outcome. A post-operative minimum and maximum follow-up period was not defined. Thus, the follow-up times of each study center were different, which resulted in different follow-up times for the audiological analysis and for adverse events (AE). Results: 72 (66 adults, 6 children) patients were implanted with the mCLIP Partial Prosthesis. 68 (62 adults, 6 children) patients underwent audiological examination; all 72 patients were examined for adverse events. All patients (N = 68): 72.1% of the patients showed a PTA4 ABG of ≤ 20 dB. Individual post-operative bone conduction (BC) PTA4 thresholds were stable in 67 patients. The mean post-operative follow-up time was 78 ± 46 days. Children (N = 6): 5 out of 6 children showed a PTA4 ABG of ≤ 20 dB. None of the children reported a BC PTA4 deterioration of > 10 dB HL after the implantation. The mean post-operative follow-up time was 101 ± 45 days. Adverse events (all patients, N = 72): 15 (14 adults, 1 child) patients had AEs (27 AEs and 2 Follow-Ups). The mean post-operative follow-up time was 375 days. Conclusion: Clinical data show satisfactory audiological parameters after implantation of the mCLIP Partial Prosthesis. The prosthesis is safe and effective for implantation in children and adults. Trial registration number: NCT05565339, 09 September 2022, retrospectively registered.
CRIS-Team Scopus Importer:2023-12-29
Keywords: Hearing restoration; mCLIP partial prosthesis; Ossiculoplasty; Passive middle ear implant

Sialendoscopy in Sialolithiasis - Iro, Heinrich (HNO, 2017)
EVALuna2:33176

Sialylation of anti-histone immunoglobulin G autoantibodies determines their capabilities to participate in the clearance of late apoptotic cells - Magorivska, I.; Munoz Becerra, Luis; Janko, Christina; Dumych, Tetiana; Rech, J.; Schett, Georg; Nimmerjahn, Falk; Bilyy, R.; Herrmann, Martin (Clinical and Experimental Immunology, 2016)
The Fc portion of immunoglobulin (Ig)G harbours a single glycosylation site. Glycan sialylation is critical for structure and for certain effector functions of IgG. Anti-histone IgG of patients with systemic lupus erythematosus is reportedly responsible for the recruitment of polymorphonuclear cells (PMN) to the clearance of apoptotic cells. Autoantibodies decorating secondary necrotic cells (SNEC) induce proinflammatory responses after activation of blood-borne phagocytes. Analysing the sialylation status of affinity-purified anti-histone IgG in patients with systemic lupus erythematosus (SLE), we demonstrated that the anti-histone IgG was contained preferentially in the non-sialylated fraction. In functional ex-vivo phagocytosis studies, non-sialylated anti-SNEC IgG directed SNEC preferentially into PMN but did not change their cytokine secretion profiles. In contrast, sialylated IgG reduced the phagocytosis by monocytes of SNEC. Moreover, the sialylated anti-SNEC IgG was not simply anti-inflammatory, but switched the cytokine secretion profiles from interleukin (IL)-6/IL-8 to tumour necrosis factor (TNF)-/IL-1. Here we describe how different sialylation statuses of IgG autoantibodies contribute to the complex inflammatory network that regulates chronic inflammation.
Keywords: autoantibodies; IgG; lectin; sialylation; SLE

Significant polyomic and functional upregulation of the PAPP-A/IGFBP-4/5/IGF-1 axis in chronic rhinosinusitis with nasal polyps - Mueller, Sarina K.; Nocera, Angela L.; Workman, Alan; Ubermann, Towia; Dillon, Simon T.; Stegmann, Achim; Wurm, Jochen; Iro, Heinrich; Wendler, Olaf; Bleier, Benjamin S. (International Forum of Allergy and Rhinology, 2020)
BACKGROUND: Chronic rhinosinusitis with nasal polyps (CRSwNP) is associated with epithelial expansion and polyp survival. However, the molecular mechanism of this aberrant proliferation is unclear. The purpose of this study was to interrogate derangements of the pappalysin-A/insulin-like growth factor binding protein/insulin-like growth factor-1 (PAPP-A/IGFBP-4/5/IGF-1 axis) as a major contributing factor to polyp growth in CRSwNP. METHODS: Matched tissue and exosomal proteomic arrays including PAPP-A, IGFBP-4, IGFBP-5, and IGF-1 were quantified using aptamer-based methods/Western blots for proteomic analysis and whole-transcriptome sequencing/quantitative polymerase chain reaction (qPCR) for transcriptomic analysis in CRSwNP and control patients. Functional PAPP-A assays were then performed in both tissue and exosomes (set 1: n = 20 per group; validation set 2: n = 26 per group). RESULTS: Tissue and exosomal PAPP-A was significantly overexpressed in CRSwNP compared to controls on both a transcriptomic and proteomic level (p < 0.0001). Known inhibitors of PAPP-A (stanniocalcin-1/-2) were significantly downregulated (p < 0.0001) as were PAPP-A cleavage products (IGFBP-5 p < 0.0001). PAPP-A function was shown to be increased 5-fold to 6-fold in tissue and exosomes. CONCLUSION: Upregulated tissue and exosomal PAPP-A signaling is significantly associated with CRSwNP and may be an important factor in the promotion of epithelial proliferation and polyp growth. These data lend further support to the emerging concept of exosomal functional and polyomic analyses as a method to study sinonasal pathology.
EVALuna2:209860

Silent sinus syndrome: Reduction of surgical invasiveness in an underdiagnosed clinical entity - Mantsopoulos, Konstantinos; Thimsen, Vivian; Karkos, Petros; Sievert, Matti; Iro, Heinrich; Constantinidis, Jannis (American Journal of Otolaryngology, 2022)
Objective: The aim of this study was to investigate our experience in the management of silent sinus syndrome. Material and methods: The records of all patients treated for silent sinus syndrome between 2011 and 2021 were evaluated retrospectively. Data were collected on epidemiological parameters (age, gender), referral specialty, imaging findings, surgical approach, and management. Results: In total, nine cases made up our final study sample (5 men, 4 women; male-female ratio 1:0.8). Their mean age was 39 years (range: 19–71 years). Besides the typical imaging findings (orbital floor depression, maxillary sinus atelectasis with ostium occlusion), lateralization of the uncinate process could be seen in seven cases (77.8 %) and ipsilateral septal deviation in six cases (66.6 %). Four cases were managed by means of middle meatal antrostomy and five with additional reconstruction of the orbital floor (transconjuctival approach in two cases, endonasal endoscopic approach in three cases). Enopthalmus recovered in all cases; diplopia (3 cases) recovered completely in two cases and partly in one case. Conclusion: Reduced surgical invasiveness in silent sinus syndrome, with management of the cause (maxillary sinus hypoventilation) and the sequel (orbital floor depression) using the same endoscopic approach, is associated with an acceptable clinical outcome.
CRIS-Team Scopus Importer:2022-07-08
Keywords: Diplopia; Maxillary sinus atelectasis; Orbital floor; Reconstruction; Silent sinus

Simulated transient hearing loss improves auditory sensitivity - Krauß, Patrick; Tziridis, Konstantin (Scientific Reports, 2021)
Recently, it was proposed that a processing principle called adaptive stochastic resonance plays a major role in the auditory system, and serves to maintain optimal sensitivity even to highly variable sound pressure levels. As a side effect, in case of reduced auditory input, such as permanent hearing loss or frequency specific deprivation, this mechanism may eventually lead to the perception of phantom sounds like tinnitus or the Zwicker tone illusion. Using computational modeling, the biological plausibility of this processing principle was already demonstrated. Here, we provide experimental results that further support the stochastic resonance model of auditory perception. In particular, Mongolian gerbils were exposed to moderate intensity, non-damaging long-term notched noise, which mimics hearing loss for frequencies within the notch. Remarkably, the animals developed significantly increased sensitivity, i.e. improved hearing thresholds, for the frequency centered within the notch, but not for frequencies outside the notch. In addition, most animals treated with the new paradigm showed identical behavioral signs of phantom sound perception (tinnitus) as animals with acoustic trauma induced tinnitus. In contrast, animals treated with broadband noise as a control condition did not show any significant threshold change, nor behavioral signs of phantom sound perception.
CRIS-Team Scopus Importer:2021-08-06

Simulation and experimental validation of magnetic nanoparticle accumulation in a bloodstream mimicking flow system - Reinelt, Magdalena; Ahlfs, Johannes; Stein, René; Alexiou, Christoph; Bänsch, Eberhard; Friedrich, Ralf P.; Lyer, Stefan; Neuß, Maria; Neuß, Nicolas (Journal of Magnetism and Magnetic Materials, 2023)
In this paper, a mathematical model for the dynamics of superparamagnetic iron oxide nanoparticles (SPIONs) in a laminar flow through a pipe under the influence of an external magnetic field of a single electromagnet is derived. The model consists of a convection–diffusion equation coupled with magnetostatic equations. The accumulation of particles along the boundary is modeled with the help of a surface concentration. Based on experimental data describing the retention of lauric acid coated SPIONs in a tubular flow under the influence of a magnetic field, the model is parametrized and finite element simulations are performed. With the exception of one outlier at low SPION concentration and high flowspeed, the simulation results agree very well with the experimental measurements within the bounds of the measurement error.
CRIS-Team Scopus Importer:2023-07-28
Keywords: Convection–diffusion equation; Finite element method (FEM); Magnetic drug targeting (MDT); Magnetic force on nanoparticles; Particle accumulation; Superparamagnetic nanoparticle (SPION)

Simulation based estimation of dynamic mechanical properties for viscoelastic materials used for vocal fold models - Rupitsch, Stefan; Ilg, Jürgen; Sutor, Alexander; Lerch, Reinhard; Döllinger, Michael (Journal of Sound and Vibration, 2011)
In order to obtain a deeper understanding of the human phonation process and the mechanisms generating sound, realistic setups are built up containing artificial vocal folds. Usually, these vocal folds consist of viscoelastic materials (e.g., polyurethane mixtures). Reliable simulation based studies on the setups require the mechanical properties of the utilized viscoelastic materials. The aim of this work is the identification of mechanical material parameters (Young's modulus, Poisson's ratio, and loss factor) for those materials. Therefore, we suggest a low-cost measurement setup, the so-called vibration transmission analyzer (VTA) enabling to analyze the transfer behavior of viscoelastic materials for propagating mechanical waves. With the aid of a mathematical Inverse Method, the material parameters are adjusted in a convenient way so that the simulation results coincide with the measurement results for the transfer behavior. Contrary to other works, we determine frequency dependent functions for the mechanical properties characterizing the viscoelastic material in the frequency range of human speech (100-250 Hz). The results for three different materials clearly show that the Poisson's ratio is close to 0.5 and that the Young's modulus increases with higher frequencies. For a frequency of 400 Hz, the Young's modulus of the investigated viscoelastic materials is approximately 80% higher than for the static case (0 Hz). We verify the identified mechanical properties with experiments on fabricated vocal fold models. Thereby, only small deviations between measurements and simulations occur. (C) 2011 Elsevier Ltd. All rights reserved.

Simulation of Sound Radiation based on PIV Measurements - Lodermeyer, Alexander; Tautz, Matthias; Mohamadi Bagheri, Eman; Kaltenbacher, Manfred; Döllinger, Michael; Kniesburges, Stefan; Becker, Stefan (ICTCA 2017 - Book of Abstracts, 2017)

Simultaneous Application of Ultrasound and Sialendoscopy and its Value in the Management of Sialolithiasis - Koch, Michael; Schapher, Mirco; Mantsopoulos, Konstantinos; Goncalves, Miguel; Iro, Heinrich (Ultraschall in der Medizin, 2020)
Objective Ultrasound (US) and sialendoscopy (SE) are routinely used in patients presenting with sialolithiasis in the submandibular (SMG) and parotid gland (PG). The objective was to assess the value of the simultaneous application of US and SE in the management of sialolithiasis. Study Design Retrospective study. Setting: Tertiary referral center for salivary gland diseases. Participants: Patients in whom US and SE as single investigation tools were neither conclusive nor useful in the management of sialolithiasis were investigated using both methods simultaneously (simUS + SE). Main outcome measures: Establishment of the final diagnosis and/or contribution to the planning/performing of treatment in sialolithiasis. Results 74 patients were examined by simUS + SE (58.1 % SMG and 41.9 % PG). In all patients (unclear) hyperechoic reflexes were assessed and/or localized by SE-controlled US na-vigation. 68.9 % of the patients were investigated for diagnostic or differential-diagnostic reasons including distinguishing extraductal from intraductal calcifications and/or to exclude residual stones after therapy. In 52.7 % simUS + SE was used to plan and/or perform further treatment, in 20.3 % to enable performing a combined approach (all PG) and in 29.7 % to evaluate and plan the most adequate therapy (mainly intraductal vs. extracorporeal shock wave lithotripsy, 68.2 % of these SMG). In two cases SE-controlled and US-guided stone extraction was performed. Conclusion SimUS + SE is an innovative approach which proved to be very useful in managing sialolithiasis. It added valuable information regarding the establishment of a diagnosis or differential diagnosis, planning and performing the most adequate treatment, intraoperative control of therapy and postoperative follow-up.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Diagnosis; Salivary gland; Sialendoscopy; Therapy; Ultrasound

Simultaneous application of ultrasound and sialendoscopy: experience in the management of stenosis and other non-sialolithiasis-related salivary gland disorders - Koch, M.; Schapher, Mirco; Goncalves, Miguel; Iro, Heinrich; Mantsopoulos, K. (European Review for Medical and Pharmacological Sciences, 2020)
OBJECTIVE: To assess the value of the simultaneous application of ultrasound and sialendoscopy (US+SE) in several salivary gland diseases not caused either by sialolithiasis or by tumours. PATIENTS AND METHODS: US+SE are routinely used in patients with inflammatory, obstructive, and other non-tumorous major salivary gland diseases. In patients in whom US and SE as single investigation tools were not conclusive or not useful in the management of several non-sialolithiasis-related conditions (stenoses, ductal anomalies, ductal trauma, space-occupying paraductal lesions), both methods were used simultaneously for diagnosis and treatment. RESULTS: US+SE were used simultaneously in 44 patients for 56 indications. Stenosis was managed in 36 cases (81.8%) and in thirty-eight of the indications (67.9%) with simultaneous US+SE. The successful opening was achieved in 23 (63.9%), conservative and/or ablative treatment was indicated in 13 (36.1%), and further imaging was indicated in two (5.5%) of these cases. Post-traumatic or postinfectious complications were managed in 12 (27.3%) of all cases, and isolated ductal anomalies and paraductal space-occupying lesions were assessed in three cases (8.3%) each. In all instances, simultaneous US+SE clearly improved the management in diagnosis and/or therapy. CONCLUSIONS: Simultaneous application of US+SE provided additional information that proved to be valuable for diagnosis, planning, and treatment in several non-sialolithiasis-related conditions such as stenoses, ductal anomalies, ductal trauma, and space-occupying paraductal lesions.
CRIS-Team Scopus Importer:2020-03-31

Single-cycle induction chemotherapy before chemoradiotherapy or surgery in functionally inoperable head and neck squamous cell carcinoma: 10-year results - Breheret, Marius; Lubgan, Dorota; Haderlein, Marlen; Hecht, Markus; Traxdorf, Maximilian; Schmidt, Daniela; Mueller, Sarina K.; Kitzsteiner, Christian; Kuwert, Torsten; Iro, Heinrich; Fietkau, Rainer; Semrau, Sabine (European Archives of Oto-Rhino-Laryngology, 2019)
Introduction The response to induction chemotherapy (IC) predicts local control after conservative treatment of laryngeal, meso- and hypopharyngeal head and neck squamous cell carcinoma (HNSCC) and can thus help to avoid surgery. Single-cycle induction chemotherapy may help to maintain a low local recurrence rate while keeping the overall toxicity manageable. However, long-term data on single-cycle IC response by tumor location is lacking. Methods N = 102 patients with functionally inoperable primary HNSCC of the larynx (n = 43), hypopharynx (n = 42) or mesopharynx/tongue (n = 17) received one cycle of docetaxel (75 mg/m(2), d1) plus cisplatin (30 mg/m(2), d1-3) or carboplatin (AUC 1.5, d1-3) and a response evaluation 3 weeks later. Responders (>= 30% tumor size reduction and >= 20% SUVmax decrease in F-18-FDG PET/CT) were recommended chemoradiotherapy (CRT), and non-responders surgery. Results The overall response rate was 72.5%. All 74 responders and 10 non-responders received primary CRT, and 18 patients received primary surgery after single-cycle IC. Overall 10-year local recurrence-free survival (LRFS) was 73.7%. Three-year LRFS was 88.2% (mesopharynx/tongue), 88.2% (larynx), and 73.3% (hypopharynx); p = 0.17. 3-year distant metastasis-free survival (DMFS) was 94.1% (mesopharynx/tongue), 88.0% (larynx) and 76.4% (hypopharynx); p > 0.05. This influenced the 3-year cancer-specific survival (CSS) for larynx (91.2%) vs. hypopharynx tumors (60.8%); p = 0.003, but CSS was not different to tumors in the mesopharynx/tongue (81.4%); p > 0.05. Conclusions A single-cycle induction chemotherapy for HNSCC enables surgery plus adjuvant therapy as well as chemoradiotherapy. The long-term local and distant disease control was good but varied between tumors in the larynx and mesopharynx/tongue vs. hypopharynx.
CRIS-Team WoS Importer:2019-10-18

Single-cycle induction chemotherapy followed by chemoradiotherapy or surgery in patients with head and neck cancer: What are the best predictors of remission and prognosis? - Semrau, Sabine; Haderlein, Marlen; Schmidt, Daniela; Lell, Michael; Wolf, Walburga; Waldfahrer, Frank; Uder, Michael; Iro, Heinrich; Kuwert, Torsten; Fietkau, Rainer (Cancer, 2015)
There is controversy over the concept of function and organ preservation by chemotherapy/chemoradiation instead of surgery in locally advanced cancer of the larynx or pharynx. Tumor response to induction chemotherapy (ICT) can help in choosing between conservative and surgical treatment. This study compared 3 methods of assessing response to ICT: endoscopy, computed tomography, and (18) F-FDG-PET/CT.Primary response to 1 cycle of ICT with docetaxel plus platinum was assessed by the aforementioned methods in 62 laryngopharyngeal cancer patients. Endoscopic response was the deciding factor for selecting further treatment: surgery for endoscopic nonresponders (<30% tumor response) versus chemoradiotherapy for endoscopic responders.ICT achieved endoscopic response in 48 of 62 patients (77%). Individual relative residual tumor activity of standardized uptake value (resSUVmax ) in (18) F-FDG-PET/CT was a median 0.38 of baseline (0.09-1.71), whereas residual tumor extent in CT (resCT) was 0.75 of baseline (0.32-1.20). Endoscopic responders and nonresponders differed significantly in SUVmax after ICT (postSUVmax , 6.0 vs 14.5; P < .001), resSUVmax (0.34 vs 0.81, P < .001), and resCT (0.71 vs 0.87, P = .004), but not in maximum tumor diameter after ICT (14 vs 20 mm, P = .11). resSUVmax <0.8 and absolute postSUVmax <10 provided the best discriminatory power for long-term success criteria (tumor-free survival, overall survival).Metabolic tumor response showed very good correlation with clinical tumor response to ICT. The value of metabolic response detected by (18) F-FDG-PET/CT should be explored in a prospective clinical trial. Cancer 2015;121:1214-1222. © 2014 American Cancer Society.
EVALuna2:13821

Single cycle induction treatment with cisplatin/docetaxel plus durvalumab/tremelimumab in stage III-IVB head and neck squamous cell cancer (CheckRad-CD8 trial) - Hecht, Markus; Gostian, A-O.; Eckstein, Markus; Rutzner, Sandra; Von Der Gruen, J.; Illmer, T.; Hautmann, M. G.; Brunner, T.; Laban, S.; Klautke, G.; Tamaskovics, B.; Frey, Benjamin; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

Sinonasal Leiomyosarcoma: Clinicopathological Analysis of Nine Cases with Emphasis on Common Association with Other Malignancies and Late Distant Metastasis - Agaimy, Abbas; Semrau, Sabine; Koch, Michael; Thompson, Lester D.R. (Head and Neck Pathology, 2018)
Sinonasal tract (SNT) leiomyosarcoma (LMS) is exceedingly rare with < 100 cases reported. Their relationship to retinoblastoma and other malignancies, along with previous irradiation has not been clarified. Routine and consultation cases were reviewed for histologically and immunohistochemically proven SNT LMS. The tumors were tested with antibodies against α-smooth muscle actin, desmin, h-caldesmon, HMB45, S100 protein, Rb1, MDM2, CDK4 and EBV (EBER-ISH). Nine tumors affecting 5 males and 4 females aged 26 to 77 years (median: 48 years) were identified in the maxillary sinus (n = 4), nasal cavity (n = 3) and combined SNT (n = 2). Three patients had previous irradiation (2 for retinoblastoma, 1 for fibrous dysplasia) and 1 patient had chemotherapy and stem cell transplantation for Hodgkin lymphoma. One patient had prostatic adenocarcinoma (prior) and rectal adenocarcinoma (post) to the LMS. All patients with follow-up developed either local recurrences and/or metastases, principally to lung (time to metastasis: 16-156 months, mean 62 months). Histologically, 6 tumors were conventional high-grade LMS, two had glycogen-rich clear cell (PEComa-like) morphology and one was spindle cell low-grade. The latter showed grade 2 in the recurrence and grade 3 in the lung metastases. Two cases showed dedifferentiation to anaplastic pleomorphic (inflammatory MFH-like) phenotype. Immunohistochemistry revealed diffuse expression of at least 2 smooth muscle markers in 8 and only actin in one case/s. All other markers were negative. RB1 loss was observed in 6/8 cases tested. Sinonasal tract leiomyosarcomas are rare aggressive sarcomas that frequently develop in a background of previous cancer therapy (4/9), most frequently irradiation. Their varied morphology underlines the wide differential diagnostic considerations. Long-term survival may be achieved with aggressive multimodal therapy.
EVALuna2:34895

Sinonasal mixed transitional epithelial-seromucinous papillary glandular neoplasms with BRAF p.V600E mutations — sinonasal analogues to the sialadenoma papilliferum family tumors - Patel, Simmi; Snyderman, Carl H.; Mueller, Sarina K.; Agaimy, Abbas; Seethala, Raja R. (Virchows Archiv, 2022)
Sinonasal non-intestinal type adenocarcinoma (non-ITAC) is a heterogeneous category that may benefit from improved taxonomy. With the recognition that most non-ITAC are phenotypically seromucinous, stratification may be improved by applying salivary type morphologic criteria and molecular findings. We report two cases of papillary seromucinous adenocarcinoma with sinonasal papilloma-like surface components that show histologic and molecular features analogous to the salivary sialadenoma papilliferum family of tumors. Case 1 concerns a 50-year-old female who presented with a left anterior nasoethmoid polyp, while case 2 is that of a 74 year old female with nasal polyposis. Histologically, both cases demonstrated a surface transitional sinonasal papilloma-like component (more prominent in case 2) with a deeper bilayered glandular component showing papillary and tufted micropapillary growth of monomorphic columnar to cuboidal cells with eosinophilic cytoplasm. Case 1 also showed a deep cribriform/microcystic component. Immunostains showed a delimiting p63/p40 positive basal layer around the SOX-10 positive glandular elements, while the transitional sinonasal papilloma-like components were diffusely p63/p40 positive. Like sialadenoma papilliferum and related tumors, both cases demonstrated BRAF p.V600E mutations in both components and no other alterations. The patients remain disease free at 9 and 19 months respectively. Our cases illustrate a novel sinonasal lesion and suggest that improved morphologic and molecular categorization may refine and reduce the category of non-ITAC.
CRIS-Team Scopus Importer:2022-07-01
Keywords: BRAF p.V600E; Non-intestinal type sinonasal adenocarcinoma; Non-salivary type sinonasal adenocarcinoma; Salivary type-adenocarcinoma; Sinonasal papilloma

Sinonasal papillomas: A single centre experience on 137 cases with emphasis on malignant transformation and EGFR/KRAS status in “carcinoma ex papilloma” - Maisch, Saskia; Mueller, Sarina K.; Traxdorf, Maximilian; Weyerer, Veronika; Stoehr, Robert; Iro, Heinrich; Hartmann, Arndt; Agaimy, Abbas (Annals of Diagnostic Pathology, 2020)
Among the three major histological subtypes of sinonasal papillomas, inverted (ISP) and oncocytic (OSP) sinonasal papillomas tend to undergo malignant transformation to carcinoma. However, criteria determining risk of recurrence and malignant progression have not been established. Recently, EGFR and KRAS mutations were detected to be characteristic for ISP and OSP, respectively. In this study, we analyzed 137 sinonasal papilloma cases (132 ISP and 5 OSP) for clinicopathological characteristics, frequency of recurrences/malignant transformation, and histological types and genetic features of carcinoma ex Schneiderian papilloma. OSP presented at a higher age than ISP (median, 75 vs. 57 years) and affected predominantly females. Overall frequency of recurrences and malignant transformation was 23.1% and 9.5%, respectively. Rates of recurrence (33.3% vs. 22.0%) and malignant transformation (33.3% vs. 8.8%) were higher in OSP compared to ISP, respectively. Carcinomas (n = 10) occurred mostly synchronously, more frequently in females and mainly associated with ISP (n = 9). Squamous cell carcinoma (SCC) was the most frequently associated malignancy. Concordant EGFR (in ISP/associated carcinoma) and KRAS (in the OSP/associated carcinoma) mutations were detected in all successfully analyzed matching papilloma/carcinoma pairs, confirming their shared clonal origin. Results of this large study are in line with recent studies showing frequent EGFR and KRAS mutations in sinonasal carcinoma ex Schneiderian papilloma. As the papilloma component might on occasion be missed on biopsy of synchronous carcinoma ex papilloma, EGFR and KRAS mutation testing represents a promising molecular surrogate for sinonasal “carcinoma ex papilloma”, at the same time offering an opportunity for targeting mutant EGFR in this rare cancer type.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Carcinoma ex papilloma; EGFR; Inverted papilloma; KRAS; Oncocytic papilloma; Schneiderian papilloma; Sinonasal papilloma; Squamous cell carcinoma

Sleep as a random walk: a super-statistical analysis of EEG data across sleep stages - Metzner, Claus; Schilling, Achim; Traxdorf, Maximilian; Schulze, Holger; Krauß, Patrick (Communications Biology, 2021)
In clinical practice, human sleep is classified into stages, each associated with different levels of muscular activity and marked by characteristic patterns in the EEG signals. It is however unclear whether this subdivision into discrete stages with sharply defined boundaries is truly reflecting the dynamics of human sleep. To address this question, we consider one-channel EEG signals as heterogeneous random walks: stochastic processes controlled by hyper-parameters that are themselves time-dependent. We first demonstrate the heterogeneity of the random process by showing that each sleep stage has a characteristic distribution and temporal correlation function of the raw EEG signals. Next, we perform a super-statistical analysis by computing hyper-parameters, such as the standard deviation, kurtosis, and skewness of the raw signal distributions, within subsequent 30-second epochs. It turns out that also the hyper-parameters have characteristic, sleep-stage-dependent distributions, which can be exploited for a simple Bayesian sleep stage detection. Moreover, we find that the hyper-parameters are not piece-wise constant, as the traditional hypnograms would suggest, but show rising or falling trends within and across sleep stages, pointing to an underlying continuous rather than sub-divided process that controls human sleep. Based on the hyper-parameters, we finally perform a pairwise similarity analysis between the different sleep stages, using a quantitative measure for the separability of data clusters in multi-dimensional spaces.
CRIS-Team WoS Importer:2021-12-24

Small dimension–Big impact! Nanoparticle-enhanced non-invasive and intravascular molecular imaging of atherosclerosis in vivo - Lenz, Tobias; Nicol, Philipp; Castellanos, Maria Isabel; Engel, Leif Christopher; Lahmann, Anna Lena; Alexiou, Christoph; Joner, Michael (Molecules, 2020)
Extensive translational research has provided considerable progress regarding the understanding of atherosclerosis pathophysiology over the last decades. In contrast, implementation of molecular in vivo imaging remains highly limited. In that context, nanoparticles represent a useful tool. Their variable shape and composition assure biocompatibility and stability within the environment of intended use, while the possibility of conjugating different ligands as well as contrast dyes enable targeting of moieties of interest on a molecular level and visualization throughout various imaging modalities. These characteristics have been exploited by a number of preclinical research approaches aimed at advancing understanding of vascular atherosclerotic disease, in order to improve identification of high-risk lesions prior to oftentimes fatal thromboembolic events. Furthermore, the combination of these targeted nanoparticles with therapeutic agents offers the potential of site-targeted drug delivery with minimized systemic secondary effects. This review gives an overview of different groups of targeted nanoparticles, designed for in vivo molecular imaging of atherosclerosis as well as an outlook on potential combined diagnostic and therapeutic applications.
CRIS-Team Scopus Importer:2020-03-20
Keywords: Atherosclerosis; Molecular imaging; Nanoparticles

SMARCB1(INI1)-deficient sinonasal basaloid carcinoma: a novel member of the expanding family of SMARCB1-deficient neoplasms - Agaimy, Abbas; Koch, Michael; Lell, Michael; Semrau, Sabine; Dudek, Wojciech; Wachter, David; Knöll, Antje; Iro, Heinrich; Haller, Florian; Hartmann, Arndt (American Journal of Surgical Pathology, 2014)
Poorly differentiated sinonasal carcinomas are a heterogenous group of aggressive neoplasms that encompasses squamous cell carcinoma including basaloid variant, lymphoepithelial carcinoma, sinonasal undifferentiated carcinoma, and neuroendocrine-type small cell carcinoma. We herein describe 3 cases of a hitherto unreported variant combining features of basaloid carcinoma with variable intermingled rhabdoid cells. Patients were 2 women (aged 28 and 35) and a man (52 y) who presented with sinonasal masses. All had advanced local disease with bone involvement (pT4). None had a history of irradiation or a family history of rhabdoid tumors. Treatment was surgery and adjuvant chemoradiation. One patient developed liver, lung, pleural, and pericardial metastases (63 mo) and is currently (70 mo) alive under palliative treatment. Another developed recurrent cervical lymph node metastases and died of disease 8.5 years later. The youngest patient was disease-free at last follow-up 7 years later. Histologic features were very similar in all 3 cases and showed intimate admixture of compact basaloid cell nests with peripheral palisading, perivascular pseudorosettes, and a few scattered rhabdoid cells. Rhabdoid cells were more extensive in the metastasis in 1 case but formed a minor inconspicuous component in the primary tumors in all cases. Striking features common to all cases were (1) basaloid "blue" appearance at low power, (2) papilloma-like exophytic component, (3) extensive pagetoid surface growth with prominent denuding features, and (4) replacement of underlying mucous glands mimicking an inverted papilloma. Clear-cut origin from benign papilloma and overt squamous differentiation were lacking. Diffuse (2) or partial (1) p16 expression was noted, but all cases lacked human papillomavirus DNA by molecular tests. In situ hybridization was negative for Epstein-Barr virus. Immunohistochemistry showed diffuse expression of pancytokeratin. CK5 and vimentin showed intermingling of CK5/vimentin basaloid and CK5/vimentin rhabdoid cells. Complete loss of nuclear SMARCB1 expression was seen in all cases including also the denuding carcinoma in situ-like surface lesions. To our knowledge, this variant of sinonasal carcinoma has not been reported before. The identical features in all 3 cases suggest a specific disease rather than a nonspecific dedifferentiated phenotype. Awareness of this rare variant and thus reporting of additional cases is necessary for defining its full morphologic and biological spectrum.
EVALuna2:6600

SMARCB1 (INI-1)-deficient Sinonasal Carcinoma: A Series of 39 Cases Expanding the Morphologic and Clinicopathologic Spectrum of a Recently Described Entity - Agaimy, Abbas; Hartmann, Arndt; Antonescu, Cristina R.; Chiosea, Simion I.; El-Mofty, Samir K.; Geddert, Helene; Iro, Heinrich; Lewis, James S.; Markl, Bruno; Mills, Stacey E.; Riener, Marc-Oliver; Robertson, Thomas; et al. (American Journal of Surgical Pathology, 2017)
To more fully characterize the clinical and pathologic spectrum of a recently described tumor entity of the sinonasal tract characterized by loss of nuclear expression of SMARCB1 (INI1), we analyzed 39 SMARCB1-deficient sinonasal carcinomas collected from multiple medical centers. The tumors affected 23 males and 16 females with an age range of 19 to 89 years (median, 52). All patients presented with locally advanced disease (T3, n=5; T4, n=27) involving the sinuses (mainly ethmoid) with variable involvement of the nasal cavity. Thirty patients received surgery and/or radiochemotherapy with curative intent. At last follow-up, 56% of patients died of disease 0 to 102 months after diagnosis (median, 15), 2 were alive with disease, and 1 died of an unrelated cause. Only 9 patients (30%) were alive without disease at last follow-up (range, 11 to 115 mo; median, 26). The original diagnosis of retrospectively identified cases was most often sinonasal undifferentiated carcinoma (n=14) and nonkeratinizing/basaloid squamous cell carcinoma (n=5). Histologically, most tumors displayed either a predominantly basaloid (61%) or plasmacytoid/rhabdoid morphology (36%). The plasmacytoid/rhabdoid form consisted of sheets of tumor cells with abundant, eccentrically placed eosinophilic cytoplasm, whereas similar cells were typically rare and singly distributed in the basaloid variant. Glandular differentiation was seen in a few tumors. None of the cases showed squamous differentiation or surface dysplasia. By immunohistochemistry, the tumors were positive for pancytokeratin (97%), CK5 (64%), p63 (55%), and CK7 (48%); and they were negative for NUT (0%). Epstein-Barr virus and high-risk human papillomavirus was not detected by in situ hybridization. Immunohistochemical loss of SMARCB1 (INI1) expression was confirmed for all 39 tumors. Investigation of other proteins in the SWI/SNF complex revealed co-loss of SMARCA2 in 4 cases, but none were SMARCA4 deficient or ARID1A deficient. Of 27 tumors with SMARCB1 fluorescence in situ hybridization analysis, 14 showed homozygous (biallelic) deletions and 7 showed heterozygous (monoallelic) deletions. SMARCB1-deficient sinonasal carcinoma represents an emerging poorly differentiated/undifferentiated sinonasal carcinoma that (1) cannot be better classified as another specific tumor type, (2) has consistent histopathologic findings (albeit with some variability) with varying proportions of plasmacytoid/rhabdoid cells, and (3) demonstrates an aggressive clinical course. This entity should be considered in any difficult-to-classify sinonasal carcinoma, as correct diagnosis will be mandatory for optimizing therapy and for further delineation of this likely underdiagnosed disease.
EVALuna2:6856

Sol-gel derived B2O3-CaO borate bioactive glasses with hemostatic, antibacterial and pro-angiogenic activities - Zheng, Kai; Bider, Faina; Monavari, Mahshid; Xu, Zhiyan; Janko, Christina; Alexiou, Christoph; Beltrán, Ana M.; Boccaccini, Aldo R. (Regenerative Biomaterials, 2024)
Sol-gel borate bioactive glasses (BGs) are promising ion-releasing biomaterials for wound healing applications. Here, we report the synthesis of a series of binary B2O3-CaO borate BGs (CaO ranging from 50 to 90 mol%) using a sol-gel-based method. The influence of CaO content in B2O3-CaO borate BG on morphology, structure and ion release behavior was investigated in detail. Reduced dissolution (ion release) and crystallization could be observed in borate BGs when CaO content increased, while the morphology was not significantly altered by increasing CaO content. Our results evidenced that the ion release behavior of borate BGs could be tailored by tuning the B2O3/CaO molar ratio. We also evaluated the in vitro cytotoxicity, hemostatic, antibacterial and angiogenic activities of borate BGs. Cytocompatibility was validated for all borate BGs. However, borate BGs exhibited composition-dependent hemostatic, antibacterial and angiogenic activities. Generally, higher contents of Ca in borate BGs facilitated hemostatic activity, while higher contents of B2O3 were beneficial for pro-angiogenic activity. The synthesized sol-gel-derived borate BGs are promising materials for developing advanced wound healing dressings, given their fast ion release behavior and favorable hemostatic, antibacterial and angiogenic activities.
CRIS-Team Scopus Importer:2024-02-02
Keywords: borate glasses; glass composition; sol-gel processing; wound healing

Sonographic Detection of Iron Oxide Nanoparticles Employing Shear Waves - Fink, Michael; Lyer, Stefan; Alexiou, Christoph; Ermert, Helmut (Current Directions in Biomedical Engineering, 2018)

Sonographic detection of magnetic nanoparticles for Magnetic Drug Targeting in weak echogenic tissue - Fink, Michael; Nüsslein, Moritz; Ermert, Helmut; Lyer, Stefan; Alexiou, Christoph (Proceedings IEEE IUS 2015, 2015)

Sonographic Detection of Magnetic Nanoparticles for Magnetic Drug Targeting Using Coded Magnetic Fields - Fink, Michael; Ermert, Helmut; Lyer, Stefan; Alexiou, Christoph (Proceedings IEEE IUS 2016, 2016)

Sonographic Detection of Nanoparticles used for Magnetic Drug Targeting - Fink, Michael; Ermert, Helmut; Löffler, Michael; Sutor, Alexander; Tewes, Barbara; Koch, Andreas; Alexiou, Christoph; Lyer, Stefan (Proceedings SENSOR 2015, 2015)

Sonographic diagnosis of tonsillar abscesses: Our experience and a systematic review - Miksch, Malin; Koch, Michael; Mantsopoulos, Konstantinos; Gostian, Antoniu-Oreste; Mueller, Sarina K.; Rupp, Robin; Iro, Heinrich; Sievert, Matti (Laryngo-Rhino-Otologie, 2022)
Background Transcutaneous sonography has been an integral part of imaging diagnostics in the head and neck region for several decades. Especially in the imaging of abscesses of the tonsillar fossa, sonography is a fast, safe, and cost-effective diagnostic method. This paper aims to provide an overview of the currently published studies in terms of diagnostic value. Material and methods systematic literature search in the following online databases: PubMed und MEDLINE according to the search terms: transcutaneous ultrasound, tonsillar abscess, peritonsillar abscess, intratonsillar abscess, peritonsillar cellulitis, parapharyngeal abscess. Evaluation of the scientific relevance of the papers according to established criteria. Results The publications were analyzed in terms of clinical application, clinical diagnosis, and diagnostic accuracy. Sensitivity and specificity are reported between 67 % - 100 %, and 50 % - 93 %, respectively, depending on the study and patient cohort. Conclusions In the synopsis of the currently published results, transcutaneous sonography promises a high potential to improve the diagnosis of peritonsillar abscess and allows a reliable differentiation to peritonsillar cellulitis. This fact seems crucial for the clinical management of patients with suspected abscesses.
CRIS-Team WoS Importer:2022-02-11

Sonographie des Halses – differenzialdiagnostische Aspekte - Sievert, Matti; Koch, Michael; Iro, Heinrich; Thimsen, Vivian (HNO, 2023)
Sonography is the preferred method for primary diagnosis and acute treatment of pathologies involving the neck’s soft tissues. Technological advances, particularly high image resolution and multiparametric ultrasound, have improved diagnostic performance. Clinical interest focuses on examining the cervical lymph nodes, salivary glands, and the thyroid gland, as well as space-occupying and inflammatory processes of the neck. In addition, sonography enables targeted minimally invasive histology acquisition using ultrasound-guided biopsies. In this context, the examiner’s comprehensive anatomical knowledge and clinical experience are of utmost importance for the quality of findings. This article provides an overview of the most important findings related to sonography of the neck and highlights the relevance of this imaging modality in the hands of the otorhinolaryngologist.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Head and neck neoplasms; Lymph nodes; Otorhinolaryngologic diseases; Salivary glands; Thyroid gland

Sources of Aerosol Dispersion During Singing and Potential Safety Procedures for Singers - Westphalen, Caroline; Kniesburges, Stefan; Veltrup, Reinhard; Gantner, Sophia; Peters, Gregor; Benthaus, Tobias; Jakubaß, Bernhard; Köberlein, Marie; Döllinger, Michael; Echternach, Matthias (Journal of Voice, 2021)
Introduction: With respect to the Covid-19 pandemic, singing is assumed to be associated with a high potential person-to-person transmission. However, it remains unclear how the impulse dispersion varies with different types of articulation, intensity levels of diction, or body position. Furthermore, it has not been understood in detail how to prevent aerosol dispersion during singing. Material and Methods: Single professional singers from the Bavarian Radio Chorus were asked to sing in different head positions, with different articulation patterns and different masks after inhaling the basic liquid of an e-cigarette. The vapor cloud was segmented and tracked over time. Results: Consonants and exaggeration of diction enhanced the distance reached by the impulse dispersion. Furthermore, the greatest dispersion was reached for a neutral head position. All protection masks stopped the initial jet of the aerosols but the FFP2 masks were the most effective. Conclusion: Some protection equipment has been identified to be promising in reducing aerosol dispersion. However, systematic effects have to be evaluated in greater collectives.
CRIS-Team Scopus Importer:2021-04-19
Keywords: SingErs—AeroSols—COVID-19

Sparsity through evolutionary pruning prevents neuronal networks from overfitting - Gerum, Richard; Erpenbeck, André; Krauß, Patrick; Schilling, Achim (Neural Networks, 2020)
Modern Machine learning techniques take advantage of the exponentially rising calculation power in new generation processor units. Thus, the number of parameters which are trained to solve complex tasks was highly increased over the last decades. However, still the networks fail – in contrast to our brain – to develop general intelligence in the sense of being able to solve several complex tasks with only one network architecture. This could be the case because the brain is not a randomly initialized neural network, which has to be trained from scratch by simply investing a lot of calculation power, but has from birth some fixed hierarchical structure. To make progress in decoding the structural basis of biological neural networks we here chose a bottom-up approach, where we evolutionarily trained small neural networks in performing a maze task. This simple maze task requires dynamic decision making with delayed rewards. We were able to show that during the evolutionary optimization random severance of connections leads to better generalization performance of the networks compared to fully connected networks. We conclude that sparsity is a central property of neural networks and should be considered for modern Machine learning approaches.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Artificial neural networks; Biological plausibility; Evolution; Evolutionary algorithm; Maze task; Overfitting

Spatiotemporal analysis of high-speed videolaryngoscopic imaging of organic pathologies in males - Bohr, Christopher; Kraeck, Angelika; Dubrovskiy, Denis; Eysholdt, Ulrich; Svec, Jan; Psychogios, Georgios; Ziethe, Anke; Döllinger, Michael (Journal of Speech Language and Hearing Research, 2014)
The aim of this study was to identify parameters that would differentiate healthy from pathological organic-based vocal fold vibrations to emphasize clinical usefulness of high-speed imaging.Fifty-five men (M age = 36 years, SD = 20 years) were examined and separated into 4 groups: 1 healthy (26 individuals) and 3 pathological (10 individuals with contact granuloma, 12 with polyps, and 7 with cysts). Vocal fold vibrations were recorded using a high-speed camera during sustained phonation. Twenty objective glottal area waveform and 24 phonovibrogram parameters representing spatiotemporal characteristics were analyzed. Statistical group comparisons were performed to document spatiotemporal changes for organic lesions that cannot be determined visually. To look for specific pattern profiles within organic lesions, the authors performed linear discriminant analysis.Thirteen parameters showed significant differences between the healthy group and at least 1 pathological group. The differences occurred more in temporal than in spatial parameters. Contact granuloma showed the fewest statistical differences (3 parameters), followed by cysts (9 parameters), and polyps (10 parameters). Linear discriminant analysis achieved accuracy performance of 76% (all groups separated) and 82% (healthy vs. pathological).The results suggest that for males, the differences between healthy voices and organic voice disorders may be more pronounced within temporal characteristics that cannot be visually detected without high-speed imaging.
EVALuna2:20186

Special issue on computational methods and engineering solutions to voice ii - Döllinger, Michael (Applied Sciences, 2021)
CRIS-Team Scopus Importer:2021-10-29

Special issues for the 55th Inner Ear Biology Workshop 06.–08.09.2018 in Berlin - Mazurek, B.; Knipper, M.; Biesinger, E.; Schulze, Holger (HNO, 2019)
CRIS-Team Scopus Importer:2019-06-28

Special Issues for the 55th Inner Ear Biology Workshop from 6th to 8th September 2018 in Berlin Basic Research and Clinical Aspects - translational Aspects of Hearing Research - Mazurek, B.; Knipper, M.; Biesinger, E.; Schulze, Holger (HNO, 2019)
CRIS-Team WoS Importer:2019-03-26

Spectrally Matched Near-Threshold Noise for Subjective Tinnitus Loudness Attenuation Based on Stochastic Resonance - Tziridis, Konstantin; Brunner, Sarah; Schilling, Achim; Krauß, Patrick; Schulze, Holger (Frontiers in Neuroscience, 2022)
Recently, we proposed a model of tinnitus development based on a physiological mechanism of permanent optimization of information transfer from the auditory periphery to the central nervous system by means of neuronal stochastic resonance utilizing neuronal noise to be added to the cochlear input, thereby improving hearing thresholds. In this view, tinnitus is a byproduct of this added neuronal activity. Interestingly, in healthy subjects auditory thresholds can also be improved by adding external, near-threshold acoustic noise. Based on these two findings and a pilot study we hypostatized that tinnitus loudness (TL) might be reduced, if the internally generated neuronal noise is substituted by externally provided individually adapted acoustic noise. In the present study, we extended the data base of the first pilot and further optimized our approach using a more fine-grained adaptation of the presented noise to the patients’ audiometric data. We presented different spectrally filtered near-threshold noises (−2 dB to +6 dB HL, 2 dB steps) for 40 s each to 24 patients with tonal tinnitus and a hearing deficit not exceeding 40 dB. After each presentation, the effect of the noise on the perceived TL was obtained by patient’s response to a 5-scale question. In 21 out of 24 patients (13 women) TL was successfully subjectively attenuated during acoustic near-threshold stimulation using noise spectrally centered half an octave below the individual’s tinnitus pitch (TP). Six patients reported complete subjective silencing of their tinnitus percept during stimulation. Acoustic noise is able to reduce TL, but the TP has to be taken into account. Based on our findings, we speculate about a possible future treatment of tinnitus by near-threshold bandpass filtered acoustic noise stimulation, which could be implemented in hearing aids with noise generators.
CRIS-Team Scopus Importer:2022-04-29
Keywords: individualized medicine; low intensity acoustic noise; stochastic resonance; tinnitus questionnaires; tinnitus treatment

Speech audiometry for indication of conventional and implantable hearing aids - Hoppe, Ulrich; Hast, A. (HNO, 2017)
The social function of the human hearing apparatus is comprehension of speech. Auditory rehabilitation aims to enhance speech perception in everyday life. Consequently, audiological evaluation contains speech perception measurement. Many speech audiometric methods have been developed in German-speaking countries, which are suitable for quantification of speech perception abilities in quiet and in noise to address specific diagnostic questions. For establishment of the indication for technical hearing systems such as hearing aids and cochlear implants, the Freiburg monosyllabic test has been employed successfully for many years. Particularly sentence tests have been suggested as a complementary measure for hearing aid indication and assessment. This paper describes the characteristics and range of application of various speech audiometric methods, and highlights the methodological limitations of the individual tests.
EVALuna2:33173

Speech developmental delay in preschool children. Evaluation of screening with anamnesis questions Sprachentwicklungsstörungen bei Vorschulkindern: Bewertung des Screenings mit Anamnesefragen - Schützenberger, Anne; Brauner, K.; Eysholdt, Ulrich; Rosanowski, Frank (HNO, 2010)
Background: In western societies, delay of speech development is frequent and important as it may affect the entire development of a child. Therefore, early diagnosis and treatment is of outstanding relevance. For screening purposes in clinical practice, questionnaires focussing on speech development are assumed to be both valid and economic assessment tools. In this study, results of a questionnaire based on "milestones in early childhood development" as previously reported by Michaelis for German children were compared with results of systematic German speech development tests. Patients and methods: In a retrospective study, data were collected from 25 German preschool children. Their parents had completed a questionnaire on their child's development prior to the examination with 4 questions focussing on speech development. In this report, the answers on these 4 questions are evaluated against the background of systematic German speech development tests, i.e. the H-SET® and PLAKSS®, and an unsystematic examination by an experienced speech and language phonologist. Results: The questionnaire had a sensitivity of 50% and a specificity of 7%. The positive and negative predictive values were 55.9% and 5%, respectively. Conclusion: A questionnaire based on "milestones in early childhood development" as previously reported by Michaelis for German children, is clinically invalid for screening speech development in preschool children. © Springer Medizin Verlag 2009.
CRIS-Team Scopus Importer:2022-09-20
Keywords: Parent questionnaire; Preschool children; Questionnaire; Screening; Speech development

Speech Perception and Information-Carrying Capacity for Hearing Aid Users of Different Ages - Hoppe, Ulrich; Hocke, Thomas; Mueller, Alexander; Hast, Anne (Audiology and Neuro-Otology, 2016)
Hearing impairment in the elderly is usually treated with conventional hearing aids; however, a large number of older people do not achieve sufficient speech recognition with hearing aids. The aim of the study was to describe speech perception with hearing aids in comparison to pure-tone hearing loss and maximum speech recognition scores for phonemically balanced words. Data from 392 hearing aid users with different degrees of hearing loss were evaluated retrospectively. In particular, pure-tone thresholds, the maximum monosyllabic word score, and the monosyllabic word score in quiet at conversational level with a hearing aid were analysed. The results showed that speech perception scores decline with increasing age. Even when corrected for pure-tone hearing loss, a significant decline in speech recognition scores after the age of 80 years was observed. Regarding the maximum monosyllabic word score, the effect is smaller but still observable; thus, speech recognition with hearing aids is significantly lower for older subjects. This can be attributed partially to the reduction of the information-carrying capacity in this group.
EVALuna2:33175

Speech Perception in Bilateral Hearing Aid Users With Different Grades of Asymmetric Hearing Loss - Hoppe, Ulrich; Hast, Anne; Hocke, Thomas (Frontiers in Neuroscience, 2022)
Hearing loss is associated with decreased speech perception as well as with changes in the auditory pathway. The effects of those changes on binaural speech perception with hearing aids are not yet fully understood. To provide further evidence on the functional changes of the auditory pathway, several speech perception tests (unilateral and bilateral, aided and unaided, in quiet, and in noise) were conducted in a population of 370 bilateral hearing aid users covering the entire range of the World Health Organization's most recent classification of hearing loss. To characterize the effects of asymmetric hearing thresholds, a generalized linear model was used for regression analysis. The model revealed a detrimental effect of the poorer ears' thresholds on both the unaided and the aided unilateral word recognition scores that were attained by the better ear. Moreover, aided binaural word recognition (in quiet and in noise) was affected to a degree that cannot be explained on the sole basis of bilateral summation. Thus, this study provides evidence that there is reorganization and altered functioning of the afferent and efferent auditory pathways due to asymmetric hearing loss. Consequently, more attention should be paid to provision with a hearing aid as early as possible, and separately for each ear.
CRIS-Team WoS Importer:2022-02-18

Speech Perception of Elderly Cochlear Implant Users Under Different Noise Conditions - Hast, Anne; Schlücker, Luisa; Digeser, Frank; Liebscher, Tim; Hoppe, Ulrich (Otology & Neurotology, 2015)
The primary objective of this study was the comparison of younger and older (>75 yr) CI recipients' performance for speech perception in quiet and in competing continuous and fluctuating noise.Prospective, comparative clinical study.University hospital.Fifty patients, 25 older and 25 younger than 75 years, with a postlingually acquired profound hearing loss who received a cochlear implant at least 1 year before study start were enrolled.Cochlear implantation.We measured speech perception using monosyllable (Freiburg monosyllables) and sentence materials (Göttingen sentences) in quiet. In addition, speech perception for sentences was measured under two different noise conditions: with a continuous, speech-simulating noise signal (CCITT noise) and the FASTL noise (fluctuating noise).We did not find a significant difference between the performance for younger and the older cohort on speech perception tasks in quiet for Freiburg monosyllables (63.4% ± 20% and 61.7% ± 18.1%, respectively) and for the Göttingen sentences in quiet (73.5% ± 24.3% and 75% ± 25%, respectively). No significant difference was observed for performance between the two age groups when listening in continuous CCITT noise (18.9% ± 24.0% and 29.5% ± 25.2% perception score respectively) or in FASTL noise (27.8% ± 24.2% and 34.4% ± 27.8% perception score, respectively).There is no supporting evidence from our evaluations of word and sentence perception in quiet and noise that elderly CI users older than 75 years of age perform more poorly than those younger than 75 years of age.
EVALuna2:20022

Speech perception with hearing aids in comparison to pure-tone hearing loss - Hoppe, Ulrich; Hast, A.; Hocke, T. (HNO, 2014)
Speech perception is the most important social task of the auditory system. Consequently, speech audiometry is essential to evaluate hearing aid benefit. The aim of the study was to describe the correlation between pure-tone hearing loss and speech perception. In particular, pure-tone audiogram, speech audiogram, and speech perception with hearing aids were compared.In a retrospective study, 102 hearing aid users with bilateral sensorineural hearing loss were included. Pure-tone loss (PTA) was correlated to monosyllabic perception at 65 dB with hearing aid and with maximum monosyllabic perception with headphones.Speech perception as a function of hearing loss can be represented by a sigmoid function. However, for higher degrees of hearing loss, substantial deviations are observed. Maximum monosyllabic perception with headphones is usually not achieved with hearing aids at standard speech levels of 65 dB.For larger groups, average pure-tone hearing loss and speech perception correlate significantly. However, prognosis for individuals is not possible. In particular for higher degrees of hearing loss substantial deviations could be observed. Speech performance with hearing aids cannot be predicted sufficiently from speech audiograms. Above the age of 80, speech perception is significantly worse.
EVALuna2:19936

Speech performance and training effects in the cochlear implant elderly - Schumann, Annette; Hast, Anne; Hoppe, Ulrich (Audiology and Neuro-Otology, 2014)
Cochlear implantation requires acclimatization to the electrical input. Usually, cochlear implant (CI) listeners undergo an auditory rehabilitation program that includes auditory training sessions. Recently, it was shown that a phoneme-based training may improve speech perception abilities even in experienced CI listeners. The current study focuses on whether the effect of an auditory training program depends on the age of CI listeners.Fifteen CI listeners took part in an auditory phoneme-based computer training program. Before and after training, speech recognition tests in moderate and difficult noise (+5 dB SNR and 0 dB SNR, respectively) were administered. Additionally, speech recognition was tested 6 months after the training (follow-up). A control group consisting of 12 subjects underwent audiometric testing without any auditory training.Speech perception in moderate noise improved significantly during the training as revealed by comparing pre- and posttraining scores evaluated in the moderate noise condition. No significant change was observed for the difficult noise situation at 0 dB SNR. The speech perception measures of the control group remained unchanged. No significant effect of age on the training effect was observed.Speech recognition can be improved even in experienced CI listeners. When motivated to participate, senior CI users with long-term CI experience may benefit in a similar way from an auditory, phoneme-based computer training program as younger CI users.
EVALuna2:19974

Speech recognition with hearing aids for 10 standard audiograms English version - Dörfler, Constantin; Hocke, T.; Hast, A.; Hoppe, Ulrich (HNO, 2020)
Background Improvement of speech perception in quiet is an important goal of hearing aid provision. In practice, results are highly variable. The aim of this study was to investigate the relationship between type and extent of hearing loss (audiogram type), maximum word recognition score, and aided speech perception. Materials and methods Pure tone and speech audiometric data of 740 ears in 370 patients were reviewed. All subjects visited our hearing center for hearing aid evaluation between 2012 and 2017. The maximum word recognition score (WRSmax) and the monosyllabic speech recognition score with hearing aids, WRS65(HA) were analyzed for 10 different standard audiogram types. Results The WRS65(HA) with hearing aids for different degrees of hearing loss is, within error boundaries, comparable to previous investigations and shows a difference of 10-20 percentage points to the WRSmax. This difference tends to be larger for flat and moderately sloping audiograms compared to steep-sloping audiograms. The ratio WRS65(HA)/WRSmax can be interpreted as an efficiency factor for hearing aid provision, since it relates speech recognition with hearing aids to the maximally achievable information carrying capacity of the hearing impaired. Conclusion The expectation regarding hearing aid provision has to be adjusted according to maximum word recognition score, the derived quality measures, degree of hearing loss, and audiogram type.
CRIS-Team WoS Importer:2020-04-10

SPIONs and magnetic hybrid materials: Synthesis, toxicology and biomedical applications - Friedrich, Ralf P.; Janko, Christina; Unterweger, Harald; Lyer, Stefan; Alexiou, Christoph (Physical Sciences Review, 2021)
In the past decades, a wide variety of different superparamagnetic iron oxide nanoparticles (SPIONs) have been synthesized. Due to their unique properties, such as big surface-to-volume ratio, superparamagnetism and comparatively low toxicity, they are principally well suited for many different technical and biomedical applications. Meanwhile, there are a numerous synthesis methods for SPIONs, but high requirements for biocompatibility have so far delayed a successful translation into the clinic. Moreover, depending on the planned application, such as for imaging, magnetic drug targeting, hyperthermia or for hybrid materials intended for regenerative medicine, specific physicochemical and biological properties are inevitable. Since a summary of all existing SPION systems, their properties and application is far too extensive, this review reports on selected methods for SPION synthesis, their biocompatibility and biomedical applications.
CRIS-Team WoS Importer:2022-01-14

SPIONs functionalized with small peptides for binding of lipopolysaccharide, a pathophysiologically relevant microbial product. - Karawacka, Weronika; Janko, Christina; Unterweger, Harald; Mühlberger, Marina; Lyer, Stefan; Taccardi, Nicola; Mokhir, Andriy; Jira, Wolfgang; Peukert, Wolfgang; Boccaccini, Aldo R.; Kolot, Mikhail; Strauss, Richard; et al. (Colloids and Surfaces B-Biointerfaces, 2018)
Systemic inflammation such as sepsis represents an acute life-threatening condition, to which often no timely remedy can be found. A promising strategy may be to functionalize magnetic nanoparticles with specific peptides, derived from the binding motives of agglutinating salivary proteins, that allow immobilization of pathogens. In this work, superparamagnetic iron oxide nanoparticles with stable polycondensed aminoalkylsilane layer were developed, to which the heterobifunctional linkers N-succinimidyl 3-(2-pyridyldithio)-propanoate (SDPD) and N-succinimidyl bromoacetate (SBA) were bound. These linkers were further chemoselectively reacted with the thiol group of singularly present cysteines of selected peptides. The resulting functional nanoparticles underwent a detailed physicochemical characterization. The biocompatibility of the primarily coated aminoalkylsilane particles was also investigated. To test the pathogen-binding efficacy of the particles, the lipopolysaccharide-immobilization capacity of the peptide-coated particles was compared with free peptides. Here, one particle-bound peptide species succeeded in capturing 90% of the toxin, whereas the degree of immobilization of the toxin with a system that varied in the sequence of the peptide dropped to 35%. With these promising results, we hope to develop extracorporeal magnetic clearance systems for removing pathogens from the human body in order to accelerate diagnosis and alleviate acute disease conditions such as sepsis.

Sporadic endolymphatic sac tumor–a diagnostic and therapeutic challenge - Kuenzel, Julian; Agaimy, Abbas; Hornung, Joachim; Lell, Michael; Ganslandt, Oliver Thomas; Semrau, Sabine; Zenk, Johannes (International Journal of Clinical and Experimental Pathology, 2014)
Endolymphatic sac tumor (ELST) is a rare low-grade locally aggressive neoplasm of the inner ear that may occur sporadically or in the setting of von Hippel-Lindau syndrome. We herein present a case of sporadic ELST in a 39-year-old man, treated using an interdisciplinary approach (surgery+radiotherapy), with a 10-year follow-up. The patient presented with hearing loss of sudden onset. The treatment of choice for ELST is radical tumor resection, which is associated with a good long-term prognosis. Remission may last for years, but there may be local recurrences, probably as a result of incomplete resection. Adjuvant radiotherapy is an option in case of recurrence and could be discussed after incomplete resection. The purpose of this report is to call attention to ELSTs, which are difficult to diagnose due to their rarity and variety of presentations.
EVALuna2:6593

Sports despite masks: no negative effects of FFP2 face masks on cardiopulmonary exercise capacity in children - Weigelt, Annika; Schöffl, Isabelle; Rottermann, Kathrin; Wällisch, Wolfgang; Müller, Susanna; Dittrich, Sven; Hübner, Matthias (European Journal of Pediatrics, 2023)
Face masks were recognized as one of the most effective ways to prevent the spread of the COVID-19 virus in adults. These benefits were extended to children and adolescents. However, the fear of negative consequences from wearing a face mask during physical exercise led to cancellations of physical education lessons. This further decreased the amount of physical activity available to children and adolescents during the pandemic. However, there is little published data on the potential adverse effects of wearing the most effective and partially mandatory FFP2/N95 face masks during PE or physical activity (PA) in this age. Even though the pandemic has been declared as passed by the WHO, the rise of a new pandemic and thus the use of face masks for limiting its spread is inevitable, so we need to be better prepared for alternative options to lockdown and limitation of PA in such a scenario. Twenty healthy children aged 8–10 years performed two identical cardiopulmonary exercise tests as an incremental step test on a treadmill within an interval of 2 weeks, one time without wearing a protective mask and one time wearing an FFP2 mask. The cardiopulmonary exercise parameter and especially the end-expiratory gas exchange for oxygen and carbon dioxide (petO2 and petCO2) were documented for each step, at rest and 1 min after reaching physical exhaustion. Twelve boys (mean age 8.5 ± 1.4 years) and 8 girls (mean age 8.8 ± 1.4 years) showed no adverse events until maximal exertion. The mean parameters measured at peak exercise did not differ significantly between both examinations (mean peak VO2 = 42.7 ± 9.5 vs 47.8 ± 12.9 ml/min/kg, p = 0.097, mean O2pulse 7.84 ± 1.9 ml/min vs. 6.89 ± 1.8, p = 0.064, mean VE/VCO2slope 33.4 ± 5.9 vs. 34.0 ± 5.3, p = 0.689). The only significant difference was the respiratory exchange rate (RER, 1.01 ± 0.08 vs 0.95 ± 0.08, p = 0.004). The measured respiratory gases (end-tidal O2 and CO2) decreased and respectively increased significantly in almost every step when wearing an FFP2 mask. However, these levels were well below hypercapnia and above hypoxia. Conclusion: In this study, no significant differences in the cardiorespiratory function at peak exercise could be discerned when wearing an FFP2/N95 face mask. While the end-tidal values for CO2 increased significantly and the end-tidal values for O2 decreased significantly, these values did never reach levels of hypercapnia or hypoxia. Furthermore, the children terminated the exercise at a lower RER and heart rate (HR) suggesting a subconscious awareness of the higher strain. Since the detrimental effects of limiting sports during the pandemic are well documented, stopping PE lessons altogether because of the minor physiological effects of wearing these masks instead of simply stopping pushing children to perform at their best seems premature and should be reconsidered in the future. What is Known: • Wearing a face mask has an influence on psychological, social, and physiological functions in adults. • Because of the observed effects of wearing face masks in adults, physical activity in children was limited during the pandemic. What is New: • Wearing an FFP2/N95 mask during physical activity did not lead to hypercapnia or hypoxia in children in this study. • Even though end-tidal CO2 values were significantly higher and end-tidal O2 values significantly lower when wearing an FFP2/N95 face mask, no pathological values were reached.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Coronavirus; COVID-19; End-tidal CO; End-tidal O; Oxygen saturation; Treadmill testing; VO

Sprachverstehen mit Hörgeräten für 10 Standardaudiogramme - Dörfler, Constantin; Hocke, T.; Hast, A.; Hoppe, Ulrich (HNO, 2019)
Background: Improvement of speech perception in quiet is an important goal of hearing aid provision. In practice, results are highly variable. The aim of this study was to investigate the relationship between type and extent of hearing loss (audiogram type), maximum word recognition score, and aided speech perception. Materials and methods: Pure tone and speech audiometric data of 740 ears in 370 patients were reviewed. All subjects visited our hearing center for hearing aid evaluation between 2012 and 2017. The maximum word recognition score (WRSmax) and the monosyllabic speech recognition score with hearing aids, WRS65(HA) were analyzed for 10 different standard audiogram types. Results: The WRS65(HA) with hearing aids for different degrees of hearing loss is, within error boundaries, comparable to previous investigations and shows a difference of 10–20 percentage points to the WRSmax. This difference tends to be larger for flat and moderately sloping audiograms compared to steep-sloping audiograms. The ratio WRS65(HA)/WRSmax can be interpreted as an efficiency factor for hearing aid provision, since it relates speech recognition with hearing aids to the maximally achievable information carrying capacity of the hearing impaired. Conclusion: The expectation regarding hearing aid provision has to be adjusted according to maximum word recognition score, the derived quality measures, degree of hearing loss, and audiogram type.
CRIS-Team Scopus Importer:2019-11-26
Keywords: IEC 60118-15; Maximum word recognition score; Speech audiometry; Speech comprehensibility; Tone audiometry

Stellenwert der Vakzine gegen humane Papillomaviren in der Prävention von Krebserkrankungen - Schulmeyer, Carla; Knöll, Antje; Iro, Heinrich; Müller, Susanna; Beckmann, Matthias (Onkologe, 2021)
Background: Human papillomaviruses (HPV) are the most common causes of genital viral infections. HPV infections usually heal, but can also persist and thus cause lesions of different grades. Infections with high-risk HPV types (hrHPV) 16, 18, 31, 33, 45, 52, and 58 are responsible for causing 90% of cervical cancer cases in Europe. Head and neck cancer, vaginal and vulvar cancer and their precursors, as well as penile or anal cancer may also be associated with hrHPV. Objectives: The aim of this work is to demonstrate the importance of HPV vaccines in the prevention of genital as well as head and neck cancers. Materials and methods: This work is based on a selective literature search in the PubMed database on the correlation between HPV vaccines and HPV-associated cancer. Results: HPV vaccination ensures a high level of protection against precancerous lesions and cancer of the cervix, vagina, vulva, anus, and genital warts. Conclusions: Results of HPV vaccination and its positive effects on head and neck tumors is expected within the next few decades.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Condylomata acuminata; HPV; Oropharyngeal neoplasms; Sexually transmitted diseases; Uterine cervical neoplasms

Stenosis and stenosis-like lesions in the submandibular duct: detailed clinical and sialendoscopy-based analysis and proposal for a classification - Koch, Michael; Zenk, Johannes; Iro, Heinrich (Oral Surgery, Oral Medicine, Oral Pathology and Oral Radiology, 2020)
Objective: The aim of this study was to perform a detailed analysis of submandibular duct stenoses and propose a classification for them. Study Design: This retrospective study covering the period 2001–2019 included 314 patients with 370 submandibular duct stenoses, assessed sialendoscopically for number, grade of narrowing, length, tissue type, and underlying main cause/associated diseases. Results: In the included patients, 58.9% of the stenoses were at the papilla, 89.2% were short, and 61.6% were of high grade. Predominantly inflammatory stenoses (type 1) differed from fibrotic stenoses (type 2). Detailed analysis identified stenosis-like lesions caused by anatomic duct narrowing and/or duct variations (type 3), differing significantly from type 2 stenoses in location, length, and bilaterality (each P = .0001) and from type 1 stenoses in location (P = .0001). Compared with type 2, type 1 stenoses were bilateral significantly more often and shorter (each P = .0001). Frequencies of the main causes of stenosis—anatomic narrowness/duct variation and chronic sialadenitis—differed significantly in the different locations (P = .0001). There were no significant differences in frequencies of associated diseases/conditions for the different stenosis types. Conclusions: Three types of stenosis/stenosis-like lesions were distinguished. In view of these results and the findings from a review of the literature, the location and type of stenoses were found to be more important parameters, whereas number, grade, and length were less important. The underlying cause may be useful for assessing the prognosis.
CRIS-Team Scopus Importer:2020-08-21

Stereotactic radiotherapy of vestibular schwannoma : Hearing preservation, vestibular function, and local control following primary and salvage radiotherapy - Putz, Florian; Müller, Jan; Wimmer, Cornelia; Goerig, Nicole; Knippen, Stefan; Iro, Heinrich; Grundtner, Philipp; Eyüpoglu, Ilker Yasin; Roessler, Karl; Semrau, Sabine; Fietkau, Rainer; Lettmaier, Sebastian (Strahlentherapie und Onkologie, 2017)
OBJECTIVE: The aim of this publication is to present long-term data on functional outcomes and tumor control in a cohort of 107 patients treated with stereotactic radiotherapy (RT) for vestibular schwannoma. PATIENTS AND METHODS: Included were 107 patients with vestibular schwannoma (primary or recurrent following resection) treated with stereotactic RT (either fractioned or single-dose radiosurgery) between October 2002 and December 2013. Local control and functional outcomes were determined. Analysis of hearing preservation was limited to a subgroup of patients with complete audiometric data collected before treatment and during follow-up. Vestibular function test (FVT) results could be analyzed in a subset of patients and were compared to patient-reported dizziness. RESULTS: After a mean follow-up of 46.3 months, actuarial local control for the whole cohort was 100% after 2, 97.6% after 5, and 94.1% after 10 years. In patients with primary RT, serviceable hearing was preserved in 72%. Predictors for preservation of serviceable hearing in multivariate analysis were time of follow-up (odds ratio, OR = 0.93 per month; p = 0.021) and pre-RT tumor size (Koos stage I-IIa vs. IIb-IV; OR = 0.15; p = 0.031). Worsening of FVT results was recorded in 17.6% (N = 3). Profound discrepancy of patient-reported dizziness and FVT results was observed after RT. In patients with primary RT, worsening of facial nerve function occurred in 1.7% (N = 1). CONCLUSION: Stereotactic RT of vestibular schwannoma provides good functional outcomes and high control rates. Dependence of hearing preservation on time of follow-up and initial tumor stage has to be considered.
EVALuna2:32910

Stimmqualitätsmessung mittels prosodischer Analyse verschiedener gelesener Textabschnitte - Haderlein, Tino; Nöth, Elmar; Döllinger, Michael; Schützenberger, Anne (Aktuelle phoniatrisch-pädaudiologische Aspekte 2017, 2017)
UnivIS-Import:2017-12-18:Pub.2017.tech.IMMD.IMMD5.stimmq_9
Keywords: Sprache

Stimuli-responsive nanosystems for enhanced drug delivery and diagnosis - Cicha, Iwona; Tietze, Rainer; Unterweger, Harald; Lyer, Stefan; Janko, Christina; Civelek, Mehtap; Alexiou, Christoph (Nanomedicine, 2022)
CRIS-Team WoS Importer:2022-11-25

Stochastic Resonance Controlled Upregulation of Internal Noise after Hearing Loss as a Putative Cause of Tinnitus-Related Neuronal Hyperactivity - Krauß, Patrick; Tziridis, Konstantin; Metzner, Claus; Schilling, Achim; Hoppe, Ulrich; Schulze, Holger (Frontiers in Neuroscience, 2016)
Subjective tinnitus is generally assumed to be a consequence of hearing loss. In animal studies it has been demonstrated that acoustic trauma induced cochlear damage can lead to behavioral signs of tinnitus. In addition it was shown that noise trauma may lead to deafferentation of cochlear inner hair cells (IHC) even in the absence of elevated hearing thresholds, and it seems conceivable that such hidden hearing loss may be sufficient to cause tinnitus. Numerous studies have indicated that tinnitus is correlated with pathologically increased spontaneous firing rates and hyperactivity of neurons along the auditory pathway. It has been proposed that this hyperactivity is the consequence of a mechanism aiming to compensate for reduced input to the auditory system by increasing central neuronal gain, a mechanism referred to as homeostatic plasticity (HP), thereby maintaining mean firing rates over longer timescales for stabilization of neuronal processing. Here we propose an alternative, new interpretation of tinnitus-related development of neuronal hyperactivity in terms of information theory. In particular, we suggest that stochastic resonance (SR) plays a key role in both short- and long-term plasticity within the auditory system and that SR is the primary cause of neuronal hyperactivity and tinnitus. We argue that following hearing loss, SR serves to lift signals above the increased neuronal thresholds, thereby partly compensating for the hearing loss. In our model, the increased amount of internal noise-which is crucial for SR to work-corresponds to neuronal hyperactivity which subsequently causes neuronal plasticity along the auditory pathway and finally may lead to the development of a phantom percept, i.e., subjective tinnitus. We demonstrate the plausibility of our hypothesis using a computational model and provide exemplary findings in human patients that are consistent with that model. Finally we discuss the observed asymmetry in human tinnitus pitch distribution as a consequence of asymmetry of the distribution of auditory nerve type I fibers along the cochlea in the context of our model.
EVALuna2:33193

Strategies to optimize the biocompatibility of iron oxide nanoparticles - "SPIONs safe by design" - Janko, Christina; Zaloga, Jan; Poettler, Marina; Dürr, Stephan; Eberbeck, Dietmar; Tietze, Rainer; Lyer, Stefan; Alexiou, Christoph (Journal of Magnetism and Magnetic Materials, 2017)
Various nanoparticle systems have been developed for medical applications in recent years. For constant improvement of efficacy and safety of nanoparticles, a close interdisciplinary interplay between synthesis, physicochemical characterizations and toxicological investigations is urgently needed. Based on combined toxicological data, we follow a safe-by design strategy for our superparamagnetic iron oxide nanoparticles (SPION). Using complementary interference-free toxicological assay systems, we initially identified agglomeration tendencies in physiological fluids, strong uptake by cells and improvable biocompatibility of lauric acid (LA)-coated SPIONs (SPIONLA). Thus, we decided to further stabilize those particles by an artificial protein corona consisting of serum albumin. This approach finally lead to increased colloidal stability, augmented drug loading capacity and improved biocompatibility in previous in vitro assays. Here, we show in whole blood ex vivo and on isolated red blood cells (RBC) that a protein corona protects RBCs from hemolysis by SPIONs. (C) 2016 Elsevier B.V. All rights reserved.
EVALuna2:33179

Studies on the adsorption and desorption of mitoxantrone to lauric acid/albumin coated iron oxide nanoparticles - Zaloga, Jan; Feoktystov, Artem; Garamus, Vasil M.; Karawacka, Weronika; Ioffe, Alexander; Brueckel, Thomas; Tietze, Rainer; Alexiou, Christoph; Lyer, Stefan (Colloids and Surfaces B-Biointerfaces, 2018)
A rational use of superparamagnetic iron oxide nanoparticles (SPIONs) in drug delivery, diagnostics, and other biomedical applications requires deep understanding of the molecular drug adsorption/desorption mechanisms for proper design of new pharmaceutical formulations. The adsorption and desorption of the cytostatic Mitoxantrone (MTO) to lauric acid-albumin hybrid coated particles SPIONs (SEONLA-HSA) was studied by Fourier transform infrared spectroscopy (FTIR), dynamic light scattering (DLS), surface titration, release experiments and small-angle neutron and X-ray scattering. Such MTO-loaded nanoparticles have shown very promising results in in vivo animal models before, while the exact binding mechanism of the drug was unknown. SEONLA-HSAformulations have shown better stability under drug loading in comparison with uncoated nanoparticle and sustainable drug release to compare with protein solution. Adsorption of MTO to SEONLA-HSAleads to decreasing of absolute value of zeta potential and repulsive interaction among particles, which points to the location of separate molecules of MTO on the outer surface of LA-HSA shell.
EVALuna2:33222

Subjective improvement of hearing through cochlear implantation - Volleth, Nadine; Hast, A.; Lehmann, E. K.; Hoppe, Ulrich (HNO, 2018)
BACKGROUND: During the past few decades various questionnaires have been developed to evaluate quality of life using audiological measures. The Hearing Implant Sound Quality Index (HISQUI) was developed especially for patients with a cochlear implant (CI). The aim of this study was to evaluate subjective hearing improvement after CI surgery and to correlate the results with objective measuring methods such as pure-tone and speech audiometry. MATERIALS AND METHODS: Pre- and postoperative data of 57 patients who received a cochlear implant (CIs) were retrospectively analyzed. For evaluation of subjective hearing ability the HISQUI questionnaire consisting of 19 questions was used as reference. Pure-tone audiometry and Freiburger monosyllable word tests were used as objective measurements for hearing. RESULTS: The mean HISQUI score increased on average from 53.0 prior to surgery to 69.0 after surgery. In addition, there were significant improvements in all seven subgroups of the questionnaire divisions. A correlation of rSp = 0.53 before surgery and rSp = 0.36 after surgery between the HISQUI scores and Freiburg monosyllable word test was recorded. In addition the 4FPTA (four frequency pure tone average) value correlated negatively with rSp = -0.48 with the HISQUI total score before surgery. CONCLUSION: The moderate correlation of both subjective and objective measurement methods underlines the importance of enquiring the patients' subjective perception and satisfaction. Through the combination of subjective statements and measurements of speech comprehension it is possible to obtain a comprehensive picture of the hearing performance of CI recipients.
EVALuna2:35452

Submandibular gland pleomorphic adenoma: Histopathological capsular characteristics and correlation with the surgical outcome - Mantsopoulos, Konstantinos; Goncalvesa, Miguel; Koch, Michael; Iro, Heinrich; Agaimy, Abbas (Annals of Diagnostic Pathology, 2018)
Pleomorphic adenoma (PA) of the submandibular gland is known to have a very low recurrence rate. The aim of this study was to investigate the histopathological and capsular characteristics of submandibular gland PA, looking for any differences between submandibular PA and the reported data for PA of the parotid gland as possible explanation for its low recurrence rate. We reviewed 72 submandibular gland PM resected at our center between 2000 and 2016. Patient age ranged from 14 to 77 years (mean, 47.2). At least follow (range, 12 to 170 months; mean, 82), none of the 72 patients developed a local recurrence. Histologically, all of the tumors were encased by a complete and intact anatomical capsule (100%). Pseudopodia were detected in 11 (15.3%) and satellite nodules in 3 (4.2%) cases. The histological subtype (according to Seifert et al.) was classic (mixed) in 39 (54.2%), stroma-rich/myxoid in 18/72 (25%) and cellular in 15 (20.8%) cases. A complete rim of healthy pericapsular tissue encasing the tumor and its capsule was observed in only 23/72 (31.9%) cases. In conclusion, submandibular PAs are characterized by consistent presence of an intact anatomical capsule, infrequent occurrence of pseudopodia, a remarkably infrequent occurrence lower frequency of secondary satellite tumor nodules and a comparatively lower proportion of the fragile risky myxoid subtype. Despite the fact that surgery of the submandibular gland can frequently lead to focal capsular exposure, the aforementioned capsular characteristics of submandibular gland PA are probably responsible for the excellent oncologic results.
EVALuna2:34875

Successful free flap salvage surgery with off-label use of Alteplase: A case report, review of the literature and our free flap salvage algorithm - Barhoum, Fatima; Tschaikowsky, Klaus; Koch, Michael; Kapsreiter, Markus; Sievert, Matti; Müller, Susanna; Goncalves, Miguel; Traxdorf, Maximilian; Scherl, Claudia (International Journal of Surgery Case Reports, 2020)
Introduction: Microvascular free tissue transfer is a technique for reconstruction of large defects in head and neck surgery. Failure due to microvascular thrombosis can lead to microvascular damage or flap loss. Recombinant tissue-type plasminogen activator (Alteplase) is still an off-label use but it can help to rescue free flaps when embedded in a salvage algorithm. Presentation of case: A 39-year-old patient with received a tumor resection and reconstruction by a radial forearm flap of the left palate. Postoperatively a venous flap thrombosis occurred and immediate surgical revision was done. Initially eperfusion of the flap could not be achieved even after mechanical removal of the thrombus. Then a thrombolysis with Alteplase, which was applied directly into the radial artery, was done. The flap was salvaged and is now completely integrated into the mucosa. Flap salvage procedure was performed according to our free flap salvage algorithm. Discussion: Thrombolysis with Alteplase for free flap salvage is not a common method. Pedicle thrombosis cannot be predicted. Important procedures during surgical intervention when thrombosis occurs are careful reopening, removal of thrombus, flushing with heparin. Since these procedures failed, surgeons decided to employ Alteplase to optimally rescue the flap. Conclusion: The present case shows that pharmacological thrombolysis with Alteplase is an effective ultima ratio in free flap salvage with venous thrombosis, although it is still considered offlabel use. Early detection of flap failure and a clear salvage algorithm are important for successful surgical revisions.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Alteplase; Flap salvage with recombinant tissue-type plasminogen activator; Free flap salvage; Free flap salvage algorithm; Recombinant tissue-type plasminogen activator; Venous thrombosis

Superparamagnetic iron oxide nanoparticles carrying chemotherapeutics improve drug efficacy in monolayer and spheroid cell culture by enabling active accumulation - Nguyen, Khanh; Nuß, Bianca; Mühlberger, Marina; Unterweger, Harald; Friedrich, Ralf P.; Alexiou, Christoph; Janko, Christina (Nanomaterials, 2020)
Cytotoxic and cytostatic chemotherapeutics act by attacking rapidly dividing tumor cells, predominantly affecting malignant tissue and to a certain degree preserving healthy cells. Nonetheless, severe side effects are caused as quickly proliferating healthy cells such as hematopoietic precursors and mucous membranes are impaired as well. This limits the administered dose and eventually allows tumor cells to escape treatment. In order to increase intratumoral drug concentration and simultaneously reduce systemic side effects, nanoparticles have come into focus as drug carriers. The functionalization of superparamagnetic iron oxide nanoparticles (SPIONs) with chemotherapeutics such as mitoxantrone (MTO) enables targeted drug transport by using magnetic forces. Here, we investigate SPIONs consisting of individual iron oxide cores of 10 nm in diameter and a total hydrodynamic diameter of 53 ± 0.8 nm as a transporting system for MTO. Comparing the killing efficacy in monolayer cell culture and multicellular tumor spheroids of HT-29 cells, we show that spheroids tolerate considerably higher doses of nanoparticle-loaded MTO. Therefore, dose predictions from conventional monolayer cell cultures are often misleading for in vivo applications. This was true for both soluble and nanoparticle-bound MTO. Using flow chambers mimicking in vivo blood flow, we furthermore demonstrate that SPIONs can magnetically accumulate MTO. We conclude that SPIONs can function as an effective delivery platform to increase local drug concentrations, thereby potentially overcoming chemotherapy resistance of cells.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Chemotherapy; Drug resistance; Magnetic drug targeting; Mitoxantrone; Nanomedicine; Superparamagnetic iron oxide nanoparticles; Tumor spheroids

Superparamagnetic Iron Oxide Nanoparticles for Targeted Cell Seeding: Magnetic Patterning and Magnetic 3D Cell Culture - Kappes, Mona; Friedrich, Bernhard; Pfister, Felix; Huber, Christian; Friedrich, Ralf Phillipp; Stein, René; Braun, Christian; Band, Julia; Schreiber, Eveline; Alexiou, Christoph; Janko, Christina (Advanced Functional Materials, 2022)
In regenerative medicine, noncontact manipulation of cells enables new possibilities for tissue engineering. Due to their physicochemical properties, superparamagnetic iron oxide nanoparticles (SPIONs) are used in biomedicine for various applications, e.g., as drug transporters, contrast agents or to make cells maneuverable by magnetic forces. SPIONs attached to and/or taken up by cells enable their magnetic targeting for adoptive immune therapies or tissue engineering. Remote control of different “magnetized” cell types can be used to construct multilayered tissues without the need for a scaffold structure. Here, the suitability of SPIONs with various coatings, such as polyacrylic acid-co-maleic acid (PAM), lauric acid (LA), lauric acid-human serum albumin (HSA), and citrate to magnetize cells is compared with the commercially available NanoShuttle-PL, designed for use in magnetic 3D cell cultures. Depending on the amount of cellular labeling, magnetic control is more or less effective. In particular, PAM- and citrate-coated SPIONs achieve good cellular loading and provide magnetic controllability of cells. In 2D cell culture, the magnetic cargo allows the patterned culture of cells. In 3D, SPIONs enable and accelerate spheroid formation as well as micropatterning using unloaded and loaded cells in parallel.
CRIS-Team Scopus Importer:2022-08-12
Keywords: 3D cell culture; iron oxide nanoparticles; magnetic targeting

Surface Modification of SPIONs in PHBV Microspheres for Biomedical Applications - Idris, Maizlinda Izwana Binti; Zaloga, Jan; Detsch, Rainer; Roether, Judith; Unterweger, Harald; Alexiou, Christoph; Boccaccini, Aldo R. (Scientific Reports, 2018)
Surface modification of superparamagnetic iron oxide nanoparticles (SPIONs) has been introduced with lauric acid and oleic acid via co-precipitation and thermal decomposition methods, respectively. This modification is required to increase the stability of SPIONs when incorporated in hydrophobic, biodegradable and biocompatible polymers such as poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV). In this work, the solid-in-oil-in-water (S/O/W) emulsion-solvent extraction/evaporation method was utilized to fabricate magnetic polymer microspheres incorporating SPIONs in PHBV. The prepared magnetic PHBV microspheres exhibited particle sizes <1 mu m. The presence of functional groups of lauric acid, oleic acid and iron oxide in the PHBV microspheres was confirmed by Fourier Transform Infrared spectroscopy (FTIR). X-ray diffraction (XRD) analysis was performed to further confirm the success of the combination of modified SPIONs and PHBV. Thermogravimetric analysis (TGA) indicated that PHBV microspheres were incorporated with SPIONs(Lauric) as compared with SPIONs(Oleic). This was also proven via magnetic susceptibility measurement as a higher value of this magnetic property was detected for PHBV/SPIONs(Lauric) microspheres. It was revealed that the magnetic PHBV microspheres were non-toxic when assessed with mouse embryotic fibroblast cells (MEF) at different concentrations of microspheres. These results confirmed that the fabricated magnetic PHBV microspheres are potential candidates for use in biomedical applications.
Keywords: biomedical materials; cell culture; superparamagnetic iron oxide nanoparticles

Surfactant proteins of the human larynx - Sheats, Michelle; Schröder, Henrik; Rauscha, F.; Bohr, Christopher; Kißlinger, Franziska; De Tristan, J.; Iro, Heinrich; Garreis, Fabian; Paulsen, Friedrich; Schicht, Martin; Bräuer, Lars (Annals of Anatomy-Anatomischer Anzeiger, 2016)
PURPOSE: Surfactant proteins (SPs) originally identified in lung tissue are important players in the innate immune system. Beyond this, they contribute to stability and rheology of gaseous or aqueous interphases. In the present study, we determined the expression and presence of SPs (A, B, C and D) in different areas of the human larynx. METHODS: mRNA expression of SP-A, -B, -C and -D was analyzed by means of RT-PCR in healthy samples of epiglottis, vocal and vestibular folds, subglottis and trachea. Distribution and localization of all four SPs were analyzed by Western blot and immunohistochemistry in healthy human tissue samples. RESULTS: All four SPs were detected at the mRNA- and protein level in the human larynx as well as by means of immunohistochemistry in the different tissue samples of the human larynx. CONCLUSION: The results reveal that all four SPs are produced with different expression patterns within the human larynx. Based on the known functions, our results suggest that SPs might be involved in maintaining mucus rheology and subsequently they could be essential components for proper phonation. Moreover, the proteins seem to play a role in immune defense of the larynx.
EVALuna2:33358

Surgery for Benign Salivary Neoplasms - Gillespie, M. Boyd; Iro, Heinrich (Advances in Oto-Rhino-Laryngology, 2016)
Salivary neoplasms are relatively infrequent entities that account for only 4% of tumors of the head and neck. Although slow-growing lesions of the preauricular area and submandibular space are often confused with sebaceous cysts, lymph nodes, or lipomas by the non-otolaryngologist, otolaryngologists-head and neck surgeons recognize that all preauricular and submandibular masses should be considered a salivary neoplasm until proven otherwise. Surgery remains the treatment of choice for benign salivary gland neoplasms; however, techniques continue to evolve in order to preserve salivary function and reduce surgical morbidity. The goals of management of benign salivary neoplasms include accurate diagnosis of the lesion, complete surgical extirpation, and functional preservation of adjacent cranial nerves. Accurate diagnosis is aided by appropriate preoperative physical examination, imaging, and fine needle aspiration biopsy. Benign neoplasms typically present as slow-growing, painless, mobile masses without adverse features, such as tissue fixation, ulceration, a cranial nerve deficit, or regional lymphadenopathy. Preoperative imaging with ultrasonography, computed tomography, or magnetic resonance imaging reveals well-circumscribed lesions without an infiltrative growth pattern or associated adenopathy. Fine needle aspiration biopsy may favor a benign neoplasm, supporting the clinical presentation. Surgery for a benign or malignant salivary neoplasm is in essence a false dichotomy since the surgeon can never be completely confident of the diagnosis until the specimen is removed. The surgeon must recognize the significant overlap between benign and malignant salivary masses in terms of clinical presentation, imaging, and cytology, which requires the surgeon to remain vigilant and flexible at the time of surgery should tissue characteristics or frozen section analysis suggest a malignant process.
EVALuna2:33359

Surgery for parotid gland cancer-controversial and proven aspects - Mantsopoulos, Konstantinos; Iro, Heinrich (HNO, 2022)
Background Due to the rarity of primary parotid malignancies, there are currently only limited clinical study data on the optimal surgical therapy. Parotid malignancies encompass a broad spectrum of more than 20 different histological subtypes with varying biology, which thus represents a challenge for even experienced pathologists and head and neck surgeons with proven expertise in salivary gland surgery. Objective The aim of this review article is to provide an overview of the current literature on surgical therapy of the primary tumor and the cN0 neck as well as treatment of the facial nerve, and to shed light on the various controversial aspects of this topic. Results In salivary gland oncology there is a trend towards safe (R0) but more conservative surgery. Currently, less-invasive surgical approaches could potentially be applied in a small subgroup with carefully selected caudally located and R0-resected "low-grade tumors" in stages T1-T2 and cN0 in relatively young patients with high compliance and more in the context of structured clinical studies. Elective neck dissection in the case of cN0 status should be carried out if risk factors for occult cervical lymph node metastasis (T3-T4a, "high-grade subtypes," advanced age, lymphangitic carcinomatosis) are present. In cases of small "low-grade parotid carcinomas," narrow resection margins or even microscopic tumor residues on the facial nerve can potentially be adequately compensated with adjuvant radiation therapy. However, due to the lack of solid data, the significance of the actual effect of the radiation in this situation should be viewed with great caution.
CRIS-Team WoS Importer:2022-05-27

Survival and Prognostic Analysis after Pulmonary Metastasectomy for Head and Neck Cancer - Dudek, Wojciech; AlMoussa, Emad; Schreiner, Waldemar; Mantsopoulos, Konstantinos; Sirbu, Horia (Thoracic and Cardiovascular Surgeon, 2020)
BACKGROUND: There is no consensus on the value of pulmonary metastasectomy (PM) for head and neck cancer (HNC). The aim of our single-institution study was to evaluate outcomes and to examine factors influencing 5-year survival of patients undergoing resections for HNC lung metastases. METHODS: All HNC patients undergoing curative-intent PM between January 2008 and December 2018 were retrospectively analyzed. The impact of factors related to primary tumor, metastases, and associated therapy on patient survival was evaluated using the univariable Cox proportional hazard model. Cutoff values of continuous variables were determined by a receiver operating characteristic analysis. RESULTS: In total, 44 patients (32 males and 12 females, with a median age of 65 years) underwent PM for metastatic HNC. There was one perioperative death, and major complications occurred in 2 (4.5%) patients. The median interval between the treatment of primary tumor and PM was 19.4 months (range: 0-151 months). Median size of the largest resected pulmonary lesion was 1.3 cm (range: 0.3-6.9 cm). Mean follow-up was 21 months (range: 0-123 months), and 5-year overall survival (OS) rate after the first PM was 41%. Resection was complete (R0) in all patients. Larger size of pulmonary metastasis (≥1.4 cm; hazard ratio: 4.49; 95% confidence interval: 1.79-11.27) was a significantly negative prognostic factor. CONCLUSION: Despite the lack of randomized controlled trials, PM for HNC is a reasonable therapeutic option with favorable survival in a selected population. In patients with larger pulmonary lesions, shorter OS after PM is to be expected.
CRIS-Team Scopus Importer:2020-06-30

Survival benefit for patients treated in a certified head and neck tumor center. - von Wilmowsky, Cornelius; Traxdorf, Maximilian; Adler, Werner; Neukam, Friedrich Wilhelm; Iro, Heinrich; Nkenke, Emeka; Kesting, Marco Rainer; Wurm, Matthias (European Review for Medical and Pharmacological Sciences, 2019)
OBJECTIVE: Increasing effort has been put in the implementation and certification of head and neck tumor centers in order to establish standardized, quality assured health care for head and neck tumor patients. This study evaluated survival rates after treatment in a certified head and neck tumor center (CHNTC) vs. a non-certified head and neck tumor center (non-CHNTC) in Middle Franconia, Germany. PATIENTS AND METHODS: Age, sex, possible obituary, and typical relevant prognostic variables were analyzed. Diagnosis was recorded according to ICD10. Clinical and pathological TNM staging, tumor grading, localization, R-stage, and morphology were assessed (ICD-0). Patients diagnosed with oral cancer (N=1047) were divided into groups based on where they received their primary treatment; CHNTCs or non-CHNTCs. RESULTS: Patients treated at CHNTCs had significantly higher survival rates vs. those treated at non-CHNTC (p=0.023) in univariate analysis. In a Cox regression model, survival rates for patients with pN0 and pN+ stage were similar at both types of centers. Men with pN0 had significantly lower survival rates (HR=0.497, p<0.001). Age had a statistically significant influence on survival rates independently from pN stage (HR=1.031 per year, p<0.001 in both groups). CONCLUSIONS: Patients treated at CHNTC had better survival rates than those treated at non-CHNTC.
EVALuna2:184478

Survival benefit for patients treated in a certified head and neck tumor center - von Wilmowsky, Cornelius; Traxdorf, Maximilian; Adler, Werner; Neukam, Friedrich Wilhelm; Iro, Heinrich; Nkenke, Emeka; Kesting, Marco Rainer; Wurm, Matthias (European Review for Medical and Pharmacological Sciences, 2019)
OBJECTIVE: Increasing effort has been put in the implementation and certification of head and neck tumor centers in order to establish standardized, quality assured health care for head and neck tumor patients. This study evaluated survival rates after treatment in a certified head and neck tumor center (CHNTC) vs. a non-certified head and neck tumor center (non-CHNTC) in Middle Franconia, Germany. PATIENTS AND METHODS: Age, sex, possible obituary, and typical relevant prognostic variables were analyzed. Diagnosis was recorded according to ICD10. Clinical and pathological TNM staging, tumor grading, localization, R-stage, and morphology were assessed (ICD-0). Patients diagnosed with oral cancer (N=1047) were divided into groups based on where they received their primary treatment; CHNTCs or non-CHNTCs. RESULTS: Patients treated at CHNTCs had sig - nificantly higher survival rates vs. those treated at non-CHNTC (p=0.023) in univariate analysis. In a Cox regression model, survival rates for patients with pN0 and pN+ stage were similar at both types of centers. Men with pN0 had significantly lower survival rates (HR=0.497, p<0.001). Age had a statistically significant influence on survival rates independently from pN stage (HR=1.031 per year, p<0.001 in both groups). CONCLUSIONS: Patients treated at CHNTC had better survival rates than those treated at non-CHNTC.
CRIS-Team Scopus Importer:2019-05-09
Keywords: Certification; Head; Neck Tumor Center; Prognosis; Survival

Synthesis and characterization of citrate-stabilized gold-coated superparamagnetic iron oxide nanoparticles for biomedical applications - Stein, René; Friedrich, Bernhard; Mühlberger, Marina; Cebulla, Nadine; Schreiber, Eveline; Tietze, Rainer; Cicha, Iwona; Alexiou, Christoph; Dutz, Silvio; Boccaccini, Aldo R.; Unterweger, Harald (Molecules, 2020)
Surface-functionalized gold-coated superparamagnetic iron oxide nanoparticles (Au-SPIONs) may be a useful tool in various biomedical applications. To obtain Au-SPIONs, gold salt was precipitated onto citrate-stabilized SPIONs (Cit-SPIONs) using a simple, aqueous one-pot technique inspired by the Turkevich method of gold nanoparticle synthesis. By the further stabilization of the Au-SPION surface with additional citrate (Cit-Au-SPIONs), controllable and reproducible Z-averages enhanced long-term dispersion stability and moderate dispersion pH values were achieved. The citrate concentration of the reaction solution and the gold/iron ratio was found to have a major influence on the particle characteristics. While the gold-coating reduced the saturation magnetization to 40.7% in comparison to pure Cit-SPIONs, the superparamagnetic behavior of Cit-Au-SPIONs was maintained. The formation of nanosized gold on the SPION surface was confirmed by X-ray diffraction measurements. Cit-Au-SPION concentrations of up to 100 µg Fe/mL for 48 h had no cytotoxic effect on Jurkat cells. At a particle concentration of 100 µg Fe/mL, Jurkat cells were found to take up Cit-Au-SPIONs after 24 h of incubation. A significantly higher attachment of thiol-containing L-cysteine to the particle surface was observed for Cit-Au-SPIONs (53%) in comparison to pure Cit-SPIONs (7%).
CRIS-Team Scopus Importer:2020-10-16
Keywords: Characterization; Cytotoxicity; Gold coating; Nanoparticles; Superparamagnetic iron oxide nanoparticles (SPIONs); Surface functionalization; Thiol-binding

Synthesis and characterization of tissue plasminogen activator—functionalized superparamagnetic iron oxide nanoparticles for targeted fibrin clot dissolution - Heid, Susanne; Unterweger, Harald; Tietze, Rainer; Friedrich, Ralf P.; Weigel, Bianca; Cicha, Iwona; Eberbeck, Dietmar; Boccaccini, Aldo R.; Alexiou, Christoph; Lyer, Stefan (International Journal of Molecular Sciences, 2017)
Superparamagnetic iron oxide nanoparticles (SPIONs) have attracted great attention in many biomedical fields and are used in preclinical/experimental drug delivery, hyperthermia and medical imaging. In this study, biocompatible magnetite drug carriers, stabilized by a dextran shell, were developed to carry tissue plasminogen activator (tPA) for targeted thrombolysis under an external magnetic field. Different concentrations of active tPA were immobilized on carboxylated nanoparticles through carbodiimide-mediated amide bond formation. Evidence for successful functionalization of SPIONs with carboxyl groups was shown by Fourier transform infrared spectroscopy. Surface properties after tPA immobilization were altered as demonstrated by dynamic light scattering and ζ potential measurements. The enzyme activity of SPION-bound tPA was determined by digestion of fibrin-containing agarose gels and corresponded to about 74% of free tPA activity. Particles were stored for three weeks before a slight decrease in activity was observed. tPA-loaded SPIONs were navigated into thrombus-mimicking gels by external magnets, proving effective drug targeting without losing the protein. Furthermore, all synthesized types of nanoparticles were well tolerated in cell culture experiments with human umbilical vein endothelial cells, indicating their potential utility for future therapeutic applications in thromboembolic diseases.
Keywords: Activated ester reaction; Drug targeting; Fibrinolysis; Protein binding; Superparamagnetic iron oxide nanoparticles; Tissue plasminogen activator

Synthesis of Magnetic-Nanoparticle/Ansamitocin Conjugates-Inductive Heating Leads to Decreased Cell Proliferation In Vitro and Attenuation Of Tumour Growth In Vivo - Seidel, Katja; Balakrishnan, Asha; Alexiou, Christoph; Janko, Christina; Komoll, Ronja-Melinda; Wang, Liang-Liang; Kirschning, Andreas; Ott, Michael (Chemistry - A European Journal, 2017)
Conjugates based on nanostructured, superparamagnetic particles, a thermolabile linker and a cytotoxic maytansinoid were developed to serve as a model for tumour-selective drug delivery and release. It combines chemo- with thermal therapy. The linker-modified toxin was prepared by a combination of biotechnology and semisynthesis. Drug release was achieved by hyperthermia through an external oscillating electromagnetic field that induces heat inside the particles. Efficacy of this release concept was demonstrated both for cancer cell proliferation in vitro, and for tumour growth in vivo, in a xenograft mouse model. Biocompatibility studies for these magnetic-nanoparticle/ansamitocin conjugates complement this work.
EVALuna2:33212

Synthetic mucus for an ex vivo phonation setup: Creation, application, and effect on excised porcine larynges - Peters, Gregor; Jakubaß, Bernhard; Weidenfeller, Katrin; Kniesburges, Stefan; Böhringer, David; Wendler, Olaf; Mueller, Sarina K.; Gostian, Antoniu-Oreste; Berry, David A.; Döllinger, Michael; Semmler, Marion (Journal of the Acoustical Society of America, 2022)
Laryngeal mucus hydrates and lubricates the deformable tissue of the vocal folds and acts as a boundary layer with the airflow from the lungs. However, the effects of the mucus' viscoelasticity on phonation remain widely unknown and mucus has not yet been established in experimental procedures of voice research. In this study, four synthetic mucus samples were created on the basis of xanthan with focus on physiological frequency-dependent viscoelastic properties, which cover viscosities and elasticities over 2 orders of magnitude. An established ex vivo experimental setup was expanded by a reproducible and controllable application method of synthetic mucus. The application method and the suitability of the synthetic mucus samples were successfully verified by fluorescence evidence on the vocal folds even after oscillation experiments. Subsequently, the impact of mucus viscoelasticity on the oscillatory dynamics of the vocal folds, the subglottal pressure, and acoustic signal was investigated with 24 porcine larynges (2304 datasets). Despite the large differences of viscoelasticity, the phonatory characteristics remained stable with only minor statistically significant differences. Overall, this study increased the level of realism in the experimental setup for replication of the phonatory process enabling further research on pathological mucus and exploration of therapeutic options. (c) 2022 Acoustical Society of America.
CRIS-Team WoS Importer:2023-01-06

Systematic classification of confocal laser endomicroscopy for the diagnosis of oral cavity carcinoma - Sievert, Matti; Oetter, Nicolai; Mantsopoulos, Konstantinos; Gostian, Antoniu-Oreste; Mueller, Sarina K.; Koch, Michael; Balk, Matthias; Thimsen, Vivian; Stelzle, Florian; Eckstein, Markus; Iro, Heinrich; Goncalves, Miguel (Oral Oncology, 2022)
Introduction: Confocal laser endomicroscopy (CLE) is an optical imaging technique that allows in vivo microscope-like images of the upper aerodigestive tract's mucosa in 1000-fold magnification. The assessment of morphological tissue characteristics for the correct differentiation between healthy and malignoma suspected mucosa requires strict evaluation criteria. This study aims to validate a score for oral cavity squamous cell carcinoma (OCSCC) diagnostic. Methods: We performed CLE and examined a total of twelve patients. All 95 sequences (778 s, 6224 images) originate from the area of the primary tumor 260 s, 2080 images) and unsuspicious mucosa of the oral cavity (518 s, 4144 images). Specimen were taken at corresponding locations and analyzed histologically in H&E staining as a reference standard. A total of eight examiners (four experienced and four inexperienced) evaluated the sequences based on a scoring system. The primary endpoints are sensitivity, specificity, and accuracy. Secondary endpoints are inter-rater reliability and receiver operator characteristics. Results: Healthy mucosa showed epithelium with uniform size and shape with distinct cytoplasmic membranes and regular vessel architecture. CLE of malignant cells demonstrated a disorganized arrangement of variable cellular morphology. We calculated an accuracy, sensitivity, specificity, PPV, and NPV of 88.7 %, 90.1 %, 87.4 %, 87.5 %, and 90.0 %, respectively, with inter-rater reliability and κ-value of 0.775, and an area under the curve of 0.935. Conclusions: The results confirm that this scoring system is applicable in the oral cavity mucosa to classify benign and malignant tissue.
CRIS-Team Scopus Importer:2022-08-12
Keywords: Carcinoma; Squamous cell/diagnosis; Confocal laser endomicroscopy; Early detection of cancer*; Endoscopy; Fluorescence; Fluorescent dyes; Head and neck cancer; Head and neck neoplasms/diagnosis; Head and neck neoplasms/pathology*; Humans; Lasers; Margins of excision; Microscopy; Confocal/methods*; Mouth neoplasms*/diagnosis; Optical biopsy; Oral cavity squamous cell carcinoma; Safe surgical margins

Systematic interpretation of confocal laser endomicroscopy: larynx and pharynx confocal imaging score Interpretazione sistematica dell’endomicroscopia confocale laser: punteggio endomicroscopico confocale laringeo e faringeo - Sievert, Matti; Mantsopoulos, Konstantinos; Müller-Hübner, Sarina; Eckstein, Markus; Rupp, Robin; Aubreville, Marc; Stelzle, Florian; Oetter, Nicolai; Maier, Andreas; Iro, Heinrich; Goncalves, Miguel (Acta Otorhinolaryngologica Italica, 2022)
Objective. Development and validation of a confocal laser endomicroscopy (CLE) classification score for the larynx and pharynx. Methods. Thirteen patients (154 video sequences, 9240 images) with laryngeal or phar-yngeal SCC were included in this prospective study between October 2020 and February 2021. Each CLE sequence was correlated with the gold standard of histopathological ex-amination. Based on a dataset of 94 video sequences (5640 images), a scoring system was developed. In the remaining 60 sequences (3600 images), the score was validated by four CLE experts and four head and neck surgeons who were not familiar with CLE. Results. Tissue homogeneity, cell size, borders and clusters, capillary loops and the nu-cleus/cytoplasm ratio were defined as the scoring criteria. Using this score, the CLE experts obtained an accuracy, sensitivity, and specificity of 90.8%, 95.1%, and 86.4%, respectively, and the CLE non-experts of 86.2%, 86.4%, and 86.1%. Interobserver agreement Fleiss’ kappa was 0.8 and 0.6, respectively. Conclusions. CLE can be reliably evaluated based on defined and reproducible imaging features, which demonstrate a high diagnostic value. CLE can be easily integrated into the intraoperative setting and generate real-time, in-vivo microscopic images to demarcate malignant changes.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Classification system; Confocal laser endomicroscopy; Head and neck cancer; Larynx; Non-invasive histological imaging; Pharynx

Systematic screening of isogenic cancer cells identifies DUSP6 as context-specific synthetic lethal target in melanoma - Wittig-Blaich, Stephanie; Wittig, Rainer; Schmidt, Steffen; Lyer, Stefan; Bewerunge-Hudler, Melanie; Gronert-Sum, Sabine; Strobel-Freidekind, Olga; Muller, Carolin; List, Markus; Jaskot, Aleksandra; Christiansen, Helle; Hafner, Mathias; et al. (Oncotarget, 2017)
Next-generation sequencing has dramatically increased genome-wide profiling options and conceptually initiates the possibility for personalized cancer therapy. State-of-the-art sequencing studies yield large candidate gene sets comprising dozens or hundreds of mutated genes. However, few technologies are available for the systematic downstream evaluation of these results to identify novel starting points of future cancer therapies.We improved and extended a site-specific recombination-based system for systematic analysis of the individual functions of a large number of candidate genes. This was facilitated by a novel system for the construction of isogenic constitutive and inducible gain- and loss-of-function cell lines. Additionally, we demonstrate the construction of isogenic cell lines with combinations of the traits for advanced functional in vitro analyses. In a proof-of-concept experiment, a library of 108 isogenic melanoma cell lines was constructed and 8 genes were identified that significantly reduced viability in a discovery screen and in an independent validation screen. Here, we demonstrate the broad applicability of this recombination-based method and we proved its potential to identify new drug targets via the identification of the tumor suppressor DUSP6 as potential synthetic lethal target in melanoma cell lines with BRAF V600E mutations and high DUSP6 expression.
EVALuna2:57246

Systems Medicine Approach for Tinnitus with Comorbid Disorders - Mazurek, Birgit; Rose, Matthias; Schulze, Holger; Dobel, Christian (Nutrients, 2022)
Despite the fact that chronic diseases usually occur together with a spectrum of possible comorbidities that may differ strongly between patients, they are classically still viewed as distinct disease entities and, consequently, are often treated with uniform therapies. Unfortunately, such an approach does not take into account that different combinations of symptoms and comorbidities may result from different pathological (e.g., environmental, genetic, dietary, etc.) factors, which require specific and individualised therapeutic strategies. In this opinion paper, we aim to put forward a more differentiated, systems medicine approach to disease and patient treatment. To elaborate on this concept, we focus on the interplay of tinnitus, depression, and chronic pain. In our view, these conditions can be characterised by a variety of phenotypes composed of variable sets of symptoms and biomarkers, rather than distinct disease entities. The knowledge of the interplay of such symptoms and biomarkers will provide the key to a deeper, mechanistic understanding of disease pathologies. This paves the way for prediction and prevention of disease pathways, including more personalised and effective treatment strategies.
CRIS-Team Scopus Importer:2022-11-11
Keywords: comorbidity; depression; pain; system medicine; tinnitus

Tangential Flow Ultrafiltration Allows Purification and Concentration of Lauric Acid-/Albumin-Coated Particles for Improved Magnetic Treatment - Zaloga, Jan; Stapf, Marcus; Nowak, Johannes; Poettler, Marina; Friedrich, Ralf P.; Tietze, Rainer; Lyer, Stefan; Lee, Geoffrey; Odenbach, Stefan; Hilger, Ingrid; Alexiou, Christoph (International Journal of Molecular Sciences, 2015)
Superparamagnetic iron oxide nanoparticles (SPIONs) are frequently used for drug targeting, hyperthermia and other biomedical purposes. Recently, we have reported the synthesis of lauric acid-/albumin-coated iron oxide nanoparticles SEON(LA-BSA), which were synthesized using excess albumin. For optimization of magnetic treatment applications, SPION suspensions need to be purified of excess surfactant and concentrated. Conventional methods for the purification and concentration of such ferrofluids often involve high shear stress and low purification rates for macromolecules, like albumin. In this work, removal of albumin by low shear stress tangential ultrafiltration and its influence on SEON(LA-BSA) particles was studied. Hydrodynamic size, surface properties and, consequently, colloidal stability of the nanoparticles remained unchanged by filtration or concentration up to four-fold (v/v). Thereby, the saturation magnetization of the suspension can be increased from 446.5 A/m up to 1667.9 A/m. In vitro analysis revealed that cellular uptake of SEON(LA-BSA) changed only marginally. The specific absorption rate (SAR) was not greatly affected by concentration. In contrast, the maximum temperature Tmax in magnetic hyperthermia is greatly enhanced from 44.4 °C up to 64.9 °C by the concentration of the particles up to 16.9 mg/mL total iron. Taken together, tangential ultrafiltration is feasible for purifying and concentrating complex hybrid coated SPION suspensions without negatively influencing specific particle characteristics. This enhances their potential for magnetic treatment.
EVALuna2:19984

Targeted Therapy, Chemotherapy, Immunotherapy and Novel Treatment Options for Different Subtypes of Salivary Gland Cancer - Mueller, Sarina K.; Haderlein, Marlen; Lettmaier, Sebastian; Agaimy, Abbas; Haller, Florian; Hecht, Markus; Fietkau, Rainer; Iro, Heinrich; Mantsopoulos, Konstantinos (Journal of Clinical Medicine, 2022)
Surgical resection remains the first line treatment for salivary gland cancer (SGC). In the case of locally advanced disease, surgery is followed by adjuvant radiotherapy. Surgical resection should be favored in resectable locoregional recurrent disease as well, and even the complete resection of all distant oligometastases has clinical benefit for the patients. For inoperable and disseminated metastatic disease, a multitude of systemic therapies including chemotherapy, targeted therapy, and immunotherapy are available. In this review, the current therapeutic options for inoperable recurrent or metastatic SGCs are summarized. Systemic treatment can achieve prolonged progression-free and overall survival, while the overall prognosis remains poor. Current clinical trials include only a limited number of patients and mostly combine different histologic subtypes. Additionally, no randomized controlled trial comparing different therapeutic options has been performed. In the future, further studies with a larger patient cohort and ideally only one histologic subtype are needed in order to improve the outcome for SGC patients. However, this may be difficult to accomplish due to the rarity and diversity of the disease. Additionally, molecular analyses need to be performed routinely in order to individualize treatment and to go one step further towards precision medicine.
CRIS-Team Scopus Importer:2022-02-04
Keywords: Acinic cell carcinoma; Adenoid cystic carcinoma; Chemotherapy; Immunotherapy; Mucoepidermoid carcinoma; Salivary duct carcinoma; Salivary gland cancer; Targeted therapy

Targeting of drug-loaded nanoparticles to tumor sites increases cell death and release of danger signals - Alev, Magdalena; Egenberger, Laura; Mühleisen, Laura; Weigel, Bianca; Frey, Benjamin; Friedrich, Ralf P.; Poettler, Marina; Alexiou, Christoph; Janko, Christina (Journal of Controlled Release, 2018)
Innovative strategies fighting cancer by inducing anti-tumor responses from the immune system are urgently needed. Amongst others, chemotherapeutics from the class of the anthracyclines have been shown to induce death of cancer cells with immunogenic features and triggering immunogenic anti-tumor responses. However, the patient's immune system often becomes severely impaired by the unspecific action of these cytotoxic drugs in systemic chemotherapy, preventing any effective immune reactions. To reduce systemic side effects and to accumulate the drug exclusively in the tumor region, we developed an iron oxide nanoparticle-based system for the magnetically targeted delivery of mitoxantrone to the tumor, which has previously proven its long-term therapeutic efficacy in tumor bearing rabbits. Here, we show in vitro that superparamagnetic iron oxide nanoparticles (SPIONs), loaded with the chemotherapeutic drug mitoxantrone, are able to induce cell death with immunogenic features and concomitant maturation of dendritic cells, comparable to the free drug, whereas unloaded nanoparticles are very biocompatible. We conclude that the targeted delivery of mitoxantrone to the tumor region might be a promising possibility to selectively modulate the tumor microenvironment and to locally stimulate immune responses against the tumor. Thus, SPIONs can be used as a platform to specifically bring immunogenic cell death inducers (e.g. mitoxantrone, hypericin, doxorubicin) to the tumor region by sparing the immune system from their toxic effects.
EVALuna2:35474

The age effect in evaluation of hearing aid benefits by speech audiometry - Mueller, A.; Hocke, T.; Hoppe, Ulrich; Mir-Salim, P. (HNO, 2016)
BACKGROUND AND AIM: Hearing loss is one of the most common disabilities in the elderly. The aim of this study was to investigate the relationship between pure-tone hearing loss and maximum monosyllabic perception and speech perception with hearing aids. The focus of the investigation was elderly patients. MATERIALS AND METHODS: In this prospective study, 188 patients with sensorineural hearing loss were included. The pure-tone audiogram (4FPTA), the Freiburg speech intelligibility test with headphones and the word recognition score with hearing aids at 65 dB SPL were measured and evaluated. RESULTS: An increasing age was associated with higher discrepancy between the maximum speech perception and speech understanding with hearing aids. The mean difference between maximum monosyllabic perception and speech perception with hearing aids is about 20% in the elderly population. CONCLUSION: The intended goal of hearing aid prescription, the match between maximum monosyllabic perception and word recognition score with hearing aids within 5 to 10%, is not achieved in the elderly population.
EVALuna2:33934

The association of ABCB1 polymorphisms and elevated serum digitoxin concentrations in geriatric patients - Dragonas, Charalampos; Wagner, Jennifer; Heppner, Hans Jürgen; Bertsch, Thomas; Mühlberg, Wolfgang; Wicklein, Susanne; Pahl, Andreas; Bachmakov, Iouri; Sieber, Cornel; Fromm, Martin; et al. (European Journal of Clinical Pharmacology, 2008)
Objective Digitoxin is a known substrate of the efflux pump P-glycoprotein (gene name: ABCB1). P-glycoprotein expression was shown to be modulated by single nucleotide polymorphisms in the ABCB1 gene, but it remains unclear whether these polymorphisms influence digitoxin blood levels. Our objective was to examine the association of ABCB1 C3435T genotype and elevated serum digitoxin concentrations (SDC) in a cohort of 77 geriatric patients consecutively admitted to a geriatric department over a 12-month period.Methods The impact of ABCB1 3435 CC, CT, and TT genotypes on SDC and SDC normalized for daily digitoxin dosage and body weight was assessed by multivariate regression analysis.Results Among participants, 18 (23%) had the CC, 36 (47%) the CT, and 23 (30%) the TT genotype. Adjusting for relevant covariates, no significant association of ABCB1 C3435T genotype and SDC or normalized SDC was detected. Mean SDC was 22.4 ng/ml (95% CI 18.9-25.9) for the TT, 21.8 ng/ml (95% CI 18.1-25.5) for the CT, and 25.7 ng/ml (95% CI 20.6-30.8) for the CC genotype. The means for normalized SDC were 5.2 kg center dot l(-1) (95% CI 4.3-6.1) for the TT, 6.1 kg center dot l(-1) (95% CI 4.7-7.5) for the CT, and 6.2 kg center dot l(-1) (95% CI 4.6-7.7) for the CC genotype.Conclusion In this sample of frail geriatric patients, the impact of ABCB1 C3435T genotype on serum digitoxin concentration was not of major relevance. Regular monitoring of digitoxin blood levels and surveillance of appropriate drug use remain the best ways to prevent digitoxin intoxications in the elderly.
Keywords: digitoxin; ABCB1; polymorphism; P-glycoprotein; geriatric

The COVID-19 pandemic and its consequences for the diagnosis and therapy of head and neck malignancies - Rupp, Robin; de Vasconcelos Craveiro, Antonio; Allner, Moritz; Grundtner, P.; Eckstein, Markus; Hecht, Markus; Iro, Heinrich; Gostian, Antoniu-Oreste; Balk, Matthias (European Review for Medical and Pharmacological Sciences, 2022)
OBJECTIVE: The COVID-19 pandemic and the measures accompanying it have been accused of having a negative influence on the frequency and methods of treatment of various diseases including head and neck cancer (HNSCC). To go further into this assumption, the diagnoses made, and treatments performed at one of Germany's largest head and neck cancer centres were evaluated.
CRIS-Team WoS Importer:2022-02-04

The current value of quantitative shear wave sonoelastography in parotid gland tumors - Thimsen, Vivian; Goncalves, Miguel; Koch, Michael; Mantsopoulos, Konstantinos; Hornung, Joachim; Iro, Heinrich; Schapher, Mirco (Gland Surgery, 2021)
Background: The preoperative differentiation between salivary gland tumor entities using computed tomography, magnetic resonance imaging (MRI) and ultrasound ( US) is still limited. Biopsies are often regarded as indispensable for properly characterizing these various lesions. The aim of this study was to analyze the value of acoustic radiation force impulse (ARFI) sonoelastography as an US differentiation tool when examining parotid gland (PG) lesions.
CRIS-Team WoS Importer:2021-05-28

The Effect of Antibacterial Particle Incorporation on the Mechanical Properties, Biodegradability, and Biocompatibility of PLA and PHBV Composites - Mazur, Karolina; Singh, Raminder; Friedrich, Ralf P.; Genc, Hatice; Unterweger, Harald; Sałasińska, Kamila; Bogucki, Rafał; Kuciel, Stanisław; Cicha, Iwona (Macromolecular Materials and Engineering, 2020)
The composites based on polylactide (PLA) and poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) with the addition of antibacterial particles: silver (Ag) and copper oxide (CuO) are characterized. Basic mechanical properties and biodegradation processes, as well as biocompatibility of materials with human cells are determined. The addition of Ag or CuO to the polymers do not significantly affect their mechanical properties, flammability, or biodegradation rate. However, several differences between the base materials are observed. PLA-based composites have higher tensile and impact strength values, while PHBV-based ones have a higher modulus of elasticity, as well as better mechanical properties at elevated temperatures. Concerning biocompatibility, each of the tested materials support the growth of fibroblasts over time, although large differences are observed in the initial cell attachment. The analysis of hydrolytic degradation effects on the structure of materials shows that PHBV degrades much faster than PLA. The results of this study confirm the good potential of the investigated biodegradable polymer composites with antibacterial particles for future biomedical applications.
CRIS-Team Scopus Importer:2020-08-14
Keywords: biocompatibility; biocomposites; copper oxide particles; poly (3-hydroxybutyrate-co-3-hydroxyvalerate); polylactide; silver particles

The Effect of Nasalance on Vocal Fold Oscillation Patterns During the Male Passaggio - Echternach, Matthias; Högerle, Catalina; Köberlein, Marie; Schlegel, Patrick; Döllinger, Michael; Richter, Bernhard; Kainz, Marie Anne (Journal of Voice, 2019)
Introduction: It is generally assumed that when singing across the region where registration events for untrained voices occur (the passaggio), singers modify the voice production system in order to avoid changes of voice quality. In this context, it has been postulated that nasalance could be used to stabilize vocal function throughout the passaggio. However, whether nasalance is frequently used by professional singers and if so, if it has a stabilizing effect on vocal fold oscillation patterns, is not yet fully understood. Material and Methods: Eight western classically trained professional male singers (6 tenors and 2 baritones) were asked to perform transitions (1) from modal to falsetto register and (2) from modal to stage voice above the passaggio (SVaP) during ascending pitch glides from A3 (ƒo approx. 220 Hz) to A4 (ƒo approx. 440 Hz) on the vowel /i/. Transnasal high-speed videoendoscopy at 20.000 fps was captured simultaneously with electroglottographic, nasal and oral flow, and audio signals, recorded using the same frame rate. The nasalance was calculated from both oral and nasal DC-flow signals. Results: Transitions to SVaP showed greater periodicity and regularity than transitions to falsetto. For 5 subjects, nasalance was increased during the passaggio for the transition to SVaP. For 4 subjects the increase of nasalance for the SVaP was associated with a stabilization of the open quotient and occurred at a comparable fundamental frequency as the increase of the open quotient for the transition to falsetto. Conclusions: Nasalance can be used in order to stabilize oscillatory regularity and open quotient in male singers for singing across the passaggio.
CRIS-Team Scopus Importer:2019-11-12
Keywords: High Speed Videoendoscopy; Nasalance; Passaggio; Register; Velopharyngeal opening; Voice

The Effect of Singers’ Masks on the Impulse Dispersion of Aerosols During Singing - Echternach, Matthias; Herrmann, Laila; Gantner, Sophia; Tur, Bogac; Peters, Gregor; Westphalen, Caroline; Benthaus, Tobias; Köberlein, Marie; Kuranova, Liudmila; Döllinger, Michael; Kniesburges, Stefan (Journal of Voice, 2021)
Background: During the Covid-19 pandemic, singing activities were restricted due to several super-spreading events that have been observed during rehearsals and vocal performances. However, it has not been clarified how the aerosol dispersion, which has been assumed to be the leading transmission factor, could be reduced by masks which are specially designed for singers. Material and Methods: Twelve professional singers (10 of the Bavarian Radio-Chorus and two freelancers, seven females and five males) were asked to sing the melody of the ode of joy of Beethoven's 9th symphony “Freude schöner Götterfunken, Tochter aus Elisium” in D-major without masks and afterwards with five different singers’ masks, all distinctive in their material and proportions. Every task was conducted after inhaling the basic liquid from an e-cigarette. The aerosol dispersion was recorded by three high-definition video cameras during and after the task. The cloud was segmented and the dispersion was analyzed for all three spatial dimensions. Further, the subjects were asked to rate the practicability of wearing the tested masks during singing activities using a questionnaire. Results: Concerning the median distances of dispersion, all masks were able to decrease the impulse dispersion of the aerosols to the front. In contrast, the dispersion to the sides and to the top was increased. The evaluation revealed that most of the subjects would reject performing a concert with any of the masks. Conclusion: Although, the results exhibit that the tested masks could be able to reduce the radius of aerosol expulsion for virus-laden aerosol particles, there are more improvements necessary to enable the practical implementations for professional singing.
CRIS-Team Scopus Importer:2021-10-15
Keywords: Aerosols; COVID19; Dispersion; Singing

The Effect of Water Resistance Therapy on the Impulse Dispersion of Aerosols During Sustained Phonation - Köberlein, Marie Christine; Hermann, Laila; Gantner, Sophia; Tur, Bogac; Westphalen, Caroline; Kuranova, Liudmila; Döllinger, Michael; Kniesburges, Stefan; Kruse, Stephanie A.; Echternach, Matthias (Journal of Voice, 2022)
Introduction: Group singing has been associated with higher transmission risks via exhaled and spread aerosols in the CoVID19 pandemic. For this reason, many musical activities, such as rehearsals and lessons, but also voice therapy sessions, have been restricted in many countries. Consequently, transmission risks and pathways have been studied, such as aerosol amounts generated by exhalation tasks, convectional flows in rooms, or the impulse dispersion of different kinds of phonation. The use of water resistance exercises such as those utilizing LAX VOX®, are common in voice lessons and as vocal warm-ups. With this context, this study investigates the impulse dispersion characteristics of aerosols during a voiced water resistance exercise in comparison to normal singing. Methods: Twelve professional singers (six male, six female) were asked to phonate a stable pitch through a silicone tube into a bottle filled with water, holding the end of the tube 5 cm below the surface. Before performing the tasks, the singers inhaled the vapor consisting of 0.5 L base liquid from an e-cigarette. The exhaled gas cloud coming out of the bottle was recorded in all three spatial directions and the dispersion was measured as a function of time. Results: At the end of the phonation task, the median distance to the front was 0.55 m and the median of the lateral expansion of the cloud was 0.89 m, the maximum to the front reached 0.88 m, and the maximum of lateral expansion 1.05 m. For the upwards direction of the clouds a median of 1.00 m and a maximum of 1.34 m from the mouth were measured. Three seconds after the end of the task, the medians were declining. Conclusion: The exhaled aerosol cloud can expand despite the obstacle of the water when using LAX VOX® during phonation.
CRIS-Team Scopus Importer:2022-07-22
Keywords: Singing—CoVID19—Aerosol dispersion—LAX VOX

The Effects of a “New Generation” of Heat and Moisture Exchangers in Laryngectomized Patients with Previous Heat and Moisture Changer Experience - Almajali, Omar; Balk, Matthias; Rupp, Robin; Allner, Moritz; Sievert, Matti; Iro, Heinrich; Schützenberger, Anne; Gostian, Antoniu-Oreste (Ent-Ear Nose & Throat Journal, 2023)
Objectives: To evaluate the effects of a new generation of heat and moisture exchangers (NG-HMEs) on pulmonary rehabilitation, quality of life, patient satisfaction, and usage patterns. Methods: A prospective observational study on 23 laryngectomized patients with prior HME experience from June 1, 2021 to November 30, 2021. Patients were interviewed at inclusion, after 6 weeks and after 12 weeks after the introduction of NG-HMEs. Two validated questionnaires were used to report pulmonary complaints and quality of life: the Cough and Sputum Assessment Questionnaire (CASA-Q), the European Quality of Life 5 Dimensions Index Score (EQ-5D Index Score), and the European Quality of Life 5 Dimensions Visual Analog Scale (EQ-5D-VAS). Usage patterns and patient satisfaction were reported using study-specific questionnaires. Results: The patients had an average age of 65.7 ± 6.8 years, with 87% being male, on average 33.7 ± 35.3 months after total laryngectomy (TLE). NG-HMEs were used for a mean of 21.87 ± 4.63 hours/day (P =.034). After 12 weeks of use, patients reported the following changes in the CASA-Q domains: cough symptoms (+5; P =.663), cough impact (0; P =.958), sputum symptoms (+8; P =.13), and sputum impact (+3; P =.489). The EQ-5D index score increased (+0.024; P =.917) as well as the EQ-5D VAS (+0.8; P =.27). All patients rated their experience with NG-HMEs with ≥3 out of 5. The patients who used NG-HMEs as instructed (n = 13) reported more profound changes in the CASA-Q domains: cough symptom (+11; P =.129), cough impact (+7; P =.209), sputum symptom (+11; P =.123), and sputum impact (+10; P =.102). Conclusions: Our results show that NG-HMEs could have a positive clinical impact on pulmonary rehabilitation after TLE, even in HME-experienced patients. The use of NG-HMEs does not affect the quality of life. The possible effects of NG-HMEs require further evaluation in long-term studies to fully assess their efficacy.
CRIS-Team Scopus Importer:2023-10-20
Keywords: devices; pulmonary rehabilitation; quality of life; total laryngectomy

The Effects of an Individualized Smartphone-Based Exercise Program on Self-defined Motor Tasks in Parkinson Disease: Pilot Interventional Study. - Gaßner, Heiko; Friedrich, Jana; Masuch, Alisa; Jukic, Jelena; Stallforth, Sabine; Regensburger, Martin; Marxreiter, Franz; Winkler, Jürgen; Klucken, Jochen (JMIR Rehabilitation and Assistive Technologies, 2022)
BACKGROUND: Bradykinesia and rigidity are prototypical motor impairments of Parkinson disease (PD) highly influencing everyday life. Exercise training is an effective treatment alternative for motor symptoms, complementing dopaminergic medication. High frequency training is necessary to yield clinically relevant improvements. Exercise programs need to be tailored to individual symptoms and integrated in patients' everyday life. Due to the COVID-19 pandemic, exercise groups in outpatient setting were largely reduced. Developing remotely supervised solutions is therefore of significant importance. OBJECTIVE: This pilot study aimed to evaluate the feasibility of a digital, home-based, high-frequency exercise program for patients with PD. METHODS: In this pilot interventional study, patients diagnosed with PD received 4 weeks of personalized exercise at home using a smartphone app, remotely supervised by specialized therapists. Exercises were chosen based on the patient-defined motor impairment and depending on the patients' individual capacity (therapists defined 3-5 short training sequences for each participant). In a first education session, the tailored exercise program was explained and demonstrated to each participant and they were thoroughly introduced to the smartphone app. Intervention effects were evaluated using the Unified Parkinson Disease Rating Scale, part III; standardized sensor-based gait analysis; Timed Up and Go Test; 2-minute walk test; quality of life assessed by the Parkinson Disease Questionnaire; and patient-defined motor tasks of daily living. Usability of the smartphone app was assessed by the System Usability Scale. All participants gave written informed consent before initiation of the study. RESULTS: In total, 15 individuals with PD completed the intervention phase without any withdrawals or dropouts. The System Usability Scale reached an average score of 72.2 (SD 6.5) indicating good usability of the smartphone app. Patient-defined motor tasks of daily living significantly improved by 40% on average in 87% (13/15) of the patients. There was no significant impact on the quality of life as assessed by the Parkinson Disease Questionnaire (but the subsections regarding mobility and social support improved by 14% from 25 to 21 and 19% from 15 to 13, respectively). Motor symptoms rated by Unified Parkinson Disease Rating Scale, part III, did not improve significantly but a descriptive improvement of 14% from 18 to 16 could be observed. Clinically relevant changes in Timed Up and Go test, 2-minute walk test, and sensor-based gait parameters or functional gait tests were not observed. CONCLUSIONS: This pilot interventional study presented that a tailored, digital, home-based, and high-frequency exercise program over 4 weeks was feasible and improved patient-defined motor activities of daily life based on a self-developed patient-defined impairment score indicating that digital exercise concepts may have the potential to beneficially impact motor symptoms of daily living. Future studies should investigate sustainability effects in controlled study designs conducted over a longer period.
EVALuna2:520112

The Erlangen Questionnaire: a new 5-item screening tool for obstructive sleep apnea in a sleep clinic population - A prospective, double blinded study - Traxdorf, Maximilian; Tziridis, Konstantin; Scherl, C.; Iro, Heinrich; Haferkamp, Jens (European Review for Medical and Pharmacological Sciences, 2017)
OBJECTIVE: The aim of this study was to develop and validate a simplified screening tool for identifying obstructive sleep apnea (OSA) in a sleep clinic population. PATIENTS AND METHODS: A total of 160 patients from a sleep clinic population was enrolled in the prospective, double-blinded study. OSA was defined by using diagnostic criteria of the ICSD-3 after overnight polysomnography (n=96) or polygraphy (n=64). The first 60 patients filled out a multi-item questionnaire and formed the development group. Subsequently, the five most predictive factors were selected to create the Erlangen Questionnaire (EQ). For validation of the EQ, the next 100 patients formed the validation group. RESULTS: The following factors were incorporated into the 5-item EQ: (1) ESS > 10, (2) age > 60, (3) gasping and (4) cardiovascular risk factors, (5) witnessed apneas. The EQ had sensitivities of 94.3%, 92.7% and 92.3%, specificities of 50.0%, 33.3% and 22.9%, positive predictive values of 81.5%, 62.9% and 29.6%, and negative predictive values of 78.9%, 78.9% and 89.5% with respect to mild, moderate and severe OSA. CONCLUSIONS: EQ is a compact 5-item-based, concise and easy-to-use screening tool to identify both male and female patients with OSA in a sleep clinic-population and exhibits all essential factors of internal and external validity. The results of the EQ are comparable to the best-validated and most commonly used STOP-Bang questionnaire regarding sensitivity and specificity in a sleep clinic population.
EVALuna2:33218

The Freiburg monosyllabic test put to the test - Baljic, I.; Hoppe, Ulrich (HNO, 2016)
EVALuna2:33931

The G protein-coupled receptor MRGX4 is a novel receptor for bile salts expressed on sensory neurons - Wolf, Katharina; Kühn, Helen; Leibl, Victoria; Gebhardt, Lisa; Glaudo, Markus; Reeh, Peter; Fischer, Michael J. M.; Neurath, Markus; Namer, Barbara; Kremer, Andreas (SWISS MEDICAL WEEKLY, 2021)
CRIS-Team WoS Importer:2022-03-11

The Hippocampus learns a language model with the help of the Successor Representation - Stöwer, Paul; Krauß, Patrick; Maier, Andreas (Montreal AI & Neuroscience 2021, 2021)

The impact of a standardized vocal loading test on vocal fold oscillations - Echternach, Matthias; Huseynov, Jamal; Döllinger, Michael; Nusseck, Manfred; Richter, Bernhard (European Archives of Oto-Rhino-Laryngology, 2020)
Introduction Vocal loading capacity is an important aspect of vocal health and is measured using standardized vocal loading tests. However, it remains unclear how vocal fold oscillation patterns are influenced by a standardized vocal loading task. Methods 21 (10 male, 11 female) vocally healthy subjects were analyzed concerning the dysphonia severity index (DSI) and high speed videolaryngoscopy (HSV) on the vowel /i/ at a comfortable pitch and loudness before and after a standardized vocal loading test (10 min standardized text reading, at a level higher than 80 dB (A) measured at 30 cm from the mouth). Results Changes in DSI were statistically significant, diminishing by 1.2 points after the vocal loading test, which was mainly caused by an increase of the minimum intensity. However, the pre-post comparison of HSV derived measures failed to show any statistically significant changes. Conclusion It seems necessary to analyze the effects of a standardized vocal loading test on vocal fold oscillation patterns with respect to softest phonation and phonation threshold pressure rather than comfortable pitch and loudness. Level of evidence 2c
CRIS-Team WoS Importer:2020-03-13

The influence of obstructive sleep apnea and continuous positive airway pressure on the nasal microbiome - Lenk, Christian; Meßbacher, Maria-Elena; Abel, Judith; Mueller, Sarina K.; Mantsopoulos, Konstantinos; Gostian, Antoniu-Oreste; Sievert, Matti; Wirtz, Stefan; Marxreiter, Franz; Winkler, Jürgen; Iro, Heinrich; Traxdorf, Maximilian (European Review for Medical and Pharmacological Sciences, 2023)
OBJECTIVE: The aim of this study was to investigate the influence of obstructive sleep apnea and continuous positive airway pressure on the nasal microbiome. PATIENTS AND METHODS: Endonasal swabs from the olfactory groove of 22 patients with moderate and severe obstructive sleep apnea (OSA) and a control group of 17 healthy controls were obtained at the Department of Otorhinolaryngology of the Friedrich-Alexander-Universität Erlangen-Nürnberg. 16S rRNA gene sequencing was performed to further evaluate the endonasal microbiome. In a second step, the longitudinal influence of continuous positive airway pressure (CPAP) therapy on the nasal microbiome was investigated (3-6 and 6-9 months). RESULTS: Analysis of the bacterial load and β-diversity showed no significant differences between the groups, although patients with severe OSA showed increased α-diversity compared to the control group, while those with moderate OSA showed decreased α-diversity. The evaluation of longitudinal changes in the nasal microbiota during CPAP treatment showed no significant difference in α- or β-diversity. However, the number of bacteria for which a significant difference between moderate and severe OSA was found in the linear discriminant analysis decreased during CPAP treatment. CONCLUSIONS: Long-term CPAP treatment showed an alignment of the composition of the nasal microbiome in patients with moderate and severe OSA as well as an alignment of biodiversity with that of the healthy control group. This change in the composition of the microbiome could be both part of the therapeutic effect in CPAP therapy and a promoting factor of the adverse side effects of the therapy. Further studies are needed to investigate whether the endonasal microbiome is related to CPAP compliance and whether CPAP compliance can be positively influenced in the future by therapeutic modification of the microbiome.
CRIS-Team WoS Importer:2023-05-26

The influence of vocal fold mass lesions on the passaggio region of professional singers - Echternach, Matthias; Burk, Fabian; Burdumy, Michael; Herbst, Christian T.; Koeberlein, Marie; Döllinger, Michael; Richter, Bernhard (Laryngoscope, 2017)
OBJECTIVES/HYPOTHESIS: In professional classical singing, an even voice quality throughout the entire singing voice range is essential. Transitions between vocal registers (passaggio) are the technically most challenging aspects in classical singing. It is hypothesized that they are most affected by vocal fold mass lesions (VFML). STUDY DESIGN: Cohort study. METHODS: In this study, the effect of VFML on vocal fold vibration in the passaggio regions was analyzed in four female and three male singers suffering from organic dysphonia. The singers were asked to sing an ascending glissando through the passaggio regions, before and after treatment. The vocal fold vibration was documented with transnasal endoscopic high-speed imaging recordings at 20,000 frames per second, supplemented by synchronized acoustic and electroglottographic recordings. RESULTS: Major irregularities were found in the passaggio region of four singers before treatment, whereas the respective phonations below the passaggio were almost regular. In two female singers only the upper, but not the lower passaggio was affected. In all four of these participants, the passaggio region was more regular after treatment. In the remaining three participants, the VFML showed no effect on the passaggio region. However, the singers' ability to reach higher pitches was impaired, but was resolved after treatment. CONCLUSIONS: The data in this case study strongly suggest that the passaggio region could be affected by VFML, even if phonation outside the passaggio regions is unimpaired. When planning surgical procedures for professional singers, clinical examination protocols should therefore include phonatory tests across the passaggio regions. LEVEL OF EVIDENCE: 4 Laryngoscope, 127:1392-1401, 2017.
EVALuna2:33365

The Influence of Vowels on Vocal Fold Dynamics in the Tenor's Passaggio - Echternach, Matthias; Burk, Fabian; Koeberlein, Marie; Burdumy, Michael; Döllinger, Michael; Richter, Bernhard (Journal of Voice, 2017)
INTRODUCTION: The influence of vowels on the frequency region where registration events in male voices usually occur (passaggio) has not yet been clarified. Particularly, for tenors who frequently have to sing across the passaggio, it might be assumed that the vowel quality has an influence on the stability of phonation. METHODS: In this investigation, six professionally trained Western classical tenors performed a glide from A3 (220 Hz) to A4 (440 Hz) and were recorded using high-speed videoendoscopy at 20,000 fps via transnasal flexible endoscopy. The participants produced transitions (1) from modal register to falsetto and (2) from modal register to stage voice above the passaggio on the vowels [aː], [iː], and [uː]. Simultaneously, acoustic and electroglottographic (EGG) signals were recorded. The glottal area waveform (GAW) open quotient (OQ), the EGG OQ, and the sample entropy derived from the EGG were calculated and phonovibrograms were established. RESULTS: In comparison to [iː] and [uː], vowel [aː] showed lower values regarding the sample entropy and greater periodicity in the phonovibrograms during the passaggio. For [iː] and [uː], the falsetto showed greater GAW OQ than the stage voice above the passaggio but no great difference for vowel [aː]. There was a good agreement between GAW OQ and EGG OQ for GAW OQ values below .65. However, for values greater than .65, the EGG OQ showed greater disagreement. CONCLUSIONS: The data support the hypothesis that the vowel condition influences the phonatory stability concerning the passaggio, suggesting that vowel [aː] is associated with greater phonation stability.
EVALuna2:33366

The Intra-Cochlear Impedance-Matrix (IIM) test for the Nucleus® cochlear implant - Hey, Matthias; Boehnke, Britta; Dillier, Norbert; Hoppe, Ulrich; Eskilsson, Gunnar; Lowgren, Karolina; Cullington, Helen; Mauch, Herbert; Mueller-Deile, Joachim (Biomedizinische Technik, 2015)
To describe the principles and operation of a new telemetry-based function test for the Nucleus® cochlear implant, known as the CS19 Intra-Cochlear Impedance Matrix (IIM) and to present results from a multicentre clinical study to establish reproducibility (test-retest reliability) and normative ranges.The IIM test measures bipolar impedances between all electrode pairs and employs a normalization procedure based on common ground impedances in order to identify abnormal current paths among electrodes. Six European clinics collected IIM data from a total of 192 devices.Reproducibility was high between initial and repeat measurements. The normative analysis demonstrated narrow ranges among devices after normalization of impedance data. The IIM is able to identify abnormal current paths that are not evident from standard impedance telemetry and may otherwise only be found utilising average electrode voltage measurements (AEV).The IIM test was found to be straightforward to perform clinically and demonstrated reproducible data with narrow ranges in normally-functioning devices. Because this test uses a very low stimulation level the IIM test is well suited for children or multiply handicapped CI users who cannot reliably report on their auditory percepts. The new algorithms show potential to improve implant integrity testing capabilities if implemented in future clinical software.
EVALuna2:20025

The involvement of E6, p53, p16, MDM2 and Gal-3 in the clinical outcome of patients with cervical cancer - Stiasny, Annika; Freier, Christoph P.; Kuhn, Christina; Schulze, Sandra; Mayr, Doris; Alexiou, Christoph; Janko, Christina; Wiest, Irmi; Dannecker, Christian; Jeschke, Udo; Kost, Bernd P. (Oncology Letters, 2017)
High-risk human papilloma virus (HPV) is the leading cause of cervical cancer. HPV oncogenes are responsible for the development of malignancy, and the E6 oncoprotein that HPV expresses induces the degradation of tumour suppressor protein p53 (p53). This degradation leads to the upregulation of p16; however, unidentified proteins may also serve a role in the development and progression of cervical cancer. Therefore, the aim of the present study was to analyse the expression levels of E6, p53, p16, MDM2 proto-oncogene (MDM2) and galectin-3 (gal-3) in cervical cancer specimens. A total of 250 cervical cancer tissue slides were used. The expression of E6, p53, p16, MDM2 and gal-3 was analysed with immunohistochemical methods and a semi-quantitative scoring. SPSS software was used for the statistical evaluation of staining results and survival analysis of patients with cervical cancer. Cervical cancer specimens demonstrated significantly increased E6 staining with advanced T-status and increased International Federation of Gynecology and Obstetrics classification. E6, p53 and p16 demonstrated significantly different expression levels in squamous epithelial tissue compared with adenocarcinomas. MDM2 and gal-3 demonstrated positively correlated expression levels in cervical cancer. In addition, gal-3 expression was correlated with poor prognosis in p16-negative cases. A negative correlation between the expression of E6 and a mutated form of p53 was also identified in cervical cancer. p53 mutation was demonstrated to be common in cervical cancer, and gal-3 and MDM2 appeared to act in a combined manner in this type of tumour. As gal-3 is overexpressed in the cervical cancer tissue of patients with poor prognosis, the use of gal-3 inhibitors should be investigated in future studies.
EVALuna2:33377

The mechanisms of harmonic sound generation during phonation: A multi-modal measurement-based approach - Lodermeyer, Alexander; Mohamadi Bagheri, Eman; Kniesburges, Stefan; Näger, Christoph; Probst, Judith; Döllinger, Michael; Becker, Stefan (Journal of the Acoustical Society of America, 2021)
Sound generation during voiced speech remains an open research topic because the underlying process within the human larynx is hardly accessible for direct measurements. In the present study, harmonic sound generation during phonation was investigated with a model that replicates the fully coupled fluid-structure-acoustic interaction (FSAI). The FSAI was captured using a multi-modal approach by measuring the flow and acoustic source fields based on particle image velocimetry, as well as the surface velocity of the vocal folds based on laser vibrometry and high-speed imaging. Strong harmonic sources were localized near the glottis, as well as further downstream, during the presence of the supraglottal jet. The strongest harmonic content of the vocal fold surface motion was verified for the area near the glottis, which directly interacts with the glottal jet flow. Also, the acoustic back-coupling of the formant frequencies onto the harmonic oscillation of the vocal folds was verified. These findings verify that harmonic sound generation is the result of a strong interrelation between the vocal fold motion, modulated flow field, and vocal tract geometry.
CRIS-Team Scopus Importer:2021-11-26

The mechanisms of subharmonic tone generation in a synthetic larynx model - Kniesburges, Stefan; Lodermeyer, Alexander; Becker, Stefan; Traxdorf, Maximilian; Döllinger, Michael (Journal of the Acoustical Society of America, 2016)
EVALuna2:33182

The Mini Nutritional Assessment (R)-Its History, Today's Practice, and Future Perspectives - Bauer, Judith; Kaiser, Matthias J.; Anthony, Patricia; Guigoz, Yves; Sieber, Cornel (Nutrition in Clinical Practice, 2008)
In the early 1990s, the Mini Nutritional Assessment(R) (MNA; Nestle Nutrition, Vevey, Switzerland) was developed for nutrition screening in the elderly. Since then, it became the most established and widespread screening tool for older persons and has been translated into many different languages. The MNA shows prognostic relevance with regard to functionality, morbidity, and mortality of the elderly in different settings. This article recalls the development of the MNA with its short form (MNA-SF) and reviews the literature, focusing on the most recent publications. Specific features of the application of the MNA in different settings (community, nursing home, hospital) are considered. Minor shortcomings of the tool, such as the resources and the cooperation necessary for completion of the MNA, are discussed. Future options for the adaptation of this valuable tool are briefly characterized. (Nutr Clin Pract. 2008;23:388-396)
Keywords: nutrition assessment; nutrition status; aged; geriatrics; geriatric assessment; malnutrition; protein-energy malnutrition

The modified Polsby–Popper score, a novel quantitative histomorphological biomarker and its potential to predict lymph node positivity and cancer-specific survival in oral tongue squamous cell carcinoma - Csűry, Tamás Dániel; Csűry, Anna Zsófia; Balk, Matthias; Kist, Andreas; Rupp, Robin; Mueller, Sarina K.; Sievert, Matti; Iro, Heinrich; Eckstein, Markus; Gostian, Antoniu-Oreste (Cancer Medicine, 2023)
Background: The significance of different histological spreading patterns of tumor tissue in oral tongue squamous cell carcinoma (TSCC) is well known. Our aim was to construct a numeric parameter on a continuous scale, that is, the modified Polsby–Popper (MPP) score, to describe the aggressiveness of tumor growth and infiltration, with the potential to analyze hematoxylin and eosin-stained whole slide images (WSIs) in an automated manner. We investigated the application of the MPP score in predicting survival and cervical lymph node metastases as well as in determining patients at risk in the context of different surgical margin scenarios. Methods: We developed a semiautomated image analysis pipeline to detect areas belonging to the tumor tissue compartment. Perimeter and area measurements of all detected tissue regions were derived, and a specific mathematical formula was applied to reflect the perimeter/area ratio in a comparable, observer-independent manner across digitized WSIs. We demonstrated the plausibility of the MPP score by correlating it with well-established clinicopathologic parameters. We then performed survival analysis to assess the relevance of the MPP score, with an emphasis on different surgical margin scenarios. Machine learning models were developed to assess the relevance of the MPP score in predicting survival and occult cervical nodal metastases. Results: The MPP score was associated with unfavorable tumor growth and infiltration patterns, the presence of lymph node metastases, the extracapsular spread of tumor cells, and higher tumor thickness. Higher MPP scores were associated with worse overall survival (OS) and tongue carcinoma-specific survival (TCSS), both when assessing all pT-categories and pT1-pT2 categories only; moreover, higher MPP scores were associated with a significantly worse TCSS in cases where a cancer-free surgical margin of <5 mm could be achieved on the main surgical specimen. This discriminatory capacity remained constant when examining pT1-pT2 categories only. Importantly, the MPP score could successfully define cases at risk in terms of metastatic disease in pT1-pT2 cancer where tumor thickness failed to exhibit a significant predictive value. Machine learning (ML) models incorporating the MPP score could predict the 5-year TCSS efficiently. Furthermore, we demonstrated that machine learning models that predict occult cervical lymph node involvement can benefit from including the MPP score. Conclusions: We introduced an objective, quantifiable, and observer-independent parameter, the MPP score, representing the aggressiveness of tumor growth and infiltration in TSCC. We showed its prognostic relevance especially in pT1-pT2 category TSCC, and its possible use in ML models predicting TCSS and occult lymph node metastases.
CRIS-Team Scopus Importer:2023-12-29
Keywords: computer-assisted image analysis; squamous cell carcinoma of head and neck; survival analysis; tongue cancer

The Motor Unit Number Index (MUNIX) in sarcopenic patients - Drey, Michael; Groesch, C.; Neuwirth, C.; Bauer, Judith; Sieber, Cornel (Experimental Gerontology, 2013)
Introduction: The cause of sarcopenia is still not fully understood. A multifactorial aetiology is discussed. Neurodegenerative aspects in the genesis of sarcopenia, such as loss of motoneurons, have not yet been explored to a sufficient extent.Method: The Motor Unit Number Index (MUNIX) is a method for assessing the number and size (Motor Unit Size Index - MUSIX) of Motor Units (MUs) using the Compound Muscle Action Potential (CMAP) and the Surface electromyographic Interference Pattern (SIP). This method was used to study the hypothenar muscle in the right hand of 27 sarcopenic patients.Results: The mean MUNIX (111 +/- 51) of all investigated sarcopenic patients lies between the mean MUNIX of healthy persons and the mean MUNIX of ALS patients. 25% of sarcopenic patients exhibit pathologic values for both MUNIX (<80) and MUSIX (> 100 mu V). A strong correlation (r= 0.75, p<0.001) between MUSIX and the reciprocal value of MUNIX was identified.Conclusion: It was demonstrated for the first time by applying the MUNIX technique that loss of motoneurons plays a pathogenic role in the onset of sarcopenia. This was shown in 25% of sarcopenic participants who exhibited pathologic values for both MUNIX and MUSIX. Nerve sprouting seems to be an important mechanism of compensation for loss of motoneurons, reflected by the strong correlation between MUNIX and MUSIX. Use of MUNIX leads to the identification of a distinct subgroup of sarcopenic patients, which might have a major impact on future diagnostic and therapeutic concepts. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Sarcopenia; Motoneuron; Neuromuscular; MUNIX; Elderly

The Neural Bases of Tinnitus: Lessons from Deafness and Cochlear Implants - Knipper, Marlies; van Dijk, Pim; Schulze, Holger; Mazurek, Birgit; Krauß, Patrick; Scheper, Verena; Warnecke, Athanasia; Schlee, Winfried; Schwabe, Kerstin; Singer, Wibke; Braun, Christoph; Delano, Paul H.; et al. (The Journal of Neuroscience, 2020)
Subjective tinnitus is the conscious perception of sound in the absence of any acoustic source. The literature suggests various tinnitus mechanisms, most of which invoke changes in spontaneous firing rates of central auditory neurons resulting from modification of neural gain. Here, we present an alternative model based on evidence that tinnitus is: (1) rare in people who are congenitally deaf, (2) common in people with acquired deafness, and (3) potentially suppressed by active cochlear implants used for hearing restoration. We propose that tinnitus can only develop after fast auditory fiber activity has stimulated the synapse formation between fast-spiking parvalbumin positive (PV+) interneurons and projecting neurons in the ascending auditory path and coactivated frontostriatal networks after hearing onset. Thereafter, fast auditory fiber activity promotes feedforward and feedback inhibition mediated by PV+ interneuron activity in auditory-specific circuits. This inhibitory network enables enhanced stimulus resolution, attention-driven contrast improvement, and augmentation of auditory responses in central auditory pathways (neural gain) after damage of slow auditory fibers. When fast auditory fiber activity is lost, tonic PV+ interneuron activity is diminished, resulting in the prolonged response latencies, sudden hyperexcitability, enhanced cortical synchrony, elevated spontaneous γ oscillations, and impaired attention/stress-control that have been described in previous tinnitus models. Moreover, because fast processing is gained through sensory experience, tinnitus would not exist in congenital deafness. Electrical cochlear stimulation may have the potential to reestablish tonic inhibitory networks and thus suppress tinnitus. The proposed framework unites many ideas of tinnitus pathophysiology and may catalyze cooperative efforts to develop tinnitus therapies.
CRIS-Team Scopus Importer:2020-09-25

The Offprint of an Abnormal Pre-Parotidectomy Electrodiagnostic Finding in a Normally Functioning Facial Nerve: Correlation with Intraoperative Findings, Histology and Postoperative Facial Nerve Function† - Katheder, Verena; Sievert, Matti; Mueller, Sarina K.; Thimsen, Vivian; Gostian, Antoniu-Oreste; Balk, Matthias; Rupp, Robin; Iro, Heinrich; Mantsopoulos, Konstantinos (Journal of Clinical Medicine, 2022)
The aim of this study was to search for associations between an electrodiagnostically abnormal but clinically normal facial nerve before parotidectomy and the intraoperative findings, as well as the postoperative facial nerve function. The records of all patients treated for parotid tumors between 2002 and 2021 with a preoperative House–Brackmann score of grade I but an abnormal electrophysiologic finding were studied retrospectively. A total of 285 patients were included in this study, and 222 patients had a benign lesion (77.9%), whereas 63 cases had a malignant tumor (22.1%). Electroneurographic facial nerve involvement was associated with nerve displacement in 185 cases (64.9%) and infiltration in 17 cases (6%). In 83 cases (29.1%), no tumor–nerve interface could be detected intraoperatively. An electroneurographic signal was absent despite supramaximal stimulation in 6/17 cases with nerve infiltration and in 17/268 cases without nerve infiltration (p < 0.001). The electrophysiologic involvement of a normal facial nerve is not pathognomonic for a malignancy (22%), but it presents a rather rare ( 6%) sign of a “true” nerve infiltration and could also appear in tumors without any contact with the facial nerve ( 29%). Of our cases, two thirds of those with an anatomic nerve preservation and facial palsy had already directly and postoperatively recovered to a major extent in the midterm.
CRIS-Team Scopus Importer:2022-01-14
Keywords: Electromyography; Electroneurography; Facial nerve; Facial paralysis; Infiltration; Parotidectomy; Tumor

The Pathogenicity of Anti-β2GP1-IgG Autoantibodies Depends on Fc Glycosylation. - Fickentscher, Christoph; Magorivska, Iryna; Janko, Christina; Biermann, Mona; Bilyy, Rostyslav; Nalli, Cecilia; Tincani, Angela; Medeghini, Veronica; Meini, Antonella; Nimmerjahn, Falk; Schett, Georg; Munoz, Luis E.; et al. (Journal of immunology research, 2015)
To analyze the glycosylation of anti-β2GP1, we investigated purified IgG from healthy children, patients with APS, and asymptomatic adult carriers of antiphospholipid antibodies. We observed that in the sera of healthy children and of patients with APS, IgG3 and IgG2 were predominant, respectively. The potentially protective anti-β2GP1-IgM was lower in the sera of healthy children. Although anti-β2GP1-associated C1q did not differ between children and patients with antiphospholipid syndrome, the associated C3c was significantly higher in the sera of healthy children. This indicates a more efficient clearance of anti-β2GP1 immune complexes in the healthy children. This clearance is not accompanied by inflammation or coagulatory events. It is likely that the most important pathogenic factor of the anti-β2GP1-IgG is related to the different glycosylation observed in healthy and diseased individuals. We detected a significantly higher sialylation of anti-β2GP1-IgG isolated from the sera of healthy children and asymptomatic adults when compared with that of patients with clinically apparent antiphospholipid syndrome. Low sialylated IgG reportedly ameliorates inflammation and inflammation promotes hyposialylation. Thus, both reactions create a vicious circle that precipitates the pathology of the antiphospholipid syndrome including thrombus-formation. We conclude that the increased sialylation of anti-β2GP1-IgG of sera of healthy individuals limits their pathogenicity.

The Progression of Cell Death Affects the Rejection of Allogeneic Tumors in Immune-Competent Mice - Implications for Cancer Therapy - Chaurio Gonzalez, Ricardo Alfredo; Munoz, Luis E.; Maueröder, Christian; Janko, Christina; Harrer, Thomas; Fuernrohr, Barbara G.; Niederweis, Michael; Bilyy, Rostyslav; Schett, Georg; Herrmann, Martin; Berens, Christian (Frontiers in Immunology, 2014)
Large amounts of dead and dying cells are produced during cancer therapy and allograft rejection. Depending on the death pathway and stimuli involved, dying cells exhibit diverse features, resulting in defined physiological consequences for the host. It is not fully understood how dying and dead cells modulate the immune response of the host. To address this problem, different death stimuli were studied in B16F10 melanoma cells by regulated inducible transgene expression of the pro-apoptotic active forms of caspase-3 (revCasp-3), Bid (tBid), and the Mycobacterium tuberculosis-necrosis inducing toxin (CpnTCTD). The immune outcome elicited for each death stimulus was assessed by evaluating the allograft rejection of melanoma tumors implanted subcutaneously in BALB/c mice immunized with dying cells. Expression of all proteins efficiently killed cells in vitro (>90%) and displayed distinctive morphological and physiological features as assessed by multiparametric flow cytometry analysis. BALB/c mice immunized with allogeneic dying melanoma cells expressing revCasp-3 or CpnTCTD showed strong rejection of the allogeneic challenge. In contrast, mice immunized with cells dying either after expression of tBid or irradiation with UVB did not, suggesting an immunologically silent cell death. Surprisingly, immunogenic cell death induced by expression of revCasp-3 or CpnTCTD correlated with elevated intracellular reactive oxygen species (ROS) levels at the time point of immunization. Conversely, early mitochondrial dysfunction induced by tBid expression or UVB irradiation accounted for the absence of intracellular ROS accumulation at the time point of immunization. Although ROS inhibition in vitro was not sufficient to abrogate the immunogenicity in our allo-immunization model, we suggest that the point of ROS generation and its intracellular accumulation may be an important factor for its role as damage associated molecular pattern in the development of allogeneic responses.
EVALuna2:13056

Therapeutic Value of Ginkgo biloba Extract EGb 761® in an Animal Model (Meriones unguiculatus) for Noise Trauma Induced Hearing Loss and Tinnitus - Krauß, Patrick; Tziridis, Konstantin; Buerbank, Stefanie; Schilling, Achim; Schulze, Holger (PLoS ONE, 2016)
Noise induced hearing loss (NIHL) is a common disease in modern societies and may lead to maladaptations within the auditory system that finally result in subjective tinnitus. Available therapies may only alleviate the symptoms rather than restore normal hearing. In a previous study we demonstrated that the prophylactic application of Ginkgo biloba extract EGb 761® significantly reduces NIHL and tinnitus development in our Mongolian gerbil (Meriones unguiculatus) animal model. Here, we tested whether the application of EGb 761® has beneficial effects after the formation of permanent NIHL and tinnitus. To this end we monitored the therapeutic effects of EGb 761® on noise trauma-induced changes in signal processing within the auditory system of our animal model by behavioral (acoustic startle response, ASR) and electrophysiological approaches (auditory brainstem responses, ABR). We found that-in contrast to vehicle-three weeks of daily oral EGb 761® treatment (100 mg/kg body weight) led to a restoration of hearing thresholds back to pre-trauma conditions. In addition, all 9 animals that displayed behavioral signs of subjective tinnitus showed improvement, with 7 of them showing complete relief of tinnitus symptoms during the time of EGb 761® treatment. After discontinuation of EGb 761® treatment, tinnitus related behavior reappeared in all but one of these animals while auditory thresholds remained restored. A detailed analysis of ABR waves revealed that EGb 761® treatment did not simply change auditory processing back to pre-trauma conditions, but led to subtle changes of ABR wave amplitude and latency at different levels of the auditory pathway, with an overall increase of response to low stimulus intensities and a decrease at high intensities. The functional relevance of these changes may be the observed improvement of hearing thresholds while at the same time suppression of responses to high stimulus intensities may point to a global inhibitory mechanism that counteracts tinnitus.
EVALuna2:20023

Therapies for synchronous malignomas - the importance of interdisciplinary oncology - Mueller, Sarina K.; Haderlein, Marlen; Traxdorf, Maximilian; Semrau, Sabine; Agaimy, Abbas; Lettmaier, Sebastian; Gostian, Antoniu-Oreste; Schubart, Christoph; Mantsopoulos, Konstantinos; Schmidt, Daniela; Wiesmüller, Marco; Sievert, Matti; et al. (Laryngo-Rhino-Otologie, 2021)
CRIS-Team WoS Importer:2021-08-06

The remediation of nano-/microplastics from water - Sarcletti, Marco; Park, Hyoungwon; Wirth, Janis; Englisch, Silvan; Eigen, Andreas; Drobek, Dominik; Vivod, Dustin; Friedrich, Bernhard; Tietze, Rainer; Alexiou, Christoph; Zahn, Dirk; Apeleo Zubiri, Benjamin; et al. (Materials Today, 2021)
Nano-/microplastics (NP) is a human-made emerging contaminant with worldwide occurrence. The small size (below one micrometer), the different chemical nature and the persistence make NP to potential hazards with suspect probability of tissue penetration and inflammation or as accumulator for toxins. A strategy to stop the spill of novel NP is the remediation from waste water or rivers as prominent distributors. We have developed core–shell superparamagnetic iron oxide nanoparticles (SPIONs) that attract NP and glue them to larger agglomerates which then can be removed from water by applying an external magnetic field. The shell molecules provide two interaction motifs towards NP. The tuned surface potential of the functionalized SPIONs attract complementary charged NP efficiently and the n-alkyl chain is dedicated to preferential interaction towards organic NP rather than inorganic particles. Structural analytics and molecular dynamics simulation support the proposed concept. Systematic remediation experiments with different NP (chemical structures, sizes and mixtures), from different waters – including river water – and with different SPION core materials indicate a universal validity of the concept, with best remediation performance for mixed NP. We suggest a method for broadband remediation of various NP with simple materials and processes, which both have the potential to be up-scaled.<br

The Role of Exosomes in the Pathophysiology of Chronic Rhinosinusitis - Mueller, Sarina K. (Frontiers in Cellular and Infection Microbiology, 2022)
Non-invasive biomarker analysis has made repetitive and painless sampling over time possible. Exosomes are being released from a parent cell and their cargo mirrors the cell micromilieu of the parent cell. Therefore, exosomes are promising surrogates for their parent cells. That is also why exosomes provide an improved signal-to-noise ratio. Current studies have identified valid non-invasive biomarkers that may be able to monitor disease severity. Exosomes are suggested to play an important role in interepithelial communication and are suggested to play a role in the initiation and maintenance of inflammation in CRS. They are, however, also involved simultaneously in several immunological processes including immune protection and immunosuppression. As the isolation of exosomes is time-consuming their value in everyday routine diagnostics has yet to be determined.
CRIS-Team Scopus Importer:2022-02-25
Keywords: cell communication; chronic rhinosinusitis (CRS); cystatin; exosome; pappalysin-1

The stochastic resonance model of auditory perception: A unified explanation of tinnitus development, Zwicker tone illusion, and residual inhibition - Schilling, Achim; Tziridis, Konstantin; Schulze, Holger; Krauß, Patrick (Progress in Brain Research, 2021)
Stochastic resonance (SR) has been proposed to play a major role in auditory perception, and to maintain optimal information transmission from the cochlea to the auditory system. By this, the auditory system could adapt to changes of the auditory input at second or even sub-second timescales. In case of reduced auditory input, somatosensory projections to the dorsal cochlear nucleus would be disinhibited in order to improve hearing thresholds by means of SR. As a side effect, the increased somatosensory input corresponding to the observed tinnitus-associated neuronal hyperactivity is then perceived as tinnitus. In addition, the model can also explain transient phantom tone perceptions occurring after ear plugging, or the Zwicker tone illusion. Vice versa, the model predicts that via stimulation with acoustic noise, SR would not be needed to optimize information transmission, and hence somatosensory noise would be tuned down, resulting in a transient vanishing of tinnitus, an effect referred to as residual inhibition.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Auditory phantom perception; Dorsal cochlear nucleus; Residual inhibition; Somatosensory projections; Speech perception; Stochastic resonance; Tinnitus; Zwicker tone

The Translational Role of MUC8 in Salivary Glands: A Potential Biomarker for Salivary Stone Disease? - Schicht, Martin; Reichle, Adrian; Schapher, Mirco; Garreis, Fabian; Kleinsasser, Benedikt; Aydin, Malik; Sahin, Afsun; Iro, Heinrich; Paulsen, Friedrich (Diagnostics, 2021)
Mucin (MUC) 8 has been shown to play an important role in respiratory disease and inflammatory responses. In the present study, we investigated the question of whether MUC8 is also produced and secreted by salivary glands and whether it may also play a role in the oral cavity in the context of inflammatory processes or in the context of salivary stone formation. Tissue samples from parotid and submandibular glands of body donors (n = 6, age range 63-88 years), as well as surgically removed salivary stones from patients (n = 38, age range 48-72 years) with parotid and submandibular stone disease were immunohistochemically analyzed targeting MUC8 and TNF alpha. The presence of MUC8 in salivary stones was additionally analyzed by dot blot analyses. Moreover, saliva samples from patients (n = 10, age range 51-72 years), who had a salivary stone of the submandibular gland on one side were compared with saliva samples from the other "healthy " side, which did not have a salivary stone, by ELISA. Positive MUC8 was detectable in the inter- and intralobular excretory ducts of both glands (parotid and submandibular). The glandular acini showed no reactivity. TNF alpha revealed comparable reactivity to MUC8 in the glandular excretory ducts and also did not react in glandular acini. Salivary stones demonstrated a characteristic distribution pattern of MUC8 that differed between parotid and submandibular salivary stones. The mean MUC8 concentration was 71.06 ng/mL in female and 33.21 ng/mL in male subjects (p = 0.156). Saliva from the side with salivary calculi contained significantly (15-fold) higher MUC8 concentration levels than saliva from the healthy side (p = 0.0005). MUC8 concentration in salivary stones varied from 4.59 ng/mL to 202.83 ng/mL. In females, the MUC8 concentration in salivary stones was significantly (2.3-fold) higher, with an average of 82.84 ng/mL compared to 25.27 ng/mL in male patients (p = 0.034). MUC8 is secreted in the excretory duct system of salivary glands and released into saliva. Importantly, MUC8 salivary concentrations vary greatly between individuals. In addition, the MUC8 concentration is gender-dependent (& FEMALE; > & MALE;). In the context of salivary stone diseases, MUC8 is highly secreted in saliva. The findings support a role for MUC8 in the context of inflammatory events and salivary stone formation. The findings allow conclusions on a gender-dependent component of MUC8.
CRIS-Team WoS Importer:2022-01-14

The use of automatic speech recognition showing the influence of nasality on speech intelligibility - Mayr, Susanne; Burkhardt, Katja; Schuster, Maria; Rogler, Katrin; Maier, Andreas; Iro, Heinrich (European Archives of Oto-Rhino-Laryngology, 2010)

The value of transcutaneous ultrasound in the diagnosis of tonsillar abscess: A retrospective analysis - Sievert, Matti; Miksch, Malin; Mantsopoulos, Konstantinos; Goncalves, Miguel; Rupp, Robin; Mueller, Sarina K.; Traxdorf, Maximilian; Iro, Heinrich; Koch, Michael (Auris Nasus Larynx, 2021)
Objective: To identify the appropriate treatment in the tonsillar region's infections, a distinction between tonsillitis with or without abscess formation is essential. Ultrasound proved to be a valuable method in identifying abscess formation in the head and neck region. However, no report described the assessment of the tonsil region. This study aims to determine the feasibility of transcervical ultrasound for abscess visualization in the palatal tonsillar region. Methods: Retrospective analysis of 354 patients presenting with clinical suspicion of tonsillar abscess to a tertiary referral center and university hospital. All patients received a transcervical ultrasound to establish a primary diagnosis. The existence of an abscess was confirmed by puncture and incision, or final tonsillectomy. If no abscess could be delineated, non-abscessing tonsillitis was supposed, and conservative primary therapy and closed follow-up examinations were performed. Results: After the first diagnostic ultrasound examination, in 257 cases (72.59%), the diagnosis of an abscess could be established, but in 97 cases (27.40%), due to missing abscess formation criteria, non-abscessing tonsillitis was documented. Overall, ultrasonography demonstrated an overall accuracy of 78.8% in this selected cohort. The sensitivity, specificity, PPV, and NPV after the first ultrasound examination were calculated with 75.1%, 88.6%, 94.6%, and 57.3%, respectively. Conclusion: The presented data confirm that an abscess formation due to tonsillitis can be detected by transcervical ultrasound, enabling prompt, adequate management. As transcervical ultrasound can be conducted fast and is not associated with radiation, it can be regarded as a first-line diagnostic tool in this condition.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Diagnostic; Intratonsillar abscess; Parapharyngeal abscess; Peritonsillar abscess; Tonsillar abscess; Transcutaneous ultrasound

Three-Dimensional Optical Reconstruction of Vocal Fold Kinematics Using High-Speed Video With a Laser Projection System - Luegmair, Georg; Mehta, Daryush D.; Kobler, James B.; Döllinger, Michael (IEEE Transactions on Medical Imaging, 2015)
Vocal fold kinematics and its interaction with aerodynamic characteristics play a primary role in acoustic sound production of the human voice. Investigating the temporal details of these kinematics using high-speed videoendoscopic imaging techniques has proven challenging in part due to the limitations of quantifying complex vocal fold vibratory behavior using only two spatial dimensions. Thus, we propose an optical method of reconstructing the superior vocal fold surface in three spatial dimensions using a high-speed video camera and laser projection system. Using stereo-triangulation principles, we extend the camera-laser projector method and present an efficient image processing workflow to generate the three-dimensional vocal fold surfaces during phonation captured at 4000 frames per second. Initial results are provided for airflow-driven vibration of an ex vivo vocal fold model in which at least 75% of visible laser points contributed to the reconstructed surface. The method captures the vertical motion of the vocal folds at a high accuracy to allow for the computation of three-dimensional mucosal wave features such as vibratory amplitude, velocity, and asymmetry.
EVALuna2:19982

Thrombose genähter vs. gekoppelter Anastomosen bei mikrovaskulären Kopf- und Halsrekonstruktionen - Sievert, Matti; Koch, Michael; Goncalves, Miguel; Richter, Daniel; Tamse, Rosalie; Mueller, Sarina K.; Gostian, Antoniu-Oreste; Traxdorf, Maximilian; Harreus, Uli; Iro, Heinrich (Laryngo-Rhino-Otologie, 2020)
Objective The Anastomotic Coupling Device for microvascular anastomoses has become widely used in free tissue transplantation. This study compares the thrombosis rate and flap failure as a function of the anastomosis technique at a large head and neck cancer center. Material and Methods Retrospective analysis of all patients receiving free flap reconstructions in the period 2001-2019. Reconstruction type, recipient vessels, number of venous anastomoses, coupler size, and operation time were investigated. We compared the rates of venous thrombosis between hand sewn and coupled anastomoses, as well as the rate of flap failure. Results A total of 403 free flap reconstructions were performed for over 17 years. The venous anastomosis was sewn in 113 flaps in single suture technique, and in 290 cases, coupler device was used. The rate of venous thrombosis requiring immediate surgical revision was 6.2 % (7/113) in the sewn group compared to 7.6 % in the coupled group (22/290; p = 0.627). With an overall success rate of 95.0 % (383/403), the rate of flap failure was 3.6 % (4/113) and 5.5 % (16/290; p = 0.421), respectively. Surgical time is comparable with 680 ± 144 minutes in the hand-sewn group and 688 ± 167 minutes in the coupled group (p = 0.678). Conclusions With similar success rates, the coupler device is an effective alternative to venous anastomosis in single suture technique. Due to the generally low rate of pedicle thrombosis in both groups, we cannot separate the influence of the anastomosis technique from possible interfering variables.
CRIS-Team Scopus Importer:2020-10-02
Keywords: anastomotic coupling device; flap failure; free flap reconstruction; pedicle thrombosis; venous anastomosis

Thyroglossal duct cysts: 20 years' experience (1992-2011) - De Tristan, Julie; Zenk, Johannes; Kuenzel, Julian; Psychogios, Georgios; Iro, Heinrich (European Archives of Oto-Rhino-Laryngology, 2015)
The objective of the present study is to report on the clinical course and management of thyroglossal duct cysts. Retrospective review of all patients who underwent surgery for thyroglossal duct cysts between 2000 and 2013 at a tertiary referral center was carried out. The operations were performed using a modification of the Sistrunk operation: transcervical cystectomy, partial dissection of the hyoid bone, and dissection of all tracts identified during surgery. A total of 352 patients (176 men, 176 women) underwent surgery for a cyst (n = 282) or discharging sinus (n = 70). The mean age for the incidence of cysts was 26 years. Four of the patients (1.4 %) had a papillary thyroid carcinoma in the epithelium of the cyst. The follow-up period ranged from 7 months to 10 years. The overall recurrence rate was 4.5 %. Resection is often regarded as an elective surgical procedure in patients with thyroglossal duct cysts, but surgery should always be considered. Papillary thyroid carcinoma in the epithelium of the cyst is a rare but possible differential diagnosis. Dissection of all tracts found is recommended and partial dissection of the hyoid bone is mandatory. Dissection of the foramen cecum is not imperative. The recurrence rates with this approach are comparable to more extensive methods such as those described by Sistrunk.
EVALuna2:19988

Time dependency of adjuvant therapy in advanced head-and-necksquamous-cell-carcinoma of unknown primary (CUP)-patients - Balk, Matthias; Rupp, Robin; Grundtner, Philipp; Mueller, Sarina K.; Allner, Moritz; Traxdorf, Maximilian; Eckstein, Markus; Hecht, Markus; Iro, Heinrich; Gostian, Antoniu-Oreste (ORAL ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-07-16

Tinnitus at the Junction of Traditional Medicine and Modern Technology - Mazurek, Birgit; Schulze, Holger; Schlee, Winfried; Dobel, Christian (Nutrients, 2023)
CRIS-Team Scopus Importer:2023-05-12

Tinnitus development is associated with synaptopathy of inner hair cells in Mongolian gerbils - Tziridis, Konstantin; Forster, Jan; Buchheidt-Dörfler, Isabelle; Krauß, Patrick; Schilling, Achim; Wendler, Olaf; Sterna, Elisabeth; Schulze, Holger (European Journal of Neuroscience, 2021)
Human hearing loss (HL) is often accompanied by comorbidities like tinnitus, which is affecting up to 15% of the adult population. Rodent animal studies could show that tinnitus may not only be a result of apparent HL due to cochlear hair cell damage but can also be a consequence of synaptopathy at the inner hair cells (IHCs) already induced by moderate sound traumata. Here, we investigate synaptopathy previously shown in mice in our animal model, the Mongolian gerbil, and relate it to behavioral signs of tinnitus. Tinnitus was induced by a mild monaural acoustic trauma leading to monaural noise induced HL in the animals, quantified by auditory brainstem response (ABR) audiometry. Behavioral signs of tinnitus percepts were detected by measurement of prepulse inhibition of the acoustic startle response in a gap-noise paradigm. Fourteen days after trauma, the cochleae of both ears were isolated, and IHC synapses were counted within several spectral regions of the cochlea. Behavioral signs of tinnitus were only found in animals with IHC synaptopathy, independent of type of HL. On the other hand, animals with apparent HL but without behavioral signs of tinnitus showed a reduction in amplitudes of ABR waves I&II but no significant changes in the number of synapses at the IHC. We conclude-in line with the literature-that HL is caused by damage to the IHC or by other reasons but that the development of tinnitus, at least in our animal model, is closely linked to synaptopathy at the IHC.
CRIS-Team WoS Importer:2021-07-09

Tinnitus is associated with improved cognitive performance and speech perception-Can stochastic resonance explain? - Schilling, Achim; Krauß, Patrick (Frontiers in Aging Neuroscience, 2022)
CRIS-Team WoS Importer:2023-01-20

Tissue and Exosomal Serine Protease Inhibitors Are Significantly Overexpressed in Chronic Rhinosinusitis With Nasal Polyps - Mueller, Sarina K.; Nocera, A. L.; Dillon, S. T.; Libermann, T. A.; Wendler, O.; Bleier, B. S. (American Journal of Rhinology & Allergy, 2019)
Background: The fibrinolysis pathway has been previously implicated in the etiopathogenesis of chronic rhinosinusitis with nasal polyps (CRSwNP). Objective: The purpose of this study was (1) to explore protein derangements of selected protease inhibitors of the serpin superfamily in CRSwNP and (2) to correlate the protease inhibitor derangements of the fibrinolysis pathway in tissue with exosomal samples to evaluate the potential of an exosomal noninvasive “liquid biopsy” for CRSwNP. Methods: Institutional review board approved study in which matched tissue and mucus exosomal proteins (SerpinB2, SerpinF2, SerpinG1, and SerpinE1) were compared between control and CRSwNP patients using Western Blot analysis (n = 6/group) and immunohistochemistry (IHC). Transcriptome analysis (n = 10/group) on the same proteins was performed using whole transcriptome sequencing. Semiquantitative analysis of the Western Blots was performed using the Whitney–Mann U test. Results: The transcriptomic data set showed multiple differentially expressed genes including SerpinB2 (fold changes [FC] 7.38), SerpinE1 (FC 1.42), SerpinF2 (FC 2.03), and SerpinG1 (FC 0.72). Western Blot and IHC analysis showed an overexpression of the Serpin protease inhibitors in tissue (SerpinB2, P <.01; SerpinE1, P <.01; SerpinF2, P <.01; and SerpinG1, P <.01) indicating a downregulation of the fibrinolysis cascade. The mucus exosomal serpin proteins exhibited similar findings. Conclusion: Our analysis supported that protease inhibitors of the fibrinolysis pathway, especially SerpinB2, SerpinF2, and SerpinG1, are highly deranged in patients with CRSwNP. These findings suggest a downregulation of the fibrinolysis pathway via proteolytic cascade imbalance leading to excessive polyp fibrin deposition. Our data further supported our hypothesis that exosomal proteomic analyses may be used as noninvasive “liquid biopsy” for CRSwNP and a novel method to study chronic sinonasal inflammation.
CRIS-Team Scopus Importer:2019-07-30
Keywords: biomarker; chronic rhinosinusitis; inflammation; microarray; nasal polyps; protease; protease inhibitor; sinusitis; Th2 cells; transcriptome

Tissue Plasminogen Activator Binding to Superparamagnetic Iron Oxide Nanoparticle-Covalent Versus Adsorptive Approach - Friedrich, Ralf P.; Zaloga, Jan; Schreiber, Eveline; Toth, Ildiko Y.; Tombacz, Etelka; Lyer, Stefan; Alexiou, Christoph (Nanoscale Research Letters, 2016)
Functionalized superparamagnetic iron oxide nanoparticles are frequently used to develop vehicles for drug delivery, hyperthermia, and photodynamic therapy and as tools used for magnetic separation and purification of proteins or for biomolecular imaging. Depending on the application, there are various possible covalent and non-covalent approaches for the functionalization of particles, each of them shows different advantages and disadvantages for drug release and activity at the desired location.Particularly important for the production of adsorptive and covalent bound drugs to nanoparticles is the pureness of the involved formulation. Especially the covalent binding strategy demands defined chemistry of the drug, which is stabilized by excess free amino acids which could reduce reaction efficiency. In this study, we therefore used tangential flow filtration (TFF) method to purify the drugs before the reaction and used the frequently applied and clinically available recombinant tissue plasminogen activator (tPA; Actilyse(®)) as a proof of concept. We then coupled the tPA preparation to polyacrylic acid-co-maleic acid (PAM)-coated superparamagnetic iron oxide nanoparticles (SPIONs) using an amino-reactive activated ester reaction and compared these particles to PAM-coated SPIONs with electrostatically adsorbed tPA.Using dynamic light scattering (DLS) and pH-dependent electrokinetic mobility measurements, we showed that surface properties of the SPIONs were significantly greater affected after activation of the particles compared to the adsorption controls. Different in vitro assays were used to investigate the activity of tPA after coupling to the particles and purification of the ferrofluid. Covalent linkage significantly improves the reactivity and long-term stability of the conjugated SPION-tPA system compared to simple adsorption. In conclusion, we have shown an effective way to produce SPIONs with covalent and non-covalent ultra-filtrated drugs. We showed that using activated ester reaction, immobilization of the protein was significantly better than in adsorptive approaches. Investigation of those functionalized SPIONs revealed diverging attributes, which should be taken into account when developing nanoparticles for different applications.
EVALuna2:33168

Too Blind to See the Elephant? Why Neuroscientists Ought to Be Interested in Tinnitus - Knipper, Marlies; Mazurek, Birgit; Van Dijk, Pim; Schulze, Holger (Jaro-Journal of the Association For Research in Otolaryngology, 2021)
A curative therapy for tinnitus currently does not exist. One may actually exist but cannot currently be causally linked to tinnitus due to the lack of consistency of concepts about the neural correlate of tinnitus. Depending on predictions, these concepts would require either a suppression or enhancement of brain activity or an increase in inhibition or disinhibition. Although procedures with a potential to silence tinnitus may exist, the lack of rationale for their curative success hampers an optimization of therapeutic protocols. We discuss here six candidate contributors to tinnitus that have been suggested by a variety of scientific experts in the field and that were addressed in a virtual panel discussion at the ARO round table in February 2021. In this discussion, several potential tinnitus contributors were considered: (i) inhibitory circuits, (ii) attention, (iii) stress, (iv) unidentified sub-entities, (v) maladaptive information transmission, and (vi) minor cochlear deafferentation. Finally, (vii) some potential therapeutic approaches were discussed. The results of this discussion is reflected here in view of potential blind spots that may still remain and that have been ignored in most tinnitus literature. We strongly suggest to consider the high impact of connecting the controversial findings to unravel the whole complexity of the tinnitus phenomenon; an essential prerequisite for establishing suitable therapeutic approaches.
CRIS-Team Scopus Importer:2021-11-05
Keywords: attention; fast auditory processing; hyperacusis; parvalbumin positive interneuron; stress; tinnitus

Toward a Shear Wave Based Mode to Sonographically Monitor the Enrichment of Iron Oxide Nanoparticles in Drug Targeting Applications - Fink, Michael; Lyer, Stefan; Alexiou, Christoph; Ermert, Helmut (Proceedings of the Ultrasonics Symposium (IUS), 2018)

Towards a clinically applicable computational larynx model - Sadeghi, Hossein; Kniesburges, Stefan; Falk, Sebastian; Kaltenbacher, Manfred; Schützenberger, Anne; Döllinger, Michael (Applied Sciences, 2019)
The enormous computational power and time required for simulating the complex phonation process preclude the effective clinical use of computational larynx models. The aim of this study was to evaluate the potential of a numerical larynx model, considering the computational time and resources required. Using Large Eddy Simulations (LES) in a 3D numerical larynx model with prescribed motion of vocal folds, the complicated fluid-structure interaction problem in phonation was reduced to a pure flow simulation with moving boundaries. The simulated laryngeal flow field is in good agreement with the experimental results obtained from authors' synthetic larynx model. By systematically decreasing the spatial and temporal resolutions of the numerical model and optimizing the computational resources of the simulations, the elapsed simulation time was reduced by 90% to less than 70 h for 10 oscillation cycles of the vocal folds. The proposed computational larynx model with reduced mesh resolution is still able to capture the essential laryngeal flow characteristics and produce results with sufficiently good accuracy in a significant shorter time-to-solution. The reduction in computational time achieved is a promising step towards the clinical application of these computational larynx models in the near future.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Clinical potential; Computational cost; Glottal aerodynamics; Numerical larynx model

Toxicity of Mitoxantrone-loaded Superparamagnetic Iron Oxide Nanoparticles in a HT-29 Tumour Spheroid Model - Hornung, Annkathrin; Poettler, Marina; Friedrich, Ralf P.; Weigel, Bianca; Dürr, Stephan; Zaloga, Jan; Cicha, Iwona; Alexiou, Christoph; Janko, Christina (Anticancer Research, 2016)
Cancer research is commonly carried out in two-dimensional (2D) cell cultures, which poorly reflect in vivo settings where the growing tumours are exposed to mechanical forces and biochemical gradients. In this study we established a HF-29 colon carcinoma tumor spheroid model to investigate the effect of free mitoxantrone (MTO) and its nanoparticle-bound form (SPION(MTO)) under 3D cell culture conditions.Tumour spheroids were generated by seeding HT-29 colon carcinoma cells on agarose-coated cell culture wells. Growth of the spheroids was monitored daily by transmission microscopy upon treatment with free MTO, SPION(MTO) or unloaded SPION.Unloaded SPION did not affect the spheroid size compared to untreated controls, while both free MTO and SPION(MTO) inhibited growth of the spheroids in a dose- and time-dependent manner. In comparison to free MTO, the effect of SPION(MTO) on spheroid growth was slightly delayed. Further analyses are necessary to investigate if MTO infiltrates spheroids in its nanoparticle-bound form or whether it is released from SPION before infiltration.
EVALuna2:20010

Toxic retrobulbar neuritis due to recurrent nonsteroidal antiinflammatory drug-exacerbated respiratory disease-based chronic sinusitis in the left sphenoid sinus: a case report - Schapher, Mirco; Brügel, Jacob; Güner, Fabian; Volbers, Bastian; Eichhorn, Philip; Agaimy, Abbas; Berger, Magdalena; Mardin, Christian; Dörfler, Arnd; Hock, Stefan (Journal of Medical Case Reports, 2023)
BACKGROUND: Abrupt visual impairment constitutes a medical urgency, necessitating an interdisciplinary diagnostic and therapeutic approach owing to the broad spectrum of potential etiologies, thereby engaging numerous medical specialties. CASE PRESENTATION: A 21-year-old Mixed White and Asian female patient, with medical history of nonsteroidal antiinflammatory drug-exacerbated respiratory disease necessitating previous sinus surgery, reported sudden monocular vision loss. Unremarkable ophthalmological examination of the fellow eye and hematological parameters, save for a slight elevation in lymphocytes and eosinophils, were observed. Imaging studies indicated recurrence of bilateral chronic rhinosinusitis with nasal polyps and a mucocele in the left sphenoid sinus, accompanied by bony structural deficits. Emergency revision sinus surgery, guided by navigation, was promptly performed. The patient received treatment with methylprednisolone, ceftriaxone, cyanocobalamin, pyridoxine, thiamine, and acetylsalicylic acid. During the hospital stay, she developed steroid-induced glaucoma, which was subsequently managed successfully. Negative microbiological swabs, along with pathohistological evidence of increased tissue eosinophilia and the patient's clinical history, led to the diagnosis of toxic retrobulbar neuritis secondary to recurrent nonsteroidal antiinflammatory drug-exacerbated respiratory disease-associated chronic rhinosinusitis of the left sphenoid sinus. CONCLUSIONS: In cases of acute unilateral vision loss, optic neuritis is a highly probable differential diagnosis and may be induced by pathologies of the paranasal sinuses. Nonsteroidal antiinflammatory drug-exacerbated respiratory disease, a subtype of chronic rhinosinusitis, is associated with type 2 inflammation, which is increasingly recognized for its role in the pathogenesis of bronchial asthma, eosinophilic esophagitis, and atopic eczema. Clinicians should consider chronic rhinosinusitis as a potential differential diagnosis in unilateral visual loss and be cognizant of the rising significance of type 2 inflammations, which are relevant to a variety of diseases.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Blindness; Case report; Inflammation mediators; Neuritis; Optic; Sinusitis

Transdermal scopolamine for the prevention of a salivary fistula after parotidectomy - Mantsopoulos, Konstantinos; Goncalves, Miguel; Iro, Heinrich (British Journal of Oral and Maxillofacial Surgery, 2018)
Our aim was to investigate whether perioperative transdermal application of scopolamine could help to prevent fistulas after parotidectomy, and to this end we retrospectively studied the records of all patients (n=645) who had benign parotid tumours treated by partial parotidectomy between 2011 and 2016. We found that scopolamine led to a significant decrease in the incidence of salivary fistulas from 54/371(15%) in the group not given it to 10/274 (4%) in the group given it (p<0.0001). The "number needed to treat" was 9.17. There was a relatively low incidence of all adverse effects after scopolamine. Our results are encouraging. Thorough consideration of the contraindications and a knowledge of the potential adverse effects are crucial for its successful implementation.
EVALuna2:35391

Transferability of Deep Learning Algorithms for Malignancy Detection in Confocal Laser Endomicroscopy Images from Different Anatomical Locations of the Upper Gastrointestinal Tract - Aubreville, Marc; Goncalves, Miguel; Knipfer, Christian; Oetter, Nicolai; Würfl, Tobias; Neumann, Helmut; Stelzle, Florian; Bohr, Christopher; Maier, Andreas (Communications in Computer and Information Science, 2019)
Squamous Cell Carcinoma (SCC) is the most common cancer type of the epithelium and is often detected at a late stage. Besides invasive diagnosis of SCC by means of biopsy and histo-pathologic assessment, Confocal Laser Endomicroscopy (CLE) has emerged as noninvasive method that was successfully used to diagnose SCC in vivo. For interpretation of CLE images, however, extensive training is required, which limits its applicability and use in clinical practice of the method. To aid diagnosis of SCC in a broader scope, automatic detection methods have been proposed. This work compares two methods with regard to their applicability in a transfer learning sense, i.e. training on one tissue type (from one clinical team) and applying the learnt classification system to another entity (different anatomy, different clinical team). Besides a previously proposed, patch-based method based on convolutional neural networks, a novel classification method on image level (based on a pre-trained Inception V.3 network with dedicated preprocessing and interpretation of class activation maps) is proposed and evaluated. The newly presented approach improves recognition performance, yielding accuracies of 91.63% on the first data set (oral cavity) and 92.63% on a joint data set. The generalization from oral cavity to the second data set (vocal folds) lead to similar area-under-the-ROC curve values than a direct training on the vocal folds data set, indicating good generalization.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Confocal Laser Endomicroscopy; Head and neck squamous cell carcinoma; Transfer learning

Translating transcription: proteomics in chronic rhinosinusitis with nasal polyps reveals significant discordance with messenger RNA expression - Workman, Alan D.; Nocera, Angela L.; Mueller, Sarina K.; Otu, Hasan H.; Libermann, Towia A.; Bleier, Benjamin S. (International Forum of Allergy and Rhinology, 2019)
Background: Much of the literature examining chronic rhinosinusitis with nasal polyps (CRSwNP) immunopathology has been predicated on messenger RNA (mRNA) analysis with the assumption that transcriptional changes would reflect end-effector protein expression. The purpose of this study was to test this hypothesis using matched transcriptomic and proteomic data sets. Methods: Matched tissue proteomic and transcriptomic arrays were quantified in CRSwNP polyp tissue and control inferior turbinate tissue (n = 10/group). Mucus samples were additionally collected in 6 subjects from each group. Proteins were grouped into functional categories by bioinformatics and differential expression analyses. Log-log regression and Pearson correlations were performed to determine the level of agreement between data sets. Results: Of the 1310 proteins examined, 393 were significantly differentially expressed in CRSwNP. On regression analysis, differences in protein expression were poorly predicted by differences in mRNA expression (R2 = 0.020, p < 0.05). Several genes canonically thought to be overexpressed in CRSwNP, including IL-5, IL-13, TSLP, CCL13, and CCL26, showed substantial increases in mRNA transcription, but had minimally or unchanged protein expression. Others, including IgE, periostin, CCL18, and CST1/2, were increased at both the transcriptomic and proteomic levels. Among differentially regulated proteins, tissue and mucus protein levels showed weak correlation (r = 0.26, p < 0.0001). Conclusion: Proteomic analysis in CRSwNP has revealed novel disease-associated proteins and pathways, yet correlates poorly with transcriptomic data. The increasing availability of proteomic arrays opens the door to new potential explanatory mechanisms in CRSwNP and suggests that mRNA based studies should be validated with protein analysis.
CRIS-Team Scopus Importer:2019-07-30
Keywords: biomarker; chronic rhinosinusitis; chronic rhinosinusitis with nasal polyps; eosinophilic rhinitis; nasal polyposis; proteomics; transcriptomics

Transnasal Endoscopic Orbit and Optic Nerve Decompressions - Bleier, Benjamin S.; Mueller, Sarina K. (Transnasal Endoscopic Skull Base and Brain Surgery. Surgical Anatomy and its Applications, 2nd edition, 2019)
Although endoscopic orbital and optic nerve decompression have been technically feasible for over three decades, their indications and extent of surgery continue to be a subject of debate. The most common indication for orbital decompression is dysthyroid orbitopathy resulting from Graves' disease. Other indications include intra- and extraconal tumors. The goals of surgery are to decrease intraocular pressure, reduce proptosis, or provide access to intraorbital pathologies. The degree of lamina papyracea and orbital floor removal, as well as the use of adjunctive lateral decompression and orbital fat resection, must be tailored to the patient's disease. Optic nerve decompression involves removal of the bone of the optic strut and canal.
CRIS-Team WoS Importer:2020-12-04

Transoral submandibulotomy for deep hilar submandibular gland sialolithiasis - Schapher, Mirco; Mantsopoulos, Konstantinos; Meßbacher, Maria-Elena; Iro, Heinrich; Koch, Michael (Laryngoscope, 2017)
OBJECTIVES/HYPOTHESIS: To assess the long-term results after transoral submandibulotomy for stones located in the deep hilar and intraparenchymal submandibular region. STUDY DESIGN: Retrospective cohort analysis. METHODS: Retrospective evaluation including all patients treated with transoral submandibulotomy for sialolithiasis at a tertiary referral center. RESULTS: Complete stone removal at the first transoral surgical treatment was achieved in 185 of 234 patients (79.1%). One hundred seventy-five of the 234 patients were followed up for a mean of 31.2 ( ± 20.5) months. During the follow-up period, 140 of the 175 patients (80.0%) became symptom free after one operation. In patients with residual symptoms, no further treatment was needed in 12 patients (6.9%) due to the mildness of the symptoms; 23 patients (13.1%) received further therapy, which was successful in 15 cases. Submandibulectomy only had to be performed in 3.4% of the patients with follow-up (6/175). In a questionnaire survey, 91.4% of the patients stated that they would be prepared to have the same operation again. CONCLUSIONS: These findings show that transoral removal of submandibular sialoliths located in the deep hilum or adjacent intraglandular parenchyma is an effective treatment that can be assisted by additional measures. The techniques described show high success rates, good long-term results, low complication rates, and they avoided the need for submandibulectomy in >95% of cases. LEVEL OF EVIDENCE: 4. Laryngoscope, 127:2038-2044, 2017.
EVALuna2:33207

Transoral ultrasound: a helpful and easy diagnostic method in obstructive salivary gland diseases - Schapher, Mirco; Goncalves, Miguel; Mantsopoulos, Konstantinos; Iro, Heinrich; Koch, Michael (European Radiology, 2019)
• Transoral ultrasound is a simple technique, very helpful for the evaluation of obstructive diseases of the salivary glands. • It overcomes most of the limitations of transcutaneous ultrasound.
CRIS-Team Scopus Importer:2019-05-02

Transoral Ultrasound in the Diagnosis of Obstructive Salivary Gland Pathologies - Schapher, Mirco; Goncalves, Miguel; Mantsopoulos, Konstantinos; Iro, Heinrich; Koch, Michael (Ultrasound in Medicine and Biology, 2019)
Transcutaneous ultrasound (TCUS) is an accepted diagnostic method in salivary gland diseases. However, sparse data are available on the use of transoral ultrasound (TOUS) in sialadenopathies. One hundred five patients presenting with various obstructive sialadenopathies were examined using TOUS and TCUS. Ultrasound findings were validated by direct visualization in subsequent sialendoscopy examinations. By TOUS, but not by TCUS, all patients with sialolithiasis (70/105) could be identified and virtually all concrements, even very small ones, were detected and distinguished from artifacts. Ductal stenoses (16/105) could be correctly differentiated from sialoliths, and exceptional insights into the delicate anatomy of parotid duct stenoses were gained. TOUS provided detailed information on other space-occupying lesions (14/105) and circumvented the method-related diagnostic weaknesses of TCUS. As a valuable tool in the diagnosis of obstructive sialadenopathies, TOUS seems superior to TCUS in pathologies involving the distal parotid duct, the submandibular duct system and the floor of the mouth.
CRIS-Team Scopus Importer:2019-06-25
Keywords: Obstructive sialadenopathy; Salivary duct stenosis; Salivary glands; Sialolithiasis; Transoral ultrasound

Treadmill training and physiotherapy similarly improve dual task gait performance: a randomized-controlled trial in Parkinson's disease - Gaßner, Heiko; Trutt, Elmar; Seifferth, Sarah; Friedrich, Jana; Zucker, Diana; Salhani, Ziad; Adler, Werner; Winkler, Jürgen; Jost, Wolfgang H. (Journal of Neural Transmission, 2022)
Motor-cognitive dual tasks are used to investigate the interplay between gait and cognition. Dual task walking in patients with Parkinson's disease (PD) results in decreased gait speed and more importantly in an increased fall risk. There is evidence that physical training may improve gait during dual task challenge. Physiotherapy and treadmill walking are known to improve single task gait. The aim of this study was to investigate the impact of individualized physiotherapy or treadmill training on gait during dual task performance. 105 PD patients were randomly assigned to an intervention group (physiotherapy or treadmill). Both groups received 10 individual interventional sessions of 25 min each and additional group therapy sessions for 14 days. Primary outcome measure was the dual task gait speed. Secondary outcomes were additional gait parameters during dual task walking, UPDRS-III, BBS and walking capacity. All gait parameters were recorded using sensor-based gait analysis. Gait speed improved significantly by 4.2% (treadmill) and 8.3% (physiotherapy). Almost all secondary gait parameters, UPDRS-III, BBS, and walking capacity improved significantly and similarly in both groups. However, interaction effects were not observed. Both interventions significantly improved gait in patients with mild to moderate PD. However, treadmill walking did not show significant benefits compared to individualized physiotherapy. Our data suggest that both interventions improve dual task walking and therefore support safe and independent walking. This result may lead to more tailored therapeutic preferences.
CRIS-Team WoS Importer:2022-06-24

Treatment Efficiency of Free and Nanoparticle-Loaded Mitoxantrone for Magnetic Drug Targeting in Multicellular Tumor Spheroids - Hornung, Annkathrin; Poettler, Marina; Friedrich, Ralf P.; Zaloga, Jan; Unterweger, Harald; Lyer, Stefan; Nowak, Johannes; Odenbach, Stefan; Alexiou, Christoph; Janko, Christina (Molecules, 2015)
Major problems of cancer treatment using systemic chemotherapy are severe side effects. Magnetic drug targeting (MDT) employing superparamagnetic iron oxide nanoparticles (SPION) loaded with chemotherapeutic agents may overcome this dilemma by increasing drug accumulation in the tumor and reducing toxic side effects in the healthy tissue. For translation of nanomedicine from bench to bedside, nanoparticle-mediated effects have to be studied carefully. In this study, we compare the effect of SPION, unloaded or loaded with the cytotoxic drug mitoxantrone (MTO) with the effect of free MTO, on the viability and proliferation of HT-29 cells within three-dimensional multicellular tumor spheroids. Fluorescence microscopy and flow cytometry showed that both free MTO, as well as SPION-loaded MTO (SPION(MTO)) are able to penetrate into tumor spheroids and thereby kill tumor cells, whereas unloaded SPION did not affect cellular viability. Since SPION(MTO) has herewith proven its effectivity also in complex multicellular tumor structures with its surrounding microenvironment, we conclude that it is a promising candidate for further use in magnetic drug targeting in vivo.
EVALuna2:19979

Treatment of cervical paragangliomas: is surgery the only way? - Künzel, Julian; Koch, Michael; Brase, Christoph; Fietkau, Rainer; Iro, Heinrich; Zenk, Johannes (American Journal of Otolaryngology, 2014)
To analyze the results after surgery or stereotactic radiotherapy (SRT) in the treatment of cervical paragangliomas. Against this background, the decision-making algorithm used in the treatment of carotid body tumors (CBTs) and vagal paragangliomas (VPs) was reevaluated relative to the existing literature on the topic.Retrospective study between 2000 and 2012. A total of 27 CBTs and nine VPs in 32 patients were treated. Shamblin class I: 59.3% (n=16); class II: 29.6% (n=8); class III: 11.1% (n=3). Treatment modalities were surgery, radiotherapy, or observation. The end points for analysis were long-term tumor control and integrity of the cranial nerves.21 CBTs and seven VPs underwent surgery; SRT was performed in three CBTs and two VPs. Three CBTs were clinically observed. Permanent nerve paresis followed after surgery for CBTs in five patients (20%) and in all patients with VPs. No impaired cranial nerve function resulted after SRT. The median follow-up period was 4.7 years. The tumor control rate after therapy for CBTs and VPs was 100%. One CBT that received clinical observation showed slow tumor progression.A surgical procedure should be regarded as the treatment of choice in patients with small CBTs. In larger CBTs, particularly in elderly patients with unimpaired cranial nerves, radical surgery should be regarded critically. As surgery for VPs caused regularly impairment of cranial nerves with functional disturbances of various degrees a comprehensive consultation with the patient is mandatory and nonsurgical strategies should be discussed.
EVALuna2:18181

Treatment of M. Meniere with Betahistine: Critical Remarks on the BEMED Study - Ernst, A.; Schlattmann, P.; Waldfahrer, F.; Westhofen, M. (Laryngo-Rhino-Otologie, 2017)
The BEMED study (BMJ 2016; 352: DOI 10.1136) was designed as multi-centric, double-blind, plaebo-controlled study in patients with Menière's disease. It should compare a low-level (2 × 24 mg/d) vs. high-level (3 × 48 mg/d) betahstine intake vs. placebo. The primary endpoint was the "number of vertigo attacks lasting longer than 20 min as documented in a patient's diary". The main finding of the study was that betahistine did not significantly better reduced the number of vertigo attacks than placebo. Therefore, the BEMED study should be critically discussed in the present paper.
EVALuna2:35530

Treatment of Salivary Gland Diseases: Established Knowledge, Current Challenges and New Insights - Mantsopoulos, Konstantinos (Journal of Clinical Medicine, 2022)
CRIS-Team Scopus Importer:2022-02-25

Treatment of sialolithiasis: What has changed? an update of the treatment algorithms and a review of the literature - Koch, Michael; Mantsopoulos, Konstantinos; Müller, Susanna; Sievert, Matti; Iro, Heinrich (Journal of Clinical Medicine, 2022)
Treatment for sialolithiasis has undergone significant changes since the 1990s. Following the development of new minimally invasive and gland-preserving treatment modalities, a 40–50% rate of gland resection was reduced to less than 5%. Extracorporeal shock-wave lithotripsy (ESWL), refinement and extension of methods of transoral duct surgery (TDS), and in particular diagnostic and interventional sialendoscopy (intSE) are substantial parts of the new treatment regimen. It has also become evident that combining the different treatment modalities further increases the effectiveness of therapy, as has been especially evident with the combined endoscopic–transcutaneous approach. In the wake of these remarkable developments, a treatment algorithm was published in 2009 including all the known relevant therapeutic tools. However, new developments have also taken place during the last 10 years. Intraductal shock-wave lithotripsy (ISWL) has led to remarkable improvements thanks to the introduction of new devices, instruments, materials, and techniques, after earlier applications had not been sufficiently effective. Techniques involving combined approaches have been refined and modified. TDS methods have been modified through the introduction of sialendoscopy-assisted TDS in submandibular stones and a retropapillary approach for distal parotid sialolithiasis. Recent trends have revealed a potential for significant changes in therapeutic strategies for both major salivary glands. For the submandibular gland, ISWL has replaced ESWL and TDS to some extent. For parotid stones, ISWL and modifications of TDS have led to reduced use of ESWL and the combined transcutaneous–sialendoscopic approach. To illustrate these changes, we are here providing an updated treatment algorithm, including tried and tested techniques as well as promising new treatment modalities. Prognostic factors (e.g., the size or location of the stones), which are well recognized as having a strong impact on the prognosis, are taken into account and supplemented by additional factors associated with the new applications (e.g., the visibility or accessibility of the stones relative to the anatomy of the duct system).
CRIS-Team Scopus Importer:2022-01-07
Keywords: Combined treatment; Extracorporeal lithotripsy; Intraductal lithotripsy; Salivary gland; Sialendoscopy; Sialolithiasis; Transoral duct surgery; Treatment

Treatment of the donor site of free radial flaps: vacuum sealing versus conventional wound care - Koch, Michael; Jalyzada, Kavan; Grundtner, Philipp; Iro, Heinrich; Scherl, Claudia; Harreus, Ulrich; Kuenzel, Julian (Acta Oto-Laryngologica, 2017)
INTRODUCTION: Radial forearm flap donor side defects can be treated by vacuum therapy and conventional wound dressing. The aim of this study was to compare different wound management considering wound healing, including risk factors and cost effectiveness. MATERIALS AND METHODS: Retrospective study including patients treated with radial flaps in the Department of Head and Neck Surgery in Erlangen from January 2005 to August 2013. Wound healing was assessed regarding complications considering several risk factors and comorbidities. Data were analyzed comparing conventional dressing and vacuum therapy, including a calculation of costs. RESULTS: The study included 138 patients (n = 55 conventional dressing; n = 83 vacuum dressing). The incidence of wound complications in the vacuum group was 50.6 and 32.7% in the conventional dressing group (p = .058). The presence of risk factors and comorbidities did not have significant impact on the occurrence of complications. Costs for vacuum therapy turned out to be at least five times higher. CONCLUSION: In view of the current state of research, these results show that using vacuum dressings has no significant benefit in the wound management of forearm donor side defect covered with full-thickness skin grafts. If the costs and economical aspects are also considered, conventional wound dressing may be preferred.
EVALuna2:33185

Treatment strategy by radioiodine refractory differentiated thyroid cancer - Mantsopoulos, Konstantinos; Mueller, Sarina K.; Pavel, Marianne Ellen; Kuwert, Torsten; Meidenbauer, Norbert; Fietkau, Rainer; Sievert, Matti; Iro, Heinrich (Laryngo-Rhino-Otologie, 2021)
Zusammenfassung Traditionell besteht das multimodale Therapiekonzept bei den differenzierten Schilddrusenkarzinomen in der Thyreoidektomie mit Neck-Dissection (bei cN+-Halsstatus) und adjuvanten Radiojodablation mit abschlie ss ender risikoadaptierter TSH-Suppression. Das Ausma ss der Radiojodaufnahme beim metastasierten Schilddrusenkarzinom spielt eine signifikante Rolle bei der Einschatzung der Prognose. Das fehlende Jodspeicherungsvermogen einer Lasion in Zusammenschau mit dem fehlenden Abfall des Tumormarkers Thyreoglobulin sowie radiologische Zeichen einer Tumorprogression charakterisieren den Radiojod-refraktaren Patienten. Aufgrund des meistens uber einen langen Zeitraum indolenten Verlaufs erscheint in den meisten Fallen ein abwartendes Verhalten in Kombination mit lokaler Metastasenbehandlung sowie Symptomlinderung primar sinnvoll zu sein. Der Nachweis einer Veranderung der Tumordynamik ist der Zeitpunkt, um eine Systemtherapie zu evaluieren. Diese beruht auf Multi-Tyrosinkinase-Inhibitoren (Sorafenib, Lenvatinib). Diese Substanzen sind gro ss tenteils mit einem ungunstigen Nebenwirkungsprofil assoziiert (Diarrho, Hautauschlage, arterielle Hypertonie mit hypertensiver Entgleisung, lokale Wundheilungsstorungen), welches zu einer nicht vernachlassigbaren Rate einer therapieassoziierten Morbiditat sowie einer hohen Anzahl an Therapieunterbrechungen fuhrt. Daher sind im Jahr 2020 2 selektive RET-Inhibitoren (Selpercatinib, Pralsetinib) fur die differenzierten Schilddrusenkarzinome von der FDA zugelassen worden. Eine neue Perspektive fur die Zukunft waren die unterschiedlichen Redifferenzierungsstrategien, welche auf die Steigerung der Sensitivitat der Tumorzellen auf Radiojod abzielen.
CRIS-Team WoS Importer:2021-10-08

Treat or track: nanoagents in the service of health - Lyer, Stefan; Janko, Christina; Friedrich, Ralf P.; Poettler, Marina; Cicha, Iwona; Alexiou, Christoph (Nanomedicine, 2017)
EVALuna2:33195

TREM-1 Neutrophil Activation Pathway Is Suppressed in Eosinophilic Nasal Polyps - Wu, Dawei; Mueller, Sarina K.; Nocera, Angela L.; Finn, Kristen; Libermann, Towia A.; Bleier, Benjamin S. (American Journal of Rhinology & Allergy, 2018)
Background Chronic rhinosinusitis with nasal polyps (CRSwNP) is characterized by type 2 helper T-cell-skewed immune profiles, but the state of the neutrophil activation signaling pathway in CRSwNP is unknown. The purpose of this study was to examine neutrophil activation pathways in the pathogenesis of CRSwNP. Methods Institutional review board approved the study in which tissue proteomes were compared between control (inferior turbinate) and CRSwNP (nasal polyps) (n = 10/group) using an aptamer-based proteomic array and confirmed by whole transcriptomic analysis. Protein expression was analyzed using Student's t test and Benjamini-Hochberg procedures followed by the application of Ingenuity Pathway, MetaCore, and Genemania bioinformatics analyses. Results All the patients with CRSwNP (n = 10) had eosinophilic nasal polyps. Compared with controls, proteins associated with the triggering receptor expressed on myeloid cells 1 (TREM-1) neutrophil activation signaling pathway such as Calcineurin B, zeta chain-associated protein kinase of 70 kD (ZAP70), 14-3-3 protein theta, 14-3-3 protein zeta/delta, protein kinase C delta type (PKC-D), Interleukin (IL)-17B, IL-17B receptor, IL-23, and IL-1B were significantly decreased in CRSwNP (fold change [FC] = -1.60, P = .003; FC = -1.85, P = .040; FC = -1.26, P < .001; FC = -1.05, P = .008; and FC = -1.31, P = .004; FC = -1.22, P < .001; FC = -1.09, P = .022; FC = -1.25, P < .001; and FC = -1.31, P = .014; respectively). In contrast, tissue eosinophil count ( P < .001) and eosinophil-associated proteins such as C-C motif chemokine 17, periostin, and galectin 10 were all significantly increased in CRSwNP (FC = 1.56, P = .009; FC = 3.95, P < .001; and FC = 2.44, P < .001; respectively). Furthermore, the FC of the studied proteins' expression significantly and positively correlated with FC of their mRNA expression ( P = .001, r = .75). Conclusions TREM-1-associated neutrophilic signaling pathway proteins are significantly suppressed in eosinophilic CRSwNP.
EVALuna2:210633

Tumour‐infiltrating lymphocytes (Tils) and pd‐l1 expression correlate with lymph node metastasis, high‐grade transformation and shorter metastasis‐free survival in patients with acinic cell carcinoma (acicc) of the salivary glands - Hiß, Selina; Eckstein, Markus; Segschneider, Paul; Mantsopoulos, Konstantinos; Iro, Heinrich; Hartmann, Arndt; Agaimy, Abbas; Haller, Florian; Mueller, Sarina K. (Cancers, 2021)
Objectives: The aim of this study was to assess the number of tumour‐infiltrating lympho-cytes (TILs) and the expression of Programmed Cell Death 1 Ligand 1 (PD‐L1) in Acinic Cell Carcinoma (AciCC) of the salivary glands, to enable a correlation with clinico‐pathological features and to analyse their prognostic impact. Methods: This single centre retrospective study represents a cohort of 36 primary AciCCs with long‐term clinical follow‐up. Immunohistochemically defined immune cell subtypes, i.e., those expressing T‐cell markers (CD3, CD4 and CD8) or a B‐cell marker (CD20) were characterized on tumour tissue sections. The number of TILs was quantitatively evaluated using software for digital bioimage analysis (QuPath). PD‐L1 expression on the tumour cells and on immune cells was assessed immunohistochemically employing established scoring criteria: tu-mour proportion score (TPS), Ventana immune cell score (IC‐Score) and combined positive score (CPS). Results: Higher numbers of tumour‐infiltrating T‐ and B‐ lymphocytes were significantly associated with high‐grade transformation. Furthermore, higher counts of T‐lymphocytes correlated with node‐positive disease. There was a significant correlation between higher levels of PD‐ L1 expression and lymph node metastases as well as the occurrence of high‐grade transformation. Moreover, PD‐L1 CPS was associated with poor prognosis regarding metastasis‐free survival (p = 0.049). Conclusions: The current study is the first to demonstrate an association between PD‐L1 expression and lymph node metastases as well as grading in AciCCs. In conclusion, increased immune cell infiltration of T and B cells as well as higher levels of PD‐L1 expression in AciCC in association with high‐grade transformation, lymph node metastasis and unfavourable prognosis suggests a rel-evant interaction between tumour cells and immune cell infiltrates in a subset of AciCCs, and might represent a rationale for immune checkpoint inhibition.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Acinic cell carcinoma; Checkpoint inhibition; Immuno‐oncology; PD‐L1; Tumour‐infiltrating lymphocytes

Tumour spillage of the pleomorphic adenoma of the parotid gland: A proposal for intraoperative measures - Mantsopoulos, Konstantinos; Iro, Heinrich (Oral Oncology, 2021)
Intraoperative rupture of a pleomorphic adenoma capsule with potential tumor spillage into the surgical field is thought to occur in approximately 5% of cases and has traditionally been recognized as one of the major causes of recurrence. It seems that recurrence of a pleomorphic adenoma is a multifactorial event, being related to surgery (capsular exposure, tumor spillage) and tumor-related factors (histologic subtype, incomplete capsule, pseudopodia, satellites). The exact quantities of these ingredients in the recipe of recurrence, as well as possible interactions between them (e.g. the potentially increased fragility of myxoid pleomorphic adenomas; satellites or pseudopodia being cut off the tumor specimen during an extremely narrow extracapsular dissection) remain unclear. A thorough literature search did not reveal any proposed algorithms for the intraoperative management of a capsular tear. The aim of this short communication is to present our department's experience-based proposal for intraoperative measures in the case of macroscopic rupture and tumor spillage of a parotid gland pleomorphic adenoma.
CRIS-Team Scopus Importer:2021-01-08

Tuning the structure of aminoferrocene-based anticancer prodrugs to prevent their aggregation in aqueous solution - Daum, Steffen; Babiy, Svetlana; Konovalova, Helen; Hofer, Walter; Shtemenko, Alexander; Shtemenko, Natalia; Janko, Christina; Alexiou, Christoph; Mokhir, Andriy (Journal of Inorganic Biochemistry, 2018)
Aminoferrocene-based prodrugs are activated in cancer cells by reactive oxygen species (ROS). They were shown to exhibit high cytotoxicity towards a variety of cancer cell lines and primary cancer cells, but remain not toxic towards non-malignant cells. However, these prodrugs have rather high lipophilicity leading to relatively low water solubility. In particular, an n-octanol/water partition coefficient for the best aminoferrocene-based pro drug (2) was found to be 4.51 +/- 0.03. Though the approaches for decreasing lipophilicity are straightforward and include the addition of polar residues to the drug structure, these modifications also lead to dramatic decrease of cell permeability and, correspondingly, lower the activity of the drug. Therefore, a delicate balance of polar and unpolar groups should be found to reduce lipophilicity without compromising the useful drug properties. In this study we optimized an N-alkyl substituent, which is a key element responsible for the stabilization of the aminoferrocene drug released in cancer cells from prodrug 2. We found that an N-propargyl residue is an optimal replacement for the N-benzyl fragment. In particular, such a substitution (prodrug 7a) leads to reduction of prodrug lipophilicity down to logP = 3.78 +/- 0.05, improvement of its water solubility, decrease of its propensity towards aggregation and dramatic increase of its ROS-generating properties. Finally, we demonstrated that the optimized prodrug strongly suppresses growth of Guerin's carcinoma (T8) in vivo at the dose of 30 mg/kg.
EVALuna2:213359

Ultra-high-Resolution-CT: optimal Detail Accuracy of the Larynx Structure Comment - Bosch, Nikolaus (Laryngo-Rhino-Otologie, 2020)
CRIS-Team WoS Importer:2020-07-10

Ultraschallbasierte Detektion von magnetischen Nanopartikeln für das Magnetic Drug Targeting - Fink, Michael; Alexiou, Christoph; Ermert, Helmut; Lyer, Stefan (Messtechnische Anwendungen von Ultraschall, 2016)

Ultrasound-Controlled Manual Magnet Repositioning in Magnet Dislocation of Cochlear Implants - Rupp, Robin; Hornung, Joachim; Balk, Matthias; Traxdorf, Maximilian; Sievert, Matti; Hoppe, Ulrich; Iro, Heinrich; Gostian, Antoniu Oreste (Otology & Neurotology, 2021)
OBJECTIVE: To investigate whether ultrasound is a helpful and reliable diagnostic tool to survey the status of the magnet previous and after manual repositioning in patients with partially dislocated cochlear implant (CI) magnets and to assess the success rate of a manual repositioning maneuver. DESIGN: A prospective cohort study. SETTING: A tertiary referral medical center. PATIENTS: Patients with a cochlear implant who presented with magnet dislocation after magnetic resonance imaging (MRI) between June 1, 2019 and July 15, 2020. INTERVENTIONS: Manual repositioning of the partially dislocated CI magnet surveyed by pre- and post-interventional ultrasound. MAIN OUTCOME MEASURES: Rate of successfully diagnosed and manually repositioned magnets; complication rate and recurrence rate after initial manual repositioning maneuver. RESULTS: Nine patients presented with a partial magnet dislocation diagnosed by pre-interventional ultrasound following MRI (n = 9 magnets; three ♀; eight right-sided implants; 65.4 ± 21.7 yr). All magnets were repositioned manually. The magnets were successfully repositioned at the first attempt in six out of eight patients. Two patients required a second and one patient a third attempt of manual repositioning. Post-interventional ultrasound confirmed the entirely restored magnet position in all cases. During the mean follow-up period of 7.3 months (±5.4 mo) no patient experienced any complication or recurrent dislocation of the respective magnet. CONCLUSION: Manual magnet repositioning is a feasible and reliable method with a high success rate for partially dislocated CI magnets. The pre-interventional diagnosis as well as the post-interventional confirmation of the magnet status can be effectively determined by ultrasound. Thus, manual magnet repositioning and ultrasound investigation can be advocated as first-line therapeutic and diagnostic instruments when dealing with partial magnet dislocation.
CRIS-Team Scopus Importer:2021-06-04

Ultrasound in Diagnosis of Magnet Dislocation of Cochlear Implants: A Retrospective Study in Patients With Surgical Magnet Repositioning and Preinterventional Ultrasound Examination - Rupp, Robin; Hornung, Joachim; Balk, Matthias; Hoppe, Ulrich; Iro, Heinrich; Gostian, Antoniu Oreste (Otology & Neurotology, 2020)
OBJECTIVE: To investigate whether ultrasound is a reliable diagnostic tool to identify magnet dislocation in patients with cochlear implant. DESIGN: Retrospective analysis. SETTING: A tertiary referral medical center. PATIENTS: Patients with cochlear implant who presented with the suspicion of magnet dislocation between January 1, 2009 and July 31, 2019. INTERVENTIONS: Preinterventional ultrasound with subsequent surgical magnet repositioning. MAIN OUTCOME MEASURES: Accuracy of ultrasound in detecting magnet dislocation; intraoperative extent of magnet dislocation. RESULTS: Out of the 28 included patients (n = 28 magnets, 36% ♀; 51.6 years [±19.0 yr]) the diagnosis by the preoperative ultrasound was confirmed intraoperatively in 25 patients (89%). In two cases (7%), tissue swelling impeded the determination of the magnet by the preoperative ultrasound. In one case, ultrasound misdiagnosed the magnet as not dislocated. During revision surgery, all 28 magnets were repositioned successfully revealing a predominant partial dislocation (86%) compared with complete magnet dislocation (14%). CONCLUSION: In CI-patients undergoing 1.5 Tesla MRI, partial magnet dislocation occurs much more frequently than complete magnet dislocation. The clinical suspicion of a dislocated cochlear implant magnet can be accurately confirmed by preoperative ultrasound. Thus, preoperative diagnostic ultrasound can be advocated as the diagnostic tool of first choice.
CRIS-Team Scopus Importer:2020-09-25

Ultrasound in inflammatory and obstructive salivary gland diseases: Own experiences and a review of the literature - Koch, Michael; Sievert, Matti; Iro, Heinrich; Mantsopoulos, Konstantinos; Schapher, Mirco (Journal of Clinical Medicine, 2021)
Background: Ultrasound is established as a diagnostic tool in salivary glands for obstructive diseases such as sialolithiasis and tumors. Concerning inflammatory diseases and in non-sialolithiasis-caused obstruction, much fewer data are available. In recent years, technical devel-opment has allowed a better assessment of the gland parenchyma, and knowledge about intraductal pathologies has increased considerably, which has provided new insights and a new interpretation of ultrasound findings. Objectives: To provide a comprehensive review of the literature that in-cludes our own experiences and to point out the state of the art in ultrasound in the diagnostics of inflammatory and obstructive salivary gland diseases, taking adequate techniques and recent technical developments into consideration. Data sources and study eligibility criteria: A systematic literature search was performed in Pubmed using various specific key words. Results: According to the literature results, including our own experiences, ultrasound is of value in up to >90% of cases presenting with inflammatory and/or obstructive diseases. Technical developments (e.g., elastography) and the application of modified ultrasound techniques (e.g., transoral ultrasound) have contributed to these results. Today, ultrasound is considered a first-line diagnostic tool in these diseases. However, in some inflammatory diseases, the final diagnosis can be made only after inclusion of the anamnesis, clinical symptoms, serologic blood tests, or histopathologic investiga-tion. Conclusions: Ultrasound can be considered as a first-line diagnostic tool in obstructive and inflammatory salivary gland diseases. In obstructive diseases, it may be sufficient for diagnostics in >90% of cases. In inflammatory diseases, ultrasound is at least an excellent screening method and can be used to establish the diagnosis in cases of an early suspicion. In all diseases ultrasound can contribute to better management and can be used for monitoring during follow-up.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Inflammatory; Obstructive; Salivary calculi; Salivary gland; Salivary gland diagnosis; Salivary gland disorders; Salivary ultrasonography; Sialadenitis

Ultrasound in the Assessment of Parotid Duct Stenosis - Goncalves, Miguel; Mantsopoulos, Konstantinos; Schapher, Mirco; Iro, Heinrich; Koch, Michael (Journal of Ultrasound in Medicine, 2019)
Objectives Parotid duct stenosis may occur with or without accompanying ductal anomalies, with associated differences in their pathogenesis and management. By identifying the characteristics of a stenosis, ultrasound (US) can assist in tailored management of parotid duct stenosis. The objective of this study was therefore to describe the US characteristics of parotid duct stenoses and to evaluate criteria for whether and in what ways these can be distinguished from each other by using US. Methods A total of 108 patients who presented with parotid duct stenoses (130 parotid glands) were examined with high-resolution US between 2014 and 2017. The stenoses were assessed for duct dilatation, location, signs of ductal anomalies (circular encroachments/webs, duct bending/kinking, and presence of a megaduct) and the echogenicity of the gland parenchyma. Results Ultrasound was able to distinguish between stenoses associated with ductal anomalies and those without anomalies. Webs (82.5% versus 7.8%; P < .001), kinking (75.0% versus 3.3%; P < .001), and a megaduct (87.50% versus 15.63%; P < .001) and a tendency toward normal echogenicity in the gland parenchyma (77.5% versus 25.6%; P < .001) were significantly associated with ductal anomalies. Stenoses associated with ductal anomalies also had significantly larger duct diameters in comparison with those without anomalies (mean +/- SD, 9.19 +/- 3.65 versus 3.27 +/- 2.17 mm; P < .001). Conclusions This study describes US parameters that allow more detailed characterization of parotid stenoses with or without accompanying ductal anomalies. Differentiating between these at an early stage may be helpful for decision making on the further management in these patients.
CRIS-Team WoS Importer:2019-11-01

Ultrasound in the diagnosis and differential diagnosis of enoral and plunging ranula: a detailed and comparative analysis - Koch, Michael; Mantsopoulos, Konstantinos; Leibl, Victoria; Mueller, Sarina K.; Iro, Heinrich; Sievert, Matti (Journal of Ultrasound, 2022)
Purpose To develop sonographic criteria for ranula that to allow rapid and precise diagnosis, differentiation between enoral (ER) and plunging ranula (PR), and differential diagnosis from other competing pathologies in this region.Methods Patients who presented with or were referred with ranula between 2002 and 2022 were assessed in a retrospective study. After clinical investigation, ultrasound examinations were performed in all cases. Several sonographic parameters describing the echotexture, shape and size of ranulas, their relationship to important surrounding anatomical landmarks and the characteristic spreading pattern of ERs and PRs were elaborated and evaluated.Results 207 ranulas were included (82.12% ERs and 17.87% PRs). The ranulas were all in close anatomical relationship to the sublingual gland (SLG) and mylohyoid muscle (MM). The echo texture was hypoechoic to anechoic in 97.6% of the lesions. In comparison with ERs, PRs were larger and irregular in shape significantly more often (P = 0.0001). There were significant differences between ERs and PRs in their exact location relative to the SLG (superficial, deep, anterior, each P = 0.0001; posterior, P = 0.03) and level of the MM (above, below, above and below, P = 0.0001 each). The exact extent and plunging pattern were depicted in all PRs, but naturally in none of the ERs.Conclusions The ultrasound criteria developed in this study, confirming previously published results, indicate that ultrasound is an excellent diagnostic tool for diagnosing ranula and differentiating between ERs and PRs.
CRIS-Team WoS Importer:2023-01-20

Ultrasound in the diagnosis of parotid duct obstruction not caused by sialolithiasis: diagnostic value in reference to direct visualization with sialendoscopy - Goncalves, Miguel; Mantsopoulos, Konstantinos; Schapher, Mirco; Iro, Heinrich; Koch, Michael (Dentomaxillofacial Radiology, 2021)
Objectives: The aim of this study was to evaluate the diagnostic value of ultrasound in the obstructive pathology of the parotic gland not caused by sialolithiasis using sialendoscopy as reference standard.
CRIS-Team WoS Importer:2021-03-26

Ultrasound-Mediated Cavitation of Magnetic Nanoparticles for Drug Delivery Applications - Huber, Christian; George, Benedikt; Rupitsch, Stefan Johann; Ermert, Helmut; Ullmann, Ingrid; Vossiek, Martin; Lyer, Stefan (Current Directions in Biomedical Engineering, 2022)
Magnetic nanoparticles guided by an external magnetic field can be used to deliver drugs (e.g., chemotherapeutics) to malignant regions (e.g., tumor tissue). Some nonmagnetic, sonosensitive nanoparticles are known to generate cavitation induced by focused ultrasound. This can can be used to monitor spatial/temporal particle distribution and to stimulate local drug release in target regions. Little to nothing is known about the sonosensitivity of magnetic nanoparticles. Therefore, we investigated this physical phenomenon in the present contribution. We showed that certain magnetic nanoparticles have high cavitation potential and are promising for further research in this regard.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cavitation; Drug Delivery; Magnetic Nanoparticles; Sonosensitivity; Ultrasound

Ultrasound Supplemented by Sialendoscopy: Diagnostic Value in Sialolithiasis - Goncalves, Miguel; Mantsopoulos, Konstantinos; Schapher, Mirco; Iro, Heinrich; Koch, Michael (Otolaryngology-Head and Neck Surgery, 2018)
Objective To assess the value of ultrasound, if indicated, supplemented by sialendoscopy, in the diagnosis of sialolithiasis. Study Design Retrospective study. Setting Referring center for salivary gland diseases. Subjects and Methods All patients who presented with a suspected diagnosis of obstructive sialopathy between January 2011 and April 2017 and had not undergone any treatment were retrospectively evaluated. A total of 2052 patients and 2277 glands were included in the study. Ultrasound examinations were carried out initially and followed by sialendoscopy in all cases. Direct demonstration of sialothiasis by sialendoscopy, transoral ductal surgery, and discharge of concrements/observation of fragments during sialendoscopy after extracorporeal shock-wave lithotripsy were regarded as definitive evidence of sialolithiasis. Results Ultrasound had an accuracy, sensitivity, specificity, positive predictive value, and negative predictive value of 94.77%, 94.91%, 94.57%, 96.14%, and 92.89%, respectively, for the diagnosis of sialolithiasis. All false-positive findings were correctly diagnosed, and in all false-negative findings, stones/fragments were visualized by sialendoscopy. Over 95% of the false-negative findings in major salivary glands (64/67) had visible ductal dilation in sonography, and in 73.1%, the stones not detected on ultrasound were located in the distal part of the duct, which is easily accessible with the sialendoscope. Conclusion This study shows that sialolithiasis can be diagnosed using ultrasonography with a high degree of certainty. If supplemented by sialendoscopy, the correct diagnosis could be established in virtually all cases of sialolithiasis. Ultrasound supplemented by sialendoscopy has the potential to serve as an alternative diagnostic standard in the future.
EVALuna2:35387

Unclear tumour of the ear lobe - Dürr, Stephan; Söder, Stephan; Rösler, Wolf; Schlechtweg, Philipp; Schick, B; Alexiou, Christoph (Laryngo-Rhino-Otologie, 2014)
EVALuna2:6586

Unexpected Detection of Parotid Gland Malignancy during Primary Extracapsular Dissection - Mantsopoulos, Konstantinos; Velegrakis, Stylianos; Iro, Heinrich (Otolaryngology-Head and Neck Surgery, 2015)
To evaluate the oncologic and functional outcome in cases in which a false preoperative working hypothesis "benign parotid tumor" led to a primary extracapsular dissection being performed rather than a traditional, more radical surgical modality.Case series with chart review.Academic tertiary referral center.The records of all patients treated for malignant tumors of the parotid gland between 2006 and 2012 were retrospectively studied. Patients were excluded from our study sample for insufficient data or if their histories indicated manifestation of malignant tumors without primary parotid origin (squamous cell carcinomas, lymphomas, melanomas), revision surgery, as well as concomitant or past malignant tumors. Consequently, a total of 29 patients with 30 primary malignant tumors of the parotid gland formed our study sample (14 men, 15 women; male:female ratio, 0.93:1; mean age, 55.4 years; range, 14-85 years).Of 30 cases, 22 had low-grade tumors. Further tumor cells were detected in only the histology specimens of the parotid in 3 of the 25 cases treated subsequently with completion parotidectomy. Five patients received adjuvant radiation. Five-year disease-specific survival was 100%; local disease control was 96.6%. Of 30 cases, 28 had House-Brackmann I after tumor treatment; the other 2 cases had a slight paralysis (House-Brackmann II).Beginning with the "false" working hypothesis and performing an extracapsular dissection in unsuspected cases seems to have no adverse impact on patients' survival and postoperative quality of life in cases in which definitive histology reveals malignancy.
EVALuna2:19991

Unexpected effects of systemic steroids on the CRSwNP proteome: is protein upregulation more important than inhibition? - Workman, Alan D.; Miyake, Michelle M.; Nocera, Angela L.; Mueller, Sarina K.; Finn, Kristen; Otu, Hasan H.; Libermann, Towia A.; Bleier, Benjamin S. (International Forum of Allergy and Rhinology, 2020)
Background: Oral steroids, traditionally thought of as immunosuppressive agents that are broad in their immunomodulatory effects, are a mainstay of treatment to reduce disease burden in chronic rhinosinusitis with nasal polyps (CRSwNP). The purpose of this study was to determine how differentially expressed proteins in CRSwNP are affected by oral steroid therapy. Methods: Matched exosomal proteomic arrays were quantified using aptamer-based methods in systemic steroid-naive CRSwNP patients before and after a standardized oral prednisone course (n = 12). Previously identified differentially expressed proteins in CRSwNP patients were compared to determine the effect of steroids on expression. Fisher's exact test and t test were applied to normalized protein expression profiles to determine significance. Results: Of 18 proteins previously identified to be highly underexpressed in CRSwNP, 16 (89%) had an average increase after systemic steroid treatment (p < 0.05). Lactoperoxidase, initially present at 9-fold lower concentrations in CRSwNP subjects, increased by 209% after steroid treatment. A similar trend was observed with other proteins of interest, including platelet factor 4 and C-C motif ligand 28. The converse of this steroid effect was not true; of the 53 proteins that are highly overexpressed in CRSwNP, only 22 (42%) decreased in quantity with steroid use. Conclusion: Proteomic analysis of differentially expressed proteins in CRSwNP demonstrates that systemic steroids cause almost uniform upregulation of transcriptionally decreased proteins, whereas the effects of steroids on transcriptionally increased proteins are more heterogeneous. Thus, proteomic analysis may be an effective tool to understand specific therapeutic benefits of steroid use in polyp disease and to create more targeted treatments.
CRIS-Team Scopus Importer:2020-02-14
Keywords: chronic rhinosinusitis; CRSwNP; nasal polyps; proteomics; steroids

Unilateral auditory cortex lesions impair or improve discrimination learning of amplitude modulated sounds, depending on lesion side - Schulze, Holger; Deutscher, Anke; Tziridis, Konstantin; Scheich, Henning (PLoS ONE, 2014)
A fundamental principle of brain organization is bilateral symmetry of structures and functions. For spatial sensory and motor information processing, this organization is generally plausible subserving orientation and coordination of a bilaterally symmetric body. However, breaking of the symmetry principle is often seen for functions that depend on convergent information processing and lateralized output control, e.g. left hemispheric dominance for the linguistic speech system. Conversely, a subtle splitting of functions into hemispheres may occur if peripheral information from symmetric sense organs is partly redundant, e.g. auditory pattern recognition, and therefore allows central conceptualizations of complex stimuli from different feature viewpoints, as demonstrated e.g. for hemispheric analysis of frequency modulations in auditory cortex (AC) of mammals including humans. Here we demonstrate that discrimination learning of rapidly but not of slowly amplitude modulated tones is non-uniformly distributed across both hemispheres: While unilateral ablation of left AC in gerbils leads to impairment of normal discrimination learning of rapid amplitude modulations, right side ablations lead to improvement over normal learning. These results point to a rivalry interaction between both ACs in the intact brain where the right side competes with and weakens learning capability maximally attainable by the dominant left side alone.
EVALuna2:19914

Untersuchung akustischer Rückkoppelung bei der menschlichen Phonation mittels Particle Image Velocimetry - Näger, Christoph; Kniesburges, Stefan; Becker, Stefan (Fortschritte der Akustik - DAGA 2023, 2023)

Untersuchung von Sprachaufnahmen heiserer Stimmen mittels phonologischer und phonemischer Merkmale - Haderlein, Tino; Middag, Catherine; Martens, Jean-Pierre; Döllinger, Michael; Nöth, Elmar (Aktuelle phoniatrisch-pädaudiologische Aspekte 2014, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD5.unters_4

Updated analysis of the phase II CheckRad-CD8 trial: First-line treatment of locally advanced head and neck squamous cell carcinoma with induction chemoimmunotherapy followed by radioimmunotherapy - Hecht, Markus; Eckstein, Markus; Kallies, Annett; Von Der Grun, Jens; Illmer, Thomas; Klautke, Gunther; Laban, Simon; Hautmann, Matthias; Brunner, Thomas; Tamaskovics, Balint; Hinke, Axel; Zhou, Jianguo; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Updated S2k AWMF guideline on obstructive sialadenitis Aktualisierte AWMF-S2k-Leitlinie zur obstruktiven Sialadenitis - Geisthoff, Urban; Al-Nawas, Bilal; Beutner, Dirk; Günzel, Thomas; Iro, Heinrich; Koch, Michael; Lell, Michael; Luers, Jan Christoffer; Schröder, Ursula; Sproll, Christoph; Teymoortash, Afshin; Uβmüller, Jürgen; et al. (Laryngo-Rhino-Otologie, 2021)
The update of this guideline was an important step to define standards for the use of sialendoscopy and other emerging minimally invasive techniques for the therapy of sialolithiasis and other obstructive salivary gland diseases. The current actualization was necessary to adapt the diagnostic and therapeutic algorithms to the current scientific knowledge. In this article they are presented in a shortened version with a focus on conservative therapeutic measures which are especially relevant for daily practice.
CRIS-Team Scopus Importer:2021-10-22
Keywords: guideline; meta-analysis; salivary duct stenosis; sialadenitis; sialolithiasis; therapy

Validation and enhancement of a vocal fold medial surface 3D reconstruction approach for in-vivo application - Schlegel, Patrick; Döllinger, Michael; Reddy, Neha K.; Zhang, Zhaoyan; Chhetri, Dinesh K. (Scientific Reports, 2023)
In laryngeal research, studying the vertical vocal fold oscillation component is often disregarded. However, vocal fold oscillation by its nature is a three-dimensional process. In the past, we have developed an in-vivo experimental protocol to reconstruct the full, three-dimensional vocal fold vibration. The goal of this study is to validate this 3D reconstruction method. We present an in-vivo canine hemilarynx setup using high-speed video recording and a right-angle prism for 3D reconstruction of vocal fold medial surface vibrations. The 3D surface is reconstructed from the split image provided by the prism. For validation, reconstruction error was calculated for objects located at a distance of up to 15 mm away from the prism. The influence of camera angle, changing calibrated volume, and calibration errors were determined. Overall average 3D reconstruction error is low and does not exceed 0.12 mm at 5 mm distance from the prism. Influence of a moderate (5°) and large (10°) deviation in camera angle led to a slight increase in error to 0.16 mm and 0.17 mm, respectively. This procedure is robust towards changes in calibration volume and small calibration errors. This makes this 3D reconstruction approach a useful tool for the reconstruction of accessible and moving tissue surfaces.
CRIS-Team Scopus Importer:2023-07-21

Validation of a classification and scoring system for the diagnosis of laryngeal and pharyngeal squamous cell carcinomas by confocal laser endomicroscopy - Sievert, Matti; Mantsopoulos, Konstantinos; Müller-Hübner, Sarina; Rupp, Robin; Eckstein, Markus; Stelzle, Florian; Oetter, Nicolai; Maier, Andreas; Aubreville, Marc; Iro, Heinrich; Goncalves, Miguel (Brazilian Journal of Otorhinolaryngology, 2021)
Introduction: Confocal laser endomicroscopy is an optical imaging technique that allows in vivo, real-time, microscope-like images of the upper aerodigestive tract's mucosa. The assessment of morphological tissue characteristics for the correct differentiation between healthy and malignant suspected mucosa requires strict evaluation criteria. Objective: This study aims to validate an eight-point score for the correct assessment of malignancy. Methods: We performed confocal laser endomicroscopy between March and October 2020 in 13 patients. 197 sequences (11.820 images) originated from the marginal area of pharyngeal and laryngeal carcinomas. Specimens were taken at corresponding locations and analyzed in H&E staining as a standard of reference. A total of six examiners evaluated the sequences based on a scoring system; they were blinded to the histopathological examination. The primary endpoints are sensitivity, specificity, and accuracy. Secondary endpoints are interrater reliability and receiver operator characteristics. Results: Healthy mucosa showed epithelium with uniform size and shape with distinct cytoplasmic membranes and regular vessel architecture. Confocal laser endomicroscopy of malignant cells demonstrated a disorganized arrangement of variable cellular morphology. We calculated an accuracy, sensitivity, specificity, positive predictive value, and negative predictive value of 83.2%, 81.3%, 85.5%, 86.7%, and 79.7%, respectively, with a κ-value of 0.64, and an area under the curve of 0.86. Conclusion: The results confirm that this scoring system is applicable in the laryngeal and pharyngeal mucosa to classify benign and malignant tissue. A scoring system based on defined and reproducible characteristics can help translate this experimental method to broad clinical practice in head and neck diagnosis.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Confocal laser endomicroscopy; Diagnosis; Head and neck cancer; Squamous cell carcinoma

Validation of an automatic speech analysis in children with isolated cleft palate - Schulz, A.; Bocklet, Tobias; Eysholdt, Ulrich; Bohr, Christopher; Döllinger, Michael; Ziethe, A. (HNO, 2014)
Following surgical repair of cleft lip and palate, hearing and speech and language development are important issues for the continued care of affected childhood and adolescent patients. Therefore, PEAKS (Program for Evaluation and Analysis of all Kinds of Speech Disorders) was developed in order to rate speech intelligibility automatically and reduce the time required for diagnostics. PEAKS is based on a speech recognition system and was extended to incorporate a speaker model. This investigation validated PEAKS for isolated cleft palate.From each of the 39 children with isolated cleft palate (3.1-14.5 years), 99 word productions were recorded digitally and analyzed-once "subjectively" by five experts and five nonexperts; once "objectively" using PEAKS.The automatic speech recognition system and the experts arrive at similar results with regard to speech intelligibility. The expert and nonexpert ratings differ significantly from each other. Within the group of nonexperts, a weak interrater reliability demonstrates the uncertainty associated with their ratings.PEAKS delivers reliable and representative results with regard to speech intelligibility among children and adolescents with isolated cleft palate. The automatic measurement of speech quality in children and adolescents with isolated cleft palate is possible.
EVALuna2:19924

Validation of a predictive model for speech discrimination after cochlear impIant provision - Hoppe, Ulrich; Hast, Anne; Hocke, Thomas (HNO, 2023)
BackgroundIf sufficient speech discrimination is no longer achieved with conventional hearing systems, an audiological indication for a cochlear implant (CI) is given. However, there are no established target criteria for CI aftercare with regard to the level of speech comprehension to be achieved. The aim of this study is to validate an existing predictive model for speech comprehension after CI provision. This is applied to different patient groups.Materials and methodsThe prospective study included 124 postlingually deaf adults. The model is based on preoperative maximum monosyllabic recognition score, aided monosyllabic recognition score at 65 dB(SPL), and age the time of implantation. The model was investigated with regard to prediction accuracy for monosyllabic recognition with CI after 6 months.ResultsMean speech discrimination improved from 10% with hearing aid to 65% with CI after 6 months, with a statistically significant improvement in 93% of cases. Deterioration of aided unilateral speech discrimination was not observed. The mean prediction error was 11.5 percentage points in the cases with preoperative scores better than zero and 23.2 percentage points in all other cases.ConclusionCochlear implantation should also be considered in patients with moderately severe to severe hearing loss and insufficient speech discrimination with hearing aids. The model based on preoperatively measured data for predicting speech discrimination with CI can be used in preoperative consultation and in the context of postoperative quality assurance.
CRIS-Team WoS Importer:2023-05-26

Validation of the Mini Nutritional Assessment short-form (MNAA (R)-SF): A practical tool for identification of nutritional status - Kaiser, Matthias; Bauer, Judith; Ramsch, C.; Uter, Wolfgang; Guigoz, Y.; Cederholm, T.; Thomas, D. R.; Anthony, P.; Charlton, K. E.; Maggio, M.; Tsai, A. C.; Grathwohl, D.; et al. (Journal of Nutrition, Health & Aging, 2009)
To validate a revision of the Mini Nutritional Assessment short-form (MNAA (R)-SF) against the full MNA, a standard tool for nutritional evaluation.A literature search identified studies that used the MNA for nutritional screening in geriatric patients. The contacted authors submitted original datasets that were merged into a single database. Various combinations of the questions on the current MNA-SF were tested using this database through combination analysis and ROC based derivation of classification thresholds.Twenty-seven datasets (n=6257 participants) were initially processed from which twelve were used in the current analysis on a sample of 2032 study participants (mean age 82.3y) with complete information on all MNA items. The original MNA-SF was a combination of six questions from the full MNA. A revised MNA-SF included calf circumference (CC) substituted for BMI performed equally well. A revised three-category scoring classification for this revised MNA-SF, using BMI and/or CC, had good sensitivity compared to the full MNA.The newly revised MNA-SF is a valid nutritional screening tool applicable to geriatric health care professionals with the option of using CC when BMI cannot be calculated. This revised MNA-SF increases the applicability of this rapid screening tool in clinical practice through the inclusion of a "malnourished" category.
Keywords: Mini Nutritional Assessment; short-form; weight; body mass index; calf circumference; elderly

Validierung eines Modells zur Vorhersage des Sprachverstehens nach Cochleaimplantation - Hoppe, Ulrich; Hast, Anne; Hocke, Thomas (HNO, 2023)
Background: If sufficient speech discrimination is no longer achieved with conventional hearing systems, an audiological indication for a cochlear implant (CI) is given. However, there are no established target criteria for CI aftercare with regard to the level of speech comprehension to be achieved. The aim of this study is to validate an existing predictive model for speech comprehension after CI provision. This is applied to different patient groups. Materials and methods: The prospective study included 124 postlingually deaf adults. The model is based on preoperative maximum monosyllabic recognition score, aided monosyllabic recognition score at 65 dBSPL, and age the time of implantation. The model was investigated with regard to prediction accuracy for monosyllabic recognition with CI after 6 months. Results: Mean speech discrimination improved from 10% with hearing aid to 65% with CI after 6 months, with a statistically significant improvement in 93% of cases. Deterioration of aided unilateral speech discrimination was not observed. The mean prediction error was 11.5 percentage points in the cases with preoperative scores better than zero and 23.2 percentage points in all other cases. Conclusion: Cochlear implantation should also be considered in patients with moderately severe to severe hearing loss and insufficient speech discrimination with hearing aids. The model based on preoperatively measured data for predicting speech discrimination with CI can be used in preoperative consultation and in the context of postoperative quality assurance.
CRIS-Team Scopus Importer:2023-03-31
Keywords: Hearing aids; Hearing loss; Hearing tests; Speech audiometry; Speech discrimination tests

Validity of tissue homogeneity in confocal laser endomicroscopy on the diagnosis of laryngeal and hypopharyngeal squamous cell carcinoma - Sievert, Matti; Aubreville, Marc; Gostian, Antoniu-Oreste; Mantsopoulos, Konstantinos; Koch, Michael; Müller-Hübner, Sarina; Eckstein, Markus; Rupp, Robin; Stelzle, Florian; Oetter, Nicolai; Maier, Andreas; Iro, Heinrich; et al. (European Archives of Oto-Rhino-Laryngology, 2022)
Purpose: Confocal laser endomicroscopy (CLE) allows imaging of the laryngeal mucosa in a thousand-fold magnification. This study analyzes differences in tissue homogeneity between healthy mucosa and squamous cell carcinoma (SCC) via CLE. Materials and methods: We included five SCC patients with planned total laryngectomy in this study between October 2020 and February 2021. We captured CLE scans of the tumor and healthy mucosa. Analysis of image homogeneity to diagnose SCC was performed by measuring the signal intensity in four regions of interest (ROI) in each frame in a total of 60 sequences. Each sequence was assigned to the corresponding histological pattern, derived from hematoxylin and eosin staining. In addition, we recorded the subjective evaluation of seven investigators regarding tissue homogeneity. Results: Out of 3600 images, 1620 (45%) correlated with benign mucosa and 1980 (55%) with SCC. ROIs of benign mucosa and SCC had a mean and standard deviation (SD) of signal intensity of, respectively, 232.1 ± 3.34 and 467.3 ± 9.72 (P < 0.001). The mean SD between the four different ROIs was 39.1 ± 1.03 for benign and 101.5 ± 2.6 for SCC frames (P < 0.001). In addition, homogeneity yielded a sensitivity and specificity of 81.8% and 86.2%, respectively, regarding the investigator-dependent analysis. Conclusions: SCC shows a significant tissue inhomogeneity in comparison to the healthy epithelium. The results support this feature’s importance in identifying malignant mucosa areas during CLE examination. However, the examiner-dependent evaluation emphasizes that homogeneity is a sub-criterion that must be considered in a broad context.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Classification system; Confocal laser endomicroscopy; Head and neck cancer; Larynx; Non-invasive histological imaging; Pharynx

Value of confocal laser endomicroscopy in the diagnosis of vocal cord lesions - Goncalves, M.; Iro, Heinrich; Dittberner, A.; Agaimy, Abbas; Bohr, Christopher (European Review for Medical and Pharmacological Sciences, 2017)
The aim of this study was to assess the reliability and limitations of confocal laser endomicroscopy (CLE) for diagnosing lesions of the vocal cords and differentiating malignant from non-malignant lesions.During microlaryngoscopy, the vocal cords were scanned by probe-based CLE (pCLE: a GastroFlex probe with the Cellvizio® laser system, Mauna Technologies, Paris, France). The video recordings were analyzed and compared with the histological results. Thirty-one representative images were extracted and presented to four medical professionals (blinded examiners) for assessment.The accuracy for the category malignant/nonmalignant ranged between 58.1% and 87.1%. Overall interrater reliability was 0.29. Sensitivity ranged between 45.5 and 100%, specificity between 60.0 and 100%, PPV between 38.5% and 100% and NPV between 66.7 and 100%.CLE is a promising method for the non-invasive diagnosis of vocal cord lesions in vivo, but factors such as small penetration depth, not available contrast media for the nuclei and subjective analyses of the images limit, at the moment, its diagnostic value.
EVALuna2:6891

Value of Sonography in the Diagnosis of Sialolithiasis: Comparison With the Reference Standard of Direct Stone Identification - Goncalves, Miguel; Schapher, Mirco; Iro, Heinrich; Wüst, Wolfgang; Mantsopoulos, Konstantinos; Koch, Michael (Journal of Ultrasound in Medicine, 2017)
The aim of this study was to assess the effectiveness of sonography for diagnosing sialolithiasis in comparison with the existing reference standard of direct identification of a stone.A total of 659 glands with signs of obstructive sialadenopathy were evaluated retrospectively. Sonographic examinations of the large head salivary glands had been performed initially in all cases. Direct depiction of a stone during sialoendoscopy or transoral ductal surgery or observation of stone fragmentation with discharge of concrements after extracorporeal shock wave lithotripsy, was regarded as definitive evidence and as the reference standard for the presence of sialolithiasis. The sonographic results were compared with those for direct identification of stones.The sensitivity of sonography was 94.7%, with specificity of 97.4%, a positive predictive value of 99.4%, and a negative predictive value of 79.6%. Stones that were not diagnosed correctly on sonography were most often located in the distal area of the duct.These results show that sialolithiasis can be diagnosed by sonography with a high degree of certainty. Sonography thus appears to be highly appropriate as the examination method of choice.
EVALuna2:14673

Vascularization of the dorsal base of the second metacarpal bone: an anatomical study using C-arm cone beam computed tomography - Bermel, Christina; Saalabian, Ali A.; Horch, Raymund E.; Dörfler, Arnd; Alexiou, Christoph; Lyer, Stefan; Neuhuber, Winfried; Arkudas, Andreas; Kneser, Ulrich (Plastic and Reconstructive Surgery, 2014)
Vascularized bone grafts of the hand are a promising option for treatment of hand abnormalities. Therefore, the purpose of this study was to analyze the arterial anatomy of the dorsal aspect of the second metacarpal base to further investigate this possible donor site for bone grafts.The authors examined 16 fresh frozen cadaveric hands by using a C-arm cone beam computed tomography scanner and depicted the three-dimensional course of the second dorsal metacarpal artery and measured the diameter, length, and arc of rotation of this nutritive vessel. In addition, the authors dissected six of the hands under a dissecting microscope and, after selective injection of gelatin dye solution, the authors analyzed the vessel entrances into the bones histologically.In all examined hands, the second dorsal metacarpal artery was a nutritive vessel to the dorsal base of the second metacarpal. The average diameter was 1.3±0.4 mm and the average length of the vascular pedicle was approximately 3.3±0.3 cm. In 14 of 16 cases, the arc of rotation was sufficient to reach the lunate without difficulty. Histologic analysis showed an intrinsic blood supply in the donor region with a vessel diameter of approximately 58 ?m. A clinical case with application in Kienböck disease is presented.Pedicled vascularized bone grafts from this area are suitable for clinical application to treat Kienböck disease if standard donor sites are unavailable.
EVALuna2:4144

Vergleich der subjektiv-auditiven RBH-Beurteilung mit apparativer prosodischer Analyse und Irregularitätsberechnung - Haderlein, Tino; Nöth, Elmar; Döllinger, Michael; Schwemmle, Cornelia; Ptok, Martin (Aktuelle phoniatrisch-pädaudiologische Aspekte 2013, 2013)

Verstaendlichkeit von Kindern mit unterschiedlichen orofazialen Spaltfehlbildungen - Schuster, Maria; Maier, Andreas; Schützenberger, Anne; Nkenke, Emeka; Holst, Alexandra; Rosanowski, Frank; Eysholdt, Ulrich (Aktuelle phoniatrische Aspekte 2008, 2008)

VEXAS syndrome mimicking lupus-like disease - Valor-Mendez, Larissa; Sticherling, Michael; Zeschick, Martin; Atreya, Raja; Schmidt, Daniela; Waldfahrer, Frank; Saake, Marc; Hüffmeier, Ulrike; Schett, Georg; Rech, Jürgen (Rheumatology, 2023)
CRIS-Team WoS Importer:2023-03-17

Visualisation of tumour regression after local chemotherapy with magnetic nanoparticles - A pilot study - Lyer, Stefan; Tietze, Rainer; Jurgons, Roland; Struffert, Tobias; Engelhorn, Tobias; Schreiber, Eveline; Dörfler, Arnd; Alexiou, Christoph (Anticancer Research, 2010)
Magnetic drug targeting (MDT) is a new locoregional chemotherapy method that increases the drug dose in the tumour region, while simultaneously reducing the overall dose through the application of chemotherapeuticbound superparamagnetic nanoparticles, which are focused by an external magnetic field to the desired body compartment. An important factor in this kind of therapy is the vascularisation of the targeted tumour. In this pilot study, the visualisation of the tumour-vascularisation before and after MDT was investigated. Materials and Methods: In a rabbit VX-2 tumour model, mitoxantrone bound to Fe3O4-nanoparticles was applied through the femoral artery close to the tumour. The visualisation of vascularisation and tumour size before and after MDT was performed using a biplane angiographic system (Siemens Axiom Artis dBA) to obtain conventional angiographic series with a standard iodine contrast agent. In addition, cross-sectional images were obtained with the new technique of flat panel detector computed tomography (FD-CT) called DYNA-CT. Results: The tumours and the supplying vessels were clearly displayed by FD-CT before and after MDT. The tumours of the study group showed considerable size reductions and the angiography showed a drastic reduction of the tumour supporting vessels following MDT. Conclusion: MDT leads to significant tumour size reductions within several weeks after a single administration of chemotherapy. In this pilot study, FD-CT offered an excellent possibility to monitor the vascularisation and the size of the tumours before and after MDT.
CRIS-Team Scopus Importer:2022-06-27
Keywords: Angiography; Computed tomography; Flat-panel CT; Local chemotherapy; Magnetic drug targeting; Tumour vascularisation

Visualization of Intelligibility Measured by Language-Independent Features - Haderlein, Tino; Middag, Catherine; Maier, Andreas; Martens, Jean-Pierre; Döllinger, Michael; Nöth, Elmar (Proc. Text, Speech and Dialogue; 17th International Conference, TSD 2014, 2014)
Automatic intelligibility assessment using automatic speech recognition is usually language-specific. In this study, a language-independent approach based on alignment-free phonological and phonemic features is proposed. It utilizes models that are trained with Flemish speech, and it is applied to assess dysphonic German speakers. In order to visualize the results, two techniques were tested: a plain selection of most relevant features emerging from Ensemble Linear Regression involving feature selection, and a Sammon transform of all the features to a 3-D space. The test data comprised recordings of 73 hoarse persons (48.3 ± 16.8 years) who read the German version of the text "The North Wind and the Sun". The reference evaluation was obtained by five speech therapists and physicians who rated intelligibility according to a 5-point Likert scale. In the 3-D visualization, the different levels of intelligibility were clearly separated. This could be the basis for an objective support for diagnostics in voice and speech rehabilitation. © 2014 Springer International Publishing.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD5.visual_0
Keywords: speech

Visualization of Magnetic Nanoparticles by Ultrasound Strain Imaging - Huber, Christian; El Aawar, Karim; Ullmann, Ingrid; Lyer, Stefan; Ermert, Helmut (SMSI 2023 Conference – Sensor and Measurement Science International, 2023)
In magnetic drug targeting, superparamagnetic nanoparticles are used as drug carriers. The local accumulation of these particles at the site of the tumor leads to a temporary change in the effective elastic tissue properties in this area. Therefore, mapping this change should allow visualization of the particle distribution. Ultrasound strain imaging is a method to map the local variation of elasticity. This method was tested using a polyvinyl alcohol ultrasound phantom with a magnetic nanoparticle inclusion. It was demonstrated, that this inclusion can be mapped in the proposed wa
Keywords: Ultraschallbildgebung; Ultraschallelastographie; Magnetische Nanopartikel; Magnetic Drug Targeting

Visualization of the flow through modulated irregular glottal gaps - Kirmse, Clemens; Triep, Michael; Brücker, Christoph; Döllinger, Michael; Stingl, Michael (Proceedings of the 16th International Congress on Sound and Vibration 2009, 2009)

Vitamin D Blood levels in Nursing home - Status Quo and Related to physical Functionality - Diekmann, Rebecca; Winning, Katrin; Bauer, Judith; Lesser, Stephanie; Stehle, P.; Sieber, Cornel; Volkert, Dorothee (Internist, 2013)

Vocal fold oscillation pattern changes related to loudness in patients with vocal fold mass lesions - Echternach, Matthias; Döllinger, Michael; Köberlein, Marie; Kuranova, Liudmila; Gellrich, Donata; Kainz, Marie Anne (Journal of Otolaryngology-Head & Neck Surgery, 2020)
Introduction: Vocal fold mass lesions can affect vocal fold oscillation patterns and therefore voice production. It has been previously observed that perturbation values from audio signals were lower with increased loudness. However, how much the oscillation patterns change with gradual alteration of loudness is not yet fully understood. Material and methods: Eight patients with vocal fold mass lesions were asked to perform a glide from minimum to maximum loudness on the vowel /i/, ƒo of 125 Hz for male or 250 Hz for female voices. During phonation the subjects were simultaneously recorded with transnasal high speed videoendoscopy (HSV, 20,000 fps), electroglottography (EGG), and an audio recording. Based on the HSV material the Glottal Area Waveform (GAW) was segmented and GAW parameters were computed. Results: The greatest vocal fold irregularities were observed at different values between minimum and maximum sound pressure level. There was a relevant discrepancy between the HSV and EGG derived open quotients. Furthermore, the EGG derived sample entropy and GAW values also evidenced different behavior. Conclusions: The amount of vocal fold irregularity changes with varying loudness. Therefore, any evaluation of the voice should be performed under different loudness conditions. The discrepancy between EGG and GAW values appears to be much stronger in patients with vocal fold mass lesions than those with normal physiological conditions. Level of evidence: 4.
CRIS-Team Scopus Importer:2020-11-27
Keywords: EGG; High-speed imaging; Loudness; Vocal fold mass lesions

Voice and Speech Assessment From Telephone Recordings Using Prosodic Analysis Based on mu-Law-Companded Features - Haderlein, Tino; Schützenberger, Anne; Döllinger, Michael; Nöth, Elmar (Speech Communication - 12. ITG Fachtagung Sprachkommunikation, 2016)
UnivIS-Import:2017-01-09:Pub.2016.tech.IMMD.IMMD5.voicea
Keywords: Sprache

Voice Handicap and Health-Related Quality of Life after Treatment for Small Laryngeal Carcinoma - Killguß, Helen; Gottwald, Frank; Haderlein, Tino; Maier, Andreas; Rosanowski, Frank; Iro, Heinrich; Psychogios, Georgios; Schuster, Maria (Folia Phoniatrica Et Logopaedica, 2011)

Voice handicap index and voice-related quality of life in small laryngeal carcinoma - Kasper, Claudia; Schuster, Maria; Psychogios, Georgios; Zenk, Johannes; Ströbele, Anika; Rosanowski, Frank; Grässel, Elmar; Haderlein, Tino (European Archives of Oto-Rhino-Laryngology, 2011)

Voice quality after thyroplasty type I using a silicone block - Sebova, I.; Ziethe, A.; Döllinger, Michael; Eysholdt, U. (Bratislava Medical Journal, 2019)
AIM: The aim of the work was to evaluate the voice quality of 10 adult patients after thyroplasty type I using a silicone block. Preoperatively patients suffered from unilateral vocal fold paralysis.
CRIS-Team WoS Importer:2019-12-06

Von der Stimmgabel zum 7T MRT - Der Einsatz objektiver Verfahren in der Audiologie From the tuning fork to 7T MRT - The use of objective methods in audiology - Hoppe, Ulrich; Hey, Matthias (Zeitschrift für Medizinische Physik, 2021)
CRIS-Team Scopus Importer:2021-07-23

Wall-less Flow Phantoms with 3D printed Soluble Filament for Ultrasonic Experiments - Huber, Christian; Lyer, Stefan; Ermert, Helmut; Heim, Christian; Rupitsch, Stefan J.; Ullmann, Ingrid (Current Directions in Biomedical Engineering, 2023)
Tissue-mimicking materials (TMMs) typically used for ultrasound phantoms include gelatin, agarose and polyvinyl alcohol (PVA). These materials have shown sufficient similarity in ultrasound parameters compared to human tissue. Despite their extensive use for years to generate ultrasound phantoms, no simple and easily reproducible way to generate complex, wall-less ultrasound flow phantoms has been introduced. Commercially available ultrasound flow phantoms are limited to simple flow geometries that do not reflect the complex blood flow in humans. Flow phantoms with complex geometries presented in scientific publications either have walls between TMMs and the flow channel, are limited to one material, or are complicated to produce. In this contribution, we present a method using 3D printing and soluble filament that allows for the reliable and consistent production of complex flow geometries with the typical materials used for ultrasound phantoms and without any walls.
CRIS-Team Scopus Importer:2023-10-20
Keywords: 3D Printing; Flow Experiments; Ultrasound; Ultrasound Phantoms

Watchful waiting in carefully selected metachronous cystadenolymphomas of the parotid gland: a reliable option? - Mantsopoulos, K.; Goncalves, Miguel; Koch, M.; Iro, Heinrich (British Journal of Oral and Maxillofacial Surgery, 2019)
The aim of this study was to evaluate the potential of watchful waiting in the treatment of metachronous cystadenolymphomas, taking the experience of our department into consideration. All patients suspected of having a metachronous cystadenolymphoma, and who had a minimum follow-up time of 12 months, were studied (n = 26). Data about the growth rate, number of lesions, and symptoms of inflammation were recorded. Mean (range) follow-up was 36 (13–94) months. Metachronous tumours developed in three cases on the ipsilateral side, in 22 cases on the contralateral side, and on both sides in one case. The mean rate of growth /lesion was 15% /year (range: 22%–158%). There were no signs of local inflammation. The extreme variability in the behaviour of metachronous cystadenolymphomas points to the need for an individualised approach, accurate investigation of the sonographic characteristics, and continuous watchful waiting in affected patients.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Benign tumours; Cystadenolymphoma; Parotid gland; Warthin tumour; Watchful waiting

Weight statistics controls dynamics in recurrent neural networks - Krauß, Patrick; Schuster, Marc; Dietrich, Verena; Schilling, Achim; Schulze, Holger; Metzner, Claus (PLoS ONE, 2019)
Recurrent neural networks are complex non-linear systems, capable of ongoing activity in the absence of driving inputs. The dynamical properties of these systems, in particular their long-time attractor states, are determined on the microscopic level by the connection strengths w(ij) between the individual neurons. However, little is known to which extent network dynamics is tunable on a more coarse-grained level by the statistical features of the weight matrix. In this work, we investigate the dynamics of recurrent networks of Boltzmann neurons. In particular we study the impact of three statistical parameters: density (the fraction of non-zero connections), balance (the ratio of excitatory to inhibitory connections), and symmetry (the fraction of neuron pairs with w(ij)= w(ij)). By computing a 'phase diagram' of network dynamics, we find that balance is the essential control parameter: Its gradual increase from negative to positive values drives the system from oscillatory behavior into a chaotic regime, and eventually into stationary fixed points. Only directly at the border of the chaotic regime do the neural networks display rich but regular dynamics, thus enabling actual information processing. These results suggest that the brain, too, is fine-tuned to the 'edge of chaos' by assuring a proper balance between excitatory and inhibitory neural connections.
CRIS-Team WoS Importer:2019-04-23

Word production in children with cochlear implant based on chronological age and hearing age Hör- und Lebensalter-bezogene Wortproduktion von Kindern mit Cochlea-Implantat - Glaubitz, Cynthia; Geiss, Katrin T.; Hoppe, Ulrich (Laryngo-Rhino-Otologie, 2022)
Background For congenitally deaf children, an early bilateral provision with cochlear implant (CI) is a favourable condition for language acquisition. The objective of the present study was to determine the word production in CI children. The focus was on a comparison of chronological age and hearing age performance and on the evaluation of potential effects of multilingualism, additional disabilities and age at provision. Methods The data of 62 children with bilateral CI (age at provision in months M= 12,1; SD = 6,2) were retrospectively analysed. Vocabulary was assessed by the test Aktiver Wortschatztest für 3- bis 5-jährige Kinder – Revision and compared for chronological age and hearing age. Group comparisons and correlation analysis was conducted regarding multilingualism, additional disabilities and age at provision. Results The cohort performed significantly better when referenced o hearing age: level were within or above the norm in more than 50 %; referenced to chronological age in around 37 %. The descriptive performance differences for multilingualism and additional disabilities were only significant for children with both characteristics. Performance of monolingual children without additional disabilities was not significantly associated with age at provision. Conclusion CI children may achieve an adequate expressive vocabulary at the age of 3 to 5 years. Multilingualism and additional disabilities seem to be particular challenges for CI children and need a more precise definition in further studies. The use of both chronological and hearing age as reference marks allows a differentiated assessment of the language status. This may lead to benefits in therapeutic interventions and parent councelling.
CRIS-Team Scopus Importer:2022-09-30
Keywords: AWST-R; Cochlea-Implantation; expressive Sprache; Höralter; Mehrsprachigkeit; Sprachdiagnostik; Sprachentwicklung; Sprachproduktion; Wortschatz; Zusatzbeeinträchtigung

YAP1-NUTM1 Gene Fusion in Porocarcinoma of the External Auditory Canal - Agaimy, Abbas; Tögel, Lars; Haller, Florian; Zenk, Johannes; Hornung, Joachim; Märkl, Bruno (Head and Neck Pathology, 2020)
Gene fusions involving the NUTM1 gene (NUT) represent defining genetic markers of a highly aggressive carcinoma type with predilection for the midline structures of children and young adults, hence the original description as NUT midline carcinoma. Recent studies have increasingly documented involvement of the NUTM1 gene in the pathogenesis of other entities as well. We herein describe two cases of auditory canal carcinomas with features of porocarcinoma, both harboring a newly described YAP1-NUTM1 gene fusion. Patients were males aged 28 and 82 years who presented with slowly growing lesions in the external auditory canal. Histologic examination showed monomorphic basaloid and squamoid cells arranged into organoid solid aggregates, nests, ducts, small cysts, and focal pseudocribriform pattern with variable mitotic activity, infiltrative growth, and focal squamous differentiation, particularly in the most superficial part of the tumor. Immunohistochemistry revealed consistent reactivity for CK5, p63 and SOX10 and diffuse aberrant expression of TP53. CK7 expression was limited to a few luminal ductal cells. The androgen receptor and S100 were negative. Next generation sequencing (TruSight RNA fusion panel, Illumina) revealed the same YAP1-NUTM1 gene fusion in both tumors, which was subsequently confirmed by NUT-FISH and the monoclonal anti-NUT antibody. These cases represent a novel contribution to the spectrum of NUT-rearranged head and neck malignancies. This adnexal carcinoma variant should not be confused with the highly lethal NUT carcinoma based on NUT immunoreactivity alone.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Auditory canal; Ear; Head and neck; Midline carcinoma; NUT carcinoma; NUTM1; YAP1

β-Secretase BACE1 Is Required for Normal Cochlear Function - Dierich, Marlen; Hartmann, Stephanie; Dietrich, Nadine; Möser, Philip; Brede, Franziska; Johnson Chacko, Lejo; Tziridis, Konstantin; Schilling, Achim; Krauß, Patrick; Heßler, Sabine; Karch, Sandra; Schrott-Fischer, Anneliese; et al. (The Journal of Neuroscience, 2019)
Cleavage of amyloid precursor protein (APP) by β-secretase BACE1 initiates the production and accumulation of neurotoxic amyloid-β peptides, which is widely considered an essential pathogenic mechanism in Alzheimer's disease (AD). Here, we report that BACE1 is essential for normal auditory function. Compared with wild-type littermates, BACE1-/- mice of either sex exhibit significant hearing deficits, as indicated by increased thresholds and reduced amplitudes in auditory brainstem responses (ABRs) and decreased distortion product otoacoustic emissions (DPOAEs). Immunohistochemistry revealed aberrant synaptic organization in the cochlea and hypomyelination of auditory nerve fibers as predominant neuropathological substrates of hearing loss in BACE1-/- mice. In particular, we found that fibers of spiral ganglion neurons (SGN) close to the organ of Corti are disorganized and abnormally swollen. BACE1 deficiency also engenders organization defects in the postsynaptic compartment of SGN fibers with ectopic overexpression of PSD95 far outside the synaptic region. During postnatal development, auditory fiber myelination in BACE1-/- mice lags behind dramatically and remains incomplete into adulthood. We relate the marked hypomyelination to the impaired processing of Neuregulin-1 when BACE1 is absent. To determine whether the cochlea of adult wild-type mice is susceptible to AD treatment-like suppression of BACE1, we administered the established BACE1 inhibitor NB-360 for 6 weeks. The drug suppressed BACE1 activity in the brain, but did not impair hearing performance and, upon neuropathological examination, did not produce the characteristic cochlear abnormalities of BACE1-/- mice. Together, these data strongly suggest that the hearing loss of BACE1 knock-out mice represents a developmental phenotype.SIGNIFICANCE STATEMENT Given its crucial role in the pathogenesis of Alzheimer's disease (AD), BACE1 is a prime pharmacological target for AD prevention and therapy. However, the safe and long-term administration of BACE1-inhibitors as envisioned in AD requires a comprehensive understanding of the various physiological functions of BACE1. Here, we report that BACE1 is essential for the processing of auditory signals in the inner ear, as BACE1-deficient mice exhibit significant hearing loss. We relate this deficit to impaired myelination and aberrant synapse formation in the cochlea, which manifest during postnatal development. By contrast, prolonged pharmacological suppression of BACE1 activity in adult wild-type mice did not reproduce the hearing deficit or the cochlear abnormalities of BACE1 null mice.
CRIS-Team Scopus Importer:2019-11-15
Keywords: Alzheimer's disease; auditory function; BACE1; BACE1 inhibitor NB-360; BACE1 knock-out mice; Neuregulin-1

Axonal Guidance Signaling Pathway Is Suppressed in Human Nasal Polyps - Wu, Dawei; Mueller, Sarina K.; Nocera, Angela L.; Finn, Kristen; Libermann, Towia A.; Bleier, Benjamin S. (American Journal of Rhinology & Allergy, 2018)
Background Dysfunctional innervation might contribute to the pathogenesis of chronic rhinosinusitis with nasal polyps (CRSwNP), but the state of the axonal outgrowth signaling in CRSwNP is unknown. The purpose of this study was to explore the axonal outgrowth pathway-related protein expression in CRSwNP. Methods Institutional review board approved study in which tissue proteomes were compared between control and CRSwNP patients (n = 10/group) using an aptamer-based proteomic array and confirmed by whole transcriptomic analysis. Results Compared with controls, proteins associated with axonal guidance signaling pathway such as beta-nerve growth factor, semaphorin 3A, Ras-related C3 botulinum toxin substrate 1, Bcl-2, protein kinase C delta type, and Fyn were significantly decreased in patients with CRSwNP (fold change [FC] = -1.17, P = .002; FC = -1.09, P < .001; FC = -1.33, P < .001; FC = -1.31, P < .001; FC = -1.31, P = .004; and FC = -1.20, P = 0.012, respectively). In contrast, reticulon-4 receptor, an inhibitory factor, was significantly increased in patients with CRSwNP (FC = 1.25, P < .001). Furthermore, neuronal growth-associated proteins such as ciliary neurotrophic factor receptor subunit alpha, neuronal growth regulator 1, neuronal cell adhesion molecule, neural cell adhesion molecule L1, platelet-derived growth factor subunit A, and netrin-4 were all significantly decreased in patients with CRSwNP (FC = -1.25, P < .001; FC = -1.27, P = .002; FC = -1.65, P = .013; FC = -4.20, P < .001; FC = -1.28, P < .001; and FC = -2.31, P < .001, respectively). In contrast, tissue eosinophil count ( P < .001) and allergic inflammation factors such as IgE, periostin, and galectin-10 were all significantly increased in patients with CRSwNP (FC = 12.28, P < .001; FC = 3.95, P < .001; and FC = 2.44, P < .001, respectively). Furthermore, the log FC of the studied proteins expression significantly and positively correlated with log FC of their mRNA expression ( P < .001, r = .88). Conclusions Axonal guidance signaling and neural growth factors pathways proteins are significantly suppressed in eosinophilic CRSwNP.
EVALuna2:210634

Cartilage Scales Embedded in Fibrin Gel - Kovacevic, Milos; Riedel, Frank; Wurm, Jochen; Bran, Gregor M. (Facial Plastic Surgery, 2017)
Multiple techniques have been described for dorsal nasal augmentation in rhinoplasty. In this article, we review common surgical techniques for raising the dorsum or eliminating dorsal irregularities, by highlighting inherent advantages and disadvantages of each method. Within the past few years, the use of diced cartilage grafts has become the workhorse in this field of interest. To overcome drawbacks of methods based on diced cartilage, we present a new concept for autologous augmentation, using regenerative medicine protocols. A mix of cartilage scales with cartilage pâté was embedded in platelet-rich fibrin (PRF). Since December 2015, a total of 48 patients were treated with this technique. Based on our preliminary results, cartilage scales in PRF appear to be a promising and reliable alternative to existing procedures for dorsal nasal augmentation.
EVALuna2:33188

Endoscopic DCR using bipedicled interlacing mucosal flaps - Mueller, Sarina K.; Freitag, Suzanne K.; Lefebvre, Daniel R.; Bleier, Benjamin S. (Laryngoscope, 2018)
OBJECTIVE: Obstruction of the nasolacrimal duct is a relatively common condition that affects patients of all ages, races, and sexes. The surgical gold standard for complete nasolacrimal duct obstruction and dacryocystitis is dacryocystorhinostomy (DCR). The purpose of this study was to describe a novel, bipedicled interlacing mucosal sparing flap technique for endoscopic DCR (eDCR). METHODS: A posteriorly based mucosal flap over the fundus is combined with a novel, anteriorly based mucosal flap over the intraosseus portion of the nasolacrimal duct (NLD). This exposes a wide area of the maxillary bone, allowing for exposure and identification of the NLD/sac complex in a safer, more inferior position. The interlacing mucosal flaps may be replaced at the conclusion of the procedure, thereby minimizing bone exposure and maintaining excellent long-term patency. RESULTS: The authors have utilized this technique in 55 procedures with 100% positive identification of the NLD and lacrimal sac, 0% complication rate, 100% anatomical patency rate, and 96.4% success rate after a minimal follow-up of 6 months. DISCUSSION: The bipedicled interlacing flap technique for eDCR provides for safe and reproducible identification of the NLD and lacrimal sac while minimizing bone exposure and restenosis rate. CONCLUSION: The bipedicled interlacing flap technique for eDCR provides for safe and reproducible identification of the NLD and lacrimal sac while minimizing bone exposure and restenosis rate. LEVEL OF EVIDENCE: NA. Laryngoscope, 128:794-797, 2018.
EVALuna2:210639

Highly multiplexed proteomic analysis reveals significant tissue and exosomal coagulation pathway derangement in chronic rhinosinusitis with nasal polyps - Mueller, Sarina K.; Nocera, Angela L.; Dillon, Simon T.; Wu, Dawei; Libermann, Towia A.; Bleier, Benjamin S. (International Forum of Allergy and Rhinology, 2018)
BACKGROUND: The coagulation pathway has been previously implicated in the etiopathogenesis of chronic rhinosinusitis with nasal polyps (CRSwNP) through analysis of individual proteins within the cascade. The purpose of this study was to: (1) apply a large-scale proteomic approach to confirm these previous findings; and (2) correlate the protein aberrations between tissue and exosomes to establish exosomal proteomics as a method to probe the pathophysiology of CRSwNP. METHODS: This investigation was an internal review board-approved study in which matched tissue and mucus exosomal proteomes were compared between control and CRSwNP (n = 10/group) using an aptamer-based proteomic array and confirmed using whole transcriptome sequencing. Protein expression and the correlation between samples were calculated using Student's t-test and Benjamini-Hochberg procedures followed by the application of Ingenuity Pathway and MetaCore™ bioinformatics analyses. RESULTS: Among all protein pathways, the coagulation cascade was the most significantly associated with CRSwNP (p = 2.85e-8). Among the 13 significantly altered coagulation-related tissue proteins, fibronectin and fibrinogen gamma chains were the most overexpressed in CRSwNP relative to control (fold change [FC], 2.59; p = 0.006; and FC, 2.38; p < 0.001, respectively), whereas von Willebrand factor was the most underexpressed (FC, -3.06; p < 0.001). The exosomal fibrinolysis and coagulation pathway proteomes exhibited strong inverse and significant correlations with the tissue findings (r = -0.86; p = 0.013; and r = -0.79; p = 0.007, respectively). CONCLUSION: Our proteomic analysis confirmed that the coagulation pathway is highly significantly deranged within nasal polyp tissue. The correlation between tissue- and mucus-derived exosomal fibrinolysis and coagulation protein alterations were strong, inverse, and highly significant. This lends further support to the emerging concept of exosomal proteomic analysis as a method to study chronic sinonasal inflammation.
EVALuna2:210632

How to operatively treat Nasal Obstruction? - Wurm, Jochen (Laryngo-Rhino-Otologie, 2017)
EVALuna2:33221

Management of the Cephalically Malpositioned Lower Lateral Crus in Aesthetic Rhinoplasty - Kovacevic, Milos; Friedman, Oren; Riedel, Frank; Wurm, Jochen; Bran, Gregor M. (Facial Plastic Surgery, 2017)
Cephalic malposition of the lower lateral cartilages (LLC) gained increasing awareness as a distinct anatomical entity within the last years. It has become clear that this type of deformity is not amenable to traditional rhinoplasty techniques. Repositioning of the lateral crus of the LLC enables the surgeon to achieve significant and reliable changes in the shape and function of the nose. The authors present their technique for repositioning of the cephalically malpositioned LLC. Their method is based on a turn-in flap that is positioned along the caudal margin of the repositioned LLC. This flap straightens a convex LLC and gives reliable structural support to the caudal alar margin. In this article, they discuss the various indications of this technique, introduce a new, more precise concept for evaluation of the axis of the lateral crus of the LLC, and highlight additional details of this reliable technique.
EVALuna2:33187

Morphometric Analysis of the Orbital Process of the Palatine Bone and its Relationship to Endoscopic Orbital Apex Surgery - Mueller, Sarina K.; Freitag, Suzanne K.; Bleier, Benjamin S. (Ophthalmic Plastic and Reconstructive Surgery, 2018)
BACKGROUND: Endoscopic approaches to the orbit improve the ability to directly access apical lesions while minimizing manipulation of normal structures. Inferomedial orbital access is limited by the orbital process of the palatine bone (OPPB) which prevents dissection and retraction in the inferolateral vector. OBJECTIVE: The objective of this study was to examine the morphometric characteristics of the OPPB and quantify the benefit of complete resection to surgical access. METHODS: Morphometric osteologic measurements of the OPPB were performed in 59 human skulls. A radius subtended by the OPPB was calculated to generate a hemispheric dissection corridor achievable by complete resection of the OPPB. Cadaveric and live surgical dissections were then performed on 15 orbits to develop discreet endoscopic surgical landmarks which could be used to both identify the OPPB and verify complete resection. RESULTS: The mean(± SD) radius of the OPPB was 0.47 ± 0.28 cm. Complete OPPB resection provided an additional 0.36 ± 0.42 cm of surgical exposure within the inferomedial apex. Relative to the Caucasian (n = 27) skulls, the radii in the Asian (n = 27) and African (n = 5) skulls were significantly smaller (p < 0.001 and p = 0.02, respectively). CONCLUSION: The OPPB significantly limits surgical access to the inferomedial orbital apex during endoscopic approaches. Complete surgical resection of the OPPB improves surgical exposure facilitating retraction of the inferior rectus muscle and circumferential dissection of lesions within this space. Knowledge of the morphology and clinical relevance of this structure provides an opportunity to improve surgical exposure for relevant pathologic assessment and optimize endoscopic surgical outcomes.
EVALuna2:210635

Options for Middle Vault and Dorsum Restoration after Hump Removal in Primary Rhinoplasty - Kovacevic, Milos; Riedel, Frank; Goksel, Abdulkadir; Wurm, Jochen (Facial Plastic Surgery, 2016)
Prevention of unfavorable sequelae following humpectomy in reduction rhinoplasty by restoration of the middle nasal vault complex today has become imperative in the majority of patients with perhaps the exception of small humps. In general, the techniques used for preservation and reconstruction of these important anatomical structures can be divided into two main categories: spreader graft and spreader flap techniques. Oversimplified spreader graft techniques require donor cartilage, whereas spreader flap techniques use the excess height of the medial portion of the upper lateral cartilages in patients with a cartilaginous hump. In principle, both donor cartilage and preserved upper lateral cartilages usually are positioned along both sides of the dorsal septum to provide natural and harmonious contours as well as to avoid functional impairment (valve collapse). However, the considerable number of publications on this topic attests to existing downsides of both surgical principles. To overcome these shortcomings, we illustrate additional modifications in the application of spreader grafts as well as spreader flaps. However, the main goal of this article is to provide an algorithm helping to decide which technique is best suited to meet the requirements of each individual patient.
EVALuna2:33189

Osteologic analysis of ethnic differences in supernumerary ethmoidal foramina: implications for endoscopic sinus and orbit surgery - Mueller, Sarina K.; Bleier, Benjamin S. (International Forum of Allergy and Rhinology, 2018)
BACKGROUND: Knowledge of the position of the ethmoidal arteries is critical to enable safe endoscopic sinus and orbital surgery. The presence of a third or "middle" ethmoid variant has recently become more relevant as endoscopic intraconal surgery continues to advance. The purpose of this study was to quantify the presence of supernumerary (ie, over 2) ethmoid foramina in different ethnicities and genders. METHODS: Morphometric osteologic measurements were performed in 273 orbits. Prevalence of supernumerary ethmoid foramina and orbital length data were obtained from human skulls of Asian (n = 54), Caucasian (n = 70), African (n = 39), Hispanic (n = 49), and Middle Eastern (n = 61) derivation. Correlations between gender, ethnicity, symmetry, orbital floor, and lamina papyracea length were assessed by analysis of variance, paired t test, and χ2 test. RESULTS: Supernumerary foramina were identified in 95 of 273 orbits (34.79%). A significantly higher prevalence was seen in Asian (42.59%), African (41.02%), and Hispanic (41.00%) skulls as compared with Caucasian (25.71%) and Middle Eastern (22.95%) skulls (p < 0.05 for all). The length of the orbital floor was significantly shorter in the Asian (3.35 ± 1.52 cm) specimens (p < 0.01). Asians were found to have the highest risk of ethmoid artery injury compared with the other ethnic groups (ratio of number of supernumerary foramina to orbital floor length = 0.72). CONCLUSION: Supernumerary ethmoidal foramina were common among all orbits studied. Orbits of Asian and African derivation had significantly greater numbers of ethmoidal foramina, both unilaterally and symmetrically and within a shorter orbital length, suggesting a greater proximity between the ethmoidal vessels. Surgeons should be alert to the possible presence of middle ethmoidal vessels during endoscopic sinus and orbital approaches.
EVALuna2:210637

Patient-reported outcome measures in external and endonasal functional septorhinoplasty – A propensity score matching study - Gostian, Magdalena; Stange, Thoralf; Wurm, Jochen; Gostian, Antoniu Oreste (American Journal of Otolaryngology, 2021)
Purpose: Patient satisfaction after functional-aesthetic SRP (faSRP) is highly influenced by the cosmetic result of the surgical procedure. Studies that directly evaluate aesthetic success after external and endonasal faSRP are scarce. The objective of this prospective propensity score matching study was to compare patient-reported satisfaction regarding aesthetic perception following faSRP using the external and endonasal approach in a single-institution single-surgeon survey. Materials and methods: Out of 161 patients operated by the senior author between October 2011 and March 2017, propensity score matching (PSM) computed 54 patients each following external (group 1) or endonasal faSRP (group 2). Patients reported their satisfaction with the aesthetic appearance of the nose on a visual analogue scale (VAS, 0–10) and five Likert scale questions using the Utrecht questionnaire three and twelve months after surgery. Results: The mean preoperative VAS score of 3.46 ± 1.06 improved significantly in all patients after faSRP to 4.54 ± 0.38 (F(1.69;157.04) = 634.01, p < 0.001). The VAS increase did not show any correlation to the surgical approach (F(1;93) = 1.12, p = 0.293). The mean aesthetic sum score (5 = low burden up to 25 = high burden) improved significantly from 13.89 ± 3.78 to 8.46 ± 3.63 after three months (t(95) = 14.021, p < 0.001) and remained almost unchanged after 12 months (8.10 ± 3.76; t(98) = 1.450, p = 0.150) irrespective of the surgical approach (F(1,544;143,587) = 0.126, p = 0.829). Conclusions: Both the external and endonasal faSRP allowed for significant improvement in patient's aesthetic self-assessment of similar extent.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Aesthetic self-assessment; Endonasal septorhinoplasty; External septorhinoplasty; Patient-reported outcome; Quality of life

Prophylactic nimodipine treatment and improvement in hearing outcome after vestibular schwannoma surgery: a combined analysis of a randomized, multicenter, Phase III trial and its pilot study - Scheller, Christian; Wienke, Andreas; Tatagiba, Marcos; Gharabaghi, Alireza; Ramina, Kristofer F.; Ganslandt, Oliver Thomas; Bischoff, Barbara; Zenk, Johannes; Engelhorn, Tobias; Matthies, Cordula; Westermaier, Thomas; Antoniadis, Gregor; et al. (Journal of Neurosurgery, 2017)
OBJECTIVE In clinical routines, neuroprotective strategies in neurosurgical interventions are still missing. A pilot study (n = 30) and an analogously performed Phase III trial (n = 112) pointed to a beneficial effect of prophylactic nimodipine and hydroxyethyl starch (HES) in vestibular schwannoma (VS) surgery. Considering the small sample size, the data from both studies were pooled. METHODS The patients in both investigator-initiated studies were assigned to 2 groups. The treatment group (n = 70) received parenteral nimodipine (1-2 mg/hour) and HES (hematocrit 30%-35%) from the day before surgery until the 7th postoperative day. The control group (n = 72) was not treated prophylactically. Facial and cochlear nerve functions were documented preoperatively, during the inpatient care, and 1 year after surgery. RESULTS Pooled raw data were analyzed retrospectively. Intent-to-treat analysis revealed a significantly lower risk for hearing loss (Class D) 12 months after surgery in the treatment group compared with the control group (OR 0.46, 95% CI 0.22-0.97; p = 0.04). After exclusion of patients with preoperative Class D hearing, this effect was more pronounced (OR 0.38, 95% CI 0.17-0.83; p = 0.016). Logistic regression analysis adjusted for tumor size showed a 4 times lower risk for hearing loss in the treatment group compared with the control group (OR 0.25, 95% CI 0.09-0.63; p = 0.003). Facial nerve function was not significantly improved with treatment. Apart from dose-dependent hypotension (p < 0.001), the study medication was well tolerated. CONCLUSIONS Prophylactic nimodipine is safe and may be recommended in VS surgery to preserve hearing. Prophylactic neuroprotective treatment in surgeries in which nerves are at risk seems to be a novel and promising concept. Clinical trial registration no.: DRKS 00000328 ( https://drks-neu.uniklinik-freiburg.de/drks_web/ ).
EVALuna2:33133

Prospective transfrontal sheep model of skull-base reconstruction using vascularized mucosa - Mueller, Sarina K.; Scangas, George; Amiji, Mansor M.; Bleier, Benjamin S. (International Forum of Allergy and Rhinology, 2018)
BACKGROUND: No high-fidelity animal model exists to examine prospective wound healing following vascularized reconstruction of the skull base. Such a model would require the ability to study the prospective behavior of vascularized mucosal repairs of large dural and arachnoid defects within the intranasal environment. The objective of this study was to therefore develop and validate a novel, in vivo, transfrontal sheep model of cranial base repair using vascularized sinonasal mucosa. METHODS: Twelve transfrontal craniotomy and 1.5-cm durotomy reconstructions were performed in 60-kg to 70-kg Dorset/Ovis Aries sheep using vascularized mucosa with or without an adjunctive Biodesign™ underlay graft (n = 6 per group). Histologic outcomes were graded (scale, 0 to 4) by a blinded veterinary histopathologist after 7, 14, and 28 days for a range of wound healing parameters. RESULTS: All sheep tolerated the surgery, which required 148 ± 33 minutes. By day 7, the mucosa was fully adherent with complete partitioning of the sinus and intracranial compartments. Fibroblast infiltration and flap neovascularization scores significantly increased between day 7 (0.3 ± 0.5 and 0.0 ± 0.0) and day 28 (4.0 ± 0.0, p = 0.01 and 2.0 ± 0.8, p = 0.01; respectively), while hemorrhage scores significantly decreased from 2.5 ± 0.6 to 0.0 ± 0.0 (p = 0.01). The inflammatory scores were not significantly different between the heterologous graft and control sides. CONCLUSION: The described sheep model accurately reflects prospective intranasal wound healing following vascularized mucosal reconstruction of dural defects. This model can be used in future studies to examine novel reconstructive materials, tissue glues, and transmucosal drug delivery to the central nervous system.
EVALuna2:210636